Cell-based in vitro models for predicting drug permeability - Sarmento, B.; Andrade, F.; Da Silva, S.B.; Rodrigues, F.; Das Neves, J.; Ferreira, D. (Expert Opinion on Drug Metabolism and ToxicologyExpert Opin. Drug Metab. Toxicol., 2012)
In vitro cell models have been used to predict drug permeation in early stages of drug development, since they represent an easy and reproducible method, allowing the tracking of drug absorption rate and mechanism, with an advantageous costbenefit ratio. Such cell-based models are mainly composed of immortalized cells with an intrinsic ability to grow in a monolayer when seeded in permeable supports, maintaining their physiologic characteristics regarding epithelium cell physiology and functionality. Areas covered: This review summarizes the most important intestinal, pulmonary, nasal, vaginal, rectal, ocular and skin cell-based in vitro models for predicting the permeability of drugs. Moreover, the similitude between in vitro cell models and in vivo conditions are discussed, providing evidence that each model may provisionally resemble different drug absorption route. Expert opinion: Despite the widespread use of in vitro cell models for drug permeability and absorption evaluation purposes, a detailed study on the properties of these models and their in vitroin vivo correlation compared with human data are required to further use in order to consider a future drug discovery optimization and clinical development. © 2012 Informa UK, Ltd.
Keywords: Animals; Caco-2 Cells; carcinoma cell; cell differentiation; cell growth; Cell Line; Cell Membrane Permeability; cell models; cell proliferation; cell strain CACO 2; cell type; Cells; conjunctiva; drug absorption; drug bioavailability; drug delivery system; drug penetration; drug screening; drug transport; epithelium cell; Eye; human; Humans; in vitro models; in vitro study; in vitroin vivo correlation; Intestinal Absorption; intestinal mucosa; intestine cell; Intestines; Lung; lung alveolus cell; Models, Biological; molecular weight; nasal cell; nonhuman; ocular cell; permeability; Pharmaceutical Preparations; rectal cell; review; Skin; skin cell; vaginal cell

Chitosan drives anti-inflammatory macrophage polarisation and pro-inflammatory dendritic cell stimulation. - Oliveira, M.I.; Santos, S.G.; Oliveira, M.J.; Torres, A.L.; Barbosa, M.A. (European cells & materialsEur Cell Mater, 2012)
Macrophages and dendritic cells (DC) share the same precursor and play key roles in immunity. Modulation of their behaviour to achieve an optimal host response towards an implanted device is still a challenge. Here we compare the differentiation process and polarisation of these related cell populations and show that they exhibit different responses to chitosan (Ch), with human monocyte-derived macrophages polarising towards an anti-inflammatory phenotype while their DC counterparts display pro-inflammatory features. Macrophages and DC, whose interactions with biomaterials are frequently analysed using fully differentiated cells, were cultured directly on Ch films, rather than exposed to the polymer after complete differentiation. Ch was the sole stimulating factor and activated both macrophages and DC, without leading to significant T cell proliferation. After 10 d on Ch, macrophages significantly down-regulated expression of pro-inflammatory markers, CD86 and MHCII. Production of pro-inflammatory cytokines, particularly TNF-α, decreased with time for cells cultured on Ch, while anti-inflammatory IL-10 and TGF-β1, significantly increased. Altogether, these results suggest an M2c polarisation. Also, macrophage matrix metalloproteinase activity was augmented and cell motility was stimulated by Ch. Conversely, DC significantly enhanced CD86 expression, reduced IL-10 secretion and increased TNF-α and IL-1β levels. Our findings indicate that cells with a common precursor may display different responses, when challenged by the same biomaterial. Moreover, they help to further comprehend macrophage/DC interactions with Ch and the balance between pro- and anti-inflammatory signals associated with implant biomaterials. We propose that an overall pro-inflammatory reaction may hide the expression of anti-inflammatory cytokines, likely relevant for tissue repair/regeneration.
Keywords: antibody specificity; Antigens, CD86; article; Biocompatible Materials; biomaterial; biosynthesis; CD86 antigen; Cell culture; cell differentiation; cell motion; Cell Movement; Cells, Cultured; chitosan; cytology; dendritic cell; Dendritic Cells; drug effect; flow cytometry; Histocompatibility Antigens Class II; HLA antigen class 2; human; Humans; IL10 protein, human; immunology; interleukin 10; Interleukin-10; macrophage; Macrophages; metabolism; monocyte; Monocytes; Organ Specificity; transforming growth factor beta1; tumor necrosis factor alpha; Tumor Necrosis Factor-alpha

E-cadherin dysfunction in gastric cancer - Cellular consequences, clinical applications and open questions - Carneiro, P.; Fernandes, M.S.; Figueiredo, J.; Caldeira, J.; Carvalho, J.; Pinheiro, H.; Leite, M.; Melo, S.; Oliveira, P.; Simões-Correia, J.; Oliveira, M.J.; Carneiro, F.; et al. (FEBS LettersFEBS Lett., 2012)
E-cadherin plays a major role in cell-cell adhesion and inactivating germline mutations in its encoding gene predispose to hereditary diffuse gastric cancer. Evidence indicates that aside from its recognized role in early tumourigenesis, E-cadherin is also pivotal for tumour progression, including invasion and metastization. Herein, we discuss E-cadherin alterations found in a cancer context, associated cellular effects and signalling pathways, and we raise new key questions that will impact in the management of GC patients and families. © 2012 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
Keywords: Adhesion; Cadherins; cancer growth; cancer invasion; cancer patient; cancer susceptibility; cell adhesion; complex formation; conference paper; E-cadherin; embryo development; endocytosis; epigenetics; epithelial mesenchymal transition; Gastric cancer; gene mutation; gene silencing; genetic susceptibility; Germ-Line Mutation; HDGC; Helicobacter infection; Helicobacter Infections; Helicobacter pylori; histone deacetylase inhibitor; human; Humans; Invasion; metastasis; molecular pathology; nonhuman; priority journal; protein analysis; protein depletion; protein expression; protein function; protein structure; regulatory mechanism; signal transduction; Signalling; stomach cancer; stomach carcinogenesis; Stomach Neoplasms; Tumour; uvomorulin

Mesenchymal stem cell recruitment by stromal derived factor-1-delivery systems based on chitosan/poly(γ-glutamic acid) polyelectrolyte complexes - Gonçalves, R.M.; Antunes, J.C.; Barbosa, M.A. (European Cells and MaterialsEur. Cells and Mater., 2012)
Human mesenchymal stem cells (hMSCs) have an enormous potential for tissue engineering and cell-based therapies. With a potential of differentiation into multiple lineages and immune-suppression, these cells play a key role in tissue remodelling and regeneration. Here a method of hMSC recruitment is described, based on the incorporation of a chemokine in Chitosan (Ch)/ Poly(γ-glutamic acid) (γ-PGA) complexes. Ch is a nontoxic, cationic polysaccharide widely investigated. γ-PGA is a hydrophilic, non-toxic, biodegradable and negatively charged poly-amino acid. Ch and γ-PGA, being oppositely charged, can be combined through electrostatic interactions. These biocompatible structures can be used as carriers for active substances and can be easily modulated in order to control the delivery of drugs, proteins, DNA, etc. Using the layer-by-layer method, Ch and γ-PGA were assembled into polyelectrolyte multilayers films (PEMs) with thickness of 120 nm. The chemokine stromal-derived factor-1 (SDF-1) was incorporated in these complexes and was continuously released during 120 h. The method of SDF-1 incorporation is of crucial importance for polymers assembly into PEMs and for the release kinetics of this chemokine. The Ch/γ-PGA PEMs with SDF-1 were able to recruit hMSCs, increasing the cell migration up to 6 fold to a maximum of 16.2 ± 4.9 cells/mm 2. The controlled release of SDF-1 would be of great therapeutic value in the process of hMSC homing to injured tissues. This is the first study suggesting Ch/γ-PGA PEMs as SDF-1 reservoirs to recruit hMSCs, describing an efficient method of chemokine incorporation that allows a sustained released up to 5 days and that can be easily scaled-up.
Keywords: adsorption kinetics; article; artificial membrane; Biocompatible Materials; biomaterial; cell differentiation; cell migration; cell motion; Cell Movement; Cell recruitment; chemistry; Chemokine CXCL12; chitosan; controlled study; CXCL12 protein, human; cytology; drug adsorption; drug delivery system; Drug Delivery Systems; drug derivative; drug effect; ellipsometry; enzyme linked immunosorbent assay; human; human cell; human tissue; Humans; in vitro study; isotope labeling; Layer-by-layer; Membranes, Artificial; Mesenchymal stem cell; Mesenchymal Stem Cells; metabolism; methodology; poly(gamma glutamic acid); poly(gamma-glutamic acid); Poly(γ-glutamic acid); polyglutamic acid; Protein delivery; static electricity; stromal cell derived factor 1; sustained drug release

A model for educational simulation of the evolution of uterine contractions during labor - Bastos, L.F.; van Meurs, W.; Ayres-de-Campos, D. (Computer Methods and Programs in BiomedicineComput. Methods Programs Biomed., 2012)
Electronic fetal monitoring remains an important tool in labor ward settings, providing continuous information on fetal heart rate and maternal uterine contractions. A prompt detection of abnormalities in these signals is essential for the timely resolution of situations that may put both mother and fetus at risk. Uterine contraction signals provide information that is important to evaluate the onset and progress of labor, as well as the significance of certain fetal heart rate abnormalities. We present a model for educational simulation of the spontaneous evolution of uterine contractions during labor, which combines a previously published signal generator with literature-based pre-programmed scripts for educationally relevant scenarios. This model is an essential component of a high-fidelity simulator of intrapartum emergencies, aimed to improve the competency of healthcare providers. Real and simulated tracings were presented to three independent clinical experts who judged simulated signals to be indistinguishable or negligibly different from real tracings. © 2011 Elsevier Ireland Ltd.
Keywords: article; clinical competence; computer memory; computer program; Computer simulation; Computer-Assisted Instruction; controlled study; Educational simulations; Essential component; Female; Fetal heart rate; Fetal monitoring; Health care; Health care providers; High-fidelity simulators; Humans; labor; Labor and delivery; medical education; Medical educational simulation; Models, Biological; Neonatal monitoring; Obstetric Labor Complications; Obstetrics; Pregnancy; Script-controlled simulation; signal detection; Signal generators; Simulated signals; User-Computer Interface; Uterine activities; Uterine activity; Uterine Contraction; Uterine Monitoring; uterus contraction

Poor reliability of visual analysis of fetal heart rate tracings: What should be done about it? - Bernardes, J.; Ayres-de-Campos, D. (American Journal of Obstetrics and GynecologyAm. J. Obstet. Gynecol., 2012)
Keywords: accuracy; Cardiotocography; clinical decision making; clinical practice; computer analysis; fetus blood sampling; fetus electrocardiography; fetus heart rate; Heart Rate, Fetal; human; Humans; letter; medical education; metabolic acidosis; newborn disease; priority journal; reliability; visual acuity

Reciprocal induction of human dermal microvascular endothelial cells and human mesenchymal stem cells: Time-dependent profile in a co-culture system - Laranjeira, M.S.; Fernandes, M.H.; Monteiro, F.J. (Cell ProliferationCell Prolif., 2012)
Objectives: Angiogenesis is closely associated with osteogenesis where reciprocal interactions between endothelial and osteoblast cells play an important role in bone regeneration. For these reasons, the aim of this work was to develop a co-culture system to study in detail any time-dependent interactions between human mesenchymal stem cells (HMSC) and human dermal microvascular endothelial cells (HDMEC), co-cultured in a 2D system, for 35 days. Materials and methods: HMSC and HDMEC were co-cultured at a ratio of 1:4, respectively. Single-cell cultures were used as controls. Cell viability/proliferation was assessed using MTT, DNA quantification and calcein-AM assays. Cell morphology was monitored using confocal microscopy, and real time PCR was performed. Alkaline phosphatase activity and histochemical staining were evaluated. Matrix mineralization assays were also performed. Results: Cells were able to grow in characteristic patterns maintaining their viability and phenotype expression throughout culture time, compared to HMSC and HDMEC monocultures. HMSC differentiation seemed to be enhanced in the co-culture conditions, since it was observed an over expression of osteogenesis-related genes, and of ALP activity. Furthermore, presence of calcium phosphate deposits was also confirmed. Conclusions: This work reports in detail the interactions between HMSC and HDMEC in a long-term co-culture 2D system. Endothelial and mesenchymal stem cells cultured in the present co-culture conditions ensured proliferation and phenotype differentiation of cell types, osteogenesis stimulation and over-expression of angiogenesis-related genes, in the same culture system. It is believed that the present work can lead to significant developments for bone tissue regeneration and cell biology studies. © 2012 Blackwell Publishing Ltd.
Keywords: alkaline phosphatase; article; Base Sequence; calcein; calcium phosphate; CD31 antigen; Cell culture; cell differentiation; cell growth; cell interaction; cell nucleus; cell population; cell proliferation; cell structure; cell viability; coculture; Coculture Techniques; confocal microscopy; controlled study; DNA; DNA determination; DNA Primers; Endothelium, Vascular; enzyme histochemistry; F actin; flow cytometry; gene overexpression; human; human cell; Humans; immunohistochemistry; in vitro study; Mesenchymal stem cell; Mesenchymal Stem Cells; Microscopy, Confocal; Microscopy, Electron, Scanning; microvascular endothelial cell; Microvessels; mineralization; nucleotide sequence; osteoblast; phenotype; process development; real time polymerase chain reaction; Real-Time Polymerase Chain Reaction; scanning electron microscope; single cell analysis; Skin

Tumor cell-educated periprostatic adipose tissue acquires an aggressive cancer-promoting secretory profile - Ribeiro, R.J.T.; Monteiro, C.P.D.; Cunha, V.F.P.M.; Azevedo, A.S.M.; Oliveira, M.J.; Monteiro, R.; Fraga, A.M.; Príncipe, P.; Lobato, C.; Lobo, F.; Morais, A.; Silva, V.; et al. (Cellular Physiology and BiochemistryCell. Physiol. Biochem., 2012)
Background/Aims: The microenvironment produces important factors that are crucial to prostate cancer (PCa) progression. However, the extent to which the cancer cells stimulate periprostatic adipose tissue (PPAT) to produce these proteins is largely unknown. Our purpose was to determine whether PCa cell-derived factors influence PPAT metabolic activity. Methods: Primary cultures of human PPAT samples from PCa patients (adipose tissue organotypic explants and primary stromal vascular fraction, SVF) were stimulated with conditioned medium (CM) collected from prostate carcinoma (PC3) cells. Cultures without CM were used as control. We used multiplex analysis and ELISA for protein quantification, qPCR to determine mitochondrial DNA (mtDNA) copy number and zymography for matrix metalloproteinase activity, in order to evaluate the response of adipose tissue explants and SVFs to PC3 CM. Results: Stimulation of PPAT explants with PCa PC3 CM induced adipokines associated with cancer progression (osteopontin, tumoral necrosis factor alpha and interleukin-6) and reduced the expression of the protective adipokine adiponectin. Notably, osteopontin protein expression was 13-fold upregulated. Matrix metalloproteinase 9 activity and mitochondrial DNA copy number were higher after stimulation with cancer CM. Stromovascular cells from PPAT in culture were not influenced by tumor-derived factors. Conclusion: The modulation of adipokine expression by tumor CM indicates the pervasive extent to which tumor cells command PPAT to produce factors favorable to their aggressiveness. © 2012 S. Karger AG, Basel.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: CEPBEdoi: 10.1159/000337604PubMed ID: 22415092Language of Original Document: EnglishCorrespondence Address: Ribeiro, R.J.T.; Portuguese Institute of Oncology, Porto Centre Molecular Oncology Group -CI, Edifício Laboratórios -Piso 4, Rua Dr. António Bernardino Almeida, 4200-072 Porto, Portugal; email: oriebir.r@gmail.comChemicals/CAS: adiponectin, 283182-39-8; gelatinase B, 146480-36-6; osteopontin, 106441-73-0; Adiponectin; Culture Media, Conditioned; Cytokines; DNA, Mitochondrial; Interleukin-6; Matrix Metalloproteinase 2, 3.4.24.24; Matrix Metalloproteinase 9, 3.4.24.35; Osteopontin, 106441-73-0; Tumor Necrosis Factor-alphaReferences: Hsing, A.W., Sakoda, L.C., Chua Jr., S., Obesity, metabolic syndrome, and prostate cancer (2007) Am J Clin Nutr, 86, pp. s843-857;Cao, Y., Ma, J., Body mass index, prostate cancer-specific mortality, and biochemical recurrence: A systematic review and meta-analysis (2011) Cancer Prev Res (Phila), 4, pp. 486-501; Baillargeon, J., Rose, D.P., Obesity, adipokines, and prostate cancer (review) (2006) Int J Oncol, 28, pp. 737-745; Mistry, T., Digby, J.E., Desai, K.M., Randeva, H.S., Obesity and Prostate Cancer: A Role for Adipokines (2007) European Urology, 52 (1), pp. 46-53. , DOI 10.1016/j.eururo.2007.03.054, PII S0302283807004307; Hirano, T., Morii, H., Nakazawa, K., Murakami, D., Yamashita, A., Asahi, J., Orimo, H., Tokura, Y., Enhancement of adipogenesis induction by conditioned media obtained from cancer cells (2008) Cancer Lett, 268, pp. 286-294; Andarawewa, K.L., Motrescu, E.R., Chenard, M.-P., Gansmuller, A., Stoll, I., Tomasetto, C., Rio, M.-C., Stromelysin-3 is a potent negative regulator of adipogenesis participating to cancer cell-adipocyte interaction/crosstalk at the tumor invasive front (2005) Cancer Research, 65 (23), pp. 10862-10871. , DOI 10.1158/0008-5472.CAN-05-1231; Jotzu, C., Alt, E., Welte, G., Li, J., Hennessy, B.T., Devarajan, E., Krishnappa, S., Song, Y.H., Adipose tissue derived stem cells differentiate into carcinoma-associated fibroblast-like cells under the influence of tumor derived factors (2011) Cell Oncol (Dordr), 34, pp. 55-67; Dolinkova, M., Dostalova, I., Lacinova, Z., Michalsky, D., Haluzikova, D., Mraz, M., The endocrine profile of subcutaneous and visceral adipose tissue of obese patients (2008) Mol Cell Endocrinol, 291, pp. 63-70; Van Roermund, J.G., Hinnen, K.A., Tolman, C.J., Bol, G.H., Witjes, J.A., Bosch, J.L., Kiemeney, L.A., Van Vulpen, M., Periprostatic fat correlates with tumour aggressiveness in prostate cancer patients (2011) BJU Int, 107, pp. 1775-1779; Sumitomo, M., Asakuma, J., Yoshii, H., Sato, A., Horiguchi, A., Ito, K., Nagakura, K., Asano, T., Anterior perirectal fat tissue thickness is a strong predictor of recurrence after high-intensity focused ultrasound for prostate cancer (2010) Int J Urol, 17, pp. 776-782; Finley, D.S., Calvert, V.S., Inokuchi, J., Lau, A., Narula, N., Petricoin, E.F., Zaldivar, F., Ornstein, D.K., Periprostatic adipose tissue as a modulator of prostate cancer aggressiveness (2009) J Urol, 182, pp. 1621-1627; Thalmann, S., Juge-Aubry, C.E., Meier, C.A., Explant cultures of white adipose tissue (2008) Methods Mol Biol, 456, pp. 195-199; Song, G.J., Lewis, V., Mitochondrial DNA integrity and copy number in sperm from infertile men (2008) Fertil Steril, 90, pp. 2238-2244; Park, J., Euhus, D.M., Scherer, P.E., Paracrine and Endocrine Effects of Adipose Tissue on Cancer Development and Progression (2011) Endocr Rev, 32, pp. 550-570; George, D.J., Halabi, S., Shepard, T.F., Sanford, B., Vogelzang, N.J., Small, E.J., Kantoff, P.W., The prognostic significance of plasma interleukin-6 levels in patients with metastatic hormone-refractory prostate cancer: Results from cancer and leukemia group B 9480 (2005) Clinical Cancer Research, 11 (5), pp. 1815-1820. , DOI 10.1158/1078-0432.CCR-04-1560; Michalaki, V., Syrigos, K., Charles, P., Waxman, J., Serum levels of IL-6 and TNF-α correlate with clinicopathological features and patient survival in patients with prostate cancer (2004) British Journal of Cancer, 90 (12), pp. 2312-2316; Dirat, B., Bochet, L., Dabek, M., Daviaud, D., Dauvillier, S., Majed, B., Wang, Y.Y., Muller, C., Cancerassociated adipocytes exhibit an activated phenotype and contribute to breast cancer invasion (2011) Cancer Res, 71, pp. 2455-2465; Culig, Z., New insights into the role of interleukin-6 in human prostate cancer (2009) J Urol, 182, pp. 1255-1256; Chun, J.Y., Nadiminty, N., Dutt, S., Lou, W., Yang, J.C., Kung, H.J., Evans, C.P., Gao, A.C., Interleukin-6 regulates androgen synthesis in prostate cancer cells (2009) Clin Cancer Res, 15, pp. 4815-4822; Weber, G.F., Lett, G.S., Haubein, N.C., Osteopontin is a marker for cancer aggressiveness and patient survival (2010) Br J Cancer, 103, pp. 861-869; Thalmann, G.N., Sikes, R.A., Devoll, R.E., Kiefer, J.A., Markwalder, R., Klima, I., Farach-Carson, C.M., Chung, L.W.K., Osteopontin: Possible role in prostate cancer progression (1999) Clinical Cancer Research, 5 (8), pp. 2271-2277; McAllister, S.S., Gifford, A.M., Greiner, A.L., Kelleher, S.P., Saelzler, M.P., Ince, T.A., Reinhardt, F., Weinberg, R.A., Systemic Endocrine Instigation of Indolent Tumor Growth Requires Osteopontin (2008) Cell, 133 (6), pp. 994-1005. , DOI 10.1016/j.cell.2008.04.045, PII S0092867408006211; Balkwill, F., TNF-alpha in promotion and progression of cancer (2006) Cancer Metastasis Rev, 25, pp. 409-416; Yan, B., Wang, H., Rabbani, Z.N., Zhao, Y., Li, W., Yuan, Y., Li, F., Li, C.-Y., Tumor necrosis factor-α is a potent endogenous mutagen that promotes cellular transformation (2006) Cancer Research, 66 (24), pp. 11565-11570. , DOI 10.1158/0008-5472.CAN-06-2540; Bates, R.C., Mercurio, A.M., Tumor necrosis factor-α stimulates the epithelial-tomesenchymal transition of human colonic organoids (2003) Molecular Biology of the Cell, 14 (5), pp. 1790-1800. , DOI 10.1091/mbc.E02-09-0583; Yamauchi, T., Kamon, J., Waki, H., Terauchi, Y., Kubota, N., Hara, K., Mori, Y., Kadowaki, T., The fat-derived hormone adiponectin reverses insulin resistance associated with both lipoatrophy and obesity (2001) Nature Medicine, 7 (8), pp. 941-946. , DOI 10.1038/90984; Li, H., Stampfer, M.J., Mucci, L., Rifai, N., Qiu, W., Kurth, T., Ma, J., A 25-year prospective study of plasma adiponectin and leptin concentrations and prostate cancer risk and survival (2010) Clin Chem, 56, pp. 34-43; Ribeiro, R., Lopes, C., Medeiros, R., The link between obesity and prostate cancer: The leptin pathway and therapeutic perspectives (2006) Prostate Cancer and Prostatic Diseases, 9 (1), pp. 19-24. , DOI 10.1038/sj.pcan.4500844, PII 4500844; Vaday, G.G., Peehl, D.M., Kadam, P.A., Lawrence, D.M., Expression of CCL5 (RANTES) and CCR5 in prostate cancer (2006) Prostate, 66 (2), pp. 124-134. , DOI 10.1002/pros.20306; Kessenbrock, K., Plaks, V., Werb, Z., Matrix metalloproteinases: Regulators of the tumor microenvironment (2010) Cell, 141, pp. 52-67; Bouloumie, A., Sengenes, C., Portolan, G., Galitzky, J., Lafontan, M., Adipocyte Produces Matrix Metalloproteinases 2 and 9 Involvement in Adipose Differentiation (2001) Diabetes, 50 (9), pp. 2080-2086; Bergers, G., Brekken, R., McMahon, G., Vu, T.H., Itoh, T., Tamaki, K., Tanzawa, K., Hanahan, D., Matrix metalloproteinase-9 triggers the angiogenic switch during carcinogenesis (2000) Nat Cell Biol, 2, pp. 737-744; Lin, C.Y., Tsai, P.H., Kandaswami, C.C., Lee, P.P., Huang, C.J., Hwang, J.J., Lee, M.T., Matrix metalloproteinase-9 cooperates with transcription factor Snail to induce epithelial-mesenchymal transition (2011) Cancer Sci, 102, pp. 815-827; Chakrabarti, S., Patel, K.D., Matrix metalloproteinase-2 (MMP-2) and MMP-9 in pulmonary pathology (2005) Experimental Lung Research, 31 (6), pp. 599-621. , DOI 10.1080/019021490944232; Sehgal, G., Hua, J., Bernhard, E.J., Sehgal, I., Thompson, T.C., Muschel, R.J., Requirement for matrix metalloproteinase-9 (Gelatinase B) expression in metastasis by murine prostate carcinoma (1998) American Journal of Pathology, 152 (2), pp. 591-596; Johnson, T.R., Koul, S., Kumar, B., Khandrika, L., Venezia, S., Maroni, P.D., Meacham, R.B., Koul, H.K., Loss of PDEF, a prostatederived Ets factor is associated with aggressive phenotype of prostate cancer: Regulation of MMP 9 by PDEF (2010) Mol Cancer, 9, p. 148; Trudel, D., Fradet, Y., Meyer, F., Tetu, B., Matrix metalloproteinase 9 is associated with Gleason score in prostate cancer but not with prognosis (2010) Hum Pathol, 41, pp. 1694-1701; Zhang, L., Shi, J., Feng, J., Klocker, H., Lee, C., Zhang, J., Type IV collagenase (matrix metalloproteinase-2 and -9) in prostate cancer (2004) Prostate Cancer and Prostatic Diseases, 7 (4), pp. 327-332. , DOI 10.1038/sj.pcan.4500750, PII 4500750; Zhong, W.D., Han, Z.D., He, H.C., Bi, X.C., Dai, Q.S., Zhu, G., Ye, Y.K., Chen, Z.N., CD147, MMP-1, MMP-2 and MMP-9 protein expression as significant prognostic factors in human prostate cancer (2008) Oncology, 75, pp. 230-236; Sauer, C.G., Kappeler, A., Spath, M., Kaden, J.J., Michel, M.S., Mayer, D., Bleyl, U., Grobholz, R., Expression and activity of matrix metalloproteinases-2 and -9 in serum, core needle biopsies and tissue specimens of prostate cancer patients (2004) Virchows Archiv, 444 (6), pp. 518-526; Opdenakker, G., Masure, S., Grillet, B., Van Damme, J., Cytokine-mediated regulation of human leukocyte gelatinases and role in arthritis (1991) Lymphokine Cytokine Res, 10, pp. 317-324; Unal, R., Yao-Borengasser, A., Varma, V., Rasouli, N., Labbate, C., Kern, P.A., Ranganathan, G., Matrix metalloproteinase-9 is increased in obese subjects and decreases in response to pioglitazone (2010) J Clin Endocrinol Metab, 95, pp. 2993-3001; Catalan, V., Gomez-Ambrosi, J., Rodriguez, A., Ramirez, B., Silva, C., Rotellar, F., Gil, M.J., Frühbeck, G., Increased adipose tissue expression of lipocalin-2 in obesity is related to inflammation and matrix metalloproteinase-2 and metalloproteinase-9 activities in humans (2009) J Mol Med (Berl), 87, pp. 803-813; Villarroya, J., Giralt, M., Villarroya, F., Mitochondrial DNA: An up-and-coming actor in white adipose tissue pathophysiology (2009) Obesity (Silver Spring), 17, pp. 1814-1820; Robin, E.D., Wong, R., Mitochondrial DNA molecules and virtual number of mitochondria per cell in mammalian cells (1988) J Cell Physiol, 136, pp. 507-513; Kaaman, M., Sparks, L.M., Van Harmelen, V., Smith, S.R., Sjolin, E., Dahlman, I., Arner, P., Strong association between mitochondrial DNA copy number and lipogenesis in human white adipose tissue (2007) Diabetologia, 50 (12), pp. 2526-2533. , DOI 10.1007/s00125-007-0818-6; Yamauchi, T., Kamon, J., Waki, H., Murakami, K., Motojima, K., Komeda, K., Ide, T., Kadowaki, T., The mechanisms by which both heterozygous peroxisome proliferator- activated receptor gamma (PPARgamma) deficiency and PPARgamma agonist improve insulin resistance (2001) J Biol Chem, 276, pp. 41245-41254; Wilson-Fritch, L., Burkart, A., Bell, G., Mendelson, K., Leszyk, J., Nicoloro, S., Czech, M., Corvera, S., Mitochondrial biogenesis and remodeling during adipogenesis and in response to the insulin sensitizer rosiglitazone (2003) Molecular and Cellular Biology, 23 (3), pp. 1085-1094. , DOI 10.1128/MCB.23.3.1085-1094.2003; Ducluzeau, P.H., Priou, M., Weitheimer, M., Flamment, M., Duluc, L., Iacobazi, F., Soleti, R., Malthièry, Y., Dynamic regulation of mitochondrial network and oxidative functions during 3T3-L1 fat cell differentiation (2011) J Physiol Biochem, 67, pp. 285-296; Bogacka, I., Ukropcova, B., McNeil, M., Gimble, J.M., Smith, S.R., Structural and functional consequences of mitochondrial biogenesis in human adipocytes in vitro (2005) Journal of Clinical Endocrinology and Metabolism, 90 (12), pp. 6650-6656. , http://jcem.endojournals.org/cgi/reprint/90/12/6650, DOI 10.1210/jc.2005-1024; Toda, S., Uchihashi, K., Aoki, S., Sonoda, E., Yamasaki, F., Piao, M., Ootani, A., Sugihara, H., Adipose tissueorganotypic culture system as a promising model for studying adipose tissue biology and regeneration (2009) Organogenesis, 5, pp. 50-56; Tuxhorn, J.A., Ayala, G.E., Rowley, D.R., Reactive stroma in prostate cancer progression (2001) Journal of Urology, 166 (6), pp. 2472-2483
Keywords: Adipokines; adiponectin; adipose tissue; adult; article; cancer cell; cancer growth; Cells, Cultured; clinical article; controlled study; Culture Media, Conditioned; culture medium; Cytokines; DNA, Mitochondrial; enzyme activity; enzyme linked immunosorbent assay; explant; gelatinase B; human; human cell; human tissue; Humans; interleukin 6; Interleukin-6; male; Matrix Metalloproteinase 2; Matrix Metalloproteinase 9; Middle Aged; mitochondrial DNA; Osteopontin; Periprostatic adipose tissue; priority journal; Prostate cancer; Prostatic Neoplasms; protein expression; protein induction; protein secretion; quantitative analysis; stroma cell; tissue metabolism; tumor necrosis factor alpha; Tumor Necrosis Factor-alpha

Bone marrow-derived endothelial progenitors expressing delta-like 4 (Dll4) regulate tumor angiogenesis - Real, C.; Remédio, L.; Caiado, F.; Igreja, C.; Borges, C.; Trindade, A.; Pinto-Do-Ó, P.; Yagita, H.; Duarte, A.; Dias, S. (PLoS ONEPLoS ONE, 2011)
Neo-blood vessel growth (angiogenesis), which may involve the activation of pre-existing endothelial cells (EC) and/or the recruitment of bone marrow-derived vascular precursor cells (BM-VPC), is essential for tumor growth. Molecularly, besides the well established roles for Vascular endothelial growth factor (VEGF), recent findings show the Notch signalling pathway, in particular the ligand Delta-like 4 (Dll4), is also essential for adequate tumor angiogenesis; Dll4 inhibition results in impaired, non-functional, angiogenesis and reduced tumor growth. However, the role of BM-VPC in the setting of Notch pathway modulation was not addressed and is the subject of the present report. Here we show that SDF-1 and VEGF, which are produced by tumors, increase Dll4 expression on recruited BM-VPC. Mechanistically, BM-VPC activated, in a Dll4-dependent manner, a transcriptional program on mature EC suggestive of EC activation and stabilization. BM-VPC induced ICAM-2 and Fibronectin expression on EC, an effect that was blocked by a Dll4-specific neutralizing antibody. In vivo, transplantation of BM-VPC with decreased Dll4 into tumor-bearing mice resulted in the formation of microvessels with decreased pericyte coverage and reduced fibronectin expression. Consequently, transplantation of BM-VPC with decreased Dll4 resulted in impaired tumor angiogenesis, increased tumor hypoxia and apoptosis, and decreased tumor growth. Taken together, our data suggests that Dll4 expression by BM-VPC affects their communication with tumor vessel endothelial cells, thereby modulating tumor angiogenesis by affecting vascular stability. © 2011 Real et al.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusArt. No.: e18323doi: 10.1371/journal.pone.0018323Language of Original Document: EnglishCorrespondence Address: Dias, S.; Angiogenesis Laboratory, CIPM/Portuguese Institute of Oncology, Lisbon, Portugal; email: sergidias@ipolisboa.min-saude.ptChemicals/CAS: fibronectin, 86088-83-7; vasculotropin, 127464-60-2; DLL4 protein, mouse; Intracellular Signaling Peptides and Proteins; Membrane ProteinsReferences: Asahara, T., Masuda, H., Takahashi, T., Kalka, C., Pastore, C., Bone marrow origin of endothelial progenitor cells responsible for postnatal vasculogenesis in physiological and pathological neovascularization (1999) Circ Res, 85, pp. 221-228;Rafii, S., Lyden, D., Benezra, R., Hattori, K., Heissig, B., Vascular and haematopoietic stem cells: Novel targets for anti-angiogenesis therapy? (2002) Nat Rev Cancer, 2, pp. 826-835. , Review; Lyden, D., Hattori, K., Dias, S., Costa, C., Blaikie, P., Impaired recruitment of bone-marrow-derived endothelial and hematopoietic precursor cells blocks tumor angiogenesis and growth (2001) Nat Med, 7, pp. 1194-1201; Larrivee, B., Niessen, K., Pollet, I., Corbel, S.Y., Long, M., Minimal contribution of marrow-derived endothelial precursors to tumor vasculature (2005) J Immunol, 175, pp. 2890-2899; Peters, B.A., Diaz, L.A., Polyak, K., Meszler, L., Romans, K., Contribution of bone marrow-derived endothelial cells to human tumor vasculature (2005) Nat Med, 11, pp. 261-262; Pasquier, E., Dias, S., Endothelial progenitor cells: Hope beyond controversy (2010) Curr Cancer Drug Targets, 10 (8), pp. 914-921; Dudley, A.C., Udagawa, T., Melero-Martin, J.M., Shih, S.C., Curatolo, A., Bone marrow is a reservoir for proangiogenic myelomonocytic cells but not endothelial cells in spontaneous tumors (2010) Blood, 116 (17), pp. 2267-2271; Krebs, L.T., Xue, Y., Norton, C.R., Shutter, J.R., Maguire, M., Notch signaling is essential for vascular morphogenesis in mice (2000) Genes Dev, 14, pp. 1343-1352; Uyttendaele, H., Ho, J., Rossant, J., Kitajewski, J., Vascular patterning defects associated with expression of activated Notch4 in embryonic endothelium (2001) Proc Natl Acad Sci U S A, 98, pp. 5643-5648; Duarte, A., Hirashima, M., Benedito, R., Trindade, A., Diniz, P., Dosage-sensitive requirement for mouse Dll4 in artery development (2004) Genes Dev, 18, pp. 2474-2478; Gale, N.W., Dominguez, M.G., Noguera, I., Pan, L., Hughes, V., Haploinsufficiency of delta-like 4 ligand results in embryonic lethality due to major defects in arterial and vascular development (2004) Proc Natl Acad Sci U S A, 101, pp. 15949-15954; Carmeliet, P., Ferreira, V., Breier, G., Pollefeyt, S., Kieckens, L., Abnormal blood vessel development and lethality in embryos lacking a single VEGF allele (1996) Nature, 380, pp. 435-439; Mailhos, C., Modlich, U., Lewis, J., Harris, A., Bicknell, R., Delta4, an endothelial specific notch ligand expressed at sites of physiological and tumor angiogenesis (2001) Differentiation, 69, pp. 135-144; Oliner, J., Min, H., Leal, J., Yu, D., Rao, S., Suppression of angiogenesis and tumor growth by selective inhibition of angiopoietin-2 (2004) Cancer Cell, 6, pp. 507-516; Patel, N.S., Li, J.L., Generali, D., Poulsom, R., Cranston, D.W., Up-regulation of delta-like 4 ligand in human tumor vasculature and the role of basal expression in endothelial cell function (2005) Cancer Res, 65, pp. 8690-8697; Williams, C.K., Li, J.L., Murga, M., Harris, A.L., Tosato, G., Up-regulation of the Notch ligand Delta-like 4 inhibits VEGF-induced endothelial cell function (2006) Blood, 107, pp. 931-939; Caiado, F., Real, C., Carvalho, T., Dias, S., Notch pathway modulation on bone marrow-derived vascular precursor cells regulates their angiogenic and wound healing potential (2008) PLoS One, 3, pp. e3752; Escudier, B., Eisen, T., Stadler, W.M., Szczylik, C., Oudard, S., Sorafenib in advanced clear-cell renal-cell carcinoma (2007) N Engl J Med, 356, pp. 125-134; Llovet, J.M., Ricci, S., Mazzaferro, V., Hilgard, P., Gane, E., Sorafenib in advanced hepatocellular carcinoma (2008) N Engl J Med, 359, pp. 378-390; Motzer, R.J., Bukowski, R.M., Targeted therapy for metastatic renal cell carcinoma (2006) J Clin Oncol, 24, pp. 5601-5608; Bergers, G., Hanahan, D., Modes of resistance to anti-angiogenic therapy (2008) Nat Rev Cancer, 8, pp. 592-603; Verheul, H.M., Pinedo, H.M., Possible molecular mechanisms involved in the toxicity of angiogenesis inhibition (2007) Nat Rev Cancer, 7, pp. 475-485; Noguera-Troise, I., Daly, C., Papadopoulos, N.J., Coetzee, S., Boland, P., Blockade of Dll4 inhibits tumour growth by promoting non-productive angiogenesis (2006) Nature, 444, pp. 1032-1037; Ridgway, J., Zhang, G., Wu, Y., Stawicki, S., Liang, W.C., Inhibition of Dll4 signalling inhibits tumour growth by deregulating angiogenesis (2006) Nature, 444, pp. 1083-1087; Moore, M.A., Hattori, K., Heissig, B., Shieh, J.H., Dias, S., Mobilization of endothelial and hematopoietic stem and progenitor cells by adenovector-mediated elevation of serum levels of SDF-1, VEGF, and angiopoietin-1 (2001) Ann N Y Acad Sci, 938, pp. 36-45. , discussion 45-37; Yamaguchi, J., Kusano, K.F., Masuo, O., Kawamoto, A., Silver, M., Stromal cell-derived factor-1 effects on ex vivo expanded endothelial progenitor cell recruitment for ischemic neovascularization (2003) Circulation, 107, pp. 1322-1328; Leslie, J.D., Ariza-McNaughton, L., Bermange, A.L., McAdow, R., Johnson, S.L., Endothelial signalling by the Notch ligand Delta-like 4 restricts angiogenesis (2007) Development, 134, pp. 839-844; Trindade, A., Kumar, S.R., Scehnet, J.S., Lopes-da-Costa, L., Becker, J., Overexpression of delta-like 4 induces arterialization and attenuates vessel formation in developing mouse embryos (2008) Blood, 112, pp. 1720-1729; Huang, M.T., Mason, J.C., Birdsey, G.M., Amsellem, V., Gerwin, N., Endothelial intercellular adhesion molecule (ICAM)-2 regulates angiogenesis (2005) Blood, 106, pp. 1636-1643; Deutsch, U., Schlaeger, T.M., Dehouck, B., Doring, A., Tauber, S., Inducible endothelial cell-specific gene expression in transgenic mouse embryos and adult mice (2008) Exp Cell Res, 314, pp. 1202-1216; Dias, S., Thomas, H., Balkwill, F., Multiple molecular and cellular changes associated with tumour stasis and regression during IL-12 therapy of a murine breast cancer model (1998) Int J Cancer, 75 (1), pp. 151-157; Scott, K.A., Holdsworth, H., Balkwill, F.R., Dias, S., Exploiting changes in the tumour microenvironment with sequential cytokine and matrix metalloprotease inhibitor treatment in a murine breast cancer model (2000) Br J Cancer, 83 (11), pp. 1538-1543
Keywords: angiogenesis; animal; animal cell; animal tissue; Animals; apoptosis; article; blood vessel; Blood Vessels; bone marrow; bone marrow cell; Bone Marrow Cells; cell activation; Cell Line, Tumor; cell proliferation; controlled study; cytology; delta like 4 protein; DLL4 protein, mouse; Endothelial Cells; endothelium cell; Female; Fibronectin; gene expression; gene expression regulation; genetics; human; human cell; Humans; hypoxia; in vitro study; in vivo study; intercellular adhesion molecule 2; Intracellular Signaling Peptides and Proteins; membrane protein; Membrane Proteins; metabolism; Mice; mouse; Mus; neoplasm; Neoplasms; neovascularization (pathology); Neovascularization, Pathologic; neutralizing antibody; nonhuman; Notch receptor; Pathology; pericyte; protein expression; signal peptide; solid tumor; stem cell; stem cell transplantation; Stem cells; stromal cell derived factor 1; tumor cell line; tumor growth; unclassified drug; vascularization; vasculotropin

Complexity and categorical analysis may improve the interpretation of agreement studies using continuous variables - Costa-Santos, C.; Bernardes, J.; Antunes, L.; Ayres-de-Campos, D. (Journal of Evaluation in Clinical PracticeJ. Eval. Clin. Pract., 2011)
Rationale Complex clinical scenarios involving a high degree of uncertainty frequently lead to a poor agreement over diagnosis and management. However, inconsistent results can be found with the most widely used measures of agreement for continuous variables - the limits of agreement and the intraclass correlation coefficient. Aims and objectives We aim to improve the interpretation of agreement studies using continues variables. Methods and results Evaluation of agreement may be improved by complexity analysis and by categorization of variables, followed by the use of the proportions of agreement. Conclusions The average never characterizes a complex phenomenon and the methods used to access agreement in continuous variables are based on the mean. For future agreement studies, involving complex continuous variables, we recommend a complexity and categorical analysis. © 2011 Blackwell Publishing Ltd.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JECPFdoi: 10.1111/j.1365-2753.2011.01668.xPubMed ID: 21489051Language of Original Document: EnglishCorrespondence Address: Costa-Santos, C.; Department of Biostatistics and Medical Informatics, Faculty of Medicine, University of Porto, Al. Prof. Hernâni Monteiro, 4200-319 Porto, Portugal; email: csantos@med.up.ptReferences: Costa Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynaecology: Inappropriateness, controversies and consequences (2005) BJOG: An International Journal of Obstetrics and Gynaecology, 112 (5), pp. 667-669. , DOI 10.1111/j.1471-0528.2004.00505.x;Khan, K.S., Chien, P.F., Evaluation of a clinical test. I: Assessment of reliability (2001) BJOG, 108, pp. 562-567; Luiz, R.R., Szklo, M., More than one statistical strategy to assess agreement of quantitative measurements may usefully be reported (2005) Journal of Clinical Epidemiology, 58 (3), pp. 215-216. , DOI 10.1016/j.jclinepi.2004.07.007; Costa-Santos, C., Bernardes, J., Ayres-De-Campos, D., Costa, A., Costa, C., The limits of agreement and the intraclass correlation coefficient may be inconsistent in the interpretation of agreement (2011) Journal of Clinical Epidemiology, 64 (3), pp. 264-269; Costa-Santos, C., Antunes, L., Souto, A., Bernardes, J., Assessment of disagreement: A new information-based approach (2010) Annals of Epidemiology, 20, pp. 555-561; Luiz, R.R., Costa, A.J.L., Kale, P.L., Werneck, G.L., Assessment of agreement of a quantitative variable: A new graphical approach (2003) Journal of Clinical Epidemiology, 56 (10), pp. 963-967. , DOI 10.1016/S0895-4356(03)00164-1; Plsek, P.E., Greenhalgh, T., The challenge of complexity in health care (2001) British Medical Journal, 323 (7313), pp. 625-628; Shiell, A., Hawe, P., Gold, L., Complex interventions or complex systems? Implications for health economic evaluation (2008) BMJ, 336 (7656), pp. 1281-1283; Wilson, T., Holt, T., Complexity science: Complexity and clinical care (2001) British Medical Journal, 323 (7314), pp. 685-688; Miles, A., Complexity in medicine and healthcare: People and systems, theory and practice (2009) Journal of Evaluation in Clinical Practice, 15 (3), pp. 409-410; Shannon, Î., A mathematical theory of communication (1948) Bell System Technical Journal, 27, pp. 379-423. , 623- 656; Bernardes, J., Costa-Pereira, A., Ayres-De-Campos, D., Van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) International Journal of Gynecology and Obstetrics, 57 (1), pp. 33-37. , DOI 10.1016/S0020-7292(97)02846-4, PII S0020729297028464; Ayres-De-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) British Journal of Obstetrics and Gynaecology, 106, pp. 1307-1310; Rooth, G., Guidelines for the use of fetal monitoring (1987) International Journal of Gynaecology and Obstetrics, 25, pp. 159-167; Grant, J.M., The fetal heart rate is normal, isn't it? Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Müller, R., Büttner, P., A critical discussion of intraclass correlation coefficients (1994) Statistics in Medicine, 13, pp. 2465-2476; Byrt, T., Bishop, J., Carlin, J.B., Bias, prevalence and kappa (1993) Journal of Clinical Epidemiology, 46 (5), pp. 423-429. , DOI 10.1016/0895-4356(93)90018-V; West, B.J., Homeostasis and Gauss statistics: Barriers to understanding natural variability (2010) Journal of Evaluation in Clinical Practice, 16, pp. 403-408; Goncalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Medical and Biological Engineering and Computing, 44 (10), pp. 847-855. , DOI 10.1007/s11517-006-0105-6; Costa Santos, C., Vitanyi, P.M.B., Bernardes, J., Antunes, L., Clustering fetal heart rate tracings by compression (2006) Proceedings - IEEE Symposium on Computer-Based Medical Systems, 2006, pp. 685-690. , DOI 10.1109/CBMS.2006.68, 1647650, Proceedings - 19th IEEE International Symposium on Computer-Based Medical Systems, CBMS 2006
Keywords: article; Biomedical research; Cardiotocography; clinical decision making; clinical practice; complexity; Data Interpretation, Statistical; Decision Making; entropy; Female; fetus heart rate; Heart Rate, Fetal; human; Humans; observer variation; Pregnancy; Pregnancy Outcome; priority journal; Reproducibility of Results; statistical data interpretation; Uncertainty

Covalent immobilization of antimicrobial peptides (AMPs) onto biomaterial surfaces - Costa, F.; Carvalho, I.F.; Montelaro, R.C.; Gomes, P.; Martins, M.C.L. (Acta BiomaterialiaActa Biomater., 2011)
Bacterial adhesion to biomaterials remains a major problem in the medical devices field. Antimicrobial peptides (AMPs) are well-known components of the innate immune system that can be applied to overcome biofilm-associated infections. Their relevance has been increasing as a practical alternative to conventional antibiotics, which are declining in effectiveness. The recent interest focused on these peptides can be explained by a group of special features, including a wide spectrum of activity, high efficacy at very low concentrations, target specificity, anti-endotoxin activity, synergistic action with classical antibiotics, and low propensity for developing resistance. Therefore, the development of an antimicrobial coating with such properties would be worthwhile. The immobilization of AMPs onto a biomaterial surface has further advantages as it also helps to circumvent AMPs' potential limitations, such as short half-life and cytotoxicity associated with higher concentrations of soluble peptides. The studies discussed in the current review report on the impact of covalent immobilization of AMPs onto surfaces through different chemical coupling strategies, length of spacers, and peptide orientation and concentration. The overall results suggest that immobilized AMPs may be effective in the prevention of biofilm formation by reduction of microorganism survival post-contact with the coated biomaterial. Minimal cytotoxicity and long-term stability profiles were obtained by optimizing immobilization parameters, indicating a promising potential for the use of immobilized AMPs in clinical applications. On the other hand, the effects of tethering on mechanisms of action of AMPs have not yet been fully elucidated. Therefore, further studies are recommended to explore the real potential of immobilized AMPs in health applications as antimicrobial coatings of medical devices. © 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996): 24Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2010.11.005PubMed ID: 21056701Language of Original Document: EnglishCorrespondence Address: Martins, M. C. L.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade Do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: cmartins@ineb.up.ptChemicals/CAS: amoxicillin, 26787-78-0, 34642-77-8, 61336-70-7; ampicillin, 69-52-3, 69-53-4, 7177-48-2, 74083-13-9, 94586-58-0; carbenicillin, 17230-86-3, 4697-36-3, 4800-94-6; cefazolin, 25953-19-9, 27164-46-1; gentamicin, 1392-48-9, 1403-66-3, 1405-41-0; penicillin G, 1406-05-9, 61-33-6; teicoplanin, 61036-62-2, 61036-64-4; tobramycin, 32986-56-4; vancomycin, 1404-90-6, 1404-93-9; Antimicrobial Cationic Peptides; Biocompatible Materials; Coated Materials, Biocompatible; Immobilized ProteinsReferences: Glinel, K., Jonas, A.M., Jouenne, T., Leprince, J., Galas, L., Huck, W.T., Antibacterial and antifouling polymer brushes incorporating antimicrobial peptide (2009) Bioconj Chem, 20 (1), pp. 71-77;Vila, J., Soriano, A., Mensa, J., Molecular basis of microbial adherence to prosthetic materials. Role of biofilms in prosthesis-associated infection (2008) Enferm Infecc Microbiol Clin, 26 (1), pp. 48-54; Hetrick, E.M., Schoenfisch, M.H., Reducing implant-related infections: Active release strategies (2006) Chemical Society Reviews, 35 (9), pp. 780-789. , DOI 10.1039/b515219b; Darouiche, R.O., Treatment of Infections Associated with Surgical Implants (2004) New England Journal of Medicine, 350 (14), pp. 1422-1429. , DOI 10.1056/NEJMra035415; Zhao, L., Chu, P.K., Zhang, Y., Wu, Z., Antibacterial coatings on titanium implants (2009) J Biomed Mater Res B Appl Biomater, 91 (1), pp. 470-480; Dee, K.C., Puleo, D.A., Bizios, R., (2002) An Introduction to Tissue-biomaterial Interactions, , Wiley-Liss New York; Subramani, K., Jung, R.E., Molenberg, A., Hammerle, C.H., Biofilm on dental implants: A review of the literature (2009) Int J Oral Maxillofac Implants, 24 (4), pp. 616-626; Fey, P.D., Olson, M.E., Current concepts in biofilm formation of Staphylococcus epidermidis (2010) Future Microbiol, 5 (6), pp. 917-933; De Carvalho, C.C., Biofilms: Recent developments on an old battle (2007) Recent Pat Biotechnol, 1 (1), pp. 49-57; Costerton, J.W., Stewart, P.S., Greenberg, E.P., Bacterial biofilms: A common cause of persistent infections (1999) Science, 284 (5418), pp. 1318-1322. , DOI 10.1126/science.284.5418.1318; Willcox, M.D., Hume, E.B., Aliwarga, Y., Kumar, N., Cole, N., A novel cationic-peptide coating for the prevention of microbial colonization on contact lenses (2008) J Appl Microbiol, 105 (6), pp. 1817-1825; Lewis, K., Riddle of biofilm resistance (2001) Antimicrobial Agents and Chemotherapy, 45 (4), pp. 999-1007. , DOI 10.1128/AAC.45.4.999-1007.2001; Monteiro, D.R., Gorup, L.F., Takamiya, A.S., Ruvollo-Filho, A.C., De Camargo, E.R., Barbosa, D.B., The growing importance of materials that prevent microbial adhesion: Antimicrobial effect of medical devices containing silver (2009) Int J Antimicrob Agents, 34 (2), pp. 103-110; Gooderham, W.J., Bains, M., McPhee, J.B., Wiegand, I., Hancock, R.E., Induction by cationic antimicrobial peptides and involvement in intrinsic polymyxin and antimicrobial peptide resistance, biofilm formation, and swarming motility of PsrA in Pseudomonas aeruginosa (2008) J Bacteriol, 190 (16), pp. 5624-5634; Bagge, N., Schuster, M., Hentzer, M., Ciofu, O., Givskov, M., Greenberg, E.P., Hoiby, N., Pseudomonas aeruginosa Biofilms Exposed to Imipenem Exhibit Changes in Global Gene Expression and β-Lactamase and Alginate Production (2004) Antimicrobial Agents and Chemotherapy, 48 (4), pp. 1175-1187. , DOI 10.1128/AAC.48.4.1175-1187.2004; Ahmed, N.A., Petersen, F.C., Scheie, A.A., AI-2/LuxS is involved in increased biofilm formation by Streptococcus intermedius in the presence of antibiotics (2009) Antimicrob Agents Chemother, 53 (10), pp. 4258-4263; Hoffman, L.R., D'Argenio, D.A., MacCoss, M.J., Zhang, Z., Jones, R.A., Miller, S.I., Aminoglycoside antibiotics induce bacterial biofilm formation (2005) Nature, 436 (7054), pp. 1171-1175. , DOI 10.1038/nature03912; Harbers, G.M., Emoto, K., Greef, C., Metzger, S.W., Woodward, H.N., Mascali, J.J., Grainger, D.W., Lochhead, M.J., Functionalized poly(ethylene glycol)-based bioassay surface chemistry that facilitates bio-immobilization and inhibits nonspecific protein, bacterial, and mammalian cell adhesion (2007) Chemistry of Materials, 19 (18), pp. 4405-4414. , DOI 10.1021/cm070509u; Chapman, R.G., Ostuni, E., Liang, M.N., Meluleni, G., Kim, E., Yan, L., Pier, G., Whitesides, G.M., Polymeric thin films that resist the adsorption of proteins and the adhesion of bacteria (2001) Langmuir, 17 (4), pp. 1225-1233. , DOI 10.1021/la001222d; Goncalves, I.C., Martins, M.C., Barbosa, M.A., Naeemi, E., Ratner, B.D., Selective protein adsorption modulates platelet adhesion and activation to oligo(ethylene glycol)-terminated self-assembled monolayers with C18 ligands (2009) J Biomed Mater Res A, 89 (3), pp. 642-653; Chung, D., Papadakis, S.E., Yam, K.L., Evaluation of a polymer coating containing triclosan as the antimicrobial layer for packaging materials (2003) International Journal of Food Science and Technology, 38 (2), pp. 165-169. , DOI 10.1046/j.1365-2621.2003.00657.x; Leung, D., Spratt, D.A., Pratten, J., Gulabivala, K., Mordan, N.J., Young, A.M., Chlorhexidine-releasing methacrylate dental composite materials (2005) Biomaterials, 26 (34), pp. 7145-7153. , DOI 10.1016/j.biomaterials.2005.05.014, PII S0142961205003881; Ravikumar, T., Murata, H., Koepsel, R.R., Russell, A.J., Surface-active antifungal polyquaternary amine (2006) Biomacromolecules, 7 (10), pp. 2762-2769. , DOI 10.1021/bm060476w; Bach, A., Darby, D., Bottiger, B., Bohrer, H., Motsch, J., Martin, E., Retention of the antibiotic teicoplanin on a hydromer-coated central venous catheter to prevent bacterial colonization in postoperative surgical patients (1996) Intensive Care Medicine, 22 (10), pp. 1066-1069. , DOI 10.1007/s001340050214; Jose, B., Antoci Jr., V., Zeiger, A.R., Wickstrom, E., Hickok, N.J., Vancomycin covalently bonded to titanium beads kills Staphylococcus aureus (2005) Chemistry and Biology, 12 (9), pp. 1041-1048. , DOI 10.1016/j.chembiol.2005.06.013, PII S1074552105002309; Kilic, D., Agalar, C., Ozturk, E., Denkbas, E.B., Cime, A., Agalar, F., Antimicrobial activity of cefazolin-impregnated mesh grafts (2007) ANZ Journal of Surgery, 77 (4), pp. 256-260. , DOI 10.1111/j.1445-2197.2007.04029.x; Gallardo-Moreno, A.M., Pacha-Olivenza, M.A., Saldana, L., Perez-Giraldo, C., Bruque, J.M., Vilaboa, N., In vitro biocompatibility and bacterial adhesion of physico-chemically modified Ti6Al4V surface by means of UV irradiation (2009) Acta Biomater, 5 (1), pp. 181-192; Jansen, B., Kohnen, W., Prevention of biofilm formation by polymer modification (1995) Journal of Industrial Microbiology, 15 (4), pp. 391-396. , DOI 10.1007/BF01569996; Martins, M.C.L., Wang, D., Ji, J., Feng, L., Barbosa, M.A., Albumin and fibrinogen adsorption on Cibacron blue F3G-A immobilised onto PU-PHEMA (polyurethane-poly (hydroxyethylmethacrylate)) surfaces (2003) Journal of Biomaterials Science, Polymer Edition, 14 (5), pp. 439-455. , DOI 10.1163/156856203766652057; Zhang, F., Zhang, Z., Zhu, X., Kang, E.T., Neoh, K.G., Silk-functionalized titanium surfaces for enhancing osteoblast functions and reducing bacterial adhesion (2008) Biomaterials, 29 (36), pp. 4751-4759; Flemming, R.G., Capelli, C.C., Cooper, S.L., Proctor, R.A., Bacterial colonization of functionalized polyurethanes (2000) Biomaterials, 21 (3), pp. 273-281; Singla, A.K., Chawla, M., Chitosan: Some pharmaceutical and biological aspects - An update (2001) Journal of Pharmacy and Pharmacology, 53 (8), pp. 1047-1067. , DOI 10.1211/0022357011776441; Murata, H., Koepsel, R.R., Matyjaszewski, K., Russell, A.J., Permanent, non-leaching antibacterial surfaces-2: How high density cationic surfaces kill bacterial cells (2007) Biomaterials, 28 (32), pp. 4870-4879. , DOI 10.1016/j.biomaterials.2007.06.012, PII S0142961207004681; Aumsuwan, N., Danyus, R.C., Heinhorst, S., Urban, M.W., Attachment of ampicillin to expanded poly(tetrafluoroethylene): Surface reactions leading to inhibition of microbial growth (2008) Biomacromolecules, 9 (7), pp. 1712-1718; Cevher, E., Orhan, Z., Mulazimoglu, L., Sensoy, D., Alper, M., Yildiz, A., Characterization of biodegradable chitosan microspheres containing vancomycin and treatment of experimental osteomyelitis caused by methicillin-resistant Staphylococcus aureus with prepared microspheres (2006) Int J Pharm, 317 (2), pp. 127-135; Faber, C., Stallmann, H.P., Lyaruu, D.M., Joosten, U., Von Eiff, C., Van Nieuw Amerongen, A., Wuisman, P.I.J.M., Comparable efficacies of the antimicrobial peptide human lactoferrin 1-11 and gentamicin in a chronic methicillin-resistant Staphylococcus aureus osteomyelitis model (2005) Antimicrobial Agents and Chemotherapy, 49 (6), pp. 2438-2444. , DOI 10.1128/AAC.49.6.2438-2444.2005; Aumsuwan, N., Heinhorst, S., Urban, M.W., Antibacterial surfaces on expanded polytetrafluoroethylene; penicillin attachment (2007) Biomacromolecules, 8 (2), pp. 713-718. , DOI 10.1021/bm061050k; Palumbi, S.R., Humans as the world's greatest evolutionary force (2001) Science, 293 (5536), pp. 1786-1790. , DOI 10.1126/science.293.5536.1786; Andreu, D., Rivas, L., Animal antimicrobial peptides: An overview (1998) Biopolymers, 47 (6), pp. 415-433; Rivas, L., Luque-Ortega, J.R., Andreu, D., Amphibian antimicrobial peptides and Protozoa: Lessons from parasites (2009) Biochim Biophys Acta, 1788 (8), pp. 1570-1581; Gordon, Y.J., Romanowski, E.G., McDermott, A.M., Mini review: A review of antimicrobial peptides and their therapeutic potential as anti-infective drugs (2005) Current Eye Research, 30 (7), pp. 505-515. , DOI 10.1080/02713680590968637; Guani-Guerra, E., Santos-Mendoza, T., Lugo-Reyes, S.O., Teran, L.M., Antimicrobial peptides: General overview and clinical implications in human health and disease (2010) Clin Immunol, 135 (1), pp. 1-11; Perron, G.G., Zasloff, M., Bell, G., Experimental evolution of resistance to an antimicrobial peptide (2006) Proceedings of the Royal Society B: Biological Sciences, 273 (1583), pp. 251-256. , DOI 10.1098/rspb.2005.3301; Reddy, K.V.R., Yedery, R.D., Aranha, C., Antimicrobial peptides: Premises and promises (2004) International Journal of Antimicrobial Agents, 24 (6), pp. 536-547. , DOI 10.1016/j.ijantimicag.2004.09.005, PII S092485790400322X; Van 'T Hof, W., Veerman, E.C.I., Heimerhorst, E.J., Nieuw Amerongen, A.V., Antimicrobial peptides: Properties and applicability (2001) Biological Chemistry, 382 (4), pp. 597-619. , DOI 10.1515/BC.2001.072; Li, M., Cha, D.J., Lai, Y., Villaruz, A.E., Sturdevant, D.E., Otto, M., The antimicrobial peptide-sensing system aps of Staphylococcus aureus (2007) Molecular Microbiology, 66 (5), pp. 1136-1147. , DOI 10.1111/j.1365-2958.2007.05986.x; Li, M., Lai, Y., Villaruz, A.E., Cha, D.J., Sturdevant, D.E., Otto, M., Gram-positive three-component antimicrobial peptide-sensing system (2007) Proceedings of the National Academy of Sciences of the United States of America, 104 (22), pp. 9469-9474. , DOI 10.1073/pnas.0702159104; Otto, M., Bacterial sensing of antimicrobial peptides (2009) Contrib Microbiol, 16, pp. 136-149; Peschel, A., Vincent Collins, L., Staphylococcal resistance to antimicrobial peptides of mammalian and bacterial origin (2001) Peptides, 22 (10), pp. 1651-1659. , DOI 10.1016/S0196-9781(01)00500-9, PII S0196978101005009; Peschel, A., Jack, R.W., Otto, M., Collins, L.V., Staubitz, P., Nicholson, G., Kalbacher, H., Van Strijp, J.A.G., Staphylococcus aureus resistance to human defensins and evasion of neutrophil killing via the novel virulence factor MprF is based on modification of membrane lipids with L-lysine (2001) Journal of Experimental Medicine, 193 (9), pp. 1067-1076. , DOI 10.1084/jem.193.9.1067; Cao, M., Helmann, J.D., The Bacillus subtilis Extracytoplasmic-Function σ X Factor Regulates Modification of the Cell Envelope and Resistance to Cationic Antimicrobial Peptides (2004) Journal of Bacteriology, 186 (4), pp. 1136-1146. , DOI 10.1128/JB.186.4.1136-1146.2004; Clarke, S.R., Foster, S.J., IsdA protects Staphylococcus aureus against the bactericidal protease activity of apolactoferrin (2008) Infection and Immunity, 76 (4), pp. 1518-1526. , DOI 10.1128/IAI.01530-07; Vuong, C., Voyich, J.M., Fischer, E.R., Braughton, K.R., Whitney, A.R., DeLeo, F.R., Otto, M., Polysaccharide intercellular adhesin (PIA) protects Staphylococcus epidermidis against major components of the human innate immune system (2004) Cellular Microbiology, 6 (3), pp. 269-275. , DOI 10.1046/j.1462-5822.2004.00367.x; Zasloff, M., Antimicrobial peptides of multicellular organisms (2002) Nature, 415 (6870), pp. 389-395. , DOI 10.1038/415389a; Hancock, R.E.W., Peptide antibiotics (1997) Lancet, 349 (9049), pp. 418-422. , DOI 10.1016/S0140-6736(97)80051-7; Cho, W.-M., Joshi, B.P., Cho, H., Lee, K.-H., Design and synthesis of novel antibacterial peptide-resin conjugates (2007) Bioorganic and Medicinal Chemistry Letters, 17 (21), pp. 5772-5776. , DOI 10.1016/j.bmcl.2007.08.056, PII S0960894X0701013X; Statz, A.R., Park, J.P., Chongsiriwatana, N.P., Barron, A.E., Messersmith, P.B., Surface-immobilised antimicrobial peptoids (2008) Biofouling, 24 (6), pp. 439-448; Deslouches, B., Gonzalez, I.A., DeAlmeida, D., Islam, K., Steele, C., Montelaro, R.C., Mietzner, T.A., De novo-derived cationic antimicrobial peptide activity in a murine model of Pseudomonas aeruginosa bacteraemia (2007) Journal of Antimicrobial Chemotherapy, 60 (3), pp. 669-672. , DOI 10.1093/jac/dkm253; Novak, K.F., Diamond, W.J., Kirakodu, S., Peyyala, R., Anderson, K.W., Montelaro, R.C., Mietzner, T.A., Efficacy of the de novo-derived antimicrobial peptide WLBU2 against oral bacteria (2007) Antimicrobial Agents and Chemotherapy, 51 (5), pp. 1837-1839. , DOI 10.1128/AAC.00924-06; Deslouches, B., Islam, K., Craigo, J.K., Paranjape, S.M., Montelaro, R.C., Mietzner, T.A., Activity of the de novo engineered antimicrobial peptide WLBU2 against Pseudomonas aeruginosa in human serum and whole blood: Implications for systemic applications (2005) Antimicrobial Agents and Chemotherapy, 49 (8), pp. 3208-3216. , DOI 10.1128/AAC.49.8.3208-3216.2005; Deslouches, B., Phadke, S.M., Lazarevic, V., Cascio, M., Islam, K., Montelaro, R.C., Mietzner, T.A., De novo generation of cationic antimicrobial peptides: Influence of length and tryptophan substitution on antimicrobial activity (2005) Antimicrobial Agents and Chemotherapy, 49 (1), pp. 316-322. , DOI 10.1128/AAC.49.1.316-322.2005; Levin, M., Quint, P.A., Goldstein, B., Barton, P., Bradley, J.S., Shemie, S.D., Recombinant bactericidal/permeability-increasing protein (rBPI21) as adjunctive treatment for children with severe meningococcal sepsis: A randomised trial. rBPI21 Meningococcal Sepsis Study Group (2000) Lancet, 356 (9234), pp. 961-967; Giroir, B.P., Scannon, P.J., Levin, M., Bactericidal/permeability-increasing protein-lessons learned from the phase III, randomized, clinical trial of rBPI21 for adjunctive treatment of children with severe meningococcemia (2001) Crit Care Med, 29 (7 SUPPL.), pp. 130-135; Brogden, K.A., Antimicrobial peptides: Pore formers or metabolic inhibitors in bacteria? (2005) Nature Reviews Microbiology, 3 (3), pp. 238-250. , DOI 10.1038/nrmicro1098; Bastos, M., Bai, G., Gomes, P., Andreu, D., Goormaghtigh, E., Prieto, M., Energetics and partition of two cecropin-melittin hybrid peptides to model membranes of different composition (2008) Biophys J, 94 (6), pp. 2128-2141; Melo, M.N., Ferre, R., Castanho, M.A., Antimicrobial peptides: Linking partition, activity and high membrane-bound concentrations (2009) Nat Rev Microbiol, 7 (3), pp. 245-250; Haynie, S.L., Crum, G.A., Doele, B.A., Antimicrobial activities of amphiphilic peptides covalently bonded to a water-insoluble resin (1995) Antimicrob Agents Chemother, 39 (2), pp. 301-307; Humblot, V., Yala, J.F., Thebault, P., Boukerma, K., Hequet, A., Berjeaud, J.M., The antibacterial activity of Magainin i immobilized onto mixed thiols self-assembled monolayers (2009) Biomaterials, 30 (21), pp. 3503-3512; Bagheri, M., Beyermann, M., Dathe, M., Immobilization reduces the activity of surface-bound cationic antimicrobial peptides with no influence upon the activity spectrum (2009) Antimicrob Agents Chemother, 53 (3), pp. 1132-1141; Gabriel, M., Nazmi, K., Veerman, E.C., Nieuw Amerongen, A.V., Zentner, A., Preparation of LL-37-grafted titanium surfaces with bactericidal activity (2006) Bioconj Chem, 17 (2), pp. 548-550; Hilpert, K., Elliott, M., Jenssen, H., Kindrachuk, J., Fjell, C.D., Korner, J., Screening and characterization of surface-tethered cationic peptides for antimicrobial activity (2009) Chem Biol, 16 (1), pp. 58-69; Batista, M.K.S., Gallemi, M., Adeva, A., Gomes, C.A.R., Gomes, P., Facile regioselective synthesis of a novel chitosan-pexiganan conjugate with potential interest for the treatment of infected skin lesions (2009) Synthetic Commun, 39 (7), pp. 1228-1240; Venter, J.C., Immobilized and insolubilized drugs, hormones, and neurotransmitters: Properties, mechanisms of action and applications (1982) Pharmacological Reviews, 34 (2), pp. 153-187; Endo, Y., Tani, T., Kodama, M., Antimicrobial activity of tertiary amine covalently bonded to a polystyrene fiber (1987) Appl Environ Microbiol, 53 (9), pp. 2050-2055; Chuang, H.F., Shukla, A., Loose, C.R., Hammond-Cunningham, P.T., Stephanopoulos, G., (2009) Structures Including Antimicrobial Peptides, , United States; Chen, R., Cole, N., Willcox, M.D., Park, J., Rasul, R., Carter, E., Synthesis, characterization and in vitro activity of a surface-attached antimicrobial cationic peptide (2009) Biofouling, 25 (6), pp. 517-524; Steven, M.D., Hotchkiss, J.H., Covalent immobilization of an antimicrobial peptide on poly(ethylene) film (2008) J Appl Polym Sci, 110 (5), pp. 2665-2670; Appendini, P., Hotchkiss, J.H., Surface modification of poly(styrene) by the attachment of an antimicrobial peptide (2001) J Appl Polym Sci, 81 (3), pp. 609-616; Fields, G.B., Noble, R.L., Solid phase peptide synthesis utilizing 9-fluorenylmethoxycarbonyl amino acids (1990) International Journal of Peptide and Protein Research, 35 (3), pp. 161-214; Rostovtsev, V.V., Green, L.G., Fokin, V.V., Sharpless, K.B., A stepwise huisgen cycloaddition process: Copper(I)-catalyzed regioselective "ligation" of azides and terminal alkynes (2002) Angewandte Chemie - International Edition, 41 (14), pp. 2596-2599. , DOI 10.1002/1521-3773(20020715)41: 14<2596::AID-ANIE2596>3.0.CO;2-4; Abad, J.M., Velez, M., Santamaria, C., Guisan, J.M., Matheus, P.R., Vazquez, L., Gazaryan, I., Fernandez, V.M., Immobilization of peroxidase glycoprotein on gold electrodes modified with mixed epoxy-boronic acid monolayers (2002) Journal of the American Chemical Society, 124 (43), pp. 12845-12853. , DOI 10.1021/ja026658p; Lee, M.-R., Shin, I., Fabrication of chemical microarrays by efficient immobilization of hydrazide-linked substances on epoxide-coated glass surfaces (2005) Angewandte Chemie - International Edition, 44 (19), pp. 2881-2884. , DOI 10.1002/anie.200462720; Hudalla, G.A., Murphy, W.L., Immobilization of peptides with distinct biological activities onto stem cell culture substrates using orthogonal chemistries (2010) Langmuir, 26 (9), pp. 6449-6456; Cole, N., Hume, E.B., Vijay, A.K., Sankaridurg, P., Kumar, N., Willcox, M.D., In vivo performance of melimine as an antimicrobial coating for contact lenses in models of CLARE and CLPU (2010) Invest Ophthalmol Vis Sci, 51 (1), pp. 390-395
Keywords: Amino Acid Sequence; amoxicillin; ampicillin; Animals; antibiotic agent; antibiotic resistance; Antimicrobial Cationic Peptides; Antimicrobial peptides; Bacteria (microorganisms); Bacterial adhesion; bacterial survival; Biocompatible Materials; biofilm; Biofilms; biomaterial; carbenicillin; cefazolin; Coated Materials, Biocompatible; Cytotoxicity; drug activity; drug half life; drug solubility; drug stability; drug targeting; gentamicin; human; Humans; Immobilized Proteins; Molecular Sequence Data; mouth inflammation; Nanostructured surfaces; nonhuman; penicillin G; polypeptide antibiotic agent; priority journal; review; sepsis; skin infection; soft tissue infection; Surface functionalization; Surface Properties; teicoplanin; tobramycin; vancomycin

Interactions of leukocytes and platelets with poly(lysine/leucine) immobilized on tetraethylene glycol-terminated self-assembled monolayers - Martins, M.C.L.; Ochoa-Mendes, V.; Ferreira, G.; Barbosa, J.N.; Curtin, S.A.; Ratner, B.D.; Barbosa, M.A. (Acta BiomaterialiaActa Biomater., 2011)
Surfaces that bind heparin are important for biomaterials for blood deheparinization. In our recent work it was demonstrated that a polypeptide composed of l-lysine and l-leucine (pKL), after immobilization onto tetra(ethylene glycol) terminated self-assembled monolayers (EG4-SAMs), can bind heparin from blood plasma in a selective, concentration-dependent way. During this work the effect of this peptide on platelet adhesion and activation and leukocyte adhesion was studied. The surface charge of these nanostructured surfaces was evaluated in order to correlate the effect of positively charged amine groups and hydrophobic methyl groups on the behavior of platelets and leukocyte adhesion. The results demonstrated that the presence of pKL decreased leukocyte adhesion to EG4-SAMs at all concentrations used. This effect is even more pronounced when surfaces were pre-immersed in heparinized plasma. In contrast, there is an increase in platelet adhesion and activation with increased percentage immobilized pKL. This effect is enhanced when surfaces were pre-immersed in heparinized plasma. However, adsorbed pKL in very low amounts does not induce platelet adhesion and activation compared with EG4, even when pre-immersed in plasma. Since only low pKL amounts are necessary to induce heparin selectivity, these results are promising for the development of heparin-binding biomaterials for blood deheparinization. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2011.01.013PubMed ID: 21237292Language of Original Document: EnglishCorrespondence Address: Martins, M. C. L.; Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade Do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cmartins@ineb.up.ptChemicals/CAS: heparin, 37187-54-5, 8057-48-5, 8065-01-8, 9005-48-5; leucine, 61-90-5, 7005-03-0; polylysine, 25104-18-1, 25988-63-0, 33960-24-6, 38000-06-5, 73565-56-7; Ethylene Glycol, 107-21-1; Imidazoles; Immobilized Proteins; N,N-carbonyldiimidazole, 530-62-1; Polyethylene Glycols; Polylysine, 25104-18-1; ProteinsReferences: Dailey, J., (1998) Blood, , 2nd ed. Ipswich (MA, USA): Medical Consulting Group;Section V: Chronic intermittent haemodialysis and prevention of clotting in the extracorporal system (2002) Nephrol Dial Transplant, 17 (SUPPL. 7), pp. 63-71. , European Best Practice Guidelines Working Group; Martins, M.C., Curtin, S.A., Freitas, S.C., Salgueiro, P., Ratner, B.D., Barbosa, M.A., Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide (2009) J Biomed Mater Res A, 88, pp. 162-173; Love, J.C., Estroff, L.A., Kriebel, J.K., Nuzzo, R.G., Whitesides, G.M., Self-assembled monolayers of thiolates on metals as a form of nanotechnology (2005) Chemical Reviews, 105 (4), pp. 1103-1169. , DOI 10.1021/cr0300789; Cardin, A.D., Weintraub, H.J.R., Molecular modeling of protein-glycosaminoglycan interactions (1989) Arteriosclerosis, 9 (1), pp. 21-32; Prime, K.L., Whitesides, G.M., Adsorption of proteins onto surfaces containing end-attached oligo(ethylene oxide) - A model system using self-assembled monolayers (1993) J Am Chem Soc, 115, pp. 10714-10721; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl-terminated alkanethiols self-assembled monolayers (2003) Journal of Biomedical Materials Research - Part A, 67 (1), pp. 158-171; Werner, C., Konig, U., Augsburg, A., Arnhold, C., Korber, H., Zimmermann, R., Jacobasch, H.-J., Electrokinetic surface characterization of biomedical polymers - A survey (1999) Colloids and Surfaces A: Physicochemical and Engineering Aspects, 159 (2-3), pp. 519-529. , DOI 10.1016/S0927-7757(99)00290-3, PII S0927775799002903; Frank, R.D., Dresbach, H., Thelen, H., Sieberth, H.-G., Glutardialdehyde induced fluorescence technique (GIFT): A new method for the imaging of platelet adhesion on biomaterials (2000) Journal of Biomedical Materials Research, 52 (2), pp. 374-381. , DOI 10.1002/1097-4636(200011)52:2<374::AID-JBM18>3.0.CO;2-Z; Chan, Y.H.M., Schweiss, R., Werner, C., Grunze, M., Electrokinetic characterization of oligo- and poly(ethylene glycol)-terminated self-assembled monolayers on gold and glass surfaces (2003) Langmuir, 19, pp. 7380-7385; Schweiss, R., Welzel, P.B., Werner, C., Knoll, W., Dissociation of surface functional groups and preferential adsorption of ions on self-assembled monolayers assessed by streaming potential and streaming current measurements (2001) Langmuir, 17 (14), pp. 4304-4311. , DOI 10.1021/la001741g; Rodrigues, S.N., Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27 (31), pp. 5357-5367. , DOI 10.1016/j.biomaterials.2006.06.010, PII S0142961206005515; Goncalves, I.C., Martins, M.C., Barbosa, M.A., Naeemi, E., Ratner, B.D., Selective protein adsorption modulates platelet adhesion and activation to oligo(ethylene glycol)-terminated self-assembled monolayers with C18 ligands (2009) J Biomed Mater Res, 89 A, pp. 642-653; Prime, K.L., Whitesides, G.M., Self-assembled organic monolayers: Model systems for studying adsorption of proteins at surfaces (1991) Science, 252 (5009), pp. 1164-1167; Mrksich, M., Using self-assembled monolayers to model the extracellular matrix (2009) Acta Biomater, 5, pp. 832-841; Sagnella, S., Mai-Ngam, K., Chitosan based surfactant polymers designed to improve blood compatibility on biomaterials (2005) Colloids Surf B Biointerfaces, 42, pp. 147-155; Chuang, W.H., Lin, J.C., Surface characterization and platelet adhesion studies for the mixed self-assembled monolayers with amine and carboxylic acid terminated functionalities (2007) J Biomed Mater Res A, 82, pp. 820-830; Chen, S., Yu, F., Yu, Q., He, Y., Jiang, S., Strong resistance of a thin crystalline layer of balanced charged groups to protein adsorption (2006) Langmuir, 22 (19), pp. 8186-8191. , DOI 10.1021/la061012m; Chen, S.F., Jiang, S.Y., A new avenue to nonfouling materials (2008) Adv Mater, 20, p. 335; Li, D., Chen, H., Glenn McClung, W., Brash, J.L., Lysine-PEG-modified polyurethane as a fibrinolytic surface. effect of PEG chain length on protein interactions, platelet interactions and clot lysis (2009) Acta Biomater, 5, pp. 1864-1871; Tsai, W.-B., Grunkemeier, J.M., Horbett, T.A., Variations in the ability of adsorbed fibrinogen to mediate platelet adhesion to polystyrene-based materials: A multivariate statistical analysis of antibody binding to the platelet binding sites of fibrinogen (2003) Journal of Biomedical Materials Research - Part A, 67 (4), pp. 1255-1268; Weisel, J.W., Nagaswami, C., Vilaire, G., Bennett, J.S., Examination of the platelet membrane glycoprotein IIb-IIIa complex and its interaction with fibrinogen and other ligands by electron microscopy (1992) J Biol Chem, 267 (23), pp. 16637-16643; Gorbet, M.B., Sefton, M.V., Biomaterial-associated thrombosis: Roles of coagulation factors, complement, platelets and leukocytes (2004) Biomaterials, 25 (26), pp. 5681-5703. , DOI 10.1016/j.biomaterials.2004.01.023, PII S0142961204000687; Brash, J.L., Tenhove, P., Protein adsorption studies on standard polymeric materials (1993) J Biomater Sci Polym Ed, 4, pp. 591-599; Sigal, G.B., Mrksich, M., Whitesides, G.M., Effect of surface wettability on the adsorption of proteins and detergents (1998) Journal of the American Chemical Society, 120 (14), pp. 3464-3473. , DOI 10.1021/ja970819l; Silin, V., Weetall, H., Vanderah, D.J., SPR studies of the nonspecific adsorption kinetics of human IgG and BSA on gold surfaces modified by self-assembled monolayers (SAMs) (1997) Journal of Colloid and Interface Science, 185 (1), pp. 94-103. , DOI 10.1006/jcis.1996.4586; Jenney, C.R., Anderson, J.M., Adsorbed serum proteins responsible for surface dependent human macrophage behavior (2000) Journal of Biomedical Materials Research, 49 (4), pp. 435-447. , DOI 10.1002/(SICI)1097-4636(20000315)49:4<435::AID-JBM2>3.0.CO;2-Y; Werthen, M., Sellborn, A., Kalltorp, M., Elwing, H., Thomsen, P., In vitro study of monocyte viability during the initial adhesion to albumin- and fibrinogen-coated surfaces (2001) Biomaterials, 22, pp. 827-832; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) Journal of Biomedical Materials Research, 50 (3), pp. 291-301. , DOI 10.1002/(SICI)1097-4636(20000605)50:3<291::AID-JBM2>3.0.CO;2-1; Barbosa, J.N., Martins, M.C.L., Freitas, S.C., Goncalves, I.C., Aguas, A.P., Barbosa, M.A., Adhesion of human leucocytes on mixtures of hydroxyl- and methyl-terminated self-assembled monolayers: Effect of blood protein adsorption (2010) J Biomed Mater Res, 93 A, pp. 12-19; Sperling, C., Schweiss, R.B., Streller, U., Werner, C., In vitro hemocompatibility of self-assembled monolayers displaying various functional groups (2005) Biomaterials, 26, pp. 6547-6557; Toda, M., Kitazawa, T., Hirata, I., Hirano, Y., Iwata, H., Complement activation on surfaces carrying amino groups (2008) Biomaterials, 29 (4), pp. 407-417. , DOI 10.1016/j.biomaterials.2007.10.005, PII S014296120700796X
Keywords: article; Blood Platelets; Cell Communication; Cell Shape; Ethylene Glycol; heparin; heparin binding protein; Humans; hydrophobicity; Imidazoles; Immobilized Proteins; leucine; leukocyte; leukocyte adherence; Leukocytes; methyl group; nanomaterial; plasma; Platelet Adhesiveness; Platelets; Polyethylene Glycols; polylysine; polypeptide; priority journal; Proteins; self assembled monolayer; Self-assembled monolayers; static electricity; Surface charge; Surface Properties; Tetra; thrombocyte; thrombocyte adhesion

Isotropic micropatterned silica coatings on zirconia induce guided cell growth for dental implants - Pelaez-Vargas, A.; Gallego-Perez, D.; Magallanes-Perdomo, M.; Fernandes, M.H.; Hansford, D.J.; De Aza, A.H.; Pena, P.; Monteiro, F.J. (Dental MaterialsDent. Mater., 2011)
Titanium implants are the gold standard in dentistry; however, problems such as gingival tarnishing and peri-implantitis have been reported. For zirconia to become a competitive alternative dental implant material, surface modification techniques that induce guided tissue growth must be developed. Objectives: To develop alternative surface modification techniques to promote guided tissue regeneration on zirconia materials, for applications in dental implantology. Methods: A methodology that combined soft lithography and sol-gel chemistry was used to obtain isotropic micropatterned silica coatings on yttria-stabilized zirconia substrates. The materials were characterized via chemical, structural, surface morphology approaches. In vitro biological behavior was evaluated in terms of early adhesion and viability/metabolic activity of human osteoblast-like cells. Statistical analysis was conducted using one-way ANOVA/Tukey HSD post hoc test. Results: Isotropic micropatterned silica coatings on yttria-stabilized zirconia substrates were obtained using a combined approach based on sol-gel technology and soft lithography. Micropatterned silica surfaces exhibited a biocompatible behavior, and modulated cell responses (i.e. inducing early alignment of osteoblast-like cells). After 7 d of culture, the cells fully covered the top surfaces of pillar microstructured silica films. Significance: The micropatterned silica films on zirconia showed a biocompatible response, and were capable of inducing guided osteoblastic cell adhesion, spreading and propagation. The results herein presented suggest that surface-modified ceramic implants via soft lithography and sol-gel chemistry could potentially be used to guide periodontal tissue regeneration, thus promoting tight tissue apposition, and avoiding gingival retraction and peri-implantitis. © 2011 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: DEMAEdoi: 10.1016/j.dental.2011.02.014Language of Original Document: EnglishCorrespondence Address: Pelaez-Vargas, A.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade Do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: alejopv@ineb.up.ptChemicals/CAS: resazurin, 550-82-3; silicon dioxide, 10279-57-9, 14464-46-1, 14808-60-7, 15468-32-3, 60676-86-0, 7631-86-9; yttrium, 7440-65-5; zirconium, 14940-68-2, 7440-67-7; Ceramics; Coated Materials, Biocompatible; Dental Implants; Dental Materials; Indicators and Reagents; Oxazines; Silicon Dioxide, 7631-86-9; Xanthenes; Yttrium, 7440-65-5; Zirconium, 7440-67-7; resazurin, 550-82-3; yttria stabilized tetragonal zirconiaReferences: Kasemo, B., Biocompatibility of titanium implants: Surface science aspects (1983) J Prosthet Dent, 49, pp. 832-837;Egusa, H., Ko, N., Shimazu, T., Yatani, H., Suspected association of an allergic reaction with titanium dental implants: A clinical report (2008) J Prosthet Dent, 100, pp. 344-347; Tschernitschek, H., Borchers, L., Geurtsen, W., Nonalloyed titanium as a bioinert metal - A review (2005) Quintessence International, 36 (7), pp. 523-530; Oliva, J., Oliva, X., Oliva, J., One-year follow-up of first consecutive 100 zirconia dental implants in human: A comparison of 2 different rough surfaces (2007) Int J Oral Maxillofac Implants, 22, pp. 430-435; Johansson, C.B., Hansson, H.A., Albrektsson, T., Qualitative interfacial study between bone and tantalum, niobium or commercially pure titanium (1990) Biomaterials, 11, pp. 277-280; De Wijs, F.L., Van Dongen, R.C., De Lange, G.L., De Putter, C., Front tooth replacement with Tubingen (Frialit) implants (1994) J Oral Rehabil, 21, pp. 11-26; Albrektsson, T., Lekholm, U., Osseointegration: Current state of the art (1989) Dent Clin North Am, 33, pp. 537-554; Albrektsson, T., Sennerby, L., State of the art in oral implants (1991) J Clin Periodontol, 18, pp. 474-481; Albrektsson, T., Sennerby, L., Wennerberg, A., State of the art of oral implants (2008) Periodontol 2000, 47, pp. 15-26; Sennerby, L., Dental implants: Matters of course and controversies (2008) Periodontol 2000, 47, pp. 9-14; Leblebicioglu, B., Rawal, S., Mariotti, A., A review of the functional and esthetic requirements for dental implants (2007) J Am Dent Assoc, 138, pp. 321-329; Chevalier, J., What future for zirconia as a biomaterial? (2006) Biomaterials, 27 (4), pp. 535-543. , DOI 10.1016/j.biomaterials.2005.07.034, PII S0142961205007039; Hochman, N., Zalkind, M., New all-ceramic indirect post-and-core system (1999) J Prosthet Dent, 81, pp. 625-629; Malmstrom, J., Slotte, C., Adolfsson, E., Norderyd, O., Thomsen, P., Bone response to free form-fabricated hydroxyapatite and zirconia scaffolds: A histological study in the human maxilla (2009) Clin Oral Implants Res, 20, pp. 379-385; Manicone, P.F., Rossi Iommetti, P., Raffaelli, L., An overview of zirconia ceramics: Basic properties and clinical applications (2007) J Dent, 35, pp. 819-826; Kim, H.-W., Kim, H.-E., Salih, V., Knowles, J.C., Dissolution control and cellular responses of calcium phosphate coatings on zirconia porous scaffold (2004) Journal of Biomedical Materials Research - Part A, 68 (3), pp. 522-530; Kim, H.W., Shin, S.Y., Kim, H.E., Lee, Y.M., Chung, C.P., Lee, H.H., Bone formation on the apatite-coated zirconia porous scaffolds within a rabbit calvarial defect (2008) J Biomater Appl, 22, pp. 485-504; Akagawa, Y., Hosokawa, R., Sato, Y., Kamayama, K., Comparison between freestanding and tooth-connected partially stabilized zirconia implants after two years' function in monkeys: A clinical and histologic study (1998) J Prosthet Dent, 80, pp. 551-558; Kohal, R.J., Att, W., Bachle, M., Butz, F., Ceramic abutments and ceramic oral implants. An update (2008) Periodontol 2000, 47, pp. 224-243; Degidi, M., Artese, L., Scarano, A., Perrotti, V., Gehrke, P., Piattelli, A., Inflammatory infiltrate, microvessel density, nitric oxide synthase expression, vascular endothelial growth factor expression, and proliferative activity in peri-implant soft tissues around titanium and zirconium oxide healing caps (2006) Journal of Periodontology, 77 (1), pp. 73-80. , DOI 10.1902/jop.2006.77.1.73; Kohal, R.J., Klaus, G., A zirconia implant-crown system: A case report (2004) International Journal of Periodontics and Restorative Dentistry, 24 (2), pp. 147-153; Sennerby, L., Dasmah, A., Larsson, B., Iverhed, M., Bone tissue responses to surface-modified zirconia implants: A histomorphometric and removal torque study in the rabbit (2005) Clin Implant Dent Relat Res, 71, pp. 13-20; Covacci, V., Bruzzese, N., Maccauro, G., Andreassi, C., Ricci, G.A., Piconi, C., Marmo, E., Cittadini, A., In vitro evaluation of the mutagenic and carcinogenic power of high purity zirconia ceramic (1999) Biomaterials, 20 (4), pp. 371-376. , DOI 10.1016/S0142-9612(98)00182-3, PII S0142961298001823; Amaral, M., Costa, M.A., Lopes, M.A., Silva, R.F., Santos, J.D., Fernandes, M.H., Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and support the osteogenic differentiation of human bone marrow cells (2002) Biomaterials, 23 (24), pp. 4897-4906. , DOI 10.1016/S0142-9612(02)00249-1, PII S0142961202002491; Garvie, R.C., Hannink, R.H., Pascoe, R.T., Ceramic steel? (1975) Nature, 258, pp. 703-704; Denry, I., Kelly, J.R., State of the art of zirconia for dental applications (2008) Dent Mater, 24, pp. 299-307; Ghosh, A., Suri, A.K., Pandey, M., Thomas, S., Rama Mohan, T.R., Rao, B.T., Nanocrystalline zirconia-yttria system-a Raman study (2006) Materials Letters, 60 (9-10), pp. 1170-1173. , DOI 10.1016/j.matlet.2005.10.102, PII S0167577X05010888; Li, M., Feng, Z., Xiong, G., Ying, P., Xin, Q., Li, C., Phase transformation in the surface region of zirconia detected by UV Raman spectroscopy (2001) J Phys Chem B, 105, pp. 8107-8111; Lughi, V., Clarke, D.R., Temperature dependence of the yttria-stabilized zirconia Raman spectrum (2007) J Appl Phys, 101; Argyriou, D.N., Howard, C.J., Re-investigation of yttria-tetragonal zirconia polycrystal (Y-TZP) by neutron powder diffraction - A cautionary tale (1995) J Appl Crystallogr, 28, pp. 206-208; Pascual, C., Duran, P., Subsolidus phase equilibria and ordering in the system ZrO 2-Y 2O 3 (1983) J Am Ceram Soc, 66, p. 23; Kelly, J.R., Denry, I., Stabilized zirconia as a structural ceramic: An overview (2008) Dent Mater, 24, pp. 289-298; Lughi, V., Sergo, V., Low temperature degradation aging of zirconia: A critical review of the relevant aspects in dentistry (2010) Dent Mater, 26, pp. 807-820; Chevalier, J., De Aza, A.H., Fantozzi, G., Schehl, M., Torrecillas, R., Extending the lifetime of ceramic orthopaedic implants (2000) Advanced Materials, 12 (21), pp. 1619-1621. , DOI 10.1002/1521-4095(200011)12:21<1619::AID-ADMA1619>3.0.CO;2-O; Kim, H.W., Kong, Y.M., Bae, C.J., Noh, Y.J., Kim, H.E., Sol-gel derived fluoro-hydroxyapatite biocoatings on zirconia substrate (2004) Biomaterials, 25, pp. 2919-2926; Lee, E.-J., Lee, S.-H., Kim, H.-W., Kong, Y.-M., Kim, H.-E., Fluoridated apatite coatings on titanium obtained by electron-beam deposition (2005) Biomaterials, 26 (18), pp. 3843-3851. , DOI 10.1016/j.biomaterials.2004.10.019, PII S0142961204009391; Vorobyev, A.Y., Guo, C., Femtosecond laser structuring of titanium implants (2007) Applied Surface Science, 253 (17), pp. 7272-7280. , DOI 10.1016/j.apsusc.2007.03.006, PII S0169433207004400; Perrie, W., Rushton, A., Gill, M., Fox, P., O'Neill, W., Femtosecond laser micro-structuring of alumina ceramic (2005) Applied Surface Science, 248 (1-4), pp. 213-217. , DOI 10.1016/j.apsusc.2005.03.005, PII S0169433205003806, 4th International Conference on Photo-Excited Processes and Applications 4-ICEPA; Teixeira, S., Monteiro, F.J., Ferraz, M.P., Vilar, R., Eugenio, S., Laser surface treatment of hydroxyapatite for enhanced tissue integration: Surface characterization and osteoblastic interaction studies (2007) Journal of Biomedical Materials Research - Part A, 81 (4), pp. 920-929. , DOI 10.1002/jbm.a.31073; Nayab, S.N., Jones, F.H., Olsen, I., Effects of calcium ion implantation on human bone cell interaction with titanium (2005) Biomaterials, 26 (23), pp. 4717-4727. , DOI 10.1016/j.biomaterials.2004.11.044, PII S0142961204010488; Kosmac, T., Oblak, C., Jevnikar, P., Funduk, N., Marion, L., The effect of surface grinding and sandblasting on flexural strength and reliability of Y-TZP zirconia ceramic (1999) Dental Materials, 15 (6), pp. 426-433. , PII S0109564199000706; Filiaggi, M.J., Pilliar, R.M., Abdulla, D., Evaluating sol-gel ceramic thin films for metal implant applications. II. Adhesion and fatigue properties of zirconia films on Ti-6Al-4V (1996) Journal of Biomedical Materials Research, 33 (4), pp. 239-256. , DOI 10.1002/(SICI)1097-4636(199624)33:4<239::AID-JBM4>3.0.CO;2-Q; Sollazzo, V., Pezzetti, F., Scarano, A., Piattelli, A., Bignozzi, C.A., Massari, L., Zirconium oxide coating improves implant osseointegration in vivo (2008) Dent Mater, 24, pp. 357-361; Sollazzo, V., Palmieri, A., Pezzetti, F., Bignozzi, C.A., Argazzi, R., Massari, L., Genetic effect of zirconium oxide coating on osteoblast-like cells (2008) J Biomed Mater Res B: Appl Biomater, 84, pp. 550-558; Kim, H.-W., Georgiou, G., Knowles, J.C., Koh, Y.-H., Kim, H.-E., Calcium phosphates and glass composite coatings on zirconia for enhanced biocompatibility (2004) Biomaterials, 25 (18), pp. 4203-4213. , DOI 10.1016/j.biomaterials.2003.10.094, PII S0142961203010470; Thian, E.S., Huang, J., Best, S.M., Barber, Z.H., Brooks, R.A., Rushton, N., Bonfield, W., The response of osteoblasts to nanocrystalline silicon-substituted hydroxyapatite thin films (2006) Biomaterials, 27 (13), pp. 2692-2698. , DOI 10.1016/j.biomaterials.2005.12.019, PII S0142961205011816; Klein, L., Sol-gel processing of silicates (1985) Annu Rev Mater Sci, 15, pp. 227-248; McDonagh, C., Sheridan, F., Butler, T., MacCraith, B.D., Characterisation of sol-gel-derived silica films (1996) Journal of Non-Crystalline Solids, 194 (1-2), pp. 72-77; Hench, L.L., Sol-gel materials for bioceramic applications (1997) Current Opinion in Solid State and Materials Science, 2 (5), pp. 604-610. , PII S1359028697800538; Garcia, C., Cere, S., Duran, A., Bioactive coatings prepared by sol-gel on stainless steel 316L (2004) J Non-Cryst Solids, 348, pp. 218-224; Garcia, C., Galliano, P., Cere, S., Electrochemical evaluation of resistance to localised corrosion of vitreous coatings containing particles applied on metallic substrates for biomedical applications (2003) Mater Lett, 57, pp. 1810-1814; Xia, Y., Whitesides, G.M., Soft lithography (1998) Angew Chem Int Ed, 37, pp. 550-575; Kim, E.J., Boehm, C.A., Mata, A., Fleischman, A.J., Muschler, G.F., Roy, S., Post microtextures accelerate cell proliferation and osteogenesis (2010) Acta Biomater, 6, pp. 160-169; Turner, A.M.P., Dowell, N., Turner, S.W.P., Kam, L., Isaacson, M., Turner, J.N., Craighead, H.G., Shain, W., Attachment of astroglial cells to microfabricated pillar arrays of different geometries (2000) Journal of Biomedical Materials Research, 51 (3), pp. 430-441. , DOI 10.1002/1097-4636(20000905)51:3<430::AID-JBM18>3.0.CO;2-C; Brunette, D.M., In vitro models of biological responses to implants (1999) Adv Dent Res, 13, p. 35; Chen, C.S., Mrksich, M., Huang, S., Whitesides, G.M., Ingber, D.E., Geometric control of cell life and death (1997) Science, 276 (5317), pp. 1425-1428. , DOI 10.1126/science.276.5317.1425; Flemming, R.G., Murphy, C.J., Abrams, G.A., Goodman, S.L., Nealey, P.F., Effects of synthetic micro- and nano-structured surfaces on cell behavior (1999) Biomaterials, 20 (6), pp. 573-588. , DOI 10.1016/S0142-9612(98)00209-9, PII S0142961298002099; Walboomers, X.F., Jansen, J.A., Cell and tissue behavior on micro-grooved surfaces (2001) Odontology, 89, pp. 2-11; Wilkinson, C.D.W., Riehle, M., Wood, M., Gallagher, J., Curtis, A.S.G., The use of materials patterned on a nano- and micro-metric scale in cellular engineering (2002) Materials Science and Engineering C, 19 (1-2), pp. 263-269. , DOI 10.1016/S0928-4931(01)00396-4, PII S0928493101003964, Current trends in Nanotechnologies: From Materials to Systems; Bettinger, C.J., Langer, R., Borenstein, J.T., Engineering substrate topography at the micro- and nanoscale to control cell function (2009) Angew Chem Int Ed, 48, pp. 5406-5415; Pelaez-Vargas, A., Ferrell, N., Fernandes, M.H., Hansford, D., Monteiro, F.J., Cells spreading on micro-fabricated silica thin film coatings (2009) Microsc Microanal, 15, pp. 77-78; Pelaez-Vargas, A., Ferrell, N., Fernandes, M.H., Hansford, D.J., Monteiro, F.J., Cellular alignment induction during early in vitro culture stages using micropatterned glass coatings produced by sol-gel process (2009) Key Eng Mater, 396-398, p. 303; Singhvi, R., Stephanopoulos, G., Wang, D.I., Effects of substratum morphology on cell physiology (1994) Biotechnol Bioeng, 43, pp. 764-771; Von Recum, A.F., Van Kooten, T.G., The influence of micro-topography on cellular response and the implications for silicone implants (1995) J Biomater Sci Polym Ed, 7, pp. 181-198; Pelaez-Vargas, A., Gallego-Perez, D., Ferrell, N., Fernandes, M.H., Hansford, D., Monteiro, F.J., Early spreading and propagation of human bone marrow stem cells on isotropic and anisotropic topographies of silica thin films produced via microstamping (2010) Microsc Microanal, 16, pp. 670-676; Brett, P.M., Harle, J., Salih, V., Mihoc, R., Olsen, I., Jones, F.H., Tonetti, M., Roughness response genes in osteoblasts (2004) Bone, 35 (1), pp. 124-133. , DOI 10.1016/j.bone.2004.03.009, PII S8756328204001140; Klinge, B., Hultin, M., Berglundh, T., Peri-implantitis (2005) Dental Clinics of North America, 49 (3 SPEC. ISS.), pp. 661-676. , DOI 10.1016/j.cden.2005.03.007, PII S0011853205000236; Leonhardt, A., Renvert, S., Dahlen, G., Microbial findings at failing implants (1999) Clin Oral Implants Res, 10, pp. 339-345; Zinelis, S., Thomas, A., Syres, K., Silikas, N., Eliades, G., Surface characterization of zirconia dental implants (2010) Dent Mater, 26, pp. 295-305; Marzolin, C., Smith, S.P., Prentiss, M., Whitesides, G.M., Fabrication of glass microstructures by micro-molding of sol-gel precursors (1998) Advanced Materials, 10 (8), pp. 571-574; Santucci, S., Di Nardo, S., Lozzi, L., Passacantando, M., Picozzi, P., XPS analysis on SiO 2 sol-gel thin films (1995) J Electron Spectrosc Relat Phenom, 76, pp. 623-628; Braet, F., De Zanger, R., Wisse, E., Drying cells for SEM, AFM and TEM by hexamethyldisilazane: A study on hepatic endothelial cells (1997) Journal of Microscopy, 186 (1), pp. 84-87
Keywords: Adhesion; article; Biological behavior; biomaterial; biomedical and dental materials; cell adhesion; Cell culture; Cell Line; cell proliferation; Cell response; cell survival; Ceramic implants; ceramics; chemistry; Coated Materials, Biocompatible; Coatings; confocal microscopy; crystallography; Dental implant materials; Dental implantology; Dental Implants; Dental Materials; Dental prostheses; diagnostic agent; dyes, reagents, indicators, markers and buffers; Gels; Gold standards; Growth kinetics; Guided tissue regeneration; Guided Tissue Regeneration, Periodontal; heat; Hot Temperature; human; Human osteoblast-like cells; Humans; In-vitro; Indicators and Reagents; Lithography; materials testing; Micropatterned; Microscopy, Confocal; Microscopy, Electron, Scanning; osteoblast; Osteoblast-like cells; Osteoblastic cell adhesion; Osteoblasts; oxazine derivative; Oxazines; Peri-implantitis; Periodontal tissue; periodontics; phase transition; physiology; Raman spectrometry; resazurin; Scanning electron microscopy; Silica; Silica coatings; Silica film; Silica surface; silicon dioxide; Soft lithography; Sol-gel; Sol-gel chemistry; Sol-gel process; Sol-gel technology; Sol-gels; Sols; Spectrum Analysis, Raman; Stabilized zirconia; Statistical analysis; Surface modification techniques; Surface morphology; Surface Properties; surface property; Surface-modified; Surfaces; time; Time Factors; Tissue; Tissue growth; Titanium; Titanium implants; tooth implantation; Top surface; X ray diffraction; X-Ray Diffraction; xanthene derivative; Xanthenes; yttria stabilized tetragonal zirconia; Yttria stabilized zirconia; yttrium; Yttrium alloys; Zirconia; Zirconia materials; zirconium

Knowledge of adverse neonatal outcome alters clinicians' interpretation of the intrapartum cardiotocograph - Ayres-de-Campos, D.; Arteiro, D.; Costa-Santos, C.; Bernardes, J. (BJOG: An International Journal of Obstetrics and GynaecologyBJOG Int. J. Obstet. Gynaecol., 2011)
Objective: To evaluate the impact of knowledge of neonatal outcome on clinicians' interpretation of the intrapartum cardiotocograph (CTG). Design: Prospective evaluation of pre-recorded cases. Setting: Five maternity hospitals. Population: From a database of intrapartum CTGs acquired with a scalp electrode in singleton near-term fetuses, 20 tracings were sequentially selected from cases with newborn umbilical artery pH < 7.05 and 20 from cases with pH > 7.20. Methods: Five experienced obstetricians practising in different maternity hospitals were asked to analyse the 40 tracings individually, according to the International Federation of Gynaecology and Obstetrics guidelines. In a first round, clinicians were given no information on neonatal outcome. In a second round, carried out 2 months later, clinicians were asked to analyse the same tracings, but the order was randomly altered and information on the newborn's arterial pH was provided. Clinicians were not informed of the purpose of the study or whether the tracings were the same. Main outcome measures: The incidence of individual fetal heart rate feature identification and tracing classification, before and after neonatal outcome was made available. Results: In the group with pH < 7.05, repetitive decelerations and reduced variability were more common in the second round (P < 0.001 and P = 0.001, respectively), as was a pathological classification (P = 0.002); variable decelerations were less common (P = 0.008). In the group with normal pH, less tracings in the second round had prolonged decelerations (P = 0.013) and no accelerations (P = 0.013), but more had pronounced decelerations (P = 0.031) and reduced variability (P = 0.007); there was a reduction in pathological classifications, but this difference failed to reach statistical significance (P = 0.051). Conclusions: A knowledge of adverse neonatal outcome leads to a more severe classification of the intrapartum CTG, which derives mainly from the evaluation of decelerations and variability. © 2011 The Authors BJOG An International Journal of Obstetrics and Gynaecology © 2011 RCOG.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: BIOGFdoi: 10.1111/j.1471-0528.2011.03003.xPubMed ID: 21609381Language of Original Document: EnglishCorrespondence Address: Ayres-de-Campos, D.; Departmento de Ginecologia e Obstetrícia, Faculdade de Medicina do Porto, 4200-309 Porto, Portugal; email: dcampos@med.up.ptReferences: (2006) Perinatal Mortality Surveillance 2004: England, Wales and Northern Ireland, , CEMACH - Centre for Maternal and Child Enquiries (previously Confidential Enquiries into Maternal and Child Health). London: CEMACH;(1997) CESDI - Confidential Enquiry into Stillbirths and Deaths in Infancy, , 4th Annual Report. London: CESDI; Wood, C., Renou, P., Oats, J., A controlled trial of fetal heart rate monitoring in a low-risk obstetric population (1981) American Journal of Obstetrics and Gynecology, 141 (5), pp. 527-534; MacDonald, D., Grant, A., Sheridan-Pereira, M., The Dublin randomized controlled trial of intrapartum fetal heart rate monitoring (1985) American Journal of Obstetrics and Gynecology, 152 (5), pp. 524-539; Shy, K.K., Luthy, D.A., Bennett, F.C., Whitfield, M., Larson, E.B., Van Belle, G., Hughes, J.P., Stenchever, M.A., Effects of electronic fetal-heart-rate monitoring, as compared with periodic auscultation, on the neurologic development of premature infants (1990) New England Journal of Medicine, 322 (9), pp. 588-593; Dillner, L., Babies' deaths linked to suboptimal care (1995) Br Med J, 310, p. 757; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310; Palomaki, O., Luukkaala, T., Luoto, R., Tuimala, R., Intrapartum cardiotocography - The dilemma of interpretational variation (2006) Journal of Perinatal Medicine, 34 (4), pp. 298-302. , DOI 10.1515/JPM.2006.057, PII JPME344298; Westerhuis, M., Van Horen, E., Kwee, A., Van Der Tweel, I., Visser, G., Moons, K., Inter- and intra-observer agreement of intrapartum ST analysis of the fetal electrocardiogram in women monitored by STAN (2009) BJOG, 116, pp. 545-551; Caplan, R.A., Posner, K.L., Cheney, F.W., Effect of outcome on physician judgment of appropriateness of care (1991) J Am Med Assoc, 265, pp. 1957-1960; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring (1987) Int J Gynecol Obstet, 25, pp. 159-167. , FIGO News; Amer-Wahlin, I., Hellsten, C., Noren, H., Hagberg, H., Herbst, A., Kjellmer, I., Lilja, H., Marsal, K., Cardiotocography only versus cardiotocography plus ST analysis of fetal electrocardiogram for intrapartum fetal monitoring: A Swedish randomised controlled trial (2001) Lancet, 358 (9281), pp. 534-538. , DOI 10.1016/S0140-6736(01)05703-8; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: A time for quality data (1994) British Journal of Obstetrics and Gynaecology, 101 (12), pp. 1054-1063; Figueras, F., Albela, S., Bonino, S., Palacio, M., Barrau, E., Hernandez, S., Casellas, C., Cararach, V., Visual analysis of antepartum fetal heart rate tracings: Inter- and intra-observer agreement and impact of knowledge of neonatal outcome (2005) Journal of Perinatal Medicine, 33 (3), pp. 241-245. , http://www.extenza-eps.com/extenza/loadPDF?objectIDValue=64432, DOI 10.1515/JPM.2005.044; Zain, H.A., Wright, J.W., Parrish, G.E., Diehl, S.J., Interpreting the fetal heart rate tracing: Effect of knowledge of neonatal outcome (1998) Journal of Reproductive Medicine for the Obstetrician and Gynecologist, 43 (4), pp. 367-370; Almström, H., Axelsson, O., Ekman, G., Ingemarsson, I., Maesel, A., Arström, K., Umbilical artery velocimetry may influence clinical interpretation of intrapartum cardiotocograms (1995) Acta Obstet Gynecol Scand, 74, pp. 526-529; Spencer, J.A.D., Clinical overview of cardiotocography (1993) British Journal of Obstetrics and Gynaecology, Supplement, 100 (9), pp. 4-7; Ayres-de-Campos, D., Bernardes, J., Early, variable and late decelerations: Can a consensus be reached in their identification? (1999) Int J Gynecol Obstet, 65, pp. 305-306; Capstick, J.B., Edwards, P.J., Trends in obstetric malpractice claims (1990) Lancet, 336 (8720), pp. 931-932. , DOI 10.1016/0140-6736(90)92291-O; Symonds, E.M., Litigation and the cardiotocogram (1993) British Journal of Obstetrics and Gynaecology, Supplement, 100 (9), pp. 8-9; Williams, B., Arulkumaran, S., Cardiotocography and medicolegal issues (2004) Best Practice and Research: Clinical Obstetrics and Gynaecology, 18 (3), pp. 457-466. , DOI 10.1016/j.bpobgyn.2004.02.005, PII S1521693404000318
Keywords: adverse outcome; Agreement; article; bradycardia; Cardiotocography; clinical competence; Female; Fetal; Fetal hypoxia; Fetal monitoring; fetus heart rate; fetus outcome; health practitioner; Heart rate; Heart Rate, Fetal; human; Humans; Hydrogen-Ion Concentration; incidence; Infant, Newborn; intrapartum care; Labor, Obstetric; medical practice; pH; practice guideline; Practice Guidelines as Topic; Pregnancy; Pregnancy Outcome; priority journal; Prospective Studies; Questionnaires; Reference Standards; Reproducibility of Results; Research Design; Risk Factors; Sweden; tachycardia; umbilical artery

The limits of agreement and the intraclass correlation coefficient may be inconsistent in the interpretation of agreement - Costa-Santos, C.; Bernardes, J.; Ayres-de-Campos, D.; Costa, A.; Costa, C. (Journal of Clinical EpidemiologyJ. Clin. Epidemiol., 2011)
Objective: To compare the interpretation of agreement in the prediction of neonatal outcome variables, using the limits of agreement (LA) and the intraclass correlation coefficient (ICC). Study Design and Setting: Three obstetricians were asked to predict neonatal outcomes independently based on the evaluation of intrapartum cardiotocographic tracings. Interobserver agreement was assessed with the LA and the ICC, and the results obtained were interpreted by six clinicians and six statisticians on a scale that established agreement as very poor, poor, fair, good, or very good. Results: Interpretation of the LA results was less consensual than the ICC results, with proportions of agreement of 0.36 (95% confidence interval [CI]: 0.28-0.44) vs. 0.63 (95% CI: 0.54-0.73), respectively. LA results suggested a fair to good agreement among obstetricians, whereas interpretation of ICC results suggested a poor to fair agreement. LA results were more plausible with reality, suggesting that obstetricians predicted neonatal outcomes better than randomly generated values, whereas it was not always the case with the ICC. Conclusions: LA and ICC can provide inconsistent results in agreement studies. Accordingly, in the absence of better strategies to assess agreement, both should be used for this purpose, but their results need to be interpreted with caution keeping their respective limitations in mind. © 2011 Elsevier Inc. All rights reserved.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JCEPEdoi: 10.1016/j.jclinepi.2009.11.010PubMed ID: 20189765Language of Original Document: EnglishCorrespondence Address: Costa-Santos, C.; Biostatistics and Medical Informatics Department, Faculty of Medicine, University of Porto, Al. Prof. Hernâni Monteiro, 4200-319 Porto, Portugal; email: csantos@med.up.ptReferences: De Vet, H., Observer reliability and agreement (1999) Encyclopedia of Biostatistics, pp. 3123-3127;Ayres-De-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in expert's classification of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310; Santos, C.C., Pereira, C.A., Bernardes, J., Agreement studies in obstetrics and gynaecology: Inappropriateness, controversies and consequences (2005) Br J Obstet Gynaecol, 112, pp. 667-669; Luiz, R.R., Szklo, M., More than one statistical strategy to assess agreement of quantitative measurements may usefully be reported (2003) J Clin Epidemiol, 56, pp. 963-967; Bland, J.M., Altman, D.G., Statistical methods for assessing two methods of clinical measurement (1986) Lancet, 1, pp. 307-310; Bartko, J.J., The intraclass correlation coefficient as a measure of reliability (1966) Psychol Rep, 19, pp. 3-11; Muller, R., Buttner, P., A critical discussion of intraclass correlation coefficients (1994) Stat Med, 13, pp. 2465-2476; Burdock, E., Fleiss, J.L., Hardesty, A.S., A new view of interobserver agreement (1963) Person Psychol, 16, pp. 373-384; Casey, B.M., McLntire, D.D., Leveno, K.J., The continuing value of the Apgar score for the assessment of newborn infants (2001) N Engl J Med, 344, pp. 467-471; Van De Riet, J.E., Vandenbussche, F.P., Le Cessie, S., Keirse, M.J., Newborn assessment and long-term adverse outcome: A systematic review (1999) Am J Obstet Gynecol, 180, pp. 1024-1029; Shrout, P.E., Fleiss, J.L., Intraclass correlations: Uses in assessing rater reliability (1979) Psychol Bull, 86, pp. 420-427; Fleiss, J.U., Davies, M., Measuring nominal scale agreement among many raters (1971) Psychol Bull, 76, pp. 378-382; Carpenter, J., Bithell, J., Bootstrap confidence intervals: When, which, what? A practical guide for medical statisticians (2000) Stat Med, 19, pp. 1141-1164; Landis, J.R., Koch, G.G., The measurement of observer agreement for categorical data (1977) Biometrics, 33, pp. 159-174
Keywords: Agreement; Apgar score; Cardiotocography; correlation coefficient; Female; Fetal Blood; human; Humans; Hydrogen-Ion Concentration; Infant, Newborn; intrapartum care; limit of agreement; newborn assessment; normal human; observer variation; Obstetrics; outcome variable; Pregnancy; Pregnancy Outcome; priority journal; reproducibility; Reproducibility of Results; review; statistical data interpretation; statistical parameters; Umbilical Arteries; Umbilical artery blood pH; umbilical cord blood

Molecularly designed alginate hydrogels susceptible to local proteolysis as three-dimensional cellular microenvironments - Fonseca, K.B.; Bidarra, S.J.; Oliveira, M.J.; Granja, P.L.; Barrias, C.C. (Acta BiomaterialiaActa Biomater., 2011)
The development of sophisticated three-dimensional (3-D) cell culture microenvironments that recreate some of the complexity of the natural extracellular matrix (ECM) remains a challenging task. Here, the modification of alginate through partial crosslinking with a matrix metalloproteinase (MMP) cleavable peptide (proline-valine-glycine-leucine-isoleucine-glycine, PVGLIG) is described, and its use in the preparation of injectable, in situ crosslinkable hydrogel-like matrices is proposed. PVGLIG-grafted alginates were synthesized by carbodiimide chemistry and characterized. Their biological performance was evaluated by comparing the response of 3-D cultured mesenchymal stem cells (MSCs) to alginate hydrogels containing only cell-adhesion peptides (RGD-alginate) or both peptides (PVGLIG/RGD-alginate). After 1 week, cells remained essentially round within RGD-alginate, while they exhibited an elongated morphology within PVGLIG/RGD-alginate hydrogels, forming cellular networks. This suggests that cells were able to structurally reorganize the matrix, through enzymatic hydrolysis of PVGLIG residues, overcoming biophysical hydrogel resistance. As shown by gelatine-zymography, MSC presented higher activity of MMP-2 when cultured within alginate functionalized with MMP-sensitive peptide, suggesting that the cell's proteolytic phenotype was modulated by the matrix composition. Additionally, PVGLIG/RGD-alginate hydrogels were clearly degraded in cell culture. Taken together, the results demonstrate that the co-incorporation of MMP-labile peptides in cell-adhesive RGD-alginate hydrogels improved their performance as ECM analogues, providing a more dynamic and physiological 3-D cellular microenvironment. © 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2010.12.029PubMed ID: 21193068Language of Original Document: EnglishCorrespondence Address: Barrias, C. C.; INEB, Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade Do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: ccbarrias@ineb.up.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; gelatin, 9000-70-8; gelatinase A, 146480-35-5; Alginates; Glucuronic Acid, 576-37-4; Hexuronic Acids; Hydrogels; Matrix Metalloproteinases, 3.4.24.-; Peptides; alginic acid, 9005-32-7References: Lukashev, M.E., Werb, Z., ECM signalling: Orchestrating cell behaviour and misbehaviour (1998) Trends in Cell Biology, 8 (11), pp. 437-441. , DOI 10.1016/S0962-8924(98)01362-2, PII S0962892498013622;Bosman, F.T., Stamenkovic, I., Functional structure and composition of the extracellular matrix (2003) Journal of Pathology, 200 (4), pp. 423-428. , DOI 10.1002/path.1437; Lutolf, M.P., Hubbell, J.A., Synthetic biomaterials as instructive extracellular microenvironments for morphogenesis in tissue engineering (2005) Nature Biotechnology, 23 (1), pp. 47-55. , DOI 10.1038/nbt1055; Lutolf, M.P., Gilbert, P.M., Blau, H.M., Designing materials to direct stem-cell fate (2009) Nature, 462 (7272), pp. 433-441; Tibbitt, M.W., Anseth, K.S., Hydrogels as extracellular matrix mimics for 3D cell culture (2009) Biotechnol Bioeng, 103 (4), pp. 655-663; Augst, A.D., Kong, H.J., Mooney, D.J., Alginate hydrogels as biomaterials (2006) Macromolecular Bioscience, 6 (8), pp. 623-633. , DOI 10.1002/mabi.200600069; Evangelista, M.B., Hsiong, S.X., Fernandes, R., Sampaio, P., Kong, H.-J., Barrias, C.C., Salema, R., Granja, P.L., Upregulation of bone cell differentiation through immobilization within a synthetic extracellular matrix (2007) Biomaterials, 28 (25), pp. 3644-3655. , DOI 10.1016/j.biomaterials.2007.04.028, PII S014296120700347X; Grellier, M., Granja, P.L., Fricain, J.C., Bidarra, S.J., Renard, M., Bareille, R., The effect of the co-immobilization of human osteoprogenitors and endothelial cells within alginate microspheres on mineralization in a bone defect (2009) Biomaterials, 30 (19), pp. 3271-3278; Bidarra, S.J., Barrias, C.C., Barbosa, M.A., Soares, R., Granja, P.L., Immobilization of human mesenchymal stem cells within RGD-grafted alginate microspheres and assessment of their angiogenic potential (2010) Biomacromolecules, 11 (8), pp. 1956-1964; West, J.L., Hubbell, J.A., Polymeric biomaterials with degradation sites for proteases involved in cell migration (1999) Macromolecules, 32 (1), pp. 241-244; Page-Mccaw, A., Ewald, A.J., Werb, Z., Matrix metalloproteinases and the regulation of tissue remodelling (2007) Nat Rev Mol Cell Biol, 8 (3), pp. 221-233; Murphy, G., Nagase, H., Progress in matrix metalloproteinase research (2008) Mol Aspects Med, 29 (5), pp. 290-308; Chau, Y., Luo, Y., Cheung, A.C.Y., Nagai, Y., Zhang, S., Kobler, J.B., Incorporation of a matrix metalloproteinase-sensitive substrate into self-assembling peptides - A model for biofunctional scaffolds (2008) Biomaterials, 29 (11), pp. 1713-1719; Chau, Y., Tan, F.E., Langer, R., Synthesis and characterization of dextran-peptide-methotrexate conjugates for tumor targeting via mediation by matrix metalloproteinase II and matrix metalloproteinase IX (2004) Bioconjugate Chemistry, 15 (4), pp. 931-941. , DOI 10.1021/bc0499174; Turk, B.E., Huang, L.L., Piro, E.T., Cantley, L.C., Determination of protease cleavage site motifs using mixture-based oriented peptide libraries (2001) Nature Biotechnology, 19 (7), pp. 661-667. , DOI 10.1038/90273; Kong, H.J., Smith, M.K., Mooney, D.J., Designing alginate hydrogels to maintain viability of immobilized cells (2003) Biomaterials, 24 (22), pp. 4023-4029. , DOI 10.1016/S0142-9612(03)00295-3; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20 (1), pp. 45-53. , DOI 10.1016/S0142-9612(98)00107-0, PII S0142961298001070; Lorenzen, A., Kennedy, S.W., A fluorescence-based protein assay for use with a microplate reader (1993) Analytical Biochemistry, 214 (1), pp. 346-348. , DOI 10.1006/abio.1993.1504; Kuo, C.K., Ma, P.X., Ionically crosslinked alginate hydrogels as scaffolds for tissue engineering: Part 1. Structure, gelation rate and mechanical properties (2001) Biomaterials, 22 (6), pp. 511-521. , DOI 10.1016/S0142-9612(00)00201-5, PII S0142961200002015; Oliveira, S.M., Barrias, C.C., Almeida, I.F., Costa, P.C., Pena Ferreira, M.R., Bahia, M.F., Injectability of a bone filler system based on hydroxyapatite microspheres and a vehicle with in situ gel-forming ability (2008) J Biomed Mater Res B Appl Biomater, 87 (1), pp. 49-58; Kavimandan, N.J., Losi, E., Wilson, J.J., Brodbelt, J.S., Peppas, N.A., Synthesis and characterization of insulin-transferrin conjugates (2006) Bioconjugate Chemistry, 17 (6), pp. 1376-1384. , DOI 10.1021/bc050344k; Lee, K.Y., Rowley, J.A., Eiselt, P., Moy, E.M., Bouhadir, K.H., Mooney, D.J., Controlling mechanical and swelling properties of alginate hydrogels independently by cross-linker type and cross-linking density (2000) Macromolecules, 33 (11), pp. 4291-4294; Dent, A., Aslam, M., The functional chemistry of proteins and protein coupling (1998) Bioconjugation: Protein Coupling Techniques for the Biomedical Sciences, pp. 50-100; Werb, Z., ECM and cell surface proteolysis: Regulating cellular ecology (1997) Cell, 91 (4), pp. 439-442; Friedl, P., Brocker, E.-B., The biology of cell locomotion within three-dimensional extracellular matrix (2000) Cellular and Molecular Life Sciences, 57 (1), pp. 41-64. , DOI 10.1007/s000180050498; Drury, J.L., Boontheeku, T., Mooney, D.J., Cellular cross-linking of peptide modified hydrogels (2005) Journal of Biomechanical Engineering, 127 (2), pp. 220-228. , DOI 10.1115/1.1865194; Boontheekul, T., Kong, H.-J., Mooney, D.J., Controlling alginate gel degradation utilizing partial oxidation and bimodal molecular weight distribution (2005) Biomaterials, 26 (15), pp. 2455-2465. , DOI 10.1016/j.biomaterials.2004.06.044, PII S0142961204006064; Ries, C., Egea, V., Karow, M., Kolb, H., Jochum, M., Neth, P., MMP-2, MT1-MMP, and TIMP-2 are essential for the invasive capacity of human mesenchymal stem cells: Differential regulation by inflammatory cytokines (2007) Blood, 109 (9), pp. 4055-4063. , http://bloodjournal.hematologylibrary.org/cgi/reprint/109/9/4055, DOI 10.1182/blood-2006-10-051060; Seiki, M., The cell surface: The stage for matrix metalloproteinase regulation of migration (2002) Current Opinion in Cell Biology, 14 (5), pp. 624-632. , DOI 10.1016/S0955-0674(02)00363-0; Will, H., Atkinson, S.J., Butler, G.S., Smith, B., Murphy, G., The soluble catalytic domain of membrane type 1 matrix metalloproteinase cleaves the propeptide of progelatinase A and initiates autoproteolytic activation. Regulation by TIMP-2 and TIMP-3 (1996) Journal of Biological Chemistry, 271 (29), pp. 17119-17123. , DOI 10.1074/jbc.271.29.17119; Itoh, Y., Seiki, M., MT1-MMP: A potent modifier of pericellular microenvironment (2006) Journal of Cellular Physiology, 206 (1), pp. 1-8. , DOI 10.1002/jcp.20431; Barbolina, M.V., Adley, B.P., Ariztia, E.V., Liu, Y., Stack, M.S., Microenvironmental regulation of membrane type 1 matrix metalloproteinase activity in ovarian carcinoma cells via collagen-induced EGR1 expression (2007) Journal of Biological Chemistry, 282 (7), pp. 4924-4931. , http://www.jbc.org/cgi/reprint/282/7/4924, DOI 10.1074/jbc.M608428200
Keywords: 3-D Cell culture; Alginate; Alginates; alginic acid; Amino Acid Sequence; article; cell adhesion; cell composition; Cell Count; Cell culture; Cell Culture Techniques; Cell Shape; cell structure; cell survival; cell viability; Cells, Cultured; controlled study; Enzyme Activation; enzyme activity; extracellular matrix; Extracellular matrix (ECM); gelatin; gelatinase A; Glucuronic Acid; Hexuronic Acids; human; human cell; Humans; hydrogel; Hydrogels; hydrolysis; matrix metalloproteinase; Matrix Metalloproteinases; Matrix metalloproteinases (MMPs); Mesenchymal stem cell; Mesenchymal Stem Cells; Molecular Sequence Data; morphology; peptide derivative; Peptides; phenotype; priority journal; prolylvalylglycylleucylisoleucylglycine; Protease-sensitive; protein cleavage; protein degradation; Protein Processing, Post-Translational; Subcellular Fractions; tumor microenvironment; unclassified drug; zymography

Non-viral gene delivery to mesenchymal stem cells: Methods, strategies and application in bone tissue engineering and regeneration - Santos, J.L.; Pandita, D.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (Current Gene TherapyCurr. Gene Ther., 2011)
Mesenchymal stem cells (MSCs) can be isolated from several tissues in the body, have the ability to selfrenewal, show immune suppressive properties and are multipotent, being able to generate various cell types. At present, due to their intrinsic characteristics, MSCs are considered very promising in the area of tissue engineering and regenerative medicine. In this context, genetic modification can be a powerful tool to control the behavior and fate of these cells and be used in the design of new cellular therapies. Viral systems are very effective in the introduction of exogenous genes inside MSCs. However, the risks associated with their use are leading to an increasing search for non-viral approaches to attain the same purpose, even if MSCs have been shown to be more difficult to transfect in this way. In the past few years, progress was made in the development of chemical and physical methods for non-viral gene delivery. Herein, an overview of the application of those methods specifically to MSCs is given and their use in tissue engineering and regenerative medicine therapeutic strategies highlighted using the example of bone tissue. Key issues and future directions in non-viral gene delivery to MSCs are also critically addressed. © 2011 Bentham Science Publishers Ltd.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: CGTUAdoi: 10.2174/156652311794520102PubMed ID: 21182464Language of Original Document: EnglishCorrespondence Address: Tomás, H.; CQM-Centro de Química da Madeira, MMRG, Universidade da Madeira, Campus Universitário da Penteada, 9000-390 Funchal, Portugal; email: lenat@uma.ptReferences: Bianco, P., Robey, P.G., Simmons, P.J., Mesenchymal stem cells: Revisitinghistory, concepts, and assays (2008) Cell Stem Cell, 2, pp. 313-319;Marot, D., Knezevic, M., Novakovic, G.V., Bone tissue engineeringwith human stem cells (2010) Stem Cell Res Ther, 1, p. 10; Caplan, A.I., Review: Mesenchymal stem cells: Cell-based reconstructivetherapy in orthopedics (2005) Tissue Eng, 11, pp. 1198-1211; Caplan, A.I., Bruder, S.P., Mesenchymal stem cells: Building blocksfor molecular medicine in the 21st century (2001) Trends Mol Med, 7, pp. 259-264; Chen, F.H., Tuan, R.S., Mesenchymal stem cells in arthritic diseases (2008) Arthritis Res Ther, 10, p. 223; Da Silva Meirelles, L., Chagastelles, P.C., Nardi, N.B., Mesenchymalstem cells reside in virtually all post-natal organs and tissues (2006) J CellSci, 119, pp. 2204-2213; Mauney, J.R., Volloch, V., Kaplan, D.L., Role of adult mesenchymalstem cells in bone tissue engineering applications: Current statusand future prospects (2005) Tissue Eng, 11, pp. 787-802; Prockop, D.J., Repair of tissues by adult stem/progenitor cells(MSCs): Controversies, myths, and changing paradigms (2009) Mol Ther, 17, pp. 939-946; Sakurada, K., McDonald, F.M., Shimada, F., Regenerative medicineand stem cell based drug discovery (2008) Angew Chem Int Ed Engl, 47, pp. 5718-5738; Väänänen, H.K., Mesenchymal stem cells (2005) Ann Med, 37, pp. 469-479; Jackson, W.M., Nesti, L.J., Tuan, R.S., Potential therapeutic applicationsof muscle-derived mesenchymal stem and progenitor cells (2010) ExpertOpin Biol Ther, 10, pp. 505-517; Nauta, A.J., Fibbe, W.E., Immunomodulatory properties of mesenchymalstromal cells (2007) Blood, 110, pp. 3499-3506; Heyde, M., Partridge, K.A., Oreffo, R.O., Gene therapy used fortissue engineering applications (2007) J Pharm Pharmacol, 59, pp. 329-350; Kimelman, N., Pelled, G., Helm, G.A., Review: Gene-and stemcell-based therapeutics for bone regeneration and repair (2007) TissueEng, 13, pp. 1135-1150; Partridge, K.A., Oreffo, R.O., Gene delivery in bone tissue engineering: Progress and prospects using viral and nonviral strategies (2004) TissueEng, 10, pp. 295-307; Pittenger, M., Vanguri, P., Simonetti, D., Adult mesenchymalstem cells: Potential for muscle and tendon regeneration and use ingene therapy (2002) J Musculoskelet Neuronal Interact, 2, pp. 309-320; Reiser, J., Zhang, X.Y., Hemenway, C.S., Potential of mesenchymalstem cells in gene therapy approaches for inherited and acquireddiseases (2005) Expert Opin Biol Ther, 5, pp. 1571-1584; Saraf, A., Mikos, A.G., Gene delivery strategies for cartilage tissueengineering (2006) Adv Drug Deliv Rev, 58, pp. 592-603; Trippel, S.B., Ghivizzani, S.C., Nixon, A.J., Gene-based approaches forthe repair of articular cartilage (2004) Gene Ther, 11, pp. 351-359; Takahashi, K., Yamanaka, S., Induction of pluripotent stem cells frommouse embryonic and adult fibroblast cultures by defined factors (2006) Cell, 126, pp. 663-676; Yu, J., Vodyanik, M.A., Smuga-Otto, K., Induced pluripotentstem cell lines derived from human somatic cells (2007) Science, 318, pp. 1917-1920; Steinert, A.F., Noth, U., Tuan, R.S., Concepts in gene therapy for cartilagerepair (2008) Injury, 39 (SUPPL 1), pp. S97-S113; Gafni, Y., Turgeman, G., Liebergal, M., Stem cells as vehiclesfor orthopedic gene therapy (2004) Gene Ther, 11, pp. 417-426; Kane, N.M., McRae, S., Denning, C., Viral and non-viral genedelivery and its role in pluripotent stem cell engineering Drug DiscovToday: Technol, , In press. doi:10.1016/j.ddtec.2008.10.002; Li, S.D., Huang, L., Non-viral is superior to viral gene delivery (2007) JControl Release, 123, pp. 181-183; Mastrobattista, E., Bravo, S.A., van der Aa, M., Nonviral genedelivery systems: From simple transfection agents to artificial viruses (2005) Drug Discov Today: Technol, 2, pp. 103-109; Chan, J., O'Donoghue, K., de la Fuente, J., Human fetal mesenchymalstem cells as vehicles for gene delivery (2005) Stem Cells, 23, pp. 93-102; Tsuda, H., Wada, T., Yamashita, T., Enhanced osteoinduction bymesenchymal stem cells transfected with a fiber-mutant adenoviralBMP2 gene (2005) J Gene Med, 7, pp. 1322-1334; Zhang, X., Godbey, W.T., Viral vectors for gene delivery in tissueengineering (2006) Adv Drug Deliv Rev, 58, pp. 515-534; Dang, J.M., Leong, K.W., Natural polymers for gene delivery and tissue engineering (2006) Adv Drug Deliv Rev, 58, pp. 487-499; Luten, J., van Nostrum, C.F., De Smedt, S.C., Biodegradablepolymers as non-viral carriers for plasmid DNA delivery (2008) J ControlRelease, 126, pp. 97-110; Mintzer, M.A., Simanek, E.E., Nonviral vectors for gene delivery (2009) Chem Rev, 109, pp. 259-302; Panyam, J., Labhasetwar, V., Biodegradable nanoparticles for drugand gene delivery to cells and tissue (2003) Adv Drug Deliv Rev, 55, pp. 329-347; Choi, J.S., Ko, K.S., Park, J.S., Dexamethasone conjugatedpoly(amidoamine) dendrimer as a gene carrier for efficient nucleartranslocation (2006) Int J Pharm, 320, pp. 171-178; Roth, C.M., Sundaram, S., Engineering synthetic vectors for improvedDNA delivery: Insights from intracellular pathways (2004) Annu RevBiomed Eng, 6, pp. 397-426; Wood, K.C., Little, S.R., Langer, R., A family of hierarchicallyself-assembling linear-dendritic hybrid polymers for highly efficienttargeted gene delivery (2005) Angew Chem Int Ed Engl, 44, pp. 6704-6708; Mehier-Humbert, S., Guy, R.H., Physical methods for gene transfer: Improving the kinetics of gene delivery into cells (2005) Adv Drug DelivRev, 57, pp. 733-753; Jo, J., Tabata, Y., Non-viral gene transfection technologies for geneticengineering of stem cells (2008) Eur J Pharm Biopharm, 68, pp. 90-104; Song, L., Chau, L., Sakamoto, Y., Electric field-induced molecularvibration for noninvasive, high-efficiency DNA transfection (2004) Mol Ther, 9, pp. 607-616; Han, S.W., Nakamura, C., Kotobuki, N., High-efficiency DNAinjection into a single human mesenchymal stem cell using ananoneedle and atomic force microscopy (2008) Nanomedicine, 4, pp. 215-225; Park, S., Kim, Y.S., Kim, W.B., Carbon nanosyringe array as aplatform for intracellular delivery (2009) Nano Lett, 9, pp. 1325-1329; Durieux, A.C., Bonnefoy, R., Busso, T., In vivo gene electrotransferinto skeletal muscle: Effects of plasmid DNA on the occurrenceand extent of muscle damage (2004) J Gene Med, 6, pp. 809-816; Winn, S.R., Hu, Y., Sfeir, C., Gene therapy approaches for modulatingbone regeneration (2000) Adv Drug Deliv Rev, 42, pp. 121-138; Lv, H., Zhang, S., Wang, B., Toxicity of cationic lipids and cationicpolymers in gene delivery (2006) J Control Release, 114, pp. 100-109; Gebhart, C.L., Kabanov, A.V., Evaluation of polyplexes as gene transferagents (2001) J Control Release, 73, pp. 401-416; Hamm, A., Krott, N., Breibach, I., Efficient transfection methodfor primary cells (2002) Tissue Eng, 8, pp. 235-245; Gill, D.R., Pringle, I.A., Hyde, S.C., Progress and prospects: The designand production of plasmid vectors (2009) Gene Ther, 16, pp. 165-171; Miller, A.M., Dean, D.A., Tissue-specific and transcription factormediatednuclear entry of DNA (2009) Adv Drug Deliv Rev, 61, pp. 603-613; Smith, D.K., Dendrimers and the double helix--from DNA bindingtowards gene therapy (2008) Curr Top Med Chem, 8, pp. 1187-1203; Duzgunes, N., De Ilarduya, C.T., Simoes, S., Cationic liposomesfor gene delivery: Novel cationic lipids and enhancement by proteinsand peptides (2003) Curr Med Chem, 10, pp. 1213-1220; Hoekstra, D., Rejman, J., Wasungu, L., Gene delivery by cationiclipids: In and out of an endosome (2007) Biochem Soc Trans, 35, pp. 68-71; Hoelters, J., Ciccarella, M., Drechsel, M., Nonviral genetic modificationmediates effective transgene expression and functionalRNA interference in human mesenchymal stem cells (2005) J Gene Med, 7, pp. 718-728; Ko, B.S., Chang, T.C., Shyue, S.K., An efficient transfectionmethod for mouse embryonic stem cells (2009) Gene Ther, 16, pp. 154-158; Park, J., Lutz, R., Felszeghy, E., The effect on bone regenerationof a liposomal vector to deliver BMP-2 gene to bone grafts in periimplantbone defects (2007) Biomaterials, 28, pp. 2772-2782; Park, J., Ries, J., Gelse, K., Bone regeneration in critical sizedefects by cell-mediated BMP-2 gene transfer: A comparison of adenoviral vectors and liposomes (2003) Gene Ther, 10, pp. 1089-1098; Vanderbyl, S., McDonald, G.N., Sidhu, S., Transfer and stabletransgene expression of a mammalian artificial chromosome intobone marrow-derived human mesenchymal stem cells (2004) Stem Cells, 22, pp. 324-333; de Jong, G., Telenius, A., Vanderbyl, S., Efficient in-vitro transferof a 60-Mb mammalian artificial chromosome into murine and hamster cells using cationic lipids and dendrimers (2001) ChromosomeRes, 9, pp. 475-485; Dass, C.R., Cytotoxicity issues pertinent to lipoplex-mediated genetherapy in-vivo (2002) J Pharm Pharmacol, 54, pp. 593-601; Wu, G.Y.W.C., Receptor-mediated in vitro gene transformation by asoluble DNA carrier system (1987) J Biol Chem, 262, pp. 4429-4432; Choi, Y.H., Liu, F., Kim, J.S., Polyethylene glycol-grafted poly-Llysineas polymeric gene carrier (1998) J Control Release, 54, pp. 39-48; Liu, G., Molas, M., Grossmann, G.A., Biological properties of poly-L-lysine-DNA complexes generated by cooperative binding of the polycation (2001) J Biol Chem, 276, pp. 34379-34387; Farrell, L.L., Pepin, J., Kucharski, C., A comparison of the effectivenessof cationic polymers poly-L-lysine (PLL) and polyethylenimine(PEI) for non-viral delivery of plasmid DNA to bone marrowstromal cells (BMSC) (2007) Eur J Pharm Biopharm, 65, pp. 388-397; Incani, V., Tunis, E., Clements, B.A., Palmitic acid substitutionon cationic polymers for effective delivery of plasmid DNA tobone marrow stromal cells (2007) J Biomed Mater Res A, 81, pp. 493-504; Clements, B.A., Incani, V., Kucharski, C., A comparative evaluationof poly-L-lysine-palmitic acid and Lipofectamine 2000 forplasmid delivery to bone marrow stromal cells (2007) Biomaterials, 28, pp. 4693-4704; Bragonzi, A., Boletta, A., Biffi, A., Comparison between cationicpolymers and lipids in mediating systemic gene delivery to thelungs (1999) Gene Ther, 6, pp. 1995-2004; Sea, F., Exgen 500 is an efficient vector for gene delivery tolung epithelial cells in vitro and in vivo (1997) Gene Ther, 4, pp. 1100-1106; Wightman, L., Kircheis, R., Rossler, V., Different behavior of branched and linear polyethylenimine for gene delivery in vitro and in vivo (2001) J Gene Med, 3, pp. 362-372; Behr, J.-P., The Proton Sponge: A Trick to Enter Cells the VirusesDid Not Exploit (1997) Chimia, 51, pp. 34-36; Dea, F., A novel non-viral vector for DNA delivery based onlow molecular weight, branched polyethylenimine: Effect of molecularweight on transfection efficiency and cytotoxicity (1999) Pharm. Res, 16, pp. 1273-1279; Godbey, W.T., Wu, K.K., Mikos, A.G., Size matters: Molecular weightaffects the efficiency of poly(ethylenimine) as a gene delivery vehicle (1999) J Biomed Mater Res, 45, pp. 268-275; Ahn, H.H., Lee, M.S., Cho, M.H., DNA/PEI nano-particles forgene delivery of rat bone marrow stem cells (2008) Colloids and SurfacesA: Physicochem Eng Aspects, 313-314, pp. 116-120; Ahn, H.H., Lee, J.H., Kim, K.S., Polyethyleneimine-mediated genedelivery into human adipose derived stem cells (2008) Biomater, 29, pp. 2415-2422; Clements, B.A., Bai, J., Kucharski, C., RGD conjugation to polyethyleneiminedoes not improve DNA delivery to bone marrowstromal cells (2006) Biomacromolecules, 7, pp. 1481-1488; Saraf, A., Hacker, M.C., Sitharaman, B., Synthesis and conformationalevaluation of a novel gene delivery vector for human mesenchymalstem cells (2008) Biomacromolecules, 9, pp. 818-827; Lei, Y., Segura, T., DNA delivery from matrix metalloproteinasedegradable poly(ethylene glycol) hydrogels to mouse cloned mesenchymalstem cells (2009) Biomaterials, 30, pp. 254-265; Gwak, S.J., Kim, B.S., Poly(lactic-co-glycolic acid) nanosphere as avehicle for gene delivery to human cord blood-derived mesenchymalstem cells: Comparison with polyethylenimine (2008) Biotechnol Lett, 30, pp. 1177-1182; Yang, F., Green, J.J., Dinio, T., Gene delivery to human adult and embryonic cell-derived stem cells using biodegradable nanoparticulatepolymeric vectors (2009) Gene Ther, 16, pp. 533-546; Huang, M., Fong, C.W., Khor, E., Transfection efficiency of chitosan vectors: Effect of polymer molecular weight and degree of deacetylation (2005) J Control Release, 106, pp. 391-406; Ishii, T., Okahata, Y., Sato, T., Mechanism of cell transfection withplasmid/chitosan complexes (2001) Biochim Biophys Acta, 1514, pp. 51-64; Moreira, C., Oliveira, H., Pires, L.R., Improving chitosanmediatedgene transfer by the introduction of intracellular bufferingmoieties into the chitosan backbone (2009) Acta Biomater, 5, pp. 2995-3006; Sato, T., Ishii, T., Okahata, Y., In vitro gene delivery mediated bychitosan. effect of pH, serum, and molecular mass of chitosan onthe transfection efficiency (2001) Biomaterials, 22, pp. 2075-2080; Corsi, K., Chellat, F., Yahia, L., Mesenchymal stem cells, MG63and HEK293 transfection using chitosan-DNA nanoparticles (2003) Biomaterials, 24, pp. 1255-1264; Nie, H., Wang, C.H., Fabrication and characterization of PLGA/HApcomposite scaffolds for delivery of BMP-2 plasmid DNA (2007) J ControlRelease, 120, pp. 111-121; Hu, Y., Cai, K., Luo, Z., Surface mediated in situ differentiationof mesenchymal stem cells on gene-functionalized titanium filmsfabricated by layer-by-layer technique (2009) Biomaterials, 30, pp. 3626-3635; Okazaki, A., Jo, J., Tabata, Y., A reverse transfection technology togenetically engineer adult stem cells (2007) Tissue Eng, 13, pp. 245-251; Hosseinkhani, H., Azzam, T., Kobayashi, H., Combination of 3Dtissue engineered scaffold and non-viral gene carrier enhance in vitroDNA expression of mesenchymal stem cells (2006) Biomaterials, 27, pp. 4269-4278; Hosseinkhani, H., Yamamoto, M., Inatsugu, Y., Enhanced ectopicbone formation using a combination of plasmid DNA impregnationinto 3-D scaffold and bioreactor perfusion culture (2006) Biomaterials, 27, pp. 1387-1398; Dufès, C., Uchegbu, I.F., Schätzlein, A.G., Dendrimers in gene delivery (2005) Adv Drug Deliv Rev, 57, pp. 2177-2202; Svenson, S., Tomalia, D.A., Dendrimers in biomedical applications--reflections on the field (2005) Adv Drug Deliv Rev, 57, pp. 2106-2129; Malik, N., Wiwattanapatapee, R., Klopsch, R., Dendrimers: Relationshipbetween structure and biocompatibility in vitro, and preliminarystudies on the biodistribution of 125I-labelled polyamidoaminedendrimers in vivo (2000) J Control Release, 65, pp. 133-148; Duncan, R., Izzo, L., Dendrimer biocompatibility and toxicity (2005) AdvDrug Deliv Rev, 57, pp. 2215-2237; Dennig, J., Duncan, E., Gene transfer into eukaryotic cells usingactivated polyamidoamine dendrimers (2002) J Biotechnol, 90, pp. 339-347; Sokolova, V.V., Radtke, I., Heumann, R., Effective transfection of cells with multi-shell calcium phosphate-DNA nanoparticles (2006) Biomaterials, 27, pp. 3147-3153; Santos, J.L., Oramas, E., Pego, A.P., Osteogenic differentiation of mesenchymal stem cells using PAMAM dendrimers as gene deliveryvectors (2009) J Control Release, 134, pp. 141-148; Gheisari, Y., Soleimani, M., Azadmanesh, K., Multipotent mesenchymalstromal cells: Optimization and comparison of five cationicpolymer-based gene delivery methods (2008) Cytotherapy, 10, pp. 815-823; Holladay, C., Keeney, M., Greiser, U., A matrix reservoir forimproved control of non-viral gene delivery (2009) J Control Release, 136, pp. 220-225; Parekh, H.S., The advance of dendrimers-a versatile targeting platformfor gene/drug delivery (2007) Curr Pharm Des, 13, pp. 2837-2850; Santos, J.L., Pandita, D., Rodrigues, J., Receptor-mediated genedelivery using PAMAM dendrimers conjudated with peptides recognizedby mesenchymal stem cells (2010) Mol Pharmaceutics, 7, pp. 763-774; Santos, J.L., Oliveira, H., Pandita, D., Rodrigues, J., Functionalizationof Poly(amidoamine) Dendrimers with hydrophobic chains forimproved gene delivery in mesenchymal stem cells (2010) J Control Release, 144, pp. 55-64; Bourgeat-Lami, E., Organic-inorganic nanostructured colloids (2002) JNanosci Nanotechnol, 2, pp. 1-24; Chowdhury, E.H., Akaike, T., Bio-functional inorganic materials: Anattractive branch of gene-based nano-medicine delivery for 21stcentury (2005) Curr Gene Ther, 5, pp. 669-676; Sokolova, V., Epple, M., Inorganic nanoparticles as carriers of nucleicacids into cells (2008) Angew Chem Int Ed Engl, 47, pp. 1382-1395; Uchimura, E., Yamada, S., Uebersax, L., Method for reversetransfection using gold colloid as a nano-scaffold (2007) J Biosci Bioeng, 103, pp. 101-103; Gonzalez-McQuire, R., Green, D.W., Partridge, K.A., Coating of human mesenchymal cells in 3D culture with bioinorganicnanoparticles promotes osteoblastic differentiation and gene transfection (2007) Adv Mater, 19, pp. 2236-2240; Park, J.S., Na, K., Woo, D.G., Non-viral gene delivery of DNApolyplexed with nanoparticles transfected into human mesenchymalstem cells (2010) Biomaterials, 31, pp. 124-132; Peister, A., Mellad, J.A., Wang, M., Stable transfection of MSCsby electroporation (2004) Gene Ther, 11, pp. 224-228; Ferreira, E., Potier, E., Logeart-Avramoglou, D., Optimization of a gene electrotransfer method for mesenchymal stem cell transfection (2008) Gene Ther, 15, pp. 537-544; Ziv, R., Steinhardt, Y., Pelled, G., Micro-electroporation of mesenchymalstem cells with alternating electrical current pulses (2009) BiomedMicrodevices, 11, pp. 95-101; Lim, J.Y., Park, S.H., Jeong, C.H., Microporation is a valuabletransfection method for efficient gene delivery into human umbilicalcord blood-derived mesenchymal stem cells (2010) BMC Biotechnol, 10, p. 38; Lee, S.-J., Kang, S.-W., Do, H.-J., Enhancement of bone regenerationby gene delivery of BMP2/Runx2 bicistronic vector into adipose-derived stromal cells (2010) Biomater, 31, pp. 5652-5659; Lakshmipathy, U., Pelacho, B., Sudo, K., Efficient transfection of embryonic and adult stem cells (2004) Stem Cells, 22, pp. 531-543; Aluigi, M., Fogli, M., Curti, A., Nucleofection is an efficientnonviral transfection technique for human bone marrow-derivedmesenchymal stem cells (2006) Stem Cells, 24, pp. 454-461; Nakashima, S., Matsuyama, Y., Nitta, A., Highly efficient transfectionof human marrow stromal cells by nucleofection (2005) TransplantProc, 37, pp. 2290-2292; Miller, D.L., Pislaru, S.V., Greenleaf, J.E., Sonoporation: MechanicalDNA delivery by ultrasonic cavitation (2002) Somat Cell Mol Genet, 27, pp. 115-134; Otani, K., Yamahara, K., Ohnishi, S., Nonviral delivery of siRNA into mesenchymal stem cells by a combination of ultrasoundand microbubbles (2009) J Control Release, 133, pp. 146-153; Aslan, H., Sheyn, D., Gazit, D., Genetically engineered mesenchymalstem cells: Applications in spine therapy (2009) Regen Med, 4, pp. 99-108; Chiang, G.G., Rubin, H.L., Cherington, V., Bone marrow stromalcell-mediated gene therapy for hemophilia A: In vitro expression of human factor VIII with high biological activity requires the inclusionof the proteolytic site at amino acid 1648 (1999) Hum Gene Ther, 10, pp. 61-76; Gelse, K., von der Mark, K., Schneider, H., Cartilage regeneration bygene therapy (2003) Curr Gene Ther, 3, pp. 305-317; Moutsatsos, I.K., Turgeman, G., Zhou, S., Exogenously regulatedstem cell-mediated gene therapy for bone regeneration (2001) Mol Ther, 3, pp. 449-461; Phillips, M.I., Tang, Y.L., Genetic modification of stem cells for transplantation (2008) Adv Drug Deliv Rev, 60, pp. 160-172; Schwarz, E.J., Reger, R.L., Alexander, G.M., Rat marrow stromalcells rapidly transduced with a self-inactivating retrovirus synthesizeL-DOPA in vitro (2001) Gene Ther, 8, pp. 1214-1223; Sun, M., Kong, L., Wang, X., Coexpression of tyrosine hydroxylase, GTP cyclohydrolase I, aromatic amino acid decarboxylase, and vesicular monoamine transporter 2 from a helper virus-freeherpes simplex virus type 1 vector supports high-level, long-termbiochemical and behavioral correction of a rat model of Parkinson'sdisease (2004) Hum Gene Ther, 15, pp. 1177-1196; Turgeman, G., Pittman, D.D., Muller, R., Engineered humanmesenchymal stem cells: A novel platform for skeletal cell mediatedgene therapy (2001) J Gene Med, 3, pp. 240-251; Tuszynski, M.H., Thal, L., Pay, M., A phase 1 clinical trial of nerve growth factor gene therapy for Alzheimer disease (2005) Nat Med, 11, pp. 551-555; Fang, J., Zhu, Y.Y., Smiley, E., Stimulation of new bone formationby direct transfer of osteogenic plasmid genes (1996) Proc Natl AcadSci U S A, 93, pp. 5753-5758; Bonadio, J., Smiley, E., Patil, P., Localized, direct plasmid genedelivery in vivo: Prolonged therapy results in reproducible tissueregeneration (1999) Nat Med, 5, pp. 753-759; Kasper, F.K., Young, S., Tanahashi, K., Evaluation of bone regenerationby DNA release from composites of oligo(poly(ethyleneglycol) fumarate) and cationized gelatin microspheres in a criticalsizedcalvarial defect (2006) J Biomed Mater Res A, 78, pp. 335-342; Kuroda, S., Kondo, H., Ohya, K., A new technique with calciumphosphate precipitate enhances efficiency of in vivo plasmid DNAgene transfer (2005) J Pharmacol Sci, 97, pp. 227-233; Endo, M., Kuroda, S., Kondo, H., Bone regeneration by modifiedgene-activated matrix: Effectiveness in segmental tibial defects inrats (2006) Tissue Eng, 12, pp. 489-497; Huang, Y.C., Simmons, C., Kaigler, D., Bone regeneration in a ratcranial defect with delivery of PEI-condensed plasmid DNA encodingfor bone morphogenetic protein-4 (BMP-4) (2005) Gene Ther, 12, pp. 418-426; Nie, H., Ho, M.L., Wang, C.K., BMP-2 plasmid loadedPLGA/HAp composite scaffolds for treatment of bone defects innude mice (2009) Biomaterials, 30, pp. 892-901; Ono, I., Yamashita, T., Jin, H.Y., Combination of porous hydroxyapatiteand cationic liposomes as a vector for BMP-2 genetherapy (2004) Biomaterials, 25, pp. 4709-4718; Kishimoto, K.N., Watanabe, Y., Nakamura, H., Ectopic boneformation by electroporatic transfer of bone morphogenetic protein-4 gene (2002) Bone, 31, pp. 340-347; Sheyn, D., Kimelman-Bleich, N., Pelled, G., Ultrasound-basednonviral gene delivery induces bone formation in vivo (2008) Gene Ther, 15, pp. 257-266; Hosseinkhani, H., Inatsugu, Y., Hiraoka, Y., Impregnation of plasmid DNA into three-dimensional scaffolds and medium perfusionenhance in vitro DNA expression of mesenchymal stem cells (2005) Tissue Eng, 11, pp. 1459-1475; Hosseinkhani, H., Hosseinkhani, M., Gabrielson, N.P., DNAnanoparticles encapsulated in 3D tissue-engineered scaffolds enhanceosteogenic differentiation of mesenchymal stem cells (2007) JBiomed Mater Res A, 85, pp. 47-60; Huang, Y.C., Kaigler, D., Rice, K.G., Combined angiogenic and osteogenic factor delivery enhances bone marrow stromal celldrivenbone regeneration (2005) J Bone Miner Res, 20, pp. 848-857; Blum, J.S., Barry, M.A., Mikos, A.G., In vivo evaluation of genetherapy vectors in ex vivo-derived marrow stromal cells for boneregeneration in a rat critical-size calvarial defect model (2003) Hum GeneTher, 14, pp. 1689-1701; Aslan, H., Zilberman, Y., Arbeli, V., Nucleofection-based ex vivononviral gene delivery to human stem cells as a platform for tissueregeneration (2006) Tissue Eng, 12, pp. 877-889; Noel, D., Gazit, D., Bouquet, C., Short-term BMP-2 expression issufficient for in vivo osteochondral differentiation of mesenchymalstem cells (2004) Stem Cells, 22, pp. 74-85
Keywords: Animals; article; artificial chromosome; Bone and Bones; Bone Regeneration; bone tissue; Bone tissue engineering; cell based gene therapy; dendrimer; ex vivo gene transfer; Gene delivery; gene targeting; Gene therapy; Gene Transfer Techniques; gene vector; genetic transfection; human; Humans; in vivo gene transfer; liposome; Mesenchymal stem cell; Mesenchymal Stem Cells; nanomedicine; nanoparticle; Non-viral vectors; nonhuman; nonviral gene delivery system; polymer; protein expression; Regeneration; Regenerative Medicine; Tissue engineering; Tissue regeneration

Scientists perception of ethical issues in nanomedicine: A case study - Silva Costa, H.; Sethe, S.; Pêgo, A.P.; Olsson, I.A.S. (NanomedicineNanomedicine, 2011)
Aim: Research and development in nanomedicine has been accompanied by the consideration of ethical issues; however, little is known about how researchers working in this area perceive such issues. This case-study explores scientists attitude towards and knowledge of ethical issues. Method: Data were collected by semi-structured interviews with 22 nanomedicine practitioners and subject to content analysis. Results: We found that scientists reflect with ambiguity on the reputed novelty of nanomedicine and what the ethical issues and risks are in their work. Respondents see no necessity for a paradigm shift in ethical considerations, but view ethical issues in nanomedicine as overlapping with those of other areas of biomedical research. Most respondents discuss ethical issues they faced in scientific work with their colleagues, but expect benefit from additional information and training on ethics. Conclusion: Our findings that scientists are motivated to reflect on ethical issues in their work, can contribute to the design of new strategies, including training programs, to engage scientists in ethical discussion and stimulate their responsibility as nanomedicine practitioners. © 2011 Future Medicine Ltd.
Keywords: adult; ambiguity; article; attitude; case study; clinical article; empirical research; ethics; Female; human; Humans; information; knowledge; male; medical ethics; medical research; Middle Aged; Models, Theoretical; nanomedicine; Nanotechnology; perception; priority journal; professional practice; qualitative study; Research Personnel; responsibility; risks; scientist; scientists perception; semi structured interview; training; Young Adult

Segmentation of ultrasound images of the carotid using RANSAC and cubic splines - Rocha, R.; Campilho, A.; Silva, J.; Azevedo, E.; Santos, R. (Computer Methods and Programs in BiomedicineComput. Methods Programs Biomed., 2011)
A new algorithm is proposed for the semi-automatic segmentation of the near-end and the far-end adventitia boundary of the common carotid artery in ultrasound images. It uses the random sample consensus method to estimate the most significant cubic splines fitting the edge map of a longitudinal section. The consensus of the geometric model (a spline) is evaluated through a new gain function, which integrates the responses to different discriminating features of the carotid boundary: the proximity of the geometric model to any edge or to valley shaped edges; the consistency between the orientation of the normal to the geometric model and the intensity gradient; and the distance to a rough estimate of the lumen boundary.A set of 50 longitudinal B-mode images of the common carotid and their manual segmentations performed by two medical experts were used to assess the performance of the method. The image set was taken from 25 different subjects, most of them having plaques of different classes (class II to class IV), sizes and shapes.The quantitative evaluation showed promising results, having detection errors similar to the ones observed in manual segmentations for 95% of the far-end boundaries and 73% of the near-end boundaries. © 2011 Elsevier Ireland Ltd.
Cited By (since 1996): 10Export Date: 21 November 2012Source: ScopusCODEN: CMPBEdoi: 10.1016/j.cmpb.2010.04.015PubMed ID: 20554343Language of Original Document: EnglishCorrespondence Address: Rocha, R.; INEB, Divisão de Sinal e Imagem, Campus FEUP, 4200-465 Porto, Portugal; email: rhr@isep.ipp.ptReferences: Baldassarre, D., Amato, M., Bondioli, A., Sirtori, C.R., Tremoli, E., Carotid artery intima-media thickness measured by ultrasonography in normal clinical practice correlates well with atherosclerosis risk factors (2000) Stroke, 31, pp. 2426-2430;O'Leary, D., Polak, J., Kronmal, R., Manolio, T., Burke, G.W.S., Carotid-artery intima and media thickness as a risk factor for myocardial infarction and stroke in older adults (1999) N. Engl. J. Med., 340, pp. 14-22; Hodis, H., Mack, W., LaBree, L., Selzer, R., Liu, C., Liu, C., Azen, S., The role of carotid arterial intima-media thickness in predicting clinical coronary events (1998) Ann. Intern. Med., 128 (4), pp. 262-269; Reneman, R.S., Meinders, J.M., Hoeks, A.P.G., Non-invasive ultrasound in arterial wall dynamics in humans: what have we learned and what remains to be solved (2005) Eur. Heart J., 26, pp. 960-966; Gee, A., Prager, R., Treece, G., Berman, L., Engineering a freehand 3D ultrasound system (2003) Pattern Recogn. Lett., 24 (4-5), pp. 757-777; Sonka, M., Liang, W., Stefancik, R., Stolpen, A., (2000), 2. , Handbook of Medical Imaging: Medical Image Processing and Analysis,SPIEGiannoglou, G.D., Chatzizisis, Y.S., Koutkias, V., Kompatsiaris, I., Papadogiorgaki, M., Mezaris, V., Parissi, E., Louridas, G.E., A novel active contour model for fully automated segmentation of intravascular ultrasound images: in vivo validation in human coronary arteries (2008) Comput. Biol. Med., 37 (9), pp. 1292-1302; Tsai, A., Yezzi, A.J., Tempany, C., Tucker, D., Fan, A., Grimson, W.E.L., Willsky, A.S., A shape-based approach to the segmentation of medical imagery using level sets (2003) IEEE Trans. Med. Imaging, 22 (2), pp. 137-154; Cremers, D., Kohlberger, T., Schnorr, C., Nonlinear shape statistics in Mumford-Shah based segmentation (2002) Proc. European Conf. on Computer Vision (ECCV'2002), vol. 2351, pp. 93-108; Cremers, D., Sochen, N., Schnorr, C., Towards recognition-based variational segmentation using shape priors and dynamic labeling (2003) Proc. European Conf. on Computer Vision (ECCV'2003), vol. 2695, pp. 388-400; Cremers, D., Osher, S., Soatto, S., Kernel density estimation and intrinsic alignment for knowledge-driven segmentation: teaching level sets to walk (2004) Pattern Recognit., 3175, pp. 36-44; Halenka, M., Noninvasive measurement of early atherosclerosis by high-resolution B-mode ultrasonography (1999) Acta-Universitatis Palackianae Olomucensis Facultatis Medicae, 142, pp. 7-12; Touboul, P.J., Prati, P., Scarabin, P.-Y., Adrai, V., Thibout, E., Ducimetiere, P., Use of monitoring software to improve the measurement of carotid wall thickness by B-mode imaging (1992) J. Hypertension, 10 (5), pp. 37-41; Gariepy, J., Massonneau, M., Levenson, J., Heudes, D., Simon, A., Evidence for in vivo carotid and femoral wall thickness in human hypertension (1993) J. Hypertension, 22 (1), pp. 111-118. , the Groupe de Prevention Cardio-vasculaire en Medecine du Travail; Selzer, R.H., Hodis, H.N., Kwong-Fu, H., Mack, W.J., Lee, P.L., Liu, C.R., Liu, C.H., Evaluation of computerized edge tracking for quantifying intima-media thickness of the common carotid artery from B-mode ultrasound images (1994) Atherosclerosis, 111, pp. 1-11; Gustavsson, T., Liang, Q., Wendelhag, I., Wikstrand, J., A dynamic programming procedure for automated ultrasonic measurement of the carotid artery (1994) Comput. Cardiol., pp. 297-300; Kozick, R.J., Detecting interfaces on ultrasound images of the carotid artery by dynamic programming (1996) SPIE, 2666, pp. 233-241; Gustavsson, T., Abu-Gharbieh, R., Hamarneh, G., Liang, Q., Implementation and comparison of four different boundary detection algorithms for quantitative ultrasonic measurements of the human carotid artery (1997) Comput. Cardiol., pp. 69-72; Detmer, P., Bashein, G., Martin, R., Matched filter identification of left-ventricle endocardial borders in transesophageal echocardiograms (1990) IEEE Trans. Med. Imaging, 9 (4), pp. 396-404; Liang, Q., Wendelhag, I., Wikstrand, J., Gustavsson, T., A multiscale dynamic programming procedure for boundary detection in ultrasound artery images (2000) IEEE Trans. Med. Imaging, 19 (2), pp. 127-142; Schmidt-Trucksass, A., Cheng, D., Sandrock, M., Schulte-Monting, J., Rauramaa, R., Huonker, M., Burkhardt, H., Computerized analysing system using the active contour in ultrasound measurement of carotid artery intima-media thickness (2001) Clin. Physiol., 5, pp. 561-569; Cheng, D., Schmidt-Trucksass, A., Cheng, K., Sandrock, M., Pu, Q., Burkhardt, H., (1999), pp. 452-457. , Automatic detection of the intimal and the adventitial layers of the common carotid artery wall in ultrasound B-mode images using snakes, in: Int. Conf. on Image Analysis and Processing, B. WernerCheng, D., Schmidt-Trucksass, A., Cheng, K., Burkhardt, H., Using snakes to detect the intimal and adventitial layers of the common carotid artery wall in sonographic images (2002) Comput. Methods Programs Biomed., 67, pp. 27-37; Kass, M., Witkin, A., Terzopoulos, D., Snakes: active contour models (1988) Int. J. Comput. Vis., pp. 321-331; Christodoulou, C.I., Pattichis, C.S., Pantziaris, M., Nicolaides, A., Texture based classification of atherosclerotic carotid plaques (2003) IEEE Trans. Med. Imaging, 22 (7), pp. 902-912; Barratt, D., Ariff, B., Humphries, K., Thom, S., Hughes, A., Reconstruction and quantification of the carotid artery bifurcation from 3-D ultrasound images (2004) IEEE Trans. Med. Imaging, 23 (5), pp. 567-583; Fischler, M.A., Bolles, R.C., Random sample consensus: a paradigm for model fitting with applications to image analysis and automated cartography (1981) Commun. ACM, 24 (6), pp. 381-395; Rossi, A.C., Brands, P.J., Hoeks, A.P.G., Automatic recognition of the common carotid artery in longitudinal ultrasound B-mode scans (2008) Med. Image Anal., 12, pp. 653-665; Zack, G.W., Rogers, W.E., Latt, S.A., Automatic measurement of sister chromatid exchange frequency (1977) J. Histochem. Cytochem., 25 (7), pp. 741-753; Tauber, C., (2005), Filtrage anisotrope robuste et segmentation par b-spline snake: application aux images échographiques, Ph.D. thesis, Institut National Polytechnique de Toulouse, ToulouseYu, Y., Acton, S., Speckle reducing anisotropic diffusion (2002) IEEE Trans. Image Process., 11 (11), pp. 1260-1270; Yu, Y., Acton, S., Edge detection in ultrasound imagery using the instantaneous coefficient of variation (2004) IEEE Trans. Image Process., 13 (12), pp. 1640-1655; Black, M.J., Sapiro, G., Marimont, D.H., Heeger, D., Robust anisotropic diffusion (1998) IEEE Trans. Image Process., 7 (3), pp. 421-432; Rudin, L., Osher, S., Fatemi, E., Nonlinear total variation based noise removal algorithms (1992) Proceedings of the 11th Annual Int. Conf. of the Center for Nonlinear Studies on Experimental Mathematics: Computational Issues in Nonlinear Science, pp. 259-268; Rudin, L., Osher, S., Total variation based image restoration with free local constraints (1994) Proceedings of IEEE Int. Conf. on Image Processing (ICIP'94), vol. 1, pp. 31-35; Canny, J., A computational approach to edge detection (1986) IEEE Trans. Pattern Anal. Mach. Intell., 8 (6), pp. 679-698; Guo, Z., Hall, R.W., Parallel thinning with two-subiteration algorithms (1989) Commun. ACM, 32 (3), pp. 359-373; Burden, R., Faires, J.D., (2000) Numerical Analysis, , Brooks Cole; Forsyth, D.A., Ponce, J., (2003) Computer Vision: A Modern Approach, , Prentice Hall; Marquina, A., Osher, S., Explicit algorithms for a new time dependent model based on level set motion for nonlinear deblurring and noise removal (2000) SIAM J. Sci. Comput., 22 (2), pp. 387-405; Chum, O., Matas, J., Kittler, J., (2003), 81, pp. 236-243. , Locally optimized RANSAC, in: Lecture Notes in Computer Science - Pattern Recognition, Springer Berlin/Heidelberg, Springer LNCSBland, J.M., Altman, D.G., Statistical methods for assessing agreement between two methods of clinical measurement (1986) Lancet, 1 (8476), pp. 307-310
Keywords: Algorithms; article; B scan; B-mode images; Carotid; carotid artery; Carotid Artery Diseases; Carotid Artery, Common; Class II; clinical article; Common carotid artery; Cubic spline; Detection error; echography; Edge map; Female; Gain function; Geometric models; Geometry; human; Humans; Image Interpretation, Computer-Assisted; image processing; Image segmentation; Image sets; Intensity gradients; Longitudinal section; male; Manual segmentation; mathematical model; Medical experts; Medical imaging; Non-linear smoothing; Pattern Recognition, Automated; quantitative analysis; Quantitative evaluation; random sample; Random sample consensus; RANSAC; Semi-automatic segmentation; Splines; Ultrasonic applications; Ultrasonics; Ultrasonography; Ultrasound image; Ultrasound images

Simulations of the NK cell immune synapse reveal that activation thresholds can be established by inhibitory receptors acting locally - Kaplan, A.; Kotzer, S.; Almeida, C.R.; Kohen, R.; Halpert, G.; Salmon-Divon, M.; Köhler, K.; Höglund, P.; Davis, D.M.; Mehr, R. (Journal of ImmunologyJ. Immunol., 2011)
NK cell activation is regulated by a balance between activating and inhibitory signals. To address the question of how these signals are spatially integrated, we created a computer simulation of activating and inhibitory NK cell immunological synapse (NKIS) assembly, implementing either a "quantity-based" inhibition model or a "distance-based" inhibition model. The simulations mimicked the observed molecule distributions in inhibitory and activating NKIS and yielded several new insights. First, the total signal is highly influenced by activating complex dissociation rates but not by adhesion and inhibitory complex dissociation rates. Second, concerted motion of receptors in clusters significantly accelerates NKIS maturation. Third, when the potential of a cis interaction between Ly49 receptors and MHC class I on murine NK cells was added to the model, the integrated signal as a function of receptor and ligand numbers was only slightly increased, at least up to the level of 50% cis-bound Ly49 receptors reached in the model. Fourth, and perhaps most importantly, the integrated signal behavior obtained when using the distance-based inhibition signal model was closer to the experimentally observed behavior, with an inhibition radius of the order 3-10 molecules. Microscopy to visualize Vav activation in NK cells on micropatterned surfaces of activating and inhibitory strips revealed that Vav is only locally activated where activating receptors are ligated within a single NK cell contact. Taken together, these data are consistent with a model in which inhibitory receptors act locally; that is, that every bound inhibitory receptor acts on activating receptors within a certain radius around it. Copyright © 2011 by The American Association of Immunologists, Inc.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JOIMAdoi: 10.4049/jimmunol.1002208PubMed ID: 21690326Language of Original Document: EnglishCorrespondence Address: Mehr, R.; Mina and Everard Goodman Faculty of Life Sciences, Bar-Ilan University, Ramat-Gan 52900, Israel; email: ramit.mehr@biu.ac.ilChemicals/CAS: Vav protein, 282122-55-8; intercellular adhesion molecule 1, 126547-89-5; H-2 Antigens; Histocompatibility Antigens Class I; Intercellular Adhesion Molecule-1, 126547-89-5; KLRK1 protein, human; Lymphocyte Function-Associated Antigen-1; MHC class I-related chain A; NK Cell Lectin-Like Receptor Subfamily A; NK Cell Lectin-Like Receptor Subfamily K; Receptors, KIRReferences: Burgess, S.J., Maasho, K., Masilamani, M., Narayanan, S., Borrego, F., Coligan, J.E., The NKG2D receptor: Immunobiology and clinical implications (2008) Immunol. Res., 40, pp. 18-34;González, S., López-Soto, A., Suarez-Alvarez, B., López-Vázquez, A., López-Larrea, C., NKG2D ligands: Key targets of the immune response (2008) Trends Immunol., 29, pp. 397-403; Vyas, Y.M., Maniar, H., Dupont, B., Cutting edge: Differential segregation of the Src homology 2-containing protein tyrosine phosphatase-1 within the early NK cell immune synapse distinguishes noncytolytic from cytolytic interactions (2002) Journal of Immunology, 168 (7), pp. 3150-3154; Long, E.O., Negative signaling by inhibitory receptors: The NK cell paradigm (2008) Immunol. Rev., 224, pp. 70-84; Ljunggren, H.G., Kärre, K., In search of the 'missing self': MHC molecules and NK cell recognition (1990) Immunol. Today, 11, pp. 237-244; Kane, K.P., Silver, E.T., Hazes, B., Specificity and function of activating Ly-49 receptors (2001) Immunol. Rev., 181, pp. 104-114; Lanier, L.L., Up on the tightrope: Natural killer cell activation and inhibition (2008) Nat. Immunol., 9, pp. 495-502; Radaev, S., Sun, P.D., Structure and function of natural killer cell surface receptors (2003) Annu. Rev. Biophys. Biomol. Struct., 32, pp. 93-114; Vivier, E., Nunes, J.A., Vely, F., Natural killer cell signaling pathways (2004) Science, 306 (5701), pp. 1517-1519. , DOI 10.1126/science.1103478; Yokoyama, W.M., Plougastel, B.F., Immune functions encoded by the natural killer gene complex (2003) Nat. Rev. Immunol., 3, pp. 304-316; Stebbins, C.C., Watzl, C., Billadeau, D.D., Leibson, P.J., Burshtyn, D.N., Long, E.O., Vav1 dephosphorylation by the tyrosine phosphatase SHP-1 as amechanism for inhibition of cellular cytotoxicity (2003) Mol. Cell. Biol., 23, pp. 6291-6299; Bryceson, Y.T., Long, E.O., Line of attack: NK cell specificity and integration of signals (2008) Curr. Opin. Immunol., 20, pp. 344-352; McCann, F.E., Suhling, K., Carlin, L.M., Eleme, K., Taner, S.B., Yanagi, K., Vanherberghen, B., Davis, D.M., Imaging immune surveillance by T cells and NK cells (2002) Immunol. Rev., 189, pp. 179-192; Davis, D.M., Assembly of the immunological synapse for T cells and NK cells (2002) Trends in Immunology, 23 (7), pp. 356-363. , DOI 10.1016/S1471-4906(02)02243-3, PII S1471490602022433; Vyas, Y.M., Mehta, K.M., Morgan, M., Maniar, H., Butros, L., Jung, S., Burkhardt, J.K., Dupont, B., Spatial organization of signal transduction molecules in the NK cell immune synapses during MHC class I-regulated noncytolytic and cytolytic interactions (2001) Journal of Immunology, 167 (8), pp. 4358-4367; Vyas, Y.M., Maniar, H., Lyddane, C.E., Sadelain, M., Dupont, B., Ligand binding to inhibitory killer cell Ig-like receptors induce colocalization with Src homology domain 2-containing protein tyrosine phosphatase 1 and interruption of ongoing activation signals (2004) Journal of Immunology, 173 (3), pp. 1571-1578; Orange, J.S., Formation and function of the lytic NK-cell immunological synapse (2008) Nat. Rev. Immunol., 8, pp. 713-725; Eleme, K., Taner, S.B., Onfelt, B., Collinson, L.M., McCann, F.E., Chalupny, N.J., Cosman, D., Davis, D.M., Cell surface organization of stress-inducible proteins ULBP and MICA that stimulate human NK cells and T cells via NKG2D (2004) J. Exp. Med., 199, pp. 1005-1010; Cebo, C., Da, R.S., Wittnebel, S., Turhan, A.G., Abdelali, J., Caillat-Zucman, S., Bourhis, J.H., Caignard, A., The decreased susceptibility of Bcr/Abl targets to NK cell-mediated lysis in response to imatinib mesylate involves modulation of NKG2D ligands, GM1 expression, and synapse formation (2006) Journal of Immunology, 176 (2), pp. 864-872; Burack, W.R., Lee, K.H., Holdorf, A.D., Dustin, M.L., Shaw, A.S., Cutting edge: Quantitative imaging of raft accumulation in the immunological synapse (2002) J. Immunol., 169, pp. 2837-2841; Harder, T., Engelhardt, K.R., Membrane domains in lymphocytes - From lipid rafts to protein scaffolds (2004) Traffic, 5, pp. 265-275; Laude, A.J., Prior, I.A., Plasma membrane microdomains: Organization, function and trafficking (2004) Mol. Membr. Biol., 21, pp. 193-205; Lou, Z., Jevremovic, D., Billadeau, D.D., Leibson, P.J., A balance between positive and negative signals in cytotoxic lymphocytes regulates the polarization of lipid rafts during the development of cell-mediated killing (2000) J. Exp. Med., 191, pp. 347-354; Pike, L.J., Lipid rafts: Bringing order to chaos (2003) Journal of Lipid Research, 44 (4), pp. 655-667. , DOI 10.1194/jlr.R200021-JLR200; Pizzo, P., Viola, A., Lymphocyte lipid rafts: Structure and function (2003) Curr. Opin. Immunol., 15, pp. 255-260; Rodgers, W., Farris, D., Mishra, S., Merging complexes: Properties of membrane raft assembly during lymphocyte signaling (2005) Trends Immunol., 26, pp. 97-103; Schmitz, G., Grandl, M., Update on lipid membrane microdomains (2008) Curr. Opin. Clin. Nutr. Metab. Care, 11, pp. 106-112; Wright, M.D., Moseley, G.W., Van Spriel, A.B., Tetraspanin microdomains in immune cell signalling and malignant disease (2004) Tissue Antigens, 64 (5), pp. 533-542. , DOI 10.1111/j.1399-0039.2004.00321.x; Vogt, A.B., Spindeldreher, S., Kropshofer, H., Clustering of MHCpeptide complexes prior to their engagement in the immunological synapse: Lipid raft and tetraspan microdomains (2002) Immunol. Rev., 189, pp. 136-151; Lee, S.J.E., Hori, Y., Groves, J.T., Dustin, M.L., Chakraborty, A.K., Correlation of a dynamic model for immunological synapse formation with effector functions: Two pathways to synapse formation (2002) Trends Immunol., 23, pp. 492-499; Giagulli, C., Scarpini, E., Ottoboni, L., Narumiya, S., Butcher, E.C., Constantin, G., Laudanna, C., RhoA and zeta PKC Control Distinct Modalities of LFA-1 Activation by Chemokines: Critical Role of LFA-1 Affinity Triggering in Lymphocyte In Vivo Homing (2004) Immunity, 20 (1), pp. 25-35. , DOI 10.1016/S1074-7613(03)00350-9; Masilamani, M., Nguyen, C., Kabat, J., Borrego, F., Coligan, J.E., CD94/NKG2A inhibits NK cell activation by disrupting the actin network at the immunological synapse (2006) J. Immunol., 177, pp. 3590-3596; Weikl, T.R., Lipowsky, R., Pattern formation during T-cell adhesion (2004) Biophysical Journal, 87 (6), pp. 3665-3678. , DOI 10.1529/biophysj.104.045609; Kotzer, S., Salmon-Divon, M., Kaplan, A., Almeida, C.R., Hoglund, P., Davis, D.M., Mehr, R., Modeling the influence of molecule and cell surface micro-domain distribution on the formation of T cell immunological synapses (2007) Life Science Systems and Applications Workshop, 2007. LISA 2007. IEEE/NIH. 8-9 November, , http://ieeexplore.ieee.org/xpl/freeabs_all.jsp?arnumber=4400878, Available at; Culley, F.J., Johnson, M., Evans, J.H., Kumar, S., Crilly, R., Casasbuenas, J., Schnyder, T., Ushakov, D.S., Natural killer cell signal integration balances synapse symmetry and migration (2009) PLoS Biol., 7, pp. e1000159; Treanor, B., Lanigan, P.M.P., Kumar, S., Dunsby, C., Munro, I., Auksorius, E., Culley, F.J., Neil, M.A.A., Microclusters of inhibitory killer immunoglobulin-like receptor signaling at natural killer cell immunological synapses (2006) J. Cell Biol., 174, pp. 153-161; Back, J., Chalifour, A., Scarpellino, L., Held, W., Stable masking by H-2Dd cis ligand limits Ly49A relocalization to the site of NK cell/target cell contact (2007) Proc. Natl. Acad. Sci. USA, 104, pp. 3978-3983; Back, J., Scarpellino, L., Held, W., Probing the interactions of NK cell receptors with ligand expressed in trans and cis (2010) MethodsMol. Biol., 612, pp. 313-323; Chalifour, A., Scarpellino, L., Back, J., Brodin, P., Devèvre, E., Gros, F., Lévy, F., Held, W., A role for cis interaction between the inhibitory Ly49A receptor and MHC class I for natural killer cell education (2009) Immunity, 30, pp. 337-347; Doucey, M.A., Scarpellino, L., Zimmer, J., Guillaume, P., Luescher, I.F., Bron, C., Held, W., Cis association of Ly49A with MHC class I restricts natural killer cell inhibition (2004) Nat. Immunol., 5, pp. 328-336; Held, W., Mariuzza, R.A., Cis interactions of immunoreceptors with MHC and non-MHC ligands (2008) Nat. Rev. Immunol., 8, pp. 269-278; Scarpellino, L., Oeschger, F., Guillaume, P., Coedert, J.D., Levy, F., Leclercq, G., Held, W., Interactions of Ly49 family receptors with MHC class I ligands in trans and cis (2007) Journal of Immunology, 178 (3), pp. 1277-1284; Saffman, P.G., Delbrück, M., Brownian motion in biological membranes (1975) Proc. Natl. Acad. Sci. USA, 72, pp. 3111-3113; Raychaudhuri, S., Chakraborty, A.K., Kardar, M., Effective membrane model of the immunological synapse (2003) Phys. Rev. Lett., 91, p. 208101; Burroughs, N.J., Wülfing, C., Differential segregation in a cell-cell contact interface: The dynamics of the immunological synapse (2002) Biophys. J., 83, pp. 1784-1796; Coombs, D., Goldstein, B., Effects of the geometry of the immunological synapse on the delivery of effector molecules (2004) Biophysical Journal, 87 (4), pp. 2215-2220. , DOI 10.1529/biophysj.104.045674; Köhler, K., Xiong, S., Brzostek, J., Mehrabi, M., Eissmann, P., Harrison, A., Cordoba, S.P., Gould, K., Matched sizes of activating and inhibitory receptor/ligand pairs are required for optimal signal integration by human natural killer cells (2010) PLoS ONE, 5, pp. e15374; Dykstra, M., Cherukuri, A., Sohn, H.W., Tzeng, S.J., Pierce, S.K., Location is everything: Lipid rafts and immune cell signaling (2003) Annu. Rev. Immunol., 21, pp. 457-481; Horejsí, V., The roles of membrane microdomains (rafts) in T cell activation (2003) Immunol. Rev., 191, pp. 148-164; Fujiwara, T., Ritchie, K., Murakoshi, H., Jacobson, K., Kusumi, A., Phospholipids undergo hop diffusion in compartmentalized cell membrane (2002) Journal of Cell Biology, 157 (6), pp. 1071-1081. , DOI 10.1083/jcb.200202050; Giurisato, E., McIntosh, D.P., Tassi, M., Gamberucci, A., Benedetti, A., T cell receptor can be recruited to a subset of plasma membrane rafts, independently of cell signaling and attendantly to raft clustering (2003) J. Biol. Chem., 278, pp. 6771-6778; Kusumi, A., Koyama-Honda, I., Suzuki, K., Molecular dynamics and interactions for creation of stimulation-induced stabilized rafts from small unstable steady-state rafts (2004) Traffic, 5 (4), pp. 213-230. , DOI 10.1111/j.1600-0854.2004.0178.x; Marwali, M.R., MacLeod, M.A., Muzia, D.N., Takei, F., Lipid rafts mediate association of LFA-1 and CD3 and formation of the immunological synapse of CTL (2004) Journal of Immunology, 173 (5), pp. 2960-2967; Montixi, C., Langlet, C., Bernard, A.M., Thimonier, J., Dubois, C., Wurbel, M.A., Chauvin, J.P., He, H.T., Engagement of T cell receptor triggers its recruitment to low-density detergent-insoluble membrane domains (1998) EMBO J., 17, pp. 5334-5348; Munro, S., Lipid rafts: Elusive or illusive? (2003) Cell, 115, pp. 377-388; Pizzo, P., Giurisato, E., Bigsten, A., Tassi, M., Tavano, R., Shaw, A., Viola, A., Physiological T cell activation starts and propagates in lipid rafts (2004) Immunol. Lett., 91, pp. 3-9; Xavier, R., Brennan, T., Li, Q., McCormack, C., Seed, B., Membrane compartmentation is required for efficient T cell activation (1998) Immunity, 8, pp. 723-732; Filipp, D., Julius, M., Lipid rafts: Resolution of the "fyn problem"? (2004) Mol. Immunol., 41, pp. 645-656; Schade, A.E., Levine, A.D., Lipid raft heterogeneity in human peripheral blood T lymphoblasts: A mechanism for regulating the initiation of TCR signal transduction (2002) J. Immunol., 168, pp. 2233-2239; Janes, P.W., Ley, S.C., Magee, A.I., Aggregation of lipid rafts accompanies signaling via the T cell antigen receptor (1999) J. Cell Biol., 147, pp. 447-461; Hiltbold, E.M., Poloso, N.J., Roche, P.A., MHC class II-peptide complexes and APC lipid rafts accumulate at the immunological synapse (2003) J. Immunol., 170, pp. 1329-1338; Wülfing, C., Tskvitaria-Fuller, I., Burroughs, N., Sjaastad, M.D., Klem, J., Schatzle, J.D., Interface accumulation of receptor/ligand couples in lymphocyte activation: Methods, mechanisms, and significance (2002) Immunol. Rev., 189, pp. 64-83; Poloso, N.J., Roche, P.A., Association of MHC class II-peptide complexes with plasma membrane lipid microdomains (2004) Curr. Opin. Immunol., 16, pp. 103-107; Anderson, H.A., Hiltbold, E.M., Roche, P.A., Concentration of MHC class II molecules in lipid rafts facilitates antigen presentation (2000) Nat. Immunol., 1, pp. 156-162; Meyer Zum Bueschenfelde, C.O., Unternaehrer, J., Mellman, I., Bottomly, K., Regulated recruitment of MHC class II and costimulatory molecules to lipid rafts in dendritic cells (2004) J. Immunol., 173, pp. 6119-6124; Szollosi, J., Horejsi, V., Bene, L., Angelisova, P., Damjanovich, S., Supramolecular Complexes of MHC Class I, MHC Class II, CD20, and Tetraspan Molecules (CD53, CD81, and CD82) at the Surface of a B Cell Line JY (1996) Journal of Immunology, 157 (7), pp. 2939-2946; Leitinger, B., Hogg, N., The involvement of lipid rafts in the regulation of integrin function (2002) Journal of Cell Science, 115 (5), pp. 963-972; Cherukuri, A., Cheng, P.C., Pierce, S.K., The role of the CD19/CD21 complex in B cell processing and presentation of complement-tagged antigens (2001) J. Immunol., 167, pp. 163-172; Sheets, E.D., Holowka, D., Baird, B., Critical role for cholesterol in Lyn-mediated tyrosine phosphorylation of FcepsilonRI and their association with detergent-resistant membranes (1999) Journal of Cell Biology, 145 (4), pp. 877-887. , DOI 10.1083/jcb.145.4.877; Jordan, S., Rodgers, W., T cell glycolipid-enriched membrane domains are constitutively assembled as membrane patches that translocate to immune synapses (2003) Journal of Immunology, 171 (1), pp. 78-87; Kaizuka, Y., Douglass, A.D., Vardhana, S., Dustin, M.L., Vale, R.D., The coreceptor CD2 uses plasma membrane microdomains to transduce signals in T cells (2009) J. Cell Biol., 185, pp. 521-534; Dustin, M.L., Membrane domains and the immunological synapse: Keeping T cells resting and ready (2002) J. Clin. Invest., 109, pp. 155-160; Almeida, C.R., Davis, D.M., Segregation of HLA-C from ICAM-1 at NK cell immune synapses is controlled by its cell surface density (2006) J. Immunol., 177, pp. 6904-6910; Delon, J., The immunological synapse (2000) Curr. Biol., 10, pp. R214; Anton Van Der Merwe, P., Davis, S.J., Shaw, A.S., Dustin, M.L., Cytoskeletal polarization and redistribution of cell-surface molecules during T cell antigen recognition (2000) Semin. Immunol., 12, pp. 5-21; Bossi, G., Trambas, C., Booth, S., Clark, R., Stinchcombe, J., Griffiths, G.M., The secretory synapse: The secrets of a serial killer (2002) Immunol. Rev., 189, pp. 152-160; Endt, J., McCann, F.E., Almeida, C.R., Urlaub, D., Leung, R., Pende, D., Davis, D.M., Watzl, C., Inhibitory receptor signals suppress ligation-induced recruitment of NKG2D to GM1-rich membrane domains at the human NK cell immune synapse (2007) Journal of Immunology, 178 (9), pp. 5606-5611; Gasser, S., Raulet, D.H., Activation and self-tolerance of natural killer cells (2006) Immunol. Rev., 214, pp. 130-142; Rubio, G., Férez, X., Sánchez-Campillo, M., Gálvez, J., Martí, S., Verdú, R., Hernández-Caselles, T., García-Peñarrubia, P., Cross-linking of MHC class I molecules on human NK cells inhibits NK cell function, segregates MHC I from the NK cell synapse, and induces intracellular phosphotyrosines (2004) J. Leukoc. Biol., 76, pp. 116-124; Kaizuka, Y., Douglass, A.D., Varma, R., Dustin, M.L., Vale, R.D., Mechanisms for segregating T cell receptor and adhesion molecules during immunological synapse formation in Jurkat T cells (2007) Proc. Natl. Acad. Sci. USA, 104, pp. 20296-20301; Brodin, P., Lakshmikanth, T., Mehr, R., Johansson, M.H., Duru, A.D., Achour, A., Salmon-Divon, M., Johansson, S., Natural killer cell tolerance persists despite significant reduction of self MHC class I on normal target cells in mice (2010) PLoS ONE, 5, pp. e1317; Carlin, L.M., Eleme, K., McCann, F.E., Davis, D.M., Intercellular transfer and supramolecular organization of human leukocyte antigen C at inhibitory natural killer cell immune synapses (2001) J. Exp. Med., 194, pp. 1507-1517; Fassett, M.S., Davis, D.M., Valter, M.M., Cohen, G.B., Strominger, J.L., Signaling at the inhibitory natural killer cell immune synapse regulates lipid raft polarization but not class I MHC clustering (2001) Proc. Natl. Acad. Sci. USA, 98, pp. 14547-14552; Faure, M., Barber, D.F., Takahashi, S.M., Jin, T., Long, E.O., Spontaneous clustering and tyrosine phosphorylation of NK cell inhibitory receptor induced by ligand binding (2003) J. Immunol., 170, pp. 6107-6114; Standeven, L.J., Carlin, L.M., Borszcz, P., Davis, D.M., Burshtyn, D.N., The actin cytoskeleton controls the efficiency of killer Ig-like receptor accumulation at inhibitory NK cell immune synapses (2004) J. Immunol., 173, pp. 5617-5625; Abeyweera, T.P., Merino, E., Huse, M., Inhibitory signaling blocks activating receptor clustering and induces cytoskeletal retraction in natural killer cells (2011) J. Cell Biol., 192, pp. 675-690; Labadia, M.E., Jeanfavre, D.D., Caviness, G.O., Morelock, M.M., Molecular regulation of the interaction between leukocyte function-associated antigen-1 and soluble ICAM-1 by divalent metal cations (1998) J. Immunol., 161, pp. 836-842; Tominaga, Y., Kita, Y., Satoh, A., Asai, S., Kato, K., Ishikawa, K., Horiuchi, T., Takashi, T., Affinity and kinetic analysis of the molecular interaction of ICAM-1 and leukocyte function-associated antigen-1 (1998) Journal of Immunology, 161 (8), pp. 4016-4022; Maenaka, K., Van Der Merwe, P.A., Stuart, D.I., Jones, E.Y., Sondermann, P., The human low affinity Fcgamma receptors IIa, IIb, and III bind IgG with fast kinetics and distinct thermodynamic properties (2001) J. Biol. Chem., 276, pp. 44898-44904; Dustin, M.L., Ferguson, L.M., Chan, P.Y., Springer, T.A., Golan, D.E., Visualization of CD2 interaction with LFA-3 and determination of the twodimensional dissociation constant for adhesion receptors in a contact area (1996) J. Cell Biol., 132, pp. 465-474; Sloan-Lancaster, J., Presley, J., Ellenberg, J., Yamazaki, T., Lippincott-Schwartz, J., Samelson, L.E., ZAP-70 association with T cell receptor zeta (TCRzeta): Fluorescence imaging of dynamic changes upon cellular stimulation (1998) J. Cell Biol., 143, pp. 613-624; Von Essen, M., Bonefeld, C.M., Siersma, V., Rasmussen, A.B., Lauritsen, J.P.H., Nielsen, B.L., Geisler, C., Constitutive and ligand-induced TCR degradation (2004) Journal of Immunology, 173 (1), pp. 384-393; Groves, J.T., Wulfing, C., Boxer, S.G., Electrical manipulation of glycan-phosphatidyl inositol-tethered proteins in planar supported bilayers (1996) Biophys. J., 71, pp. 2716-2723; Krogsgaard, M., Li, Q.J., Sumen, C., Huppa, J.B., Huse, M., Davis, M.M., Agonist/endogenous peptide-MHC heterodimers drive T cell activation and sensitivity (2005) Nature, 434, pp. 238-243; Dimasi, N., Sawicki, M.W., Reineck, L.A., Li, Y., Natarajan, K., Margulies, D.H., Mariuzza, R.A., Crystal structure of the Ly49I natural killer cell receptor reveals variability in dimerization mode within the Ly49 family (2002) J. Mol. Biol., 320, pp. 573-585; Natarajan, K., Boyd, L.F., Schuck, P., Yokoyama, W.M., Eliat, D., Margulies, D.H., Interaction of the NK cell inhibitory receptor Ly49A with H-2Dd: Identification of a site distinct from the TCR site (1999) Immunity, 11, pp. 591-601; O'Callaghan, C.A., Cerwenka, A., Willcox, B.E., Lanier, L.L., Bjorkman, P.J., Molecular competition for NKG2D: H60 and RAE1 compete unequally for NKG2D with dominance of H60 (2001) Immunity, 15, pp. 201-211; Borrego, F., Masilamani, M., Marusina, A.I., Tang, X., Coligan, J.E., The CD94/NKG2 family of receptors: From molecules and cells to clinical relevance (2006) Immunol. Res., 35, pp. 263-278
Keywords: animal cell; animal experiment; Animals; antigen recognition; article; cell maturation; cell membrane; Computer simulation; controlled study; dissociation; H-2 Antigens; Histocompatibility Antigens Class I; HLA antigen; HLA C antigen; Humans; immunological synapse; Immunological Synapses; intercellular adhesion molecule 1; Intercellular Adhesion Molecule-1; killer cell immunoglobulin like receptor 2DL1; Killer Cells, Natural; lymphocyte activation; lymphocyte function associated antigen 1; Lymphocyte Function-Associated Antigen-1; major histocompatibility antigen class 1; Membrane Microdomains; Mice; Models, Immunological; mouse; natural killer cell; natural killer cell receptor NKG2D; NK Cell Lectin-Like Receptor Subfamily A; NK Cell Lectin-Like Receptor Subfamily K; nonhuman; priority journal; protein assembly; Receptors, KIR; signal transduction; steady state; Vav protein

Access to computerised analysis of intrapartum cardiotocographs improves clinicians' prediction of newborn umbilical artery blood pH - Costa, A.; Santos, C.; Ayres-de-Campos, D.; Costa, C.; Bernardes, J. (BJOG: An International Journal of Obstetrics and GynaecologyBJOG Int. J. Obstet. Gynaecol., 2010)
Objective To evaluate the impact of access to computerised cardiotocograph (CTG) analysis on reproducibility and accuracy of clinicians' predictions of umbilical artery blood pH (UAB pH) and 5-minute Apgar score. Design Prospective evaluation of pre-recorded cases. Setting A tertiary-care university hospital. Population From databases of intrapartum CTGs acquired in singleton term pregnancies, 204 tracings with low signal loss and short time interval to delivery were consecutively selected. Methods Tracings were randomly assigned to computer analysis by the Omniview-SisPorto 3.5 ® system (study group n = 104) or to no analysis (control group n = 100). Three experienced clinicians evaluated all tracing printouts independently and were asked to predict the newborns' UAB pH and 5-minute Apgar scores from them. Main outcome measures Interobserver agreement (measured by the intraclass correlation coefficient [ICC]) and accuracy in prediction of neonatal outcomes with 95% CI. Results Agreement on prediction of UAB pH was significantly higher in the study group (ICC = 0.70; 95% CI 0.61-0.77) than in the control group (ICC = 0.43; 95% CI 0.21-0.60), and a trend towards better agreement was also seen in estimation of 5-minute Apgar scores (ICC = 0.55; 95% CI 0.38-0.68 versus ICC = 0.43; 95% CI 0.25-0.57). Observers predicted UAB pH values correctly within a 0.10 margin in 70% of cases in the study group (95% CI 0.61-0.79) versus 46% in the control group (95% CI 0.35-0.56). They predicted 5-minute Apgar scores within a margin of one in 81% of cases in the study group (95% CI 0.73-0.88) and in 70% of cases in the control group (95% CI 0.61-0.79). Conclusions Prediction of UAB pH is more reproducible and accurate when clinicians have access to computerised analysis of CTGs. © RCOG 2010 BJOG An International Journal of Obstetrics and Gynaecology.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: BIOGFdoi: 10.1111/j.1471-0528.2010.02645.xPubMed ID: 20618316Language of Original Document: EnglishCorrespondence Address: Costa, A.; Departamento de Ginecologia e Obstetrícia, Faculdade de Medicina da Universidade Do Porto, Alameda Hernani Monteiro, 4200-319 Porto, Portugal; email: cosantonia@gmail.comReferences: Ayres-De-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-10;Donker, D.K., Van Geijn, H.P., Hasman, A., Interobserver variation in the assessment of fetal heart rate recordings (1993) Eur J Obstet Gynecol Reprod Biol, 52, pp. 21-8; Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-65; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-5; Ayres-De-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto ® 3.5 - A central fetal monitoring station with online alerts based on computerized cardiotocogram+ST event analysis (2008) J Perinat Med, 36, pp. 260-4; Costa, A., Ayres-De-Campos, D., Costa, F., Santos, C., Bernardes, J., Prediction of neonatal acidemia by computer analysis of fetal heart rate and ST event signals (2009) Am J Obstet Gynecol, 201, pp. 464e1-6. , Jun 17. [Epub ahead of print]; Westerhuis, M., Van Horen, E., Kwee, A., Van Dertweel, I., Visser, G., Moons, K., Inter- and intra-observer agreement of intrapartum ST analysis of the fetal electrocardiogram in women monitored by STAN (2009) BJOG, 116, pp. 545-51; Ayres-De-Campos, D., Bernardes, J., Marsalb, K., Nickelsen, C., Makarainend, L., Banfield, P., Can the reproducibility of fetal heart rate baseline estimation be improved? (2004) Eur J Obstet Gynecol Reprod Biol, 112, pp. 49-54; Huch, A., Huch, C., Rooth, G., Guidelines for blood sampling and measurement of pH and blood gas values in Obstetrics (1994) Eur J Obstet Gynecol Reprod Biol, 54, pp. 165-75; Umbilical artery blood acid-base analysis (1996) Int J Gynecol Obstet, 52, pp. 305-10. , ACOG technical bulletin; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: A time for quality data (1994) Br J Obstet Gynaecol, 101, pp. 1054-63; Costa-Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynaecology: Inappropriateness, controversies and consequences (2005) BJOG, 112, pp. 667-9; Bland, J.M., Altman, D.G., Agreement between methods of measurement with multiple observations per individual (2007) J Biopharm Stat, 17, pp. 571-82; Chauhan, S.P., Klauser, C.K., Woodring, T.C., Sanderson, M., Magann, E.F., Morrison, J.C., Intrapartum nonreassuring fetal heart rate tracing and prediction of adverse outcomes: Interobserver variability (2008) Am J Obstet Gynecol, 199, pp. 623e1-e5; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., The value of computer assessment compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464
Keywords: access to information; Apgar score; arterial pH; article; Cardiotocography; clinical competence; computer analysis; computerised analysis; controlled study; delivery; Diagnosis, Computer-Assisted; diagnostic accuracy; Female; Fetal Blood; Fetal heart rate; Fetal monitoring; Gestational Age; human; Humans; Hydrogen-Ion Concentration; Infant, Newborn; male; neonatal acidaemia; Neonatology; newborn; observer variation; outcome assessment; prediction; Pregnancy; priority journal; Prospective Studies; prospective study; reproducibility; Umbilical Arteries; umbilical artery; university hospital

Adhesion of human leukocytes on mixtures of hydroxyl- and methyl-terminated self-assembled monolayers: Effect of blood protein adsorption - Barbosa, J.N.; Martins, M.C.L.; Freitas, S.C.; Gonçalves, I.C.; Águas, A.P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
The adhesion of human leukocytes to nanostructured surfaces with different chemical properties and the effect of protein adsorption were investigated. Selfassembled monolayers (SAMs) prepared with mixtures of methyl- and hydroxyl-terminated alkanethiols in different percentages on gold were used. The surfaces were preimmersed in distinct protein solutions (human serum albumin, human fibrinogen, and autologous plasma). Adherent leukocytes were analyzed both by light and SEM. SAMs submitted to pre-immersion in plasma presented higher numbers of adherent leukocytes in the pure OH-terminated SAM, whereas methyl-terminated surfaces accounted for the lowest number of adherent cells. We observed a general increase in the number of adherent human leukocytes as the percentage of OH groups on the surface of the SAMs increased for all the pre-immersion conditions investigated. The number of adherent human leukocytes is highly influenced by the pre-immersion conditions used, and this observation is particularly relevant in the case of the methyl-terminated SAMs. The results obtained demonstrate that surface chemistry has a major influence in leukocyte adhesion to biomaterials, and that pre-immersion in protein solutions has a determinant effect in leukocyte adhesion. © 2009 Wiley Periodicals, Inc.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32480PubMed ID: 19484768Language of Original Document: EnglishCorrespondence Address: Barbosa, J. N.; Divisão de Biomateriais, INEB-Instituto de Engenharia Biomédica, Universidade do Porto, Porto 4150-180, Portugal; email: judite@ineb.up.ptChemicals/CAS: Blood Proteins; Gold, 7440-57-5; Hydroxyl Radical, 3352-57-6References: Brodbeck, W.G., Nakayama, Y., Matsuda, T., Colton, E., Ziats, N.P., Anderson, J.M., Biomaterial surface chemistry dictates adherent monocyte/macrophage cytokine expression in vitro (2002) Cytokine, 18, pp. 311-319;Kao, W.Y.J., Evaluation of leukocyte adhesion on polyurethanes: The effects of shear stress and blood proteins (2000) Biomaterials, 21, pp. 2295-2303; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Nimeri, G., Ohman, L., Elwing, H., Wettero, J., Bengtsson, T., The influence of plasma proteins and platelets on oxygen radical production and F-actin distribution in neutrophils adhering to polymer surfaces (2002) Biomaterials, 23, pp. 1785-1795; Wettero, J., Bengtsson, T., Tengvall, P., C1q-independent activation of neutrophils by immunoglobulin M-coated surfaces (2001) J Biomed Mater Res, 57, pp. 550-558; Yung, L.Y.L., Colman, R.W., Cooper, S.L., Neutrophil adhesion on polyurethanes preadsorbed with high molecular weight kininogen (1999) Blood, 94, pp. 2716-2724; Eriksson, C., Nygren, H., Polymorphonuclear leukocytes in coagulating whole blood recognize hydrophilic and hydrophobic titanium surfaces by different adhesion receptors and show different patterns of receptor expression (2001) J Lab Clin Med, 137, pp. 296-302; Tang, L.P., Eaton, J.W., Mechanism of acute inflammatory response to biomaterials (1994) Cell Mater, 4, pp. 429-436; Tang, L.P., Eaton, J.W., Inflammatory responses to biomaterials (1995) Am J Clin Pathol, 103, pp. 466-471; Jenney, C.R., Anderson, J.M., Adsorbed serum proteins responsible for surface dependent human macrophage behavior (1999) J Biomed Mater Res, 49, pp. 435-447; Collier, T.O., Anderson, J.M., Protein and surface effects on monocyte and macrophage adhesion, maturation, and survival (2002) J Biomed Mater Res, 60, pp. 487-496; Yun, J.K., Defife, K., Colton, E., Stack, S., Azeez, A., Cahalan, L., Verhoeven, M., Anderson, J.M., Human monocytemacrophage adhesion and cytokine production on surface-modified poly(tetrafluoroethylene hexafluoropropylene) polymers with and without protein preadsorption (1995) J Biomed Mater Res, 29, pp. 257-268; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Mrksich, M., Tailored substrates for studies of attached cell culture (1998) Cell Mol Life Sci, 54, pp. 653-662; Mrksich, M., Model substrates for studying and controlling cell adhesion (2000) Abstr Pap Am Chem Soc, 219, pp. U572-U572; Rodrigues, S.N., Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27, pp. 5357-5367; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methylterminated alkanethiols self-assembled monolavers (2003) J Biomed Mater Res, 67 A, pp. 158-171. , Part A; Anderson, J.M., Biological responses to materials (2001) Annu Rev Mater Res, 31, pp. 81-110; Tang, L.P., Liu, L., Elwing, H.B., Complement activation and inflammation triggered by model biomaterial surfaces (1998) J Biomed Mater Res, 41, pp. 333-340; Bergman, A.J., Zygourakis, K., Migration of lymphocytes on fibronectin-coated surfaces: Temporal evolution of migratory parameters (1999) Biomaterials, 20, pp. 2235-2244; Taborelli, M., Eng, L., Descouts, P., Ranieri, J.P., Bellamkonda, R., Aebischer, P., Bovine serum-albumin conformation on methyl and amine functionalized surfaces compared by scanning force microscopy (1995) J Biomed Mater Res, 29, pp. 707-714; Liu, L., Elwing, H., Complement activation on thiol-modi.ed gold surfaces (1996) J Biomed Mater Res, 30, pp. 535-541; Sperling, C., Schweiss, R.B., Streller, U., Werner, C., In vitro hemocompatibility of self-assembled monolayers displaying various functional groups (2005) Biomaterials, 26, pp. 6547-6557; Hirata, I., Hioko, Y., Toda, M., Kitazawa, T., Murakami, Y., Kitano, E., Kitamura, H., Iwata, H., Deposition of complement protein C3b on mixed self-assembled monolayers carrying surface hydroxyl and methyl groups studied by surface plasmon resonance (2003) J Biomed Mater Res, 66 A, pp. 669-676. , Part A; Kalltorp, M., Oblogina, S., Jacobsson, S., Karlsson, A., Tengvall, P., Thomsen, P., In vivo cell recruitment, cytokine release and chemiluminescence response at gold, and thiol functionalized surfaces (1999) Biomaterials, 20, pp. 2123-2137; Brash, J.L., Tenhove, P., Protein adsorption studies on standard polymeric materials (1993) J Biomater Sci Polym Ed, 4, pp. 591-599; Brash, J.L., Tenhove, P., Effect of plasma dilution on adsorption of fibrinogen to solid-surfaces (1984) Thromb Haemost, 51, pp. 326-330; Tang, L.P., Ugarova, T.P., Plow, E.F., Eaton, J.W., Molecular determinants of acute inflammatory responses to biomaterials (1996) J Clin Invest, 97, pp. 1329-1334; Thomsen, P., Gretzer, C., Macrophage interactions with modified material surfaces (2001) Curr Opin Solid State Mater Sci, 5, pp. 163-176; Werthen, M., Sellborn, A., Kalltorp, M., Elwing, H., Thomsen, P., In vitro study of monocyte viability during the initial adhesion to albumin- and fibrinogen-coated surfaces (2001) Biomaterials, 22, pp. 827-832; Wettero, J., Bengtsson, T., Tengvall, P., Complement activation on immunoglobulin G-coated hydrophobic surfaces enhances the release of oxygen radicals from neutrophils through an actin-dependent mechanism (2000) J Biomed Mater Res, 51, pp. 742-751; Jenney, C.R., Anderson, J.M., Adsorbed IgG: A potent adhesive substrate for human macrophages (2000) J Biomed Mater Res, 50, pp. 281-290; Lindblad, M., Lestelius, M., Johansson, A., Tengvall, P., Thomsen, P., Cell and soft tissue interactions with methyl- and hydroxyl-terminated alkane thiols on gold surfaces (1997) Biomaterials, 18, pp. 1059-1068; Roach, P., Farrar, D., Perry, C.C., Interpretation of protein adsorption: Surface-induced conformational changes (2005) J Am Chem Soc, 127, pp. 8168-8173; Barbosa, J.N., Barbosa, M.A., Aguas, A.P., Adhesion of human leukocytes to biomaterials: An in vitro study using alkanethiolate monolayers with different chemically functionalized surfaces (2003) J Biomed Mater Res, 65 A, pp. 429-434. , Part A; Barbosa, J.N., Barbosa, M.A., Aguas, A.P., Inflammatory responses and cell adhesion to self-assembled monolayers of alkanethiolates on gold (2004) Biomaterials, 25, pp. 2557-2563; Barbosa, J.N., Barbosa, M.A., Aguas, A.P., Inflammatory cell recruitment and adhesion to methyl-terminated selfassembled monolayers: Effect of implantation time (2005) Microsc Res Tech, 66, pp. 37-42; Barbosa, J.N., Madureira, P., Barbosa, M.A., Aguas, A.P., The attraction of Mac-1(+) phagocytes during acute inflammation by methyl-coated self-assembled monolayers (2005) Biomaterials, 26, pp. 3021-3027
Keywords: Adherent cells; Adhesion; Adsorption; Alkanethiols; article; Biological materials; biomaterial; Blood protein adsorption; Blood Proteins; cell adhesion; Cell Count; Chemical properties; gold; human; human cell; Human leukocytes; Human serum albumins; Humans; hydroxyl group; Hydroxyl Radical; Hydroxyl-terminated; immersion; Inflammatory response; leukocyte adherence; Leukocyte adhesion; Leukocytes; Nanostructured materials; Nanostructured surface; Nanostructured surfaces; OH group; Protein adsorption; protein blood level; Protein solution; Proteins; Sams; Scanning electron microscopy; Self assembled monolayers; Self-assembled monolayers; SEM; Surface chemistry; Surface Properties

Anti-adhesion and antiproliferative cellulose triacetate membrane for prevention of biomaterial-centred infections associated with Staphylococcus epidermidis - Extremina, C.I.; Fonseca, A.F.d.; Granja, P.L.; Fonseca, A.P. (International Journal of Antimicrobial AgentsInt. J. Antimicrob. Agents, 2010)
The initial step in preventing biomaterial-associated infections consists of preventing bacterial adhesion to the device surface. One possible approach is the design of antibiotic-releasing biomaterials. Cellulose triacetate (CTA) membranes with the antibiotic imipenem (IPM) entrapped (CTA-IPM) were prepared. The material was characterised in terms of surface morphology by scanning electron microscopy, surface free energy of interaction and X-ray photoelectron spectroscopy (XPS). Antibiotic release studies were also performed. In vitro adhesion of Staphylococcus epidermidis RP62A to CTA-IPM was investigated using a modified microtitre plate assay, and the antibacterial activity of the CTA-IPM membrane was assessed by a modified Kirby-Bauer test, which showed effective entrapment of the antibiotic as confirmed by XPS and hydrophilicity assays. Release studies showed that this drug-polymer conjugate serves as an adequate reservoir for sustained release of IPM over a period of 71 h at an effective bacteriostatic concentration. Moreover, bacterial adhesion tests showed a statistically significant decrease in the adhesion of S. epidermidis RP62A to CTA-IPM compared with its adhesion to CTA alone. The present innovative approach is capable of providing a membrane with anti-adhesive and antiproliferative properties, thus encouraging in vivo studies to provide a better simulation of the clinical situation. © 2009 Elsevier B.V. and the International Society of Chemotherapy.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: IAAGEdoi: 10.1016/j.ijantimicag.2009.09.017PubMed ID: 19942411Language of Original Document: EnglishCorrespondence Address: Extremina, C.I.; REQUIMTE, Faculdade de Farmácia, Universidade do Porto, Rua Aníbal Cunha 164, 4050-047 Porto, Portugal; email: extremina@gmail.comChemicals/CAS: cellulose triacetate, 9012-09-3; cilastatin plus imipenem, 92309-29-0; Anti-Bacterial Agents; Biocompatible Materials; Cellulose, 9004-34-6; Imipenem, 74431-23-5; cellulose triacetate, 9012-09-3Tradenames: tienam, Merck Sharp and Dohme, GermanyManufacturers: Eastman Kodak, Netherlands; Merck Sharp and Dohme, GermanyReferences: Darouiche, R.O., Treatment of infections associated with surgical implants (2004) N Engl J Med, 350, pp. 1422-1429;Fonseca, A.P., Extremina, C., Fonseca, A.F., Sousa, J.C., Effect of subinhibitory concentration of piperacillin/tazobactam on Pseudomonas aeruginosa (2004) J Med Microbiol, 53, pp. 903-910; Donelli, G., Francolini, I., Piozzi, A., Di Rosa, R., Marconi, W., New polymer-antibiotic systems to inhibit bacterial biofilm formation: a suitable approach to prevent central venous catheter-associated infections (2002) J Chemother, 14, pp. 501-507; Akiyama, H., Okamoto, S., Prophylaxis of indwelling urethral catheter infection: clinical experience with a modified Foley catheter and drainage system (1979) J Urol, 121, pp. 40-42; Granja, P.L., Baquey, C., Pouységu, L., Bareille, R., De Jéso, B., Barbosa, M.A., Cellulose-based biomaterials for bone regeneration: hemi-synthesis and characterisation (1996) Proceedings of polymers in medicine and surgery-PIMS'96, pp. 73-80. , Glasgow, UK; Elam, J.H., Karlsson, C.H., Nygren, H., Pre-adsorption of cellulose ether onto polymer surfaces: adsorption of adhesins and platelet activation (1992) Biomaterials, 14, pp. 233-237; Fonseca, A.P., Granja, P.L., Nogueira, J.A., Oliveira, D.R., Barbosa, M.A., Staphylococcus epidermidis RP62A adhesion to chemically modified cellulose derivatives (2001) J Mater Sci Mater Med, 12, pp. 543-548; Performance standards for antimicrobial susceptibility testing (2006) Sixteenth informational supplement. Document M100-S16. Wayne, PA: CLSI, , Clinical and Laboratory Standards Institute; Vacheethasanee, K., Temenoff, J.S., Higashi, J.M., Gary, A., Anderson, J.M., Bayston, R., Bacterial surface properties of clinically isolated Staphylococcus epidermidis strains determine adhesion on polyethylene (1998) J Biomed Mater Res, 42, pp. 425-432; Bhat, N.V., Wavhal, D.S., Preparation of cellulose triacetate pervaporation membrane by ammonia plasma treatment (2000) J Appl Polym Sci, 76, pp. 258-265; Amaral, I.F., Granja, P.L., Melo Luis, V., Saramago, B., Barbosa, M.A., Functionalization of chitosan membranes through phosphorylation: atomic force microscopy, wettability, and cytotoxicity studies (2006) J Appl Polym Sci, 102, pp. 276-284; Thomas, M.J.K., Ando, D.J., (1996) Ultraviolet and visible spectroscopy: analytical chemistry by open learning, , Wiley, New York, NY; (1992) High resolution XPS of organic polymers: the Scienta ESCA300 database, , Beamson G., and Briggs D. (Eds), John Wiley & Sons Ltd, Chichester, UK; Yigong Ge, Wikler, M.A., Sahm, D.F., Blosser-Middleton, R.S., Karlowsky, J.A., In vitro antimicrobial activity of doripenem, a new carbapenem (2004) Antimicrob Agents Chemother, 48, pp. 1384-1396; Martínez-Martínez, L., Pascual, A., Giglio, M.I., Perea, E.J., Effect of subinhibitory concentrations of β-lactams on the production of slime, surface hydrophobicity and adhesion of Staphylococcus epidermidis [in Spanish] (1991) Enferm Infecc Microbiol Clin, 9, pp. 543-546
Keywords: Adhesion; Anti-Bacterial Agents; antibacterial activity; Antimicrobial agents; article; Bacterial adhesion; bacterial growth; bacteriostasis; bacterium adherence; Biocompatible Materials; biomaterial; Cellulose; Cellulose triacetate; cilastatin plus imipenem; controlled study; device infection; drug screening; Equipment and Supplies; growth inhibition; Humans; hydrophilicity; Imipenem; in vitro study; infection prevention; Membranes; Microbial Sensitivity Tests; microtiter plate assay; nonhuman; priority journal; Prosthesis-Related Infections; Scanning electron microscopy; Staphylococcus epidermidis; surface property; sustained drug release; X ray photoelectron spectroscopy

Assessment of Disagreement: A New Information-Based Approach - Costa-Santos, C.; Antunes, L.; Souto, A.; Bernardes, J. (Annals of EpidemiologyAnn. Epidemiol., 2010)
Purpose: Disagreement on the interpretation of diagnostic tests and clinical decisions remains an important problem in medicine. As no strategy to assess agreement seems to be fail-safe to compare the degree of agreement, or disagreement, we propose a new information-based approach to assess disagreement. Methods: The sum over all logarithms of possible outcomes of a variable is a valid measure of the amount of information contained in the variable. The proposed measure is based on the amount of information contained in the differences between two observations. This measure is normalized and satisfies the flowing properties: it is a metric, scaled invariant and it has differential weighting. Results: Two real examples and a simulation were used to illustrate the usefulness of the proposed measure to compare the degree of disagreement. Conclusions: Used as complement to the existing methods, we believe our approach can be useful to compare the degree of disagreement among different populations. © 2010 Elsevier Inc.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: ANNPEdoi: 10.1016/j.annepidem.2010.02.011Language of Original Document: EnglishCorrespondence Address: Costa-Santos, C.; Biostatistics and Medical Informatics Department, Faculty of Medicine, University of Porto, Al. Prof. Hernâni Monteiro, 4200-319 Porto, Portugal; email: csantos@med.up.ptReferences: Bland, M., (2000) An introduction to medical statistics, , Oxford University Press, Oxford;Costa Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynecology: inappropriateness, controversies and consequences (2005) Br J Obstet Gynaecol, 112, pp. 667-669; Gow, R.M., Barrowman, N.J., Lai, L., Moher, D., A review of five cardiology journals found that observer variability of measured variables was infrequently reported (2008) J Clin Epidemiol, 61, pp. 394-401; Luiz, R.R., Szklo, M., More than one statistical strategy to assess agreement of quantitative measurements may usefully be reported (2005) J Clin Epidemiol, 58, pp. 215-216; de Vet, H., Observer reliability and agreement (1999) Encyclopedia of Biostatistics, pp. 3123-3127. , Wiley, Chichester, P. Armitage, T. Colton (Eds.); Shrout, P.E., Fleiss, J.L., Intraclass correlation: uses in assessing rater reliability (1979) Psychol Bull, 88, pp. 420-428; Burdock, E.I., Fleiss, J.L., Hardesty, A.S., A new view of interobserver agreement (1963) Psychol Bull, 16, pp. 373-384; McGraw, K.O., Wong, S.P., Forming inferences about some intraclass correlation coefficients (1996) Psychol Methods, 1, pp. 30-46; Muller, R., Buttner, P., A critical discussion of intraclass correlation coefficients (1994) Stat Med, 13, pp. 2465-2476; Steiner, D.L., Norman, G.R., (2003) Health measurements scales. A practical guide to their development and use, , Oxford University Press, Oxford; Lee, D., Koh, D., Ong, C.N., Statistical evaluation of the agreement between two methods for measuring a quantitative variable (1989) Comput Biol Med, 19, pp. 61-70; Lin, L.K., A concordance correlation coefficient to evaluate reproducibility (1989) Biometrics, 45, pp. 255-268; Nickerson, C.A.E., A note on " A Concordance Correlation Coefficient to Evaluate Reproducibility" (1997) Biometrics, 53, pp. 1503-1507; Atkinson, G., Nevill, A., Comment on the " Use of Concordance Correlation to Assess the Agreement between Two Variables" (1997) Biometrics, 53, pp. 775-777; Bland, J.M., Altman, D.G., Statistical methods for assessing two methods of clinical measurement (1986) Lancet, 1, pp. 307-310; Luiz, R.R., Costa, A.J., Kale, P.L., Werneck, G.L., Assessment of agreement of a quantitative variable: a new graphical approach (2003) J Clin Epidemiol, 56, pp. 963-967; Monti, K.L., Folded empirical distribution function curves-mountain plots (1995) Am Stat, 33, pp. 525-527; Shannon, I., A mathematical theory of communication (1948) Bell System Tech J, 27, pp. 379-423. , 623-656; Bland, J.M., Altaman, D.G., Measuring agreement in method comparison studies (1999) Stat Methods Med Res, 8, pp. 135-160
Keywords: analysis of variance; Apgar score; article; Blood Pressure Determination; blood pressure measurement; correlation coefficient; human; Humans; information science; Information Theory; intermethod comparison; mathematical computing; measurement error; medical research; metric system; Models, Statistical; observer variation; priority journal; probability; process model; reliability; Reproducibility of Results; scale up; standard; Statistical analysis; statistical model; statistics; Statistics as Topic; systolic blood pressure; validity; variance

Bioactivity of immobilized EGF on self-assembled monolayers: Optimization of the immobilization process - Gonçalves, R.; Martins, M.C.L.; Oliveira, M.J.; Almeida-Porada, G.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
Last trends in Biomaterials focus the mimic of cellular environments capable to control cellular responses. Epidermal growth factor (EGF) is a pleiotropic cytokine known to regulate cell proliferation, differentiation, and death. This study aims to optimize the immobilization of EGF on 11-mercapto-1-undecyl-tetra(ethylene)glycol (EG4) - self-assembled monolayers (SAMs) and to establish a new model surface to study EGF-mediated signaling. Gold substrates were modified with a monolayer of EG4 and N,N′- carbonyldiimidazole (CDI) was used to activate hydroxyl terminated groups of EG4-SAMs. EGF was then immobilized on activated EG4-SAMs at pH 7.4, 4°C, and 100 rpm. Different immobilization reaction times were tested as well as different CDI concentrations to optimize the reaction conditions and obtain a range of immobilized EGF concentrations on the surfaces. Surface characterization of EGF-SAMs was performed using radiolabeling, water contact angle measurements, X-ray photoelectron spectroscopy, and ELISA. Phosphorylation of EGFR on BT-20 breast cancer cell line by EGF-SAMs was tested by immunostaining. EGF was successfully immobilized on EG4-SAMs, at 4°C and pH 7.4 in a range of concentrations from 3.6 ± 0.8 to 17.6 ± 1.5 ng/cm 2. The concentration of EGF increases with immobilization time and with the CDI concentration reaching the maximum for surfaces activated with 30 mg/mL of CDI after 48 h. The bioactivity of EGF-SAMs was confirmed by immunostaining of phospho-EGFR of BT-20 cells. This study described EGF immobilization on EG4-SAMs at different concentrations, which could be important surface models to study specific protein interactions at the molecular level evolving EGF-family of proteins. © 2010 Wiley Periodicals, Inc. J.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32723PubMed ID: 20198690Language of Original Document: EnglishCorrespondence Address: Gonçalves, R.; INEB, Biomaterials Division, NEWTherapies Group, R. Campo Alegre, 823, Porto 4150-180, Portugal; email: raquelg@ineb.up.ptChemicals/CAS: epidermal growth factor, 62229-50-9; gold, 7440-57-5; Biocompatible Materials; Epidermal Growth Factor, 62229-50-9; Gold, 7440-57-5; Imidazoles; N,N-carbonyldiimidazole, 530-62-1; Polyethylene Glycols; Receptor, Epidermal Growth Factor, 2.7.10.1; Sulfhydryl CompoundsReferences: Singh, A., Harris, R.C., Autocrine, paracrine and juxtacrine signaling by EGFR ligands (2005) Cell Signal, 17, pp. 1183-1193;Luca, A., Carotenuto, A., Rachiglio, A., Gallo, M., Maiello, M.R., Aldinucci, D.L., Pinto, A., Normanno, N., The role of the EGFR signaling in tumor microenvironment (2008) J Cell Physiol, 214, pp. 559-567; Stenflo, J., Stenberg, Y., Muranyi, A., Calcium-binding EGF-like modules in coagulation proteinases: Function of the calcium ion in module interactions (2000) Biochim Biophys Acta, 1477, pp. 51-63; Leong, K., Karsan, A., Recent insights in the role of notch signaling in tumorigenesis (2006) Blood, 107, pp. 2223-2233; Sakamoto, K., Chao, W.S., Katsube, K.-I., Yamaguchi, A., Distinct roles of EGF repeats for the Notch signaling system (2005) Experimental Cell Research, 302 (2), pp. 281-291. , DOI 10.1016/j.yexcr.2004.09.016, PII S0014482704005658; Savage, C., Hash, J.H., Cohen, S., Epidermal growth factor (1973) J Biol Chem, 248, pp. 7669-7672; Bell, G., Fong, N.M., Stempien, M.M., Wormsted, M.A., Caput, D., Ku, L., Urdea, M.S., Sanchez-Pescador, R., Human epidermal growth factor precursor: cDNA sequence, expression in vitro and gene organization (1986) Nucleic Acids Res, 14, pp. 8427-8446; Carpenter, G., Cohen, S., Epidermal growth factor (1990) J Biol Chem, 265, pp. 7709-7712; Schlessinger, J., Allosteric regulation of epidermal growth factor receptor kinase (1986) J Cell Biol, 103, pp. 2067-2072; Mitamura, T., Higashiyama, S., Taniguchi, N., Klagsbrun, M., Mekada, E., Diphtheria toxin binds to the epidermal growth factor (EGF)-like domain of human heparin-binding EGF-like growth factor/diphtheria toxin receptor and inhibits specifically its mitogenic activity (1995) J Biol Chem, 270, pp. 1015-1019; Wong, R.W.C., Guillaud, L., The role of epidermal growth factor and its receptors in mammalian CNS (2004) Cytokine Growth Factor Rev, 15, pp. 147-156; Mrksich, M., What can surface chemistry do for cell biology? (2002) Curr Opion Chem Biol, 6, pp. 794-797; Tohda, S.K.H., Murakami, N., Sakano, S., Nara, N., Diverse effects of the notch ligands Jagged1 and Delta1 on the growth and differentiation of primary acute myeloblastic leukemia cells (2005) Exp Hematol, 33, pp. 558-563; France, R.M., Short, R.D., Dawson, R.A., MacNeil, S., Attachment of human keratinocytes to plasma co-polymers of acrylic acid/octa-1,7-diene and allyl amine/octa-1,7-diene (1998) Journal of Materials Chemistry, 8 (1), pp. 37-42; Love, J., Estroff, L.A., Kriebel, J.K., Nuzzo, R.G., Whitesides, G.M., Selfassembled monolayers of thiolates on metals as a form of nanotechnology (2005) Chem Rev, 105, pp. 1103-1169; Saha, K.P.J., Schaffer, D.V., Healy, K.E., Designing synthetic materials to control stem cell phenotype (2007) Curr Opin Chem Biol, 11, pp. 381-387; Barbosa, J.B.M., Águas, A.P., Adhesion of human leukocytes to biomaterials: An in vitro study using alkanethiolate monolayers with different chemically functionalized surfaces (2003) J Biomed Mater Res A, 65, pp. 429-434; Rodrigues, S.N.G.I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27, pp. 5357-5367; Barrias, C., Martins, M.C., Almeida-Porada, G., Barbosa, M.A., Granja, P.L., The correlation between the adsorption of adhesive proteins and cell behaviour on hydroxyl-methyl mixed self-assembled monolayers (2009) Biomaterials, 30, pp. 307-316; Curran, J.M.C.R., Hunt, J.A., The guidance of human mesenchymal stem cell differentiation in vitro by controlled modifications to the cell substrate (2006) Biomaterials, 27, pp. 4783-4793; Lee, M., Brass, D.A., Morris, R., Composto, R.J., Ducheyne, P., The effect of non-specific interactions on cellular adhesion using model surfaces (2005) Biomaterials, 26, pp. 1721-1730; Martins, M.C.L.C.S., Freitas, S.C., Salgueiro, P., Ratner, B.D., Barbosa, M.A., Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide (2009) J Biomed Mater Res A, 88, pp. 162-173; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Silva, M.F., Ion beam deposition of Mn-Ir spin valves (1999) IEEE Trans Magn, 35, pp. 4361-4367; Martins, M.C.L.R.B., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl- Terminated self-assebled monolyers (2003) J Biomed Mater Res, 67, pp. 158-171; Barrias, C.C.M.M., Bidarra, S., Sámiranda, M.C., Barbosa, M.A., Adsorption of a therapeutic enzyme to self-assembled monolayers: Effect of the surface chemistry and solution pH on the amount and activity of adsorbed enzyme (2005) Biomaterials, 26, pp. 2695-2704; (1993) Iodine-125. A Guide to Radioiodination Techniques, , Amersham Life Science. Amersham Place, Little Chalfont, Bucks: Amersham International plc; Zhang, J., Matthews, J.M., Ward, L.D., Simpson, R.J., Disruption of the disulfide bonds of recombinant murine interleukin-6 induces formation of a partially unfolded state (1997) Biochemistry, 36, pp. 2380-2389; Solomons, T., (1996) Organic Chemistry, , New York: Wiley; Lukkari, J., Meretoja, M., Kartio, I., Laajalehto, K., Rajamaki, M., Lindstrom, M., Kankare, J., Organic thiosulfates (bunte salts): Novel surface-active sulfur compounds for the preparation of selfassembled monolayers on gold (1999) Langmuir, 15, pp. 3529-3537; Castner, D.G., Hinds, K., Grainger, D.W., X-ray photoelectron spectroscopy sulfur 2p study of organic thiol and bisulfide binding interactions with gold surfaces (1996) Langmuir, 12 (21), pp. 5083-5086; Molina, R., Espinós, J.P., Yubero, F., Erra, P., González-Elipe, A.R., XPS analysis of down stream plasma treated wool: Influence of the nature of the gas on the surface modification of wool (2005) Appl Surf Sci, 252, pp. 1417-1429; Flynn, N., Tran, T.N.T., Cima, M.J., Langer, R., Long-term stability of self-assembled monolayers in biological media (2003) Langmuir, 19, pp. 10909-10915; Willey, T., Vance, A.L., Van Buuren, T., Bostedt, C., Terminello, L.J., Fadley, C.S., Rapid degradation of alkanethiol-based self-assembled monolayers on gold in ambient laboratory conditions (2005) Surf Sci, 576, pp. 188-196; Lage, A., Crombet, T., González, G., Targeting epidermal growth factor receptor signaling: Early results and future trends in oncology (2003) Trends Mol Med, 35, pp. 327-336; Lee, H., Hu, M., Reilly, R.M., Allen, C., Apoptotic epidermal growth factor (EGF)- Conjugated block copolymer micelles as a nanotechnology platform for targeted combination therapy (2007) Mol Pharm, 4, pp. 769-781; Nakaji-Hirabayashi, T., Kato, K., Arima, Y., Iwata, H., Oriented immobilization of epidermal growth factor onto culture substrates for the selective expansion of neural stem cells (2007) Biomaterials, 28, pp. 3517-3529; Stefonek, T., Masters, K.S., Immobilized gradients of epidermal growth factor promote accelerated and directed keratinocyte migration (2007) Wound Repair Regen, 15, pp. 847-855; Ito, Y., Li, J.S., Takahashi, T., Imanishi, Y., Okabayashi, Y., Kido, Y., Kasuga, M., Enhancement of the mitogenic effect by artificial juxtacrine stimulation using immobilized EGF (1997) J Biochem, 121, pp. 514-520; Wang, Q., Bohn, P.W., Surface composition gradients of immobilized cell signaling molecules: Epidermal growth factor on gold (2006) Thin Solid Films, 513, pp. 338-346; Karakecili, A., Satriano, C., Gumusderelioglu, M., Marletta, G., Enhancement of fibroblastic proliferation on chitosan surfaces by immobilized epidermal growth factor (2008) Acta Biomater, 4, pp. 989-996; Hodneland, C., Lee, Y.S., Min, D.H., Mrksich, M., Selective immobilization of proteins to self-assembled monolayers presenting active site-directed capture ligands (2002) PNAS, 99, pp. 5048-5052; Liu, L., Chen, S., Giachelli, C.M., Ratner, B.D., Jiang, S., Controlling osteopontin orientation on surfaces to modulate endothelial cell adhesion (2005) J Biomed Mater Res A, 74, pp. 23-31; Kim, H., Noh, J., Hara, M., Lee, H., Characterization of mixed selfassembled monolayers for immobilization of streptavidin using chemical force microscopy (2008) Ultramicroscopy, 108, pp. 1140-1143; Delamarche, E., Sundarababu, G., Biebuyck, H., Michel, B., Gerber, Ch., Sigrist, H., Wolf, H., Mathieu, H.J., Immobilization of antibodies on a photoactive self-assembled monolayer on gold (1996) Langmuir, 12 (8), pp. 1997-2006; Gonçalves, R., Martins, M.C.L., Almeida-Porada, G., Barbosa, M.A., Induction of notch signaling by immobilization of jagged-1 on self-assembled monolayers (2009) Biomaterials, 30, pp. 6879-6887; Mrksich, M., Whitesides, G.M., Using Self-Assembled Monolayers That Present Oligo(ethylene glycol) Groups to Control the Interactions of Proteins with Surfaces (1997) ACS Symposium Series, 680, pp. 361-373; Chen, G., Ito, Y., Gradient micropattern immobilization of EGF to investigate the effect of artificil juxtacrine stimulation (2001) Biomaterials, 22, pp. 2453-2457; Allewood, D., Nielsen, K., Alewwod, P.F., Craik, D.J., Andrews, P., Nerrie, M., White, S., Nice, E.C., The role of disulfide bonds in the structure and function of murine epidermal growth factor (mEGF) (2005) Growth Factors, 23, pp. 97-110; Morton, R., Mangroo, D., Gerber, G.E., A novel method of complete activation by carbonyldiimidazole: Application to esther synthesis (1988) Can J Chem, 66, pp. 1701-1705; Stollner, D., Scheller, F.W., Warsinke, A., Activation of cellulose membranes with 1,1-carbonyldiimidazole or 1-cyano-4-dimethylaminopyridinium tetrafluoroborate as a basis for the development of immunosensors (2002) Anal Biochem, 304, pp. 157-165; Crowley, S.C., Chan, K.C., Walters, R.R., Optimization of protein immobilization on 1,1′-carbonyldiimidazole- activated diol-bonded silica (1986) J Chromatogr A, 359, pp. 359-368; Mateus, A., Seruca, R., Machado, J.C., Keller, G., Oliveira, M.J., Suriano, G., Luber, B., EGFR regulates RhoA-GTP dependent cell motility in E-cadherin mutant cells (2007) Hum Mol Genet, 16, pp. 1639-1647; Garcia, R., Franklin, R.A., Mccubrey, J.A., EGF induces cell motility and multi-drug resistance gene expression in breast cancer cells (2006) Cell Cycle, 5, pp. 2820-2826
Keywords: Adsorption; Angle measurement; article; Biocompatible Materials; Biological materials; Breast cancer cells; cancer cell culture; Carbonyldiimidazole; Cell culture; Cell immobilization; Cell Line, Tumor; cell proliferation; Cellular environment; Cellular response; Concentration (process); Concentration of; Contact angle; controlled study; Cytokines; EGF; Electron energy levels; enzyme linked immunosorbent assay; Enzyme-Linked Immunosorbent Assay; epidermal growth factor; Epidermal growth factors; Ethylene; Glycols; gold; Gold substrates; human; human cell; Humans; Hydroxyl-terminated; Imidazoles; Immobilization process; Immobilization reaction; immunofluorescence; immunohistochemistry; Immunostaining; Molecular levels; Nanostructured materials; Nanostructured surface; Nanostructured surfaces; New model; Optimization; Phosphorylation; Photoelectron spectroscopy; Polyethylene Glycols; Protein adsorption; protein immobilization; protein interaction; protein phosphorylation; Proteins; Radiolabeling; Radioligand Assay; Reaction conditions; reaction optimization; Receptor, Epidermal Growth Factor; Sams; self assembled monolayer; Self assembled monolayers; Self-assembled monolayers; Sulfhydryl Compounds; Surface characterization; Surface functionalization; Surface models; Surface Properties; Water contact angle measurement; X ray photoelectron spectroscopy

Chitosan-based gene delivery vectors targeted to the peripheral nervous system - Oliveira, H.; Pires, L.R.; Fernandez, R.; Martins, M.C.L.; Simões, S.; Pêgo, A.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
A non-toxic, targeted, simple and efficient system that can specifically transfect peripheral sensorial neurons can pave the way towards the development of new therapeutics for the treatment of peripheral neuropathies. In this study chitosan (CH), a biodegradable polymer, was used as the starting material in the design of a multicomponent vector targeted to the peripheral nervous system (PNS). Polycation-DNA complexes were optimized using imidazole-and thiol-grafted CH (CHimiSH), in order to increase transfection efficiency and allow the formation of ligand conjugated nanocomplexes, respectively. The 50 kDa non-toxic fragment from the tetanus toxin (HC), shown to interact specifically with peripheral neurons and undergo retrograde transport, was grafted to the binary complex via a bi-functional poly(ethylene glycol) (HC-PEG) reactive for the thiol moieties present in the complex surface. The targeting of the developed nanocomplexes was assessed by means of internalization and transfection studies in the ND7/23 (neuronal) vs. NIH 3T3 (fibroblast) cell lines. Targeted transfection was further confirmed in dorsal root ganglion dissociated primary cultures. A versatile, multi-component nanoparticle system that successfully targets and transfects neuronal cell lines, as well as dorsal root ganglia (DRG) primary neuron cultures was obtained for the 1.0 (w/w) HC-PEG/DNA formulation. © 2010 Wiley Periodicals, Inc.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32874PubMed ID: 20734332Language of Original Document: EnglishCorrespondence Address: Pêgo, A. P.; INEB, Instituto de Engenharia Biomédica, Universidade Do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: apego@ineb.up.ptChemicals/CAS: DNA, 9007-49-2; chitosan, 9012-76-4; imidazole, 1467-16-9, 288-32-4; macrogol, 25322-68-3; Cations; Chitosan, 9012-76-4; DNA, 9007-49-2; Polyethylene GlycolsTradenames: Chimarin, medicarb, SwedenManufacturers: medicarb, SwedenReferences: Rodriguez, F.J., Valero-Cabre, A., Navarro, X., Regeneration and functional recovery following peripheral nerve injury (2004) Drug Discov Today, 1, pp. 177-185;Apfel, S.C., Neurotrophic factors in peripheral neuropathies: Therapeutic implications (1999) Brain Pathol, 9, pp. 393-413; Apfel, S.C., Is the therapeutic application of neurotrophic factors dead? (2002) Ann Neurol, 51, pp. 8-11; Glorioso, J.C., Mata, M., Fink, D.J., Therapeutic gene transfer to the nervous system using viral vectors (2003) J Neurovirol, 9, pp. 165-172; Fishman, P.S., Carrigan, D.R., Retrograde transneuronal transfer of the C-fragment of tetanus toxin (1987) Brain Res, 406, pp. 275-279; Evinger, C., Erichsen, J.T., Transsynaptic retrograde transport of fragment C of tetanus toxin demonstrated by immunohistochemical localization (1986) Brain Res, 380, pp. 383-388; Figueiredo, D.M., Hallewell, R.A., Chen, L.L., Fairweather, N.F., Dougan, G., Savitt, J.M., Parks, D.A., Fishman, P.S., Delivery of recombinant tetanus-superoxide dismutase proteins to central nervous system neurons by retrograde axonal transport (1997) Exp Neurol, 145 (2 PART 1), pp. 546-554; Fishman, P.S., Savitt, J.M., Farrand, D.A., Enhanced CNS uptake of systemically administered proteins through conjugation with tetanus C-fragment (1990) J Neurol Sci, 98, pp. 311-325; Coen, L., Osta, R., Maury, M., Brulet, P., Construction of hybrid proteins that migrate retrogradely and transynaptically into the central nervous system (1997) Proc Natl Acad Sci USA, 94, pp. 9400-9405; Knight, A., Carvajal, J., Schneider, H., Coutelle, C., Chamberlain, S., Fairweather, N., Non-viral neuronal gene delivery mediated by the HC fragment of tetanus toxin (1999) Eur J Biochem, 259, pp. 762-769; Oliveira, H., Fernandez, R., Pires, L.R., Simões, S., Martins, M.C.L., Barbosa, M.A., Pêgo, A.P., Targeted gene delivery into peripheral sensorial neurons mediated by self-assembled vectors composed of poly(ethilenimine) and tetanus toxin fragment c (2010) J Control Release, 143, pp. 350-358; Neu, M., Fischer, D., Kissel, T., Recent advances in rational gene transfer vector design based on poly(ethylene imine) and its derivatives (2005) J Gene Med, 7, pp. 992-1009; Tang, G.P., Guo, H.Y., Alexis, F., Wang, X., Zeng, S., Lim, T.M., Ding, J., Wang, S., Low molecular weight polyethylenimines linked by beta-cyclodextrin for gene transfer into the nervous system (2006) J Gene Med, 8, pp. 736-744; Chollet, P., Favrot, M.C., Hurbin, A., Coll, J.L., Side-effects of a systemic injection of linear polyethylenimine-DNA complexes (2002) J Gene Med, 4, pp. 84-91; Shi, C., Zhu, Y., Ran, X., Wang, M., Su, Y., Cheng, T., Therapeutic potential of chitosan and its derivatives in regenerative medicine (2006) J Surg Res, 133, pp. 185-192; Mansouri, S., Lavigne, P., Corsi, K., Benderdour, M., Beaumont, E., Fernandes, J.C., Chitosan-DNA nanoparticles as non-viral vectors in gene therapy: Strategies to improve transfection efficacy (2004) Eur J Pharm Biopharm, 57, pp. 1-8; Moreira, C., Oliveira, H., Pires, L.R., Simoes, S., Barbosa, M.A., Pego, A.P., Improving chitosan-mediated gene transfer by the introduction of intracellular buffering moieties into the chitosan backbone (2009) Acta Biomater, 5, pp. 2995-3006; Verma, A., Stellacci, F., Effect of surface properties on nanoparticle-cell interactions (2010) Small, 6, pp. 12-21; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; (1987) Guideline on Validation of the Limulus Amebocyte Lysate Test As An End-product Endotoxin Test for Human and Animal Parental Drugs, Biological Products, and Medical Devices, , US Department of Health and Human Services. US Department of Health and Human Services; MacUlotti, K., Genta, I., Perugini, P., Imam, M., Bernkop-Schnurch, A., Pavanetto, F., Preparation and in vitro evaluation of thiolated chitosan microparticles (2005) J Microencapsul, 22, pp. 459-470; Mao, H., Roy, K., Troung-Le, V.L., Janes, K.A., Lin, K.Y., Wang, Y., August, J.T., Leong, K.W., Chitosan-DNA nanoparticles as gene carriers: Synthesis, characterization and transfection efficiency (2001) J Control Release, 70, pp. 399-421; Innes, N.P.T., Ogden, G.R., A technique for the study of endocytosis in human oral epithelial cells (1999) Arch Oral Biol, 44, pp. 519-523; O'Brien, J., Wilson, I., Orton, T., Pognan, F., Investigation of the Alamar Blue (resazurin) fluorescent dye for the assessment of mammalian cell cytotoxicity (2000) Eur J Biochem, 267, pp. 5421-5426; Ellman, G.L., Tissue sulfhydryl groups (1959) Arch Biochem Biophys, 82, pp. 70-77; Lee, D., Zhang, W., Shirley, S.A., Kong, X., Hellermann, G.R., Lockey, R.F., Mohapatra, S.S., Thiolated chitosan/DNA nanocomplexes exhibit enhanced and sustained gene delivery (2007) Pharm Res, 24, pp. 157-167; Loretz, B., Thaler, M., Bernkop-Schnurch, A., Role of sulfhydryl groups in transfection? A case study with chitosan-NAC nanoparticles (2007) Bioconjug Chem, 18, pp. 1028-1035; Deinhardt, K., Berninghausen, O., Willison, H.J., Hopkins, C.R., Schiavo, G., Tetanus toxin is internalized by a sequential clathrin-dependent mechanism initiated within lipid microdomains and independent of epsin 1 (2006) J Cell Biol, 174, pp. 459-471; Williamson, L.C., Neale, E.A., Bafilomycin A1 inhibits the action of tetanus toxin in spinal-cord neurons in cell-culture (1994) J Neurochem, 63, pp. 2342-2345; Bohnert, S., Schiavo, G., Tetanus toxin is transported in a novel neuronal compartment characterized by a specialized pH regulation (2005) J Biol Chem, 280, pp. 42336-42344
Keywords: animal cell; Animals; article; Binary complexes; Biodegradable polymers; Carbohydrate Conformation; Carbohydrate Sequence; Cations; Cell culture; Cell lines; cell population; Cells, Cultured; Chitin; chitosan; Complex surface; DNA; DNA complex; Dorsal root ganglia; Efficient systems; embryo; Ethylene; Ethylene Glycol; Female; Ganglia, Spinal; Gene delivery; gene delivery system; Gene delivery vectors; Gene therapy; Gene transfer; Gene Transfer Techniques; genetic transfection; Genetic Vectors; Grafting (chemical); Humans; imidazole; macrogol; materials testing; Mice; Molecular Sequence Data; Molecular Structure; mouse; Multicomponents; Nanocomplexes; Nanoparticle systems; nanoparticles; nerve cell culture; Neuron culture; Neuronal cell; NIH 3T3 Cells; nonhuman; Nontoxic fragment of tetanus toxin; Peripheral nervous system; Peripheral neuropathy; Polycations; Polyethylene Glycols; Polyethylene oxides; Pregnancy; Primary culture; rat; Rats; Rats, Wistar; spinal ganglion; Starting materials; Targeted; Tetanus toxin; Toxic materials; Transfection; Transfection efficiency

Comparison of a computer system evaluation of intrapartum cardiotocographic events and a consensus of clinicians. - Costa, M.A.; Ayres-de-Campos, D.; Machado, A.P.; Santos, C.C.; Bernardes, J. (Journal of perinatal medicineJ Perinat Med, 2010)
AIMS: To compare between computer analysis of intrapartum cardiotocography (CTG) features by the Omniview-SisPorto 3.5 and a consensus of clinicians. METHODS: Agreement study using 50 consecutively acquired tracings (206 h of signals) with >60 min duration, <10% signal loss and recorded in labor at term by internal fetal heart rate (FHR) monitoring. Tracings were divided into 10-min segments and independently analyzed by three experienced clinicians, in order to estimate the FHR baseline and identify periodic events. A consensus was reached using a three round Delphi procedure. Results were compared with the analysis provided by the Omniview-SisPorto 3.5 system. RESULTS: For baseline estimation, agreement between the computer and the consensus was high [intraclass correlation coefficient (ICC)=0.85; 95% confidence interval (CI) 0.46-0.93], with a mean difference of 3.7 bpm (limits of agreement -4.4-11.9 bpm), and 99% of differences under 15 bpm. A concordant identification was observed in 71% of accelerations (95% CI: 69%-73%), 68% of decelerations (95% CI: 66%-70%), and 87% of uterine contractions (95% CI: 85%-89%). CONCLUSIONS: A high agreement was observed between the Omniview-SisPorto 3.5 and a consensus of clinicians in evaluation of intrapartum CTG baseline, accelerations, decelerations and uterine contractions.
Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1515/JPM.2010.030PubMed ID: 20121542Language of Original Document: EnglishCorrespondence Address: Costa, M.A.email: cosantonia@gmail.com
Keywords: algorithm; Algorithms; article; Cardiotocography; comparative study; computer assisted diagnosis; Diagnosis, Computer-Assisted; Female; Fetal Heart; Fetal monitoring; fetus heart; fetus monitoring; human; Humans; instrumentation; methodology; physician; Physicians; physiology; Pregnancy

De novo expression of CD44 variants in sporadic and hereditary gastric cancer - Da Cunha, C.B.; Oliveira, C.; Wen, X.; Gomes, B.; Sousa, S.; Suriano, G.; Grellier, M.; Huntsman, D.G.; Carneiro, F.; Granja, P.L.; Seruca, R. (Laboratory InvestigationLab. Invest., 2010)
CD44 is the major ubiquitously expressed cell surface receptor for hyaluronate. The CD44 gene encodes several protein isoforms due to extensive alternative splicing and post-translational modifications. Some of these CD44 variable isoforms have been foreseen as key players in malignant transformation and their expression is highly restricted and highly specific, unlike the canonical CD44 standard isoform. In this study, we aimed at dissecting the mRNA splicing pattern of CD44 in normal stomach and gastric cancer (GC) cell lines (n9) using cloning and quantitative mRNA amplification assays. Moreover, we assessed the RNA levels and protein expression pattern of relevant splicing forms in distinct premalignant and malignant gastric lesions (sporadic (n43) and hereditary (n3) forms) using real-time RT-PCR and immunohistochemistry. We also explored the association of CD44 and E-cadherin expression by immunohistochemistry, as E-cadherin has a pivotal functional role in GC. We established the pattern of CD44 variant forms in normal stomach and gastric malignancy. We observed that although exon v6-containing isoforms were rarely expressed in normal gastric mucosa, they became increasingly expressed both in gastric premalignant (hyperplastic polyps, complete and incomplete intestinal metaplasia, low- and high-grade dysplasia) and malignant lesions (cell lines derived from GCs, primary sporadic GCs and hereditary diffuse GCs (HDGCs)). Moreover, we verified that whenever E-cadherin expression was absent, exon v6-containing CD44 isoforms were overexpressed. The lack of expression of CD44 isoforms containing exon v6 in the surface and foveolar epithelia of normal stomach and, its de novo expression in premalignant, as well as in sporadic and hereditary malignant lesions of the stomach, pinpoint CD44 v6-containg isoforms as potential biomarkers for early transformation of the gastric mucosa. Further, our results raise the hypothesis of using CD44v6 as a marker of early invasive intramucosal carcinoma in HDGC CDH1 mutation carriers that lack CDH1 expression in their tumors. © 2010 USCAP, Inc All rights reserved.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: LAINAdoi: 10.1038/labinvest.2010.155PubMed ID: 20856229Language of Original Document: EnglishCorrespondence Address: Da Cunha, C. B.; IPATIMUP, Institute of Molecular Pathology and Immunology, University of Porto, Rua Dr. Roberto Frias s/n, 4200-465 Porto, Portugal; email: rseruca@ipatimup.ptChemicals/CAS: uvomorulin, 112956-45-3; Antigens, CD44; CD44 protein, human; CD44v6 antigen; Cadherins; RNA, MessengerReferences: Aruffo, A., Stamenkovic, I., Melnick, M., CD44 is the principal cell surface receptor for hyaluronate (1990) Cell, 61, pp. 1303-1313;Screaton, G.R., Bell, M.V., Jackson, D.G., Genomic structure of DNA encoding the lymphocyte homing receptor CD44 reveals at least 12 alternatively spliced exons (1992) Proc Natl Acad Sci USA, 89, pp. 12160-12164; Ponta, H., Wainwright, D., Herrlich, P., Molecules in focus the CD44 protein family (1998) Int J Biochem Cell Biol, 30, pp. 299-305; Rudzki, Z., Jothy, S., CD44 and the adhesion of neoplastic cells (1997) Mol Pathol, 50, pp. 57-71; Shtivelman, E., Bishop, J.M., Expression of CD44 is repressed in neuroblastoma cells (1991) Mol Cell Biol, 11, pp. 5446-5453; De Marzo, A.M., Bradshaw, C., Sauvageot, J., CD44 and CD44v6 downregulation in clinical prostatic carcinoma: Relation to Gleason grade and cytoarchitecture (1998) Prostate, 34, pp. 162-168; Joensuu, H., Klemi, P.J., Toikkanen, S., Glycoprotein CD44 expression and its association with survival in breast cancer (1993) Am J Pathol, 143, pp. 867-874; Friedrichs, K., Kugler, G., Franke, F., CD44 isoforms in prognosis of breast cancer (1995) Lancet, 345, p. 1237; Kaufmann, M., Heider, K.H., Sinn, H.P., CD44 variant exon epitopes in primary breast cancer and length of survival (1995) Lancet, 345, pp. 615-619; Mulder, J.W., Kruyt, P.M., Sewnath, M., Colorectal cancer prognosis and expression of exon-v6-containing CD44 proteins (1994) Lancet, 344, pp. 1470-1472; Wielenga, V.J., Heider, K.H., Offerhaus, G.J., Expression of CD44 variant proteins in human colorectal cancer is related to tumor progression (1993) Cancer Res, 53, pp. 4754-4756; Terpe, H.J., Koopmann, R., Imhof, B.A., Expression of integrins and CD44 isoforms in non-Hodgkin's lymphomas: CD44 variant isoforms are preferentially expressed in high-grade malignant lymphomas (1994) J Pathol, 174, pp. 89-100; Takaishi, S., Okumura, T., Tu, S., Identification of gastric cancer stem cells using the cell surface marker CD44 (2009) Stem Cells, 27, pp. 1006-1020; Heider, K.-H., Dammrich, J., Skroch-Angel, P., Differential EXpression of CD44 splice variants in intestinal-and diffuse-type human gastric carcinomas and normal gastric mucosa (1993) Cancer Res, 53, pp. 4197-4203; Mayer, B., Jauch, K.W., Gunthert, U., De-novo expression of CD44 and survival in gastric cancer (1993) Lancet, 342, pp. 1019-1022; Muller, W., Schneiders, A., Heider, K.H., Expression and prognostic value of the CD44 splicing variants v5 and v6 in gastric cancer (1997) J Pathol, 183, pp. 222-227; Mirecka, J., Marx, D., Schauer, A., Immunohistochemical localization of CD44 variants 5 and 6 in human gastric mucosa and gastric cancer (1995) Anticancer Res, 15, pp. 1459-1465; Heider, K.H., Dammrich, J., Skroch-Angel, P., Differential expression of CD44 splice variants in intestinal-and diffuse-type human gastric carcinomas and normal gastric mucosa (1993) Cancer Res, 53, pp. 4197-4203; Hong, R.L., Lee, W.J., Shun, C.T., Expression of CD44 and its clinical implication in diffuse-type and intestinal-type gastric adenocarcinomas (1995) Oncology, 52, pp. 334-339; Ghaffarzadehgan, K., Jafarzadeh, M., Raziee, H.R., Expression of cell adhesion molecule CD44 in gastric adenocarcinoma and its prognostic importance (2008) World J Gastroenterol, 14, pp. 6376-6381; Carneiro, F., Huntsman, D.G., Smyrk, T.C., Model of the early development of diffuse gastric cancer in E-cadherin mutation carriers and its implications for patient screening (2004) J Pathol, 203, pp. 681-687; Suriano, G., Mulholland, D., De Wever, O., The intracellular E-cadherin germline mutation V832M lacks the ability to mediate cell-cell adhesion and to suppress invasion (2003) Oncogene, 22, pp. 5716-5719; Suriano, G., Oliveira, C., Ferreira, P., Identification of CDH1 germline missense mutations associated with functional inactivation of the E-cadherin protein in young gastric cancer probands (2003) Hum Mol Genet, 12, pp. 575-582; Suriano, G., Oliveira, M.J., Huntsman, D., E-cadherin germline missense mutations and cell phenotype: Evidence for the independence of cell invasion on the motile capabilities of the cells (2003) Hum Mol Genet, 12, pp. 3007-3016; Oliveira, C., Bordin, M.C., Grehan, N., Screening E-cadherin in gastric cancer families reveals germline mutations only in hereditary diffuse gastric cancer kindred (2002) Hum Mutat, 19, pp. 510-517; MacHado, J.C., Oliveira, C., Carvalho, R., E-cadherin gene (CDH1) promoter methylation as the second hit in sporadic diffuse gastric carcinoma (2001) Oncogene, 20, pp. 1525-1528; Huntsman, D.G., Carneiro, F., Lewis, F.R., Early gastric cancer in young, asymptomatic carriers of germ-line E-cadherin mutations (2001) N Engl J Med, 344, pp. 1904-1909; Carneiro, F., MacHado, J.C., Seruca, R., E-cadherin changes in gastric carcimona (1999) Histopathology, 35, pp. 477-478; Mateus, A.R., Simoes-Correia, J., Figueiredo, J., E-cadherin mutations and cell motility: A genotype-phenotype correlation (2009) Exp Cell Res, 315, pp. 1393-1402; Oliveira, C., Senz, J., Kaurah, P., Germline CDH1 deletions in hereditary diffuse gastric cancer families (2009) Hum Mol Genet, 18, pp. 1545-1555; Oliveira, C., Sousa, S., Pinheiro, H., Quantification of epigenetic and genetic second hits in CDH1 during hereditary diffuse gastric cancer syndrome progression (2009) Gastroenterology, 136, pp. 2137-2148; Lynch, H.T., Grady, W., Suriano, G., Gastric cancer: New genetic developments (2005) J Surg Oncol, 90, pp. 114-133. , discussion 133; Lauren, P., The two histological main types of gastric carcinoma: Diffuse and so-called intestinal-type carcinoma. An attempt at a histo-clinical classification (1965) Acta Pathol Microbiol Scand, 64, pp. 31-49; Filipe, M.I., Jass, J.R., Intestinal metaplasia subtypes and cancer risk (1986) Gastric Carcinoma, pp. 87-115. , Filipe MI, Jass JR (eds). Churchill Livingstone, London; Sato, S., Yokozaki, H., Yasui, W., Silencing of the CD44 gene by CpG methylation in a human gastric carcinoma cell line (1999) Jpn J Cancer Res, 90, pp. 485-489; Guilford, P.H.J., Harraway, J., McLeod, M., E-cadherin germline mutations in familial gastric cancer (1998) Nature, 26, p. 6674; Günthert, U., Hofmann, M., Rudy, W., A new variant of glycoprotein CD44 confers metastatic potential to rat carcinoma cells (1991) Cell, 65, pp. 13-24; Vr, O., Chen, L., Sleeman, J.P., CD44 is required for two consecutive steps in HGF/c-Met signaling (2002) Genes Dev, 16, pp. 3074-3086; Spk, D., Stefan, M., Wels, C., HGF-Promoted Motility in Primary Melanocytes Depends on CD44v6 Regulated via NF-kappa B, Egr-1, and C/EBP-beta (2010) J Investig Dermatol, 130, pp. 1893-1903; Mielgo, A., Van Driel, M., Bloem, A., A novel antiapoptotic mechanism based on interference of Fas signaling by CD44 variant isoforms (2006) Cell Death Differ, 13, pp. 465-477; Marhaba, R., Bourouba, M., Zoller, M., CD44v6 promotes proliferation by persisting activation of MAP kinases (2005) Cell Signal, 17, pp. 961-973; Bates, R.C., Edwards, N.S., Burns, G.F., A CD44 survival pathway triggers chemoresistance via lyn kinase and phosphoinositide 3-kinase/Akt in colon carcinoma cells (2001) Cancer Res, 61, pp. 5275-5283; Carvalho, R., Milne, A.N., Polak, M., A novel region of amplification at 11p12-13 in gastric cancer, revealed by representational difference analysis, is associated with overexpression of CD44v6, especially in early-onset gastric carcinomas (2006) Genes Chromosomes Cancer, 45, pp. 967-975; Heider, K.H., Hofmann, M., Hors, E., A human homologue of the rat metastasis-associated variant of CD44 is expressed in colorectal carcinomas and adenomatous polyps (1993) J Cell Biol, 120, pp. 227-233; Gulmann, C., Grace, A., Leader, M., CD44v6: A potential marker of malignant transformation in intestinal metaplasia of the stomach? An immunohistochemical study using tissue microarrays (2003) Eur J Gastroenterol Hepatol, 15, pp. 981-986; Wimmel, A., Kogan, E., Ramaswamy, A., Variant expression of CD44 in preneoplastic lesions of the lung (2001) Cancer, 92, pp. 1231-1236; Afify, A.M., Craig, S., Paulino, A.F., Expression of hyaluronic acid and its receptors, CD44s and CD44v6, in normal, hyperplastic, and neoplastic endometrium (2005) Ann Diagn Pathol, 9, pp. 312-318; Soon Cheol, H., Jae Yun, S., Jae Kwan, L., Significance of CD44v6 expression in gynecologic malignancies (2006) J Obstet Gynaecol Res, 32, pp. 379-386; Afify, A., Ma, M., Braggin, J., Expression of CD44s, CD44v6, and hyaluronan across the spectrum of normal-hyperplasia-carcinoma in breast (2008) Appl Immunohistochem Mol Morphol, 16, pp. 121-127; Judd, L.M., Andriga, A., Rubio, C.A., Gastric achlorhydria in H/K-ATPase-deficient (Atp4a(-/-)) mice causes severe hyperplasia, muco-cystic metaplasia and upregulation of growth factors (2005) J Gastroenterol Hepatol, 20, pp. 1266-1278; Liu, Y.J., Yan, P.S., Li, J., Expression and significance of CD44 s, CD44v6, and nm23 mRNA in human cancer (2005) World J Gastroenterol, 11, pp. 6601-6606; Polkowski, W.P., Skomra, D.G., Mielko, J., E-cadherin expression as predictive marker of proximal resection line involvement for advanced carcinoma of the gastric cardia (2004) E J Surg Oncol, 30, pp. 1084-1092; Seiter, S.A.R., Reber, S., Komitowski, D., Prevention of tumor metastasis formation by anti-variant CD44 (1993) J Experiment Med, 177, pp. 443-455; Reeder, J.A., Gotley, D.C., Walsh, M.D., Expression of ANTisense CD44 variant 6 inhibits colorectal tumor metastasis and tumor growth in a wound environment (1998) Cancer Res, 58, pp. 3719-3726; Nishii, T., Yashiro, M., Shinto, O., Cancer stem cell-like SP cells have a high adhesion ability to the peritoneum in gastric carcinoma (2009) Cancer Sci, 100, pp. 1397-1402; Carneiro, F., Huntsman, D.G., Smyrk, T.C., Model of the early development of diffuse gastric cancer in E-cadherin mutation carriers and its implications for patient screening (2004) J Pathol, 203, pp. 681-687; Pdp, P., Guilford, P., Caldas, C., The International Gastric Cancer Linkage C. Incidence of gastric cancer and breast cancer in CDH1 (E-cadherin) mutation carriers from hereditary diffuse gastric cancer families (2001) Gastroenterology, 121, pp. 1348-1353; Humar, B., Fukuzawa, R., Blair, V., Destabilized adhesion in the gastric proliferative zone and c-Src kinase activation mark the development of early diffuse gastric cancer (2007) Cancer Res, 67, pp. 2480-2489; Ferrari, M., Cancer nanotechnology: Opportunities and challenges (2005) Nat Rev Cancer, 5, pp. 161-171; Yww, W., Chen, Y., Huang, K., The investigation of polymer-siRNA nanoparticle for gene therapy of gastric cancer in vitro (2010) Int J Nanomed, 5, pp. 129-136
Keywords: Alternative Splicing; Antigens, CD44; article; Cadherins; CD44; CD44v6; CD44v6 antigen; CD44v7 antigen; Cell Line, Tumor; clinical article; controlled study; E-cadherin; familial cancer; Gastric Mucosa; Germ-Line Mutation; HDGC; Hermes antigen; human; human tissue; Humans; immunohistochemistry; intestine metaplasia; messenger RNA; Neoplasm Metastasis; priority journal; protein expression; real time polymerase chain reaction; reverse transcription polymerase chain reaction; RNA splicing; RNA, Messenger; splicing; sporadic GC; stomach; stomach cancer; stomach mucosa; Stomach Neoplasms; stomach polyp; tumor marker; unclassified drug; uvomorulin

Dynamic cell-cell interactions between cord blood haematopoietic progenitors and the cellular niche are essential for the expansion of CD34 +, CD34 +CD38 - Da Silva, C.L.; Gonçalves, R.; Dos Santos, F.; Andrade, P.Z.; Almeida-Porada, G.; Cabral, J.M.S. (Journal of Tissue Engineering and Regenerative MedicineJ. Tissue Eng. Regenerative Med., 2010)
Most clinical applications of haematopoietic stem/progenitor cells (HSCs) would benefit from their ex vivo expansion to obtain a therapeutically significant amount of cells from the available donor samples. We studied the impact of cellular interactions between umbilical cord blood (UCB) haematopoietic cells and bone marrow (BM)-derived mesenchymal stem cells (MSCs) on the ex vivo expansion and differentiative potential of UCB CD34 +-enriched cells. UCB cells were cultured: (a) directly in contact with BM MSC-derived stromal layers (contact); (b) separated by a microporous membrane (non-contact); or (c) without stroma (no stroma). Highly dynamic culture events occurred in HSC-MSC co-cultures, involving cell-cell interactions, which preceded HSC expansion. Throughout the time in culture [18 days], total cell expansion was significantly higher in contact (fold increase of 280 ± 37 at day 18) compared to non-contact (85 ± 25). No significant cell expansion was observed in stroma-free cultures. CD34 + cell expansion was also clearly favoured by direct contact with BM MSCs (35 ± 5- and 7 ± 3-fold increases at day 18 for contact and non-contact, respectively). Moreover, a higher percentage of CD34 +CD38
Cited By (since 1996): 8Export Date: 21 November 2012Source: Scopusdoi: 10.1002/term.226PubMed ID: 19937912Language of Original Document: EnglishCorrespondence Address: Da Silva, C. L.; IBB-Institute for Biotechnology and Bioengineering, Centre for Biological and Chemical Engineering, Instituto Superior Técnico, Avenida Rovisco Pais, 1049-001 Lisbon, Portugal; email: claudialobato@ist.utl.ptChemicals/CAS: Antigens, CD34; Antigens, CD38, 3.2.2.5; Antigens, CD7; SuspensionsReferences: Alakel, N., Jing, D., Muller, K., Direct contact with mesenchymal stromal cells affects migratory behavior and gene expression profile of CD133 + hematopoietic stem cells during ex vivo expansion (2009) Exp Hematol, 37 (4), pp. 504-513;Almeida-Porada, G., Brown, R.L., MacKintosh, F.R., Evaluation of serum-free culture conditions able to support the ex vivo expansion and engraftment of human hematopoietic stem cells in the human-to-sheep xenograft model (2000) J Hematother Stem Cell Res, 9 (5), pp. 683-693; Ando, K., Nakamura, Y., Chargui, J., Extensive generation of human cord blood CD34 + stem cells from Lin -CD34 - cells in a long-term in vitro system (2000) Exp Hematol, 28 (6), pp. 690-699; Bernstein, I.D., Boyd, R.L., van den Brink, M.R., Clinical strategies to enhance posttransplant immune reconstitution (2008) Biol Blood Marrow Transpl, 14 (1 and SUPPL. 1), pp. 94-99; Bilko, N.M., Votyakova, I.A., Vasylovska, S.V., Characterization of the interactions between stromal and haematopoietic progenitor cells in expansion cell culture models (2005) Cell Biol Int, 29 (1), pp. 83-86; Breems, D.A., Blokland, E.A., Siebel, K.E., Stroma contact prevents loss of hematopoietic stem cell quality during ex vivo expansion of CD34 + mobilized peripheral blood stem cells (1998) Blood, 91 (1), pp. 111-117; Cheng, X., Macvittie, T., Meisenberg, B., Human brain endothelial cells (HUBEC) promote SCID repopulating cell expansion through direct contact (2007) Growth Factors, 25 (3), pp. 141-150; Corre, J., Planat-Benard, V., Corberand, J., Human bone marrow adipocytes support complete myeloid and lymphoid differentiation from human CD34 + cells (2004) Br J Haematol, 127 (3), pp. 344-347; da Silva, C.L., Goncalves, R., Crapnell, K.B., A human stromal-based serum-free culture system supports the ex vivo expansion/maintenance of bone marrow and cord blood hematopoietic stem/progenitor cells (2005) Exp Hematol, 33 (7), pp. 828-835; da Silva, C.L., Goncalves, R., Porada, C.D., Differences amid bone marrow and cord blood hematopoietic stem/progenitor cell division kinetics (2009) J Cell Physiol, , DOI: 10.1002/jcp.21736; de Lima, M., Shpall, E., Strategies for widening the use of cord blood in hematopoietic stem cell transplantation (2006) Haematologica, 91 (5), pp. 584-587; Foguenne, J., Di Stefano, I., Giet, O., Ex vivo expansion of hematopoietic progenitor cells is associated with downregulation of α4 integrin- and CXCR4-mediated engraftment in NOD/SCID β2-microglobulin-null mice (2009) Haematologica, 94 (2), pp. 185-194; Freund, D., Bauer, N., Boxberger, S., Polarization of human hematopoietic progenitors during contact with multipotent mesenchymal stromal cells: Effects on proliferation and clonogenicity (2006) Stem Cells Dev, 15 (6), pp. 815-829; Frias, A.M., Porada, C.D., Crapnell, K.B., Generation of functional natural killer and dendritic cells in a human stromal-based serum-free culture system designed for cord blood expansion (2008) Exp Hematol, 36 (1), pp. 61-68; Goncalves, R., Lobato da Silva, C., Cabral, J.M.S., A Stro-1 + human universal stromal feeder layer to expand/maintain human bone marrow hematopoietic stem/progenitor cells in a serum-free culture system (2006) Exp Hematol, 34 (10), pp. 1353-1359; Gordon, M.Y.M.S., Davidson, R.J., Grand, F.H., Contact-mediated inhibition of human hematopoietic progenitor cell proliferationmay be conferred by stem cell antigen, CD34 (2000) Hematol J, 1, pp. 77-86; Hao, Q.L., Zhu, J., Price, M.A., Identification of a novel, human multilymphoid progenitor in cord blood (2001) Blood, 97 (12), pp. 3683-3690; Haylock, D.N., Nilsson, S.K., Osteopontin: A bridge between bone and blood (2006) Br J Haematol, 134 (5), pp. 467-474; Hidalgo, A., Robledo, M.M., Teixido, J., CD44-mediated hematopoietic progenitor cell adhesion and its complex role in myelopoiesis (2002) J Hematother Stem Cell Res, 11 (3), pp. 539-547; Hofmeister, C.C., Zhang, J., Knight, K.L., Ex vivo expansion of umbilical cord blood stem cells for transplantation: Growing knowledge from the hematopoietic niche (2007) Bone Marrow Transpl, 39 (1), pp. 11-23; Jones, P., May, G., Healy, L., Stromal expression of Jagged 1 promotes colony formation by fetal hematopoietic progenitor cells (1998) Blood, 92 (5), pp. 1505-1511; Katayama, Y., Frenette, P.S., Galactocerebrosides are required postnatally for stromal-dependent bone marrow lymphopoiesis (2003) Immunity, 18 (6), pp. 789-800; Kawada, H., Ando, K., Tsuji, T., Rapid ex vivo expansion of human umbilical cord hematopoietic progenitors using a novel culture system (1999) Exp Hematol, 27 (5), pp. 904-915; Kilroy, G.E., Foster, S.J., Wu, X., Cytokine profile of human adipose-derived stem cells: Expression of angiogenic, hematopoietic, and pro-inflammatory factors (2007) J Cell Physiol, 212 (3), pp. 702-709; Kim, J.A., Kang, Y.J., Park, G., Identification of a stromamediated Wnt/β-catenin signal promoting self-renewal of hematopoietic stem cells in the stem cell niche (2009) Stem Cells, 27 (6), pp. 1318-1329; Koller, M.R., Oxender, M., Jensen, T.C., Direct contact between CD34 +lin - cells and stroma induces a soluble activity that specifically increases primitive hematopoietic cell production (1999) Exp Hematol, 27 (4), pp. 734-741; Lewis, I.D., Almeida-Porada, G., Du, J., Umbilical cord blood cells capable of engrafting in primary, secondary, and tertiary xenogeneic hosts are preserved after ex vivo culture in a noncontact system (2001) Blood, 97 (11), pp. 3441-3449; Li, N., Feugier, P., Serrurrier, B., Human mesenchymal stem cells improve ex vivo expansion of adult human CD34 + peripheral blood progenitor cells and decrease their allostimulatory capacity (2007) Exp Hematol, 35 (3), pp. 507-515; Li, Y.P., Paczesny, S., Lauret, E., Human mesenchymal stem cells license adult CD34 + hemopoietic progenitor cells to differentiate into regulatory dendritic cells through activation of the Notch pathway (2008) J Immunol, 180 (3), pp. 1598-1608; Loeuillet, C., Bernard, G., Remy-Martin, J., Distinct hematopoietic support by two human stromal cell lines (2001) Exp Hematol, 29 (6), pp. 736-745; Mayani, H., Lansdorp, P.M., Biology of human umbilical cord blood-derived hematopoietic stem/progenitor cells (1998) Stem Cells, 16 (3), pp. 153-165; McKenzie, J.L., Gan, O.I., Doedens, M., Reversible cell surface expression of CD38 on CD34-positive human hematopoietic repopulating cells (2007) Exp Hematol, 35 (9), pp. 1429-1436; Moore, K.A., Lemischka, I.R., Stem cells and their niches (2006) Science, 311 (5769), pp. 1880-1885; Nolta, J.A., Smogorzewska, E.M., Kohn, D.B., Analysis of optimal conditions for retroviral-mediated transduction of primitive human hematopoietic cells (1995) Blood, 86 (1), pp. 101-110; Oostendorp, R.A., Robin, C., Steinhoff, C., Long-term maintenance of hematopoietic stem cells does not require contact with embryo-derived stromal cells in cocultures (2005) Stem Cells, 23 (6), pp. 842-851; Oritani, K., Wu, X., Medina, K., Antibody ligation of CD9 modifies production of myeloid cells in long-term cultures (1996) Blood, 87 (6), pp. 2252-2261; Sadlon, T.J., Lewis, I.D., D'Andrea, R.J., BMP4: Its role in development of the hematopoietic system and potential as a hematopoietic growth factor (2004) Stem Cells, 22 (4), pp. 457-474; Shih, C.C., Hu, M.C.T., Hu, J., Long-term ex vivo maintenance and expansion of transplantable human hematopoietic stem cells (1999) Blood, 94 (5), pp. 1623-1636; Shpall, E.J., Quinones, R., Giller, R., Transplantation of ex vivo expanded cord blood (2002) Biol Blood Marrow Transpl, 8 (7), pp. 368-376; Suzuki, T., Yokoyama, Y., Kumano, K., Highly efficient ex vivo expansion of human hematopoietic stem cells using Δ1-Fc chimeric protein (2006) Stem Cells, 24 (11), pp. 2456-2465; Verfaillie, C.M., Direct contact between human primitive hematopoietic progenitors and bone marrow stroma is not required for long-term in vitro hematopoiesis (1992) Blood, 79 (11), pp. 2821-2826; Wagner, W., Wein, F., Roderburg, C., Adhesion of hematopoietic progenitor cells to human mesenchymal stem cells as a model for cell-cell interaction (2007) Exp Hematol, 35 (2), pp. 314-325; Yin, T., Li, L., The stem cell niches in bone (2006) J Clin Invest, 116 (5), pp. 1195-1201; Zhang, C.C., Kaba, M., Iizuka, S., Angiopoietin-like 5 and IGFBP2 stimulate ex vivo expansion of human cord blood hematopoietic stem cells as assayed by NOD/SCID transplantation (2008) Blood, 111 (7), pp. 3415-3423; Zhang, Y., Chai, C., Jiang, X.S., Co-culture of umbilical cord blood CD34 + cells with human mesenchymal stem cells (2006) Tissue Eng, 12 (8), pp. 2161-2170
Keywords: Antigens, CD34; Antigens, CD38; Antigens, CD7; article; Bone marrow microenvironment; CD34 antigen; CD38 antigen; CD7 antigen; cell adhesion; Cell Communication; cell contact; Cell culture; cell differentiation; cell interaction; cell proliferation; Cells, Cultured; cellular distribution; clonogenic assay; coculture; Coculture Techniques; Colony-Forming Units Assay; controlled study; Ex vivo expansion; ex vivo study; Fetal Blood; flow cytometry; Haematopoietic stem/progenitor cells; hematopoietic stem cell; Hematopoietic Stem Cells; human; human cell; Humans; Lymphocytes; lymphoid cell; Mesenchymal stem cell; Mesenchymal Stem Cells; Microscopy, Electron, Scanning; phenotype; priority journal; Scanning electron microscopy; somatic gene therapy; stem cell expansion; Stem Cell Niche; stroma cell; Suspensions; umbilical cord blood

Early spreading and propagation of human bone marrow stem cells on isotropic and anisotropic topographies of silica thin films produced via microstamping - Pelaez-Vargas, A.; Gallego-Perez, D.; Ferrell, N.; Fernandes, M.H.; Hansford, D.; Monteiro, F.J. (Microscopy and MicroanalysisMicrosc. Microanal., 2010)
While there has been rapid development of microfabrication techniques to produce high-resolution surface modifications on a variety of materials in the last decade, there is still a strong need to produce novel alternatives to induce guided tissue regeneration on dental implants. High-resolution microscopy provides qualitative and quantitative techniques to study cellular guidance in the first stages of cell-material interactions. The purposes of this work were (1) to produce and characterize the surface topography of isotropic and anisotropic microfabricated silica thin films obtained by sol-gel processing, and (2) to compare the in vitro biological behavior of human bone marrow stem cells on these surfaces at early stages of adhesion and propagation. The results confirmed that a microstamping technique can be used to produce isotropic and anisotropic micropatterned silica coatings. Atomic force microscopy analysis was an adequate methodology to study in the same specimen the sintering derived contraction of the microfabricated coatings, using images obtained before and after thermal cycle. Hard micropatterned coatings induced a modulation in the early and late adhesion stages of cell-material and cell-cell interactions in a geometry-dependent manner (i.e., isotropic versus anisotropic), as it was clearly determined, using scanning electron and fluorescence microscopies. © Microscopy Society of America 2010.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: MIMIFdoi: 10.1017/S1431927610094158PubMed ID: 20964878Language of Original Document: EnglishCorrespondence Address: Pelaez-Vargas, A.; INEB - Instituto de Engenharia Biomédica, Faculdade de Engenharia, Departamento de Engenharia Metalrgica e Materiais, Porto, Portugal; email: alejopv@ineb.up.ptChemicals/CAS: silicon dioxide, 10279-57-9, 14464-46-1, 14808-60-7, 15468-32-3, 60676-86-0, 7631-86-9; Silicon Dioxide, 7631-86-9References: Albrektsson, T., Sennerby, L., Wennerberg, A., State of the art of oral implants (2000) Periodontology, 47, pp. 15-26;Albrektsson, T., Wennerberg, A., Oral implant surfaces: Part 1-Review focusing on topographic and chemical properties of different surfaces and in vivo responses to them (2004) Int J Prosthodont, 17 (5), pp. 536-543; Batista, L.H., Junior, J.G., Silva, M.F., Tonholo, J., Atomic force microscopy of removal of dentin smear layers (2007) Microsc Microanal, 13 (4), pp. 245-250; Baudino, T.A., McFadden, A., Fix, C., Hastings, J., Price, R., Borg, T.K., Cell patterning: Interaction of cardiac myocytes and fibroblasts in three-dimensional culture (2008) MicroscMicroanal, 14 (2), pp. 117-125; Bohil, A.B., Robertson, B.W., Cheney, R.E., Myosin-X is a molecular motor that functions in filopodia formation (2006) Proc Natl Acad Sci USA, 103 (33), pp. 12411-12416; Brunette, D.M., Kenner, G.S., Gould, T.R., Grooved titanium surfaces orient growth and migration of cells from human gingival explants (1983) J Dent Res, 62 (10), pp. 1045-1048; Curtis, A., Wilkinson, C., Topographical control of cells (1997) Biomaterials, 18 (24), pp. 1573-1583; Curtis, A.S., Cell reactions with biomaterials: The microscopies (2001) Eur Cell Mater, 1, pp. 59-65; Dalby, M.J., Riehle, M.O., Johnstone, H., Affrossman, S., Curtis, A.S., Investigating the limits of filopodial sensing: A brief report using SEM to image the interaction between 10 nm high nano-topography and fibroblast filopodia (2004) Cell Biol Int, 28 (3), pp. 229-236; Durán, A., Conde, A., Coedo, A.G., Dorado, T., García, C., Ceré, S., Sol-gel coatings for protection and bioactiva- tion of metals used in orthopaedic devices (2004) J Mater Chem, 14 (14), pp. 2282-2290; Falconnet, D., Csucs, G., Grandin, H.M., Textor, M., Surface engineering approaches to micropattern surfaces for cell-based assays (2006) Biomaterials, 27 (16), pp. 3044-3063; Gallardo, J., Galliano, P., Durán, A., Thermal evolution of hybrid sol-gel silica coatings: A structural analysis (2000) J Sol-Gel Sci Technol, 19 (1), pp. 393-397; Gallardo, J., Galliano, P., Moreno, R., Durán, A., Bioactive sol-gel coatings for orthopaedic prosthesis (2000) J Sol-Gel Sci Technol, 19 (1-3), pp. 107-111; Gallego, D., Ferrell, N., Sun, Y., Hansford, D., Multilayer micromolding of degradable polymer tissue engineering scaffolds (2008) Mater Sci Eng C, 28 (3), pp. 353-358; Gallego-Perez, D., Higuita-Castro, N., Sharma, S., Reen, R.K., Palmer, A.F., Gooch, K.J., Lee, L.J., Hansford, D.J., High throughput assembly of spatially controlled 3D cell clusters on a micro/nanoplatform (2010) Lab Chip, 10 (6), pp. 775-782; Garcia, C., Ceré, S., Durán, A., Bioactive coatings prepared by sol-gel on stainless steel 316L (2004) J Non-Cryst Solids, 348, pp. 218-224; Healy, K.E., Thomas, C.H., Rezania, A., Kim, J.E., McKeown, P.J., Lom, B., Hockberger, P.E., Kinetics of bone cell organization and mineralization on materials with patterned surface chemistry (1996) Biomaterials, 17 (2), pp. 195-208; Ito, Y., Surface micropatterning to regulate cell functions (1999) Biomaterials, 20 (23-24), pp. 2333-2342; Kim, E.J., Boehm, C.A., Mata, A., Fleischman, A.J., Muschler, G.F., Roy, S., Post microtextures accelerate cell proliferation and osteogenesis (2010) Acta Biomater, 6 (1), pp. 160-169; Lee, E.-J., Lee, S.H., Kim, H.W., Kong, Y.M., Kim, H.-E., Fluoridated apatite coatings on titanium obtained by electronbeam deposition (2005) Biomaterials, 26 (18), pp. 3843-3851; Lim, J.Y., Topographic control of cell response to synthetic materials (2009) Tissue Eng Regen Med, 6 (1), pp. 365-370; Marzolin, C., Smith, S.P., Prentiss, M., Whitesides, G.M., Fabrication of glass microstructures by micro-molding of sol-gel precursors (1998) Adv Mater, 10 (8), pp. 571-574; Mata, A., Boehm, C., Fleischman, A.J., Muschler, G., Roy, S., Growth of connective tissue progenitor cells on microtextured polydimethylsiloxane surfaces (2002) J Biomed Mater Res, 62 (4), pp. 499-506; Mata, A., Kim, E.J., Boehm, C.A., Fleischman, A.J., Muschler, G.F., Roy, S., A three-dimensional scaffold with precise micro-architecture and surface micro-textures (2009) Biomaterials, 30 (27), pp. 4610-4617; Meirelles, L., Currie, F., Jacobsson, M., Albrektsson, T., Wennerberg, A., The effect of chemical and nanotopographical modifications on the early stages of osseointegration (2008) Int J Oral Maxillofac Implants, 23 (4), pp. 641-647; Nayab, S.N., Jones, F.H., Olsen, I., Effects of calcium ion implantation on human bone cell interaction with titanium (2005) Biomaterials, 26 (23), pp. 4717-4727; Pelaez-Vargas, A., Ferrell, N., Fernandes, M.H., Hansford, D., Monteiro, F.J., Cells spreading on micro-fabricated silica thin film coatings (2009) Microsc Microanal, 15 (S3), pp. 77-78; Perrie, W., Rushton, A., Gill, M., Fox, P., O'Neill, W., Femtosecond laser micro-structuring of alumina ceramic (2005) Appl Surf Sci, 248 (1-4), pp. 213-217; Rhee, S.W., Taylor, A.M., Tu, C.H., Cribbs, D.H., Cotman, C.W., Jeon, N.L., Patterned cell culture inside microfluidic devices (2005) Lab Chip, 5 (1), pp. 102-107; Rompen, E., Domken, O., Degidi, M., Pontes, A.E., Piattelli, A., The effect of material characteristics, of surface topography and of implant components and connections on soft tissue integration: A literature review (2006) Clin Oral Implants Res, 17 (S2), pp. 55-67; Sennerby, L., Dental implants: Matters of course and controversies (2000) Periodontol, 47, pp. 9-14; Silva, P.L., Santos, J.D., Monteiro, F.J., Knowles, J.C., Adhesion and microstructural characterization of plasmasprayed hydroxyapatite/glass ceramic coatings onto Ti-6A1-4V substrates (1998) Surf Coat Technol, 102 (3), pp. 191-196; Tan, J., Saltzman, W.M., Biomaterials with hierarchically defined micro- and nanoscale structure (2004) Biomaterials, 25 (17), pp. 3593-3601; Teixeira, S., Monteiro, F.J., Ferraz, M.P., Vilar, R., Eugenio, S., Laser surface treatment of hydroxyapatite for enhanced tissue integration: Surface characterization and osteoblastic interaction studies (2007) J Biomed Mater Res A, 81 (4), pp. 920-929; Vorobyev, A.Y., Guo, C., Femtosecond laser structuring of titanium implants (2007) Appl Surf Sci, 253 (17), pp. 7272-7280; Wang, Y.C., Ho, C.C., Micropatterning of proteins and mammalian cells on biomaterials (2004) Faseb J, 18 (3), pp. 525-527; Wennerberg, A., Albrektsson, T., Andersson, B., Krol, J.J., A histomorphometric study of screw shaped and removal torque titanium implants with three different surface topographies (1995) Clin Oral Impl Res, 6 (1), p. 24; Xia, Y., Whitesides, G.M., Soft lithography (1998) Ann Rev Mater Sci, 28 (1), pp. 153-184; Xia, Y., Whitesides, G.M., Soft lithography (1998) Angew Chem Int Edit, 37 (5), pp. 550-575; Zinger, O., Zhao, G., Schwartz, Z., Simpson, J., Wieland, M., Landolt, D., Boyan, B., Differential regulation of osteoblasts by substrate microstructural features (2005) Biomaterials, 26 (14), pp. 1837-1847
Keywords: AFM; Atomic force microscopy; audiovisual equipment; cell adhesion and proliferation; Cell Culture Techniques; cell proliferation; conference paper; culture technique; cytology; Fluorescence microscopy; Guided tissue regeneration; human; Humans; Microscopy, Atomic Force; Microscopy, Electron, Scanning; Microscopy, Fluorescence; microstamping; Motion Pictures as Topic; myeloid progenitor cell; Myeloid Progenitor Cells; Scanning electron microscopy; SEM; silica sol-gel films; silicon dioxide; Soft lithography; Surface Properties; surface property; Tissue regeneration; tissue scaffold; Tissue Scaffolds

The effect of immobilization of thrombin inhibitors onto self-assembled monolayers on the adsorption and activity of thrombin - Freitas, S.C.; Barbosa, M.A.; Martins, M.C.L. (BiomaterialsBiomaterials, 2010)
Thrombus formation is the major problem associated with biomaterials for blood contact medical devices. The immobilization of inhibitors to thrombin, a serine protease that plays a central role on the coagulation system, on the surface of biomaterials should be a good strategy to avoid blood clotting and increase their hemocompatibility. The aim of this work is the design of a nanostructured surface with capacity to adsorb and inactivate thrombin. The pentapeptide sequence d-Phenylalanine-Proline-Arginine-Proline-Glycine (fPRPG), that was described as a thrombin inhibitor, was immobilized onto tetra(ethylene glycol) terminated self-assembled monolayers (EG4-SAMs). Surface containing different amounts of fPRPG were prepared using different concentrations of N,N′-Carbonyldiimidazole (CDI) during immobilization. The efficiency of fPRPG immobilization was followed using ellipsometry, contact angle measurements, Infrared reflection absorption spectroscopy (IRRAS) and X-ray photoelectron spectroscopy (XPS). Thrombin adsorption was quantified using radiolabelled thrombin and its activity in solution and after adsorption on the developed surfaces was assessed using a chromogenic assay. It was found that, although the immobilization of fPRPG on to EG4-SAMs does not increase its selectivity to thrombin, the activity of the adsorbed thrombin was inhibited in a peptide concentration dependent way. We concluded that SAMs with fPRPG immobilized in high amounts can be used as thrombin-inhibitor surfaces, which is a good step on the development of new surfaces for blood contact devices. © 2010 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2010.01.097PubMed ID: 20153046Language of Original Document: EnglishCorrespondence Address: Martins, M.C.L.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: cmartins@ineb.up.ptChemicals/CAS: thrombin, 9002-04-4; Albumins; Gold, 7440-57-5; Immobilized Proteins; Iodine Radioisotopes; Peptides; Solutions; Thrombin, 3.4.21.5References: Gorbet, M.B., Sefton, M.V., Biomaterial-associated thrombosis: roles of coagulation factors, complement, platelets and leukocytes (2004) Biomaterials, 25 (26), pp. 5681-5703;Ratner, B.D., Hoffman, A.F., Schoen, F.J., Lemons, J.L., (2004) Biomaterials science - an introduction to materials in medicine. 2nd ed., , Elsevier Academic Press, San Diego, CA, USA; Bode, W., Structure and interaction modes of thrombin (2006) Blood Cells Mol Dis, 36 (2), pp. 122-130; Huntington, J.A., Molecular recognition mechanisms of thrombin (2005) J Thromb Haemost, 3 (8), pp. 1861-1872; Schwienhorst, A., Direct thrombin inhibitors - a survey of recent developments (2006) Cell Mol Life Sci, 63 (23), pp. 2773-2791; Tseng, P.-Y., Rele, S.S., Sun, X.-L., Chaikof, E.L., Membrane-mimetic films containing thrombomodulin and heparin inhibit tissue factor-induced thrombin generation in a flow model (2006) Biomaterials, 27 (12), pp. 2637-2650; Sperling, C., Salchert, K., Streller, U., Werner, C., Covalently immobilized thrombomodulin inhibits coagulation and complement activation of artificial surfaces in vitro (2004) Biomaterials, 25 (21), pp. 5101-5113; Lin, J.C., Tseng, S.M., Surface characterization and platelet adhesion studies on polyethylene surface with hirudin immobilization (2001) J Mater Sci Mater Med, 12 (9), pp. 827-832; Wendel, H.P., Ziemer, G., Coating-techniques to improve the hemocompatibility of artificial devices used for extracorporeal circulation (1999) Eur J Cardiothorac Surg, 16 (3), pp. 342-350; Werner, C., Maitz, M.F., Sperling, C., Current strategies towards hemocompatible coatings (2007) J Mater Chem, 17 (32), pp. 3376-3384; Weitz, J.I., Crowther, M., Direct thrombin inhibitors (2002) Thromb Res, 106 (3), pp. V275-V284; Di Nisio, M., Middeldorp, S., Büller, H.R., Direct thrombin inhibitors (2005) N Engl J Med, 353 (10), pp. 1028-1040; Stone, S.R., Hofsteenge, J., Kinetics of the inhibition of thrombin by hirudin (1986) Biochemistry, 25 (16), pp. 4622-4628; Grutter, M.G., Priestle, J., Rahuel, J., Grossenbacher, H., Bode, W., Hofsteenge, J., Crystal structure of the thrombin-hirudin complex: a novel mode of serine protease inhibition (1990) EMBO J, 9 (8), pp. 2361-2365; Lahann, J., Plüster, W., Klee, D., Gattner, H.G., Höcker, H., Immobilization of the thrombin inhibitor r-hirudin conserving its biological activity (2001) J Mater Sci Mater Med, 12 (9), pp. 807-810; Phaneuf, M.D., Berceli, S.A., Bide, M.J., Quist, W.C., LoGerfo, F.W., Covalent linkage of recombinant hirudin to poly(ethylene terephthalate) (Dacron): creation of a novel antithrombin surface (1997) Biomaterials, 18 (10), pp. 755-765; Wyers, M.C., Phaneuf, M.D., Rzucidlo, E.M., Contreras, M.A., Logerfo, F.W., Quist, W.C., In vivo assessment of a novel Dacron surface with covalently bound recombinant hirudin (1999) Cardiovasc Pathol, 8 (3), pp. 153-159; Maraganore, J.M., Bourdon, P., Jablonski, J., Ramachandran, K.L., Fenton Ii, J.W., Design and characterization of hirulogs: a novel class of bivalent peptide inhibitors of thrombin (1990) Biochemistry, 29 (30), pp. 7095-7101; Maraganore, J.M., Chao, B., Joseph, M.L., Jablonski, J., Ramachandran, K.L., Anticoagulant activity of synthetic hirudin peptides (1989) J Biol Chem, 264 (15), pp. 8692-8698; Sun, X., Sheardown, H., Tengvall, P., Brash, J.L., Peptide modified gold-coated polyurethanes as thrombin scavenging surfaces (2000) J Biomed Mater Res, 49 (1), pp. 66-78; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) J Am Chem Soc, 111 (1), pp. 321-335; Herrwerth, S., Eck, W., Reinhardt, S., Grunze, M., Factors that determine the protein resistance of oligoether self-assembled monolayers - internal hydrophilicity, terminal hydrophilicity, and lateral packing density (2003) J Am Chem Soc, 125 (31), pp. 9359-9366; Lottenberg, R., Christensen, U., Jackson, C.M., Coleman, P.L., Assay of coagulation proteases using peptide chromogenic and fluorogenic substrates (1981) Meth Enzymol, 80 (PART C), pp. 341-361; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl-terminated alkanethiols self-assembled monolayers (2003) J Biomed Mater Res A, 67 A (1), pp. 158-171; Martins, M.C.L., Curtin, S.A., Freitas, S.C., Salgueiro, P., Ratner, B.D., Barbosa, M.A., Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide (2009) J Biomed Mater Res A, 88 (1), pp. 162-173; (1993) Iodine-125. A guide to radioiodination techniques, , Amersham Life Science, Little Chalfort; Rahmelow, K., Hubner, W., Ackermann, T., Infrared absorbances of protein side chains (1998) Anal Biochem, 257 (1), pp. 1-11; Barth, A., The infrared absorption of amino acid side chains (2000) Prog Biophys Mol Biol, 74 (3-5), pp. 141-173; Li, L., Chen, S., Zheng, J., Ratner, B.D., Jiang, S., Protein adsorption on oligo(ethylene glycol)-terminated alkanethiolate self-assembled monolayers: the molecular basis for nonfouling behavior (2005) J Phys Chem B, 109 (7), pp. 2934-2941; Beamson, G., Briggs, D., (1992) High resolution XPS of organic polymers, , John Wiley and Sons, Ltd;, New York; Adden, N., Gamble, L.J., Castner, D.G., Hoffmann, A., Gross, G., Menzel, H., Phosphonic acid monolayers for binding of bioactive molecules to titanium surfaces (2006) Langmuir, 22 (19), pp. 8197-8204; Sousa, S.R., Moradas-Ferreira, P., Saramago, B., Viseu Melo, L., Barbosa, M.A., Human serum albumin adsorption on TiO 2 from single protein solutions and from plasma (2004) Langmuir, 20 (22), pp. 9745-9754; Di Cera, E., Thrombin interactions (2003) Chest, 124 (SUPPL. 3), pp. 11S-17S; Markwardt, F., Historical perspective of the development of thrombin inhibitors (2002) Pathophysiol Haemost Thromb, 32 (SUPPL. 3), pp. 15-22; Hearn, M.T., 1,1′-Carbonyldiimidazole-mediated immobilization of enzymes and affinity ligands (1987) Methods Enzymol, 135, pp. 102-117; Stöllner, D., Scheller, F.W., Warsinke, A., Activation of cellulose membranes with 1,1′-carbonyldiimidazole or 1-cyano-4-dimethylaminopyridinium tetrafluoroborate as a basis for the development of immunosensors (2002) Anal Biochem, 304 (2), pp. 157-165; Martins, M.C.L., Naeemi, E., Ratner, B.D., Barbosa, M.A., Albumin adsorption on Cibacron Blue F3G-A immobilized onto oligo(ethylene glycol)- terminated self-assembled monolayers (2003) J Mater Sci Mater Med, 14 (11), pp. 945-954; Dee, K.C., Puleo, D.A., Bizios, R., (2002) An introduction to tissue-biomaterial interactions, , Wiley-Liss, Inc; Malmsten, M., Lassen, B., Competitive adsorption at hydrophobic surfaces from binary protein systems (1994) J Colloid Interface Sci, 166 (2), pp. 490-498
Keywords: Absorption spectroscopy; Adsorption; adsorption kinetics; Albumins; Amino Acid Sequence; Amino acids; Angle measurement; article; Biomaterials; Blood; Blood clotting; Blood contact; Carbonyldiimidazole; Coagulation; Coagulation system; concentration (parameters); Concentration-dependent; Contact angle; D-phenylalanine; ellipsometry; Ethylene; Ethylene Glycol; ethylene glycol derivative; gold; Hemocompatibility; Humans; imidazole derivative; Immobilized Proteins; Infrared reflection absorption spectroscopy; infrared spectroscopy; Iodine Radioisotopes; isotope labeling; Medical Devices; monolayer culture; nanoanalysis; Nanostructured surface; peptide; Peptide immobilization; Peptides; phenylalanylprolylarginylprolylglycine; Phosphatases; priority journal; Protein adsorption; protein assembly; protein function; protein immobilization; quantitative study; Sams; Self assembled monolayers; Self-assembled monolayers; Serine protease; Solubility; Solutions; Spectroscopy, Fourier Transform Infrared; Surface functionalization; Surface Properties; Tetra; tetra(ethylene glycol); Thrombin; thrombin inhibitor; Thrombin inhibitors; Thrombus formation; unclassified drug; X ray photoelectron spectroscopy

Effect of nanoscale topography on fibronectin adsorption, focal adhesion size and matrix organisation - González-García, C.; Sousa, S.R.; Moratal, D.; Rico, P.; Salmerón-Sánchez, M. (Colloids and Surfaces B: BiointerfacesColloids Surf. B Biointerfaces, 2010)
Phase separation of PLLA/PS (50/50, w/w) solutions during a spin-casting process gives rise to well-defined nanotopographies of 14, 29 and 45. nm deep pits depending on the concentration of the solution. Their influence on the biological activity of fibronectin (FN) was investigated. FN adsorption was quantified by radiolabelling the protein. The amount of adsorbed FN was higher on the 14. nm deep pit nanotopography than on the other two surfaces. FN distribution between valleys and peaks was investigated by AFM combined with image analysis. FN tends to adsorb preferentially on the valleys of the nanotopography only for the 14. nm system and when adsorbed from solutions of concentration lower than 10μg/ml. Higher concentration of the FN solution leads to evenly distribution of the protein throughout the surface; moreover, there is no difference in the distribution of the protein between valleys and peaks for the other two systems (29 and 45. nm) irrespective of the concentration of the FN solution. The biological activity of the adsorbed protein layer was assessed by investigating MC3T3 osteoblast-like cells adhesion, FN reorganisation and late matrix formation on the different substrates. Even if initial cell adhesion is excellent for every substrate, the size of the focal adhesion plaques increases as the size of the pits in the nanotopography does. This is correlated to FN reorganisation, which only takes places on the 29 and 45. nm deep pits surfaces, where enhanced late matrix production was also found. © 2010 Elsevier B.V.
Cited By (since 1996): 25Export Date: 21 November 2012Source: ScopusCODEN: CSBBEdoi: 10.1016/j.colsurfb.2010.01.021PubMed ID: 20185279Language of Original Document: EnglishCorrespondence Address: Rico, P.; Center for Biomaterials and Tissue Engineering, Universidad Politécnica de Valencia, 46022 Valencia, Spain; email: parico@upvnet.upv.esChemicals/CAS: fibronectin, 86088-83-7; polylactic acid, 26100-51-6; polystyrene, 9003-53-6; Fibronectins; ProteinsReferences: Spie, J., (2002) Ann. N. Y. Acad. Sci., 961, p. 1;Griffin, L., Naughton, G., (2002) Science, 259, p. 1009; Grinnell, F., (1986) J. Cell Biol., 103, p. 2697; Hynes, R.O., (2002) Cell, 110, p. 673; Wong, J.Y., Leach, J.B., Brown, X.Q., (2004) Surf. Sci., 570, p. 119; Schwarz, U.S., Bischofs, I.B., (2005) Med. Eng. Phys., 27, p. 763; Ohara, P.T., Buck, R.C., (1979) Exp. Cell Res., 121, p. 235; Lim, J.Y., Donahue, H.J., (2007) Tissue Eng., 13, p. 1879; Affrossman, S., Jerome, R., O'Neill, S.A., Schmitt, T., Stamm, M., (2000) Colloid Polym. Sci., 278, p. 888; Denis, F.A., Hanarp, P., Sutherland, D.S., Dufrene, Y.F., (2002) Nanoletters, 2, p. 1419; Vieu, C., Carcenac, F., Pepin, A., Chen, Y., Mejias, M., Lebib, A., Manin-Ferlazzo, L., Launois, H., (2000) Appl. Surf. Sci., 164, p. 111; Kriparamanan, R., Aswath, P., Zhou, A., Tang, L., Nguyen, K.T., (2006) J. Nanosci. Nanotechnol., 6, p. 1905; Dalby, M.J., Giannaras, D., Riehle, M.O., Gadegaard, N., Affrossman, S., Curtis, A.S.G., (2004) Biomaterials, 25, p. 77; Lim, J.Y., Dreiss, D., Zhou, Z., Hansen, J.C., Siedlecki, C.A., Hengstebeck, R.W., Cheng, J., Donahue, H.J., (2007) Biomaterials, 28, p. 1787; Dalby, M.J., Hart, A., Yarwood, S.J., (2008) Biomaterials, 29, p. 282; Zinger, O., Zhao, G., Schwartz, Z., Simpson, J., Wieland, M., Landlolt, D., Boyan, B., (2005) Biomaterials, 26, p. 1837; Dalby, M.J., Gadegaard, N., Tare, R., Andar, A., Riehle, M.O., Herzyk, P., Wilkinson, C.D.W., Oreffo, R.O.C., (2007) Nat. Mater., 9, p. 997; Dalby, M.J., McCloy, D., Robertson, M., Wilkinson, C.D.W., Oreffo, R.O.C., (2006) Biomaterials, 27, p. 1306; Pirouz-Dolatshahi, A., Rechendorff, K., Hovgaard, M.B., Foss, M., Chevallier, J., Besenbacher, F., (2008) Colloid Surf. B, 66, p. 53; Khor, H.L., Kukula, H., Tamada, K., Knoll, W., Moeller, M., Hutmacher, D.W., (2007) Biomacromolecules, 8, p. 1530; Cai, K., Bossert, J., Jandt, K., (2006) Colloid Surf. B, 49, p. 136; (1993), p. 64. , Iodine-125, Amersham International, Little Chalfont, Buckinghamshire, U.K.Sousa, S.R., Brás, M., Moradas-Ferreira, P., Barbosa, M.A., (2007) Langmuir, 23, p. 7046; Otsu, N.A., (1979) IEEE Trans. Syst. Man Cybern., 9, p. 62; Gonzalez, R.C., Woods, R.E., Eddins, S.L., (2003) Digital Image Processing Using MATLAB, , Prentice-Hall, Upper Saddle River, NJ; Gonzalez, R.C., Woods, R.E., (2007) Digital Image Processing, , Prentice-Hall, Upper Saddle River, NJ; (2006), MATLAB Image Processing Toolbox User's Guide, The MathWorks, Inc., Natick, MAAllen, L.T., Tosetto, M., Miller, I.S., O'Connor, D.P., Penney, S.C., Lynch, I., Keenan, A.K., Gallagher, W.M., (2006) Biomaterials, 27, p. 3096; Gugutkov, D., Altankov, G., Rodríguez Hernández, J.C., Monleón Pradas, M., Salmerón Sánchez, M., (2010) J. Biomed. Mater. Res. A, 92, p. 322; Rico, P., Rodríguez Hernández, J.C., Moratal, D., Monleón Pradas, M., Salmerón Sánchez, M., (2009) Macromol. Biosci., 9, p. 766; Keselowsky, B.G., Collard, D.M., García, A.J., (2003) J. Biomed. Mater. Res. A, 66, p. 247; Lee, M.H., Ducheyne, P., Lynch, L., Boettiger, D., Composto, R.J., (2006) Biomaterials, 27, p. 1907; Costa Martínez, E., Rodríguez Hernández, J.C., Machado, M., Mano, J., Gómez Ribelles, J.L., Monleón Pradas, M., Salmerón Sánchez, M., (2008) Tissue Eng., 14, p. 1751; Lim, J.Y., Hansen, J.C., Siedlecki, C.A., Hengstebeck, R.A., Cheng, J., Winograd, N., (2005) Biomacromolecules, 6, p. 3319; Liu, X., Lim, J.Y., Donahue, H.J., Dhurjati, R., Maestro, A.M., Vogler, E.A., (2007) Biomaterials, 28, p. 4535; Dalby, M.J., Yarwood, S.J., Riehle, M.O., Johnstone, H.J., Affressman, S., Curtis, A.S., (2002) Exp. Cell Res., 276, p. 1; Dalby, M.J., Childs, S., Riehle, M.O., Johnston, H.J.H., Affrossman, S., (2003) Biomaterials, 24, p. 927; Dalby, M.J., McCloy, D., Robertson, M., Agheli, H., Sutherland, D., Affrossman, S., Oreffo, R.O.C., (2006) Biomaterials, 27, p. 2980; Dalby, M.J., (2005) Med. Eng. Phys., 27, p. 730; Galbraith, C.G., Yamada, K.M., Sheetz, M.P., (2002) J. Cell Biol., 159, p. 695; Balaban, N.Q., Schwarz, U.S., Riveline, D., Goichberg, P., Tzur, G., Sabanay, I., (2001) Nat. Cell Biol., 3, p. 466; Pegueroles, M., Aparicio, C., Bosio, M., Engel, E., Gil, F.J., Planell, J.A., Altankov, G., Acta Biomater. (). doi:10.1016/j.actbio.2009.07.030Altankov, G., Groth, T., (1994) J. Mater. Sci. Mater. Med., 5, p. 732; Altankov, G., Groth, T., (1996) J. Mater. Sci. Mater. Med., 7, p. 425; Altankov, G., Grinnell, F., Groth, T., (1996) J. Biomed. Mater. Res., 30, p. 385; Tzoneva, R., Groth, T., Altankov, G., Paul, D., (2002) J. Mater. Sci. Mater. Med., 13, p. 1235; Gonçalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., (2005) Biomaterials, 26, p. 3891; Luthen, F., Lange, R., Becker, P., Rychly, J., Beck, U., Nebe, J.G.B., (2005) Biomaterials, 26, p. 2423; Geiger, B., Bershadsky, A., Pankov, R., Yamada, K.M., (2001) Nat. Rev. Mol. Cell Biol., 2, p. 793; Altankov, G., Groth, T., (1996) J. Biomater. Sci. Polym. Ed., 8, p. 299
Keywords: 3T3 Cells; Adhesion; Adsorption; AFM; animal cell; Animals; article; Atomic force microscopy; Bioactivity; Biological activities; biological activity; Casting process; cell adhesion; Cell Line; concentration (parameters); Concentration (process); Concentration of; Deep pit; Different substrates; Electric currents; extracellular matrix; Fibronectin; Fibronectin adsorption; Fibronectins; focal adhesion; Focal adhesion plaques; Focal adhesions; Humans; Image analysis; Image Processing, Computer-Assisted; isotope labeling; Landforms; matrix; Matrix formation; Mice; Microscopy, Atomic Force; nanomaterial; Nanoscale topography; Nanotechnology; Nanotopographies; Nanotopography; nonhuman; osteoblast; Osteoblast-like cells; Osteoblasts; Phase separation; polylactic acid; polystyrene; priority journal; Protein adsorption; Protein layers; protein localization; Proteins; Radiolabelling; Reorganisation; Substrates; Surface Properties

Functionalization of poly(amidoamine) dendrimers with hydrophobic chains for improved gene delivery in mesenchymal stem cells - Santos, J.L.; Oliveira, H.; Pandita, D.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (Journal of Controlled ReleaseJ. Control. Release, 2010)
A new family of gene delivery vectors is synthesized consisting of a medium-size generation PAMAM dendrimer (generation 5, with amine termini) core randomly linked at the periphery to hydrophobic chains that vary in length (12 to 16 carbon alkyl chains) and number (from 4.2 to 9.7 in average). The idea subjacent to the present work is to join the advantages of the cationic nature of the dendrimer with the capacity of lipids to interact with biological membranes. Unlike other amphiphilic systems designed for the same purpose, where the hydrophobic and hydrophilic moieties coexist in opposite sides, the present vectors have a hydrophilic interior and a hydrophobic corona. The vectors are characterized in respect to their ability to neutralize, bind and compact plasmid DNA (pDNA). The complexes formed between the vectors and pDNA are analyzed concerning their size, ζ-potential, resistance to serum nucleases, capacity of being internalized by cells and transfection efficiency. These new vectors show a remarkable capacity for mediating the internalization of pDNA with minimum cytotoxicity, being this effect positively correlated with the -CH 2- content present in the hydrophobic corona. Gene expression in MSCs, a cell type with relevancy in the regenerative medicine clinical context, is also enhanced using the new vectors but, in this case, the higher efficiency is shown by the vectors containing the smallest hydrophobic chains. © 2010 Elsevier B.V.
Cited By (since 1996): 28Export Date: 21 November 2012Source: ScopusCODEN: JCREEdoi: 10.1016/j.jconrel.2010.01.034PubMed ID: 20138937Language of Original Document: EnglishCorrespondence Address: Tomás, H.; CQM - Centro de Química da Madeira, MMRG, Departamento de Química, Universidade da Madeira, Campus Universitário da Penteada, 9000-390 Funchal, Portugal; email: lenat@uma.ptChemicals/CAS: lipid, 66455-18-3; nuclease, 9026-81-7; Cations; DNA, 9007-49-2; Dendrimers; Lipids; PAMAM StarburstReferences: Segura, T., Shea, L.D., Materials for non-viral gene delivery (2001) Annu. Rev. Mat. Res., 31, pp. 25-46;Mastrobattista, E., Bravo, S.A., van der Aa, M., Crommelin, D.J.A., Nonviral gene delivery systems: from simple transfection agents to artificial viruses (2005) Drug Discov. Today Technol., 2, pp. 103-109; Colella, P., Cotugno, G., Auricchio, A., Ocular gene therapy: current progress and future prospects (2009) Trends Mol. Med., 15, pp. 23-31; Scanlon, K.J., Cancer gene therapy: challenges and opportunities (2004) Anticancer Res., 24, pp. 501-504; Gersbach, C.A., Phillips, J.E., Garcia, A.J., Genetic engineering for skeletal regenerative medicine (2007) Annu. Rev. Biomed. Eng., 9, pp. 87-119; Heyde, M., Partridge, K.A., Oreffo, R.O., Howdle, S.M., Shakesheff, K.M., Garnett, M.C., Gene therapy used for tissue engineering applications (2007) J. Pharm. Pharmacol., 59, pp. 329-350; Gafni, Y., Turgeman, G., Liebergal, M., Pelled, G., Gazit, Z., Gazit, D., Stem cells as vehicles for orthopedic gene therapy (2004) Gene Ther., 11, pp. 417-426; Vaananen, H.K., Mesenchymal stem cells (2005) Ann. Med., 37, pp. 469-479; Phillips, J.E., Gersbach, C.A., Garcia, A.J., Virus-based gene therapy strategies for bone regeneration (2007) Biomaterials, 28, pp. 211-229; Lundstrom, K., Latest development in viral vectors for gene therapy (2003) Trends Biotechnol., 21, pp. 117-122; Noel, D., Gazit, D., Bouquet, C., Apparailly, F., Bony, C., Plence, P., Millet, V., Jorgensen, C., Short-term BMP-2 expression is sufficient for in vivo osteochondral differentiation of mesenchymal stem cells (2004) Stem Cells, 22, pp. 74-85; Mintzer, M.A., Simanek, E.E., Nonviral vectors for gene delivery (2009) Chem. Rev., 109, pp. 259-302; Hamm, A., Krott, N., Breibach, I., Blindt, R., Bosserhoff, A.K., Efficient transfection method for primary cells (2002) Tissue Eng., 8, pp. 235-245; McMahon, J.M., Conroy, S., Lyons, M., Greiser, U., O'Shea, C., Strappe, P., Howard, L., O'Brien, T., Gene transfer into rat mesenchymal stem cells: a comparative study of viral and nonviral vectors (2006) Stem Cells Dev., 15, pp. 87-96; Jang, W.-D., Selim, K.M.K., Lee, C.-H., Kang, I.-K., Bioinspired application of dendrimers: from bio-mimicry to biomedical applications (2009) Prog. Polym. Sci., 34, pp. 1-23; Svenson, S., Tomalia, D.A., Dendrimers in biomedical applications-reflections on the field (2005) Adv. Drug Deliv. Rev., 57, pp. 2106-2129; Caminade, A.M., Turrin, C.O., Majoral, J.P., Dendrimers and DNA: combinations of two special topologies for nanomaterials and biology (2008) Chemistry, 14, pp. 7422-7432; Dufes, C., Uchegbu, I.F., Schatzlein, A.G., Dendrimers in gene delivery (2005) Adv. Drug Deliv. Rev., 57, pp. 2177-2202; Guillot, M., Eisler, S., Diederich, F., Dendritic vectors for gene transfection (2007) New J. Chem., 31, pp. 1111-1127; Lechardeur, D., Verkman, A.S., Lukacs, G.L., Intracellular routing of plasmid DNA during non-viral gene transfer (2005) Adv. Drug Deliv. Rev., 57, pp. 755-767; Smith, D.K., Dendrimers and the double helix - from DNA binding towards gene therapy (2008) Curr. Top. Med. Chem., 8, pp. 1187-1203; Dobrovolskaia, M.A., McNeil, S.E., Immunological properties of engineered nanomaterials (2007) Nat. Nanotechnol., 2, pp. 469-478; Kukowska-Latallo, J.F., Bielinska, A.U., Johnson, J., Spindler, R., Tomalia, D.A., Baker, J.R., Efficient transfer of genetic material into mammalian cells using Starburst polyamidoamine dendrimers (1996) Proc. Natl. Acad. Sci. U.S.A., 93, pp. 4897-4902; Santos, J.L., Oramas, E., Pego, A.P., Granja, P.L., Tomas, H., Osteogenic differentiation of mesenchymal stem cells using PAMAM dendrimers as gene delivery vectors (2009) J. Control. Release, 134, pp. 141-148; Dennig, J., Duncan, E., Gene transfer into eukaryotic cells using activated polyamidoamine dendrimers (2002) J. Biotechnol., 90, pp. 339-347; Kono, K., Akiyama, H., Takahashi, T., Takagishi, T., Harada, A., Transfection activity of polyamidoamine dendrimers having hydrophobic amino acid residues in the periphery (2005) Bioconjug. Chem., 16, pp. 208-214; Takahashi, T., Harada, A., Emi, N., Kono, K., Preparation of efficient gene carriers using a polyamidoamine dendron-bearing lipid: improvement of serum resistance (2005) Bioconjug. Chem., 16, pp. 1160-1165; Takahashi, T., Kojima, C., Harada, A., Kono, K., Alkyl chain moieties of polyamidoamine dendron-bearing lipids influence their function as a nonviral gene vector (2007) Bioconjug. Chem., 18, pp. 1349-1354; Takahashi, T., Kono, K., Itoh, T., Emi, N., Takagishi, T., Synthesis of novel cationic lipids having polyamidoamine dendrons and their transfection activity (2003) Bioconjug. Chem., 14, pp. 764-773; Jones, S.P., Gabrielson, N.P., Pack, D.W., Smith, D.K., Synergistic effects in gene delivery - a structure-activity approach to the optimisation of hybrid dendritic-lipidic transfection agents (2008) Chem. Commun., 39, pp. 4700-4702; Shah, D.S., Sakthivel, T., Toth, I., Florence, A.T., Wilderspin, A.F., DNA transfection and transfected cell viability using amphipathic asymmetric dendrimers (2000) Int. J. Pharm., 208, pp. 41-48; Ahmad, A., Evans, H.M., Ewert, K., George, C.X., Samuel, C.E., Safinya, C.R., New multivalent cationic lipids reveal bell curve for transfection efficiency versus membrane charge density: lipid-DNA complexes for gene delivery (2005) J. Gene Med., 7, pp. 739-748; Ewert, K.K., Evans, H.M., Zidovska, A., Bouxsein, N.F., Ahmad, A., Safinya, C.R., A columnar phase of dendritic lipid-based cationic liposome-DNA complexes for gene delivery: hexagonally ordered cylindrical micelles embedded in a DNA honeycomb lattice (2006) J. Am. Chem. Soc., 128, pp. 3998-4006; Guillot, M., Eisler, S., Weller, K., Merkle, H.P., Gallani, J.L., Diederich, F., Effects of structural modification on gene transfection and self-assembling properties of amphiphilic dendrimers (2006) Org. Biomol. Chem., 4, pp. 766-769; Joester, D., Losson, M., Pugin, R., Heinzelmann, H., Walter, E., Merkle, H.P., Diederich, F., Amphiphilic dendrimers: novel self-assembling vectors for efficient gene delivery (2003) Angew. Chem. Int. Ed., 42, pp. 1486-1490; Alvarez, E., Girones, N., Davis, R.J., Inhibition of the receptor-mediated endocytosis of diferric transferrin is associated with the covalent modification of the transferrin receptor with palmitic acid (1990) J. Biol. Chem., 265, pp. 16644-16655; Jevprasesphant, R., Penny, J., Attwood, D., McKeown, N.B., D'Emanuele, A., Engineering of dendrimer surfaces to enhance transepithelial transport and reduce cytotoxicity (2003) Pharm. Res., 20, pp. 1543-1550; Snyder, S.L., Sobocinski, P.Z., An improved 2,4,6-trinitrobenzenesulfonic acid method for the determination of amines (1975) Anal. Biochem., 64, pp. 284-288; Lapidot, Y., Rappoport, S., Wolman, Y., Use of esters of N-hydroxysuccinimide in the synthesis of N-acylamino acids (1967) J. Lipid. Res., 8, pp. 142-145; Gao, X., Huang, L., Potentiation of cationic liposome-mediated gene delivery by polycations (1996) Biochemistry, 35, pp. 1027-1036; Aubin, J.E., Osteoprogenitor cell frequency in rat bone marrow stromal populations: role for heterotypic cell-cell interactions in osteoblast differentiation (1999) J. Cell Biochem., 72, pp. 396-410; Perrot, S., Dutertre-Catella, H., Martin, C., Rat, P., Warnet, J.M., Resazurin metabolism assay is a new sensitive alternative test in isolated pig cornea (2003) Toxicol. Sci., 72, pp. 122-129; Hosseinkhani, H., Yamamoto, M., Inatsugu, Y., Hiraoka, Y., Inoue, S., Shimokawa, H., Tabata, Y., Enhanced ectopic bone formation using a combination of plasmid DNA impregnation into 3-D scaffold and bioreactor perfusion culture (2006) Biomaterials, 27, pp. 1387-1398; Wong, S.Y., Pelet, J.M., Putnam, D., Polymer systems for gene delivery - past, present, and future (2007) Prog. Polym. Sci., 32, pp. 799-837; Abbasi, M., Uludag, H., Incani, V., Hsu, C.Y., Jeffery, A., Further investigation of lipid-substituted poly(L-lysine) polymers for transfection of human skin fibroblasts (2008) Biomacromolecules, 9, pp. 1618-1630; Sorgi, F.L., Bhattacharya, S., Huang, L., Protamine sulfate enhances lipid-mediated gene transfer (1997) Gene Ther., 4, pp. 961-968; Lampela, P., Soininen, P., Urtti, A., Männistö, P.T., Raasmaja, A., Synergism in gene delivery by small PEIs and three different nonviral vectors (2004) Int. J. Pharm., 270, pp. 175-184; Brito, L., Little, S., Langer, R., Amiji, M., Poly(β-amino ester) and cationic phospholipid-based lipopolyplexes for gene delivery and transfection in human aortic endothelial and smooth muscle cells (2008) Biomacromolecules, 9, pp. 1179-1187; Hardy, J.G., Love, C.S., Gabrielson, N.P., Pack, D.W., Smith, D.K., Synergistic effects on gene delivery - co-formulation of small disulfide-linked dendritic polycations with Lipofectamine 2000TM (2009) Org. Biomol. Chem., 7, pp. 789-793; Callow, P., Fragneto, G., Cubitt, R., Barlow, D.J., Lawrence, M.J., Timmins, P., Interaction of cationic lipid vesicles with model cell membranes - as determined by neutron reflectivity (2005) Langmuir, 21, pp. 7912-7920; Malik, N., Wiwattanapatapee, R., Klopsch, R., Lorenz, K., Frey, H., Weener, J.W., Meijer, E.W., Duncan, R., Dendrimers: relationship between structure and biocompatibility in vitro, and preliminary studies on the biodistribution of 125I-labelled polyamidoamine dendrimers in vivo (2000) J. Control. Release, 65, pp. 133-148
Keywords: amphophile; animal cell; animal experiment; article; Biological membranes; Biomedical applications; cation; Cations; Cell culture; cell membrane transport; cell type; Cellular uptake; controlled study; Cytotoxicity; dendrimer; Dendrimers; DNA; DNA binding; Dyes; Functional polymers; Gene delivery; gene delivery system; gene expression; Gene therapy; Gene transfer; Gene Transfer Techniques; gene vector; Genes; genetic transfection; Genetic Vectors; Humans; Hydrocarbons; hydrophilicity; hydrophobicity; internalization; lipid; Lipids; male; Mesenchymal stem cell; Mesenchymal Stem Cells; nonhuman; nuclease; Nucleic acids; plasmid DNA; Plasmids; Poly(amidoamine) dendrimers; polyamidoamine; Polyamidoamine dendrimers; priority journal; rat; Regenerative Medicine; Stem cells; Transfection; Vectors; Zeta potential

Immobilization of human mesenchymal stem cells within RGD-grafted alginate microspheres and assessment of their angiogenic potential - Bidarra, S.J.; Barrias, C.C.; Barbosa, M.A.; Soares, R.; Granja, P.L. (BiomacromoleculesBiomacromolecules, 2010)
In this work, human mesenchymal stem cells (hMSC) immobilized in RGD-coupled alginate microspheres, with a binary composition of high and low molecular weight alginate, were investigated. Cells immobilized within RGD-alginate microspheres (during 21 days) showed metabolic activity, with an overall viability higher than 90%, short cell extensions, and, when induced, they were able to differentiate into the osteogenic lineage. In osteogenic conditions (comparing to basal conditions), immobilized cells presented alkaline phosphatase (ALP) activity and an upregulation of ALP, collagen type I, and Runx 2 expression. Moreover, mineralization was also detected in immobilized cells under osteogenic stimulus. In addition, it was demonstrated for the first time that MSCs immobilized in this 3D matrix were able to enhance the ability of neighboring endothelial cells to form tubelike structures. Overall, these findings represent a step forward in the development of injectable stem cell carriers for bone tissue engineering. © 2010 American Chemical Society.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm100264aPubMed ID: 20690708Language of Original Document: EnglishCorrespondence Address: Granja, P. L.; INEB-Instituto de Engenharia Biomédica, Rua do Campo Alegre No. 823, 4150-180 Porto, Portugal; email: pgranja@ineb.up.ptMolecular Sequence Numbers: GENBANK: BC021289, NM_000088, NM_002046;Chemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; alkaline phosphatase, 9001-78-9; arginylglycylaspartic acid, 99896-85-2; Alginates; Alkaline Phosphatase, 3.1.3.1; Collagen Type I; DNA Primers; Oligopeptides; arginyl-glycyl-aspartic acid, 99896-85-2References: Temenoff, J.S., Mikos, A.G., Injectable biodegradable materials for orthopedic tissue engineering (2000) Biomaterials, 21, pp. 2405-2412;Barralet, J.E., Wang, L., Lawson, M., Triffitt, J.T., Cooper, P.R., Shelton, R.M., Comparison of bone marrow cell growth on 2D and 3D alginate hydrogels (2005) J. Mater. Sci.: Mater. Med., 16, pp. 515-519; Ma, H.L., Hung, S.C., Lin, S.Y., Chen, Y.L., Lo, W.H., Chondrogenesis of human mesenchymal stem cells encapsulated in alginate beads (2003) J. Biomed. Mater. Res., 64, pp. 273-281; Augst, A.D., Kong, H.J., Mooney, D.J., Alginate hydrogels as biomaterials (2006) Macromol. Biosci., 6, pp. 623-633; Smidsrod, O., Skjak-Braek, G., Alginate as immobilization matrix for cells (1990) Trends Biotechnol., 8, pp. 71-78; Jen, A.C., Wake, M.C., Mikos, A.G., Review: Hydrogels for cell immobilization (1996) Biotechnol. Bioeng., 50, pp. 357-364; Oliveira, S.M., Barrias, C.C., Almeida, I.F., Costa, P.C., Ferreira, M.R.P., Bahia, M.F., Barbosa R. M, A., Injectability of a bone filler system based on hydroxyapatite microspheres and a vehicle with in situ gel-forming ability (2008) J. Biomed. Mater. Res. B, 87, pp. 49-8; Evangelista, M.B., Hsiong, S.X., Fernandes, R., Sampaio, P., Kong, H.-J., Barrias, C.C., Salema, R., Granja, P.L., Upregulation of bone cell differentiation through immobilization within a synthetic extracellular matrix (2007) Biomaterials, 28, pp. 3644-3655; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20, pp. 45-53; Kong, H.J., Smith, M.K., Mooney, D.J., Designing alginate hydrogels to maintain viability of immobilized cells (2003) Biomaterials, 24, pp. 4023-4029; Grellier, M., Granja, P.L., Fricain, J.-C., Bidarra, S.J., Renard, M., Bareille, R., Bourget, C., Barbosa, M.A., The effect of the co-immobilization of human osteoprogenitors and endothelial cells within alginate microspheres on mineralization in a bone defect (2009) Biomaterials, 30, pp. 3271-3278; Caplan, A.I., Adult mesenchymal stem cells for tissue engineering versus regenerative medicine (2007) J. Cell. Physiol., 213, pp. 341-347; Horwitz, E.M., MSC: A coming of age in regenerative medicine (2006) Cytotherapy, 8, pp. 194-195; Sumanasinghe, R.D., Bernacki, S.H., Loboa, E.G., Osteogenic differentiation of human mesenchymal stem cells in collagen matrices: Effect of uniaxial cyclic tensile strain on bone morphogenetic protein (BMP-2) mRNA expression (2006) Tissue Eng., 12, pp. 3459-3465; Granero-Molto, F., Weis, J.A., Longobardi, L., Spagnoli, A., Role of mesenchymal stem cells in regenerative medicine: Application to bone and cartilage repair (2008) Expert Opin. Biol. Ther., 8, pp. 255-268; Markusen, J.F., Mason, C., Hull, D.A., Town, M.A., Tabor, A.B., Clements, M., Boshoff, C.H., Dunnill, P., Behavior of adult human mesenchymal stem cells entrapped in alginate-GRGDY beads (2006) Tissue Eng., 12, pp. 821-830; Duggal, S., Fronsdal, K.B., Szoke, K., Shahdadfar, A., Melvik, J.E., Brinchmann, J.E., Phenotype and gene expression of human mesenchymal stem cells in alginate scaffolds (2009) Tissue Eng., Part A, 15, pp. 1763-1773; Kasper, G., Dankert, N., Tuischer, J., Hoeft, M., Gaber, T., Glaeser, J.D., Zander, D., Duda, G.N., Mesenchymal stem cells regulate angiogenesis according to their mechanical environment (2007) Stem Cells, 25, pp. 903-910; Gruber, R., Kandler, B., Holzmann, P., Vogele-Kadletz, M., Losert, U., Fischer, M.B., Watzek, G., Bone marrow stromal cells can provide a local environment that favors migration and formation of tubular structures of endothelial cells (2005) Tissue Eng., 11, pp. 896-903; Valarmathi, M.T., Yost, M.J., Goodwin, R.L., Potts, J.D., A three-dimensional tubular scaffold that modulates the osteogenic and vasculogenic differentiation of rat bone marrow stromal cells (2008) Tissue Eng., Part A, 14, pp. 491-504; Potapova, I.A., Gaudette, G.R., Brink, P.R., Robinson, R.B., Rosen, M.R., Cohen, I.S., Doronin, S.V., Mesenchymal stem cells support migration, extracellular matrix invasion, proliferation, and survival of endothelial cells in vitro (2007) Stem Cells, 25, pp. 1761-1768; Moon, J.J., West, J.L., Vascularization of engineered tissues: Approaches to promote angiogenesis in biomaterials (2008) Curr. Top. Med. Chem., 8, pp. 300-310; Carano, R.A.D., Filvaroff, E.H., Angiogenesis and bone repair (2003) Drug Discovery Today, 8, pp. 980-989; Eriksen, E.F., Eghbali-Fatourechi, G.Z., Khosla, S., Remodeling and vascular spaces in bone (2007) J. Bone Miner. Res., 22, pp. 1-6; Schroeder, T.M., Jensen, E.D., Westendorf, J.J., Runx2: A master organizer of gene transcription in developing and maturing osteoblasts (2005) Birth Defects Res., Part C, 75, pp. 213-225; Soares, R., Guo, S., Ga'rtner, F., Schmitt, F., Russo, J., 17β-Estradiol-mediated vessel assembly and stabilization in tumor angiogenesis requires TGFβ and EGFR crosstalk (2003) Angiogenesis, 6, pp. 271-281; Kubota, Y., Kleinman, H.K., Martin, G.R., Lawley, T.J., Role of laminin and basement membrane in the morphological differentiation of human endothelial cells into capillary-like structures (1988) J. Cell Biol., 107, pp. 1589-1598; Kaully, T., Kaufman-Francis, K., Lesman, A., Levenberg, S., Vascularization-The conduit to viable engineered tissues (2009) Tissue Eng., Part B, 15, pp. 159-169; Silva, E.A., Mooney, D.J., Spatiotemporal control of vascular endothelial growth factor delivery from injectable hydrogels enhances angiogenesis (2007) J. Thromb. Haemost., 5, pp. 590-598; Fuchs, S., Jiang, X., Schmidt, H., Dohle, E., Ghanaati, S., Orth, C., Hofmann, A., Kirkpatrick, C.J., Dynamic processes involved in the pre-vascularization of silk fibroin constructs for bone regeneration using outgrowth endothelial cells (2009) Biomaterials, 30, pp. 1329-1338; Hsiong, S.X., Mooney, D.J., Regeneration of vascularized bone (2006) Periodontol. 2000, 41, pp. 109-122; Abbah, S., Lu, W., Chan, D., Cheung, K., Liu, W., Zhao, F., Li, Z., Luk, K., Osteogenic behavior of alginate encapsulated bone marrow stromal cells: An in vitro study (2008) J. Mater. Sci.: Mater. Med., 19, pp. 2113-2119; Moioli, E.K., Hong, L., Mao, J.J., Inhibition of osteogenic differentiation of human mesenchymal stem cells (2007) Wound Repair Regen., 15, pp. 413-421; Healy, K.E., Guldberg, R.E., Bone tissue engineering (2007) J. Musculoskelet. Neuronal Interact., 7, pp. 328-330; Stein, G.S., Lian, J.B., Owen, T.A., Relationship of cell growth to the regulation of tissue-specific gene expression during osteoblast differentiation (1990) FASEB J., 4, pp. 3111-3123; Lian, J.B., Stein, G.S., Concepts of osteoblast growth and differentiation: Basis for modulation of bone cell development and tissue formation (1992) Crit. Rev. Oral Biol. Med., 3, pp. 269-305; Huang, Y.-C., Kaigler, D., Rice, K.G., Krebsbach, P.H., Mooney, D.J., Combined angiogenic and osteogenic factor delivery enhances bone marrow stromal cell-driven bone regeneration (2005) J. Bone Miner. Res., 20, pp. 848-857; Fang, T.D., Salim, A., Xia, W., Nacamuli, R.P., Guccione, S., Song, H.M., Carano, R.A., Longaker, M.T., Angiogenesis is required for successful bone induction during distraction osteogenesis (2005) J. Bone Miner. Res., 20, pp. 1114-1124; Villars, F., Bordenave, L., Bareille, R., Amédée, J., Effect of human endothelial cells on human bone marrow stromal cell phenotype: Role of VEGF (2000) J. Cell. Biochem., 79, pp. 672-685; Kaigler, D., Krebsbach, P.H., Polverini, P.J., Mooney, D.J., Role of vascular endothelial growth factor in bone marrow stromal cell modulation of endothelial cells (2003) Tissue Eng., 9, pp. 95-103; Grellier, M., Ferreira-Tojais, N., Bourget, C., Bareillke, R., Guillemot, F., Amédée, J., Role of vascular endothelial growth factor in the communication between human osteoprogenitors and endothelial cells (2009) J. Cell. Biochem., 106, pp. 390-398; Yu, J., Gu, Y., Du, K.T., Mihardja, S., Sievers, R.E., Lee, R.J., The effect of injected RGD modified alginate on angiogenesis and left ventricular function in a chronic rat infarct model (2009) Biomaterials, 30, pp. 751-756
Keywords: Alginate; Alginates; alginic acid; alkaline phosphatase; Alkaline phosphatase activity; angiogenesis; arginylglycylaspartic acid; article; Basal conditions; Base Sequence; Binary composition; bone development; Bone tissue engineering; Cell culture; cell differentiation; Cell extension; Cell immobilization; cell metabolism; cell structure; cell viability; collagen type 1; Collagen type I; controlled study; DNA Primers; Endothelial Cells; endothelium cell; enzyme activity; human; human cell; Human mesenchymal stem cells; Humans; immobilized cell; Immobilized cells; Low molecular weight; matrix; Mesenchymal stem cell; Mesenchymal Stem Cells; Metabolic activity; Microscopy, Electron, Scanning; microsphere; Microspheres; molecular weight; Neovascularization, Physiologic; nucleotide sequence; Oligopeptides; osteoblast; Osteogenic; Phosphatases; priority journal; protein expression; quantitative analysis; Reverse Transcriptase Polymerase Chain Reaction; stem cell; Stem cells; three dimensional imaging; Tissue engineering; transcription factor RUNX2; umbilical vein; Up-regulation; upregulation

An improved collagen scaffold for skeletal regeneration - Oliveira, S.M.; Ringshia, R.A.; Legeros, R.Z.; Clark, E.; Yost, M.J.; Terracio, L.; Teixeira, C.C. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
Bone repair and regeneration is one of the most extensively studied areas in the field of tissue engineering. All of the current tissue engineering approaches to create bone focus on intramembranous ossification, ignoring the other mechanism of bone formation, endochondral ossification. We propose to create a transient cartilage template in vitro, which could serve as an intermediate for bone formation by the endochondral mechanism once implanted in vivo. The goals of the study are (1) to prepare and characterize type I collagen sponges as a scaffold for the cartilage template, and (2) to establish a method of culturing chondrocytes in type I collagen sponges and induce cell maturation. Collagen sponges were generated from a 1% solution of type I collagen using a freeze/dry technique followed by UV light crosslinking. Chondrocytes isolated from two locations in chick embryo sterna were cultured in these sponges and treated with retinoic acid to induce chondrocyte maturation and extracellular matrix deposition. Material strength testing as well as microscopic and biochemical analyzes were conducted to evaluate the properties of sponges and cell behavior during the culture period. We found that our collagen sponges presented improved stiffness and supported chondrocyte attachment and proliferation. Cells underwent maturation, depositing an abundant extracellular matrix throughout the scaffold, expressing high levels of type X collagen, type I collagen and alkaline phosphatase. These results demonstrate that we have created a transient cartilage template with potential to direct endochondral bone formation after implantation. © 2010 Wiley Periodicals, Inc.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32694PubMed ID: 20186736Language of Original Document: EnglishCorrespondence Address: Teixeira, C. C.; Department of Basic Science and Craniofacial Biology, Department of Biomaterials and Biomimetics, New York University College of Dentistry, New York, NY 10010, United States; email: ct40@nyu.eduChemicals/CAS: alkaline phosphatase, 9001-78-9; retinoic acid, 302-79-4; Biocompatible Materials; Collagen, 9007-34-5; Protein IsoformsReferences: Pountos, I., Jones, E., Tzioupis, C., Mcgonagle, D., Giannoudis, P.V., Growing bone and cartilage. The role of mesenchymal stem cells (2006) J Bone Joint Surg Br, 88, pp. 421-426;Newman, A.P., Articular cartilage repair (1998) Am J Sports Med, 26, pp. 309-324; Tomihisa, K., Tomoo, M., Toshitaka, T., Tomoyuki, S., New bone formation around porous hydroxyapatite wedge implanted in opening wedge high tibial osteotomy in patients with osteoarthritis (2001) Biomaterials, 22, pp. 1579-1582; Weiss, P., Layrolle, P., Clergeau, L.P., Enckel, B., Pilet, P., Amouriq, Y., Daculsi, G., Giumelli, B., The safety and efficacy of an injectable bone substitute in dental sockets demonstrated in a human clinical trial (2007) Biomaterials, 28, pp. 3295-3305; Verlaan, J.J., Oner, F.C., Dhert, W.J., Anterior spinal column augmentation with injectable bone cements (2006) Biomaterials, 27, pp. 290-301; Zelzer, E., Olsen, B.R., The genetic basis for skeletal diseases (2003) Nature, 423, pp. 343-348; Ivaska, K.K., Gerdhem, P., Åkesson, K., Garnero, P., Obrant, K.J., Effect of fracture on bone turnover markers: A longitudinal study comparing marker levels before and after injury in 113 elderly women (2007) J Bone Miner Res, 22, pp. 1155-1164; Hunziker, E.B., Articular cartilage repair: Basic science and clinical progress. A review of the current status and prospects (2002) Osteoarthritis Cartilage, 10, pp. 432-463; Curran, S.J., Chen, R., Curran, J.M., Hunt, J.A., Expansion of human chondrocytes in an intermittent stirred flow bioreactor, using modified biodegradable microspheres (2005) Tissue Eng, 11, pp. 1312-1322; Vinatier, C., Magne, D., Moreau, A., Gauthier, O., Malard, O., Vignes-Colombeix, C., Daculsi, G., Guicheux, J., Engineering cartilage with human nasal chondrocytes and a silanized hydroxypropyl methylcellulose hydrogel (2007) J Biomed Mater Res Part A, 80, pp. 66-74; Pound, J.C., Green, D.W., Chaudhuri, J.B., Mann, S., Roach, H.I., Oreffo, R.O., Strategies to promote chondrogenesis and osteogenesis from human bone marrow cells and articular chondrocytes encapsulated in polysaccharide templates (2006) Tissue Eng, 12, pp. 2789-2799; Kasten, P., Vogel, J., Luginbuhl, R., Niemeyer, P., Tonak, M., Lorenz, H., Helbig, L., Leo, A., Ectopic bone formation associated with mesenchymal stem cells in a resorbable calcium deficient hydroxyapatite carrier (2005) Biomaterials, 26, pp. 5879-5889; Joon Yung, L., Musgrave, D., Pelinkovic, D., Fukushima, K., Cummins, J., Usas, A., Robbins, P., Huard, J., Effect of bone morphogenetic protein-2-expressing muscle-derived cells on healing of critical-sized bone defects in mice (2001) Journal of Bone and Joint Surgery - Series a, 83 (7), pp. 1032-1039; Sumanasinghe, R.D., Osborne, J.A., Loboa, E.G., Mesenchymal stem cell-seeded collagen matrices for bone repair: Effects of cyclic tensile strain, cell density, and media conditions on matrix contraction in vitro (2008) J Biomed Mater Res Part A, 88, pp. 778-786; Alsberg, E., Anderson, K.W., Albeiruti, A., Rowley, J.A., Mooney, D.J., Engineering growing tissues (2002) Proc Natl Acad Sci USA, 99, pp. 12025-12030; Arpornmaeklong, P., Suwatwirote, N., Pripatnanont, P., Oungbho, K., Growth and differentiation of mouse osteoblasts on chitosan-collagen sponges (2007) Int J Oral Maxillacial Surgery, 36, pp. 328-337; Lode, A., Bernhardt, A., Gelinsky, M., Cultivation of human bone marrow stromal cells on three-dimensional scaffolds of mineralized collagen: Influence of seeding density on colonization, proliferation and osteogenic differentiation (2008) J Tissue Eng Regenerative Med, 2, pp. 400-407; Balooch, M., Habelitz, S., Kinney, J.H., Marshall, S.J., Marshall, G.W., Mechanical properties of mineralized collagen fibrils as influenced by demineralization (2008) J Struct Biol, 162, pp. 404-410; Gelse, K., Poschl, E., Aigner, T., Collagens-structure, function, and biosynthesis (2003) Adv Drug Deliv Rev, 55, pp. 1531-1546; Berglund, J.D., Mohseni, M.M., Nerem, R.M., Sambanis, A., A biological hybrid model for collagen-based tissue engineered vascular constructs (2003) Biomaterials, 24, pp. 1241-1254; Chvapil, M., Collagen sponge: Theory and practice of medical applications (1977) J Biomed Mater Res, 11, pp. 721-741; Chvapil, M., Kronenthal, L., Van Winkle, W., Medical and surgical applications of collagen (1973) Int Rev Connect Tissue Res, 6, pp. 1-61; Matton, G., Anseeuw, A., De Keyser, F., The history of injectable biomaterials and the biology of collagen (1985) Aesthetic Plastic Surgery, 9 (2), pp. 133-140. , DOI 10.1007/BF01570345; Radhika, M., Babu, M., Sehgal, P.K., Cellular proliferation on desamidated collagen matrices (1999) Comp Biochem Physiol C Pharmacol Toxicol Endocrinol, 124, pp. 131-139; Elliott, J.T., Woodward, J.T., Langenbach, K.J., Tona, A., Jones, P.L., Plant, A.L., Vascular smooth muscle cell response on thin films of collagen (2005) Matrix Biol, 24, pp. 489-502; Song, J., Rolfe, B.E., Hayward, I.P., Campbell, G.R., Campbell, J.H., Effects of collagen gel configuration on behavior of vascular smooth muscle cells in vitro: Association with vascular morphogenesis (2000) In Vitro Cell Dev Biol Anim, 36, pp. 600-610; Weinberg, C.B., Bell, E., A blood vessel model constructed from collagen and cultured vascular cells (1986) Science, 231 (4736), pp. 397-400; Reid, G.G., Gorham, S.D., Lackie, J.M., The attachment, spreading and growth of baby hamster-kidney cells on collagen, chemically modified collagen and collagen-composite substrata (1993) J Mater Sci-Mater Med, 4, pp. 201-209; Michalopoulos, G., Pitot, H.C., Primary culture of parenchymal liver cells on collagen membranes. Morphological and biochemical observations (1975) Exp Cell Res, 94, pp. 70-78; Winder, S.J., Turvey, A., Forsyth, I.A., Characteristics of ruminant mammary epithelial cells grown in primary culture in serumfree medium (1992) J Dairy Res, 59, pp. 491-498; Sato, T., Chen, G., Ushida, T., Ishii, T., Ochiai, N., Tateishi, T., Tissue-engineered cartilage by in vivo culturing of chondrocytes in PLGA-collagen hybrid sponge (2001) Mater Sci Engineering: C, 17, pp. 83-89; Takahiro, O., Keizo, T., Yosuke, H., Takashi, U., Tamotsu, T., Tetsuya, T., Effect of type I and type II collagen sponges as 3D scaffolds for hyaline cartilage-like tissue regeneration on phenotypic control of seeded chondrocytes in vitro (2004) Mater Sci Eng C, 24, pp. 407-411; Fuchs, J.R., Kaviani, A., Oh, J.T., Lavan, D., Udagawa, T., Jennings, R.W., Wilson, J.M., Fauza, D.O., Diaphragmatic reconstruction with autologous tendon engineered from mesenchymal amniocytes (2004) J Pediatr Surg, 39, pp. 834-838; Kall, S., Nöth, U., Reimers, K., Choi, C.Y.U., Muehlberger, T., Allmeling, C., Jahn, S., Vogt, P.M., In vitro fabrication of tendon substitutes using human mesenchymal stem cells and a collagen type i gel (2004) Handchir Mikrochir Plast Chir, 4, pp. 205-211; Domaschke, H., Gelinsky, M., Burmeister, B., Fleig, R., Hanke, T., Reinstorf, A., Pompe, W., Rosen-Wolff, A., In vitro ossification and remodeling of mineralized collagen i scaffolds (2006) Tissue Eng, 12, pp. 949-958; Rodrigues, C.V.M., Serricella, P., Linhares, A.B.R., Guerdes, R.M., Borojevic, R., Rossi, M.A., Duarte, M.E.L., Farina, M., Characterization of a bovine collagen-hydroxyapatite composite scaffold for bone tissue engineering (2003) Biomaterials, 24, pp. 4987-4997; Cooperman, L., Michaeli, D., The immunogenicity of injectable collagen. I. A 1-year prospective study (1984) J Am Acad Dermatol, 10, pp. 638-646; Delustro, F., Condell, R.A., Nguyen, M.A., Mcpherson, J.M., A comparative study of the biologic and immunologic response to medical devices derived from dermal collagen (1986) J Biomed Mater Res, 20, pp. 109-120; Sandberg, M., Vurio, E., Localization of types I, II, and III collagen mRNAs in developing human skeletal tissues by in situ hybridization (1987) J Cell Biol, 104, pp. 1077-1084; DeLustro, F., Smith, S.T., Sundsmo, J., Reaction to injectable collagen: Results in animal models and clinical use (1987) Plastic and Reconstructive Surgery, 79 (4), pp. 581-592; Lynn, A.K., Yannas, I.V., Bonfield, W., Antigenicity and immunogenicity of collagen (2004) J Biomed Mater Res Part B: Appl Biomaterials, 71, pp. 343-354; Mizuno, M., Shindo, M., Kobayashi, D., Tsuruga, E., Amemiya, A., Kuboki, Y., Osteogenesis by bone marrow stromal cells maintained on type I collagen matrix gels in vivo (1997) Bone, 20, pp. 101-107; Wambach, B.A., Cheung, H., Josephson, G.D., Cartilage tissue engineering using thyroid chondrocytes on a type i collagen matrix (2000) Laryngoscope, 110, pp. 2008-2011; Rajpurohit, R., Koch, C.J., Tao, Z., Teixeira, C.M., Shapiro, I.M., Adaptation of chondrocytes to low oxygen tension: Relationship between hypoxia and cellular metabolism (1996) J Cell Physiol, 168, pp. 424-432; Schipani, E., Ryan, H.E., Didrickson, S., Kobayashi, T., Knight, M., Johnson, R.S., Hypoxia in cartilage: HIF-1 alpha is essential for chondrocyte growth arrest and survival (2001) Genes Dev, 15, pp. 2865-2876; Maes, C., Carmeliet, P., Moermans, K., Stockmans, I., Smets, N., Collen, D., Bouillon, R., Carmeliet, G., Impaired angiogenesis and endochondral bone formation in mice lacking the vascular endothelial growth factor isoforms VEGF164 and VEGF188 (2002) Mech Dev, 111, pp. 61-73; Petersen, W., Tsokos, M., Pufe, T., Expression of VEGF121 and VEGF165 in hypertrophic chondrocytes of the human growth plate and epiphyseal cartilage (2002) J Anat, 201, pp. 153-157; Oliveira, S.M., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., Engineering endochondral bone: In vitro studies (2009) Tissue Eng, 15, pp. 625-634; Teixeira, C.C., Nemelivsky, Y., Karkia, C., Legeros, R.Z., Biphasic calcium phosphate: A scaffold for growth plate chondrocyte maturation (2006) Tissue Eng, 12, pp. 2283-2289; Oliveira, S.M., Turner, G., Mijares, D., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., Engineering endochondral bone: In vivo studies (2009) Tissue Eng, 15, pp. 635-643; Hiraoka, Y., Kimura, Y., Ueda, H., Tabata, Y., Fabrication and biocompatibility of collagen sponge reinforced with poly(glycolic acid) fiber (2003) Tissue Eng, 9, pp. 1101-1112; Yost, M.J., Baicu, C.F., Stonerock, C.E., Terracio, L., A novel tubular scaffold for cardiovascular tissue engineering (2004) Tissue Eng, 10, pp. 273-284; Mow, V.C., Kuei, S.C., Lai, W.M., Armstrong, C.G., Biphasic creep and stress relaxation of articular cartilage in compression? Theory and experiments (1980) J Biomech Eng, 102, pp. 73-84; Iwamoto, M., Shapiro, I.M., Yagami, K., Boskey, A.L., Leboy, P.S., Adams, S.L., Pacifici, M., Retinoic acid induces rapid mineralization and expression of mineralization-related genes in chondrocytes (1993) Exp Cell Res, 207, pp. 413-420; Teixeira, C.C., Hatori, M., Leboy, P.S., Pacifici, M., Shapiro, I.M., A rapid and ultrasensitive method for measurement of DNA, calcium and protein content, and alkaline phosphatase activity of chondrocyte cultures (1995) Calcif Tissue Int, 56, pp. 252-256; Leboy, P.S., Vaias, L., Uschmann, B., Golub, E., Adams, S.L., Pacifici, M., Ascorbic acid induces alkaline phosphatase, type X collagen, and calcium deposition in cultured chick chondrocytes (1989) Journal of Biological Chemistry, 264 (29), pp. 17281-17286; Whyte, M.P., Hypophosphatasia and the role of alkaline phosphatase in skeletal mineralization (1994) Endocr Rev, 15, pp. 439-461; Wang, W., Kirsch, T., Retinoic acid stimulates annexin-mediated growth plate chondrocyte mineralization (2002) J Cell Biol, 157, pp. 1061-1069; Chen, D., Zhao, M., Mundy, G.R., Bone morphogenetic proteins (2004) Growth Factors, 22, pp. 233-241; Gerstenfeld, L.C., Shapiro, F.D., Expression of bone-specific genes by hypertrophic chondrocytes: Implications of the complex functions of the hypertrophic chondrocyte during endochondral bone development (1996) J Cell Biochem, 62, pp. 1-9; Bianco, P., Cancedda, F.D., Riminucci, M., Cancedda, R., Bone formation via cartilage models: The "borderline" chondrocyte (1998) Matrix Biol, 17, pp. 185-192; De Bernard, B., Bianco, P., Bonucci, E., Costantini, M., Lunazzi, G.C., Martinuzzi, P., Modricky, C., Pollesello, P., Biochemical and immunohistochemical evidence that in cartilage an alkaline phosphatase is a Ca 2" - Binding glycoprotein (1986) J Cell Biol, 103, pp. 1615-1623; Galotto, M., Campanile, G., Robino, G., Cancedda, F.D., Bianco, P., Cancedda, R., Hypertrophic chondrocytes undergo further differentiation to osteoblast- Like cells and participate in the initial bone formation in developing chick embryo (1994) Journal of Bone and Mineral Research, 9 (8), pp. 1239-1249; Mark, M.P., Butler, W.T., Prince, C.W., Finkelman, R.D., Ruch, J.V., Developmental expression of 44-kDa bone phosphoprotein (osteopontin) and bone gamma-carboxyglutamic acid (Gla)-containing protein (osteocalcin) in calcifying tissues of rat (1988) Differentiation, 37, pp. 123-136; Sims, C.D., Butler, P.E., Casanova, R., Lee, B.T., Randolph, M.A., Lee, W.P., Vacanti, C.A., Yaremchuk, M.J., Injectable cartilage using polyethylene oxide polymer substrates (1996) Plast Reconstr Surg, 98, pp. 843-850; Woodard, J.C., Donovan, G.A., Fisher, L.W., Pathogenesis of vitamin (A and D)-induced premature growth-plate closure in calves (1997) Bone, 27, pp. 171-182; Liao, E., Yaszemski, M., Krebsbach, P., Hollister, S., Tissue-engineered cartilage constructs using composite hyaluronic acid/ collagen I hydrogels and designed poly(propylene fumarate) scaffolds (2007) Tissue Eng, 13, pp. 537-550; Gerstenfeld, L.C., Cruceta, J., Shea, C.M., Sampath, K., Barnes, G.L., Einhorn, T.A., Chondrocytes provide morphogenic signals that selectively induce osteogenic differentiation of mesenchymal stem cells (2002) Journal of Bone and Mineral Research, 17 (2), pp. 221-230
Keywords: alkaline phosphatase; animal cell; animal tissue; Animals; article; Biocompatible Materials; Body fluids; Bone; Bone and Bones; Bone Regeneration; Cartilage; cartilage cell; Cattle; Cell culture; cell maturation; chick embryo; Chondrocytes; Collagen; collagen implant; collagen type 1; collagen type 10; Compressive Strength; controlled study; embryo; enchondral ossification; Endochondral ossification; extracellular matrix; freeze drying; Humans; immunohistochemistry; Ligaments; materials testing; Microscopy, Electron, Scanning; nonhuman; Phosphatases; protein cross linking; Protein Isoforms; retinoic acid; Scaffolds; Scanning electron microscopy; Stress, Mechanical; Tissue engineering; tissue scaffold; Type I collagen; Type X collagen; Ultraviolet radiation

In vitro study of the proliferation and growth of human bone marrow cells on apatite-wollastonite-2M glass ceramics - Magallanes-Perdomo, M.; De Aza, A.H.; Mateus, A.Y.; Teixeira, S.; Monteiro, F.J.; De Aza, S.; Pena, P. (Acta BiomaterialiaActa Biomater., 2010)
This study concerns the preparation and in vitro characterization of an apatite-wollastonite-2M bioactive glass ceramic which is intended to be used for the regeneration of hard tissue (i.e. in dental and craniomaxillofacial surgery). This bioglass ceramic has been obtained by appropriate thermal treatment through the devitrification (crystallization) of a glass with a stoichiometric eutectic composition within the Ca 3(PO 4)2-CaSiO 3 binary system. Crack-free specimens of the bioglass ceramic were immersed in human bone marrow cell cultures for 3, 7, 14 and 21 days, in order to study biocompatibility. Cell morphology, proliferation and colonization were assessed by scanning electron microscopy and confocal laser scanning microscopy. A total protein content assay was used to evaluate the viability and proliferation of cultured bone marrow cells. The results showed that the cells were able to adhere and proliferate on the designed material due to the essentiality of silicon and calcium as accessory factors for cell activity stimulation. © 2009 Acta Materialia Inc. All rights reserved.
Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2009.12.027Language of Original Document: EnglishCorrespondence Address: De Aza, A. H.; Instituto de Cerámica y Vidrio, CSIC, C/Kelsen 5, 28049 Madrid, Spain; email: aaza@icv.csic.esChemicals/CAS: apatite, 64476-38-6; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; calcium silicate, 1344-95-2, 13983-17-0; silicate, 12627-13-3; Apatites; Bone Substitutes; Calcium Compounds; Ceramics; Silicates; calcium silicate, 1344-95-2References: Hench, L.L., Wilson, J., (1993) An Introduction to Bioceramics, , London: World Scientific;Hench, L.L., Bioceramics: From concept to clinic (1991) J. Am. Ceram. Soc., 74, pp. 1487-1510; Best, S.M., Porter, A.E., Thian, E.S., Huan, J., Bioceramics: Past, present and for the future (2008) J. Eur. Ceram. Soc., 28, pp. 1319-1327; Chevalier, J., Gremillard, L., Ceramics for medical applications: A picture for the next 20 years (2009) J. Eur. Ceram. Soc., 29, pp. 1245-1255; Teixeira, S., Oliveira, S., Ferraz, M.P., Monteiro, F.J., Mesenchymal stem cell proliferation and morphological analysis on interconnected macroporous structures (2007) Key Eng. Mater., 330-332, pp. 1129-1132; Temenoff, J.S., Mikos, A.G., (2008) Biomaterials: The Intersection of Biology and Materials Science, p. 471. , London: Pearson International; Carlisle, E.M., Biochemical and morphological changes associated with long bone abnormalities in silicon deficiency (1980) J. Nutr., 110, pp. 1046-1055; Carlisle, E.M., A silicon requirement for normal skull formation (1980) J. Nutr., 110, pp. 352-359; Reffitt, M., Ogston, N., Jugdaohsingh, R., Cheung, H.F., Evans, B.A., Thompson, R.P., Orthosilicic acid stimulates collagen type 1 synthesis and osteoblastic differentiation in human osteoblast-like cells in vitro (2003) Bone, 32, pp. 127-135; Brown, L., Luklinska, Z., De Aza, P.N., De Aza, S., Anseau, M., Hughes, F.J., Mechanism of osteoinduction by pseudowollastonite (psW) ceramic (2004) 7th World Biomaterials Congress, , Paper presented at the, Sydney; De Aza, P.N., De Aza, A.H., De Aza, S., Crystalline bioceramic materials (2005) Bol Soc. Esp. Ceram. V, 44, pp. 135-145; De Aza, P.N., De Aza, A.H., Pena, P., De Aza, S., Bioactive glasses and glass-ceramics (2007) Bol Soc. Esp. Ceram. V, 46, pp. 45-55; Kokubo, T., Ito, S., Sakka, S., Formation of a high-strength bioactive glass-ceramic in the system MgO-CaO-SiO 2-P 2O 5 (1986) J. Mat. Sci., 21, pp. 536-540; De Aza, P.N., Guitián, F., De Aza, S., Bioeutectic: A new ceramic material for human bone replacement (1997) Biomaterials, 18, pp. 1285-1291; De Aza, P.N., Guitián, F., De Aza, S., A new bioactive material which transforms in situ into hydroxyapatite (1998) Act Mater., 46, pp. 2541-2549; De Aza, P.N., Guitián, F., De Aza, S., Bioeutectics (1994) Internacional Trademark, 780 (1), p. 697. , Universidad de Santiago de Compostela; De Aza, P.N., Guitián, F., De Aza, S., Bioeutectics: New bioceramic materials (1999) Advances in Science and Technology, 28, pp. 25-32. , Vicenzini P, editor, Materials in clinical applications, Faenza: Publi Techna Italia; De Aza, P.N., Luklinska, Z.B., Anseau, M.R., Guitian, F., De Aza, S., Reactivity of wollastonite-tricalcium phosphate ceramic (Bioeutectic ®) in parotid human saliva (2000) Biomaterials, 21, pp. 1735-1741; De Aza, A.H., Velasquez, P., Alemany, M.I., Pena, P., De Aza, P.N., In situ bone-like apatite formation from a Bioeutectic ceramic in SBF dynamic flow (2007) J. Am. Ceram. Soc., 90, pp. 1200-1207; Sánchez, F.M., Díaz-Güemes, I., Enciso, S., Moreno, B., De Aza, A.H., Carrodeguas, R.G., Evaluación de una cerámica bioactiva de p-wollastonita como sustituto óseo en el modelo ovino (2009) XVII Congreso Internacional de la Sociedad Española de Cirugía Veterinaria, , Cáceres; 6-8 November, Paper Presented at the; Llorca, J., Orera, V., Directionally solidified eutectic ceramic oxides (2006) Prog. Mater. Sci., 51, pp. 711-809; Magallanes-Perdomo, M., Carrodeguas, R.G., Pena, P., De Aza, P.N., De Aza, S., De Aza, A.H., Non-isothermal devitrification study of wollastonite-tricalcium phosphate Bioeutectic ® glass (2009) Key Eng. Mat., 396-398, pp. 127-130; Magallanes-Perdomo, M., Pena, P., De Aza, P.N., Carrodeguas, R.G., Rodriguez, M.A., Turrillas, X., Devitrification studies of wollastonite-tricalcium phosphate eutectic glass (2009) Acta Biomater, 5, pp. 3057-3066; De Aza, P.N., Guitián, F., De Aza, S., Phase diagram of wollastonite-tricalcium phosphate (1995) J. Am. Ceram. Soc., 78, pp. 1653-1656; Young, R.A., (1993) The Rietveld Method, p. 336. , Oxford: Oxford University Press; Larson, A.C., Von Dreele, R.B., (1994) Los Alamos National Laboratory Report No. LA-UR-86-748, , Los Alamos, NM: Los Alamos National Laboratory; Finger, L.W., Cox, D.E., Jephcoat, A.P., A correction for powder diffraction peak asymmetry due to axial divergence (1994) J. Appl. Cryst., 27, pp. 892-900; Wilson, R.M., Elliott, J.C., Dowker, S.E., Rodriguez-Lorenzo, L.M., Rietveld refinements and spectroscopic studies of the structure of Ca-deficient apatite (2005) Biomaterials, 26, pp. 1317-1327; Wilson, R.M., Elliott, J.C., Dowker, S.E., Rodriguez-Lorenzo, L.M., Ca 9.303 (PO 4) 6 (OH) 0.6061.97 (H 2O) (2005) ICSD Collection Code 152190, Inorganic Crystal Structure Database, , Karlsruhe: Fachonformationszentrum; Trojer, F.J., The crystal structure of parawollastonite (1968) Zeitschrift fur Kristallographie Kristallgeometrie Kristallphysik Kristallchemie, 127, pp. 291-308; Trojer, F.J., CaSiO 3-wollastonite-2M (1968) ICSD Collection Code 34908, Inorganic Crystal Structure Database, , Karlsruhe: Fachonformationszentrum; De La, T.A.G., Bruque, S., Aranda, M.A.G., Rietveld quantitative amorphous content analysis (2001) J. Appl. Cryst., 34, pp. 196-202; De Aza, A.H., De La Torre, A.G., Aranda, M.A.G., Valle, F.J., De Aza, S., Rietveld quantitative analysis of Buen Retiro porcelains (2004) J. Am. Ceram. Soc., 87, pp. 449-454; Magallanes-Perdomo, M., Luklinska, Z.B., De Aza, A.H., Carrodeguas, R.G., De Aza, S., Pena, P., Bone like apatite forming ability of apatite-wollastonite glass ceramic (2009) 11th International Conference and Exhibition of the European Ceramic Society, , Krakow, Poland; 21-25 June, Paper Presented at the; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., HA and double-layer HA-P 2O 3/CaO glass coatings: Influence of chemical composition on human bone marrow cells osteoblastic behavior (2001) J. Mater. Sci. Mater. Med., 12, pp. 629-638; Meseguer-Olmo, L., Bernabeu-Esclapez, A., Ros-Martinez, E., Sanchez-Salcedo, S., Padilla, S., Martin, A.I., In vitro behaviour of adult mesenchymal stem cells seeded on a bioactive glass ceramic in the SiO 2-CaO-P 2O 5 system (2008) Acta Biomater, 4, pp. 1104-1113; Muller, P., Bulnheim, U., Diener, A., Luthen, F., Teller, M., Klinkenberg, E.D., Calcium phosphate surfaces promote osteogenic differentiation of mesenchymal stem cells (2008) J. Cell. Mol. Med., 12, pp. 281-291; Saldana, L., Sanchez-Salcedo, S., Izquierdo-Barba, I., Bensiamar, F., Munuera, L., Vallet-Regi, M., Calcium phosphate-based particles influence osteogenic maturation of human mesenchymal stem cells (2009) Acta Biomater, 5, pp. 1294-1305; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Effect of titanium surface-roughness on proliferation, differentiation, and protein-synthesis of human osteoblast-like cells (MG63) (1995) J. Biomed. Mater. Res., 29, pp. 389-401; Bowers, K.T., Keller, J.C., Randolph, B.A., Wick, D.G., Michaels, C.M., Optimization of surface micromorphology for enhanced osteoblast responses in vitro (1992) Int. J. Oral. Maxillofac. Implants, 7, pp. 302-310; Boyan, B.D., Batzer, R., Kieswetter, K., Liu, Y., Cochran, D.L., Szmuckler-Moncler, S., Titanium surface roughness alters responsiveness of MG63 osteoblastlike cells to 1 alpha, 25-(OH) (2) D-3 (1998) J. Biomed. Mater. Res., 39, pp. 77-85; Mateus, A.Y.P., Barrias, C.C., Ribeiro, C., Ferraz, M.P., Monteiro, F.J., Comparative study of nanohydroxyapatite microspheres for medical applications (2008) J. Biomed. Mater. Res. A, 86, pp. 483-493; Ni, S.Y., Chang, J., Chou, L., Zhai, W.Y., Comparison of osteoblast-like cell responses to calcium silicate and tricalcium phosphate ceramics in vitro (2007) J. Biomed. Mater. Res. B. Appl. Biomater, 80, pp. 174-183; Sarmento, C., Luklinska, Z.B., Brown, L., Anseau, M., De Aza, P.N., De Aza, S., In vitro behavior of osteoblastic cells cultured in the presence of pseudowollastonite ceramic (2004) J. Biomed. Mater. Res. A, 69 A, pp. 351-358
Keywords: Apatite; Apatites; article; Bioceramics; Biocompatibility; bone marrow cell; bone prosthesis; Bone Substitutes; Calcium Compounds; calcium derivative; calcium phosphate; calcium silicate; cell activity; cell adhesion; Cell culture; cell differentiation; cell enlargement; cell growth; cell proliferation; cell structure; cell viability; Cells, Cultured; ceramics; chemistry; confocal laser microscopy; crystal structure; Crystallization; cytology; glass; Glass ceramics; human; human cell; Humans; in vitro study; materials testing; Mesenchymal stem cell; Mesenchymal Stem Cells; methodology; osteoblast; Osteoblasts; physiology; priority journal; protein content; Scanning electron microscopy; silicate; Silicates; Surface Properties; surface property; Tissue regeneration; Wollastonite; X ray fluorescence

In vivo evaluation of highly macroporous ceramic scaffolds for bone tissue engineering - Teixeira, S.; Fernandes, H.; Leusink, A.; Van Blitterswijk, C.; Ferraz, M.P.; Monteiro, F.J.; De Boer, J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
During the last decades, different materials of both natural and synthetic origin have been developed with the aim of inducing and controlling osteogenic differentiation of mesenchymal stem cells (MSCs). In order for that to happen, it is necessary that the material to be implanted obey a series of requirements, namely: osteoconduction, biocompatibility, and biodegradability. Additionally, they must be low-priced, easy to produce, shape, and store. Hydroxyapatite (HA) is a well known ceramic with a composition similar to the mineral component of bone and is highly biocompatible and easy to obtain and/or process. On the other hand, collagen is the main structural protein present in the human body and bone. In this study, a polymer replication method was applied and a highly porous HA scaffold was produced. Collagen was later incorporated to improve the biological properties of the scaffold while resembling the bone composition. The scaffolds were characterized by means of scanning electron microscopy, Fourier transform infrared spectroscopy and energy dispersive spectroscopy. In vitro and in vivo testing was performed in all scaffolds produced. The goal of this study was to evaluate the in vivo osteogenic potential of MSCs from two different species seeded on the different HA based porous scaffolds with collagen type I. The results indicate that all scaffolds exhibit relevant bone formation, being more prominent in the case of the HA scaffolds. © 2009 Wiley Periodicals, Inc.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32532PubMed ID: 19591232Language of Original Document: EnglishCorrespondence Address: Teixeira, S.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomaterials, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: sandra_teixeira3@yahoo.comChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; Biocompatible Materials; Ceramics; Durapatite, 1306-06-5References: Jones, A.C., Milthorpe, B., Averdunk, H., Limaye, A., Senden, T.J., Sakellariou, A., Sheppard, A.P., Dwdw, H., Analysis of 3D bone ingrowth into polymer scaffolds via micro-computed tomography imaging (2004) Biomaterials, 25, pp. 4947-4954;Aizawa, M., Shinoda, H., Uchida, H., Itatani, K., Okada, I., Matsumoto, M., Toyama, Y., Development and biological evaluation of apatite fibre scaffolds with large pore size and high porosity for bone regeneration (2003) Bioceramics, 240-242, pp. 647-650; Ebaretonbofa, E., Evans, J.R.G., High porosity hydroxyapatite foam scaffolds for bone substitute (2002) J Porous Mater, 9, pp. 257-263; Wissink, M.J.B., Beernink, R., Pieper, J.S., Poot, A.A., Engbers, G.H.M., Beugeling, T., Van Aken, W.G., Feijen, J., Immobilization of heparin to EDC/NHS-crosslinked collagen (2001) Characterization and in Vitro Evaluation. Biomaterials, 22, pp. 151-163; Lee, C.H., Singla, A., Lee, Y., Biomedical applications of collagen (2001) Int J Pharm, 221, pp. 1-22; Jensen, T.B., Overgaard, S., Lind, M., Rahbek, O., Bünger, C., Søballe, K., Osteogenic protein 1 device increases bone formation and bone graft resorption around cementless implants (2002) Acta Orthop Scand, 73, pp. 31-39; Niemeyer, P., Krause, U., Fellenberg, J., Kasten, P., Seckinger, A., Ho, A.D., Simank, H.G., Evaluation of mineralized collagen and alpha-tricalcium phosphate as scaffolds for tissue engineering of bone using human mesenchymal stem cells (2004) Cells Tissues Organs, 177, pp. 68-78; Yang, X.B., Bhatnagar, R.S., Li, S., Oreffo, R.O., Biomimetic collagen scaffolds for human bone cell growth and differentiation (2004) Tissue Eng, 10, pp. 1148-1159; Xu, C., Wang, Y., Yu, X., Chen, X., Li, X., Yang, X., Li, S., Xiang, A.P., Evaluation of human mesenchymal stem cells response to biomimetic bioglass-collagen-hyaluronic acidphosphatidylserine composite scaffolds for bone tissue engineering (2009) J Biomed Mater Res A, 88, pp. 264-273; Kikuchi, M., Matsumoto, H.N., Yamada, T., Koyama, Y., Takakuda, K., Tanaka, J., Glutaraldehyde cross-linked hydroxyapatite/collagen self-organized nanocomposites (2004) Biomaterials, 25, pp. 63-69; Liao, S., Wang, W., Uo, M., Ohkawa, S., Akasaka, T., Tamura, K., Cui, F., Watari, F., A three-layered nano-carbonated hydroxyapatite/ collagen/PLGA composite membrane for guided tissue regeneration (2005) Biomaterials, 26, pp. 7564-7571; Liao, S., Watari, F., Zhu, Y., Uo, M., Akasaka, T., Wang, W., Xu, G., Cui, F., The degradation of the three layered nano-carbonated hydroxyapatite/ collagen/PLGA composite membrane in vitro (2007) Dent Mater, 23, pp. 1120-1128; Zhang, S.M., Cui, F.Z., Liao, S.S., Zhu, Y., Han, L., Synthesis and biocompatibility of porous nano-hydroxyapatite/collagen/ alginate composite (2003) J Mater Sci, 14, pp. 641-645; Glowacki, J., Mizuno, S., Collagen scaffolds for tissue engineering (2008) Biopolymers, 89, pp. 338-344; Hao, W., Hu, Y.Y., Wei, Y.Y., Pang, L., Lv, R., Bai, J.P., Xiong, Z., Jiang, M., Collagen I gel can facilitate homogenous bone formation of adipose-derived stem cells in PLGA-beta-TCP scaffold (2008) Cells Tissues Organs, 187, pp. 89-102; Liuyun, J., Yubao, L., Li, Z., Jianguo, L., Preparation and properties of a novel bone repair composite: Nano-hydroxyapatite/ chitosan/carboxymethyl cellulose (2008) J Mater Sci, 19, pp. 981-987; Zhou, G., Li, Y., Zhang, L., Zuo, Y., Jansen, J.A., Preparation and characterization of nano-hydroxyapatite/chitosan/konjac glucomannan composite (2007) J Biomed Mater Res, 83, pp. 931-939; Hua, Y., Ning, C., Xiaoying, L., Buzhong, Z., Wei, C., Xiaoling, S., Natural hydroxyapatite/chitosan composite for bone substitute materials (2005) Conf Proc IEEE Eng Med Biol Soc, 5, pp. 4888-4891; Oliveira, J.M., Rodrigues, M.T., Silva, S.S., Malafaya, P.B., Gomes, M.E., Viegas, C.A., Dias, I.R., Reis, R.L., Novel hydroxyapatite/ chitosan bilayered scaffold for osteochondral tissue- Engineering applications: Scaffold design and its performance when seeded with goat bone marrow stromal cells (2006) Biomaterials, 27, pp. 6123-6137; Kong, L., Gao, Y., Cao, W., Gong, Y., Zhao, N., Zhang, X., Preparation and characterization of nano-hydroxyapatite/chitosan composite scaffolds (2005) J Biomed Mater Res, 75, pp. 275-282; Zhao, F., Yin, Y., Lu, W.W., Leong, J.C., Zhang, W., Zhang, J., Zhang, M., Yao, K., Preparation and histological evaluation of biomimetic three-dimensional hydroxyapatite/chitosan-gelatin network composite scaffolds (2002) Biomaterials, 23, pp. 3227-3234; Everaerts, F., Torrianni, M., Hendriks, M., Feijen, J., Biomechanical properties of carbodiimide crosslinked collagen: Influence of the formation of ester crosslinks (2008) J Biomed Mater Res A, 85, pp. 547-555; Vrana, N.E., Builles, N., Kocak, H., Gulay, P., Justin, V., Malbouyres, M., Ruggiero, F., Hasirci, V., EDC/NHS cross-linked collagen foams as scaffolds for arti.cial corneal stroma (2007) J Biomater Sci, 18, pp. 1527-1545; Wissink, M.J.B., Beernink, R., Scharenborg, N.M., Poot, A.A., Engbers, G.H.M., Beugeling, T., Van Aken, W.G., Feijen, J., Endothelial cell seeding of (heparinized) collagen matrices: Effects of bFGF pre-loading on proliferation (after low density seeding) and pro-coagulant factors (2000) J Control Release, 67, pp. 141-155; Wissink, M.J.B., Van Luyn, M.J.A., Beernink, R., Dijk, F., Poot, A.A., Engbers, G.H.M., Beugeling, T., Feijen, J., Endothelial cell seeding on crosslinked collagen: Effects of crosslinking on endothelial cell proliferation and functional parameters (2000) Thrombosis Haemostasis, 84, pp. 325-331; Teixeira, S., Ferraz, M.P., Monteiro, F.J., Biocompatibility of highly macroporous ceramic scaffolds: Cell adhesion and morphology studies (2008) J Mater Sci Mater Med, 19, pp. 855-859; Wissink, M.J.B., Beernink, R., Pieper, J.S., Poot, A.A., Engbers, G.H.M., Beugeling, T., Van Aken, W.G., Feijen, J., Binding and release of basic fibroblast growth factor from heparinized collagen matrices (2001) Biomaterials, 22, pp. 2291-2299; Wissink, M.J.B., Beernink, R., Poot, A.A., Engbers, G.H.M., Beugeling, T., Van Aken, W.G., Feijen, J., Improved endothelialization of vascular grafts by local release of growth factor from heparinized collagen matrices (2000) J Control Release, 64, pp. 103-114; Habibovic, P., Yuan, H., Van Den Doel, M.A., Sees, T.M., Van Blitterswijk, C.A., De Groot, K., Relevance of osteoinductive biomaterials in critical-sized orthotopic defect (2006) J Orthop Res, 24, pp. 867-876; Habibovic, P., Sees, T.M., Van Den Doel, M.A., Van Blitterswijk, C.A., De Groot, K., Osteoinduction by biomaterials-physicochemical and structural influences (2006) J Biomed Mater Res A, 77, pp. 747-762; Both, S.K., Van Der Muijsenberg, A.J., Van Blitterswijk, C.A., De Boer, J., De Bruijn, J.D., A rapid and ef.cient method for expansion of human mesenchymal stem cells (2007) Tissue Eng, 13, pp. 3-9; Habibovic, P., Gbureck, U., Doillon, C.J., Bassett, D.C., Van Blitterswijk, C.A., Barralet, J.E., Osteoconduction and osteoinduction of low-temperature 3D printed bioceramic implants (2008) Biomaterials, 29, pp. 944-953; Teixeira, S., Oliveira, S., Ferraz, M.P., Monteiro, F.J., Three dimensional macroporous calcium phosphate scaffolds for bone tissue engineering (2008) Key Eng Mater, 361-363 (2), pp. 947-950; Teixeira, S., Rodriguez, M.A., Pena, P., De Aza, A.H., De Aza, S., Ferraz, M.P., Monteiro, F.J., Physical characterization of hydroxyapatite porous scaffolds for tissue engineering (2009) Mat Sci Eng: C, 29, pp. 1510-1514; Kim, H.W., Knowles, J.C., Kim, H.E., Hydroxyapatite porous scaffold engineered with biological polymer hybrid coating for antibiotic Vancomycin release (2005) J Mater Sci, 16, pp. 189-195; Gibson, I.R., Best, S.M., Bonfield, W., Chemical characterization of silicon-substituted hydroxyapatite (1999) J Biomed Mater Res, 44, pp. 422-428; Siddappa, R., Fernandes, H., Liu, J., Van Blitterswijk, C., De Boer, J., The response of human mesenchymal stem cells to osteogenic signals and its impact on bone tissue engineering (2007) Curr Stem Cell Res Ther, 2, pp. 209-220; Olivo, C., Alblas, J., Verweij, V., Van Zonneveld, A.J., Dhert, W.J., Martens, A.C., In vivo bioluminescence imaging study to monitor ectopic bone formation by luciferase gene marked mesenchymal stem cells (2008) J Orthop Res, 26, pp. 901-909; Yuan, H., Van Blitterswijk, C.A., De Groot, K., De Bruijn, J.D., A comparison of bone formation in biphasic calcium phosphate (BCP) and hydroxyapatite (HA) implanted in muscle and bone of dogs at different time periods (2006) J Biomed Mater Res A, 78, pp. 139-147; Habibovic, P., Li, J., Van Der Valk, C.M., Meijer, G., Layrolle, P., Van Blitterswijk, C.A., Groot, K., Biological performance of uncoated and octacalcium phosphate-coated Ti6Al4V (2005) Biomaterials, 26, pp. 23-36; Habibovic, P., Yuan, H., Van Der Valk, C.M., Meijer, G., Van Blitterswijk, C.A., De Groot, K., 3D microenvironment as essential element for osteoinduction by biomaterials (2005) Biomaterials, 26, pp. 3565-3575
Keywords: animal cell; animal experiment; animal model; Animals; article; Biocompatibility; Biocompatible Materials; Biodegradation; Bone; Bone and Bones; Bone formation; bone tissue; Calcium; Calcium alloys; calcium phosphate; Calcium phosphates; Cell Count; Cell culture; Cell Culture Techniques; Cells, Cultured; cellular distribution; Ceramic materials; ceramics; Collagen; collagen type 1; Durapatite; Energy dispersive spectroscopy; Flowcharting; Fourier transform infrared spectroscopy; Humans; hydroxyapatite; Hydroxylation; in vitro study; In vivo bone formation; in vivo study; In-vivo; infrared spectroscopy; Macroporous; Macroporous scaffolds; male; materials testing; Mesenchymal stem cell; Mesenchymal Stem Cells; Mice; Microscopy, Electron, Scanning; nonhuman; ossification; Osteogenesis; porous polymer; rat; Rats; Rats, Wistar; Scaffolds; Scanning electron microscopy; Spectroscopy, Fourier Transform Infrared; Stem cells; Tissue engineering; tissue scaffold; Tissue Scaffolds

Innovative macroporous granules of nanostructured-hydroxyapatite agglomerates: Bioactivity and osteoblast-like cell behaviour - Laranjeira, M.S.; Fernandes, M.H.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
To modulate the biological response of implantable granules, two types of bioactive porous granules composed of nanostructured-hydroxyapatite (HA) agglomerates and microstructured-HA, respectively, were prepared using a polyurethane sponge impregnation and burnout method. The resulting granules presented a highly porous structure with interconnected porosity. Both types of granules were characterized using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and mercury intrusion porosimetry. Results showed that nanostructed-HA granules presented higher surface area and porosity than microstructured-HA granules. In vitro testing using MG63 human osteoblast-like cells showed that on both types of surfaces cells were able to adhere, proliferate, and migrate through the macropores, and a higher growth rate was achieved on nanostructured-HA granules than on microstructured-HA granules (76 and 40%, respectively). In addition, these cells maintained similar expression levels of osteoblastic-associated markers namely collagen type I, alkaline phosphatase, bone morphogenetic protein-2, macrophage colony-stimulating factor, and osteoprotegerin. These innovative nanostructured-HA granules may be considered as promising bioceramic alternative matrixes for bone regeneration and drug release application. © 2010 Wiley Periodicals, Inc.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32916PubMed ID: 20845490Language of Original Document: EnglishCorrespondence Address: Laranjeira, M. S.; Divisão de Biomateriais, INEB-Instituto de Engenharia Biomédica, Universidade Do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: dce06004@fe.up.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; colony stimulating factor 1, 81627-83-0; hydroxyapatite, 1306-06-5, 51198-94-8; osteoprotegerin, 205944-50-9; polyurethan, 61789-63-7; Biocompatible Materials; Biological Markers; Durapatite, 1306-06-5; PolyurethanesReferences: Ferraz, M., Monteiro, F., Manuel, C., Hydroxyapatite nanoparticles: A review of preparation methodologies (2004) J Appl Biomater Biomech, 2, pp. 74-80;Murugan, R., Ramakrishna, S., Development of nanocomposites for bone grafting (2005) Compos Sci Technol, 65, pp. 2385-2406; Wahl, D., Czernuszka, J.T., Collagen-hydroxyapatite composites for hard tissue repair (2006) Eur Cell Mater, 11, pp. 43-46; Chen, Q.Z., Wong, C.T., Lu, W.W., Cheung, K.M., Leong, J.C., Luk, K.D., Strengthening mechanisms of bone bonding to crystalline hydroxyapatite in vivo (2004) Biomaterials, 25, pp. 4243-4254; Watari, F., Yokoyama, A., Gelinsky, M., Pompe, W., Conversion of functions by nanosizing from osteoconductivity to bone substitutional properties in apatite (2007) Interface Oral Health Sci, 23, pp. 139-148; Nihouannen, D., Duval, L., Lecomte, A., Julien, M., Guicheux, J., Daculsi, G., Layrolle, P., Interactions of total bone marrow cells with increasing quantities of macroporous calcium phosphate ceramic granules (2007) J Mater Sci Mater Med, 18, pp. 1983-1990; Le Nihouannen, D., Daculsi, G., Saffarzadeh, A., Gauthier, O., Delplace, S., Pilet, P., Layrolle, P., Ectopic bone formation by microporous calcium phosphate ceramic particles in sheep muscles (2005) Bone, 36, pp. 1086-1093; Kalita, S.J., Bhardwaj, A., Bhatt, H.A., Nanocrystalline calcium phosphate ceramics in biomedical engineering (2007) Mater Sci Eng C, 27, pp. 441-449; Kong, L.B., Ma, J., Boey, F., Nanosized hydroxyapatite powders derived from coprecipitation process (2002) J Mater Sci, 37, pp. 1131-1134; Habibovic, P., Kruyt, M.C., Juhl, M.V., Clyens, S., Martinetti, R., Dolcini, L., Theilgaard, N., Blitterswijk, C., Comparative in vivo study of six hydroxyapatite-based bone graft substitutes (2008) J Orthop Res, 26, pp. 1363-1370; Simon, J.L., Michna, S., Lewis, J.A., Rekow, E.D., Thompson, V.P., Smay, J.E., Yampolsky, A., Ricci, J.L., In vivo bone response to 3D periodic hydroxyapatite scaffolds assembled by direct ink writing (2007) J Biomed Mater Res A, 83, pp. 747-758; Clarke, S.A., Hoskins, N.L., Jordan, G.R., Henderson, S.A., Marsh, D.R., In vitro testing of advanced JAX TM bone void filler system: Species differences in the response of bone marrow stromal cells to b tri-calcium phosphate and carboxymethylcellulose gel (2007) J Mater Sci Mater Med, 18, pp. 2283-2290; Wei, G., Ma, P.X., Structure and properties of nano-hydroxyapatite/polymer composite scaffolds for bone tissue engineering (2004) Biomaterials, 25, pp. 4749-4757; Xu, T., Zhang, N., Nichols, H.L., Shi, D., Wen, X., Modification of nanostructured materials for biomedical applications (2007) Mater Sci Eng C, 27, pp. 579-594; Mateus, A.Y.P., Ferraz, M.P., Monteiro, F.J., Microspheres based on hydroxyapatite nanoparticles aggregates for bone regeneration (2007) Key Eng Mater, 330-332, pp. 243-246; Potoczek, M., Zima, A., Paszkiewicz, Z., Slosarczyk, A., Manufacturing of highly porous calcium phosphate bioceramics via gel-casting using agarose (2009) Ceram Int, 35, pp. 2249-2254; Okamoto, M., Dohi, Y., Ohgushi, H., Shimaoka, H., Ikeuchi, M., Matsushima, A., Yonemasu, K., Hosoi, H., Influence of the porosity of hydroxyapatite ceramics on in vitro and in vivo bone formation by cultured rat bone marrow stromal cells (2006) J Mater Sci Mater Med, 17, pp. 327-336; Tas, A.C., Preparation of porous apatite granules from calcium phosphate cement (2008) J Mater Sci Mater Med, 19, pp. 2231-2239; Joschek, S., Nies, B., Krotz, R., Gokpferich, A., Chemical and physicochemical characterization of porous hydroxyapatite ceramics made of natural bone (2000) Biomaterials, 21, pp. 1645-1658; Turhani, D., Cvikl, B., Watzinger, E., Weißenböck, M., Yerit, K., Thurnher, D., Lauer, G., Ewers, R., In vitro growth and differentiation of osteoblast-like cells on hydroxyapatite ceramic granule calcified from red algae (2005) J Oral Maxillofac Surg, 63, pp. 793-799; Teixeira, S., Ferraz, M.P., Monteiro, F.J., Biocompatibility of highly macroporous ceramic scaffolds: Cell adhesion and morphology studies (2008) J Mater Sci Mater Med, 19, pp. 855-859; Kim, Z., Oak, J., Kimura, H., Goto, T., Inoue, A., Yoon, S., Architecture of porous hydroxyapatite scaffolds using polymer foam process (2009) J Biomech Sci Eng, 4, pp. 377-383; Chevalier, E., Viana, M., Cazalbou, S., Makein, L., Dubois, J., Chulia, D., Ibuprofen-loaded calcium phosphate granules: Combination of innovative characterization methods to relate mechanical strength to drug location (2010) Acta Biomater, 6, pp. 266-274; Taboas, J.M., Maddox, R.D., Krebsbach, P.H., Hollister, S.J., Indirect solid free form fabrication of local and global porous, biomimetic and composite 3D polymer-ceramic scaffolds (2003) Biomaterials, 24, pp. 181-194; Wang, X., Ruan, J., Chen, Q., Effects of surfactants on the microstructure of porous ceramic scaffolds fabricated by foaming for bone tissue engineering (2009) Mater Res Bull, 44, pp. 1275-1279; Mateus, A.Y.P., Barrias, C.C., Ribeiro, C., Ferraz, M.P., Monteiro, F.J., Comparative study of nanohydroxyapatite microspheres for medical applications (2008) J Biomed Mater Res A, 86, pp. 483-493; Gibson, I.R., Best, S.M., Bonfield, W., Chemical characterization of silicon-substituted hydroxyapatite (1999) J Biomed Mater Res, 44, pp. 422-428; Panda, R.N., Hsieh, M.F., Chung, R.J., Chin, T.S., FTIR, XRD, SEM and solid state NMR investigations of carbonate-containing hydroxyapatite nano-particles synthesized by hydroxide-gel technique (2003) J Phys Chem Solids, 64, pp. 193-199; Penel, G., Leroy, G., Rey, C., Sombret, B., Huvenne, J.P., Bres, E., Infrared and Raman microspectrometry study of fluor-fluor-hydroxy and hydroxy-apatite powders (1997) J Mater Sci Mater Med, 8, pp. 271-276; Elliott, J.C., Holcomb, D.W., Young, R.A., Infrared determination of the degree of substitution of hydroxyl by carbonate ions in human dental enamel (1985) Calcif Tissue Int, 37, pp. 372-375; Rouahi, M., Gallet, O., Champion, E., Dentzer, J., Hardouin, P., Anselme, K., Influence of hydroxyapatite microstructure on human bone cell response (2006) J Biomed Mater Res A, 78, pp. 222-235; Fierz, F.C., Beckmann, F., Huser, M., Irsen, S.H., Leukers, B., Witte, F., Degistirici, O., Muller, B., The morphology of anisotropic 3D-printed hydroxyapatite scaffolds (2008) Biomaterials, 29, pp. 3799-3806; Singh, R., Lee, P.D., Lindley, T.C., Dashwood, R.J., Ferrie, E., Imwinkelried, T., Characterization of the structure and permeability of titanium foams for spinal fusion devices (2009) Acta Biomater, 5, pp. 477-487; Wei, J., Jia, J., Wu, F., Wei, S., Zhou, H., Zhang, H., Shin, J.W., Liu, C., Hierarchically microporous/macroporous scaffold of magnesium-calcium phosphate for bone tissue regeneration (2010) Biomaterials, 31, pp. 1260-1269; Rucker, M., Laschke, M.W., Junker, D., Carvalho, C., Tavassol, F., Mulhaupt, R., Gellrich, N.C., Menger, M.D., Vascularization and biocompatibility of scaffolds consisting of different calcium phosphate compounds (2007) J Biomed Mater Res A, 68, pp. 1002-1011; Klenke, F.M., Liu, Y., Yuan, H., Hunziker, E.B., Siebenrock, K.A., Hofstetter, W., Impact of pore size on the vascularization and osseointegration of ceramic bone substitutes in vivo (2007) J Biomed Mater Res A, 85, pp. 777-786; Lee, S.J., Choi, J.S., Park, K.S., Khang, G., Lee, Y.M., Lee, H.B., Response of MG63 osteoblast-like cells onto polycarbonate membrane surfaces with different micropore sizes (2004) Biomaterials, 25, pp. 4699-4707; Kim, H., Lee, E., Kim, H., Salih, V., Knowles, J.C., Effect of fluoridation of hydroxyapatite in hydroxyapatite- polycaprolactone composites on osteoblast activity (2005) Biomaterials, 25, pp. 4395-4404; Son, E., Do, H., Joo, H., Pyo, S., Induction of alkaline phosphatase activity by L-ascorbic acid in human osteoblastic cells: A potential role for CK2 and Ikaros (2007) Nutrition, 23, pp. 745-753; Guo, X., Gough, J.E., Xiao, P., Liu, J., Shen, Z., Fabrication of nanostructured hydroxyapatite and analysis of human osteoblastic cellular response (2007) J Biomed Mater Res A, 82, pp. 1022-1032; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21, pp. 1803-1810; Mendonça, G., Mendonça, D.B., Simões, L.G., Araújo, A.L., Leite, E.R., Duarte, W.R., Aragão, F.J., Cooper, L.F., The effects of implant surface nanoscale features on osteoblast-specific gene expression (2009) Biomaterials, 30, pp. 4053-4062
Keywords: Agglomeration; alkaline phosphatase; Apatite; article; Bioceramics; Biocompatible Materials; Biological Markers; Biological materials; Biological response; Biomaterials; Bone; bone morphogenetic protein 2; Bone morphogenetic protein-2; Bone Regeneration; cell adhesion; cell function; cell granule; cell migration; cell proliferation; Cells, Cultured; collagen type 1; Collagen type I; colony stimulating factor 1; Colony-stimulating factor; drug activity; Drug release; Durapatite; Expression levels; Fourier transform infrared spectroscopy; Fourier transforms; Granulation; Granules; growth rate; human; human cell; Human osteoblast-like cells; Humans; hydroxyapatite; In-vitro; infrared spectroscopy; Interconnected porosity; Macro-porosity; Macropores; Macroporosity; Macroporous; materials testing; matrix; Mercury (metal); Mercury intrusion porosimetry; Microscopy, Electron, Scanning; Microstructured; Nano-materials; Nano-structured; nanomaterial; Nanomaterials; Nanostructured materials; Nanostructures; osteoblast; Osteoblast response; Osteoblast-like cells; Osteoblasts; Osteoprotegerin; Phosphatases; polyurethan; Polyurethane sponge; Polyurethanes; porosity; Porous structures; Reverse Transcriptase Polymerase Chain Reaction; Scanning electron microscopy; SEM; Spectroscopy, Fourier Transform Infrared; Surface area; surface property; X ray diffraction; X-Ray Diffraction

An intrauterine pressure generator for educational simulation of labour and delivery - Bastos, L.F.; Lobo, M.F.; van Meurs, W.L.; Ayres-de-Campos, D. (Medical Engineering and PhysicsMed. Eng. Phys., 2010)
Simulation provides a risk free and controllable environment for training of healthcare providers. The limited realism of available simulators and training programs impedes immersive training in obstetric emergencies. In developed countries, intrapartum monitoring in high-risk cases involves continuous evaluation of foetal heart rate and uterine contractions signals. We present an essential component of a high-fidelity simulator for normal and critical situations in labour and delivery, namely an intrauterine pressure generator. The signal model behind the generator consists of a truncated Gaussian curve with the programmable features: amplitude, frequency, duration, and resting tone. Through analysis of 44. h of physiological data, we demonstrate that the natural variability of these features and of the baseline pressure can be approximated by deterministic trends and stationary stochastic processes. Signal parameters can be controlled by simulation instructors, scripts, or other models to reflect different patients, pathologies, and evolving clinical situations. Twelve 40-min tracings reflecting three different patients in labour were presented to three clinical experts, who attributed similar realism scores to simulated and to real tracings. © 2010 IPEM.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: MEPHEdoi: 10.1016/j.medengphy.2010.04.015PubMed ID: 20494606Language of Original Document: EnglishCorrespondence Address: Bastos, L.F.; Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Rua Dr. Roberto Frias, s/n, I302, 4200-465 Porto, Portugal; email: lbastos@fe.up.ptReferences: Carlin, A., Alfirevic, Z., Intrapartum foetal emergencies (2006) Semin Foetal Neonatal Med, 11, pp. 150-157;Draycott, T., Sibanda, T., Owen, L., Akande, V., Winter, C., Reading, S., Does training in obstetric emergencies improve neonatal outcome? (2006) BJOG, 113, pp. 177-182; Daniels, K., Lipman, S., Harney, K., Arafeh, J., Druzin, M., Use of simulation based team training for obstetric crises in resident education (2008) Simul Healthc, 3, pp. 154-160; Gardner, R., Walzer, T.B., Simon, R., Raemer, D.B., Obstetric simulation as a risk control strategy: course design and evaluation (2008) Simul Healthc, 3, pp. 119-127; Pliego, J.F., Wehbe-Janek, H., Rajab, M.H., Browning, J.L., Fothergill, R.E., Ob/Gyn boot camp using high-fidelity human simulators: enhancing residents' perceived competency, confidence in taking a leadership role, and stress hardiness (2008) Simul Healthc, 3, pp. 82-89; Crofts, J.F., Bartlett, C., Ellis, D., Hunt, L.P., Fox, R., Draycott, T.J., Training for shoulder dystocia: a trial of simulation using low-fidelity and high-fidelity mannequins (2006) Obstet Gynecol (New York, 1953), 108, pp. 1477-1485; Gardner, R., Raemer, D.B., Simulation in obstetrics and gynecology (2008) Obstet Gynecol Clin North Am, 35, pp. 97-127; (2001) The use of electronic foetal monitoring: the use and interpretation of cardiotocography in intrapartum foetal surveillance, , Royal-College-of-Obstetricians-and-Gynaecologists, RCOG, London; (2006) Intrapartum foetal surveillance: clinical guidelines, , Royal-Australian-and-New-Zealand-College-of-Obstetricians-and-Gynaecologists, RANZCOG, Melbourne; Bracero, L.A., Roshanfekr, D., Byrne, D.W., Analysis of antepartum foetal heart rate tracing by physician and computer (2000) J Matern Foetal Med, 9, pp. 181-185; Doyle, C., Angelotti, T., Diagnosis of an unsuspected maternal hemorrhage via foetal heart rate tracing (2004) J Clin Anesth, 16, pp. 465-468; Donn, S.M., Sinha, S.K., Chiswick, M.L., (2002) Birth asphyxia and the brain: basic science and clinical implications, , Blackwell Publishing; Laros, J.R.K., Presidential address: medical-legal issues in obstetrics and gynecology (2005) Am J Obstet Gynecol, 192, pp. 1883-1889; Cusick, W., Smulian, J.C., Vintzileos, A.M., Intrapartum use of foetal heart rate monitoring, contraction monitoring, and amnioinfusion (1995) Clin Perinatol, 22, pp. 875-906; Vanner, T., Gardosi, J., Intrapartum assessment of uterine activity (1996) Baillieres Clin Obstet Gynaecol, 10, pp. 243-257; Bakker, P.C.A.M., Van Rijswijk, S., Van Rijsiwijk, S., van Geijn, H.P., Uterine activity monitoring during labor (2007) J Perinat Med, 35, pp. 468-477; Bakker, P.C.A.M., van Geijn, H.P., Uterine activity: implications for the condition of the foetus (2008) J Perinat Med, 36, pp. 30-37; Andersen, H.F., Barclay, M.L., A computer-model of uterine contractions based on discrete contractile elements (1995) Obstet Gynecol, 86, pp. 108-111. , J; Young, R.C., A computer model of uterine contractions based on action potential propagation and intercellular calcium waves (1997) Obstet Gynecol, 89, pp. 604-608. , A; Wray, S., Uterine contraction and physiological mechanisms of modulation (1993) Am J Physiol, 264, pp. C1-C18. , J; Wray, S., Kupittayanant, S., Shmygol, A., Smith, R.D., Burdyga, T., The physiological basis of uterine contractility: a short review (2001) Exp Physiol, 86, pp. 239-246; Vauge, C., Carbonne, B., Papiernik, E., Ferre, F., A mathematical model of uterine dynamics and its application to human parturition (2000) Acta Biotheor, 48, pp. 95-105. , J; Moreau, R., Pham, M.T., Redarce, T., Dupuis, O., Simulation of forceps extraction on a childbirth simulator (2008) Proceedings of the IEEE International Conference on Robotics and Automation (ICRA), pp. 1100-1105; Klavan, M., Laver, A.T., Boscola, M.A., (1977) Clinical concepts of foetal heart rate monitoring, , Hewlett-Packard Waltham, Mass; Parer, J.T., (1997) Handbook of foetal heart rate monitoring, , W.B. Saunders Company, Philadelphia; Maul, H., Maner, W.L., Olson, G., Saade, G.R., Garfield, R.E., Non-invasive transabdominal uterine electromyography correlates with the strength of intrauterine pressure and is predictive of labor and delivery (2004) J Matern Foetal Neonatal Med, 15, pp. 297-301; Cobo, E., Quintero, C.A., Strada, G., Zambrana, M.A., Uterine behavior in abruptio placentae. I. Contraction patterns and their reactivity to oxytocin (1965) Am J Obstet Gynecol, 93, pp. 1151-1156; Seitchik, J., Quantitating uterine contractility in clinical context (1981) Obstet Gynecol, 57, pp. 453-457; Burchell, H.J., Odendaal, H.J., de Wet, J.I., Badenhorst, P.N., Uterine contraction patterns in abruptio placentae (1985) S Afr Med J, 67, pp. 48-50; Harbert, G.M., Assessment of uterine contractility and activity (1992) Clin Obstet Gynecol, 35, pp. 546-558; Bruce, E.N., (2001) Biomedical signal processing and signal modeling, , Wiley-Interscience; Levinson, N., The Wiener RMS (root mean square) error criterion in filter design and prediction (1947) J Math Phys, 25, pp. 261-278; Paul, M.J., Smeltzer, J.S., Relationship of measured external tocodynamometry with measured internal uterine activity (1991) Am J Perinatol, 8, pp. 417-420; Miles, A.M., Monga, M., Richeson, K.S., Correlation of external and internal monitoring of uterine activity in a cohort of term patients (2001) Am J Perinatol, 18, pp. 137-140; van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit Comput, 13, pp. 317-324; van Meurs, W.L., Nikkelen, E., Good, M.L., Pharmacokinetic-pharmacodynamic model for educational simulations (1998) IEEE Trans Biomed Eng, 45, pp. 582-590
Keywords: article; Clinical situations; Computer simulation; delivery; Delivery, Obstetric; Developed countries; Educational simulations; Essential component; Female; Fetal monitoring; Gaussian curves; generator; Health care providers; Heart Rate, Fetal; Heart rates; High-fidelity simulators; Humans; Immersive; intrauterine pressure; labor; Labor, Obstetric; Labour and delivery; medical education; Medical educational simulation; muscle tone; Natural variability; normal distribution; Obstetrics; Physiological data; Pregnancy; Prenatal Diagnosis; Pressure; Pressure generators; priority journal; Random processes; Risk free; Signal generator; Signal generators; Signal models; Signal parameters; Signal Processing, Computer-Assisted; simulation; Stationary stochastic process; statistical model; statistical parameters; statistics; Stochastic Processes; Time Factors; Training program; Uterine activities; Uterine activity; Uterine Contraction; Uterine Monitoring; uterus contraction

A model for educational simulation of hemodynamic transitions at birth - Sá-Couto, C.D.; Andriessen, P.; van Meurs, W.L.; Ayres-de-Campos, D.; Sá-Couto, P.M. (Pediatric ResearchPediatr. Res., 2010)
Birth is characterized by swift and complex transitions in hemodynamic and respiratory variables. Unrecognized pathologies or incidents may quickly become fatal or cause permanent damage. This article introduces an essential component of an acute perinatal care simulator, namely a model for educational simulation of normal hemodynamic transitions seen during and shortly after birth. We explicitly formulate educational objectives and adapt a preexisting model for the simulation of neonatal cardiovascular physiology to include essential aspects of fetal hemodynamics. From the scientific literature, we obtain model parameters that characterize these aspects quantitatively. The fetal model is controlled by a time-and event-based script of changes occurring at birth, such as onset of breathing and cord clamping, and the transitory phase up to 24 h after birth. Comparison of simulation results with published target data confirms that realistic simulated hemodynamic vital signs are achieved. Copyright © 2010 International Pediatric Research Foundation, Inc.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: PEREBdoi: 10.1203/PDR.0b013e3181c2def3Language of Original Document: EnglishCorrespondence Address: Van Meurs, W. L.; INEB-Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUP, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: wvanmeurs@ineb.up.ptReferences: Van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit, 13, pp. 317-324;Sá Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Andriessen, P., A model for educational simulation of neonatal cardiovascular pathophysiology (2006) Simul Healthc, 1, pp. 4-9; Zijlmans, M., Sá-Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Andriessen, P., Corrected and improved model for educational simulation of neonatal cardiovascular pathophysiology (2009) Simul Healthc, 4, pp. 49-53; Goodwin, J.A., Van Meurs, W.L., Sá Couto, C.D., Beneken, J.E., Graves, S.A., A model for educational simulation of infant cardiovascular physiology (2004) Anesth Analg, 99, pp. 1655-1664; Ménigault, E., Vieyres, P., Lepoivre, B., Durand, A., Pourcelot, L., Berson, M., Fetal heart modelling based on a pressure-volume relationship (1997) Med Biol Eng Comput, 35, pp. 715-721; Pennati, G., Bellotti, M., Fumero, R., Mathematical modeling of the human foetal cardiovascular system based on Doppler ultrasound data (1997) Med Eng Phys, 19, pp. 327-335; Huikeshoven, F., Coleman, T.G., Jongsma, H.W., Mathematical model of the fetal cardiovascular system: The uncontrolled case (1980) Am J Physiol, 239, pp. R317-R325; Mielke, G., Benda, N., Cardiac output and central distribution of blood flow in the human fetus (2001) Circulation, 103, pp. 1662-1668; Cunningham, G., Leveno, K., MacDonald, P., Gilstrap III, L., Gant, N., Hankins, G., Clark, S., The morphological and functional development of the fetus (1996) Williams Obstetrics, pp. 151-190. , Cunningham G, Leveno K, MacDonald P, Gilstrap III L, Gant N, Hankins G, Clark S (eds) 20th Ed. Appleton & Lange, CT; Huikeshoven, F.J., Hope, I.D., Power, G.G., Gilbert, R.D., Longo, L.D., Mathematical model of fetal circulation and oxygen delivery (1985) Am J Physiol, 249, pp. R192-R202; Rasanen, J., Wood, D.C., Weiner, S., Ludomirski, A., Huhta, J.C., Role of the pulmonary circulation in the distribution of human fetal cardiac output during the second half of pregnancy (1996) Circulation, 94, pp. 1068-1073; Assali, N.S., Morris, J.A., Beck, R., Cardiovascular hemodynamics in the fetal lamb before and after lung expansion (1965) Am J Physiol, 208, pp. 122-129; Vilos, G.A., Liggins, G.C., Intrathoracic pressures in fetal sheep (1982) J Dev Physiol, 4, pp. 247-256; Hooper, S.B., Wallace, M.J., Role of the physicochemical environment in lung development (2006) Clin Exp Pharmacol Physiol, 33, pp. 273-279; Greenspan, J.S., Shaffer, T.H., Fox, W.W., Spitzer, A.R., Assisted ventilation: Physiologic implications and complications (1998) Fetal and Neonatal Physiology, 2. , Polin RA, Fox WW (eds) W.B. Saunders Company, Philadelphia, PA; Friedman, A.H., Fahey, J.T., The transitions from fetal to neonatal circulation: Normal responses and implications for infants with heart disease (1993) Semin Perinatol, 17, pp. 106-121; Ghanayem, N.S., Gordon, J.B., Modulation of pulmonary vasomotor tone in the fetus and neonate (2001) Respir Res, 2, pp. 139-144; Dawes, G.S., Mott, J.C., Widdicombe, J.G., Wyatt, D.G., Changes in the lungs of the new-born lamb (1953) J Physiol, 121, pp. 141-162; Brook, M.M., Heymann, M.A., Teitel, D.F., The heart (2001) Care of the High-Risk, , Klaus MH, Fanaroff AA (eds) 5th ed. W.B. Saunders Company, Philadelphia, PA; Gutyon, A.C., Fetal and neonatal physiology (1991) Textbook of Medical Physiology, , Guyton AC (ed) 8th ed. W.B. Saunders Company Philadelphia, PA; Lagercrantz, H., Bistoletti, P., Catecholamine release in the newborn infant at birth (1977) Pediatr Res, 11, pp. 889-893; Padbury, J.F., Diakomanolis, E.S., Hobel, C.J., Perelman, A., Fisher, D.A., Neonatal adaptation: Sympatho-adrenal response to umbilical cord cutting (1981) Pediatr Res, 15, pp. 1483-1487; Minoura, S., Gilbert, R.D., Postnatal change of cardiac function in lambs: Effects of ganglionic block and afterload (1987) J Dev Physiol, 9, pp. 123-135; Coskun, S., Yüksel, H., Bilgi, Y., Lacin, S., Tansug, N., Onag, A., Non-invasive evaluation of the adaptations of cardiac function in the neonatal period: A comparison of healthy infants delivered by vaginal route and caesarean section (2001) Acta Med Okayama, 55, pp. 213-218; Kishkurno, S., Takahashi, Y., Harada, K., Ishida, A., Tamura, M., Takada, G., Postnatal changes in left ventricular volume and contractility in healthy term infants (1997) Pediatric Cardiology, 18 (2), pp. 91-95. , DOI 10.1007/s002469900123; Shiota, T., Harada, K., Takada, G., Left ventricular systolic and diastolic function during early neonatal period using transthoracic echocardiography (2002) Tohoku J Exp Med, 197, pp. 151-158; Walther, F.J., Benders, M.J., Leighton, J.O., Early changes in the neonatal circulatory transition (1993) J Pediatr, 123, pp. 625-632; Hiraishi, S., Misawa, H., Oguchi, K., Kadoi, N., Saito, K., Fujino, N., Hojo, M., Yashiro, K., Two-dimensional Doppler echocardiographic assessment of closure of the ductus arteriosus in normal newborn infants (1987) J Pediatr, 111, pp. 755-760; Migliavacca, F., Dubini, G., Pennati, G., Pietrabissa, R., Fumero, R., Hsia, T.Y., De Leval, M.R., Computational model of the fluid dynamics in systemic-to-pulmonary shunts (2000) J Biomech, 33, pp. 549-557; Teitel, D.F., Iwamoto, H.S., Rudolph, A.M., Effects of birth-related events on central blood flow patterns (1987) Pediatr Res, 22, pp. 557-566; Anderson, D.F., Bissonnette, J.M., Faber, J.J., Thornburg, K.L., Central shunt flows and pressures in the mature fetal lamb (1981) Am J Physiol, 241, pp. H60-H66; Agata, Y., Hiraishi, S., Oguchi, K., Misawa, H., Horiguchi, Y., Fujino, N., Yashiro, K., Shimada, N., Changes in left ventricular output from fetal to early neonatal life (1991) J Pediatr, 119, pp. 441-445; Harada, K., Shiota, T., Takahashi, Y., Tamura, M., Takada, G., Changes in the volume and performance of the left ventricle in the early neonatal period (1994) Early Hum Dev, 39, pp. 201-209; Moss, A.J., Emmanouilides, G.C., Adams, F.H., Chuang, K., Response of ductus arteriosus and pulmonary and systemic arterial pressure to changes in oxygen environment in newborn infants (1964) Pediatrics, 33, pp. 937-944; Emmanouilides, G.C., Moss, A.J., Monset-Couchard, M., Marcano, B.A., Rzeznic, B., Cardiac output in newborn infants (1970) Biol Neonate, 15, pp. 186-197; Emmanouilides, G.C., Moss, A.J., Duffie Jr., E.R., Adams, F.H., Pulmonary arterial pressure changes in human newborn infants from birth to 3 days of age (1964) J Pediatr, 65, pp. 327-333; Soni, N., Williams, P., Positive pressure ventilation: What is the real cost? (2008) Br J Anaesth, 101, pp. 446-457; Moss, A.J., Emmanouilides, G.C., Duffie Jr., E.R., Closure of the ductus arteriosus in the newborn infant (1963) Pediatrics, 32, pp. 25-30
Keywords: article; artificial ventilation; biological model; birth; Blood flow; blood flow velocity; blood pressure; breathing; breathing mechanics; cardiovascular function; clamp; comparative study; Computer simulation; Constriction; education; evaluation; fetus; hemodynamics; human; Humans; Infant, Newborn; ligation; Models, Cardiovascular; newborn; Parturition; perinatal care; priority journal; Regional Blood Flow; reproducibility; Reproducibility of Results; Respiration, Artificial; Respiratory Mechanics; scientific literature; simulator; stimulation; time; Time Factors; umbilical cord; vascularization; vital sign

Neuropeptide y and osteoblast differentiation - The balance between the neuro-osteogenic network and local control: Review Article - Franquinho, F.; Liz, M.A.; Nunes, A.F.; Neto, E.; Lamghari, M.; Sousa, M.M. (FEBS JournalFEBS J., 2010)
Accumulating evidence has contributed to a novel view in bone biology: bone remodeling, specifically osteoblast differentiation, is under the tight control of the central and peripheral nervous systems. Among other players in this neuro-osteogenic network, the neuropeptide Y (NPY) system has attracted particular attention. At the central nervous system level, NPY exerts its function in bone homeostasis through the hypothalamic Y2 receptor. Locally in the bone, NPY action is mediated by its Y1 receptor. Besides the presence of Y1, a complex network exists locally: not only there is input of the peripheral nervous system, as the bone is directly innervated by NPY-containing fibers, but there is also input from non-neuronal cells, including bone cells capable of NPY expression. The interaction of these distinct players to achieve a multilevel control system of bone homeostasis is still under debate. In this review, we will integrate the current knowledge on the impact of the NPY system in bone biology, and discuss the mechanisms through which the balance between central and the peripheral NPY action might be achieved. © 2010 FEBS.
Cited By (since 1996): 5Export Date: 21 November 2012Source: Scopusdoi: 10.1111/j.1742-4658.2010.07774.xPubMed ID: 20681986Language of Original Document: EnglishCorrespondence Address: Sousa, M. M.; IBMC, Rua Campo Alegre 823, 4150-180 Porto, Portugal; email: msousa@ibmc.up.ptChemicals/CAS: neuropeptide Y, 82785-45-3, 83589-17-7; Leptin; Neuropeptide Y; Protein Isoforms; Receptors, Neuropeptide YReferences: Bellido, T., Ali, A.A., Gubrij, I., Plotkin, L.I., Fu, Q., O'Brien, C.A., Manolagas, S.C., Jilka, R.L., Chronic elevation of parathyroid hormone in mice reduces expression of sclerostin by osteocytes: A novel mechanism for hormonal control of osteoblastogenesis (2005) Endocrinology, 146, pp. 4577-4583;Keller, H., Kneissel, M., SOST is a target gene for PTH in bone (2005) Bone, 37, pp. 148-158; O'Brien, C.A., Plotkin, L.I., Galli, C., Goellner, J.J., Gortazar, A.R., Allen, M.R., Robling, A.G., Turner, C.H., Control of bone mass and remodeling by PTH receptor signaling in osteocytes (2008) PLoS ONE, 3, p. 2942; Robling, A.G., Niziolek, P.J., Baldridge, L.A., Condon, K.W., Allen, M.R., Alam, I., Mantila, S.M., Harris, S.E., Mechanical stimulation of bone in vivo reduces osteocyte expression of Sost/sclerostin (2008) J Biol Chem, 283, pp. 5866-5875; Tatsumi, S., Ishii, K., Amizuka, N., Li, M., Kobayashi, T., Kohno, K., Ito, M., Ikeda, K., Targeted ablation of osteocytes induces osteoporosis with defective mechanotransduction (2007) Cell Metab, 5, pp. 464-475; McDonald, A.C., Schuijers, J.A., Shen, P.J., Gundlach, A.L., Grills, B.L., Expression of galanin and galanin receptor-1 in normal bone and during fracture repair in the rat (2003) Bone, 33, pp. 788-797; Pacifici, R., Cytokines, estrogen, and postmenopausal osteoporosis - The second decade (1998) Endocrinology, 139, pp. 2659-2661; You, L., Temiyasathit, S., Lee, P., Kim, C.H., Tummala, P., Yao, W., Kingery, W., Jacobs, C.R., Osteocytes as mechanosensors in the inhibition of bone resorption due to mechanical loading (2008) Bone, 42, pp. 172-179; Lerner, U.H., The role of skeletal nerve fibers in bone metabolism (2000) Endocrinologist, 10, pp. 377-382; Sherman, M.S., The nerves of bone (1963) J Bone Joint Surg Am, 45, pp. 522-528; Kuntz, A., Richins, C.A., Innervation of the bone marrow (1945) J Comp Neurol, 83, pp. 213-222; Miller, M.R., Kasahara, M., Observations on innervation of human long bones (1963) Anat Rec, 145, pp. 13-23; Thurston, T.J., Distribution of nerves in long bones as shown by silver impregnation (1982) J Anat, 134, pp. 719-728; Calvo, W., Fortezav, J., On development of bone marrow innervation in new-born rats as studied with silver impregnation and electron microscopy (1969) Am J Anat, 126, pp. 355-371; Sisask, G., Bjurholm, A., Ahmed, M., Kreicbergs, A., The development of autonomic innervation in bone and joints of the rat (1996) J Auton Nerv Syst, 59, pp. 27-33; Gajda, M., Litwin, J.A., Cichocki, T., Timmermans, J.P., Adriaensen, D., Development of sensory innervation in rat tibia: Co-localization of CGRP and substance P with growth-associated protein 43 (GAP-43) (2005) J Anat, 207, pp. 135-144; Jackman, A., Fitzgerald, M., Development of peripheral hindlimb and central spinal cord innervation by subpopulations of dorsal root ganglion cells in the embryonic rat (2000) J Comp Neurol, 418, pp. 281-298; Kosaras, B., Jakubowski, M., Kainz, V., Burstein, R., Sensory innervation of the calvarial bones of the mouse (2009) J Comp Neurol, 515, pp. 331-348; Jones, K.B., Mollano, A.V., Morcuende, J.A., Cooper, R.R., Saltzman, C.L., Bone and brain: A review of neural, hormonal, and musculoskeletal connections (2004) Iowa Orthop J, 24, pp. 123-132; Alberius, P., Skagerberg, G., Adrenergic innervation of the calvarium of the neonatal rat. Its relationship to the sagittal suture and developing parietal bones (1990) Anat Embryol (Berl), 182, pp. 493-498; Herskovits, M.S., Hallas, B.H., Singh, I.J., Study of sympathetic innervation of cranial bones by axonal transport of horseradish peroxidase in the rat: Preliminary findings (1993) Acta Anat (Basel), 147, pp. 178-183; Hill, E.L., Elde, R., Distribution of CGRP-, VIP-, D beta H-, SP-, and NPY-immunoreactive nerves in the periosteum of the rat (1991) Cell Tissue Res, 264, pp. 469-480; Kruger, L., Silverman, J.D., Mantyh, P.W., Sternini, C., Brecha, N.C., Peripheral patterns of calcitonin-gene-related peptide general somatic sensory innervation: Cutaneous and deep terminations (1989) J Comp Neurol, 280, pp. 291-302; Silverman, J.D., Kruger, L., Calcitonin-gene-related-peptide-immunoreactive innervation of the rat head with emphasis on specialized sensory structures (1989) J Comp Neurol, 280, pp. 303-330; Ducy, P., Amling, M., Takeda, S., Priemel, M., Schilling, A.F., Beil, F.T., Shen, J., Karsenty, G., Leptin inhibits bone formation through a hypothalamic relay: A central control of bone mass (2000) Cell, 100, pp. 197-207; Robertson, S.A., Leinninger, G.M., Myers, Jr.M.G., Molecular and neural mediators of leptin action (2008) Physiol Behav, 94, pp. 637-642; Ahima, R.S., Flier, J.S., Leptin (2000) Annu Rev Physiol, 62, pp. 413-437; Tartaglia, L.A., Dembski, M., Weng, X., Deng, N., Culpepper, J., Devos, R., Richards, G.J., Deeds, J., Identification and expression cloning of a leptin receptor, OB-R (1995) Cell, 83, pp. 1263-1271; Zhang, Y., Proenca, R., Maffei, M., Barone, M., Leopold, L., Friedman, J.M., Positional cloning of the mouse obese gene and its human homologue (1994) Nature, 372, pp. 425-432; Takeda, S., Elefteriou, F., Levasseur, R., Liu, X., Zhao, L., Parker, K.L., Armstrong, D., Karsenty, G., Leptin regulates bone formation via the sympathetic nervous system (2002) Cell, 111, pp. 305-317; Stephens, T.W., Basinski, M., Bristow, P.K., Bue-Valleskey, J.M., Burgett, S.G., Craft, L., Hale, J., Kriauciunas, A., The role of neuropeptide y in the antiobesity action of the obese gene product (1995) Nature, 377, pp. 530-532; Chronwall, B.M., Dimaggio, D.A., Massari, V.J., Pickel, V.M., Ruggiero, D.A., O'Donohue, T.L., The anatomy of neuropeptide-Y-containing neurons in rat brain (1985) Neuroscience, 15, pp. 1159-1181; Tatemoto, K., Carlquist, M., Mutt, V., Neuropeptide y - A novel brain peptide with structural similarities to peptide YY and pancreatic polypeptide (1982) Nature, 296, pp. 659-660; Pedrazzini, T., Pralong, F., Grouzmann, E., Neuropeptide Y: The universal soldier (2003) Cell Mol Life Sci, 60, pp. 350-377; Erickson, J.C., Hollopeter, G., Palmiter, R.D., Attenuation of the obesity syndrome of ob/ob mice by the loss of neuropeptide y (1996) Science, 274, pp. 1704-1707; Allison, S.J., Baldock, P.A., Herzog, H., The control of bone remodeling by neuropeptide y receptors (2007) Peptides, 28, pp. 320-325; Bjurholm, A., Kreicbergs, A., Terenius, L., Goldstein, M., Schultzberg, M., Neuropeptide Y-, tyrosine hydroxylase- and vasoactive intestinal polypeptide-immunoreactive nerves in bone and surrounding tissues (1988) J Auton Nerv Syst, 25, pp. 119-125; Ahmed, M., Bjurholm, A., Kreicbergs, A., Schultzberg, M., Neuropeptide Y, tyrosine hydroxylase and vasoactive intestinal polypeptide-immunoreactive nerve fibers in the vertebral bodies, discs, dura mater, and spinal ligaments of the rat lumbar spine (1993) Spine, 18, pp. 268-273; Hill, E.L., Turner, R., Elde, R., Effects of neonatal sympathectomy and capsaicin treatment on bone remodeling in rats (1991) Neuroscience, 44, pp. 747-755; Lindblad, B.E., Nielsen, L.B., Jespersen, S.M., Bjurholm, A., Bunger, C., Hansen, E.S., Vasoconstrictive action of neuropeptide y in bone. The porcine tibia perfused in vivo (1994) Acta Orthop Scand, 65, pp. 629-634; Ahmad, T., Ugarph-Morawski, A., Li, J., Bileviciute-Ljungar, I., Finn, A., Ostenson, C.G., Kreicbergs, A., Bone and joint neuropathy in rats with type-2 diabetes (2004) Regul Pept, 119, pp. 61-67; Ericsson, A., Schalling, M., McIntyre, K.R., Lundberg, J.M., Larhammar, D., Seroogy, K., Hokfelt, T., Persson, H., Detection of neuropeptide y and its mRNA in megakaryocytes: Enhanced levels in certain autoimmune mice (1987) Proc Natl Acad Sci USA, 84, pp. 5585-5589; Ahmed, M., Srinivasan, G.R., Theodorsson, E., Bjurholm, A., Kreicbergs, A., Extraction and quantitation of neuropeptides in bone by radioimmunoassay (1994) Regul Pept, 51, pp. 179-188; Bjurholm, A., Neuroendocrine peptides in bone (1991) Int Orthop, 15, pp. 325-329; Bjurholm, A., Kreicbergs, A., Schultzberg, M., Lerner, U.H., Neuroendocrine regulation of cyclic AMP formation in osteoblastic cell lines (UMR-106-01, ROS 17/2.8, MC3T3-E1, and Saos-2) and primary bone cells (1992) J Bone Miner Res, 7, pp. 1011-1019; Lundberg, P., Allison, S.J., Lee, N.J., Baldock, P.A., Brouard, N., Rost, S., Enriquez, R.F., Simmons, P., Greater bone formation of Y2 knockout mice is associated with increased osteoprogenitor numbers and altered Y1 receptor expression (2007) J Biol Chem, 282, pp. 19082-19091; Nakamura, M., Sakanaka, C., Aoki, Y., Ogasawara, H., Tsuji, T., Kodama, H., Matsumoto, T., Noma, M., Identification of two isoforms of mouse neuropeptide Y-Y1 receptor generated by alternative splicing. Isolation, genomic structure, and functional expression of the receptors (1995) J Biol Chem, 270, pp. 30102-30110; Togari, A., Arai, M., Mizutani, S., Koshihara, Y., Nagatsu, T., Expression of mRNAs for neuropeptide receptors and beta-adrenergic receptors in human osteoblasts and human osteogenic sarcoma cells (1997) Neurosci Lett, 233, pp. 125-128; Igwe, J.C., Jiang, X., Paic, F., Ma, L., Adams, D.J., Baldock, P.A., Pilbeam, C.C., Kalajzic, I., Neuropeptide y is expressed by osteocytes and can inhibit osteoblastic activity (2009) J Cell Biochem, 108, pp. 621-630; Nunes, A.F., Liz, M.A., Franquinho, F., Teixeira, L., Sousa, V., Chenu, C., Lamghari, M., Sousa, M.M., Neuropeptide y expression and function during osteoblast differentiation - Insights from transthyretin knockout mice (2010) FEBS J, 277, pp. 263-275; Baldock, P.A., Sainsbury, A., Couzens, M., Enriquez, R.F., Thomas, G.P., Gardiner, E.M., Herzog, H., Hypothalamic Y2 receptors regulate bone formation (2002) J Clin Invest, 109, pp. 915-921; Ducy, P., Schinke, T., Karsenty, G., The osteoblast: A sophisticated fibroblast under central surveillance (2000) Science, 289, pp. 1501-1504; Allison, S.J., Baldock, P., Sainsbury, A., Enriquez, R., Lee, N.J., Lin, E.J., Klugmann, M., Li, M., Conditional deletion of hypothalamic Y2 receptors reverts gonadectomy-induced bone loss in adult mice (2006) J Biol Chem, 281, pp. 23436-23444; Clegg, D.J., Brown, L.M., Zigman, J.M., Kemp, C.J., Strader, A.D., Benoit, S.C., Woods, S.C., Geary, N., Estradiol-dependent decrease in the orexigenic potency of ghrelin in female rats (2007) Diabetes, 56, pp. 1051-1058; Zengin, A., Zhang, L., Herzog, H., Baldock, P.A., Sainsbury, A., Neuropeptide y and sex hormone interactions in humoral and neuronal regulation of bone and fat (2010) Trends Endocrinol Metab, 21, pp. 411-418; Hosaka, H., Nagata, A., Yoshida, T., Shibata, T., Nagao, T., Tanaka, T., Saito, Y., Tatsuno, I., Pancreatic polypeptide is secreted from and controls differentiation through its specific receptors in osteoblastic MC3T3-E1 cells (2008) Peptides, 29, pp. 1390-1395; Teixeira, L., Sousa, D.M., Nunes, A.F., Sousa, M.M., Herzog, H., Lamghari, M., NPY revealed as a critical modulator of osteoblast function in vitro: New insights into the role of Y1 and Y2 receptors (2009) J Cell Biochem, 107, pp. 908-916; Sainsbury, A., Schwarzer, C., Couzens, M., Herzog, H., Y2 receptor deletion attenuates the type 2 diabetic syndrome of ob/ob mice (2002) Diabetes, 51, pp. 3420-3427; Wilding, J.P., Gilbey, S.G., Bailey, C.J., Batt, R.A., Williams, G., Ghatei, M.A., Bloom, S.R., Increased neuropeptide-Y messenger ribonucleic acid (mRNA) and decreased neurotensin mRNA in the hypothalamus of the obese (ob/ob) mouse (1993) Endocrinology, 132, pp. 1939-1944; Baldock, P.A., Allison, S., McDonald, M.M., Sainsbury, A., Enriquez, R.F., Little, D.G., Eisman, J.A., Herzog, H., Hypothalamic regulation of cortical bone mass: Opposing activity of Y2 receptor and leptin pathways (2006) J Bone Miner Res, 21, pp. 1600-1607; Baldock, P.A., Sainsbury, A., Allison, S., Lin, E.J., Couzens, M., Boey, D., Enriquez, R., Gardiner, E.M., Hypothalamic control of bone formation: Distinct actions of leptin and y2 receptor pathways (2005) J Bone Miner Res, 20, pp. 1851-1857; Baldock, P.A., Allison, S.J., Lundberg, P., Lee, N.J., Slack, K., Lin, E.J., Enriquez, R.F., During, M.J., Novel role of Y1 receptors in the coordinated regulation of bone and energy homeostasis (2007) J Biol Chem, 282, pp. 19092-19102; Lee, N.J., Doyle, K.L., Sainsbury, A., Enriquez, R.F., Hort, Y.J., Riepler, S.J., Baldock, P.A., Herzog, H., Critical role for Y1 receptors in mesenchymal progenitor cell differentiation and osteoblast activity (2010) J Bone Miner Res, , doi:; Allison, S.J., Baldock, P.A., Enriquez, R.F., Lin, E., During, M., Gardiner, E.M., Eisman, J.A., Herzog, H., Critical interplay between neuropeptide y and sex steroid pathways in bone and adipose tissue homeostasis (2009) J Bone Miner Res, 24, pp. 294-304; Sainsbury, A., Baldock, P.A., Schwarzer, C., Ueno, N., Enriquez, R.F., Couzens, M., Inui, A., Gardiner, E.M., Synergistic effects of Y2 and Y4 receptors on adiposity and bone mass revealed in double knockout mice (2003) Mol Cell Biol, 23, pp. 5225-5233; Elefteriou, F., Takeda, S., Liu, X., Armstrong, D., Karsenty, G., Monosodium glutamate-sensitive hypothalamic neurons contribute to the control of bone mass (2003) Endocrinology, 144, pp. 3842-3847; Baldock, P.A., Lee, N.J., Driessler, F., Lin, S., Allison, S., Stehrer, B., Lin, E.J., Wong, I.P., Neuropeptide y knockout mice reveal a central role of NPY in the coordination of bone mass to body weight (2009) PLoS ONE, 4, p. 8415; Sainsbury, A., Cusin, I., Doyle, P., Rohner-Jeanrenaud, F., Jeanrenaud, B., Intracerebroventricular administration of neuropeptide y to normal rats increases obese gene expression in white adipose tissue (1996) Diabetologia, 39, pp. 353-356; Sainsbury, A., Herzog, H., Inhibitory effects of central neuropeptide y on the somatotropic and gonadotropic axes in male rats are independent of adrenal hormones (2001) Peptides, 22, pp. 467-471; Nunes, A.F., Saraiva, M.J., Sousa, M.M., Transthyretin knockouts are a new mouse model for increased neuropeptide y (2006) FASEB J, 20, pp. 166-168; Prigge, S.T., Mains, R.E., Eipper, B.A., Amzel, L.M., New insights into copper monooxygenases and peptide amidation: Structure, mechanism and function (2000) Cell Mol Life Sci, 57, pp. 1236-1259; Eipper, B.A., Stoffers, D.A., Mains, R.E., The biosynthesis of neuropeptides: Peptide alpha-amidation (1992) Annu Rev Neurosci, 15, pp. 57-85; Marques, F., Sousa, J.C., Oliveira, P., Oliveira, H.C., Palha, J.A., The absence of transthyretin does not impair regulation of lipid and glucose metabolism (2007) Horm Metab Res, 39, pp. 529-533
Keywords: Animals; Bone and Bones; bone cell; bone innervation; bone mass; cell differentiation; Homeostasis; Humans; immunoreactivity; leptin; Nerve Net; neuropeptide Y; neuropeptide Y receptor; neuropeptide Y2 receptor; nonhuman; NPY; NPY receptors; osteoblast; Osteoblasts; phenotype; priority journal; protein expression; protein interaction; Protein Isoforms; Receptors, Neuropeptide Y; review

Proliferation and mineralization of bone marrow cells cultured on macroporous hydroxyapatite scaffolds functionalized with collagen type I for bone tissue regeneration - Teixeira, S.; Fernandes, M.H.; Ferraz, M.P.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
This study concerns the preparation and in vitro characterization of functionalized hydroxyapatite (HA) porous scaffolds, which are intended to be used as drug-delivery systems and bone-regeneration matrices. Hydroxyapatite scaffolds were prepared using the polymer replication method, and, after being submitted to a specific sintering cycle, collagen Type I was incorporated on the surface. After the coating procedure, collagen was crosslinked using the N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) conjugation method. In this study, hydroxyapatite scaffolds with uncrosslinked and cross-linked Type I collagen were evaluated. Cell morphology and deposition of extracellular matrix were assessed by scanning electron microscopy, whereas cell distribution was visualized by means of methylene blue staining. MTS and total DNA quantification assays were used to evaluate the viability and proliferation of human bone marrow cells cultured on all the materials for 28 days. Results showed that the cells were able to adhere, proliferate, and form a mineralized matrix on the surface of all the materials. Furthermore, the cells were able to spread from one pore to another and form cell clusters. The results show that these scaffolds are good candidates to serve as drug delivery vehicles and for tissue engineering purposes. © 2010 Wiley Periodicals, Inc.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32600Language of Original Document: EnglishCorrespondence Address: Teixeira, S.; Divisão de Biomateriais, INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: sandra_teixeira3@yahoo.comChemicals/CAS: 1 (3 dimethylaminopropyl) 3 ethylcarbodiimide, 1892-57-5, 25952-53-8, 7084-11-9; DNA, 9007-49-2; hydroxyapatite, 1306-06-5, 51198-94-8; methylene blue, 61-73-4; n hydroxysuccinimide, 6066-82-6; Collagen Type I; Cross-Linking Reagents; DNA, 9007-49-2; Durapatite, 1306-06-5; Methylene Blue, 61-73-4Manufacturers: SigmarecticelReferences: Nair, M.B., Suresh Babu, S., Varma, H.K., John, A., A triphasic ceramic-coated porous hydroxyapatite for tissue engineering application (2008) Acta Biomaterialia, 4 (1), pp. 173-181. , DOI 10.1016/j.actbio.2007.07.004, PII S174270610700102X;Navarro, M., Ginebra, M.P., Planell, J.A., Zeppetelli, S., Ambrosio, L., Development and cell response of a new biodegradable composite scaffold for guided bone regeneration (2004) Journal of Materials Science: Materials in Medicine, 15 (4), pp. 419-422. , DOI 10.1023/B:JMSM.0000021113.88702.9d; Nishikawa, M., Myoui, A., Ohgushi, H., Ikeuchi, M., Tamai, N., Yoshikawa, H., Bone tissue engineering using novel interconnected porous hydroxyapatite ceramics combined with marrow mesenchymal cells: Quantitative and three-dimensional image analysis (2004) Cell Transplant, 13, pp. 367-376; Fredericks, D.C., Bobst, J.A., Petersen, E.B., Nepola, J.V., Dennis, J.E., Caplan, A.I., Burgess, A.V., Schulz, O.H., Cellular interactions and bone healing responses to a novel porous tricalcium phosphate bone graft material (2004) Orthopedics, 27 (1 SUPPL.), pp. s167-s173; Wang, Y., Uemura, T., Dong, J., Kojima, H., Tanaka, J., Tateishi, T., Application of Perfusion Culture System Improves in Vitro and in Vivo Osteogenesis of Bone Marrow-Derived Osteoblastic Cells in Porous Ceramic Materials (2003) Tissue Engineering, 9 (6), pp. 1205-1214. , DOI 10.1089/10763270360728116; Wilson, C.E., De Bruijn, J.D., Van Blitterswijk, C.A., Verbout, A.J., Dhert, W.J., Design and fabrication of standardized hydroxyapatite scaffolds with a defined macro-architecture by rapid prototyping for bone-tissue-engineering research (2004) J Biomed Mater Res, 68, pp. 123-132; Rice, J.M., Hunt, J.A., Gallagher, J.A., Quantitative evaluation of the biocompatible and osteogenic properties of a range of biphasic calcium phosphate (BCP) granules using primary cultures of human osteoblasts and monocytes (2003) Calcif Tissue Int, 72, pp. 726-736; Zheng, Q., Zhu, T., Du, J., Wang, H., Li, S., Studies on the ossification of compound transplantation of porous TCP ceramics and bone marrow (1996) J Tongji Med Univ, 16, pp. 236-240; Goshima, J., Goldberg, V.M., Caplan, A.I., The osteogenic potential of culture-expanded rat marrow mesenchymal cells assayed in vivo in calcium phosphate ceramic blocks (1991) Clin Orthop Relat Res, 262, pp. 298-311; Cheung, H.S., Haak, M.H., Growth of osteoblasts on porous calcium phosphate ceramic: An in vitro model for biocompatibility study (1989) Biomaterials, 10, pp. 63-67; Barrere, F., Van Blitterswijk, C.A., De Groot, K., Bone regeneration: Molecular and cellular interactions with calcium phosphate ceramics (2006) Int J Nanomedicine, 1, pp. 317-332; Grynpas, M.D., Pilliar, R.M., Kandel, R.A., Renlund, R., Filiaggi, M., Dumitriu, M., Porous calcium polyphosphate scaffolds for bone substitute applications in vivo studies (2002) Biomaterials, 23, pp. 2063-2070; Heilmann, F., Standard, O.C., Muller, F.A., Hoffman, M., Development of graded hydroxyapatite/CaCO(3) composite structures for bone ingrowth (2007) J Mater Sci, 18, pp. 1817-1824; Hsu, Y.H., Turner, I.G., Miles, A.W., Mechanical characterization of dense calcium phosphate bioceramics with interconnected porosity (2007) J Mater Sci, 18, pp. 2319-2329; Huang, X., Miao, X., Novel porous hydroxyapatite prepared by combining H 2O 2 foaming with PU sponge and modified with PLGA and bioactive glass (2007) Journal of Biomaterials Applications, 21 (4), pp. 351-374. , DOI 10.1177/0885328206063905; Ito, Y., Tanaka, N., Fujimoto, Y., Yasunaga, Y., Ishida, O., Agung, M., Ochi, M., Bone formation using novel interconnected porous calcium hydroxyapatite ceramic hybridized with cultured marrow stromal stem cells derived from Green rat (2004) J Biomed Mater Res A, 69, pp. 454-461; Li, S.H., De Wijn, J.R., Layrolle, P., De Groot, K., Synthesis of macroporous hydroxyapatite scaffolds for bone tissue engineering (2002) J Biomed Mater Res A, 61, pp. 109-120; Navarro, M., Del Valle, S., Martinez, S., Zeppetelli, S., Ambrosio, L., Planell, J.A., Ginebra, M.P., New macroporous calcium phosphate glass ceramic for guided bone regeneration (2004) Biomaterials, 25 (18), pp. 4233-4241. , DOI 10.1016/j.biomaterials.2003.11.012, PII S0142961203010780; Ramay, H.R.R., Zhang, M., Biphasic calcium phosphate nanocomposite porous scaffolds for load-bearing bone tissue engineering (2004) Biomaterials, 25 (21), pp. 5171-5180. , DOI 10.1016/j.biomaterials.2003.12.023, PII S0142961203011724; Wang, C., Kasuga, T., Nogami, M., Macroporous calcium phosphate glass-ceramic prepared by two-step pressing technique and using sucrose as a pore former (2005) JMater Sci, 16, pp. 739-744; Xin, R., Leng, Y., Chen, J., Zhang, Q., A comparative study of calcium phosphate formation on bioceramics in vitro and in vivo (2005) Biomaterials, 26 (33), pp. 6477-6486. , DOI 10.1016/j.biomaterials.2005.04.028, PII S0142961205003030; De Bruijn, J.D., Van Den Brink, I., Mendes, S., Dekker, R., Bovell, Y.P., Van Blitterswijk, C.A., Bone induction by implants coated with cultured osteogenic bone marrow cells (1999) Adv Dent Res, 13, pp. 74-81; De Groot, K., Effect of porosity and physicochemical properties on the stability, resorption, and strength of calcium phosphate ceramics (1988) Ann N Y Acad Sci, 523, pp. 227-233; De Groot, K., Wolke, J.G., Jansen, J.A., Calcium phosphate coatings for medical implants (1998) Proc Inst Mech Eng, 212, pp. 137-147; Van Blitterswijk, C.A., Grote, J.J., De Groot, K., Daems, W.T., Kuijpers, W., The biological performance of calcium phosphate ceramics in an infected implantation site. I. Biological performance of hydroxyapatite during Staphylococcus aureus infection (1986) J Biomed Mater Res, 20, pp. 989-1002; Arinzeh, T.L., Tran, T., Mcalary, J., Daculsi, G., A comparative study of biphasic calcium phosphate ceramics for human mesenchymal stem-cell-induced bone formation (2005) Biomaterials, 26 (17), pp. 3631-3638. , DOI 10.1016/j.biomaterials.2004.09.035, PII S0142961204008646; Kim, H.W., Knowles, J.C., Kim, H.E., Porous scaffolds of gelatin-hydroxyapatite nanocomposites obtained by biomimetic approach: Characterization and antibiotic drug release (2005) J Biomed Mater Res B Appl Biomater, 74, pp. 686-698; Legeros, R.Z., Properties of osteoconductive biomaterials: Calcium phosphates (2002) Clin Orthop Relat Res, 395, pp. 81-98; Mao, X.Z., Zhou, J.N., Hu, J.Z., Ruan, J.M., Wang, W.C., Ni, J.D., Hydroxyapatite/ tricalcium phosphate matrix scaffold as cell carriers in vitro (2004) Zhong Nan Da Xue Xue Bao Yi Xue Ban, 29, pp. 371-375; Rodriguez-Lorenzo, L.M., Vallet-Regi, M., Ferreira, J.M., Ginebra, M.P., Aparicio, C., Planell, J.A., Hydroxyapatite ceramic bodies with tailored mechanical properties for different applications (2002) J Biomed Mater Res A, 60, pp. 159-166; Tancred, D.C., Mccormack, B.A., Carr, A.J., A quantitative study of the sintering and mechanical properties of hydroxyapatite/ phosphate glass composites (1998) Biomaterials, 19, pp. 1735-1743; Rusnah, M., Andanastuti, M., Idris, B., The influence of sintering temperature on the porosity and strength of porous hydroxyapatite ceramics (2004) Med J Malaysia, 59 (SUPPL. B), pp. 158-159; Sanchez-Salcedo, S., Werner, J., Vallet-Regi, M., Hierarchical pore structure of calcium phosphate scaffolds by a combination of gel-casting and multiple tape-casting methods (2008) Acta Biomaterialia, 4, pp. 913-922; Teixeira, S., Ferraz, M.P., Monteiro, F.J., Biocompatibility of highly macroporous ceramic scaffolds: Cell adhesion and morphology studies (2008) J Mater Sci, 19, pp. 855-899; Gelse, K., Pöschl, E., Aigner, T., Collagens - Structure, function, and biosynthesis (2003) Adv Rev, 55, pp. 1531-1546; Friess, W., Collagen - Biomaterial for drug delivery (1998) Eur J Pharm Biopharm, 45, pp. 113-136; Weadock, K.S., Miller, E.J., Bellincampi, L.D., Zawadsky, J.P., Dunn, M.G., Physical crosslinking of collagen fibers: Comparison of ultraviolet irradiation and dehydrothermal treatment (1995) J Biomed Mater Res, 29, pp. 1373-1379; Yoshioka, S.A., Goissis, G., Thermal and spectrophotometric studies of new crosslinking method for collagen matrix with glutaraldehyde acetals (2008) Journal of Materials Science: Materials in Medicine, 19 (3), pp. 1215-1223. , DOI 10.1007/s10856-007-0151-0; Wissink, M.J., Beernink, R., Pieper, J.S., Poot, A.A., Engbers, G.H., Beugeling, T., Van Aken, W.G., Feijen, J., Binding and release of basic fibroblast growth factor from heparinized collagen matrices (2001) Biomaterials, 22, pp. 2291-2299; Wissink, M.J., Beernink, R., Pieper, J.S., Poot, A.A., Engbers, G.H., Beugeling, T., Van Aken, W.G., Feijen, J., Immobilization of heparin to EDC/NHS-crosslinked collagen. Characterization and in vitro evaluation (2001) Biomaterials, 22, pp. 151-163; Wissink, M.J., Beernink, R., Poot, A.A., Engbers, G.H., Beugeling, T., Van Aken, W.G., Feijen, J., Improved endothelialization of vascular grafts by local release of growth factor from heparinized collagen matrices (2000) J Control Release, 64, pp. 103-114; Wissink, M.J., Beernink, R., Scharenborg, N.M., Poot, A.A., Engbers, G.H., Beugeling, T., Van Aken, W.G., Feijen, J., Endothelial cell seeding of (heparinized) collagen matrices: Effects of bFGF pre-loading on proliferation (after low density seeding) and pro-coagulant factors (2000) J Control Release, 67, pp. 141-155; Wissink, M.J.B., Van Luyn, M.J.A., Beernink, R., Dijk, F., Poot, A.A., Engbers, G.H.M., Beugeling, T., Feijen, J., Endothelial cell seeding on crosslinked collagen: Effects of crosslinking on endothelial cell proliferation and functional parameters (2000) Thrombosis and Haemostasis, 84 (2), pp. 325-331; Teixeira, S., Oliveirał, S., Ferrazł, M.P., Monteiro, F.J., Three dimensional macroporous calcium phosphate scaffolds for bone tissue engineering (2008) Key Eng Mater, 361-363, pp. 947-950; Teixeira, S., Rodriguez, M., Pena, P., De Aza, A., De Aza, S., Ferraz, M., Monteiro, F., Physical characterization of hydroxyapatite porous scaffolds for tissue engineering (2009) Mater Sci Eng: C, 29, pp. 1510-1514
Keywords: 1 (3 dimethylaminopropyl) 3 ethylcarbodiimide; adult; Animal cell culture; Apatite; article; Automobile exhibitions; Bone; bone marrow cell; Bone Marrow Cells; bone matrix; bone mineralization; Bone Regeneration; bone tissue; Bone tissue regeneration; Calcification, Physiologic; cell adhesion; Cell clusters; Cell culture; Cell distribution; Cell morphology; cell proliferation; cell structure; cell viability; Cells, Cultured; cellular distribution; Ceramic materials; chemistry; Coating procedures; Collagen; collagen type 1; Collagen type I; conjugation; controlled study; cross linking; cross linking reagent; Cross-Linking Reagents; Crosslinked; cytology; Cytotoxicity; DNA; DNA quantification; drug conjugation; Drug delivery; drug delivery system; Drug delivery vehicles; drug effect; Drug-delivery systems; Durapatite; Extracellular matrices; extracellular matrix; Functionalized; human; Human bone marrow cells; human cell; Humans; hydroxyapatite; in vitro study; In-vitro; Macroporous; Macroporous ceramics; male; matrix; metabolism; methylene blue; Methylene blue staining; Microscopy, Electron, Scanning; molecular scaffold; n hydroxysuccinimide; N-hydroxysuccinimide; polymer; Polymer replication; porosity; Porous scaffold; Scaffolds; Scanning electron microscopy; Sintering; Sintering cycles; spectrometry; Spectrometry, X-Ray Emission; Tissue engineering; tissue scaffold; Tissue Scaffolds; Type I collagen; Young Adult

Cancer cell angiogenic capability is regulated by 3D culture and integrin engagement - Fischbach, C.; Hyun, J.K.; Hsiong, S.X.; Evangelista, M.B.; Yuen, W.; Mooney, D.J. (Proceedings of the National Academy of Sciences of the United States of AmericaProc. Natl. Acad. Sci. U. S. A., 2009)
Three-dimensional culture alters cancer cell signaling; however, the underlying mechanisms and importance of these changes on tumor vascularization remain unclear. A hydrogel system was used to examine the role of the transition from 2D to 3D culture, with and without integrin engagement, on cancer cell angiogenic capability. Three-dimensional culture recreated tumor microenvironmental cues and led to enhanced interleukin 8 (IL-8) secretion that depended on integrin engagement with adhesion peptides coupled to the polymer. In contrast, vascular endothelial growth factor (VEGF) secretion was unaffected by 3D culture with or without substrate adhesion. IL-8 diffused greater distances and was present in higher concentrations in the systemic circulation, relative to VEGF. Implantation of a polymeric IL-8 delivery system into GFP bone marrow-transplanted mice revealed that localized IL-8 up-regulation was critical to both the local and systemic control of tumor vascularization in vivo. In summary, 3D integrin engagement within tumor microenvironments regulates cancer cell angiogenic signaling, and controlled local and systemic blockade of both IL-8 and VEGF signaling may improve antiangiogenic therapies. © 2009 by The National Academy of Sciences of the USA.
Cited By (since 1996): 48Export Date: 21 November 2012Source: ScopusCODEN: PNASAdoi: 10.1073/pnas.0808932106PubMed ID: 19126683Language of Original Document: EnglishCorrespondence Address: Mooney, D. J.; School of Engineering and Applied Sciences, Harvard University, 40 Oxford Street, Cambridge, MA 02138, United States; email: mooneyd@seas.harvard.eduChemicals/CAS: arginylglycylaspartic acid, 99896-85-2; interleukin 8, 114308-91-7; vasculotropin, 127464-60-2; Hydrogels; Integrins; Interleukin-8; Vascular Endothelial Growth Factor AReferences: Debnath, J., Brugge, J.S., Modelling glandular epithelial cancers in 3-dimensional cultures (2005) Nat Rev Cancer, 5, pp. 675-688;Wang, F., Reciprocal interactions between β1-integrin and epidermal growth factor receptor in 3-dimensional basement membrane breast cultures: A different perspective in epithelial biology (1998) Proc Natl Acad Sci USA, 95, pp. 14821-14826; Fischbach, C., Engineering tumors with 3D scaffolds (2007) Nat Methods, 4, pp. 855-860; Paszek, M.J., Tensional homeostasis and the malignant phenotype (2005) Cancer Cell, 8, pp. 241-254; Hanahan, D., Weinberg, R.A., The hallmarks of cancer (2000) Cell, 100, pp. 57-70; De, S., VEGF-integrin interplay controls tumor growth and vascularization (2005) Proc Natl Acad Sci USA, 102, pp. 7589-7594; Lowrie, A.G., Salter, D.M., Ross, J.A., Latent effects of fibronectin, α5β1 integrin, αvβ5 integrin, and the cytoskeleton regulate pancreatic carcinoma cell IL-8 secretion (2004) Br J Cancer, 91, pp. 1327-1334; Cukierman, E., Pankov, R., Stevens, D.R., Yamada, K.M., Taking cell matrix adhesions to the third dimension (2001) Science, 294, pp. 1708-1712; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20, pp. 45-53; Lingen, M.W., Angiogenesis in the development of head and neck cancer and its inhibition by chemopreventive agents (1999) Crit Rev Oral Biol Med, 10, pp. 153-164; Fischbach, C., Mooney, D., Polymeric systems for bioinspired delivery of angiogenic molecules (2006) Adv Polym Sci, 203, pp. 191-221; Ruoslahti, E., Pierschbacher, M.D., New perspectives in cell adhesion: RGD and integrins (1987) Science, 238, pp. 491-497; Kong, H.J., Boontheekul, T., Mooney, D.J., Quantifying the relation between adhesion ligand-receptor bond formation and cell phenotype (2006) Proc Natl Acad Sci USA, 103, pp. 18534-18539; Harris, A.L., Hypoxia: A key regulatory factor in tumour growth (2002) Nat Rev Cancer, 2, pp. 38-47; Xu, L., Hypoxia-induced elevation in interleukin-8 expression by human ovarian carcinoma cells (1999) Cancer Res, 59, pp. 5822-5829; Weaver, V.M., Reversion of the malignant phenotype of human breast cells in three-dimensional cultureandin vivo by integrin-blocking antibodies (1997) J Cell Biol, 137, pp. 231-245; Chung, J., Hypoxia-induced vascular endothelial growth factor transcription and protection from apoptosis are dependent on α6β1 integrin in breast carcinoma cells (2004) Cancer Res, 64, pp. 4711-4716; Ghosh, S., Three-dimensional culture of melanoma cells profoundly affects gene expression profile: A high density oligonucleotide array study (2005) J Cell Physiol, 204, pp. 522-531; De Larco, J.E., A potential role for interleukin-8 in the metastatic phenotype of breast carcinoma cells (2001) Am J Pathol, 158, pp. 639-646; Nemeth, Z.H., Disruption of the actin cytoskeleton results in nuclear factor-κB activation and inflammatory mediator production in cultured human intestinal epithelial cells (2004) J Cell Physiol, 200, pp. 71-81; Xie, K., Interleukin-8 and human cancer biology (2001) Cytokine Growth Factor Rev, 12, pp. 375-391; Casanovas, O., Hicklin, D.J., Bergers, G., Hanahan, D., Drug resistance by evasion of antiangiogenic targeting of VEGF signaling in late-stage pancreatic islet tumors (2005) Cancer Cell, 8, pp. 299-309; Mizukami, Y., Induction of interleukin-8 preserves the angiogenic response in HIF-1α-deficient colon cancer cells (2005) Nat Med, 11, pp. 992-997; Esposito, I., Inflammatory cells contribute to the generation of an angiogenic phenotype in pancreatic ductal adenocarcinoma (2004) J Clin Pathol, 57, pp. 630-636; Ferrara, N., Henzel, W.J., Pituitary follicular cells secrete a novel heparin-binding growth factor specific for vascular endothelial cells (1989) Biochem Biophys Res Commun, 161, pp. 851-858; Gaertner, H.F., Offord, R.E., Site-specific attachment of functionalized poly(ethylene glycol) to the amino terminus of proteins (1996) Bioconjug Chem, 7, pp. 38-44; Goerges, A.L., Nugent, M.A., Regulation of vascular endothelial growth factor binding and activity by extracellular pH (2003) J Biol Chem, 278, pp. 19518-19525; Kuschert, G.S., Identification of a glycosaminoglycan binding surface on human interleukin-8 (1998) Biochemistry, 37, pp. 11193-11201; Kerbel, R., Folkman, J., Clinical translation of angiogenesis inhibitors (2002) Nat Rev Cancer, 2, pp. 727-739; Fischbach, C., Mooney, D.J., Polymers for pro- and antiangiogenic therapy (2007) Biomaterials, 28, pp. 2069-2076; Alsberg, E., Engineering growing tissues (2002) Proc Natl Acad Sci USA, 99, pp. 12025-12030; Simmons, C.A., Dual growth factor delivery and controlled scaffold degradation enhance in vivo bone formation by transplanted bone marrow stromal cells (2004) Bone, 35, pp. 562-569; Comisar, W.A., Kazmers, N.H., Mooney, D.J., Linderman, J.J., Engineering RGD nanopatterned hydrogels to control preosteoblast behavior: A combined computational and experimental approach (2007) Biomaterials, 28, pp. 4409-4417; Alsberg, E., Regulating bone formation via controlled scaffold degradation (2003) J Dent Res, 82, pp. 903-908; Richardson, T.P., Peters, M.C., Ennett, A.B., Mooney, D.J., Polymeric system for dual growth factor delivery (2001) Nat Biotechnol, 19, pp. 1029-1034
Keywords: animal experiment; animal model; Animals; arginylglycylaspartic acid; article; bone marrow transplantation; cancer cell; cancer cell culture; Cell Culture Techniques; concentration (parameters); controlled study; cytokine release; Diffusion; Drug delivery; ECM; Humans; hydrogel; Hydrogels; IL-8; implantation; in vivo study; integrin; Integrins; interleukin 8; Interleukin-8; Mice; microenvironment; Models, Biological; mouse; Mus; Neoplasms; Neovascularization, Pathologic; nonhuman; polymer; priority journal; signal transduction; systemic circulation; Tumor vascularization; upregulation; Vascular Endothelial Growth Factor A; vasculotropin

Cancer invasion and metastasis: Interacting ecosystems - Mareel, M.; Oliveira, M.J.; Madani, I. (Virchows ArchivVirchows Arch., 2009)
Malignant tumors invade and metastasize. They consist of cancer cells, evolving through genetic and epigenetic modulation, mixed with tumor-associated host cells, emerging from resident or bone marrow-derived precursors. These cells establish ecosystems to activate cellular programs for local invasion and distant metastasis. Characteristic of such malignancy-related activities is communication inside ecosystems between cells, ligands, receptor protein complexes, and signaling pathways as well as between ecosystems comprising the primary tumor, lymph node and distant metastasis, bone marrow and blood and lymph circulation. Complexity is another characteristic, resulting from: heterogeneity of the cell populations; the numbers of promoter and suppressor genes, their levels of regulation, and the pleiotropic activities of their products; biological redundancy of the molecular mechanisms underpinning invasion-related activities. Clinical attention is paid to putative new targets, namely host cells, individual molecules and their signaling pathways, as well as the effects of current treatment on invasion and metastasis. © 2009 Springer-Verlag.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: VARCEdoi: 10.1007/s00428-009-0784-0PubMed ID: 19471961Language of Original Document: EnglishCorrespondence Address: Madani, I.; Department of Radiotherapy, Ghent University Hospital, De Pintelaan 185, 9000 Ghent, Belgium; email: indira.madani@ugent.beReferences: Tarin, D., New insights into the pathogenesis of breast cancer metastasis (2006) Breast Disease, 26 (1), pp. 13-25;Stafford, L.J., Vaidya, K.S., Welch, D.R., Metastasis suppressors genes in cancer (2008) Int J Biochem Cell Biol, 40, pp. 874-891; Oliveira, M.J., (2004) The Effect of Bacteria on Colon Cancer Cell Invasion: Molecular Mechanisms Associated, , Faculty of Medicine and Health Sciences. Ghent University. PhD thesis; Madani, I., De Neve, W., Mareel, M., Does ionizing radiation stimulate cancer invasion and metastasis? (2008) Bull Cancer, 95, pp. 292-300; De Wever, O., Mareel, M., Role of tissue stroma in cancer cell invasion (2003) Journal of Pathology, 200 (4), pp. 429-447. , DOI 10.1002/path.1398; Bracke, M.E., Vanhoecke, B.W.A., Derycke, L., Bolca, S., Possemiers, S., Heyerick, A., Stevens, C.V., Parmar, V.S., Plant polyphenolics as anti-invasive cancer agents (2008) Anti-Cancer Agents in Medicinal Chemistry, 8 (2), pp. 171-185. , http://www.ingentaconnect.com/content/ben/acamc/2008/00000008/00000002/ art00004, DOI 10.2174/187152008783497037; Ottewell, P.D., Coleman, R.E., Holen, I., From genetic abnormality to metastases: Murine models of breast cancer and their use in the development of anticancer therapies (2006) Breast Cancer Res Treat, 96, pp. 101-113; Langley, R.R., Fidler, I.J., Tumor cell-organ microenvironment interactions in the pathogenesis of cancer metastasis (2007) Endocrine Reviews, 28 (3), pp. 297-321. , http://edrv.endojournals.org/cgi/reprint/28/3/297.pdf, DOI 10.1210/er.2006-0027; Kuperwasser, C., Chavarria, T., Wu, M., Magrane, G., Gray, J.W., Carey, L., Richardson, A., Weinberg, R.A., Reconstruction of functionally normal and malignant human breast tissues in mice (2004) Proceedings of the National Academy of Sciences of the United States of America, 101 (14), pp. 4966-4971. , DOI 10.1073/pnas.0401064101; Hoffman, R.M., Real-time subcellular imaging in live animals: New visible targets for cancer drug discovery (2006) IDrugs, 9 (9), pp. 632-635; Fomchenko, E.I., Holland, E.C., Mouse models of brain tumors and their applications in preclinical trials (2006) Clinical Cancer Research, 12 (18), pp. 5288-5297. , DOI 10.1158/1078-0432.CCR-06-0438; Gingrich, J.R., Barrios, R.J., Morton, R.A., Boyce, B.F., DeMayo, F.J., Finegold, M.J., Angelopoulou, R., Greenberg, N.M., Metastatic prostate cancer in a transgenic mouse (1996) Cancer Research, 56 (18), pp. 4096-4102; Peri, A.-K., Wilgenbus, P., Dahl, U., Semb, H., Christofori, G., A causal role for E-cadherin in the transition from adenoma to carcinoma (1998) Nature, 392 (6672), pp. 190-193. , DOI 10.1038/32433; Ambartsumian, N., Grigorian, M., Lukanidin, E., Genetically modified mouse models to study the role of metastasis-promoting S100A4(mts1) protein in metastatic mammary cancer (2005) Journal of Dairy Research, 72 (SPEC. ISS.), pp. 27-33. , DOI 10.1017/S0022029905001093; Scherer, R.L., McIntyre, J.O., Matrisian, L.M., Imaging matrix metalloproteinases in cancer (2008) Cancer Metastasis Rev, 27, pp. 679-690; Espina, V., Heiby, M., Pierobon, M., Liotta, L.A., Laser capture microdissection technology (2007) Expert Review of Molecular Diagnostics, 7 (5), pp. 647-657. , http://www.future-drugs.com/doi/pdf/10.1586/14737159.7.5.647, DOI 10.1586/14737159.7.5.647; Eccles, S.A., Welch, D.R., Metastasis: recent discoveries and novel treatment strategies (2007) Lancet, 369 (9574), pp. 1742-1757. , DOI 10.1016/S0140-6736(07)60781-8, PII S0140673607607818; Brenton, J.D., Carey, L.A., Ahmed, A., Caldas, C., Molecular classification and molecular forecasting of breast cancer: Ready for clinical application? (2005) Journal of Clinical Oncology, 23 (29), pp. 7350-7360. , DOI 10.1200/JCO.2005.03.3845; Montel, V., Huang, T.-Y., Mose, E., Pestonjamasp, K., Tarin, D., Expression profiling of primary tumors and matched lymphatic and lung metastases in a xenogeneic breast cancer model (2005) American Journal of Pathology, 166 (5), pp. 1565-1579; Karpf, A.R., Jones, D.A., Reactivating the expression of methylation silenced genes in human cancer (2002) Oncogene, 21 (35 REV. ISS. 3), pp. 5496-5503. , DOI 10.1038/sj.onc.1205602; Feng, Y., Sun, B., Li, X., Zhang, L., Niu, Y., Xiao, C., Ning, L., Hao, X., Differentially expressed genes between primary cancer and paired lymph node metastases predict clinical outcome of node-positive breast cancer patients (2007) Breast Cancer Research and Treatment, 103 (3), pp. 319-329. , DOI 10.1007/s10549-006-9385-7; Van't Veer, L.J., Dai, H., Van De Vijver, M.J., He, Y.D., Hart, A.A.M., Mao, M., Peterse, H.L., Friend, S.H., Gene expression profiling predicts clinical outcome of breast cancer (2002) Nature, 415 (6871), pp. 530-536. , DOI 10.1038/415530a; Wang, W., Klijn, J.G., Zhang, Y., Gene-expression profiles to predict distant metastasis of lymph-node-negative primary breast cancer (2005) Lancet, 415, pp. 530-536; Eckhardt, B.L., Parker, B.S., Van Laar, R.K., Restall, C.M., Natoli, A.L., Tavaria, M.D., Stanley, K.L., Anderson, R.L., Genomic analysis of a spontaneous model of breast cancer metastasis to bone reveals a role for the extracellular matrix (2005) Molecular Cancer Research, 3 (1), pp. 1-13; Adib, T.R., Henderson, S., Perrett, C., Hewitt, D., Bourmpoulia, D., Ledermann, J., Boshoff, C., Predicting biomarkers for ovarian cancer using gene-expression microarrays (2004) British Journal of Cancer, 90 (3), pp. 686-692. , DOI 10.1038/sj.bjc.6601603; Suzuki, M., Tarin, D., Gene expression profiling of human lymph node metastases and matched primary breast carcinomas: Clinical implications (2007) Molecular Oncology, 1 (2), pp. 172-180. , DOI 10.1016/j.molonc.2007.03.005, PII S1574789107000154; Chang, H.Y., Nuyten, D.S.A., Sneddon, J.B., Hastie, T., Tibshirani, R., Sorlie, T., Dai, H., Van De Vijver, M.J., Robustness, scalability, and integration of a wound-response gene expression signature in predicting breast cancer survival (2005) Proceedings of the National Academy of Sciences of the United States of America, 102 (10), pp. 3738-3743. , DOI 10.1073/pnas.0409462102; Finak, G., Bertos, N., Pepin, F., Sadekova, S., Souleimanova, M., Zhao, H., Chen, H., Park, M., Stromal gene expression predicts clinical outcome in breast cancer (2008) Nature Medicine, 14 (5), pp. 518-527. , DOI 10.1038/nm1764, PII NM1764; Clark, I.M., Swingler, T.E., Sampieri, C.L., The regulation of matrix metalloproteinases and their inhibitors (2008) Int J Biochem Cell Biol, 40, pp. 1362-1378; Li, Y., Liang, J., Kang, S., Dong, Z., Wang, N., Xing, H., Zhou, R., Zhao, X., E-cadherin gene polymorphisms and haplotype associated with the occurrence of epithelial ovarian cancer in Chinese (2008) Gynecologic Oncology, 108 (2), pp. 409-414. , DOI 10.1016/j.ygyno.2007.10.024, PII S0090825807008517; Brendle, A., Lei, H., Brandt, A., Polymorphisms in predicted microRNA-binding sites in integrin genes and breast cancer: ITGB4 as prognostic marker (2008) Carcinogenesis, 29, pp. 1394-1399; Hunter, K.W., Crawford, N.P., Germ line polymorphism in metastatic progression (2006) Cancer Research, 66 (3), pp. 1251-1254. , DOI 10.1158/0008-5472.CAN-05-3705; Crawford, N.P., Ziogas, A., Peel, D.J., Germline polymorphisms in SIPA1 are associated with metastasis and other indicators of poor prognosis in breast cancer (2006) Breast Cancer Res, 8, p. 16; Van Roy, F., Berx, G., The cell-cell adhesion molecule E-cadherin (2008) Cell Mol Life Sci, 65, pp. 3756-3788; Bartel, D.P., Chen, C.-Z., Micromanagers of gene expression: The potentially widespread influence of metazoan microRNAs (2004) Nature Reviews Genetics, 5 (5), pp. 396-400; Ma, L., Weinberg, R.A., Micromanagers of malignancy: Role of microRNAs in regulating metastasis (2008) Trends Genet, 24, pp. 448-456; Graff, J.R., Zimmer, S.G., Translational control and metastatic progression: Enhanced activity of the mRNA cap-binding protein eIF-4E selectively enhances translation of metastasis-related mRNAs (2003) Clinical and Experimental Metastasis, 20 (3), pp. 265-273. , DOI 10.1023/A:1022943419011; Hao, X., Sun, B., Hu, L., Lahdesmaki, H., Dunmire, V., Feng, Y., Zhang, S.-W., Zhang, W., Differential Gene and Protein Expression in Primary Breast Malignancies and Their Lymph Node Metastases as Revealed by Combined cDNA Microarray and Tissue Microarray Analysis (2004) Cancer, 100 (6), pp. 1110-1122. , DOI 10.1002/cncr.20095; Hakomori, S.-I., Tumor malignancy defined by aberrant glycosylation and sphingo(glyco)lipid metabolism (1996) Cancer Research, 56 (23), pp. 5309-5318; Yoshimura, M., Ihara, Y., Matsuzawa, Y., Taniguchi, N., Aberrant glycosylation of E-cadherin enhances cell-cell binding to suppress metastasis (1996) Journal of Biological Chemistry, 271 (23), pp. 13811-13815. , DOI 10.1074/jbc.271.23.13811; McLachlan, R.W., Yap, A.S., Not so simple: The complexity of phosphotyrosine signaling at cadherin adhesive contacts (2007) Journal of Molecular Medicine, 85 (6), pp. 545-554. , DOI 10.1007/s00109-007-0198-x, Special Topic: Tumor Cell Invasion and Metastasis; Wipff, P.J., Hinz, B., Integrins and the activation of latent transforming growth factor beta1-an intimate relationship (2008) Eur J Cell Biol, 87, pp. 601-615; Paredes, J., Correia, A.L., Ribeiro, A.S., P-cadherin expression in breast cancer: A review (2007) Breast Cancer Res, 9, p. 214; Van Marck, V., Stove, C., Van Den Bossche, K., Stove, V., Paredes, J., Vander Haeghen, Y., Bracke, M., P-cadherin promotes cell-cell adhesion and counteracts invasion in human melanoma (2005) Cancer Research, 65 (19), pp. 8774-8783. , DOI 10.1158/0008-5472.CAN-04-4414; Wheelock, M.J., Shintani, Y., Maeda, M., Fukumoto, Y., Johnson, K.R., Cadherin switching (2008) Journal of Cell Science, 121 (6), pp. 727-735. , DOI 10.1242/jcs.000455; De Wever, O., Westbroek, W., Verloes, A., Bloemen, N., Bracke, M., Gespach, C., Bruyneel, E., Mareel, M., Critical role of N-cadherin in myofibroblast invasion and migration in vitro stimulated by colon-cancer-cell-derived TGF-β or wounding (2004) Journal of Cell Science, 117 (20), pp. 4691-4703. , DOI 10.1242/jcs.01322; Alexander, N.R., Tran, N.L., Rekapally, H., N-cadherin gene expression in prostate carcinoma is modulated by integrin-dependent nuclear translocation of Twist1 (2006) Cancer Res, 66, pp. 3365-3369; Stove, C., Bracke, M., Roles for neuregulins in human cancer (2005) Clinical and Experimental Metastasis, 21 (8), pp. 665-684. , DOI 10.1007/s10585-004-6917-6; Kerbel, R.S., Tumor angiogenesis (2008) New England Journal of Medicine, 358 (19), pp. 2039-2049. , http://content.nejm.org/cgi/reprint/358/19/2039.pdf, DOI 10.1056/NEJMra0706596; Chabottaux, V., Noel, A., Breast cancer progression: Insights into multifaceted matrix metalloproteinases (2007) Clinical and Experimental Metastasis, 24 (8), pp. 647-656. , DOI 10.1007/s10585-007-9113-7; Noel, A., Jost, M., Maquoi, E., Matrix metalloproteinases at cancer tumor-host interface (2008) Seminars in Cell and Developmental Biology, 19 (1), pp. 52-60. , DOI 10.1016/j.semcdb.2007.05.011, PII S1084952107000821, Matrix Metalloproteinases; Jones, R.B., Gordus, A., Krall, J.A., MacBeath, G., A quantitative protein interaction network for the ErbB receptors using protein microarrays (2006) Nature, 439 (7073), pp. 168-174. , DOI 10.1038/nature04177, PII NATURE04177; Pawson, T., Nash, P., Assembly of cell regulatory systems through protein interaction domains (2003) Science, 300 (5618), pp. 445-452. , DOI 10.1126/science.1083653; Kopfstein, L., Christofori, G., Metastasis: Cell-autonomous mechanisms versus contributions by the tumor microenvironment (2006) Cell Mol Life Sci, 63, pp. 449-468; Paget, S., The distribution of secondary growths in cancer of the breast (1889) Lancet, 1, pp. 571-573; Mareel, M.M., Behrens, J., Birchmeier, W., Down-regulation of E-cadherin expression in Madin Darby canine kidney (MDCK) cells inside tumors of nude mice (1991) Int J Cancer, 47, pp. 922-928; Creighton, C.J., Bromberg-White, J.L., Misek, D.E., Monsma, D.J., Brichory, F., Kuick, R., Giordano, T.J., Hanash, S.M., Analysis of tumor-host interactions by gene expression profiling of lung adenocarcinoma xenografts identifies genes involved in tumor formation (2005) Molecular Cancer Research, 3 (3), pp. 119-129. , DOI 10.1158/1541-7786.MCR-04-0189; Dimanche-Boitrel, M.T., Vakaet Jr., L., Pujuguet, P., Chauffert, B., Martin, M.S., Hammann, A., Van Roy, F., Martin, F., In vivo and in vitro invasiveness of a rat colon-cancer cell line maintaining E-cadherin expression: An enhancing role of tumor-associated myofibroblasts (1994) International Journal of Cancer, 56 (4), pp. 512-521; Lin, E.Y., Pollard, J.W., Tumor-associated macrophages press the angiogenic switch in breast cancer (2007) Cancer Research, 67 (11), pp. 5064-5066. , http://cancerres.aacrjournals.org/cgi/reprint/67/11/5064, DOI 10.1158/0008-5472.CAN-07-0912; Korc, M., Pancreatic cancer-associated stroma production (2007) Am J sur, 194 (4 SUPPL.), pp. 84-S86; He, Y., Rajantie, I., Pajusola, K., Jeltsch, M., Holopainen, T., Yla-Herttuala, S., Harding, T., Alitalo, K., Vascular endothelial cell growth factor receptor 3-mediated activation of lymphatic endothelium is crucial for tumor cell entry and spread via lymphatic vessels (2005) Cancer Research, 65 (11), pp. 4739-4746. , DOI 10.1158/0008-5472.CAN-04-4576; Mahabeleshwar, G.H., Byzova, T.V., Angiogenesis in Melanoma (2007) Seminars in Oncology, 34 (6), pp. 555-565. , DOI 10.1053/j.seminoncol.2007.09.009, PII S0093775407001832, Malignant Melanoma; Benoy, I.H., Salgado, R., Elst, H., Relative microvessel area of the primary tumour, and not lymph node status, predicts the presence of bone marrow micrometastases detected by reverse transcriptase polymerase chain reaction in patients with clinically non-metastatic breast cancer (2005) Breast Cancer Res, 7, pp. 210-R219; Hicklin, D.J., Ellis, L.M., Role of the vascular endothelial growth factor pathway in tumor growth and angiogenesis (2005) Journal of Clinical Oncology, 23 (5), pp. 1011-1027. , DOI 10.1200/JCO.2005.06.081; Schoppmann, S.F., Bayer, G., Aumayr, K., Taucher, S., Geleff, S., Rudas, M., Kubista, E., Horvat, R., Prognostic value of lymphangiogenesis and lymphovascular invasion in invasive breast cancer (2004) Annals of Surgery, 240 (2), pp. 306-312. , DOI 10.1097/01.sla.0000133355.48672.22; Tobler, N.E., Detmar, M., Tumor and lymph node lymphangiogenesis - Impact on cancer metastasis (2006) Journal of Leukocyte Biology, 80 (4), pp. 691-696. , http://www.jleukbio.org/cgi/reprint/80/4/691, DOI 10.1189/jlb.1105653; Nathanson, S.D., Leong, S., Preclinical models of regional lymph node tumor metastasis (2007) Cancer Metastasis and the Lymphvascular System: Basis for Rational Therapy, pp. 129-156. , Springer New York; Wissmann, C., Detmar, M., Pathways targeting tumor lymphangiogenesis (2006) Clinical Cancer Research, 12 (23), pp. 6865-6868. , DOI 10.1158/1078-0432.CCR-06-1800; Rafii, D.C., Psaila, B., Butler, J., Jin, D.K., Lyden, D., Regulation of vasculogenesis by platelet-mediated recruitment of bone marrow-derived cells (2008) Arteriosclerosis, Thrombosis, and Vascular Biology, 28 (2), pp. 217-222. , DOI 10.1161/ATVBAHA.107.151159, PII 0004360520080200000004; Mantovani, A., Sica, A., Sozzani, S., Allavena, P., Vecchi, A., Locati, M., The chemokine system in diverse forms of macrophage activation and polarization (2004) Trends in Immunology, 25 (12), pp. 677-686. , DOI 10.1016/j.it.2004.09.015, PII S1471490604002959; Mantovani, A., Romero, P., Palucka, A.K., Tumour immunity: Effector response to tumour and role of the microenvironment (2008) Lancet, 371, pp. 771-783; Talmadge, J.E., Donkor, M., Scholar, E., Inflammatory cell infiltration of tumors: Jekyll or Hyde (2007) Cancer and Metastasis Reviews, 26 (3-4), pp. 373-400. , DOI 10.1007/s10555-007-9072-0, Forty Years of Metastasis Research: A Tribute to Dr. Isaiah J. Fidler; Lewis, C.E., Pollard, J.W., Distinct role of macrophages in different tumor microenvironments (2006) Cancer Research, 66 (2), pp. 605-612. , DOI 10.1158/0008-5472.CAN-05-4005; Condeelis, J., Pollard, J.W., Macrophages: Obligate partners for tumor cell migration, invasion, and metastasis (2006) Cell, 124 (2), pp. 263-266. , DOI 10.1016/j.cell.2006.01.007, PII S0092867406000559; Wyckoff, J.B., Wang, Y., Lin, E.Y., Li, J.-F., Goswami, S., Stanley, E.R., Segall, J.E., Condeelis, J., Direct visualization of macrophage-assisted tumor cell intravasation in mammary tumors (2007) Cancer Research, 67 (6), pp. 2649-2656. , DOI 10.1158/0008-5472.CAN-06-1823; Mahadevan, D., Von Hoff, D.D., Tumor-stroma interactions in pancreatic ductal adenocarcinoma (2007) Molecular Cancer Therapeutics, 6 (4), pp. 1186-1197. , DOI 10.1158/1535-7163.MCT-06-0686; De Wever, O., Demetter, P., Mareel, M., Stromal myofibroblasts are drivers of invasive cancer growth (2008) Int J Cancer, 123, pp. 2229-2238; Massaguè, J., TGFbeta in cancer (2008) Cell, 134, pp. 215-230; Hu, M., Yao, J., Carroll, D.K., Weremowicz, S., Chen, H., Carrasco, D., Richardson, A., Polyak, K., Regulation of In Situ to Invasive Breast Carcinoma Transition (2008) Cancer Cell, 13 (5), pp. 394-406. , DOI 10.1016/j.ccr.2008.03.007, PII S1535610808000913; Lerwill, M.F., Current practical applications of diagnostic immunohistochemistry in breast pathology (2004) American Journal of Surgical Pathology, 28 (8), pp. 1076-1091. , DOI 10.1097/01.pas.0000126780.10029.f0; Allinen, M., Beroukhim, R., Cai, L., Brennan, C., Lahti-Domenici, J., Huang, H., Porter, D., Polyak, K., Molecular characterization of the tumor microenvironment in breast cancer (2004) Cancer Cell, 6 (1), pp. 17-32. , DOI 10.1016/j.ccr.2004.06.010, PII S1535610804001783; Hu, M., Yao, J., Cai, L., Bachman, K.E., Van Den Brule, F., Velculescu, V., Polyak, K., Distinct epigenetic changes in the stromal cells of breast cancers (2005) Nature Genetics, 37 (8), pp. 899-905. , DOI 10.1038/ng1596; Barsky, S.H., Karlin, N.J., Myoepithelial cells: Autocrine and paracrine suppressors of breast cancer progression (2005) J Mammary Gland Biol Neoplasia, 10, pp. 249-260; Polyak, K., Hu, M., Do myoepithelial cells hold the key for breast tumor progression? (2005) J Mammary Gland Biol Neoplasia, 10, pp. 231-247; Mantyh, P.W., Clohisy, D.R., Koltzenburg, M., Hunt, S.P., Molecular mechanisms of cancer pain (2002) Nature Reviews Cancer, 2 (3), pp. 201-209; Ayala, G.E., Dai, H., Powell, M., Cancer-related axonogenesis and neurogenesis in prostate cancer (2008) Clin Cancer Res, 14, pp. 7593-7603; Wang, W., Zhao, H., Zhang, S., Al, E., Patterns of expression and function of the p75(NGFR) protein in pancreatic cancer cells and tumours (2008) Eur J Surg Oncol, , Nov 26 (in press); Marchesi, F., Piemonti, L., Fedele, G., The chemokine receptor CX3CR1 is involved in the neural tropism and malignant behavior of pancreatic ductal adenocarcinoma (2008) Cancer Res, 68, pp. 9060-9069; Zhang, S., Qi, L., Li, M., Chemokine CXCL12 and its receptor CXCR4 expression are associated with perineural invasion of prostate cancer (2008) J Exp Clin Cancer Res, 27, p. 62; Andarawewa, K.L., Motrescu, E.R., Chenard, M.-P., Gansmuller, A., Stoll, I., Tomasetto, C., Rio, M.-C., Stromelysin-3 is a potent negative regulator of adipogenesis participating to cancer cell-adipocyte interaction/crosstalk at the tumor invasive front (2005) Cancer Research, 65 (23), pp. 10862-10871. , DOI 10.1158/0008-5472.CAN-05-1231; Caers, J., Van Valckenborgh, E., Menu, E., Unraveling the biology of multiple myeloma disease: Cancer stem cells, acquired intracellular changes and interactions with the surrounding micro-environment (2008) Bull Cancer, 95, pp. 301-313; Vona-Davis, L., Rose, D.P., Adipokines as endocrine, paracrine, and autocrine factors in breast cancer risk and progression (2007) Endocrine-Related Cancer, 14 (2), pp. 189-206. , DOI 10.1677/ERC-06-0068; Kunduzova, O., Alet, N., Delesque-Touchard, N., Apelin/APJ signaling system: A potential link between adipose tissue and endothelial angiogenic processes (2008) FASEB J, 22, pp. 4146-4153; Cirillo, D., Rachiglio, A.M., La Montagna, R., Leptin signaling in breast cancer: An overview (2008) J Cell Biochem, 105, pp. 956-964; Jaffe, T., Schwartz, B., Leptin promotes motility and invasiveness in human colon cancer cells by activating multiple signal-transduction pathways (2008) Int J Cancer, 123, pp. 2543-2556; Horiguchi, A., Sumitomo, M., Asakuma, J., Asano, T., Zheng, R., Asano, T., Nanus, D.M., Hayakawa, M., Leptin Promotes Invasiveness of Murine Renal Cancer Cells Via Extracellular Signal-Regulated Kinases and Rho Dependent Pathway (2006) Journal of Urology, 176 (4), pp. 1636-1641. , DOI 10.1016/j.juro.2006.06.040, PII S0022534706014169; Bussard, K.M., Gay, C.V., Mastro, A.M., The bone microenvironment in metastasis; What is special about bone? (2008) Cancer Metastasis Rev, 27, pp. 41-55; Vakaet, L.A.M.-L., Boterberg, T., Pain control by ionizing radiation of bone metastasis (2004) International Journal of Developmental Biology, 48 (5-6), pp. 599-606. , DOI 10.1387/ijdb.041817lv, Invasion in Cancer and Embryonic Development; Oliveira, M.J., Van Damme, J., Lauwaet, T., De Corte, V., De Bruyne, G., Verschraegen, G., Vaneechoutte, M., Leroy, A., β-casein-derived peptides, produced by bacteria, stimulate cancer cell invasion and motility (2003) EMBO Journal, 22 (22), pp. 6161-6173. , DOI 10.1093/emboj/cdg586; Oliveira, M.J., Costa, A.C., Costa, A.M., Henriques, L., Suriano, G., Atherton, J.C., Machado, J.C., Figueiredo, C., Helicobacter pylori induces gastric epithelial cell invasion in a c-Met and type IV secretion system-dependent manner (2006) Journal of Biological Chemistry, 281 (46), pp. 34888-34896. , http://www.jbc.org/cgi/reprint/281/46/34888, DOI 10.1074/jbc.M607067200; Oliveira, M.J., Costa, A.M., Costa, A.C., Al, E., CagA associates with c-Met, E-cadherin, and p120-catenin in a multiproteic complex that suppresses Helicobacter pylori-induced cell invasive phenotype (2009) J Infect Dis, , in press; Miller, M.J., Wei, S.H., Parker, I., Cahalan, M.D., Two-photon imaging of lymphocyte motility and antigen response in intact lymph node (2002) Science, 296 (5574), pp. 1869-1873. , DOI 10.1126/science.1070051; Mullen, J.T., Wang, H., Yao, J.C., Carcinoid tumors of the duodenum (2005) Surgery, 138, pp. 971-977; Hoon, D.S.B., Kitago, M., Kim, J., Mori, T., Piris, A., Szyfelbein, K., Mihm Jr., M.C., Pantel, K., Molecular mechanisms of metastasis (2006) Cancer and Metastasis Reviews, 25 (2), pp. 203-220. , DOI 10.1007/s10555-006-8500-x; Muller, A., Homey, B., Soto, H., Ge, N., Catron, D., Buchanan, M.E., McClanahan, T., Zlotnik, A., Involvement of chemokine receptors in breast cancer metastasis (2001) Nature, 410 (6824), pp. 50-56. , DOI 10.1038/35065016; Hirakawa, S., Brown, L.F., Kodama, S., Paavonen, K., Alitalo, K., Detmar, M., VEGF-C-induced lymphangiogenesis in sentinel lymph nodes promotes tumor metastasis to distant sites (2007) Blood, 109 (3), pp. 1010-1017. , http://www.bloodjournal.org/cgi/reprint/109/3/1010, DOI 10.1182/blood-2006-05-021758; Van Den Eynden, G.G., Vandenberghe, M.K., Van Dam, P.-J.H., Colpaert, C.G., Van Dam, P., Dirix, L.Y., Vermeulen, P.B., Van Marck, E.A., Increased sentinel lymph node lymphangiogenesis is associated with nonsentinel axillary lymph node involvement in breast cancer patients with a positive sentinel node (2007) Clinical Cancer Research, 13 (18), pp. 5391-5397. , http://clincancerres.aacrjournals.org/cgi/reprint/13/18/5391, DOI 10.1158/1078-0432.CCR-07-1230; Dimeo, T.A., Kuperwasser, C., The evolving paradigm of tissue-specific metastasis (2006) Breast Cancer Res, 8, p. 301; Andre, F., Cabioglu, N., Assi, H., Sabourin, J.C., Delaloge, S., Sahin, A., Broglio, K., Cristofanilli, M., Expression of chemokine receptors predicts the site of metastatic relapse in patients with axillary node positive primary breast cancer (2006) Annals of Oncology, 17 (6), pp. 945-951. , DOI 10.1093/annonc/mdl053; Stessels, F., Van Den Eynden, G., Van Der Auwera, I., Salgado, R., Van Den Heuvel, E., Harris, A.L., Jackson, D.G., Vermeulen, P.B., Breast adenocarcinoma liver metastases, in contrast to colorectal cancer liver metastases, display a non-angiogenic growth pattern that preserves the stroma and lacks hypoxia (2004) British Journal of Cancer, 90 (7), pp. 1429-1436. , DOI 10.1038/sj.bjc.6601727; Mendes, O., Kim, H.-T., Lungu, G., Stoica, G., MMP2 role in breast cancer brain metastasis development and its regulation by TIMP2 and ERK1/2 (2007) Clinical and Experimental Metastasis, 24 (5), pp. 341-351. , DOI 10.1007/s10585-007-9071-0; Kaplan, R.N., Psaila, B., Lyden, D., Bone marrow cells in the 'pre-metastatic niche': Within bone and beyond (2006) Cancer and Metastasis Reviews, 25 (4), pp. 521-529. , DOI 10.1007/s10555-006-9036-9, Special issue on Bone Metastasis and Cancer; Hiratsuka, S., Watanabe, A., Aburatani, H., Maru, Y., Tumour-mediated upregulation of chemoattractants and recruitment of myeloid cells predetermines lung metastasis (2006) Nature Cell Biology, 8 (12), pp. 1369-1375. , DOI 10.1038/ncb1507, PII NCB1507; Kaplan, R.N., Psaila, B., Lyden, D., Niche-to-niche migration of bone-marrow-derived cells (2007) Trends in Molecular Medicine, 13 (2), pp. 72-81. , DOI 10.1016/j.molmed.2006.12.003, PII S1471491406002681; Pantel, K., Brakenhoff, R.H., Dissecting the metastatic cascade (2004) Nature Reviews Cancer, 4 (6), pp. 448-456; Vincent-Salomon, A., Bidard, F.C., Pierga, J.Y., Bone marrow micrometastasis in breast cancer: Review of detection methods, prognostic impact and biological issues (2008) Journal of Clinical Pathology, 61 (5), pp. 570-576. , DOI 10.1136/jcp.2007.046649; Bidard, F.C., Vincent-Salomon, A., Gomme, S., Disseminated tumor cells of breast cancer patients: A strong prognostic factor for distant and local relapse (2008) Clin Cancer Res, 14, pp. 3306-3311. , Institut Curie Breast Cancer Study Group et al; Ceelen, W.P., Bracke, M.E., Peritoneal minimal residual disease in colorectal cancer: Mechanisms, prevention, and treatment (2009) Lancet Oncol, 10, pp. 72-79; Bidard, F.C., Pierga, J.Y., Vincent-Salomon, A., A "class action" against the microenvironment: Do cancer cells cooperate in metastasis? (2008) Cancer Metastasis Rev, 27, pp. 5-10; Bertolini, F., Mancuso, P., Shaked, Y., Kerbel, R.S., Molecular and cellular biomarkers for angiogenesis in clinical oncology (2007) Drug Discovery Today, 12 (19-20), pp. 806-812. , DOI 10.1016/j.drudis.2007.08.011, PII S1359644607003534; Shields, J.D., Fleury, M.E., Yong, C., Tomei, A.A., Randolph, G.J., Swartz, M.A., Autologous Chemotaxis as a Mechanism of Tumor Cell Homing to Lymphatics via Interstitial Flow and Autocrine CCR7 Signaling (2007) Cancer Cell, 11 (6), pp. 526-538. , DOI 10.1016/j.ccr.2007.04.020, PII S1535610807001456; Nierodzik, M.L., Karpatkin, S., Thrombin induces tumor growth, metastasis, and angiogenesis: Evidence for a thrombin-regulated dormant tumor phenotype (2006) Cancer Cell, 10 (5), pp. 355-362. , DOI 10.1016/j.ccr.2006.10.002, PII S1535610806002868; Podsypanina, K., Du, Y.C., Jechlinger, M., Seeding and propagation of untransformed mouse mammary cells in the lung (2008) Science, 321, pp. 1841-1844; Aguirre-Ghiso, J.A., Models, mechanisms and clinical evidence for cancer dormancy (2007) Nature Reviews Cancer, 7 (11), pp. 834-846. , DOI 10.1038/nrc2256, PII NRC2256; Brackstone, M., Townson, J.L., Chambers, A.F., Tumour dormancy in breast cancer: An update (2007) Breast Cancer Res, 9, p. 208; O'Reilly, M.S., Holmgren, L., Shing, Y., Chen, C., Rosenthal, R.A., Moses, M., Lane, W.S., Folkman, J., Angiostatin: A novel angiogenesis inhibitor that mediates the suppression of metastases by a Lewis lung carcinoma (1994) Cell, 79 (2), pp. 315-328. , DOI 10.1016/0092-8674(94)90200-3; Norton, L., Massague, J., Is cancer a disease of self-seeding? (2006) Nature Medicine, 12 (8), pp. 875-878. , DOI 10.1038/nm0806-875, PII NM0806875; Bidard, F.C., (2008) Interactions en CoopéRations Cellulaires dans le Processus Métastatique, , MSc thesis. L'Université Paris XI; Benvenuti, S., Comoglio, P.M., The MET receptor tyrosine kinase in invasion and metastasis (2007) Journal of Cellular Physiology, 213 (2), pp. 316-325. , DOI 10.1002/jcp.21183; Mareel, M., Leroy, A., Clinical, cellular, and molecular aspects of cancer invasion (2003) Physiological Reviews, 83 (2), pp. 337-376; Christofori, G., New signals from the invasive front (2006) Nature, 441 (7092), pp. 444-450. , DOI 10.1038/nature04872, PII NATURE04872; Sabbah, M., Emami, S., Redeuilh, G., Molecular signature and therapeutic perspective of the epithelial-to-mesenchymal transitions in epithelial cancers (2008) Drug Resist Updat, 11, pp. 123-151; Thiery, J.P., Sleeman, J.P., Complex networks orchestrate epithelial-mesenchymal transitions (2006) Nature Reviews Molecular Cell Biology, 7 (2), pp. 131-142. , DOI 10.1038/nrm1835, PII NRM1835; Yang, J., Weinberg, R.A., Epithelial-Mesenchymal Transition: At the Crossroads of Development and Tumor Metastasis (2008) Developmental Cell, 14 (6), pp. 818-829. , DOI 10.1016/j.devcel.2008.05.009, PII S1534580708002098; Christiansen, J.J., Rajasekaran, A.K., Reassessing epithelial to mesenchymal transition as a prerequisite for carcinoma invasion and metastasis (2006) Cancer Research, 66 (17), pp. 8319-8326. , DOI 10.1158/0008-5472.CAN-06-0410; Brabletz, T., Jung, A., Spaderna, S., Hlubek, F., Kirchner, T., Migrating cancer stem cells - An integrated concept of malignant tumour progression (2005) Nature Reviews Cancer, 5 (9), pp. 744-749. , DOI 10.1038/nrc1694, PII N1694; Tarin, D., The fallacy of epithelial mesenchymal transition in neoplasia (2005) Cancer Research, 65 (14), pp. 5996-6000. , DOI 10.1158/0008-5472.CAN-05-0699; Garber, K., Epithelial-to-mesenchymal transition is important to metastasis, but questions remain (2008) J Natl Cancer Inst, 100, pp. 232-239; De Wever, O., Derycke, L., Hendrix, A., De Meerleer, G., Godeau, F., Depypere, H., Bracke, M., Soluble cadherins as cancer biomarkers (2007) Clinical and Experimental Metastasis, 24 (8), pp. 685-697. , DOI 10.1007/s10585-007-9104-8; Bellahcene, A., Castronovo, V., Ogbureke, K.U.E., Fisher, L.W., Fedarko, N.S., Small integrin-binding ligand N-linked glycoproteins (SIBLINGs): Multifunctional proteins in cancer (2008) Nature Reviews Cancer, 8 (3), pp. 212-226. , DOI 10.1038/nrc2345, PII NRC2345; Gimona, M., Buccione, R., Adhesions that mediate invasion (2006) International Journal of Biochemistry and Cell Biology, 38 (11), pp. 1875-1892. , DOI 10.1016/j.biocel.2006.05.003, PII S1357272506001580; Gimona, M., Buccione, R., Courtneidge, S.A., Assembly and biological role of podosomes and invadopodia (2008) Curr Opin Cell Biol, 20, pp. 235-241; Lopez-Otin, C., Matrisian, L.M., Emerging roles of proteases in tumour suppression (2007) Nature Reviews Cancer, 7 (10), pp. 800-808. , DOI 10.1038/nrc2228, PII NRC2228; Martin, M.D., Matrisian, L.M., The other side of MMPs: Protective roles in tumor progression (2007) Cancer and Metastasis Reviews, 26 (3-4), pp. 717-724. , DOI 10.1007/s10555-007-9089-4, Forty Years of Metastasis Research: A Tribute to Dr. Isaiah J. Fidler; Sahai, E., Mechanisms of cancer cell invasion (2005) Current Opinion in Genetics and Development, 15 (1), pp. 87-96. , DOI 10.1016/j.gde.2004.12.002, PII S0959437X04001881, Oncogenes and Cell Proliferation; Wolf, K., Mazo, I., Leung, H., Engelke, K., Von Andrian, U.H., Deryugina, E.I., Strongin, A.Y., Friedl, P., Compensation mechanism in tumor cell migration: Mesenchymal-amoeboid transition after blocking of pericellular proteolysis (2003) Journal of Cell Biology, 160 (2), pp. 267-277. , DOI 10.1083/jcb.200209006; Wolf, K., Friedl, P., Molecular mechanisms of cancer cell invasion and plasticity (2006) Br J Dermatol, 154 (SUPPL. 1), pp. 11-15; Yilmaz, M., Christofori, G., Lehembre, F., Distinct mechanisms of tumor invasion and metastasis (2007) Trends in Molecular Medicine, 13 (12), pp. 535-541. , DOI 10.1016/j.molmed.2007.10.004, PII S1471491407001888; Wicki, A., Christofori, G., The potential role of podoplanin in tumour invasion (2007) British Journal of Cancer, 96 (1), pp. 1-5. , DOI 10.1038/sj.bjc.6603518, PII 6603518; Yamaguchi, H., Condeelis, J., Regulation of the actin cytoskeleton in cancer cell migration and invasion (2007) Biochimica et Biophysica Acta - Molecular Cell Research, 1773 (5), pp. 642-652. , DOI 10.1016/j.bbamcr.2006.07.001, PII S0167488906001558; Sahai, E., Garcia-Medina, R., Pouyssegur, J., Vial, E., Smurf1 regulates tumor cell plasticity and motility through degradation of RhoA leading to localized inhibition of contractility (2007) Journal of Cell Biology, 176 (1), pp. 35-42. , http://www.jcb.org/cgi/reprint/176/1/35, DOI 10.1083/jcb.200605135; Gentile, A., Trusolino, L., Comoglio, P.M., The Met tyrosine kinase receptor in development and cancer (2008) Cancer Metastasis Rev, 27, pp. 85-94; Lengyel, E., Sawada, K., Salgia, R., Tyrosine kinase mutations in human cancer (2007) Current Molecular Medicine, 7 (1), pp. 77-84. , http://www.ingentaconnect.com/content/ben/cmm/2007/00000007/00000001/ art00007, DOI 10.2174/156652407779940486; Funasaka, T., Raz, A., The role of autocrine motility factor in tumor and tumor microenvironment (2007) Cancer and Metastasis Reviews, 26 (3-4), pp. 725-735. , DOI 10.1007/s10555-007-9086-7, Forty Years of Metastasis Research: A Tribute to Dr. Isaiah J. Fidler; Hehlgans, S., Haase, M., Cordes, N., Signalling via integrins: Implications for cell survival and anticancer strategies (2007) Biochimica et Biophysica Acta - Reviews on Cancer, 1775 (1), pp. 163-180. , DOI 10.1016/j.bbcan.2006.09.001, PII S0304419X06000588; Douma, S., Van Laar, T., Zevenhoven, J., Suppression of anoikis and induction of metastasis by the neurotrophic receptor TrkB (2004) Nature, 430, pp. 1034-1039; Geiger, T.R., Peeper, D.S., The neurotrophic receptor TrkB in anoikis resistance and metastasis: A perspective (2005) Cancer Research, 65 (16), pp. 7033-7036. , DOI 10.1158/0008-5472.CAN-05-0709; Sandri, M.T., Circulating tumor cells (2007) IEO-Scientific Report 2007-ongoing Research 2008, pp. 192-194; Gnerlich, J., Jeffe, D.B., Deshpande, A.D., Beers, C., Zander, C., Margenthaler, J.A., Surgical removal of the primary tumor increases overall survival in patients with metastatic breast cancer: Analysis of the 1988-2003 SEER data (2007) Annals of Surgical Oncology, 14 (8), pp. 2187-2194. , DOI 10.1245/s10434-007-9438-0; Salama, J.K., Chmura, S.J., Mehta, N., An initial report of a radiation dose-escalation trial in patients with one to five sites of metastatic disease (2008) Clin Cancer Res, 14, pp. 5255-5259; Dolle, L., Depypere, H.T., Bracke, M.E., Anti-invasive and anti-metastasis strategies: New roads, new tools and new hopes (2006) Current Cancer Drug Targets, 6 (8), pp. 729-751. , http://docstore.ingenta.com/cgi-bin/ds_deliver/1/u/d/ISIS/33724480.1/ben/ ccdt/2006/00000006/00000008/art00007/9C146EDF9740EFD9116485319359E89FF5E8D1E22C. pdf?link=http://www.ingentaconnect.com/error/delivery&format=pdf, DOI 10.2174/156800906779010263; Fox, S.B., Generali, D.G., Harris, A.L., Breast tumour angiogenesis (2007) Breast Cancer Res, 9, p. 216; Shaked, Y., Kerbel, R.S., Antiangiogenic strategies on defense: On the possibility of blocking rebounds by the tumor vasculature after chemotherapy (2007) Cancer Research, 67 (15), pp. 7055-7058. , http://cancerres.aacrjournals.org/cgi/reprint/67/15/7055, DOI 10.1158/0008-5472.CAN-07-0905; Formenti, S.C., Demaria, S., Local control by radiotherapy: Is that all there is? (2008) Breast Cancer Res, 10, p. 215; Husemann, Y., Geigl, J.B., Schubert, F., Musiani, P., Meyer, M., Burghart, E., Forni, G., Klein, C.A., Systemic Spread Is an Early Step in Breast Cancer (2008) Cancer Cell, 13 (1), pp. 58-68. , DOI 10.1016/j.ccr.2007.12.003, PII S1535610807003728; Denys, H., Derycke, L., Hendrix, A., Differential impact of TGF-beta and EGF on fibroblast differentiation and invasion reciprocally promotes colon cancer cell invasion (2008) Cancer Lett, 266, pp. 263-274; Milas, L., Mason, K., Liao, Z., Nieder, C., Milas, L., Ang, K.K., Role of cyclooxygenase-2 (COX-2) and its inhibition in tumor biology and radiotherapy (2003) Modification of Radiation Response, pp. 241-258. , Springer Berlin; Opdenakker, G., Van Damme, J., The countercurrent principle in invasion and metastasis of cancer cells. Recent insights on the roles of chemokines (2004) International Journal of Developmental Biology, 48 (5-6), pp. 519-527. , DOI 10.1387/ijdb.041796go, Invasion in Cancer and Embryonic Development; Nugent, J.L., Bunn Jr., P.A., Matthews, M.J., CNS metastases in small cell bronchogenic carcinoma. Increasing frequency and changing pattern with lengthening survival (1979) Cancer, 44 (5), pp. 1885-1893; Camphausen, K., Moses, M.A., Beecken, W.-D., Khan, M.K., Folkman, J., O'Reilly, M.S., Radiation therapy to a primary tumor accelerates metastatic growth in mice (2001) Cancer Research, 61 (5), pp. 2207-2211; Ramaswamy, S., Ross, K.N., Lander, E.S., Golub, T.R., A molecular signature of metastasis in primary solid tumors (2003) Nature Genetics, 33 (1), pp. 49-54. , DOI 10.1038/ng1060; Chen, Y.-J., Lin, S.-C., Kao, T., Chang, C.-S., Hong, P.-S., Shieh, T.-M., Chang, K.-W., Genome-wide profiling of oral squamous cell carcinoma (2004) Journal of Pathology, 204 (3), pp. 326-332. , DOI 10.1002/path.1640; Perou, C.M., Sorile, T., Eisen, M.B., Van De Rijn, M., Jeffrey, S.S., Ress, C.A., Pollack, J.R., Botstein, D., Molecular portraits of human breast tumours (2000) Nature, 406 (6797), pp. 747-752. , DOI 10.1038/35021093; LaTulippe, E., Satagopan, J., Smith, A., Scher, H., Scardino, P., Reuter, V., Gerald, W.L., Comprehensive gene expression analysis of prostate cancer reveals distinct transcriptional programs associated with metastatic disease (2002) Cancer Research, 62 (15), pp. 4499-4506; Lapointe, J., Li, C., Giacomini, C.P., Salari, K., Huang, S., Wang, P., Ferrari, M., Pollack, J.R., Genomic profiling reveals alternative genetic pathways of prostate tumorigenesis (2007) Cancer Research, 67 (18), pp. 8504-8510. , http://cancerres.aacrjournals.org/cgi/reprint/67/18/8504, DOI 10.1158/0008-5472.CAN-07-0673; Lips, E.H., Van Eijk, R., De Graaf, E.J., Integrating chromosomal aberrations and gene expression profiles to dissect rectal tumorigenesis (2008) BMC Cancer, 8, p. 314; Cromer, A., Carles, A., Millon, R., Ganguli, G., Chalmel, F., Lemaire, F., Young, J., Wasylyk, B., Identification of genes associated with tumorigenesis and metastatic potential of hypopharyngeal cancer by microarray analysis (2004) Oncogene, 23 (14), pp. 2484-2498. , DOI 10.1038/sj.onc.1207345; Couvelard, A., Hu, J., Steers, G., O'Toole, D., Sauvanet, A., Belghiti, J., Bedossa, P., Pezzella, F., Identification of Potential Therapeutic Targets by Gene-Expression Profiling in Pancreatic Endocrine Tumors (2006) Gastroenterology, 131 (5), pp. 1597-1610. , DOI 10.1053/j.gastro.2006.09.007, PII S0016508506020014; Bertucci, F., Finetti, P., Rougemont, J., Charafe-Jauffret, E., Nasser, V., Loriod, B., Camerlo, J., Viens, P., Gene expression profiling for molecular characterization of inflammatory breast cancer and prediction of response to chemotherapy (2004) Cancer Research, 64 (23), pp. 8558-8565. , DOI 10.1158/0008-5472.CAN-04-2696
Keywords: bone marrow; cancer cell; cancer invasion; carcinogenesis; cell activity; Circulation; ecosystem; epigenetics; extracellular matrix; gene control; host cell; human; Humans; lymph node metastasis; metastasis; Metastatic site; microarray analysis; Molecular biology; molecular imaging; Neoplasm Invasiveness; Neoplasm Metastasis; Neoplasms; nonhuman; pleiotropy; primary tumor; priority journal; Promoter and suppressor genes; promoter region; review; signal transduction; suppressor gene; Therapy guidance; Tumor-associated host cells

Corrected and improved model for educational simulation of neonatal cardiovascular pathophysiology - Zijlmans, M.; Sá-Couto, C.D.; van Meurs, W.L.; Goodwin, J.A.; Andriessen, P. (Simulation in HealthcareSimul. Healthc., 2009)
We identified errors in the software implementation of the mathematical model presented in: Sá Couto CD, van Meurs WL, Goodwin JA, Andriessen P. A model for educational simulation of neonatal cardiovascular pathophysiology. Simul Healthcare 2006;1:4-12. Simulation results obtained with corrected code are presented for future reference. All but one of the simulation results do not differ by more than 9% from the previously published results. The heart rate response to acute loss of 30% of blood volume, simulated with corrected code is stronger than published target data. This modeling error was masked by errors in code implementation. We improved this response and the model by adjusting the gains and adding thresholds and saturations in the baroreflex model. General considerations on identification of model and code errors and model validity are presented. Copyright © 2009 Society for Simulation in Healthcare.
Cited By (since 1996): 4Export Date: 21 November 2012Source: Scopusdoi: 10.1097/SIH.0b013e31818b27a8Language of Original Document: EnglishCorrespondence Address: Zijlmans, M.; INEB-Instituto de Engenharia Biomédica, Porto, PortugalReferences: Sá Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Andriessen, P., A model for educational simulation of neonatal cardiovascular pathophysiology (2006) Simul Healthc, 1, pp. 4-12;Goodwin, J.A., Van Meurs, W.L., Sá Couto, C.D., Beneken, J.E.W., Graves, S.A., A model for educational simulation of infant cardiovascular physiology (2004) Anesth Analg, 99, pp. 1655-1664; Beneken, J.E.W., A mathematical approach to cardiovascular function (1965) The Uncontrolled Human System, , Thesis, University of Utrecht, The Netherlands; Andriessen, P., Bambang Oetomo, S., Peters, C., Vermeulen, B., Wijn, P.F.F., Blanco, C.E., Baroreceptor reflex sensitivity in human neonates: The effect of postmenstrual age (2005) J Physiol, 568, pp. 333-341; Segar, J.L., Roghair, R.D., Segar, E.M., Bailey, M.C., Scholz, T.D., Lamb, F.S., Early gestation dexamethasone alters baroreflex and vascular responses in newborn lambs before hypertension (2006) Am J Physiol Regul Integr Comp Physiol, 291, pp. R481-R488; Wallgren, G., Barr, M., Rudhe, U., Hemodynamic studies of induced acute hypo- and hypervolemia in the newborn infant (1964) Acta Paediatr, 53, pp. 1-12
Keywords: aorta coarctation; article; Baroreflex; bleeding; blood pressure; blood volume; Cardiac Output; cardiovascular disease; Cardiovascular Diseases; Cardiovascular physiology; computer program; Computer simulation; Congenital heart defect; congenital heart malformation; diastolic blood pressure; Education, Medical; Erratum; Fallot tetralogy; great vessels transposition; heart output; Heart rate; heart right ventricle pressure; human; Humans; Infant, Newborn; lung pressure; mathematical model; mean arterial pressure; medical education; medical error; methodology; Neonate; Neonatology; newborn; patent ductus arteriosus; pathophysiology; physiology; pressoreceptor reflex; priority journal; simulation; Software Design; systolic blood pressure; Validation; validity; vascular resistance; Verification; vital sign

The correlation between the adsorption of adhesive proteins and cell behaviour on hydroxyl-methyl mixed self-assembled monolayers - Barrias, C.C.; Martins, M.C.L.; Almeida-Porada, G.; Barbosa, M.A.; Granja, P.L. (BiomaterialsBiomaterials, 2009)
The objective of this study was to compare the biological effects of two key cell-adhesive proteins, fibronectin (FN) and vitronectin (VN), upon adsorption onto molecularly-designed model surfaces. Single-component and mixed self-assembled monolayers (SAMs) of alkanethiols on gold with OH and CH 3 terminal groups were prepared at 100%, 65%, 36% and 0% of OH at the surface, to generate a range of surfaces with a simple chemistry and a wettability gradient. FN and VN were adsorbed under non-competitive (single-protein solutions) and competitive (multi-protein solutions) conditions, and compared at different levels: adsorbed amount (radiolabelling), elution, functional presentation of cell-binding domains (ELISA), and role in mediating cell adhesion (antibody-based assay). The observed trends were related to mesenchymal stem cell response in terms of adhesion and overall cell morphology. Under non-competitive conditions, adsorption of both proteins increased with surface hydrophobicity. The presence of competitive proteins significantly decreased the adsorbed amounts, although both proteins were still detected in all SAMs. Adsorption of FN followed a trend similar to that of non-competitive conditions, while adsorption of VN was higher on 100%OH-SAMs. Concerning elution, retention of adsorbed VN was always higher than that of FN. For both proteins, functional presentation of cell-binding domains was more effective on the more hydrophilic 100%OH-SAMs. This fact, coupled to the ability of this type of SAMs to selectively recruit and retain VN in the presence of competitive serum proteins, seems to correlate with the better cell response observed on these surfaces, as compared with hydrophobic 0%OH(100%CH 3)-SAMs. © 2008 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 41Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2008.09.048PubMed ID: 18952279Language of Original Document: EnglishCorrespondence Address: Barrias, C.C.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, R. Campo Alegre 823, 4150-180 Porto, Portugal; email: ccbarrias@ineb.up.ptChemicals/CAS: fibronectin, 86088-83-7; gold, 7440-57-5; thiol derivative, 13940-21-1; Biocompatible Materials; Fibronectins; VitronectinReferences: Wilson, C.J., Clegg, R.E., Leavesley, D.I., Pearcy, M.J., Mediation of biomaterial-cell interactions by adsorbed proteins: a review (2005) Tissue Eng, 11, pp. 1-18;García, A.J., Vega, M.D., Boettiger, D., Modulation of cell proliferation and differentiation through substrate-dependent changes in fibronectin conformation (1999) Mol Biol Cell, 10, pp. 785-798; Keselowsky, B.G., Collard, D.M., García, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) J Biomed Mater Res A, 66, pp. 247-259; Underwood, P.A., Bennett, F.A., A comparison of the biological activities of the cell-adhesive proteins vitronectin and fibronectin (1989) J Cell Sci, 93, pp. 641-649; Steele, J.G., Johnson, G., Underwood, P.A., Role of serum vitronectin and fibronectin in adhesion of fibroblasts following seeding onto tissue culture polystyrene (1992) J Biomed Mater Res, 26, pp. 861-884; Steele, J.G., Dalton, B.A., Johnson, G., Underwood, P.A., Polystyrene chemistry affects vitronectin activity: an explanation for cell attachment to tissue culture polystyrene but not to unmodified polystyrene (1993) J Biomed Mater Res, 27, pp. 927-940; Underwood, P.A., Steele, J.G., Dalton, B.A., Effects of polystyrene surface chemistry on the biological activity of solid phase fibronectin and vitronectin, analysed with monoclonal antibodies (1993) J Cell Sci, 104, pp. 793-803; Suzuki, S., Oldberg, A., Hayman, E.G., Pierschbacher, M.D., Ruoslahti, E., Complete amino acid sequence of human vitronectin deduced from cDNA. Similarity of cell attachment sites in vitronectin and fibronectin (1985) EMBO J, 4, pp. 2519-2524; Lee, M.H., Ducheyne, P., Lynch, L., Boettiger, D., Composto, R.J., Effect of biomaterial surface properties on fibronectin-alpha5beta1 integrin interaction and cellular attachment (2006) Biomaterials, 27, pp. 1907-1916; Grinnell, F., Feld, M.K., Fibronectin adsorption on hydrophilic and hydrophobic surfaces detected by antibody binding and analyzed during cell adhesion in serum-containing medium (1982) J Biol Chem, 257, pp. 4888-4893; Sousa, S.R., Lamghari, M., Sampaio, P., Moradas-Ferreira, P., Barbosa, M.A., Osteoblast adhesion and morphology on TiO 2 depends on the competitive preadsorption of albumin and fibronectin (2008) J Biomed Mater Res A, 84, pp. 281-290; Fabrizius-Homan, D.J., Cooper, S.L., Competitive adsorption of vitronectin with albumin, fibrinogen, and fibronectin on polymeric biomaterials (1991) J Biomed Mater Res, 25, pp. 953-971; Bale, M.D., Wohlfahrt, L.A., Mosher, D.F., Tomasini, B., Sutton, R.C., Identification of vitronectin as a major plasma protein adsorbed on polymer surfaces of different copolymer composition (1989) Blood, 74, pp. 2698-2706; Thomas, C.H., McFarland, C.D., Jenkins, M.L., Rezania, A., Steele, J.G., Healy, K.E., The role of vitronectin in the attachment and spatial distribution of bone-derived cells on materials with patterned surface chemistry (1997) J Biomed Mater Res, 37, pp. 81-93; McFarland, C.D., Thomas, C.H., DeFilippis, C., Steele, J.G., Healy, K.E., Protein adsorption and cell attachment to patterned surfaces (2000) J Biomed Mater Res, 49, pp. 200-210; Love, J.C., Estroff, L.A., Kriebel, J.K., Nuzzo, R.G., Whitesides, G.M., Self-assembled monolayers of thiolates on metals as a form of nanotechnology (2005) Chem Rev, 105, pp. 1103-1169; Mrksich, M., Whitesides, G.M., Using self-assembled monolayers to understand the interactions of man-made surfaces with proteins and cells (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-78; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) J Am Chem Soc, 111, pp. 321-335; Faucheux, N., Schweiss, R., Lützow, K., Werner, C., Groth, T., Self-assembled monolayers with different terminating groups as model substrates for cell adhesion studies (2004) Biomaterials, 25, pp. 2721-2730; Bernards, M.T., Jiang, S., pH-induced conformation changes of adsorbed vitronectin maximize its bovine aortic endothelial cell binding ability (2008) J Biomed Mater Res A; Martins, M.C., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl-terminated alkanethiols self-assembled monolayers (2003) J Biomed Mater Res A, 67, pp. 158-171; Rodrigues, S.N., Gonçalves, I.C., Martins, M.C., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27, pp. 5357-5367; Chamberlain, J., Yamagami, T., Colletti, E., Theise, N.D., Desai, J., Frias, A., Efficient generation of human hepatocytes by the intrahepatic delivery of clonal human mesenchymal stem cells in fetal sheep (2007) Hepatology, 46, pp. 1935-1945; (1993) Iodine-125. A guide to radioiodination techniques, , Amersham Life Science, Little Chalfort; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of biocompatibility tests, pp. 183-214. , Williams D.F. (Ed), CRC Press Inc., Harcover; Arima, Y., Iwata, H., Effect of wettability and surface functional groups on protein adsorption and cell adhesion using well-defined mixed self-assembled monolayers (2007) Biomaterials, 28, pp. 3074-3082; Capadona, J.R., Collard, D.M., Garcia, A.J., Fibronectin adsorption and cell adhesion to mixed monolayers of tri(ethylene glycol)- and methyl-terminated alkanethiols (2003) Langmuir, 19, pp. 1847-1852; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalized, self-assembled monolayers of alkanethiolates on gold (1997) Langmuir, 13, pp. 3404-3413; Jenney, C.R., Anderson, J.M., Adsorbed serum proteins responsible for surface dependent human macrophage behavior (2000) J Biomed Mater Res, 49, pp. 435-447; Wertz, C.F., Santore, M.M., Fibrinogen adsorption on hydrophilic and hydrophobic surfaces: geometrical and energetic aspects of interfacial relaxations (2002) Langmuir, 18, pp. 706-715; Pitt, W.G., Fabrizius-Homan, D.J., Mosher, D.F., Cooper, S.L., Vitronectin adsorption on polystyrene and oxidized polystyrene (1989) J Colloid Interface Sci, 129, pp. 231-239; Seiffert, D., Smith, J.W., The cell adhesion domain in plasma vitronectin is cryptic (1997) J Biol Chem, 272, pp. 13705-13710
Keywords: Adhesion; Adhesiveness; Adsorption; alkane; Animals; article; Biocompatible Materials; Biological Assay; bone marrow; Cattle; cell adhesion; Cell culture; Cell Movement; Cells; Cells, Cultured; cytology; cytoskeleton; Electric currents; Electron energy levels; enzyme linked immunosorbent assay; Fibronectin; Fibronectins; Focal adhesions; Functional groups; Functionalization; gold; human; human cell; Humans; hydrophilicity; hydrophobicity; Hydroxylation; isotope labeling; Mesenchymal stem cell; Mesenchymal Stem Cells; Microscopy, Confocal; Missile bases; Molecular interactions; monoclonal antibody; priority journal; Protein adsorption; protein analysis; protein binding; Protein Structure, Tertiary; Proteins; Self assembled monolayers; Self-assembled monolayers; stem cell; Stem cells; Surface Properties; thiol derivative; Vitronectin

Cytotoxicity evaluation of nanocrystalline diamond coatings by fibroblast cell cultures - Amaral, M.; Gomes, P.S.; Lopes, M.A.; Santos, J.D.; Silva, R.F.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2009)
The cytotoxicity profile of nanocrystalline diamond (NCD) coatings on a Si 3N 4 ceramic was investigated. This material is envisaged to have biomedical dental applications such as burrs and surgical instruments. Two fibroblast cell culture systems were used to address the cytotoxicity of NCD-coated samples: L929 cells (a mouse permanent cell line) and human gingival fibroblasts. Cell behavior was evaluated in terms of cell adhesion, cell viability/proliferation (mitochondrial function, MTT assay) and the pattern of cell growth. Fibroblast cell behavior on standard polystyrene culture plates was used as control, as Si 3N 4 substrates have previously been shown to be biocompatible. NCD coatings provided a suitable surface for cell attachment, spreading and proliferation. Human gingival cells showed a homogeneous cytoplasm spreading, a flattened elongated morphology and a typical parallel alignment on confluent cultures. In comparison, L929 cells denoted a lower cytoplasm expansion, a heterogeneous spreading but a higher proliferation rate. For both cells, after few days, the NCD coating was completely covered with continuous cell layers. As compared to standard polystyrene culture plates, no deleterious or cytotoxic responses were observed with L929 and human fibroblast cell cultures, and in both a slight enhancement in cell proliferation was observed. In addition, the seeded NCD film allowed reproduction of the typical features of the two cell culture systems tested, further suggesting the lack of cytotoxicity of this coating. © 2008 Acta Materialia Inc.
Cited By (since 1996): 8Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2008.08.015PubMed ID: 18819854Language of Original Document: EnglishCorrespondence Address: Amaral, M.; CICECO, Department of Ceramics and Glass Engineering, University of Aveiro, 3810-193 Aveiro, Portugal; email: margarida.amaral@ua.ptChemicals/CAS: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide, 298-93-1; diamond, 7782-40-3; polystyrene, 9003-53-6; silicon nitride, 12033-89-5; Culture Media; Diamond, 7782-40-3References: Griffin, J., Ray, P.C., Role of inert gas in the low-temperature nano-diamond chemical vapour deposition process (2006) Nanotechnology, 17, pp. 1225-1229;Mitura, S., Mitura, K., Niedzielski, P., Louda, P., Danilenko, V., Nanocrystalline diamond, its synthesis, properties and applications (2006) J Achievements Mater Manuf Eng, 16, pp. 9-16; Okrój, W., Kamińska, M., Klimek, L., Szymański, W., Walkowiak, B., Blood platelets in contact with nanocrystalline diamond surfaces (2006) Diamond Relat Mater, 15, pp. 1535-1539; Xiao, X., Wang, J., Liu, C., Carlisle, J.A., Mech, B., Greenberg, R., In vitro and in vivo evaluation of ultrananocrystalline diamond for coating of implantable retinal microchips (2006) J Biomed Mater Res B: Appl Biomater, 77 B, pp. 273-281; Tang, L., Tsai, C., Gerberich, W.W., Kruckeberg, L., Kania, D.R., Biocompatibility of chemical-vapour-deposited diamond (1995) Biomaterials, 16, pp. 483-488; Steinmueller-Nethl, D., Kloss, F.R., Haq, M.N.U., Rainer, M., Larsson, K., Linsmeier, C., Strong binding of bioactive BMP-2 to nanocrystalline diamond by physisorption (2006) Biomaterials, 27, pp. 4547-4556; Wenmackers, S., Christiaens, P., Daenen, M., Haenen, K., Nesládek, M., Ven, M., DNA attachment to nanocrystalline diamond films (2005) Phys Status Solidi, 202, pp. 2212-2216; Retama, J.R., Hernando, J., Lopez-Ruiz, B., Härtl, A., Steinmüller, D., Stutzmann, M., Synthetic nanocrystalline diamond as a third-generation biosensor support (2006) Langmuir, 22, pp. 5837-5842; Siew, P.S., Loh, K.P., Poh, W.C., Zhang, H., Biosensing properties of nanocrystalline diamond film grown on polycrystalline diamond electrodes (2005) Diamond Relat Mater, 14, pp. 426-431; Jakubowski, W., Bartosz, G., Niedzielski, P., Szymanski, W., Walkowiak, B., Nanocrystalline diamond surface is resistant to bacterial colonization (2004) Diamond Relat Mater, 13, pp. 1761-1763; Trava-Airoldi, V.J., Corat, E.J., Leite, N.F., Nono, M., Ferreira, N.G., Baranauskas, V., CVD diamond burrs-development and applications (1996) Diamond Relat Mater, 5, pp. 857-860; Amar, M., Ahmed, W., Sein, H., Jones, A.N., Rego, C., Chemical vapour deposition of diamond coatings onto molybdenum dental tools (2003) J Phys Condens Matter, 15, pp. S2977-S2982; Tetsumura, A., Honda, E., Sasaki, T., Kino, K., Metallic residues as a source of artifacts in magnetic resonance imaging of the temporomandibular joint (1999) Dentomaxillofac Radiol, 28, pp. 186-190; Carvalho, C.A., Fagundes, T.C., Barata, T.E., Trava-Airoldi, V.J., Navarro, M.L., The use of CVD diamond burrs for ultraconservative cavity preparations: a report of two cases (2007) J Esthet Restor Dent, 19, pp. 19-29; Mitura, K., Niedzielski, P., Grzegorz, B., Moll, J., Walkowiak, B., Pawlowska, Z., Interactions between carbon coatings and tissue (2006) Surf Coat Technol, 201, pp. 2117-2123; Fries, M.D., Vohra, Y.K., Microcrystalline and nanocrystalline diamond film deposition on cobalt chrome alloy (1999) Thin films-stresses and mechanical properties VIII, , Vinci R., Kraft O., Moody N., Besser P., and Shaffer II E. (Eds), MRS Publications, Boston, MA; Fries, M.D., Vohra, Y.K., Properties of nanocrystalline thin films grown by MPCVD for biomedical implant purposes (2004) Diamond Relat Mater, 13, pp. 1740-1743; Papo, M.J., Catledge, S.A., Vohra, Y.K., Mechanical wear behavior of nanocrystalline and multilayer diamond coatings on temporomandibular joint implants (2004) J Mater Sci: Mater Med, 15, pp. 773-777; Sun, F.H., Zhang, Z.M., Ma, Y.P., Chen, M., Synthesis of nanocrystalline diamond films on smooth WC-Co cemented carbide substrates (2007) Int J Abrasive Technol, 1, pp. 161-172; Belmonte, M., Fernandes, A.J.S., Costa, F.M., Oliveira, F.J., Silva, R.F., Adhesion behaviour assessment on diamond coated silicon nitride by acoustic emission (2003) Diamond Relat Mater, 12, pp. 733-737; Petzow, G., Herrmann, M., Silicon nitride ceramics (2002) Struct Bond, 102, pp. 47-167; Amaral, M., Costa, M.A., Lopes, M.A., Silva, R.F., Santos, J.D., Fernandes, M.H., Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and osteogenic differentiation of human bone marrow cells (2002) Biomaterials, 23, pp. 4897-4906; Kue, R., Sahrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201; Popov, C., Kulisch, W., Jelinek, M., Bock, A., Strnad, J., Nanocrystalline diamond/amorphous carbon composite films for applications in tribology, optics and biomedicine (2006) Thin Solid Films, 494, pp. 92-97; Chong, K.F., Loh, K.P., Vedula, S.R., Lim, C.T., Sternschulte, H., Steinmüller, D., Cell adhesion properties on photochemically functionalized diamond (2007) Langmuir, 23, pp. 5615-5621; Bajaj, P., Akin, D., Gupta, A., Sherman, D., Shi, B., Auciello, O., Ultra-nanocrystalline diamond film as an optimal cell interface for biomedical applications (2007) Biomed Microdevices, , [Epub ahead of print]; Arnold, L.F., Baram, B., In vitro culture of periodontal ligament cells (1972) J Dent Res, 51, pp. 953-959; Piche, J.E., Carnes Jr., D.L., Graves, D.T., Initial characterization of cells derived from human periodontia (1989) J Dent Res, 68, pp. 761-767; Trigo Cabral, C., Costa, M.A., Fernandes, M.H., In vitro models of periodontal cells: a comparative study of long-term gingival, periodontal ligament and alveolar bone cell cultures in the presence of β-glycerophosphate and dexamethasone (2007) J Mater Sci: Mater Med, 18, pp. 1079-1088; Bajpai, P.K., Billote, W.G., Ceramic biomaterials (1995) The biomedical engineering handbook, pp. 552-580. , Bronzino J.D. (Ed), CRC Press, Boca Raton, FL; Nishitani-Gamo, M., Ando, T., Watanabe, K., Sekita, M., Dennig, P.A., Yamamoto, K., Interfacial structures of oriented diamond on Si (1 0 0) characterized by confocal Raman spectroscopy (1997) Diamond Relat Mater, 6, pp. 1036-1040; Ferrari, A.C., Robertson, J., Origin of the 1150 cm -1 Raman mode in nanocrystalline diamond (2001) Phys Rev B, 63, pp. 121405-1-121405-4; Pfeiffer, R., Kuzmany, H., Knoll, P., Bokova, S., Salk, N., Günther, B., Evidence for trans-polyacetylene in nano-crystalline diamond films (2003) Diamond Relat Mater, 12, pp. 268-271; Zimmermann, T., Janischowsky, K., Denisenko, A., Guillén, F.J.H., Kubovic, M., Gruen, D.M., Nanocrystalline diamond pn-structure grown by hot-filament CVD (2006) Diamond Relat Mater, 15, pp. 203-206; Krauss, A.R., Auciello, O., Gruen, D.M., Jayatissa, A., Sumant, A., Tucek, J., Ultrananocrystalline diamond thin films for MEMS and moving mechanical assembly devices (2001) Diamond Relat Mater, 10, pp. 1952-1961; Amaral, M., Fernandes, A.J.S., Vila, M., Oliveira, F.J., Silva, R.F., Growth rate improvements in the hot-filament CVD deposition of nanocrystalline diamond (2006) Diamond Relat Mater, 15, pp. 1822-1827; Alberts, B., Johnson, A., Lewis, J., Raff, M., Roberts, K., Walter, P., The cytoskeleton (2002) Molecular biology of the cell. 4th ed., pp. 907-972. , Alberts B., Johnson A., Lewis J., Raff M., Roberts K., and Walter P. (Eds), Garland Publishing, New York; Stamenovic, D., Effects of cytoskeletal prestress on cell rheological behaviour (2005) Acta Biomater, 1, pp. 255-262; Freshney, T.I., Biology of cultured cells (2000) Culture of animal cells. A manual of basic technique, pp. 9-18. , Wiley-Liss, New York; Garguilo, J.M., Davis, B.A., Buddie, M., Köck, F.A.M., Nemanich, R.J., Fibrinogen adsorption onto microwave plasma chemical vapor deposited diamond films (2004) Diamond Relat Mater, 13, pp. 595-599; Ariano, P., Baldellia, P., Carbonea, E., Gilardino, A., Giudicea, A.L., Lovisolo, D., Cellular adhesion and neuronal excitability on functionalised diamond surfaces (2005) Diamond Relat Mater, 14, pp. 669-674; Heinrich, G., Grijgler, T., Rosiwal, S.M., Singer, R.F., CVD diamond coated titanium alloys for biomedical and aerospace applications (1997) Surf Coat Technol, 94-95, pp. 514-520; Müller, R., Adamschik, M., Steidl, D., Kohn, E., Thamasett, S., Stiller, S., Application of CVD-diamond for catheter ablation in the heart (2004) Diamond Relat Mater, 13, pp. 1080-1083; Nordsletten, L., Hogasen, A.K.M., Konttinen, Y.T., Santavirta, S., Aspenberg, P., Aasen, A.O., Human monocytes stimulation by particles of hydroxyapatite, silicon carbide and diamond: in vitro studies of new prosthesis coatings (1996) Biomaterials, 17, pp. 1521-1527; Aspenberg, P., Antilla, A., Konttinen, Y.T., Lappalainen, R., Goodman, S.B., Nordsletten, L., Benign response to particles of diamond and SiC: bone chamber studies of new joint replacement coating materials in rabbits (1996) Biomaterials, 17, pp. 807-812; Specht, C.G., Williams, O.A., Jackman, R.B., Schoepfer, R., Ordered growth of neurons on diamond (2004) Biomaterials, 25, pp. 4073-4078; Schrand, A.M., Huang, H., Carlson, C., Schlager, J.J., Omacr Sawa, E., Hussain, S.M., Are diamond nanoparticles cytotoxic? (2007) J Phys Chem B, 111, pp. 2-7; International Organization for Standardization, ISO 10993-5: biological evaluation of medical devices. Part 5. Tests for cytotoxicity: in vitro methods. Geneva; 1992International Organization for Standardization, ISO 7405: dentistry-preclinical evaluation of biocompatibility of medical devices used in dentistry-test methods for dental materials. Geneva; 1997Kaplan, F.S., Hayes, W.C., Keaveny, T.M., Boskey, A., Einhorn, T.A., Iannotti, J.P., Form and function of bone (1994) Orthopedic basic science, pp. 127-185. , Simon S.P. (Ed), American Academy of Orthopedic Surgeons, Columbus, OH; Webster, T.J., Proteins: structure and interactions patterns to solid surfaces (2004) Encyclopedia of nanoscience and nanotechnology, pp. 3079-3095. , Schwarz J.A., Contescu C., and Putyera K. (Eds), Marcel Dekker, New York; Webster, T.J., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21, pp. 1803-1810; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Specific proteins mediate enhanced osteoblast adhesion on nanophase ceramics (2000) J Biomed Mater Res, 51, pp. 475-483; Shane, A.C., Marc, D.F., Yogesh, K.V., William, R.L., Jack, E.L., Shanna, W., Nanostructured ceramics for biomedical implants (2002) J Nanosci Nanotechnol, 2, pp. 1-20; Price, R.L., Haberstroh, K.M., Webster, T.J., Enhanced functions of osteoblasts on nanostructured surfaces of carbon and alumina (2003) Med Biol Eng Comput, 41, pp. 372-375; Webster, T.J., Siegel, R.W., Bizios, R., Osteoblast adhesion on nanophase ceramics (1999) Biomaterials, 20, pp. 1221-1227; Perla, V., Webster, T.J., Better osteoblast adhesion on nanoparticulate selenium-A promising orthopedic implant material (2005) J Biomed Mater Res, 75 A, pp. 356-364
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; animal cell; Animals; article; Biocompatibility; Biomedical dental applications; biomedicine; cell adhesion; Cell Division; cell function; cell growth; Cell Line; cell proliferation; cell spreading; cell structure; cell surface; cell survival; cell viability; ceramics; controlled study; Culture Media; cytoplasm; Cytotoxicity; dentistry; diamond; Fibroblast cell cultures; fibroblast culture; Fibroblasts; gingiva; human; human cell; Humans; material coating; Mice; Microscopy, Electron, Scanning; mitochondrial respiration; mouse; nanocrystal; Nanocrystalline diamond coating; Nanostructures; nonhuman; polystyrene; priority journal; Silicon nitride; Surgical instrument

The effect of the co-immobilization of human osteoprogenitors and endothelial cells within alginate microspheres on mineralization in a bone defect - Grellier, M.; Granja, P.L.; Fricain, J.-C.; Bidarra, S.J.; Renard, M.; Bareille, R.; Bourget, C.; Amédée, J.; Barbosa, M.A. (BiomaterialsBiomaterials, 2009)
Bone regeneration seems to be dependant on cell communication between osteogenic and endothelial cells arising from surrounding blood vessels. This study aims to determine whether endothelial cells can regulate the osteogenic potential of osteoprogenitor cells in vitro and in vivo, in a long bone defect, when co-immobilized in alginate microspheres. Alginate is a natural polymer widely used as a biomaterial for cell encapsulation. Human osteoprogenitors (HOP) from bone marrow mesenchymal stem cells were immobilized alone or together with human umbilical vein endothelial cells (HUVEC) inside irradiated, oxidized and RGD-grafted alginate microspheres. Immobilized cells were cultured in dynamic conditions and cell metabolic activity increased during three weeks. The gene expression of alkaline phosphatase and osteocalcin, both specific markers of the osteoblastic phenotype, and mineralization deposits were upregulated in co-immobilized HOPs and HUVECs, comparing to the immobilization of monocultures. VEGF secretion was also increased when HOPs were co-immobilized with HUVECs. Microspheres containing co-cultures were further implanted in a bone defect and bone formation was analysed by μCT and histology at 3 and 6 weeks post-implantation. Mineralization was observed inside and around the implanted microspheres containing the immobilized cells. However, when HOPs were co-immobilized with HUVECs, mineralization significantly increased. These findings demonstrate that co-immobilization of osteogenic and endothelial cells within RGD-grafted alginate microspheres provides a promising strategy for bone tissue engineering. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 38Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2009.02.033PubMed ID: 19299013Language of Original Document: EnglishCorrespondence Address: Grellier, M.; INSERM, U577, Université Victor Segalen Bordeaux 2, UMR-S577, F-33076 Bordeaux Cedex, France; email: maritie.grellier@inserm.frChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; alkaline phosphatase, 9001-78-9; arginylglycylaspartic acid, 99896-85-2; osteocalcin, 136461-80-8; Alginates; Glucuronic Acid, 576-37-4; Hexuronic Acids; alginic acid, 9005-32-7References: Oreffo, R.O., Triffitt, J.T., Future potentials for using osteogenic stem cells and biomaterials in orthopedics (1999) Bone, 25 (2 SUPPL), pp. 5S-9S;Lubiatowski, P., Kruczynski, J., Gradys, A., Trzeciak, T., Jaroszewski, J., Articular cartilage repair by means of biodegradable scaffolds (2006) Transplant Proc, 38 (1), pp. 320-322; Evangelista, M.B., Hsiong, S.X., Fernandes, R., Sampaio, P., Kong, H.J., Barrias, C.C., Upregulation of bone cell differentiation through immobilization within a synthetic extracellular matrix (2007) Biomaterials, 28 (25), pp. 3644-3655; Gerber, H.P., Ferrara, N., Angiogenesis and bone growth (2000) Trends Cardiovasc Med, 10 (5), pp. 223-228; Carano, R.A., Filvaroff, E.H., Angiogenesis and bone repair (2003) Drug Discov Today, 8 (21), pp. 980-989; Deckers, M.M., Karperien, M., van der Bent, C., Yamashita, T., Papapoulos, S.E., Lowik, C.W., Expression of vascular endothelial growth factors and their receptors during osteoblast differentiation (2000) Endocrinology, 141 (5), pp. 1667-1674; Guillotin, B., Bourget, C., Remy-Zolgadri, M., Bareille, R., Fernandez, P., Conrad, V., Human primary endothelial cells stimulate human osteoprogenitor cell differentiation (2004) Cell Physiol Biochem, 14 (4-6), pp. 325-332; Villars, F., Bordenave, L., Bareille, R., Amedee, J., Effect of human endothelial cells on human bone marrow stromal cell phenotype: role of VEGF? (2000) J Cell Biochem, 79 (4), pp. 672-685; Kaigler, D., Krebsbach, P.H., Wang, Z., West, E.R., Horger, K., Mooney, D.J., Transplanted endothelial cells enhance orthotopic bone regeneration (2006) J Dent Res, 85 (7), pp. 633-637; Sun, H., Qu, Z., Guo, Y., Zang, G., Yang, B., In vitro and in vivo effects of rat kidney vascular endothelial cells on osteogenesis of rat bone marrow mesenchymal stem cells growing on polylactide-glycoli acid (PLGA) scaffolds (2007) Biomed Eng Online, 6, p. 41; Augst, A.D., Kong, H.J., Mooney, D.J., Alginate hydrogels as biomaterials (2006) Macromol Biosci, 6 (8), pp. 623-633; Leal, D., Matsuhiro, B., Rossi, M., Caruso, F., FT-IR spectra of alginic acid block fractions in three species of brown seaweeds (2008) Carbohydr Res, 343 (2), pp. 308-316; Keshaw, H., Forbes, A., Day, R.M., Release of angiogenic growth factors from cells encapsulated in alginate beads with bioactive glass (2005) Biomaterials, 26 (19), pp. 4171-4179; Alsberg, E., Anderson, K.W., Albeiruti, A., Franceschi, R.T., Mooney, D.J., Cell-interactive alginate hydrogels for bone tissue engineering (2001) J Dent Res, 80 (11), pp. 2025-2029; Abbah, S.A., Lu, W.W., Chan, D., Cheung, K.M., Liu, W.G., Zhao, F., In vitro evaluation of alginate encapsulated adipose-tissue stromal cells for use as injectable bone graft substitute (2006) Biochem Biophys Res Commun, 347 (1), pp. 185-191; Barrias, C.C., Lamghari, M., Granja, P.L., Sa Miranda, M.C., Barbosa, M.A., Biological evaluation of calcium alginate microspheres as a vehicle for the localized delivery of a therapeutic enzyme (2005) J Biomed Mater Res A, 74 (4), pp. 545-552; Durrieu, M.C., Pallu, S., Guillemot, F., Bareille, R., Amedee, J., Baquey, C.H., Grafting RGD containing peptides onto hydroxyapatite to promote osteoblastic cells adhesion (2004) J Mater Sci Mater Med, 15 (7), pp. 779-786; Kong, H.J., Smith, M.K., Mooney, D.J., Designing alginate hydrogels to maintain viability of immobilized cells (2003) Biomaterials, 24 (22), pp. 4023-4029; Bordenave, L., Baquey, C., Bareille, R., Lefebvre, F., Lauroua, C., Guerin, V., Endothelial cell compatibility testing of three different Pellethanes (1993) J Biomed Mater Res, 27 (11), pp. 1367-1381; Rowley, J.A., Mooney, D.J., Alginate type and RGD density control myoblast phenotype (2002) J Biomed Mater Res, 60 (2), pp. 217-223; Villars, F., Guillotin, B., Amedee, T., Dutoya, S., Bordenave, L., Bareille, R., Effect of HUVEC on human osteoprogenitor cell differentiation needs heterotypic gap junction communication (2002) Am J Physiol Cell Physiol, 282 (4), pp. C775-C785; Clarkin, C.E., Emery, R.J., Pitsillides, A.A., Wheeler-Jones, C.P., Evaluation of VEGF-mediated signaling in primary human cells reveals a paracrine action for VEGF in osteoblast-mediated crosstalk to endothelial cells (2007) J Cell Physiol; Cheng, C., Liu, H., Ge, H., Qian, J., Qin, J., Sun, L., Essential role of Src suppressed C kinase substrates in endothelial cell adhesion and spreading (2007) Biochem Biophys Res Commun, 358 (1), pp. 342-348; Gerber, H.P., McMurtrey, A., Kowalski, J., Yan, M., Keyt, B.A., Dixit, V., Vascular endothelial growth factor regulates endothelial cell survival through the phosphatidylinositol 3′-kinase/Akt signal transduction pathway. Requirement for Flk-1/KDR activation (1998) J Biol Chem, 273 (46), pp. 30336-30343; Cross, M.J., Claesson-Welsh, L., FGF and VEGF function in angiogenesis: signalling pathways, biological responses and therapeutic inhibition (2001) Trends Pharmacol Sci, 22 (4), pp. 201-207; Volkmer, E., Drosse, I., Otto, S., Stangelmayer, A., Stengele, M., Kallukalam, B.C., Hypoxia in static and dynamic 3D culture systems for tissue engineering of bone (2008) Tissue Eng Part A, 14 (8), pp. 1331-1340; Stiehler, M., Bunger, C., Baatrup, A., Lind, M., Kassem, M., Mygind, T., Effect of dynamic 3-D culture on proliferation, distribution, and osteogenic differentiation of human mesenchymal stem cells (2008) J Biomed Mater Res A; Mann, V., Huber, C., Kogianni, G., Jones, D., Noble, B., The influence of mechanical stimulation on osteocyte apoptosis and bone viability in human trabecular bone (2006) J Musculoskelet Neuronal Interact, 6 (4), pp. 408-417; Bjerre, L., Bunger, C.E., Kassem, M., Mygind, T., Flow perfusion culture of human mesenchymal stem cells on silicate-substituted tricalcium phosphate scaffolds (2008) Biomaterials, 29 (17), pp. 2616-2627; Bouletreau, P.J., Warren, S.M., Spector, J.A., Peled, Z.M., Gerrets, R.P., Greenwald, J.A., Hypoxia and VEGF up-regulate BMP-2 mRNA and protein expression in microvascular endothelial cells: implications for fracture healing (2002) Plast Reconstr Surg, 109 (7), pp. 2384-2397; Simmons, C.A., Alsberg, E., Hsiong, S., Kim, W.J., Mooney, D.J., Dual growth factor delivery and controlled scaffold degradation enhance in vivo bone formation by transplanted bone marrow stromal cells (2004) Bone, 35 (2), pp. 562-569; Lu, H.H., Vo, J.M., Chin, H.S., Lin, J., Cozin, M., Tsay, R., Controlled delivery of platelet-rich plasma-derived growth factors for bone formation (2008) J Biomed Mater Res A; Yu, H., Vandevord, P.J., Gong, W., Wu, B., Song, Z., Matthew, H.W., Promotion of osteogenesis in tissue-engineered bone by pre-seeding endothelial progenitor cells-derived endothelial cells (2008) J Orthop Res, 26 (8), pp. 1147-1152; Bouhadir, K.H., Lee, K.Y., Alsberg, E., Damm, K.L., Anderson, K.W., Mooney, D.J., Degradation of partially oxidized alginate and its potential application for tissue engineering (2001) Biotechnol Prog, 17 (5), pp. 945-950
Keywords: adult; aged; Alginate; Alginates; alginic acid; alkaline phosphatase; animal tissue; Animals; arginylglycylaspartic acid; article; Bioactivity; Biopolymers; Blood vessel prostheses; Blood Vessels; Bone; Bone and Bones; bone defect; Bone defects; Bone formations; Bone marrow mesenchymal stem cells; bone mineralization; Bone Regeneration; Bone regenerations; bone tissue; Bone tissue engineerings; Calcification, Physiologic; Cell communications; Cell culture; Cell encapsulations; cell function; cell growth; Cell immobilization; Cell membranes; cell metabolism; Cells, Cultured; Co immobilizations; Co-culture; coculture; computer assisted tomography; controlled study; Defects; Dynamic conditions; Endothelial Cells; endothelium cell; gene expression; gene expression regulation; Glucuronic Acid; Grafting (chemical); Hexuronic Acids; histology; human; human cell; Human umbilical vein endothelial cells; Humans; Humulus; immobilized cell; Immobilized cells; in vitro study; in vivo study; In-vitro; In-vivo; irradiation; long bone; Long bones; Mesenchymal stem cell; Metabolic activities; Mice; Mice, Nude; microsphere; Microspheres; Middle Aged; Mineralogy; monoculture; mouse; nonhuman; osteoblast; osteocalcin; Osteogenic; Osteogenic potentials; Osteoprogenitor cells; Osteoprogenitors; Oxidation; Peptides; phenotype; Post implantations; priority journal; Self assembly; Sodium compounds; stem cell transplantation; Stem cells; Tissue engineering; umbilical vein; upregulation; Vascular endothelial growth factor (VEGF); X ray analysis; Young Adult

Fibronectin-mediated endothelialisation of chitosan porous matrices - Amaral, I.F.; Unger, R.E.; Fuchs, S.; Mendonça, A.M.; Sousa, S.R.; Barbosa, M.A.; Pêgo, A.P.; Kirkpatrick, C.J. (BiomaterialsBiomaterials, 2009)
Chitosan (Ch) porous matrices were investigated regarding their ability to be colonized by human microvascular endothelial cells (HPMEC-ST1.6R cell line) and macrovascular endothelial cells namely HUVECs. Specifically we assessed if previous incubation of Ch in a fibronectin (FN) solution was effective in promoting endothelial cell (EC) adhesion to Ch matrices with different degrees of acetylation (DAs). Upon FN physiadsorption, marked differences were found between the two DAs investigated, namely DA 4% and 15%. While cell adhesion was impaired on Ch with DA 15%, ECs were able to not only adhere to Ch with DA 4%, but also to spread and colonize the scaffolds, with retention of the EC phenotype and angiogenic potential. To explain the observed differences between the two DAs, protein adsorption studies using 125I-FN and immunofluorescent labelling of FN cell-binding domains were carried out. In agreement with the higher cell numbers found, scaffolds with DA 4% revealed a higher number of exposed FN cell-binding domains as well as greater ability to adsorb FN and to retain and exchange adsorbed FN in the presence of competitive proteins. These findings suggest that the DA is a key parameter modulating EC adhesion to FN-coated Ch by influencing the adsorbed protein layer. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2009.06.056PubMed ID: 19615736Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; fibronectin, 86088-83-7; Biocompatible Materials; Chitosan, 9012-76-4; FibronectinsReferences: Moon, J.J., West, J.L., Vascularization of engineered tissues: approaches to promote angiogenesis in biomaterials (2008) Current Topics in Medicinal Chemistry, 8 (4), pp. 300-310;Blitterswijk, C.A., Moroni, L., Rouwkema, J., Siddappa, R., Sohier, J., Tissue engineering - an introduction (2008) Tissue engineering, , Blitterswijk C.A. (Ed), Elsevier; Ehrbar, M., Zeisberger, S.M., Raeber, G.P., Hubbell, J.A., Schnell, C., Zisch, A.H., The role of actively released fibrin-conjugated VEGF for VEGF receptor 2 gene activation and the enhancement of angiogenesis (2008) Biomaterials, 29 (11), pp. 1720-1729; Elbjeirami, W.M., West, J.L., Angiogenesis-like activity of endothelial cells co-cultured with VEGF-producing smooth muscle cells (2006) Tissue Engineering, 12 (2), pp. 381-390; Unger, R.E., Peters, K., Wolf, M., Motta, A., Migliaresi, C., Kirkpatrick, C.J., Endothelialization of a non-woven silk fibroin net for use in tissue engineering: growth and gene regulation of hunian endothelial cells (2004) Biomaterials, 25 (21), pp. 5137-5146; Fuchs, S., Motta, A., Migliaresi, C., Kirkpatrick, C.J., Outgrowth endothelial cells isolated and expanded from human peripheral blood progenitor cells as a potential source of autologous cells for endothelialization of silk fibroin biomaterials (2006) Biomaterials, 27 (31), pp. 5399-5408; Kirkpatrick, C.J., Unger, R.E., Krump-Konvalinkova, V., Peters, K., Schmidt, H., Kamp, G., Experimental approaches to study vascularization in tissue engineering and biomaterial applications (2003) Journal of Materials Science, 14 (8), pp. 677-681; Calonder, C., Matthew, H.W.T., Van Tassel, P.R., Adsorbed layers of oriented fibronectin: a strategy to control cell-surface interactions (2005) Journal of Biomedical Materials Research Part A, 75 A (2), pp. 316-323; Kouvroukoglou, S., Dee, K.C., Bizios, R., McIntire, L.V., Zygourakis, K., Endothelial cell migration on surfaces modified with immobilized adhesive peptides (2000) Biomaterials, 21 (17), pp. 1725-1733; Burdick, J.A., Khademhosseini, A., Langer, R., Fabrication of gradient hydrogels using a microfluidics/photopolymerization process (2004) Langmuir, 20 (13), pp. 5153-5156; Garcia, A.J., Get a grip: integrins in cell-biomaterial interactions (2005) Biomaterials, 26, pp. 7525-7529; Tomihata, K., Ikada, Y., In vitro and in vivo degradation of films of chitin and its deacetylated derivatives (1997) Biomaterials, 18 (7), pp. 567-575; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., Rat bone marrow stromal cells osteogenic differentiation and fibronectin adsorption on chitosan membranes: the effect of the degree of acetylation (2005) Journal of Biomedical Materials Research Part A, 75 A (2), pp. 387-397; Nettles, D.L., Elder, S.H., Gilbert, J.A., Potential use of chitosan as a cell scaffold material for cartilage tissue engineering (2002) Tissue Engineering, 8 (6), pp. 1009-1016; Oliveira, S.M., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., Engineering endochondral bone: in vitro studies (2009) Tissue Engineering, 15 (3), pp. 625-634; Freier, T., Koh, H.S., Kazazian, K., Shoichet, M.S., Controlling cell adhesion and degradation of chitosan films by N-acetylation (2005) Biomaterials, 26 (29), pp. 5872-5878; Wang, X.H., Cui, F.Z., Feng, Q.L., Li, J.C., Zhang, Y.H., Preparation and characterization of collagen/chitosan matrices as potential biomaterials (2003) Journal of Bioactive and Compatible Polymers, 18 (6), pp. 453-467; Chupa, J.M., Foster, A.M., Sumner, S.R., Madihally, S.V., Matthew, H.W.T., Vascular cell responses to polysaccharide materials: in vitro and in vivo evaluations (2000) Biomaterials, 21 (22), pp. 2315-2322; Chung, T.W., Lu, Y.F., Wang, S.S., Lin, Y.S., Chu, S.H., Growth of human endothelial cells on photochemically grafted Gly-Arg-Gly-Asp (GRGD) chitosans (2002) Biomaterials, 23 (24), pp. 4803-4809; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., Adhesive protein interactions with chitosan: consequences for valve endothelial cell growth on tissue-engineering materials (2003) Journal of Biomedical Materials Research Part A, 67 A (2), pp. 538-547; Huang, Y., Onyeri, S., Siewe, M., Moshfeghian, A., Madihally, S.V., In vitro characterization of chitosan-gelatin scaffolds for tissue engineering (2005) Biomaterials, 26 (36), pp. 7616-7627; Huang, Y., Siewe, M., Madilhally, S.V., Effect of spatial architecture on cellular colonization (2006) Biotechnology and Bioengineering, 93 (1), pp. 64-75; Kirsebom, H., Aguilar, M.R., Roman, J.S., Fernandez, M., Prieto, M.A., Bondar, B., Macroporous scaffolds based on chitosan and bioactive molecules (2007) Journal of Bioactive and Compatible Polymers, 22 (6), pp. 621-636; Cao, W.L., Jing, D.H., Li, J.M., Gong, Y.D., Zhao, N.M., Zhang, X.F., Effects of the degree of deacetylation on the physicochemical properties and Schwann cell affinity of chitosan films (2005) Journal of Biomaterials Applications, 20 (2), pp. 157-177; Amaral, I.F., Sampaio, P., Barbosa, M.A., Three-dimensional culture of human osteoblastic cells in chitosan sponges: the effect of the degree of acetylation (2006) Journal of Biomedical Materials Research Part A, 76 A (2), pp. 335-346; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42 (8), pp. 3569-3580; Vachoud, L., Zydowicz, N., Domard, A., Formation and characterisation of a physical chitin gel (1997) Carbohydrate Research, 302 (3-4), pp. 169-177; Montembault, A., Viton, C., Domard, A., Physico-chemical studies of the gelation of chitosan in a hydroalcoholic medium (2005) Biomaterials, 26 (8), pp. 933-943; Amaral, I.F., Cordeiro, A.L., Sampaio, P., Barbosa, M.A., Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation (2007) Journal of Biomaterials Science Polymer Edition, 18 (4), pp. 469-485; Krump-Konvalinkova, V., Bittinger, F., Unger, R.E., Peters, K., Lehr, H.A., Kirkpatrick, C.J., Generation of human pulmonary microvascular endothelial cell lines (2001) Laboratory Investigation, 81 (12), pp. 1717-1727; Unger, R.E., Krump-Konvalinkova, V., Peters, K., Kirkpatrick, C.J., In vitro expression of the endothelial phenotype: comparative study of primary isolated cells and cell lines, including the novel cell line HPMEC-ST1.6R (2002) Microvascular Research, 64 (3), pp. 384-397; Jaffe, E.A., Nachman, R.L., Becker, C.G., Minick, C.R., Culture of human endothelial cells derived from umbilical veins. Identification by morphologic and immunologic criteria (1973) J Clin Invest, 52 (11), pp. 2745-2756; O'Brien, J., Wilson, I., Orton, T., Pognan, F., Investigation of the Alamar blue (resazurin) fluorescent dye for the assessment of mammalian cell cytotoxicity (2000) European Journal of Biochemistry, 267 (17), pp. 5421-5426; Teixeira, C.C., Hatori, M., Leboy, P.S., Pacifici, M., Shapiro, I.M., A rapid and ultrasensitive method for measurement of DNA, calcium and protein-content, and alkaline-phosphatase activity of chondrocyte cultures (1995) Calcified Tissue International, 56 (3), pp. 252-256; Barbosa, J.N., Amaral, I.F., Águas, A.P., Barbosa, M.A., Evaluation of the effect of the degree of acetylation on the inflammatory response to 3D porous chitosan scaffolds Journal of Biomedical Materials Research Part A, , in press, doi:10.1002/jbm.a.32499; Marshall, A.J., Barker, T., Sage, E.H., Hauch, K.D., Ratner, B.D., (2004) Pore size controls angiogenesis in subcutaneously implanted porous matrices. 7th World Biomaterials Congress; 2004, , Australian Society for Biomaterials Inc., Sydney, Australia p. 710; Unger, R.E., Sartoris, A., Peters, K., Motta, A., Migliaresi, C., Kunkel, M., Tissue-like self-assembly in cocultures of endothelial cells and osteoblasts and the formation of microcapillary-like structures on three-dimensional porous biomaterials (2007) Biomaterials, 28 (27), pp. 3965-3976; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalized, self-assembled monolayers of alkanethiolates on gold (1997) Langmuir, 13 (13), pp. 3404-3413; Wendt, D., Marsano, A., Jakob, M., Heberer, M., Martin, I., Oscillating perfusion of cell suspensions through three-dimensional scaffolds enhances cell seeding efficiency and uniformity (2003) Biotechnology and Bioengineering, 84 (2), pp. 205-214; Santos, M.I., Fuchs, S., Gomes, M.E., Unger, R.E., Reis, R.L., Kirkpatrick, C.J., Response of micro- and macrovascular endothelial cells to starch-based fiber meshes for bone tissue engineering (2007) Biomaterials, 28 (2), pp. 240-248; Vestweber, D., Molecular mechanisms that control endothelial cell contacts (2000) Journal of Pathology, 190 (3), pp. 281-291; Mori, T., Irie, Y., Nishimura, S., Tokura, S., Matsuura, M., Okumura, M., Endothelial cell responses to chitin and its derivatives (1998) Journal of Biomedical Materials Research, 43 (4), pp. 469-472; Panetti, T.S., Hannah, D.F., Avraamides, C., Gaughan, J.P., Marcinkiewicz, Z., Huttenlocher, A., Extracellular matrix molecules regulate endothelial cell migration stimulated by lysophosphatidic acid (2004) Journal of Thrombosis and Haemostasis, 2 (9), pp. 1645-1656; Garcia, A.J., Boettiger, D., Integrin-fibronectin interactions at the cell-material interface: initial integrin binding and signaling (1999) Biomaterials, 20 (23-24), pp. 2427-2433; Danen, E.H.J., Sonnenberg, A., Integrins in regulation of tissue development and function (2003) Journal of Pathology, 200 (4), pp. 471-480; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) Journal of Biomedical Materials Research Part A, 66 A (2), pp. 247-259; Renner, L., Jorgensen, B., Markowski, M., Salchert, K., Werner, C., Pompe, T., Control of fibronectin displacement on polymer substrates to influence endothelial cell behaviour (2004) Journal of Materials Science-Materials in Medicine, 15 (4), pp. 387-390; Garcia, A.J., Vega, M.D., Boettiger, D., Modulation of cell proliferation and differentiation through substrate-dependent changes in fibronectin conformation (1999) Molecular Biology of the Cell, 10 (3), pp. 785-798; Koenig, A.L., Gambillara, V., Grainger, D.W., Correlating fibronectin adsorption with endothelial cell adhesion and signaling on polymer substrates (2003) Journal of Biomedical Materials Research Part A, 64 A (1), pp. 20-37; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates focal adhesion composition and signaling through changes in integrin binding (2004) Biomaterials, 25, pp. 5947-5954; Pompe, T., Kobe, F., Salchert, K., Jorgensen, B., Oswald, J., Werner, C., Fibronectin anchorage to polymer substrates controls the initial phase of endothelial cell adhesion (2003) Journal of Biomedical Materials Research Part A, 67 A (2), pp. 647-657
Keywords: Acetylation; Adhesion; Adsorption; angiogenesis; article; Biocompatible Materials; Blood vessel prostheses; cell adhesion; Cell culture; cell invasion; Cell Line; Cell lines; Cell membranes; Cell number; cell proliferation; Cell size; cell spreading; cell survival; Cell-binding domain; Chitin; Chitin/chitosan; chitosan; colony formation; controlled study; Degrees of acetylation; Electric conductivity measurement; Electric currents; Endothelial cell; Endothelial Cells; Endothelialisation; endothelium; endothelium cell; epithelization; Fibronectin; Fibronectins; human; human cell; Human microvascular endothelial cells; Humans; immunofluorescence test; Key parameters; Labels; materials testing; Matrix algebra; Neovascularization, Physiologic; phenotype; porosity; Porous matrixs; priority journal; Protein adsorption; Protein layers; Scaffold; Scaffolds; Self assembly; Tissue engineering; tissue scaffold; umbilical vein

Improving chitosan-mediated gene transfer by the introduction of intracellular buffering moieties into the chitosan backbone - Moreira, C.; Oliveira, H.; Pires, L.R.; Simões, S.; Barbosa, M.A.; Pêgo, A.P. (Acta BiomaterialiaActa Biomater., 2009)
Chitosan was functionalized with imidazole moieties (CHimi) with the aim of improving its buffering capacity and promoting the endosomal escape ability of chitosan-DNA complexes, ultimately increasing their transfection efficiency. 5.6%, 12.9% and 22.1% of the glucosamine residues of chitosan were substituted. Complexes with different molar ratios of primary amines to DNA phosphate anion (N/P) were prepared by a coacervation method. For an N/P > 3, CHimi polymers are able to complex electrostatically with DNA and condense it into positively charged nanostructures (average size 260 nm and zeta potential +16 mV at pH 5.5). In the concentration range 2.5-100 μg ml
Cited By (since 1996): 17Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2009.04.021PubMed ID: 19427930Language of Original Document: EnglishCorrespondence Address: Pêgo, A.P.; INEB-Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: apego@ineb.up.ptChemicals/CAS: DNA, 9007-49-2; chitosan, 9012-76-4; imidazole, 1467-16-9, 288-32-4; Biocompatible Materials; Buffers; Chitosan, 9012-76-4; DNA, 9007-49-2; Drug CarriersReferences: Kirkpatrick, C.J., Fuchs, S., Peters, K., Brochhausen, C., Hermanns, M.I., Unger, R.E., Visions for regenerative medicine: interface between scientific fact and science fiction (2006) Artif Organs, 30, pp. 822-827;Simões, S., Filipe, A., Faneca, H., Mano, M., Penacho, N., Duzgunes, N., Cationic liposomes for gene delivery (2005) Expert Opin Drug Deliv, 2, pp. 237-254; Lungwitz, U., Breunig, M., Blunk, T., Gopferich, A., Polyethylenimine-based non-viral gene delivery systems (2005) Eur J Pharm Biopharm, 60, pp. 247-266; Filion, M.C., Phillips, N.C., Major limitations in the use of cationic liposomes for DNA delivery (1998) Int J Pharm, 162, pp. 159-170; Lv, H., Zhang, S., Wang, B., Cui, S., Yan, J., Toxicity of cationic lipids and cationic polymers in gene delivery (2006) J Control Release, 114, pp. 100-109; Itaka, K., Ohba, S., Miyata, K., Kawaguchi, H., Nakamura, K., Takato, T., Bone regeneration by regulated in vivo gene transfer using biocompatible polyplex nanomicelles (2007) Mol Ther, 15, pp. 1655-1662; Borchard, G., Chitosans for gene delivery (2001) Adv Drug Deliv Rev, 52, pp. 145-150; Khalil, I.A., Kogure, K., Akita, H., Harashima, H., Uptake pathways and subsequent intracellular trafficking in nonviral gene delivery (2006) Pharmacol Rev, 58, pp. 32-45; Behr, J.P., The proton sponge: a trick to enter cells the viruses did not exploit (1997) Chimia, 51, pp. 34-36; Kim, T.H., Kim, S.I., Akaike, T., Cho, C.S., Synergistic effect of poly(ethylenimine) on the transfection efficiency of galactosylated chitosan/DNA complexes (2005) J Control Release, 105, pp. 354-366; Midoux, P., Monsigny, M., Efficient gene transfer by histidylated polylysine/pDNA complexes (1999) Bioconjug Chem, 10, pp. 406-411; Benns, J.M., Choi, J.S., Mahato, R.I., Park, J.S., Kim, S.W., pH-sensitive cationic polymer gene delivery vehicle: N-Ac-poly(l-histidine)-graft-poly(l-lysine) comb shaped polymer (2000) Bioconjug Chem, 11, pp. 637-645; Putnam, D., Gentry, C.A., Pack, D.W., Langer, R., Polymer-based gene delivery with low cytotoxicity by a unique balance of side-chain termini (2001) Proc Natl Acad Sci USA, 98, pp. 1200-1205; Dubruel, P., Christiaens, B., Vanloo, B., Bracke, K., Rosseneu, M., Vandekerckhove, J., Physicochemical and biological evaluation of cationic polymethacrylates as vectors for gene delivery (2003) Eur J Pharm Sci, 18, pp. 211-220; Dubruel, P., Dekie, L., Schacht, E., Poly-l-glutamic acid derivatives as multifunctional vectors for gene delivery. Part A. Synthesis and physicochemical evaluation (2003) Biomacromolecules, 4, pp. 1168-1176; Kim, T.H., Ihm, J.E., Choi, Y.J., Nah, J.W., Cho, C.S., Efficient gene delivery by urocanic acid-modified chitosan (2003) J Control Release, 93, pp. 389-402; Dubruel, P., Christiaens, B., Rosseneu, M., Vandekerckhove, J., Grooten, J., Goossens, V., Buffering properties of cationic polymethacrylates are not the only key to successful gene delivery (2004) Biomacromolecules, 5, pp. 379-388; Juusola, P., Minkkinen, P., Leino, L., Laihia, J.K., Determination of the dissociation constants of urocanic acid isomers in aqueous solutions (2007) Monatsh Chem, 138, pp. 951-965; Roberts, J.D., Yu, C., Flanagan, C., Birdseye, T.R., A nitrogen-15 nuclear magnetic resonance study of the acid-base and tautomeric equilibria of 4-substituted imidazoles and its relevance to the catalytic mechanism of alfa-lytic protease (1982) J Am Chem Soc, 104, pp. 3945-3949; Roberts, G.A.F., (1992) Chitin chemistry, , Palgrave Macmillan, London; Nakagawa, Y., Murai, T., Hasegawa, C., Hirata, M., Tsuchiya, T., Yagami, T., Endotoxin contamination in wound dressings made of natural biomaterials (2003) J Biomed Mater Res B Appl Biomater, 66, pp. 347-355; (1987) Guideline on validation of the limulus amebocyte lysate test as an end-product endotoxin test for human and animal parenteral drugs, biological products, and medical devices, , U.S. Department of Health and Human Services, Public Health Service, Food and Drug Administration; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., Molecular parameters of chitosans depolymerized with the aid of papain (1996) Carbohydr Polym, 29, pp. 63-68; Sehgal, D., Vijay, I.K., A method for the high-efficiency of water-soluble carbodiimide-mediated amidation (1994) Anal Biochem, 218, pp. 87-91; Leong, K.W., Mao, H.Q., Truong-Le, V.L., Roy, K., Walsh, S.M., August, J.T., DNA-polycation nanospheres as non-viral gene delivery vehicles (1998) J Control Release, 53, pp. 183-193; Lee, M., Nah, J.W., Kwon, Y., Koh, J.J., Ko, K.S., Kim, S.W., Water-soluble and low molecular weight chitosan-based plasmid DNA delivery (2001) Pharm Res, 18, pp. 427-431; van Kuppeveld, F.J., van der Logt, J.T., Angulo, A.F., van Zoest, M.J., Quint, W.G., Niesters, H.G., Genus- and species-specific identification of mycoplasmas by 16S rRNA amplification (1992) Appl Environ Microbiol, 58, pp. 2606-2615; van Kuppeveld, F.J., van der Logt, J.T., Angulo, A.F., van Zoest, M.J., Quint, W.G., Niesters, H.G., Genus- and species-specific identification of mycoplasmas by 16S rRNA amplification (1993) Appl Environ Microbiol, 59, p. 655; Mosmann, T., Rapid colorimetric assay for cellular growth and survival: application to proliferation and cytotoxicity assays (1983) J Immunol Methods, 65, pp. 55-63; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Godbey, W.T., Ku, K.K., Hirasaki, G.J., Mikos, A.G., Improved packing of poly(ethylenimine)/DNA complexes increases transfection efficiency (1999) Gene Ther, 6, pp. 1380-1388; Pouton, C.W., Lucas, P., Thomas, B.J., Uduehi, A.N., Milroy, D.A., Moss, S.H., Polycation-DNA complexes for gene delivery: a comparison of the biopharmaceutical properties of cationic polypeptides and cationic lipids (1998) J Control Release, 53, pp. 289-299; Mao, H.Q., Roy, K., Troung-Le, V.L., Janes, K.A., Lin, K.Y., Wang, Y., Chitosan-DNA nanoparticles as gene carriers: synthesis, characterization and transfection efficiency (2001) J Control Release, 70, pp. 399-421; Poole, B., Ohkuma, S., Effect of weak bases on the intralysosomal pH in mouse peritoneal-macrophages (1981) J Cell Biol, 90, pp. 665-669; Bowman, E.J., Siebers, A., Altendorf, K., Bafilomycins: a class of inhibitors of membrane ATPases from microorganisms, animal cells, and plant cells (1988) Proc Natl Acad Sci USA, 85, pp. 7972-7976; van Deurs, B., Holm, P.K., Sandvig, K., Inhibition of the vacuolar H+ATPase with bafilomycin reduces delivery of internalized molecules from mature multivesicular endosomes to lysosomes in HEp-2 cells (1996) Eur J Cell Biol, 69, pp. 343-350; Merdan, T., Kopecek, J., Kissel, T., Prospects for cationic polymers in gene and oligonucleotide therapy against cancer (2002) Adv Drug Deliv Rev, 54, pp. 715-758; Mansouri, S., Lavigne, P., Corsi, K., Benderdour, M., Beaumont, E., Fernandes, J.C., Chitosan-DNA nanoparticles as non-viral vectors in gene therapy: strategies to improve transfection efficacy (2004) Eur J Pharm Biopharm, 57, pp. 1-8; Erbacher, P., Zou, S.M., Bettinger, T., Steffan, A.M., Remy, J.S., Chitosan-based vector/DNA complexes for gene delivery: biophysical characteristics and transfection ability (1998) Pharm Res, 15, pp. 1332-1339; Kiang, T., Wen, J., Lim, H.W., Leong, K.W., The effect of the degree of chitosan deacetylation on the efficiency of gene transfection (2004) Biomaterials, 25, pp. 5293-5301; Ishii, T., Okahata, Y., Sato, T., Mechanism of cell transfection with plasmid/chitosan complexes (2001) BBA-Biomembranes, 1514, pp. 51-64; Lavertu, M., Methot, S., Tran-Khanh, N., Buschmann, M.D., High efficiency gene transfer using chitosan/DNA nanoparticles with specific combinations of molecular weight and degree of deacetylation (2006) Biomaterials, 27, pp. 4815-4824; de Smedt, S.C., Demeester, J., Hennink, W.E., Cationic polymer based gene delivery systems (2000) Pharm Res, 17, pp. 113-126; Kichler, A., Leborgne, C., Coeytaux, E., Danos, O., Polyethylenimine-mediated gene delivery: a mechanistic study (2001) J Gene Med, 3, pp. 135-144; Wattiaux, R., Laurent, N., Wattiaux-De Coninck, S., Jadot, M., Endosomes, lysosomes: their implication in gene transfer (2000) Adv Drug Deliv Rev, 41, pp. 201-208; Pelkmans, L., Helenius, A., Endocytosis via caveolae (2002) Traffic, 3, pp. 311-320; Felgner, P.L., Gadek, T.R., Holm, M., Roman, R., Chan, H.W., Wenz, M., Lipofection-a highly efficient, lipid-mediated DNA-transfection procedure (1987) Proc Natl Acad Sci USA, 84, pp. 7413-7417; Conner, S.D., Schmid, S.L., Regulated portals of entry into the cell (2003) Nature, 422, pp. 37-44; Koping-Hoggard, M., Tubulekas, I., Guan, H., Edwards, K., Nilsson, M., Varum, K.M., Chitosan as a nonviral gene delivery system. Structure-property relationships and characteristics compared with polyethylenimine in vitro and after lung administration in vivo (2001) Gene Ther, 8, pp. 1108-1121; Boussif, O., Zanta, M.A., Behr, J.P., Optimized galenics improve in vitro gene transfer with cationic molecules up to 1000-fold (1996) Gene Ther, 3, pp. 1074-1080
Keywords: article; beta galactosidase; Biocompatible Materials; Buffers; Cell Line; cell transport; Chemical structure; chitosan; coacervation; complex formation; controlled study; Cytotoxicity; Diffusion; DNA; Drug Carriers; Drug Compounding; endosome; Gene delivery; Gene transfer; genetic transfection; human; human cell; Humans; imidazole; Kidney; materials testing; nanomaterial; nanoparticle; priority journal; protein expression; proton transport; Tissue engineering; Transfection

Induction of notch signaling by immobilization of jagged-1 on self-assembled monolayers - Gonçalves, R.M.; Martins, M.C.L.; Almeida-Porada, G.; Barbosa, M.A. (BiomaterialsBiomaterials, 2009)
Notch signaling is a key mechanism during mammal development and stem cell regulation. This study aims to target and control Notch signaling by ligands immobilization using self-assembled monolayers (SAMs) as model surfaces. Non-fouling substrates were prepared by immersion of gold substrates in (1-Mercapto-11-undecyl)tetra(ethylene glycol) thiol solutions. These surfaces were activated with N,N′-carbonyldiimidazole (CDI) at different concentrations (0, 0.03, 0.3, 3 and 30 mg/ml) and an anti-human IgG, Fc specific fragment antibody (Ab) was covalently bound to EG4-SAMs to guarantee the correct exposure of the Notch ligand Jagged-1/Fc chimera (Jag-1). The presence of Ab and Jag-1 was confirmed by radiolabeling, X-ray photoelectron spectroscopy (XPS), ellipsometry and ELISA. The biological activity of Jag-1-Ab-SAMs was assessed by real-time PCR for Hes-1 family gene expression, a Notch pathway target gene, in HL-60 cell line. Results have shown an increase of the amount of immobilized Ab with increasing surface activator concentrations. Jag-1 concentration also increases with Ab concentration. Interestingly, a higher Jagged-1 exposure and fold increase in Hes-1 expression were obtained for surfaces activated with the lowest concentration of CDI (0.03 mg/ml). These results illustrate the great importance of ligands orientation and exposure, when compared with density. This investigation brings new insights into Notch signaling mechanisms. In particular, Jag-1-Ab-SAMs have shown to be adequate model surfaces to study Notch pathway activation and may provide a basis to develop new interfaces in biomaterials to control Notch mechanism in different cell systems. © 2009 Elsevier Ltd.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2009.09.010PubMed ID: 19783294Language of Original Document: EnglishCorrespondence Address: Gonçalves, R.M.; INEB, Biomaterials Division, NEWTherapies Group, R. Campo Alegre, 823, 4150-180 Porto, Portugal; email: raquelg@ineb.up.ptChemicals/CAS: Calcium-Binding Proteins; Gold, 7440-57-5; Immunoglobulin G; Intercellular Signaling Peptides and Proteins; Membrane Proteins; Receptors, Fc; Receptors, Notch; Recombinant Fusion Proteins; Serrate proteins, 134324-36-0References: Artavanis-Tsakonas, S., Rand, M.D., Lake, R.J., Notch signaling: cell fate control and signal integration in development (1999) Science, 284, pp. 770-776;Leong, K., Karsan, A., Recent insights in the role of notch signaling in tumorigenesis (2006) Blood, 107 (6), pp. 2223-2233; Chiba, S., Concise review: notch signaling in stem cell systems (2006) Stem Cells, 24, pp. 2437-2447; Lowell, S., Benchoua, A., Heavey, B., Smith, A.G., Notch promotes neural lineage entry by pluripotent embryonic stem cells (2006) PLoS Biol, 4 (5); Hellström, M.P.L., Hofmann, J.J., Wallgard, E., Coultas, L., Lindblom, P., Alva, J., Dll4 signalling through notch1 regulates formation of tip cells during angiogenesis (2007) Nature, 15 (445), pp. 776-780; Hofmeister, C., Zhang, J., Knight, K.L., Le, P., Stiff, P.J., Ex vivo expansion of umbilical cord blood stem cells for transplantation: growing knowledge from the hematopoietic niche (2007) Bone Marrow Transplant, 39 (1), pp. 11-23; Hilton, M., Tu, X., Wu, X., Bai, S., Zhao, H., Kobayashi, T., F. Notch signaling maintains bone marrow mesenchymal progenitors by suppressing osteoblast differentiation (2008) Nat Med, 14 (3), pp. 306-314; Stylianou, S., Clarke, R.B., Brennan, K., Aberrant activation of notch signaling in human breast cancer (2006) Cancer Res, 66 (3), pp. 1517-1525; Demarest, R., Ratti, F., Capobianco, A.J., It's T-ALL about notch (2008) Oncogene, 27 (38), pp. 5082-5091; Fre, S., Huyghe, M., Mourikis, P., Robine, S., Louvard, D., Artavanis-Tsakonas, S., Notch signals control the fate of immature progenitor cells in the intestine (2005) Nature, 16 (435), pp. 964-968; Fischer, A., Gessler, M., Delta-notch-and then? Protein interactions and proposed modes of repression by Hes and Hey bHLH factors (2007) Nucleic Acids Res, 35 (14), pp. 4583-4596; Zweidler-McKay, P.A., He, Y., Xu, L., Rodriguez, C.G., Karnell, F.G., Carpenter, A.C., Notch signaling is a potent inducer of growth arrest and apoptosis in a wide range of B-cell malignancies (2005) Blood, 106 (12), pp. 3898-3906; Beckstead, B., Santosa, D.M., Giachelli, C.M., Mimicking cell-cell interactions at the biomaterial-cell interface for control of stem cell differentiation (2006) J Biomed Mater Res, 79 A, pp. 94-103; Varnum-Finney, B., Wu, L., Yu, M., Brashem-Stein, C., Staats, S., Flowers, D., Immobilization of Notch ligand, Delta-1, is required for induction of notch signaling (2000) J Cell Sci, 113 (23), pp. 4313-4318; Delaney, C., Varnum-Finney, B., Aoyama, K., Brashem-Stein, C., Bernstein, I.D., Dose-dependent effects of the notch ligand delta1 on ex vivo differentiation and in vivo marrow repopulating ability of cord blood cells (2005) Blood, 106, pp. 2693-2699; Lefort, N., Bennea, C., Lelièvrea, J.D., Dorivala, C., Balboa, M., Sakanoc, S., Short exposure to notch ligand delta-4 is sufficient to induce T-cell differentiation program and to increase the T cell potential of primary human CD34+ cells (2006) Exp Hematol, 34, pp. 1720-1729; Taqvi, S., Dixit, L., Krishnendu, R., Biomaterial-based notch signaling for the differentiation of hematopoietic stem cells into T cells (2006) J Biomed Mater Res, 79 A, pp. 689-697; Bernstein, I., Delaney, C., Dallas, M., Heimfeld, S., Varnum-Finney, B., Notch signaling in hematopoiesis: implication for improving stem cell transplantation (2008) Biol Blood Marrow Transplant, 14, pp. 94-99; De Smedt, M., Hoebeke, I., Reyvoet, K., Leclercq, G., Plum, J., Different thresholds of Notch signaling bias human precursor cells toward B-, NK-, monocytic/dendritic-, or T-cell lineage in thymus microenvironment (2005) Blood, 106, pp. 3498-3506; Mrksich, M., What can surface chemistry do for cell biology? (2002) Curr Opin Chem Biol, 6, pp. 794-797; France, R., Short, R.D., Dawsonb, R.A., MacNeilb, S., Attachment of human keratinocytes to plasma copolymers of acrylic acid/octa-1,7-diene and allyl amine/octa-1,7-diene (1998) J Mater Chem, 81 (1), pp. 37-42; Neves, H., Weerkamp, F., Gomes, A.C., Naber, B., Gameiro, P., Becker, J.L., Effects of delta1 and jagged1 on early human hematopoiesis: correlation with expression of notch signaling-related genes in CD34+ Cells (2006) Stem Cells, 24, pp. 1328-1337; Sokolova, V., Epple, M., Inorganic nanoparticles as carriers of nucleic acids into cells (2008) Angewandte Chemie, 47, pp. 1382-1395; Yao, J., Duan, L., Fan, M., Yuan, J., Wu, X., Notch1 induces cell cycle arrest and apoptosis in human cervical cancer cells: involvement of nuclear factor kappa B inhibition (2007) Int J Gynecol Cancer, 17, pp. 502-510; Chadwick, N., Nostro, M.C., Baron, M., Mottram, R., Brady, G., Buckle, A., Notch signaling induces apoptosis in primary human CD34+ hematopoietic progenitor cells (2007) Stem Cells, 25, pp. 203-210; Love, J., Estroff, L.A., Kriebel, J.K., Nuzzo, R.G., Whitesides, G.M., Self-assembled monolayers of thiolates on metals as a form of nanotechnology (2005) Chem Rev, 105, pp. 1103-1169; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Ion beam deposition of Mn-Ir spin valves (1999) IEEE Trans Magn, 35, pp. 4361-4367; Martins, M.C.L., Ratner, B., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl- terminated self-assembled monolyers (2003) J Biomed Mater Res, 67 (A), pp. 158-171; Martins, M.C.L., Curtins, S.A., Freitas, S.C., Salgueiro, P., Ratner, B.D., Barbosa, M.A., Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide (2009) J Biomed Mater Res A, 88 (1), pp. 162-173; Barrias, C.C., Martins, M.C.L., Bidarra, S., Sá Miranda, M.C., Barbosa, M.A., Adsorption of a therapeutic enzyme to self-assembled monolayers: effect of the surface chemistry and solution pH on the amount and activity of adsorbed enzyme (2005) Biomaterials, 26, pp. 2695-2704; Iodine-125. A guide to radioiodination techniques. In: techniques I-Agtr, ed.: Little Chalfort: Amersham Life Science 1993Horbett, T., Techniques for protein adsorption studies (1986) Techniques of biocompatibility tests, pp. 183-214. , DF W. (Ed), CRC Press Inc, Harcover; Ohishi, K., Varnum-Finney, B., Bernstein, I.D., Delta-1 enhances marrow and thymus repopulating ability of human CD34+ CD38- cord blood cells (2002) J Clin Invest, 110, pp. 1165-1174; Li, L., Chen, S., Zheng, J., Ratner, B.D., Jiang, S., Protein adsorption on oligo(ethylene glycol)-terminated alkanethiolate self-assembled monolayers: the molecular basis for nonfouling behavior (2005) J Phys Chem B, 109 (7), pp. 2934-2941; Tohda, S., Murata-Ohsawa, M., Sakano, S., Nara, N., Notch ligands, Delta-1 and Delta-4 supress the self-renewal capacity and long-term growth of two myeloblastic leukemia cell lines (2003) Int J Oncol, 22 (5), pp. 1073-1079; Tohda, S.K.H., Murakami, N., Sakano, S., Nara, N., Diverse effects of the Notch ligands Jagged1 and Delta1 on the growth and differentiation of primary acute myeloblastic leukemia cells (2005) Exp Hematol, 33, pp. 558-563; Aoyama, K., Delaney, C., Varnun-Finney, B., Kohn, A.D., Moon, R.T., Bernstein, I.D., The interaction of the Wnt and notch pathways modulates natural killer versus T cell differentiation (2007) Stem Cells, 25, pp. 2488-2497; Beckstead B, Tung JC, Liang KJ, Tavakkol Z, Usui ML, Olerud JE, et al. Methods to promote notch signaling at the biomaterial interface and evaluation in a rafted organ culture model. J Biomed Mater Res A, in press. [Epub ahead of print]Semler, E., Dasgupta, A., Moghe, P.V., Cytomimetic engineering of hepatocyte morphogenesis and function by substrate-based presentation of acellular E-cadherin (2005) Tissue Eng, 11 (5-6), pp. 734-750; Zhao, Z., Matsui, H., Accurate immobilization of antibody-functionalized peptide nanotubes on protein-patterned arrays by optimizing their ligand-receptor interactions (2007) Small, 3 (8), pp. 1390-1393; Longo, G., Szleifer, Ligand-receptor interactions in tethered polymer layers (2005) Langmuir, 21, pp. 11342-11351; Gonçalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Protein adsorption and clotting time of pHEMA hydrogels modified with C18 ligands to adsorb albumin selectively and reversibly (2009) Biomaterials, 30 (29), pp. 5541-5551
Keywords: Activator concentration; Adequate models; Adsorption; Animals; article; Bioactivity; Biological activities; Biological materials; biomaterial; Calcium-Binding Proteins; Carbonyldiimidazole; Cell culture; Cell Line; Cell membranes; cell strain HL 60; Cell system; Chemical activation; Concentration (process); Concentration of; controlled study; Covalently bound; Ethylene; Ethylene Glycol; gene expression; gold; Gold substrates; HL-60 cell line; human; human cell; Human IgG; Humans; Immunoassay; immunoglobulin Fc fragment; Immunoglobulin G; immunoglobulin G antibody; Intercellular Signaling Peptides and Proteins; Jagged1; Ligands; Mammalia; Membrane Proteins; Model surface; Molecular Structure; Nanostructured materials; Nanostructured surfaces; Nonfouling; Notch receptor; Notch signaling; Photoelectron spectroscopy; priority journal; Protein adsorption; protein immobilization; Radiolabeling; Real-time PCR; Receptors, Fc; Receptors, Notch; Recombinant Fusion Proteins; Sams; self assembled monolayer; Self assembled monolayers; Self-assembled monolayers; signal transduction; Signaling; stem cell; Surface Properties; Target genes; Tetra; transcription factor HES 1; X ray photoelectron spectroscopy

Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide - Martins, M.C.L.; Curtin, S.A.; Freitas, S.C.; Salgueiro, P.; Ratner, B.D.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2009)
Systemic heparinization, used during haemodialysis to prevent blood clotting on the extracorporeal circuit, leads to a high incidence of hemorrhagic complications. The adverse reactions associated with heparin neutralization using protamine sulphate justify the development of an alternative system for blood deheparinization. The main objective of this work is to design nanostructured surfaces with the capacity to bind heparin from blood in a selective way. A heparin-binding polypeptide, composed of L-lysine and L-leucine (pKL), was synthesized and immobilized, in different concentrations, onto self-assembled monolayers (SAMs) terminated with tetra(ethylene-glycol) (EG4 SAMs). Immobilization was performed using a fixed concentration of pKL after surface activation to different degrees using a range of CDI (N,N′-carbonyldiimidazole) concentrations. Results demonstrated that the presence of pKL increases heparin adsorption to EG4-SAMs, independently of the pKL concentration and the way of immobilization (adsorption or covalent bound). Selectivity towards heparin was successfully achieved on SAMs with low concentrations of immobilized pKL (9-17% of pKL). Surfaces were characterized using ellipsometry, contact angle measurements, Fourier transform infrared reflection absorption spectroscopy (IRAS), atomic force microscopy, and X-ray photoelectron spectroscopy. Heparin adsorption was assessed using IRAS and N-sulphonate- 35S-heparin. Therefore, this study could give a good contribution for the design of blood deheparinization devices. © 2008 Wiley Periodicals, Inc.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31849PubMed ID: 18286636Language of Original Document: EnglishCorrespondence Address: Martins, M. C. L.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomaterials, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180, Porto, Portugal; email: cmartins@ineb.up.ptChemicals/CAS: carbonyldiimidazole, 530-62-1; heparin, 37187-54-5, 8057-48-5, 8065-01-8, 9005-48-5; imidazole, 1467-16-9, 288-32-4; leucine, 61-90-5, 7005-03-0; lysine, 56-87-1, 6899-06-5, 70-54-2; tetraethylene glycol, 112-60-7; Ethylene Glycol, 107-21-1; Heparin, 9005-49-6; Leucine, 61-90-5; Lysine, 56-87-1; PeptidesReferences: Dailey J. Blood. Ipswich, MA, USA: Medical Consulting Group; 1998Section, V., Chronic intermittent haemodialysis and prevention of clotting in the extracorporal system (2002) Nephrol Dialysis Transplant, 17, pp. 63-71;Zhang, Y.H., Singh, V.K., Yang, V.C., Novel approach for optimizing the capacity and efficacy of a protamine filter for clinical extracorporeal heparin removal (1998) Asaio J, 44, pp. M368-M373; Tao, W., Deyo, D.J., Brunston, R.L., Vertrees, R.A., Zwischenberger, J.B., Extracorporeal heparin adsorption following cardiopulmonary bypass with a heparin removal device - An alternative to protamine (1998) Critical Care Med, 26, pp. 1096-1102; Ameer, G.A., Barabino, G., Sasisekharan, R., Harmon, W., Cooney, C.L., Langer, R., Ex vivo evaluation of a Taylor-Couette flow, immobilized heparinase I device for clinical application (1999) Proc Natl Acad Sci USA, 96, pp. 2350-2355; Ostuni, E., Yan, L., Whitesides, G.M., The interaction of proteins and cells with self-assembled monolayers of alkanethiolates on gold and silver (1999) Colloids Surf B-Biointerfaces, 15, pp. 3-30; Mrksich, M., Whitesides, G.M., Using self-assembled monolayers that present oligo(ethylene glycol) groups to control the interactions of proteins with surfaces. Poly(Ethylene Glycol) (1997) ACS Symposium Series, 680, pp. 361-373; Cardin, A.D., Weintraub, H.J.R., Molecular modeling of proteinglycosaminoglycan interactions (1989) Arteriosclerosis, 9, pp. 21-32; Kricheldorf, H.R., (1987) α-Amino Acid N-Carboxyanhydrides and Related Heterocycles, , New York: Springer Verlag;; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methylterminated alkanethiols self-assembled monolayers (2003) J Biomed Mater Res A, 67, pp. 158-171; Lee, H.J., Nedelkov, D., Corn, R.M., Surface plasmon resonance imaging measurements of antibody arrays for the multiplexed detection of low molecular weight protein biomarkers (2006) Anal Chem, 78, pp. 6504-6510; Roeges, N.P.G., (1994) A Guide to the Complete Interpretation of Infrared Spectra of Organic Structures, , England: Wiley;; Li, L.Y., Chen, S.F., Zheng, J., Ratner, B.D., Jiang, S.Y., Protein adsorption on oligo(ethylene glycol)-terminated alkanethiolate self-assembled monolayers: The molecular basis for non-fouling behavior (2005) J Phys Chem B, 109, pp. 2934-2941; Beamson, G., High, B.D., (1992) Resolution XPS of Organic Polymers, , Chichester: Wiley;; Sousa, S.R., Moradas, F.P., Saramago, B., Viseu, M.L., Barbosa, M.A., Human serum albumin adsorption on TiO2 from single protein solutions and from plasma (2004) Langmuir, 20, pp. 9745-9754; Socrates, G., (2001) Infrared and Raman Characteristic Group Frequencies: Tables and Charts, , Chichester: Wiley;; Capila, I., Linhardt, R.J., Heparin - Protein interactions (2002) Angewandte Chemie-Int Ed, 41, pp. 391-112; Snell, C.R.F.G., Kinetics and thermodynamics of the alpha Helix - β Transconformation of poly(L-lysine) and L-leucine copolymers. A compensation phenomenon (1973) Biochemistry, 12, pp. 1017-1025; Hearn, M.T.W., 1,1′-Carbonyldiimidazole-mediated immobilization of enzymes and affinity ligands (1987) Methods Enzymol, 135, pp. 102-117; Stollner, D., Scheller, F.W., Warsinke, A., Activation of cellulose membranes with 1,1′-carbonyldiimidazole or 1-cyano-4-dimethylaminopyridinium tetrafluoroborate as a basis for the development of immunosensors (2002) Anal Biochem, 304, pp. 157-165
Keywords: Absorption spectroscopy; Adsorption; Alternative systems; Amines; Amino acids; Angle measurement; article; Atomic force microscopy; Atomic forces; Atomic spectroscopy; Binding peptides; Blood; Blood clotting; Carbonyl diimidazole; Carbonyldiimidazole; Contact angle; deheparinization; device; Dialysis; Electron energy levels; ellipsometry; Ethylene; Ethylene Glycol; Fourier Transform Infrared; Fourier transforms; Glycols; Haemodialysis; heparin; heparin binding protein; Heparinization; High incidences; Humans; imidazole; immobilization; infrared spectroscopy; leucine; Low concentrations; lysine; Methods; Missile bases; Monolayers; nanomaterial; Nanostructured surfaces; Nanostructures; Peptide immobilization; Peptides; Photoelectron spectroscopy; Polysaccharides; Protein adsorption; protein binding; Renal Dialysis; Self assembled monolayers; Self-assembled monolayers; Sulphate; Surface activations; Surface functionalization; Surface Properties; surface property; tetraethylene glycol; unclassified drug; X ray photoelectron spectroscopy; X-ray photoelectron spectroscopies

NPY signalling pathway in bone homeostasis: Y1 receptor as a potential drug target - Sousa, D.M.; Herzog, H.; Lamghari, M. (Current Drug TargetsCurr. Drug Targets, 2009)
Neuropeptide (NPY) is a neurotransmitter widely distributed in central and peripheral nervous system that has been implicated in several physiological processes through activation of five different Y receptors: Y1, Y2, Y4, Y5, and y6. NPY system has been extensively studied for the last decades due to its implications in a wide variety of physiological processes. For this purpose a diversity of sophisticated animal models and receptors agonists and antagonists has been developed to better understand its actions throughout body homeostasis. Consequently, NPY and its receptors have recently emerged as a potential regulator of bone homeostasis. This is supported by the demonstration of an increase of bone mass in mice lacking Y1 or Y2 receptor genes. Recent findings revealed Y1 receptor as a potential drug target candidate for prevention and treatment of bone loss. Indeed, it has been demonstrated that osteoblasts express Y1 receptor while no other Y receptor was detected in these cells, implicating Y1 receptor signalling in the local control of bone turnover. In this review, we have summarized the findings obtained from studies on NPY system in skeletogenesis focusing on Y1 receptor. © 2009 Bentham Science Publishers Ltd.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: CDTUAdoi: 10.2174/138945009787122888Language of Original Document: EnglishCorrespondence Address: Lamghari, M.; INEB - Instituto de Engenharia Biomédica, Universidade do Porto, NEWTherapies Group, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: lamghari@ineb.up.ptChemicals/CAS: gr 231118, 158859-98-4; n [1 [4 [[[[4 [(dimethylamino)methyl]cyclohexyl]methyl]amino]iminomethyl]benzyl] 2 oxo 2 (1 pyrrolidinyl)ethyl] alpha [(2 naphthalenylsulfonyl)amino]benzenepropanamide, 163238-19-5; n2 diphenylacetyl n (4 ureidomethylbenzyl)argininamide, 191868-14-1, 217977-06-5; nalpha (diphenylacetyl) n (4 hydroxybenzyl) dextro argininamide, 159013-54-4; neuropeptide Y, 82785-45-3, 83589-17-7; peptide YY, 81858-94-8; Ligands; Neuropeptide Y; Receptors, Neuropeptide YTradenames: bibo 3304; bibp 3226; gi 264879a; gr 231118; gw 1229; j 115814; ly 357897; sr 120819aReferences: Lundberg, P., Lerner, U.H., (2002) Microsc. Res. Tech, 58 (2), pp. 98-103;Baldock, P.A., Sainsbury, A., Couzens, M., Enriquez, R.F., Thomas, G.P., Gardiner, E.M., Herzog, H., (2002) J. Clin. Invest, 109 (7), pp. 915-921; Baldock, P.A., Allison, S., McDonald, M.M., Sainsbury, A., Enriquez, R.F., Little, D.G., Eisman, J.A., Herzog, H., (2006) J. Bone Miner. Res, 21 (10), pp. 1600-1607; Tatemoto, K., Carlquist, M., Mutt, V., (1982) Nature, 296 (5858), pp. 659-660; Tatemoto, K., (1982) Proc. Natl. Acad. Sci. U.S.A, 79 (18), pp. 5485-5489; Larhammar, D., (1996) Regul. Pept, 62, pp. 1-11; Tatemoto, K., (1982) Proc. Natl. Acad. Sci. U.S.A, 79 (8), pp. 2514-2518; Kimmel, J.R., Hayden, J., Pollock, H.G., (1975) J. Biol. Chem, 250 (24), pp. 9369-9376; Michel, M.C., Beck-Sickinger, A., Cox, H., Doods, H.N., Herzog, H., Larhammar, D., Quirion, R., Westfall, T., (1998) Pharmacol. Rev, 50 (1), pp. 143-150; Fuhlendorff, J., Johansen, N.L., Melberg, S.G., Thogersen, H., And Schwartz, T.W., (1990) J. Biol. Chem, 265 (20), pp. 11706-11712; Blundell, T.L., Pitts, J.E., Tickle, I.J., Wood, S.P., Wu, C.W., (1981) Proc. Natl. Acad. Sci. U.S.A, 78 (7), pp. 4175-4179; Cerdá-Reverter, J., Larhammar, D., (2000) Biochem. Cell Biol, 78 (3), pp. 371-392; Allen, J., Novotný, J., Martin, J., Heinrich, G., (1987) Proc. Natl. Acad. Sci. U.S A, 84 (8), pp. 2532-2536; Wan, C.P., Lau, B.H.S., (1995) Life Sci, 56 (13), pp. 1055-1064; Schwartz, T.W., Fuhlendorff, J., Kjems, L.L., Kristensen, M.S., Vervelde, M., O'Hare, M., Krstenansky, J.L., Bjornholm, B., (1990) Ann. N.Y. Acad. Sci, 611, pp. 35-47; Nordmann, A., Blommers, M.J.J., Fretz, H., Arvinte, T., Drake, A.F., (1999) Eur. J. Biochem, 261 (1), pp. 216-226; Minth, C.D., Bloom, S.R., Polak, J.M., Dixon, J.E., (1984) Proc. Natl. Acad. Sci. U.S.A, 81 (14), pp. 4577-4581; Chronwall, B.M., DiMaggio, D.A., Massari, V.J., Pickel, V.M., Ruggiero, D.A., O'Donohue, T.L., (1985) Neuroscience, 15 (4), pp. 1159-1181; Wai, S.M., Kindler, P.M., Lam, E.T., Zhang, A., Yew, D.T., (2004) Cell Mol. Neurobiol, 24 (5), pp. 667-684; Sundler, F., Böttcher, G., Ekblad, E., Hakanson, R., (1993) The Biology of Neuropeptide Y and Related Peptides, pp. 157-196. , Colmers, W.F. and Wahlestedt, C, Ed, Humana Press, New Jersey, pp; Ekblad, E., Hakanson, R., Sundler, F., (1984) Regul. Pept, 10 (1), pp. 47-55; Cavadas, C., Silva, A.P., Mosimann, F., Cotrim, M.D., Ribeiro, C.A.F., Brunner, H.R., Grouzmann, E., (2001) J. Clin. Endocrinol. Metab, 86 (12), pp. 5956-5963; Silva, A.P., Cavadas, C., Grouzmann, E., (2002) Clin. Chim. Acta, 326 (1-2), pp. 3-25; Strand, F.L., (1999) Neuropeptides: Regulators of Physiological Processes, , MIT Press: Cambridge; Ericsson, A., Schalling, M., McIntrye, K.R., Lundberg, J.M., Larhammar, D., Seroogy, K., Hokfelt, T., Persson, H., (1987) Proc. Natl. Acad. Sci. U.S.A, 84 (16), pp. 5585-5589; Yang, K., Guan, H., Arany, E., Hill, D.J., Cao, X., (2008) FASEB J, 22 (7), pp. 2452-2464; Pedrazzini, T., Pralong, F., Grouzmann, E., (2003) Cell Mol. Life Sci, 60 (2), pp. 350-377; Blomqvist, A.G., Herzog, H., (1997) Trends Neurosci, 20 (7), pp. 294-298; Berglund, M.M., Schober, D.A., Statnick, M.A., McDonald, P.H., Gehlert, D.R., (2003) J. Pharmacol. Exp. Ther, 306 (1), pp. 147-156; Berglund, M., Hipskind, P., Gehlert, D., (2005) NPY Family of Peptides in Immune Disorders, Inflammation, Angiogenesis and Cancer, pp. 29-62. , Zukowska, Z. and Feuerstein, G.Z, Ed, Birkhaeuser Verlag, Switzerland, pp; Larhammar, D., Salaneck, E., (2004) Neuropeptides, 38 (4), pp. 141-151; Gregor, P., Feng, Y., DeCarr, L.B., Cornfield, L.J., McCaleb, M.L., (1996) J. Biol. Chem, 271 (44), pp. 27776-27781; Starbäck, P., Wraith, A., Eriksson, H., Larhammar, D., (2000) Biochem. Biophys. Res. Commun, 277 (1), pp. 264-269; Wraith, A., Törnsten, A., Chardon, P., Harbitz, I., Chowdhary, B.P., Andersson, L., Lundin, L.G., Larhammar, D., (2000) Genome Res, 10 (3), pp. 302-310; Larhammar, D., Wraith, A., Berglund, M.M., Holmberg, S.K.S., Lundell, I., (2001) Peptides, 22 (3), pp. 295-307; Larhammar, D., Blomqvist, A., Yee, F., Jazin, E., Yoo, H., Wahlested, C., (1992) Proc. Natl. Acad. Sci. U.S.A, 267 (16), pp. 10935-10938; Herzog, H., Hort, Y.J., Ball, H.J., Hayes, G., Shine, J., Selbie, L.A., (1992) Proc. Natl. Acad. Sci. U.S.A, 89 (13), pp. 5794-5798; Mullins, D.E., Zhang, X., Hawes, B.E., (2002) Regul. Pept, 105 (1), pp. 65-73; Krause, J., Eva, C., Seeburg, P.H., Sprengel, R., (1992) Mol. Pharmacol, 41 (5), pp. 817-821; Eva, C., Keinanen, K., Monyer, H., Seeburg, P., Sprengel, R., (1990) FEBS J, 271 (1-2), pp. 81-84; Nakamura, M., Sakanaka, C., Aoki, Y., Ogasawara, H., Tsuji, T., Kodama, H., Matsumoto, T., Noma, M., (1995) J. Biol. Chem, 270 (50), pp. 30102-30110; Álvaro, A.R., Martins, J., Araújo, I.M., Rosmaninho-Salgado, J., Ambrósio, A.F., Cavadas, C., (2008) J. Neurochem, , Epub ahead of print; Herzog, H., Baumgartner, M., Vivero, C., Selbie, L.A., Auer, B., Shine, J., (1993) J. Biol. Chem, 268 (9), pp. 6703-6707; Marklund, U., Byström, M., Gedda, K., Larefalk, A., Juneblad, K., Nyström, S., Ekstrand, A.J., (2002) Mol. Cell Endocrinol, 188 (1-2), pp. 85-97; Ball, H.J., Shine, J., Herzog, H., (1995) J. Biol. Chem, 270 (45), pp. 27272-27276; Ferguson, S.S., (2001) Pharmacol. Rev, 53 (1), pp. 1-24; Okamoto, T., Schlegel, A., Scherer, P.E., Lisanti, M.P., (1998) J. Biol. Chem, 273 (10), pp. 5419-5422; Fabry, M., Langer, M., Rothen-Rutishauser, B., Wunderli-Allenspach, H., Höcker, H., Beck-Sickinger, A.G., (2000) Eur. J. Biochem, 267 (17), pp. 5631-5637; Parker, S.L., Kane, J.K., Parker, M.S., Berglund, M.M., Lundell, I.A., Li, M.D., (2001) Eur. J. Biochem, 268 (4), pp. 877-886; Gicquiaux, H., Lecat, S., Gaire, M., Dieterlen, A., Mély, Y., Takeda, K., Bucher, B., Galzi, J.L., (2002) J. Biol. Chem, 277 (8), pp. 6645-6655; Ouedraogo, M., Lecat, S., Rochdi, M.D., Hachet-Haas, M., Matthes, H., Gicquiaux, H., Verrier, S., Bucher, B., (2008) Traffic, 9 (3), pp. 305-324; Holliday, N.D., Lam, C.W., Tough, I.R., Cox, H.M., (2005) Mol. Pharmacol, 67 (3), pp. 655-664; Broberger, C., Visser, T.J., Kuhar, M.J., Hökfelt, T., (1999) Neuroendocrinology, 70 (5), pp. 295-305; Kopp, J., Xu, Z.Q., Zhang, X., Pedrazzini, T., Herzog, H., Kresse, A., Wong, H., Hökfelt, T., (2002) Neurosci, 111 (3), pp. 443-532; Larsen, P.J., Tang-Christensen, M., Stidsen, C.E., Madsen, K., Smith, M.S., Cameron, J.L., (1999) J. Clin. Endocrinol. Metab, 84 (10), pp. 3781-3791; Wharton, J., Gordon, L., Byrne, J., Herzog, H., Selbie, L.A., Moore, K., Sullivan, M.H., Polak, J.M., (1993) Proc. Natl. Acad. Sci. U.S.A, 90 (2), pp. 687-691; Feth, F., Rascher, W., Michel, M.C., (1992) Br. J. Pharmacol, 105 (1), pp. 71-76; DiMaggio, D.A., Farah Jr, J.M., Westfall, T.C., (1994) Endocrinology, 134 (2), pp. 719-727; Dumont, Y., Quirion, R., (2006) Progress in Inflammation Research, pp. 7-33. , Feuernstein, G. and Zukowska-Grojec, Z, Ed, Birkhaeuser Verlag, Switzerland, pp; Balasubramaniam, A., (2003) Curr. Pharm. Des, 9 (15), pp. 1165-1175; Fuhlendorff, J., Gether, U., Aakerlund, L., Langeland-Johansen, N., Thogersen, H., Melberg, S.G., Olsen, U.B., Schwartz, T.W., (1990) Proc. Natl. Acad. Sci. U.S.A, 87 (1), pp. 182-186; Grandt, D., Feth, F., Rascher, W., Reeve Jr., J.R., Schlicker, E., Schimiczek, M., Layer, P., Michel, M.C., (1994) Eur. J. Pharmacol, 269 (2), pp. 127-132; Söll, R.M., Dinger, M.C., Lundell, I., Larhammer, D., Beck-Sickinger, A.G., (2001) Eur. J. Biochem, 268 (10), pp. 2828-2837; Mullins, D., Kirby, D., Hwa, J., Guzzi, M., Rivier, J., Parker, E., (2001) Mol. Pharmacol, 60 (3), pp. 534-540; Rudolf, K., Eberlein, W., Engel, W., Wieland, H.A., Willim, K.D., Entzeroth, M., Wienen, W., Doods, H.N., (1994) Eur. J. Pharmacol, 271 (2-3), pp. R11-R13; Wieland, H.A., Engel, W., Eberlein, W., Rudolf, K., Doods, H.N., (1998) Br. J. Pharmacol, 125 (3), pp. 549-555; Daniels, A.J., Matthews, J.E., Slepetis, R.J., Jansen, M., Viveros, O.H., Tadepalli, A., Harrington, W., Spaltenstein, A., (1995) Proc. Natl. Acad. Sci. U.S.A, 92 (20), pp. 9067-9071; Schober, D.A., Van Abbema, A.M., Smiley, D.L., Bruns, R.F., Gehlert, D.R., (1998) Peptides, 19 (3), pp. 537-542; Balasubramaniam, A., Dhawan, V.C., Mullins, D.E., Chance, W.T., Sheriff, S., Guzzi, M., Prabhakaran, M., Parker, E.M., (2001) J. Med. Chem, 44 (10), pp. 1479-1482; Daniels, A.J., Chance, W.T., Grizzle, M.K., Heyer, D., Matthews, J.E., (2001) Peptides, 22 (3), pp. 483-491; Hipskind, P.A., Lobb, K.L., Nixon, J.A., Britton, T.C., Bruns, R.F., Catlow, J., Dieckman-McGinty, D.K., Gehlert, D.R., (1997) J. Med. Chem, 40 (23), pp. 3712-3714; Schneider, E., Keller, M., Brennauer, A., Hoefelschweiger, B.K., Gross, D., Wolfbeis, O.S., Bernhardt, G., Buschauer, A., (2007) ChemBioChem, 8 (16), pp. 1981-1988; Serradeil-Le, G.C., Valeet, G., Rouby, P.E., Pellet, A., Oury-Donat, F., Brossard, G., Lespy, L., LeFur, G., (1995) FEBS Lett, 362 (2), pp. 192-196; Kanatani, A., Hata, M., Mashiko, S., Ishihara, A., Okamoto, O., Haga, Y., Ohe, T., Ihara, M., (2001) Mol. Pharmacol, 59 (3), pp. 501-505; Wahlestedt, C., Håkanson, R., (1986) Med. Biol, 64 (2-3), pp. 85-88; Doods, H.N., Wieland, H.A., Engel, W., Eberlein, W., Willim, K.D., Entzeroth, M., Wienen, W., Rudolf, K., (1996) Regul. Pept, 65 (1), pp. 71-77; Gerald, C., Walker, M.W., Criscione, L., Gustafson, E.L., Batzl-Hartmann, C., Smith, K.E., Vaysse, P., Weinshank, R.L., (1996) Nature, 382 (6587), pp. 168-171; Lin, S., Boey, D., Herzog, H., (2004) Neuropeptides, 38 (4), pp. 189-200; Pedrazzini, T., (2004) Neuropeptides, 38 (4), pp. 267-275; Pedrazzini, T., Seydoux, J., Künstner, P., Aubert, J.F., Grouzmann, E., Beermann, F., Brunner, H.R., (1998) Nat. Med, 4 (6), pp. 722-726; Kushi, A., Sasai, H., Koizumi, H., Takeda, N., Yokoyama, M., Nakamura, M., (1998) Proc. Natl. Acad. Sci. U.S.A, 95 (26), pp. 15659-15664; Naveilhan, P., Canals, J.M., Arenas, E., Ernfors, P., (2001) J. Neurochem, 78 (6), pp. 1201-1207; Thiele, T.E., Koh, M.T., Pedrazzini, T., (2002) J. Neurosci, 22 (3), pp. RC208-RC214; Karlsson, R.M., Choe, J.S., Cameron, H.A., Thorsell, A., Crawley, J.N., Holmes, A., Heilig, M., (2008) Psychopharmacology (Berlin, Ger.), 195 (4), pp. 547-557; Wheway, J., Mackay, C.R., Newton, R.A., Sainsbury, A., Boey, D., Herzog, H., Mackay, F., (2005) J. Exp. Med, 202 (11), pp. 1527-1538; Zukowska-Grojec, Z., Karwatowska-Prokopczuk, E., Fisher, T.A., Ji, H., (1998) Regul. Pept, 75-76, pp. 231-238; Hansel, D.E., Eipper, B.A., Ronnett, G.V., (2001) Nature, 410 (6831), pp. 940-944; Howell, O.W., Doyle, K., Goodman, J.H., Scharfman, H.E., Herzog, H., Pringle, A., Beck-Sickinger, A.G., Gray, W.P., (2005) J. Neurochem, 93 (3), pp. 560-570; Cho, Y.R., Kim, C.W., (2004) Biochem. Biophys. Res. Commun, 314 (3), pp. 773-780; Milenkovic, I., Weick, M., Wiedemann, P., Reichenbach, A., Bringmann, A., (2004) Graefe's Arch. Clin. Exp. Ophthalmol, 242 (11), pp. 944-950; Anitha, M., Chandrasekharan, B., Salgado, J.R., Grouzmann, E., Mwangi, S., Sitaraman, S.V., Srinivasan, S., (2006) Gastroenterology, 131 (4), pp. 1164-1178; Doyle, K.L., Karl, T., Hort, Y., Duffy, L., Shine, J., Herzog, H., (2008) J. Neurochem, 105 (3), pp. 641-652; Jacques, D., Abdel-Samad, D., (2007) Can. J. Physiol. Pharmacol, 85 (1), pp. 43-53; Agasse, F., Bernardino, L., Kristiansen, H., Christiansen, S.H., Ferreira, R., Silva, B., Grade, S., Malva, J.O., (2008) Stem Cells, 26 (6), pp. 1636-1645; Movafagh, S., Hobson, J.P., Spiegel, S., Kleinman, H.K., Zukowska, Z., (2006) FASEB J, 20 (11), pp. 1924-1926; Ruscica, M., Dozio, E., Boghossian, S., Bovo, G., Riaño, V.M., Motta, M., Magni, P., (2006) Endocrinology, 147 (3), pp. 1466-1473; Seger, R., Krebs, E.G., (1995) FASEB J, 9 (9), pp. 726-735; Kholodenko, B.N., (2002) Trends Cell Biol, 12 (4), pp. 173-177; Eva, C., Serra, M., Mele, P., Panzica, G.C., Oberto, A., (2006) Front. Neuroendocrinol, 27 (3), pp. 308-339; Elefteriou, F., Bone Cell Mol (2005) Life Sci, 62 (19-20), pp. 2339-2349; Chenu, C., (2004) J. Musculoskcl. Neuron. Interact, 4 (2), pp. 132-134; Allison, S.J., Baldock, P.A., Herzog, H., (2007) Peptides, 28 (2), pp. 320-325; Bjurholm, A., Kreicbergs, A., Terenius, L., Goldstein, M., Schultzberg, M., (1988) J. Auton. Nerv. Syst, 25 (2-3), pp. 119-125; Hill, E.L., Elde, R., (1991) Cell Tissue Res, 264 (3), pp. 469-480; Ahmad, T., Ugarph-Morawski, A., Li, J., Bileviciute-Ljungar, I., Finn, A., Ostenson, C.G., Kreicbergs, A., (2004) Regul. Pept, 119 (1-2), pp. 61-67; Togari, A., Arai, M., Mizutani, S., Mizutani, S., Koshihara, Y., Nagatsu, T., (1997) Neurosci. Lett, 233 (2-3), pp. 125-128; Lundberg, P., Allison, S.J., Lee, N.J., Baldock, P.A., Brouard, N., Rost, S., Enriquez, R.F., Herzog, H., (2007) J. Biol. Chem, 282 (26), pp. 19082-19091; Baldock, P.A., Sainsbury, A., Allison, S., Lin, E.J., Couzens, M., Boey, D., Enriquez, R., Gardiner, E.M., (2005) J. Bone Miner. Res, 20 (10), pp. 1851-1857; Ducy, P., Schinke, T., Karsenty, G., (2000) Science, 289 (5484), pp. 1501-1504; Takeda, S., Karsenty, G., (2001) J. Bone Miner. Metab, 19 (3), pp. 195-198; Ducy, P., Amling, M., Takeda, S., Priemel, M., Schilling, A.F., Beil, F.T., Shen, J., Karsenty, G., (2000) Cell, 100 (2), pp. 197-207; Stephens, T.W., Basinski, M., Bristow, P.K., Bue-Valleskey, J.M., Burgett, S.G., Craft, L., Hale, J., Heiman, M., (1995) Nature, 377 (6549), pp. 530-532; Erickson, J.C., Hollopeter, G., Palmiter, R.D., (1996) Science, 274 (5293), pp. 1704-1707; Allison, S.J., Baldock, P., Sainsbury, A., Enriquez, R., Lee, N.J., Lin, E.J., Klugmann, M., Gardiner, E.M., (2006) J. Biol. Chem, 281 (33), pp. 23436-23444; Bjurholm, A., Kreicbergs, A., Schultzberg, M., Lerner, U.H., (1992) J. Bone Miner. Res, 7 (9), pp. 1011-1019; Bjurholm, A., Kreicbergs, A., Schultzberg, M., Lerner, U.H., (1998) Acta Physiol. Scand, 134 (3), pp. 451-462; Amano, S., Arai, M., Goto, S., Togari, A., (2007) Biochim. Biophys. Acta, 1770 (6), pp. 966-973; Baldock, P.A., Allison, S.J., Lundberg, P., Lee, N.J., Slack, K., Lin, E.J., Enriquez, R.F., Herzog, H., (2007) J. Biol. Chem, 282 (26), pp. 19092-19102
Keywords: 1 [1 [3 [(3 piperidyl)]]propyl] 2 [[(4 chlorophenoxyl)methyl]indol 3 yl] 2 (4 piperidylpiperidyl)ethan 1 one; 2 [1 (3 chloro 5 isopropoxycarbonylaminophenyl)ethylamino] 6 [2 (5 ethyl 4 methyl 2 thiazolyl)ethyl] 4 morpholinopyridine; 2 [1 (3 chloro 5 isopropyloxycarbonylaminophenyl)ethylamino] 6 [2 (5 ethyl 4 methyl 1,3 thiazol 2 yl)ethyl] 4 morpholinopyridine; Amino Acid Sequence; animal; Animals; bone development; bone mass; bone remodeling; Bone remodelling; bone turnover; Brain; drug antagonism; drug effect; drug potentiation; drug targeting; genetics; gi 264879a; gr 231118; Homeostasis; human; Humans; ligand; Ligands; ly 357897; metabolism; molecular genetics; Molecular Sequence Data; n alpha [3,3 bis(1 naphthyl)propionyl]dextro arginine n [1 benzyl 2 methoxyethyl]amide; n [1 [4 [[[[4 [(dimethylamino)methyl]cyclohexyl]methyl]amino]iminomethyl]benzyl] 2 oxo 2 (1 pyrrolidinyl)ethyl] alpha [(2 naphthalenylsulfonyl)amino]benzenepropanamide; n2 diphenylacetyl n (4 ureidomethylbenzyl)argininamide; nalpha (diphenylacetyl) n (4 hydroxybenzyl) dextro argininamide; neuropeptide Y; neuropeptide Y receptor; neuropeptide Y receptor agonist; neuropeptide Y receptor antagonist; neuropeptide Y [25 dextro arginine]; neuropeptide Y [26 dextro histidine]; neuropeptide Y [31 leucine 34 proline]; neuropeptide Y [6 arginine 34 proline]; neuropeptide Y [7 phenylalanine 34 proline]; neuropeptide Y1 receptor; neuropeptide Y2 receptor; neuropeptide Y4 receptor; neuropeptide Y5 receptor; neuropeptide Y6 receptor; nonhuman; osteoblast; osteoclast; osteolysis; peptide YY; peptide YY [31 leucine 34 proline]; peptide YY [34 proline]; pharmacological blocking; physiology; protein binding; protein expression; protein family; protein isolation; receptor intrinsic activity; Receptors, Neuropeptide Y; review; signal transduction; unclassified drug; Y1 receptor

Osteogenic differentiation of mesenchymal stem cells using PAMAM dendrimers as gene delivery vectors - Santos, J.L.; Oramas, E.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (Journal of Controlled ReleaseJ. Control. Release, 2009)
This paper reports the use of different generations of polyamidoamine (PAMAM) dendrimers for the in vitro transfection of mesenchymal stem cells (MSCs). A systematic study was carried out on the transfection efficiency achieved by the PAMAM dendrimers using a β-galactosidase reporter gene system. Transfection results were shown to be dependent upon the generation of dendrimers, the amine to phosphate group ratio and the cell passage number. In all cases, the transfection efficiency was very low. Nevertheless, it was hypothesized that a low transfection level could be sufficient to promote the in vitro differentiation of MSCs towards the osteoblastic lineage. To address this possibility, dendrimers carrying the human bone morphogenetic protein-2 (hBMP-2) gene-containing plasmid were used. All quantitative (alkaline phosphatase activity, osteocalcin secretion and calcium deposition) and qualitative (von Kossa staining) osteogenic markers were significantly stronger in transfected cells when compared to non-transfected ones. This study not only clearly demonstrates that a low transfection level can be sufficient for inducing in vitro differentiation of MSCs to the osteoblast phenotype but also highlights the importance of focusing research on the development of gene delivery vectors in the concrete application. © 2008 Elsevier B.V. All rights reserved.
Cited By (since 1996): 29Export Date: 21 November 2012Source: ScopusCODEN: JCREEdoi: 10.1016/j.jconrel.2008.11.007PubMed ID: 19070635Language of Original Document: EnglishCorrespondence Address: Tomás, H.; Centro de Química da Madeira, Departamento de Química, Universidade da Madeira, Campus Universitario da Penteada, 9000-390 Funchal, Portugal; email: lenat@uma.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; calcium, 14092-94-5, 7440-70-2; osteocalcin, 136461-80-8; phosphate, 14066-19-4, 14265-44-2; BMP2 protein, human; Bone Morphogenetic Protein 2; Dendrimers; PAMAM Starburst; Polyamines; beta-Galactosidase, 3.2.1.23References: Dai, J., Rabie, A.B.M., Hagg, U., Xu, R.A., Alternative gene therapy strategies for the repair of craniofacial bone defects (2004) Curr. Gene Ther., 4 (4), pp. 469-485;Gersbach, C.A., Phillips, J.E., Garcia, A.J., Genetic engineering for skeletal regenerative medicine (2007) Annu. Rev. Biomed. Eng., 9, pp. 87-119; Kofron, M.D., Laurencin, C.T., Orthopaedic applications of gene therapy (2005) Curr. Gene Ther., 5 (1), pp. 37-61; Kofron, M.D., Laurencin, C.T., Bone tissue engineering by gene delivery (2006) Adv. Drug Deliv. Rev., 58 (4), pp. 555-576; Luo, J., Sun, M.H., Kang, Q., Peng, Y., Jiang, W., Luu, H.H., Luo, Q., He, T.C., Gene therapy for bone regeneration (2005) Curr. Gene Ther., 5 (2), pp. 167-179; Partridge, K.A., Oreffo, R.O., Gene delivery in bone tissue engineering: progress and prospects using viral and nonviral strategies (2004) Tissue Eng., 10 (1-2), pp. 295-307; Turgeman, G., Aslan, H., Gazit, Z., Gazit, D., Cell-mediated gene therapy for bone formation and regeneration (2002) Curr. Opin. Mol. Ther., 4 (4), pp. 390-394; Chen, Y., Cheung, K.M.C., Kung, H.F., Leong, J.C.Y., Lu, W.W., Luk, K.D.K., In vivo new bone formation by direct transfer of adenoviral-mediated bone morphogenetic protein-4 gene (2002) Biochem. Biophys. Res. Commun., 298 (1), pp. 121-127; Lieberman, J.R., Daluiski, A., Stevenson, S., Wu, L., McAllister, P., Lee, Y.P., Kabo, J.M., Witte, O.N., The effect of regional gene therapy with bone morphogenetic protein-2-producing bone-marrow cells on the repair of segmental femoral defects in rats (1999) J. Bone Joint Surg. Am., 81 (7), pp. 905-917; Park, J., Ries, J., Gelse, K., Kloss, F., von der Mark, K., Wiltfang, J., Neukam, F.W., Schneider, H., Bone regeneration in critical size defects by cell-mediated BMP-2 gene transfer: a comparison of adenoviral vectors and liposomes (2003) Gene Ther., 10 (13), pp. 1089-1098; Riew, K.D., Wright, N.M., Cheng, S.L., Avioli, L.V., Lou, J., Induction of bone formation using a recombinant adenoviral vector carrying the human BMP-2 gene in a rabbit spinal fusion model (1998) Calcif. Tissue Int., 63 (4), pp. 357-360; Tsuda, H., Wada, T., Ito, Y., Uchida, H., Dehari, H., Nakamura, K., Sasaki, K., Hamada, H., Efficient BMP2 gene transfer and bone formation of mesenchymal stem cells by a fiber-mutant adenoviral vector (2003) Mol. Ther., 7 (3), pp. 354-365; De Laporte, L., Cruz Rea, J., Shea, L.D., Design of modular non-viral gene therapy vectors (2006) Biomaterials, 27 (7), pp. 947-954; Eliyahu, H., Barenholz, Y., Domb, A.J., Polymers for DNA delivery (2005) Molecules, 10 (1), pp. 34-64; Roth, C.M., Sundaram, S., Engineering synthetic vectors for improved DNA delivery: insights from intracellular pathways (2004) Annu. Rev. Biomed. Eng., 6, pp. 397-426; Corsi, K., Chellat, F., Yahia, L., Fernandes, J.C., Mesenchymal stem cells, MG63 and HEK293 transfection using chitosan-DNA nanoparticles (2003) Biomaterials, 24 (7), pp. 1255-1264; Hamm, A., Krott, N., Breibach, I., Blindt, R., Bosserhoff, A.K., Efficient transfection method for primary cells (2002) Tissue Eng., 8 (2), pp. 235-245; Lakshmipathy, U., Pelacho, B., Sudo, K., Linehan, J.L., Coucouvanis, E., Kaufman, D.S., Verfaillie, C.M., Efficient transfection of embryonic and adult stem cells (2004) Stem Cells, 22 (4), pp. 531-543; Kim, S.W., Ogawa, T., Tabata, Y., Nishimura, I., Efficacy and cytotoxicity of cationic-agent-mediated nonviral gene transfer into osteoblasts (2004) J. Biomed. Mater. Res. A, 71 (2), pp. 308-315; Dufes, C., Uchegbu, I.F., Schatzlein, A.G., Dendrimers in gene delivery (2005) Adv. Drug Deliv. Rev., 57 (15), pp. 2177-2202; Guillot-Nieckowski, M., Eisler, S., Diederich, F., Dendritic vectors for gene transfection (2007) New J. Chem., 31 (7), pp. 1111-1127; Svenson, S., Tomalia, D.A., Dendrimers in biomedical applications-reflections on the field (2005) Adv. Drug Deliv. Rev., 57 (15), pp. 2106-2129; Haensler, J., Szoka, F.C., Polyamidoamine cascade polymers mediate efficient transfection of cells in culture (1993) Bioconjug. Chem., 4 (5), pp. 372-379; Choi, J.S., Nam, K., Park, J., Kim, J.B., Lee, J.K., Park, J., Enhanced transfection efficiency of PAMAM dendrimer by surface modification with l-arginine (2004) J. Control. Release, 99 (3), pp. 445-456; Kono, K., Akiyama, H., Takahashi, T., Takagishi, T., Harada, A., Transfection activity of polyamidoamine dendrimers having hydrophobic amino acid residues in the periphery (2005) Bioconjug. Chem., 16 (1), pp. 208-214; KukowskaLatallo, J.F., Bielinska, A.U., Johnson, J., Spindler, R., Tomalia, D.A., Baker, J.R., Efficient transfer of genetic material into mammalian cells using Starburst polyamidoamine dendrimers (1996) Proc. Natl. Acad. Sci. U. S. A., 93 (10), pp. 4897-4902; Gebhart, C.L., Kabanov, A.V., Evaluation of polyplexes as gene transfer agents (2001) J. Control. Release, 73 (2), pp. 401-416; Aubin, J.E., Osteoprogenitor cell frequency in rat bone marrow stromal populations: role for heterotypic cell-cell interactions in osteoblast differentiation (1999) J. Cell. Biochem., 72 (3), pp. 396-410; Lennon, D.P., Haynesworth, S.E., Young, R.G., Dennis, J.E., Caplan, A.I., A chemically-defined medium supports in-vitro proliferation and maintains the osteochondral potential of rat marrow-derived mesenchymal stem-cells (1995) Exp. Cell Res., 219 (1), pp. 211-222; Bielinska, A.U., Chen, C.L., Johnson, J., Baker, J.R., DNA complexing with polyamidoamine dendrimers: implications for transfection (1999) Bioconjug. Chem., 10 (5), pp. 843-850; Eichman, J.D., Bielinska, A.U., Kukowska-Latallo, J.F., Baker Jr., J.R., The use of PAMAM dendrimers in the efficient transfer of genetic material into cells (2000) Pharm. Sci. Technol. Today, 7, pp. 232-245; Haleem-Smith, H., Derfoul, A., Okafor, C., Tuli, R., Olsen, D., Hall, D.J., Tuan, R.S., Optimization of high-efficiency transfection of adult human mesenchymal stem cells in vitro (2005) Mol. Biotechnol., 30 (1), pp. 9-19; Fischer, D., Li, Y.X., Ahlemeyer, B., Krieglstein, J., Kissel, T., In vitro cytotoxicity testing of polycations: influence of polymer structure on cell viability and hemolysis (2003) Biomaterials, 24 (7), pp. 1121-1131; Jevprasesphant, R., Penny, J., Jalal, R., Attwood, D., McKeown, N.B., D'Emanuele, A., The influence of surface modification on the cytotoxicity of PAMAM dendrimers (2003) Int. J. Pharm., 252 (1-2), pp. 263-266; Wilke, M., Fortunati, E., vandenBroek, M., Hoogeveen, A.T., Scholte, B.J., Efficacy of a peptide-based gene delivery system depends on mitotic activity (1996) Gene Ther., 3 (12), pp. 1133-1142; Xie, Y.B., Yang, S.T., Kniss, D.A., Three-dimensional cell-scaffold constructs promote efficient gene transfection: implications for cell-based gene therapy (2001) Tissue Eng., 7 (5), pp. 585-598; Yamagiwa, H., Endo, N., Tokunaga, K., Hayami, T., Hatano, H., Takahashi, H.E., In vivo bone-forming capacity of human bone marrow-derived stromal cells is stimulated by recombinant human bone morphogenetic protein-2 (2001) J. Bone Miner. Metab., 19 (1), pp. 20-28; Chaudhari, A., Ron, E., Rethman, M.P., Recombinant human bone morphogenetic protein-2 stimulates differentiation in primary cultures of fetal rat calvarial osteoblasts (1997) Mol. Cell. Biochem., 167 (1-2), pp. 31-39; Hay, E., Hott, M., Graulet, A.M., Lomri, A., Marie, P.J., Effects of bone morphogenetic protein-2 on human neonatal calvaria cell differentiation (1999) J. Cell. Biochem., 72 (1), pp. 81-93; Yamaguchi, A., Regulation of differentiation pathway of skeletal mesenchymal cells in cell-lines by transforming growth-factor-beta superfamily (1995) Semin. Cell Biol., 6 (3), pp. 165-173; Yamaguchi, A., Ishizuya, T., Kintou, N., Wada, Y., Katagiri, T., Wozney, J.M., Rosen, V., Yoshiki, S., Effects of BMP-2, BMP-4, and BMP-6 on osteoblastic differentiation of bone marrow-derived stromal cell lines, ST2 and MC3T3-G2/PA6 (1996) Biochem. Biophys. Res. Commun., 220 (2), pp. 366-371; Baltzer, A.W.A., Lattermann, C., Whalen, J.D., Wooley, P., Weiss, K., Grimm, M., Ghivizzani, S.C., Evans, C.H., Genetic enhancement of fracture repair: healing of an experimental segmental defect by adenoviral transfer of the BMP-2 gene (2000) Gene Ther., 7 (9), pp. 734-739; Wang, E.A., Rosen, V., Dalessandro, J.S., Bauduy, M., Cordes, P., Harada, T., Israel, D.I., Wozney, J.M., Recombinant human bone morphogenetic protein induces bone-formation (1990) Proc. Natl. Acad. Sci. U. S. A., 87 (6), pp. 2220-2224; Chuang, C.K., Sung, L.Y., Hwang, S.M., Lo, W.H., Chen, H.C., Hu, Y.C., Baculovirus as a new gene delivery vector for stem cell engineering and bone tissue engineering (2007) Gene Ther., 14 (19), pp. 1417-1424; Aslan, H., Zilberman, Y., Arbeli, V., Sheyn, D., Matan, Y., Liebergall, M., Li, J.Z., Gazit, Z., Nucleofection-based ex vivo nonviral gene delivery to human stem cells as a platform for tissue regeneration (2006) Tissue Eng., 12 (4), pp. 877-889; Noel, D., Gazit, D., Bouquet, C., Apparailly, F., Bony, C., Plence, P., Millet, V., Jorgensen, C., Short-term BMP-2 expression is sufficient for in vivo osteochondral differentiation of mesenchymal stem cells (2003) Stem Cells, 22 (1), pp. 74-85
Keywords: alkaline phosphatase; amine; Amines; animal cell; Animals; article; beta galactosidase; beta-Galactosidase; Bone; Bone morphogenetic protein; bone morphogenetic protein 2; Bone Regeneration; Calcium; Cell culture; cell differentiation; Cell Line; cell lineage; cell survival; Cells; Cells, Cultured; controlled study; dendrimer; Dendrimers; embryo; enzyme activity; Flowcharting; gene expression; Gene transfer; Gene Transfer Techniques; gene vector; Genes, Reporter; genetic transfection; human; human cell; Humans; in vitro study; Kidney; male; Mesenchymal stem cell; Mesenchymal Stem Cells; nonhuman; Nonviral gene delivery; nonviral gene delivery system; Nucleic acids; osteoblast; osteocalcin; Osteogenesis; PAMAM dendrimers; phosphate; plasmid; Plasmids; polyamidoamine; Polyamines; priority journal; protein secretion; Proteins; qualitative analysis; quantitative analysis; rat; Rats; Rats, Wistar; reporter gene; staining

Physical, chemical and in vitro biological profile of chitosan hybrid membrane as a function of organosiloxane concentration - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Costa, M.A.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2009)
We attempted to prepare chitosan-silicate hybrid for use in a medical application and evaluated the physico-chemical properties and osteocompatibility of the hybrids as a function of γ-glycidoxypropyltrimethoxysilane (GPTMS) concentration. Chitosan-silicate hybrids were synthesized using GPTMS as the reagent for cross-linking of the chitosan chains. Fourier transform infrared spectroscopy, 29Si CP-MAS NMR spectroscopy and the ninhydrin assay were used to analyze the structures of the hybrids, and stress-strain curves were recorded to estimate their Young's modulus. The swelling ability, contact angle and cytocompatibility of the hybrids were investigated as a function of the GPTMS concentration. A certain fraction of GPTMS in each hybrid was linked at the epoxy group to the amino group of chitosan, which was associated with the change in the methoxysilane group of GPTMS due to hybridization. The cross-linking density was around 80% regardless of the volume of GPTMS. As the content of GPTMS increased, the water uptake decreased and the hydrophilicity of the hybrids increased except when the content exceeded amolar ratio of 1.5, when it caused a decrease. The values of the mechanical parameters assessed indicated that significant stiffening of the hybrids was obtained by the addition of GPTMS. The adhesion and proliferation of the MG63 osteoblast cells cultured on the chitosan-GPTMS hybrid surface were improved compared to those on the chitosan membrane, regardless of the GPTMS concentration. Moreover, human bone marrow osteoblast cells proliferated on the chitosan-GPTMS hybrid surface and formed a fibrillar extracellular matrix with numerous calcium phosphate globular structures, both in the presence and in the absence of dexamethasone. Therefore, the chitosan-GPTMS hybrids are promising candidates for basic materials that can promote bone regeneration because of their controllable composition (chitosan/GPTMS ratio). © 2008 Acta Materialia Inc.
Cited By (since 1996): 10Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2008.07.022PubMed ID: 18722166Language of Original Document: EnglishCorrespondence Address: Hayakawa, S.; Biomaterial Laboratory, Graduate School of Natural Science and Technology, Okayama University, Tsushima, Okayama-shi, 700-8530, Japan; email: satoshi@cc.okayama-u.ac.jpChemicals/CAS: (3 glycidyloxypropyl)trimethoxysilane, 2530-83-8; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; chitosan, 9012-76-4; silicate, 12627-13-3; Chitosan, 9012-76-4; Cross-Linking Reagents; gamma-glycidoxypropyltrimethoxysilane, 2530-83-8; Silanes; SiloxanesTradenames: AldrichReferences: Lai, J.Y., Lin, F.C., Wang, C.C., Wang, D.M., Effect of nonsolvent additives on the porosity and morphology of asymmetric TPX membranes [J] (1996) J Membrane Sci, 118, pp. 49-61;Wang, D.M., Lin, F.C., Chiang, J.C., Lai, J.Y., Control of porosity of asymmetric TPX membranes [J] (1998) J Membrane Sci, 141, pp. 1-12; Piattelli, A., Scarano, A., Russo, P., Matarasso, S., Evaluation of guided bone regeneration in rabbit tibia using bioresorbable and non-resorbable membranes (1996) Biomaterials, 17 (8), pp. 791-796; Gotfredsen, K., Nimb, L., Hjorting-Hansen, E., Immediate implant placement using a biodegradable barrier, polyhydroxybutyratehydroxyvalerate reinforced with polyglactin 910: an experimental study in dogs (1994) Clin Oral Implants Res, 5 (2), pp. 83-91; Kostopoulos, L., Karring, T., Augmentation of the rat mandible using guided tissue regeneration (1994) Clin Oral Implants Res, 5 (2), pp. 75-82; Kostopoulos, L., Karring, T., Guided bone regeneration in mandibular defects in rats using a bioresorbable polymer (1994) Clin Oral Implants Res, 5 (2), pp. 666-674; Nyman, S., Gottlow, J., Karring, T., The regeneration potential of the periodontal ligament: an experimental study in the monkey (1982) J Clin Periodontal, 9, pp. 257-265; Dupoirieux, L., Pourquier, D., Picot, M.C., Neves, M., Comparative study of three different membranes for guided bone regeneration of rat cranial defects (2001) Int J Oral Maxillofac Surg, 30 (1), pp. 58-62; Zhang, R., Ma, P.X., Porous poly(l-lactic acid)/apatite composites created by biomimetic process (1999) J Biomed Mater Res, 45, pp. 285-293; Murphy, W.L., Kohn, D.H., Mooney, D.J., Growth of continuous bonelike mineral within porous poly(lactide-co-glycolide) scaffolds in vitro (2000) J Biomed Mater Res, 50, pp. 50-58; Lin, F.C., Wang, D.M., Lai, J.Y., Asymmetric TPX membranes. J membranes with high gas flux. (1996) J Membrane Sci, 110, pp. 25-36; Vert, M., Mauduit, J., Li, S., Biodegradation of PLA/GA polymers: increasing complexity (1994) Biomaterials, 15, pp. 1209-1213; Lee, Y.K., Mooney, D.J., Hydrogels for tissue enigineering (2001) Chem Rev, 101, pp. 1869-1879; Domard, A., Rinaudo, M., Preparation and characterization fully deacetylated chitosan (1983) Int J Biol Macromol, 5, pp. 49-52; Chandy, T., Sharma, P.C., Chitosan - as a biomaterial (1990) Biomater Artif Cells Artif Organo, 18, pp. 1-24; Ueno, H., Yamada, H., Tanaka, I., Kaba, N., Matsuura, M., Okumura, M., Accelerating effects of chitosan for healing at early phase of experimental open wound in dogs (1999) Biomaterials, 20, pp. 1407-1414; Muzzareli, R.A.A., Mattioli-Belmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Stimulatory effect on bone formation exerted by a modified chitosan (1994) Biomaterials, 15, pp. 1075-1081; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., In vitro cytocompatibility of MG63 cells on chitosan-organosiloxane hybrid membranes (2005) Biomaterials, 26, pp. 485-493; Prochazkova, S., Varum, K.M., Æstgaard. Quantitative determination of chitosans by ninhydrin (1999) Carbohydr Polym, 38, pp. 115-122; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II: effect of ascorbic acid, β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Coelho, M.J., Cabral, A.T., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part I: osteoblastic differentiation of serially passaged human bone marrow cells cultured in α-MEM and in D-MEM (2000) Biomaterials, 21, pp. 1087-1094; Berridge, V., Tan, A.S., Characterization of the cellular reduction of 3-(4,5-dimethhylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT): subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch Biochem Biophys, 303, pp. 474-482; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Argüelles-Monal, W., Desbriéres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Sol-gel preparation and in vitro deposition of apatite on porous gelatin-siloxane hybrids (2001) J Non Cryst Solid, 285, pp. 116-122; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Novel approach to fabricate porous gelatin-siloxane hybrids for bone tissue engineering (2002) Biomaterials, 23, pp. 4765-4773; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Incorporation of Ca 2+ ions in gelatin-siloxane hybrids through a sol-gel process (2001) J Ceram Soc Jpn, 109, pp. 403-408; Rashidova, S.S.h., Shakarova, D.S.h., Ruzimuradov, O.N., Satabaldieva, D.T., Zalyalieva, S.V., Shpigun, O.A., Bionanocompositional chitosan-silica sorbent for liquid chromatography (2004) J Chromatogr B, 800, pp. 49-53; Hench, L.L., Ethridge, E.C., (1982) Biomaterials an interfacial approach, , Academic Press, New York 10; Xynos, I.D., Hukkanen, M.V.J., Batten, J.J., Buttery, L.D., Hench, L.L., Polak, J.M., Bioglass ® 45S5 stimulates osteoblast turnover and enhances bone formation in vitro: implications and applications for bone tissue engineering (2000) Calcif Tissue Int, 67, pp. 321-329; Xynos, I.D., Edgar, A.J., Buttery, L.D.K., Hench, L.L., Ionic products of bioactive glass dissolution increase proliferation of human osteoblasts and induce insulin-like growth factor II mRNA expression and protein synthesis (2000) Biochem Biophys Res Commun, 276, pp. 461-465; Gough, J.E., Jones, J.R., Hench, L.L., Nodule formation and mineralisation of human primary osteoblasts cultured on a porous bioactive glass scaffold (2004) Biomaterials, 25, pp. 2039-2046; Maniatopoulos, C., Sodek, J., Melcher, A., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Fernandes, M.H., Costa, M.A., Carvalho, G.S., Mineralization in serially passaged human alveolar bone cells (1997) J Mater Sci Mater Med, 8, pp. 61-65; Costa, M.A., Gutierres, M., Almeida, L., Lopes, M.A., Santos, J.D., Fernandes, M.H., In vitro mineralization of human bone marrow cells cultured on Bonelike ® (2004) Key Eng Mater, 254-256, pp. 821-824
Keywords: (3 glycidyloxypropyl)trimethoxysilane; article; assay; Biocompatibility; Bone Marrow Cells; calcium phosphate; cell adhesion; Cell Line, Tumor; cell proliferation; cell survival; cell viability; Chemical analysis; chitosan; concentration (parameters); controlled study; cross linking; Cross-Linking Reagents; extracellular matrix; human; human cell; Humans; hydrophobicity; in vitro study; infrared spectroscopy; Magnetic Resonance Spectroscopy; Microscopy, Electron, Scanning; molecular hybridization; Nuclear magnetic resonance spectroscopy; Organic-inorganic hybrid; osteoblast; Osteoblasts; Osteocompatibility; physical chemistry; priority journal; Silanes; silicate; siloxane; Siloxanes; Spectrophotometry, Ultraviolet; Spectroscopy, Fourier Transform Infrared; stress strain relationship; structure analysis; surface property; Tissue engineering; unclassified drug; water transport; γ-Glycidoxypropyltrimethoxysilane (GPTMS)

Prediction of neonatal acidemia by computer analysis of fetal heart rate and ST event signals - Costa, A.; Ayres-de-Campos, D.; Costa, F.; Santos, C.; Bernardes, J. (American Journal of Obstetrics and GynecologyAm. J. Obstet. Gynecol., 2009)
Objective: The objective of the study was to evaluate the accuracy of computer analysis of fetal heart rate (FHR) and ST event signals in prediction of neonatal acidemia. Study Design: One hundred forty-eight FHR tracings were evaluated to identify red alerts provided by the system, based on automated analysis of FHR and ST event signals, and compared with the occurrence of umbilical artery acidemia (pH ≤7.05). Results: The presence of red alerts obtained sensitivity of 1.00 (95% confidence interval [CI], 0.56-1.00), specificity of 0.94 (95% CI, 0.89-0.97), positive predictive value (PPV) of 0.47 (95% CI, 0.22-0.72), negative predictive value (NPV) of 1 (95% CI, 0.96-1.00), positive likelihood ratio (PLR) of 17.6 (95% CI, 9.0-34.5), and negative likelihood ratio (NLR) of 0. When limiting analysis to red alerts that did not include ST data, sensitivity was 0.57 (95% CI, 0.20-0.88), specificity was 0.97 (95% CI, 0.92-0.99), PPV was 0.50 (95% CI, 0.17-0.82), NPV was 0.98 (95% CI, 0.93-0.99), PLR was 20.14 (95% CI, 6.3-64.2), and NLR was 0.44 (95% CI, 0.19-1.04). Conclusion: Computer analysis of FHR and ST event signals provide higher accuracy in predicting neonatal academia. © 2009 Mosby, Inc. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: AJOGAdoi: 10.1016/j.ajog.2009.04.033PubMed ID: 19539895Language of Original Document: EnglishCorrespondence Address: Costa, A.; Departamento de Ginecologia e Obstetrícia, Faculdade de Medicina, Hospital S. JoãoPortugal; email: cosantonia@gmail.comReferences: (2006) Perinatal Mortality Surveillance 2004: England, Wales, and Northern Ireland, , CEMACH (Confidential Enquiry into Maternal and Child Health), Confidential Enquiry into Maternal and Child Health, London, UK;(1997) 4th annual report, , CESDI (Confidential Enquiry into Stillbirths and Deaths in Infancy), Maternal and Child Health Research Consortium, London, UK; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310; Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-165; Bernardes, J., Costa-Pereira, A., Ayres-de-Campos, D., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57, pp. 33-37; Donker, D.K., van Geijn, H.P., Hasman, A., Interobserver variation in the assessment of fetal heart rate recordings (1993) Eur J Obstet Gynecol Reprod Biol, 52, pp. 21-28; Neilson, J.P., Fetal electrocardiogram (ECG) for fetal monitoring during labour (2006) Cochrane Database Syst Rev, 3; Doria, V., Papageorghiou, A., Gustafsson, A., Ugwumadu, A., Farrer, K., Arulkumaran, S., Review of the first 1502 cases of ECG-ST waveform analysis during labour in a teaching hospital (2007) BJOG, 114, pp. 1202-1207; Westerhuis, M., Kwee, A., van Ginkel, A., Drogtrop, A., Gyselaers, W., Visser, G., Limitations of ST analysis in clinical practice: three cases of intrapartum metabolic acidosis (2007) BJOG, 114, pp. 1194-1201; Amer-Wahlin, I., Arulkumaran, S., Hagberg, H., Marsal, K., Visser, G., Fetal electrocardiogram: ST waveform analysis in intrapartum surveillance (2007) BJOG, 114, pp. 1191-1193; Dawes, G.S., Redman, C.W., Smith, J.H., Improvements in the registration and analysis of fetal heart rate records at the bedside (1985) Br J Obstet Gynaecol, 92, pp. 317-325; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: the antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118, pp. 52-60. , SisPorto Multicentre Validation Study Group; Dawes, G.S., Moulden, M., Redman, C.W.G., System 8000: computerized antenatal FHR analysis (1991) J Perinat Med, 19, pp. 47-51; Bernardes, J., Moura, C., Marques-de-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sá, J.P., Pereira-Leite, L., SisPorto 2.0-a program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Ayres-de-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto® 3.5-a central fetal monitoring station with online alerts based on computerized cardiotocogram+S.T.event analysis (2008) J Perinat Med, 36, pp. 260-264; Ayres-de-Campos, D., Bernardes, J., Kwee, A., Westehuis, M., Visser, G.H.A., Computer quantification of short-term variability as an adjunct to fetal electrocardiographic monitoring (2007) BJOG, 114, pp. 1446-1447; Downing, J.W., Houlton, P.C., Barclay, A., Extradural analgesia for cesarean section: a comparison with general anesthesia (1979) Br J Anaesth, 51, pp. 367-374; Crawford, J.S., James, F.M., Davies, P., Crawley, M., A further study of general anaesthesia for cesarean section (1976) Br J Anaesth, 48, pp. 661-667; Huch, A., Huch, C., Rooth, G., Guidelines for blood sampling and measurement of pH and blood gas values in obstetrics (1994) Eur J Obstet Gynecol Reprod Biol, 54, pp. 165-175; ACOG technical bulletin. Umbilical artery blood acid-base analysis (1996) Int J Gynecol Obstet, 52, pp. 305-310; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: a time for quality data (1994) Br J Obstet Gynaecol, 101, pp. 1054-1063; Low, J.A., Intrapartum fetal asphyxia: definition, diagnosis and classification (1997) Am J Obstet Gynecol, 176, pp. 957-959; Fleiss, J.L., (1981) Statistical methods for rates and proportions. 2nd ed., , John Wiley & Sons, New York, NY Section 5.6; Keith, R.D., Beckley, S., Garibaldi, J.M., Westgate, J.A., Ifeachor, E.C., Greene, K.R., A multicentre comparative study of 17 experts and an intelligent computer system for managing labour using cardiotocogram (1995) Br J Obstet Gynecol, 102, pp. 668-700; Chung, T.K., Mohajer, M.P., Yang, Z.j., Chang, A.M., Sahota, D.S., The prediction of fetal acidosis at birth by computerised analysis of intrapartum cardiotocography (1995) Br J Obstet Gynaecol, 102, pp. 454-460; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., Computer assessment of the intrapartum cardiotocogram. II. The value of computer assessment compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464; Policy statement. The Apgar score-American Academy of Pediatrics and American College of Obstetricians and Gynecologists (2006) Pediatrics, 117, pp. 1444-1447; Casey, B.M., McIntire, D.D., Leveno, K.J., The continuing value of the Apgar score for the assessment of the newborn infants (2001) N Engl J Med, 334, pp. 467-471; Moster, D., Lie, R.T., Irgens, L.M., Bjerkedal, T., Markestad, The association of Apgar score with subsequent death and cerebral palsy: a population-based study in term infants (2001) J Pediatr, 138, pp. 798-803
Keywords: acidemia; Acidosis; article; autoanalysis; Cardiotocography; computer analysis; computer assisted; computer prediction; Diagnosis, Computer-Assisted; diagnostic value; Electrocardiography; Female; Fetal heart rate; Fetal hypoxia; Fetal monitoring; fetus electrocardiography; fetus heart rate; Heart Rate, Fetal; human; Humans; Infant, Newborn; major clinical study; male; newborn; newborn acidosis; observational study; pH; Predictive Value of Tests; priority journal; Prospective Studies; prospective study; Reproducibility of Results; sensitivity and specificity; signal transduction; ST segment; umbilical artery

Role of vascular endothelial growth factor in the communication between human osteoprogenitors and endothelial cells - Grellier, M.; Ferreira-Tojais, N.; Bourget, C.; Bareillke, R.; Guillemot, F.; Amédée, J. (Journal of Cellular BiochemistryJ. Cell. Biochem., 2009)
Proper bone remodeling requires an active process of angiogenesis which in turn supplies the necessary growth factors and stem cells. This tissue cooperation suggests a cross-talk between osteoblasts and endothelial cells. This work aims to identify the role of paracrine communication through vascular endothelial growth factor (VEGF) in co-culture between osteoblastic and endothelial cells. Through a well defined direct contact co-culture model between human osteoprogenitors (HOPs) and human umbilical vein endothelial cells (HUVECs), we observed that HUVECs were able to migrate along HOPs, inducing the formation of specific tubular-like structures. VEGF 165 gene expression was detected in the HOPs, was up-regulated in the co-cultured HOPs and both Fit-1 and KDR gene expression increased in co- cultured HUVECs. However, the cell rearrangement observed in co-culture was promoted by a combination of soluble chemoattractive factors and not by VEGF 165 alone. Despite having no observable effect on endothelial cell tubular-like formation, VEGF appeared to have a crucial role in osteoblastic differentiation since the inhibition of its receptors reduced the co-culture-stimulated osteoblastic phenotype. This co-culture system appears to enhance both primary angiogenesis events and osteoblastic differentiation, thus allowing for the development of new strategies in vascularized bone tissue engineering. © 2009 Wiley-Liss, Inc.
Cited By (since 1996): 32Export Date: 21 November 2012Source: ScopusCODEN: JCEBDdoi: 10.1002/jcb.22018Language of Original Document: EnglishCorrespondence Address: Grellier, M.; 146 Rue Leo Saignat, Zone Nord, Bat 4A, Case 45, F-33076 Bordeaux Cedex, France; email: maritie.grellier@inserm.frMolecular Sequence Numbers: GENBANK: AB021221, AF063657, AF063658, BC015690, BC021289, NM_000089;Chemicals/CAS: vasculotropin A, 489395-96-2; vasculotropin receptor, 301253-48-5; Receptors, Vascular Endothelial Growth Factor, EC 2.7.1.112; RNA, Messenger; Vascular Endothelial Growth Factor AReferences: Bordenave, L., Baquey, C., Bareille, R., Lefebvre, F., Lauroua, C., Guerin, V., Rouais, F., Anderson, J.M., Endothelial cell compatibility testing of three different Pellethanes (1993) J Biomed Mater Res, 27, pp. 1367-1381;Bouletreau, P.J., Warren, S.M., Spector, J.A., Peled, Z.M., Gerrets, R.P., Greenwald, J.A., Longaker, M.T., Hypoxia and VEGF up-regulate BMP-2 mRNA and protein expression in microvascular endothelial cells: Implications for fracture healing (2002) Plast Reconstr Surg, 109, pp. 2384-2397; Carano, R.A., Filvaroff, E.H., Angiogenesis and bone repair (2003) Drug Discov Today, 8, pp. 980-989; Carmeliet, P., Collen, D., Molecular basis of angiogenesis. Role of VEGF and VE-cadherin (2000) Ann NY Acad Sci, 902, pp. 249-262. , discussion 262-264; Clarkin, C.E., Emery, R.J., Pitsillides, A.A., Wheeler-Jones, C.P., Evaluation of VEGF-mediated signaling in primary human cells reveals a paracrine action for VEGF in osteoblast-mediated crosstalk to endothelial cells (2007) J Cell Physiol, 214, pp. 437-444; Cross, M.J., Claesson-Welsh, L., FGF and VEGF function in angiogenesis: Signalling pathways, biological responses and therapeutic inhibition (2001) Trends Pharmacol Sci, 22, pp. 201-207; Cross, M.J., Dixelius, J., Matsumoto, T., Claesson-Welsh, L., VEGF-receptor signal transduction (2003) Trends Biochem Sci, 28, pp. 488-494; Dallas, S.L., Rosser, J.L., Mundy, G.R., Bonewald, L.F., Proteolysis of latent transforming growth factor-beta (TGF-beta)-binding protein-1 by osteoclasts. A cellular mechanism for release of TGF-beta from bone matrix (2002) J Biol Chem, 277, pp. 21352-21360; Ferrara, N., Gerber, H.P., LeCouter, J., The biology of VEGF and its receptors (2003) Nat Med, 9, pp. 669-676; Fiedler, J., Leucht, F., Waltenberger, J., Dehio, C., Brenner, R.E., VEGF-A and P1GF-1 stimulate chemotactic migration of human mesenchymal progenitor cells (2005) Biochem Biophys Res Commun, 334, pp. 561-568; Gerber, H.P., Ferrara, N., Angiogenesis and bone growth (2000) Trends Cardiovasc Med, 10, pp. 223-228; Gerhardt, H., Golding, M., Fruttiger, M., Ruhrberg, C., Lundkvist, A., Abramsson, A., Jeltsch, M., Betsholtz, C., VEGF guides angiogenic sprouting utilizing endothelial tip cell filopodia (2003) J Cell Biol, 161, pp. 1163-1177; Guillotin, B., Bourget, C., Remy-Zolgadri, M., Bareille, R., Fernandez, P., Conrad, V., Amedee-Vilamitjana, J., Human primary endothelial cells stimulate human osteoprogenitor cell differentiation (2004) Cell Physiol Biochem, 14, pp. 325-332; Guillotin, B., Bareille, R., Bourget, C., Bordenave, L., Amedee, J., Interaction between human umbilical vein endothelial cells and human osteoprogenitors triggers pleiotropic effect that may support osteoblastic function (2008) Bone, 42, pp. 1080-1091; Jaffe, E.A., Culture of human endothelial cells (1980) Transplant Proc, 12, pp. 49-53; Lamalice, L., Le Boeuf, F., Huot, J., Endothelial cell migration during angiogenesis (2007) Circ Res, 100, pp. 782-794; Lampugnani, M.G., Orsenigo, F., Gagliani, M.C., Tacchetti, C., Dejana, E., Vascular endothelial cadherin controls VEGFR-2 internalization and signaling from intracellular compartments (2006) J Cell Biol, 174, pp. 593-604; Lebrin, F., Deckers, M., Bertolino, P., Ten Dijke, P., TGF-beta receptor function in the endothelium (2005) Cardiovasc Res, 65, pp. 599-608; Mayr-Wohlfart, U., Waltenberger, J., Hausser, H., Kessler, S., Gunther, K.P., Dehio, C., Puhl, W., Brenner, R.E., Vascular endothelial growth factor stimulates chemotactic migration of primary human osteoblasts (2002) Bone, 30, pp. 472-477; Miralem, T., Steinberg, R., Price, D., Avraham, H., VEGF(165) requires extracellular matrix components to induce mitogenic effects and migratory response in breast cancer cells (2001) Oncogene, 20, pp. 5511-5524; Neufeld, G., Cohen, T., Gengrinovitch, S., Poltorak, Z., Vascular endothelial growth factor (VEGF) and its receptors (1999) FASEB J, 13, pp. 9-22; Ortega, N., Behonick, D., Stickens, D., Werb, Z., How proteases regulate bone morphogenesis (2003) Ann NY Acad Sci, 995, pp. 109-116; Rousseau, S., Houle, F., Huot, J., Integrating the VEGF signals leading to actin-based motility in vascular endothelial cells (2000) Trends Cardiovasc Med, 10, pp. 321-327; Sorrell, J.M., Baber, M.A., Caplan, A., Human dermal fibroblast subpo- pulations; differential interactions with vascular endothelial cells in coculture: Nonsoluble factors in the extracellular matrix influence interactions (2008) Wound Repair Regen, 16, pp. 300-309; Street, J., Bao, M., deGuzman, L., Bunting, S., Peale Jr., F.V., Ferrara, N., Steinmetz, H., Filvaroff, E.H., Vascular endothelial growth factor stimulates bone repair by promoting angiogenesis and bone turnover (2002) Proc Natl Acad Sci USA, 99, pp. 9656-9661; Suarez, S., Ballmer-Hofer, K., VEGF transiently disrupts gap junctional communication in endothelial cells (2001) J Cell Sci, 114, pp. 1229-1235; Sun, L., Vitolo, M., Passaniti, A., Runt-related gene 2 in endothelial cells: Inducible expression and specific regulation of cell migration and invasion (2001) Cancer Res, 61, pp. 4994-5001; Unger, R.E., Sartoris, A., Peters, K., Motta, A., Migliaresi, C., Kunkel, M., Bulnheim, U., Kirkpatrick, C.J., Tissue-like self-assembly in cocultures of endothelial cells and osteoblasts and the formation of microcapillary-like structures on three-dimensional porous biomaterials (2007) Biomaterials, 28, pp. 3965-3976; Villars, F., Bordenave, L., Bareille, R., Amedee, J., Effect of human endothelial cells on human bone marrow stromal cell phenotype: Role of VEGF? (2000) J Cell Biochem, 79, pp. 672-685; Villars, F., Guillotin, B., Amedee, T., Dutoya, S., Bordenave, L., Bareille, R., Amedee, J., Effect of HUVEC on human osteoprogenitor cell differentiation needs heterotypic gap junction communication (2002) Am J Physiol Cell Physiol, 282, pp. C775-C785; Walker, D.L., Vacha, S.J., Kirby, M.L., Lo, C.W., Connexin43 deficiency causes dysregulation of coronary vasculogenesis (2005) Dev Biol, 284, pp. 479-498; Wang, H., Keiser, J.A., Vascular endothelial growth factor upregulates the expression of matrix metalloproteinases in vascular smooth muscle cells: Role of flt-1 (1998) Circ Res, 83, pp. 832-840; Wang, D.S., Miura, M., Demura, H., Sato, K., Anabolic effects of 1,25- dihydroxyvitamin D3 on osteoblasts are enhanced by vascular endothelial growth factor produced by osteoblasts and by growth factors produced by endothelial cells (1997) Endocrinology, 138, pp. 2953-2962; Xin, X., Yang, S., Ingle, G., Zlot, C., Rangell, L., Kowalski, J., Schwall, R., Gerritsen, M.E., Hepatocyte growth factor enhances vascular endothelial growth factor-induced angiogenesis in vitro and in vivo (2001) Am J Pathol, 158, pp. 1111-1120
Keywords: angiogenesis; article; Cell Communication; cell contact; Cell culture; cell differentiation; cell migration; cell motion; Cell Movement; Cells, Cultured; Co-culture; coculture; Coculture Techniques; controlled study; cytology; Endothelial Cells; endothelium cell; Enzyme Activation; gene expression; gene expression regulation; genetics; human; human cell; Human stem cells; human tissue; Humans; Humulus; messenger RNA; metabolism; Microscopy, Electron, Scanning; Migration; nucleotide sequence; osteoblast; Osteoblasts; Osteogenesis; paracrine signaling; phenotype; priority journal; Receptors, Vascular Endothelial Growth Factor; RNA, Messenger; Scanning electron microscopy; secretion; stem cell; umbilical cord; umbilical vein; upregulation; Vascular Endothelial Growth Factor A; vasculotropin 165; vasculotropin A; vasculotropin receptor; vasculotropin receptor 1; vasculotropin receptor 2; Vegf

Selective protein adsorption modulates platelet adhesion and activation to oligo(ethylene glycol)-terminated self-assembled monolayers with C18 ligands - Gonçalves, I.C.; Martins, M.C.L.; Barbosa, M.A.; Naeemi, E.; Ratner, B.D. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2009)
This study focuses on the selective binding of albumin to a nanostructured surfaces to inhibit other blood proteins from adsorbing thereby reducing platelet adhesion and activation. Tetra (ethylene-glycol)-terminated self- assembled monolayers (EG4 SAMs) with different percentages of CI 8 ligands on the surface were characterized by contact angle measurements, X-ray photoelectron microscopy, infrared reflection-absorption spectroscopy, and ellipsometry. A specific surface (2.5% C18 SAM) was found to be selective for human serum albumin (HSA) in the presence of both albumin and fibrinogen (HFG). The importance of this concentration of C18 ligands was stressed in reversibility studies since that surface exchanged almost all the preadsorbed HSA by HSA in solution, but not by HFG. The effect of protein adsorption in the subsequent adhesion and activation of platelets was studied by pre-immersing the surfaces in albumin and plasma before contact with platelets. Scanning electron microscopy and glutaraldehyde induced fluorescence technique images showed that as surfaces got more hydrophobic due to the immobilization of C18 ligands, the number of adherent platelets increased and their morphology changed from round to fully spread. Pre-immersion in HSA led to an 80°/o decrease in platelet adhesion and reduction of activation. Pre-immersion in 1% plasma was only relevant in 2.5% CI 8 SAMs since this was the only surface that demonstrated less adhesion of platelets comparing with buffer pre-immersion. However, they still adsorb more platelets then when HSA was preadsorbed. This was confirmed in competition studies between HSA and plasma that suggested that other plasma proteins were also adsorbing to this surface. © 2008 Wiley Periodicals, Inc.
Cited By (since 1996): 11Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32011PubMed ID: 18442116Language of Original Document: EnglishCorrespondence Address: Gonçalves, I. C.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Universidade do Porto, Run do Campo Alegre, 823, 4150-180 Porto, Portugal; email: icastro@ineb.up.ptChemicals/CAS: fibrinogen, 9001-32-5; glutaraldehyde, 111-30-8, 37245-61-7; human serum albumin, 9048-49-1; Carbon, 7440-44-0; Ethylene Glycol, 107-21-1; Ligands; Serum AlbuminReferences: Nath, N., Hyun, J., Ma, H., Chilkoti, A., Surface engineering strategies for control of protein and cell interactions (2004) Surf Sci, 570, pp. 98-110;Mao, C., Qiu, Y.Z., Sang, H.B., Mei, H., Zhu, A.P., Shen, J., Lin, S.C., Various approaches to modify biomaterial surfaces for improving hemocompatibility (2004) Adv Colloid Interface Sci, 110, pp. 5-17; Gorbet, M.B., Sefton, M.V., Biomaterial-associated thrombosis: Roles of coagulation factors, complement, platelets and leukocytes (2004) Biomaterials, 25, pp. 5681-5703; Kottkemarchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., Effect of albumin coating on the in vitro blood compatibility of dacron arterial prostheses (1989) Biomaterials, 10, pp. 147-155; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., Alkyl substituted polymers with enhanced albumin affinity (1981) Trans Am Soc Artif Intern Organs, 27, pp. 499-503; Eberhart, R.C., Munro, M.S., Williams, G.B., Kulkarni, P.V., Shannon, W.A., Brink, B.E., Fry, W.J., Albumin adsorption and retention on C-18-alkyl-derivatized polyurethane vascular grafts (1987) Artif Organs, 11, pp. 375-382; Frautschi, J.R., Munro, M.S., Lloyd, D.R., Eberhart, R.C., Alkyl derivatized cellulose-acetate membranes with enhanced albumin affinity (1983) Trans Am Soc Artif Intern Organs, 29, pp. 242-244; Pitt WG, Cooper SL. Albumin adsorption on alkyl chain derivatized polyurethanes. I. The effect of C-18 alkylation. T Biomed Mater Res 1988;22:359-382Johnston, E., Ratner, B.D., Protein Adsorption: Friend or Foe? (1998) Immobilized biomolecules in analysis: A practical approach, pp. 79-94. , Cass T, Ligler FS, editors, Oxford: Oxford University Press;; Ji, J., Feng, L.X., Barbosa, M.A., Stearyl poly(ethylene oxide) grafted surfaces for preferential adsorption of albumin (2001) Biomaterials, 22, pp. 3015-3023; Martins, M.C.L., Naeemi, E., Ratner, B.D., Barbosa, M.A., Albumin adsorption on cibacron blue F3G-A immobilized onto oligo (ethylene glycol)-terminated self-assembled monolayers (2003) J Mater Sci Mater Med, 14, pp. 945-954; Sigal, G.B., Mrksich, M., Whitesides, G.M., Effect of surface wettability on the adsorption of proteins and detergents (1998) J Am Chem Soc, 120, pp. 3464-3473; Palegrosdemange, C., Simon, E.S., Prime, K.L., Whitesides, G.M., Formation of self-assembled monolayers by chemisorption of derivatives of oligo(ethylene glycol) of structure Hs(Ch2)11 (Och2ch2)meta-Oh on gold (1991) J Am Chem Soc, 113, pp. 12-20; Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Protein adsorption on 18-alkyl chains immobilized on hydroxyl-ter- minated self-assembled monolayers (2005) Biomaterials, 26, pp. 3891-3899; Martins MCL, Ratner BD, Barbosa MA. Protein adsorption on mixtures of hydroxyl- and methylterminated alkanethiols self-assembled monolavers. I Biomed Mater Res 2003;67A: 158-171Owens, D.K., Wendt, R.C., Estimation of surface free energy of polymers (1969) J Appl Polym Sci, 13, pp. 1741-1747; Sousa, S.R., Moradas Ferreira, P., Saramago, B., Viseu Melo, L., Barbosa, M.A., Human serum albumin adsorption on TiO 2 from single protein solutions and from plasma (2004) Langmuir, 20, pp. 9745-9754; Sastry, M., A note on the use of ellipsometry for studying the kinetics of formation of self-assembled monolayers (2000) Bull Mater Sci, 23, pp. 159-163; Rodrigues, S.N., Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ralner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27, pp. 5357-5367; Frank, R.D., Dresbach, H., Thelen, H., Sieberth, H.G., Glutardialde- hyde induced fluorescence technique (GIFT): A new method for the imaging of platelet adhesion on biomaterials (2000) J Biomed Mater Res, 52, pp. 374-381; Herrwerth, S., Eck, W., Reinhardt, S., Grunze, M., Factors that determine the protein resistance of oligoether self-assembled monolayers-internal hydrophilicity, terminal hydrophilicity, and lateral packing density (2003) J Am Chem Soc, 125, pp. 9359-9366; Harder, P., Grunze, M., Dahint, R., Whitesides, G.M., Laibinis, P.E., Molecular conformation in oligo(ethylene glycol)-terminated self-assembled monolayers on gold and silver surfaces deter-mines their ability to resist protein adsorption (1998) J Phys Chem B, 102, pp. 426-436; Schwendel, D., Dahint, R., Herrwerth, S., Schloerholz, M., Eck, W., Grunze, M., Temperature dependence of the protein resistance of poly- and oligo(ethylene glycol)-terminated alkanethiolate monolayers (2001) Langmuir, 17, pp. 5717-5720; Zhu, B., Eurell, T., Gunawan, R., Leckband, D., Chain-length dependence of the protein and cell resistance of oligo(ethylene glycol)-terminated self-assembled monolayers on gold (2001) J Biomed Mater Res, 56, pp. 406-416; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) J Am Chem Soc, 111, pp. 321-335; Jenney, C.R., Anderson, J.M., Adsorbed serum proteins responsible for surface dependent human macrophage behavior (1999) J Biomed Mater Res, 49, pp. 435-447; Sperling, C., Schweiss, R.B., Streller, U., Werner, C., In vitro hemocompatibility of self-assembled monolayers displaying various functional groups (2005) Biomaterials, 26, pp. 6547-6557; Barbosa, J.N., Barbosa, M.A., Aguas, A.P., Inflammatory responses and cell adhesion to self-assembled monolayers of alkanethio- lates on gold (2004) Biomaterials, 25, pp. 2557-2563
Keywords: Absorption spectroscopy; Acoustic microscopes; Adhesion; Adsorption; Albumin; Aldehydes; Angle measurement; article; Biological materials; Biomaterials; Blood Platelets; Blood protein; Blood substitutes; Carbon; Cell Shape; chemical composition; Concentration of; Contact angle; controlled study; Ethylene; Ethylene Glycol; ethylene glycol derivative; fibrinogen; Fluorescence technique; glutaraldehyde; gold nanoparticle; human; human serum albumin; Human serum albumins; Humans; hydrophobicity; Infrared reflection absorption spectroscopy; infrared spectroscopy; ligand; Ligands; Nanostructured surface; normal human; Oligo(ethylene glycol); Photoelectron spectroscopy; plasma; Plasma diagnostics; Plasma protein; Plasmas; Platelet adhesion; Platelet Adhesiveness; Platelets; Protein adsorption; protein binding; Proteins; Sams; Scanning electron microscopy; Selective binding; Selective protein adsorption; self assembled monolayer; Self assembled monolayers; Self-assembled monolayers; Serum Albumin; Specific surface; Spectrophotometry, Infrared; Surface Properties; surface property; thrombocyte activation; thrombocyte adhesion; thrombocyte shape; X ray photoelectron spectroscopy; X-ray photoelectron microscopy

Sex differences in linear and complex fetal heart rate dynamics of normal and acidemic fetuses in the minutes preceding delivery - Bernardes, J.; Gonçalves, H.; Ayres-de-Campos, D.; Rocha, A.P. (Journal of Perinatal MedicineJ. Perinat. Med., 2009)
Aim: To assess linear and complex heart rate dynamics in relation to fetal gender in normal and acidemic fetuses during the minutes preceding delivery. Methods: Linear and non-linear fetal heart rate indices, namely mean FHR, long-term irregularity index, short-term variability, low and high frequency spectral indices, approximate and sample entropy, were assessed in 36 female and 30 male fetuses, adjusted for gestational age and weight, during the minutes preceding delivery. Analysis was performed in the initial and final minutes of each tracing in fetuses with umbilical artery blood pH at delivery ≥7.20, 7.11-7.19 and ≤7.10. Results: Progression of labor was associated with a significant decrease in non-linear indices and an increase in almost all linear indices, both in female and male fetuses, but changes were more marked in female fetuses. Non-acidemic females showed higher mean FHR in the final minutes of labor, compared with males. Acidemic females had higher linear indices when compared to similar male fetuses. Conclusions: During the minutes preceding delivery, female fetuses express higher linear indices than male fetuses, suggesting greater activation of the autonomic nervous system, while maintaining similar complexity indices, which suggests different reaction and adaptation capabilities to stress and distress. © 2009 by Walter de Gruyter.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: JPEMAdoi: 10.1515/JPM.2009.024PubMed ID: 19021459Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Faculdade de Medicina, Universidade Do Porto, Ginecologia e Obstetrícia, Al. Hernani Monteiro, Porto, 4200, Portugal; email: jbernardes59@gmail.comReferences: Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310;Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sà, J.P., Pereira-Leite, L., SisPorto 2.0 - a program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., SisPorto Multicentre Validation Study Group. Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118, pp. 52-60; Ayres-de-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto 3.5 - a central fetal monitoring station with online alerts based on computerized cardio-tocogram+ST event analysis (2008) J Perinat Med, 36, pp. 260-264; Beckers, F., Verheyden, B., Aubert, A.E., Aging and non-linear heart rate control in a healthy population (2006) Am J Physiol Heart Circ Physiol, 290, pp. H2560-H2570; Bekedam, D.J., Engelsbel, S., Mol, B.W., Buitendijk, S.E., van der Pal-de Bruin, K.M., Male predominance in fetal distress during labor (2002) Am J Obstet Gynecol, 187, pp. 1605-1607; Bennet, L., Booth, L.C., Ahmed-Nasef, N., Dean, J.M., Davidson, J., Quaedackers, J.S., Male disadvantage? Fetal sex and cardiovascular responses to asphyxia in preterm fetal sheep (2007) Am J Physiol Regul Integr Comp Physiol, 293, pp. R1280-R1286; Bernardes, J., Moura, C., Marques-de-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Bernardes, J., Costa-Pereira, A., Ayres-de-Campos, D., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57, pp. 33-37; Bernardes, J., Ayres-de-Campos, D., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int J Gynaecol Obstet, 62, pp. 141-147; Bernardes, J., Gonçalves, H., Ayres-de-Campos, D., Rocha, A.P., Linear and complex heart rate dynamics vary with sex in relation to fetal behavioural states (2008) Early Hum Dev, 84, pp. 433-439; Boog, G., Analyse informatisée du rythme cardiaque foetal au cours de la grosssesse et de l'accouchement. (2004) Encyclopédie Médico- Chirurgicale, 148, pp. 1-10; Browner, W.S., Newman, T.B., Cummings, S.R., Hulley, S.B., (2001) Estimating sample size and power: The nitty-gritty, pp. 65-84. , Hulley SB, Cummings SR, Browner WS, Grady D, Hearst N, Newman TB, editors. Philadelphia: Lippincot Williams & Wilkins; Chaffin, D.G., Barnard, J.M., Phernetton, T., Reed, K.L., Decreased approximate entropy of heart rate variability in the hypoxic ovine fetus (1998) J Matern Fetal Invest, 8, pp. 23-26; Dawes, G.S., Moulden, M., Redman, C.W., Improvements in computerized fetal heart rate analysis antepartum (1996) J Perinat Med, 24, pp. 25-36; Dawes, N.W., Dawes, G.S., Moulden, M., Redman, C.W., Fetal heart rate patterns in term labor vary with sex, gestational age, epidural analgesia, and fetal weight (1999) Am J Obstet Gynecol, 180, pp. 181-187; DiPietro, J.A., Costigan, K.A., Shupe, A.K., Pressman, E.K., Johnson, T.R., Fetal neurobehavioral development: Associations with socioeconomic class and fetal sex (1998) Dev Psychobiol, 33, pp. 79-91; Dudewicz, E., Mishra, S., (1998) Modern mathematical statistics, , John Wiley and Sons, Inc; Fleisher, L.A., Dipietro, J.A., Johnson, T.R., Pincus, S., Complementary and non-coincident increases in heart rate variability and irregularity during fetal development (1997) Clin Sci (Lond), 92, pp. 345-349; Fusheng, Y., Bo, H., Qingyu, T., (1998) Approximate entropy and its application in biosignal analysis, 2, pp. 72-91. , editor. Nonlinear biomedical signal processing, Dynamical analysis and modelling. IEEE Press;; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters (2006) Physiol Meas, 27, pp. 307-319; Goncalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Med Biol Eng Comput, 44, pp. 847-855; Goncalves, H., Bernardes, J., Rocha, A.P., Ayres-de-Campos, D., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Hum Dev, 83, pp. 585-591; Groome, L.J., Mooney, D.M., Holland, S.B., Smith, L.A., Atterbury, J.L., Dykman, R.A., Behavioral state affects heart rate response to low-intensity sound in human fetuses (1999) Early Hum Dev, 54, pp. 39-54; Ingemarsson, I., Herbst, A., Thorngren-Jerneck, K., Long-term outcome after umbilical artery acidemia at term birth: Influence of gender and duration of fetal heart rate abnormalities (1997) Br J Obstet Gynaecol, 104, pp. 1123-1127; Jensen-Urstad, K., Storck, N., Bouvier, F., Ericson, M., Lindblad, L.E., Jensen-Urstad, M., Heart rate variability in healthy subjects is related to age and gender (1997) Acta Physiol Scand, 160, pp. 235-241; King, T., Parer, J., The physiology of fetal heart rate patterns and perinatal asphyxia (2000) J Perinat Neonat Nurs, 14, pp. 19-39; Kuo, T.B., Yang, C.C., Sexual dimorphism in the complexity of cardiac pacemaker activity (2002) Am J Physiol Heart Circ Physiol, 283, pp. H1695-H1702; Li, X., Tang, D., Zhou, S., Zhou, G., Wang, C., Zhuang, Y., Redistribution of power spectrum of heart rate variability during acute umbilical artery embolism and hypoxemia in late-gestation fetal sheep (2004) J Obstet Gynecol Reprod Biol, 114, pp. 137-143; Magenes, G., Signorini, M.G., Arduini, D., Classification of cardiotocographic records by neural networks (2000) IJCNN 2000, Proceedings of the IEEE-INNS-ENNS International Joint Conference on Neural Networks, 3, pp. 637-641; Martinez, W.L., Martinez, A.R., (2002) Computational statistics handbook with MATLAB, , CRC Press;; Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc Natl Acad Sci USA, 88, pp. 2297-2301; Pincus, S., Viscarello, R., Approximate Entropy: A regularity measure for fetal heart rate analysis (1992) Obstet Gynecol, 79, pp. 249-255; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am J Physiol Heart Circ Physiol, 278, pp. H2039-H2049; Ryan, S.M., Goldberger, A.L., Pincus, S.M., Mietus, J., Lipsitz, L.A., Gender- and age-related differences in heart rate dynamics: Are women more complex than men? (1994) J Am Coll Cardiol, 24, pp. 1700-1707; Sheiner, E., Hadar, A., Hallak, M., Katz, M., Mazor, M., Shoham-Vardi, I., Clinical significance of fetal heart rate tracings during the second stage of labor (2001) Obstet Gynecol, 97, pp. 747-752; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Transactions on Biomedical Engineering, 50, pp. 365-373; Siira, S.M., Ojala, T.H., Vahlberg, T.J., Jalonen, J.O., Välimäki, I.A., Rosén, K.G., Marked fetal acidosis and specific changes in power spectrum analysis of fetal heart rate variability recorded during the last hour of labor (2005) Br J Obstet Gynaecol, 112, pp. 418-423; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Yaegashi, N., Murotsuki, J., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am J Obstet Gynecol, 182, pp. 1227-1232;
Keywords: acidemia; Acidemic fetuses; article; autonomic nervous system; Birth Weight; blood pH; Cross-Sectional Studies; delivery; Delivery, Obstetric; entropy; Entropy and spectral analysis; Female; Fetal Heart; fetus; fetus heart rate; Gestational Age; Heart Rate, Fetal; human; Humans; Hydrogen-Ion Concentration; Intrapartum; labor; Labor, Obstetric; male; Pregnancy; priority journal; Retrospective Studies; Sex Characteristics; sex difference; Umbilical Arteries; umbilical artery

Skin adhesive versus subcuticular suture for perineal skin repair after episiotomy - A randomized controlled trial - Mota, R.; Costa, F.; Amaral, A.; Oliveira, F.; Santos, C.C.; Ayres-de-Campos, D. (Acta Obstetricia et Gynecologica ScandinavicaActa Obstet. Gynecol. Scand., 2009)
Objective. Surgical repair of perineal lesions after delivery is frequently associated with pain and discomfort, interfering with the normal activities of the puerperium. The aim of this study was to compare perineal skin repair after episiotomy with adhesive glue versus a subcuticular suture, regarding the incidence of pain and wound complications. Study design. Randomized clinical trial. Setting. Tertiary care university hospital. Material and methods. One hundred women having mediolateral episiotomy at vaginal delivery were enrolled. They were randomized to receive skin adhesive (n = 53) or subcuticular suture (n = 47) for closure of perineal skin. The main outcome measure was self-evaluated pain in the 30 days following delivery. Secondary outcome measures were technical difficulties reported with the procedure, duration of surgical repair, wound complications observed at 42-68 hours post-partum and re-initiation of sexual activity by 30 days post-partum. Results. No significant differences were observed between the two groups in incidence of technical difficulties and failed procedures, pain during the procedure, wound complications at hospital discharge, self-evaluated measures of pain at 7 and 30 days or re-initiation of sexual activity by 30 days post-partum. The skin adhesive group had a significantly shorter mean duration of the procedure (four minutes less). Conclusion. Perineal skin closure using adhesive glue is faster than subcuticular suture, and associated with a similar incidence of complications and pain in the first 30 days.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: AOGSAdoi: 10.1080/00016340902883133Language of Original Document: EnglishCorrespondence Address: Mota, R.; Serviço de Ginecologia e Obstetrícia, Hospital de S. João, 4200-319 Porto, Portugal; email: sisporto@med.up.ptChemicals/CAS: Tissue Adhesives; cyanoacrylic acid octyl ester, 6701-17-3; polyglactin, 26780-50-7, 34346-01-5Tradenames: Dermabond, EthiconManufacturers: EthiconReferences: Kettle, C., Hills, R.K., Jones, P., Darby, L., Gray, R., Johanson, R., Continuous versus interrupted perineal repair with standard or rapidly absorbed sutures after spontaneous vaginal birth: A randomized controlled trial (2002) Lancet, 359, pp. 2217-2223;Gordon, B., Mackrodt, C., Fern, E., Truesdale, A., Ayers, S., Grant, A., The Ipswich Childbirth Study: 1. A randomized evaluation of two stage postpartum perineal repair leaving the skin unsutured (1998) Br J Obstet Gynaecol, 105, pp. 435-440; Mackrodt, C., Gordon, B., Fern, E., Ayers, S., Truesdale, A., Grant, A., The Ipswich Childbirth Study: 2. A randomized comparison of polyglactin 910 with chromic catgut for postpartum perineal repair (1998) Br J Obstet Gynaecol, 105, pp. 441-445; Kettle, C., Johanson, R.B., Continuous versus interrupted sutures for perineal repair (2000) Cochrane DataBase Syst Rev, (2). , CD000947; Kettle, C., Hills, R.K., Ismail, K.M.K., Continuous versus interrupted sutures for repair of episiotomy or second degree tears (2007) Cochrane DataBase Syst Rev, (4). , CD000947; Gemynthe, A., Langhoff-Roos, J., Sahl, S., Knudsen, J., New VICRYL formulation: An improved method of perineal repair? (1996) Br J Midwifery, 4, pp. 230-234; Oboro, V.O., Tabowei, T.O., Loto, O.M., Bosah, J.O., A multicentre evaluation of the two-layered repair of postpartum perineal trauma (2003) J Obstet Gynaecol, 23, pp. 5-8; Kindberg, S., Stehouwer, M., Hvidman, L., Henriksen, T.B., Postpartum perineal repair performed by midwives: A randomised trial comparing two suture techniques leaving the skin unsutured (2008) Br J Obstet Gynaecol, 115, pp. 472-479; Gennari, R., Rotmensz, N., Ballardini, B., Scevola, S., Perego, E., Zanini, V., A prospective, randomized, controlled clinical trial of tissue adhesive (2-octylcyanoacrylate) versus standard wound closure in breast surgery (2004) Surgery, 136, pp. 593-599; Bernard, L., Doyle, J., Friedlander, S.F., Eichenfield, L.F., Gibbs, N.F., Cunningham, B.B., A prospective comparison of octylcya-noacrylate tissue adhesive (dermabond) and suture for the closure of excisional wounds in children and adolescents (2001) Arch Dermatol, 137, pp. 1177-1180; Matin, S.F., Prospective randomized trial of skin adhesive versus sutures for closure of 217 laparoscopic port-site incisions (2003) J Am Coll Surg, 196, pp. 845-853; Bhende, S., Rothenburger, S., Spangler, D.J., Dito, M., In vitro assessment of microbial barrier properties of Dermabond( topical skin adhesive (2002) Surg Infect, 3, pp. 251-257; Rogerson, L., Mason, G.C., Roberts, A.C., Preliminary experience with twenty perineal repairs using Indermil tissue adhesive (2000) Eur J Obstet Gynecol Reprod Biol, 88, pp. 139-142; Bowen, M.L., Selinger, M., Episiotomy closure comparing enbucrilate tissue adhesive with conventional sutures (2002) Int J Gynecol Obstet, 78, pp. 201-205; Adoni, A., Anteby, E., The use of Histoacryl for the episiotomy repair (1991) Br J Obstet Gynaecol, 98, pp. 476-478; Man, J., Quinn, J., Cyanoacrylate tissue adhesives (1997) Am J Cosm Surg, 14, pp. 413-416; Maw, J.L., Quinn, J.V., Wells, G.A., Ducic, Y., Odell, P.F., Lamothe, A., A prospective comparison of octylcyanoacrylate tissue adhesive and suture for the closure of head and neck incisions (1997) J Otolaryngol, 26, pp. 26-30
Keywords: adult; article; clinical trial; comparative study; controlled clinical trial; controlled study; cyanoacrylic acid octyl ester; edema; episiotomy; Episiotomy closure; Female; granuloma; human; Humans; injury; major clinical study; obstetric care; pain; pain assessment; Perineal repair; perineum; perineum injury; polyglactin; priority journal; questionnaire; randomized controlled trial; sexual intercourse; Skin; Skin adhesive; suture; Suture Techniques; suturing method; Tissue adhesive; Tissue Adhesives; treatment outcome; vaginal delivery; wound closure; wound dehiscence; Wounds and Injuries

Biocompatibility of highly macroporous ceramic scaffolds: Cell adhesion and morphology studies - Teixeira, S.; Ferraz, M.P.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2008)
Hydroxyapatite porous scaffolds can be used for tissue engineering applications since they can serve as templates for cell adhesion, proliferation and ultimately for tissue repair. One way to address this issue is to evaluate the cell adhesion using several characterization techniques namely, cytotoxicity assays and cell visualization. On the other hand, when using highly macroporous scaffolds some techniques may not be adequate for evaluation, such as MTT. In this work, cytotoxicity assay (MTS), scanning electron microscopy (SEM) and Confocal laser scanning microscopy (CLSM) were used to evaluate cell adhesion in highly macroporous hydroxyapatite scaffolds. It was possible to observe that some techniques were not suitable to evaluate cell adhesion. In addition, it was shown that for this kind of scaffolds, confocal laser scanning microscopy is a powerful tool for cell adhesion and proliferation evaluation. © 2007 Springer Science+Business Media, LLC.
Cited By (since 1996): 23Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-007-3005-xPubMed ID: 17665126Language of Original Document: EnglishCorrespondence Address: Teixeira, S.; Laboratório de Biomateriais, INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: smsilva@ineb.up.ptChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; Biocompatible Materials; Ceramics; Durapatite, 1306-06-5References: Jones, A.C., (2004) Biomaterials, 25, p. 4947;Karaggeorgiou, V., (2005) Biomaterials, 27, p. 5474; Leon, C.A., Leon, Y., (1998) Adv. Colloid. Interface Sci., 76-77, p. 341; Kuboki, Y., Takita, H., Kobayashi, D., Tsuruga, E., Inoue, M., Murata, M., (1998) J. Biomed. Mater. Res., 39, p. 190. , 2; Heise, U., Osborn, J.F., Duwe, F., (1990) Int. Orthop., 14, p. 329; Bucholz, R.W., Carlton, A., Holmes, R.E., (1987) Orthop. Clin. North. Am., 18, p. 323; Hill, P.A., (1998) Br. J. Orthod., 25, p. 101; Martin, R.B., (1999) Mater. Sci. Forum, 293, p. 5; Nunes, C.R., Simske, S.J., Sachdeva, R., Wolford, L.M., (1997) J. Biomed. Mater. Res., 36, p. 560; Queiroz, A.C., Teixeira, S., Monteiro, F.J., Santos, J.D., (2004) Key Eng. Mater., 254-256, p. 997; Queiroz, A.C., Teixeira, S., Monteiro, F.J., Santos, J.D., (2004) Mater. Sci. Forum, 455-456, p. 358; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Porous, H.A., (2005) Key Eng. Mater., 284-286; Teixeira, S.M., Queiroz, A.C., Monteiro, F.J., Ferraz, M.P., In vitro analysis of macroporous ceramic matrices: Preliminary results (2005) 19th European Conference on Biomaterials, , PP-P173; Naples, Italy, Sept 11-15
Keywords: article; Bioassay; Biocompatibility; Biocompatible Materials; cell adhesion; Cell Line, Tumor; cell proliferation; cell structure; Ceramic materials; ceramics; confocal laser microscopy; controlled study; Cytotoxicity; Cytotoxicity assay; Durapatite; human; human cell; Humans; hydroxyapatite; Macroporous ceramic scaffolds; Microscopy, Confocal; Microscopy, Electron, Scanning; Osteoblasts; priority journal; Scanning electron microscopy; Tissue engineering; Tissue Scaffolds

Bone ingrowth in macroporous Bonelike ® for orthopaedic applications - Gutierres, M.; Lopes, M.A.; Sooraj Hussain, N.; Lemos, A.F.; Ferreira, J.M.F.; Afonso, A.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Acta BiomaterialiaActa Biomater., 2008)
The aim of this study was to evaluate the biological behaviour of porous scaffold structures of Bonelike ® which is suitable for either direct clinical use or tissue engineering applications. Porous cylindrical specimens 8 × 10 mm were implanted in the lateral aspect of the tibia of 13 patients (mean age 54 years), during osteotomy surgery for the treatment of medial compartment osteoarthritis of the knee. Implanted cylinders were retrieved at the same time as the removal of the blade plates at 3, 6, 9 and 12 months. Scanning electron microscopy and histological evaluations were performed to observe the biological responses of human bone tissue to porous Bonelike ®. The penetration depth was determined for all implantation periods, and after 6 months it was already possible to see new bone in the centre of the implanted cylinders, which gives 100% of penetration depth for all implantations periods except for 3 months when bone could only be seen in the peripherical region. Regarding the percentage of the area covered by new bone calculated from two-dimensional histological sections, values of 53 ± 15, 76 ± 12 and 88 ± 9% were achieved for 6, 9 and 12 months, respectively. Due to its structural features porous Bonelike ® permitted effective vascularization and bone ingrowth, and therefore was fully osteointegrated as shown in the histological surveys. A slow biomaterial degradation with implantation time is envisaged since the material has displayed surface degradation. Bonelike ® scaffolds show potential for complete ingrowth of osseous tissue and restoration of vascularization throughout the defected site. © 2007.
Cited By (since 1996): 13Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2007.06.009PubMed ID: 17716960Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; FEUP - Faculdade de Engenharia, Universidade do Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Bone SubstitutesTradenames: BonelikeReferences: Akamatsu, Y., Koshino, T., Saito, T., Wada, J., Changes in osteosclerosis of the osteoarthritic knee after high tibial osteotomy (1997) Clin Orthop, 334, pp. 207-214;Coventry, M.B., Ilstrup, D.M., Wallrichs, S.L., Proximal tibial osteotomy. A critical long-term study of eighty-seven cases (1993) J Bone Joint Surg, 75 -A, pp. 196-201; Hernigou, P., Medevielle, D., Debeyre, J., Goutallier, D., Proximal tibial osteotomy for osteoarthritis with varus deformity. A ten to thirteen-year follow-up study (1987) J Bone Joint Surg Am, 69, pp. 332-354; Hernigou, P., Ma, W., Open wedge tibial osteotomy with acrylic bone cement as bone substitute (2001) Knee, 8, pp. 103-110; Koshino, T., Murase, T., Saito, T., Medial opening-wedge high tibial osteotomy with use of porous hydroxyapatite to treat medial compartment osteoarthritis of the knee (2003) J Bone Joint Surg Am, 85, pp. 78-85; Simske SJ, Ayers RA, Bateman TA. Porous Materials for Bone Engineered. In: Materials Science Forum. Zurich: Trans Tech Publications; 1997. Vol. 250, pp. 151-182Hing, K.A., Bone repair in the twenty-first century: biology, chemistry or engineering? (2004) Philos Trans A Math Phys Eng Sci, 362 (1825), pp. 2821-2850; Hui, P.W., Leung, P.C., Sher, A., Fluid conductance of cancellous bone graft as a predictor for graft-host interface healing (1996) J Biomech, 29 (1), pp. 123-132; Ben-Nissan, B., Natural bioceramics: from coral to bone and beyond (2003) Curr Opin Solid State Mater Sci, 7 (4-5), p. 283; Shors, E.C., Holmes, R.E., Porous hydroxyapatite (1993) Introduction to Biomaterials, pp. 181-198. , Hench L.L., and Wilson J. (Eds), World Scientific, Singapore; Prado da Silva, M.H., Lemos, A.F., Gibson, I.R., Ferreira, J.M.F., Santos, J.D., Porous glass reinforced hydroxyapatite materials produced with different organic additives (2002) J Non-Cryst Solids, 304, pp. 286-292; Prado da Silva, M.H., Lemos, A.F., Ferreira, J.M.F., Lopes, M.A., Santos, J.D., Production of porous biomaterials based on glass reinforced hydroxyapatite composites (2002) Key Eng Mater, 230-232, pp. 483-486; Rocha, J., Lemos, A., Agathopoulos, S., Valério, P., Kannan, S., Oktar, F., Scaffolds for bone restoration from cuttlefish (2005) Bone, 37 (6), pp. 850-857; Sepulveda, P., Binner, J.G.P., Processing of cellular ceramics by foaming and in situ polymerization of organic monomers (1999) J Eur Ceram Soc, 19 (12), pp. 2059-2066; Ozgur Engin, N., Cuneyt Tas, A., Manufacture of macroporous calcium hydroxyapatite bioceramics (1999) J Eur Ceram Soc, 19 (13-14), pp. 2569-2572; Peng, H.X., Fan, Z., Evans, J.R.G., Busfield, J.J.C., Microstructure of ceramic foams (2000) J Eur Ceram Soc, 20 (7), pp. 807-813; Komlev Vladimir, S., Barinov Serguei, M., Koplik Elena, V., A method to fabricate porous spherical hydroxyapatite granules intended for time-controlled drug release (2002) Biomaterials, 23 (16), pp. 3449-3454; Milosevski, M., Bossert, J., Milosevski, D., Gruevska, N., Preparation and properties of dense and porous calcium phosphate (1999) Ceram Int, 25, pp. 693-696; Tadic, D., Beckmann, F., Schwarz, K., Epple, M., A novel method to produce hydroxyapatite objects with interconnecting porosity that avoids sintering (2004) Biomaterials, 25, pp. 3335-3340; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., Influence of characteristics of the starting hydroxyapatite powders and of deagglomeration procedure, on rheological behaviour of the suspensions (2004) Mater Sci Forum, 455-456, pp. 361-365; Lemos, A.F., Ferreira, J.M.F., Porous bioactive calcium carbonate implants processed by starch consolidation (2000) J Mat Sci Eng C, C11, pp. 35-40; Lemos, A.F., Ferreira, J.M.F., Combining foaming and starch consolidation methods to develop macroporous HA implants (2004) Key Eng Mater, 254-256, pp. 1041-1044; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., New method for the incorporation of soluble bioactive glasses to reinforce porous HA structures (2004) Key Eng Mater, 254-256, pp. 1033-1036; Gauthiera, O., Boulerb, J.M., Aguadoa, E., Piletb, P., Daculsi, G., Macroporous biphasic calcium phosphate ceramics: influence of macropore diameter and macroporosity percentage on bone ingrowth (1998) Biomaterials, 19, pp. 133-139; Hing, A.K., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Mediation of bone ingrowth in porous hydroxyapatite bone graft substitutes (2004) J Biomed Mater Res, 68 A, pp. 187-200; Rubin, P.A., Popham, J.K., Bilyk, J.R., Shore, J.W., Comparison of fibrovascular ingrowth into hydroxyapatite and porous polyethylene orbital implants (1994) Ophthal Plast Reconstr Surg, 10 (2), pp. 96-103; Hing, K.A., Annaz, B., Saeed, S., Revell, P.A., Buckland, T., Microporosity enhances bioactivity of synthetic bone graft substitutes (2005) J Mater Sci: Mater Med, 16, pp. 467-475; Klawitter, J.J., Bagwell, J.G., Weinstein, A.M., Sauer, B.W., An evaluation of bone growth into porous high density polyethylene (1976) J Biomed Mater Res, 10 (2), pp. 311-323; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Quantification of bone ingrowth within bone-derived porous hydroxyapatite implants of varying density (1999) J Mater Sci: Mater Med, 10, pp. 663-670; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Biomechanical assessment of bone ingrowth in porous hydroxyapatite (1997) J Mater Sci: Mater Med, 8, pp. 731-736; Ayers, R.A., Wolford, L.M., Bateman, T.A., Ferguson, V.L., Simske, S.J., Quantification of bone ingrowth into porous block hydroxyapatite in humans (1999) J Biomed Mater Res, 47, pp. 54-59; Lu, J.X., Flautre, B., Anselme, K., Hardouin, P., Gallur, A., Descamps, M., Role of interconnections in porous bioceramics on bone recolonization in vitro and in vivo (1999) J Mater Sci: Mater Med, 10 (2), pp. 111-120; Eggli, P.S., Muller, W., Schenk, R.K., Porous hydroxyapatite and tricalcium phosphate cylinders with two different pore size ranges implanted in the cancellous bone of rabbits - A comparative histomorphometric and histologic study of bony ingrowth and implant substitution (1988) Clin Orthop Relat Res, 232, pp. 127-138; Kuhne, J.H., Bartl, R., Frisch, B., Hammer, C., Jansson, V., Zimmer, M., Bone formation in coralline hydroxyapatite. Effects of pore size studied in rabbits (1994) Acta Orthop Scand, 65 (3), pp. 246-252; Holmes, R., Mooney, V., Bucholz, R., Tencer, A., A coralline hydroxyapatite bone graft substitute. Preliminary report (1984) Clin Orthop Relat Res, 188, pp. 252-262; Lopes, M.A., Knowles, J.C., Santos, J.D., Structural insights of glass-reinforced hydroxyapatite composites by Rietveld refinement (2000) Biomaterials, 21 (18), pp. 1905-1910; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass-reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39 (2), pp. 244-251; Santos JD, Hastings G, Knowles JC. Sintered hydroxyapatite compositions and method for the preparation thereof. Worldwide Application (PCT), Patent No. 1 189 851, 1999Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: fracture toughness and hardness dependence on microstructural characteristics (1999) Biomaterials, 20 (21), pp. 2085-2090; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: Secondary phase proportions and densification effects on biaxial bending strength (1999) J Biomed Mater Res, 48 (5), pp. 734-740; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, Surface tension and Zeta potential measurements of glass reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Direct and Indirect effects of P 2O 5 - glass reinforced - hydroxyapatite composites and growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibiae of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., HA and Double layer HA-P 2O 5/CaO Glass coatings: influence of chemical composition on human bone marrow cells osteoblastic behaviour (2001) J Mater Sci: Mater Med, 12, pp. 629-638; Gutierres, M., Hussain, N.S., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Biological behaviour of Bonelike ® graft implanted in the tibia of humans (2005) Key Eng Mater, 17, pp. 1041-1044; Duarte, F., Santos, J.D., Afonso, A., Medical applications of Bonelike ® in maxillofacial surgery (2004) Adv Mater Forum, pp. 370-373; Lobato, J.V., Hussain, N.S., Botelho, C.M., Titanium dental implants coated with Bonelike ®: clinical case report (2006) Thin Solid Films, 515, p. 279; Coventry, M.B., Osteotomy of the upper portion of the tibia for degenerative arthritis of the knee: a preliminary report (1965) J Bone Joint Surg Am, 47, pp. 984-990; Coventry, M.B., Upper tibia osteotomy for gonarthrosis. The evolution of the operation in the last 18 years and long term results (1979) Orthop Clin North Am, 10, pp. 191-210; Coventry, M.B., Current concepts review. Upper tibia osteotomy for osteoarthritis (1985) J Bone Joint Surg Am, 67 A, pp. 1136-1140
Keywords: adult; aged; article; biomaterial; bone defect; Bone graft; bone growth; Bone Regeneration; Bone Substitutes; bone tissue; Bonelike; clinical article; controlled study; Female; histology; human; human tissue; Humans; implant; knee osteoarthritis; male; materials testing; Microscopy, Electron, Scanning; Middle Aged; molecular scaffold; Orthopaedic; orthopedics; Osseointegration; Osteoarthritis; osteotomy; porosity; Porous materials; priority journal; Prostheses and Implants; Scanning electron microscopy; tibia; Time Factors; Tissue engineering; tissue section; vascularization; ®

Cell-induced response by tetracyclines on human bone marrow colonized hydroxyapatite and Bonelike ® - Gomes, P.S.; Santos, J.D.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2008)
Semi-synthetic tetracyclines are commonly used antibiotics that also seem to play an important role in the modulation of the immuno-inflammatory imbalance, verified in several bone diseases. The association of a therapeutic agent (that prevents bacterial infection and induces tissue formation) to a biomaterial aiming to repair/regenerate bone defects could contribute to a more predictable clinical outcome. The present study intends to evaluate the proliferation and functional activity of osteoblast-induced human bone marrow cells, cultured on the surface of hydroxyapatite (HA) and Bonelike ®, in the presence of therapeutic concentrations of doxycycline and minocycline. First passage bone marrow cells were cultured for 35 days on the surface of HA and Bonelike ® discs, in the absence or presence of 1 μg ml
Cited By (since 1996): 9Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2007.12.006PubMed ID: 18291737Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Laboratório de Farmacologia e Biocompatibilidade Celular, Faculdade de Medicina Dentária, Universidade do Porto (FMDUP), Rua Dr. Manuel Pereira da Silva, s/n, 4200-392 Porto, Portugal; email: mhrf@portugalmail.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; doxycycline, 10592-13-9, 17086-28-1, 564-25-0; hydroxyapatite, 1306-06-5, 51198-94-8; minocycline, 10118-90-8, 11006-27-2, 13614-98-7; Alkaline Phosphatase, EC 3.1.3.1; Bone Substitutes; Calcium, 7440-70-2; Culture Media; Durapatite, 1306-06-5; Minerals; Tetracycline, 60-54-8Tradenames: BonelikeReferences: Chambers, H., Protein synthesis inhibitors and miscellaneous antibacterial agents (2006) Goodman and Gilman's - The Pharmacological Basis of Therapeutics, pp. 1173-1202. , Brunton L. (Ed), McGraw-Hill, Germany;Alkan, A., Erdem, E., Gunhan, O., Karasu, C., Histomorphometric evaluation of the effect of doxycycline on the healing of bone defects in experimental diabetes mellitus: a pilot study (2002) J Oral Maxillofac Surg, 60, p. 898; Buchter, A., Kleinheinz, J., Meyer, U., Joos, U., Treatment of severe peri-implant bone loss using autogenous bone and a bioabsorbable polymer that delivered doxycycline (Atridox TM) (2004) Brit J Oral Maxillofacial Surg, 42, pp. 452-456; Ramamurthy, N., Rifkin, B., Greenwald, R., Xu, J.-W., Liu, Y., Turner, G., Inhibition of matrix metalloproteinase-mediated periodontal bone loss in rats: a comparison of 6 chemically modified tetracyclines (2005) J Periodontol, 73, pp. 726-734; Golub, L., Ramamurthy, N., Kaneko, H., Sasaki, T., Rifkin, B., McNamara, T., Tetracycline administration prevents diabetes-induced osteopenia in the rat: initial observations (1990) Res Commun Chem Pathol Pharmacol, 68, p. 27; Williams, S., Wakisaka, A., Zeng, Q., Barnes, J., Martin, G., Wechter, W., Minocycline prevents the decrease in bone mineral density and trabecular bone in ovariectomized aged rats (1996) Bone, 19, pp. 637-644; Williams, S., Wakisaka, A., Zeng, Q., Barnes, J., Seyedin, S., Martin, G., Effect of minocycline on osteoporosis (1998) Adv Dental Res, 12, pp. 71-75; Pytlik, M., Folwarczna, J., Janiec, W., Effects of doxycycline on mechanical properties of bones in rats with ovariectomy-induced osteopenia (2004) Calcified Tissue Int, 75, pp. 225-230; Holmes, S., Still, K., Buttle, D., Bishop, N., Grabowski, P., Chemically modified tetracyclines act through multiple mechanisms directly on osteoclast precursors (2004) Bone, 35, pp. 471-478; Polson, A., Bouwsma, O., McNamara, T., Golub, L., Enhancement of alveolar bone formation after tetracycline administration in squirrel monkeys (2005) J Appl Res Clin Dent, pp. 32-42; Yamaguchi, A., Udagawa, T., Sawai, T., Transport of divalent cations with tetracycline as mediated by the transposon Tn10-encoded tetracycline resistance protein (1990) J Biol Chem, 265, pp. 4809-4813; Li, S., de Wijn, J., Layrolle, P., de Groot, K., Synthesis of macroporous hydroxyapatite scaffolds for bone tissue engineering (2002) J Biomed Mater Res, 61, pp. 109-120; Giannoudis, P., Dinopoulos, H., Tsiridis, E., Bone substitutes: an update (2005) Int J Care Injured, 365, p. 220; LeGeros, R., Properties of osteoconductive biomaterials: calcium phosphates (2002) Clin Orthop, 395, pp. 81-98; Suchanek, W., Yoshimura, M., Processing and properties of hydroxyapatite-based biomaterials for use as hard tissue replacement implants (1998) J Mater Res, 13, pp. 94-117; Lopes, M., Santos, J., Monteiro, F., Knowles, J., Glass reinforced hydroxyapatite: a comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-250; Hench, L., Bioactive materials: the potential for tissue regeneration (1998) J Biomed Mater Res, 41, pp. 511-518; Kellomaki, M., Niiranen, H., Puumanen, K.A.N., Waris, T., Tormala, P., Bioabsorbable scaffolds for guided bone, regeneration, and generation (2000) Biomaterials, 21, pp. 2495-2505; Santos, J., Reis, R., Monteiro, F., Knowles, J., Hastings, G., Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions structure and properties of the composites (1995) J Mater Sci Mat Med, 6, p. 348; Santos, J., Silva, P., Knowles, J., Talal, S., Monteiro, F., Reinforcement of hydroxyapatite by adding P 2O 5-CaO glasses with Na 2O, K 2O and MgO (1996) J Mater Sci Mat Med., 7, p. 187; Duarte, F., Santos, J., Afonso, A., Medical applications of Bonelike in maxillofacial surgery (2004) Mater Sci Forum, 370, pp. 455-456; Gutierres, M., Hussain, N., Afonso, A., Almeida, L., Cabral, A., Lopes, M., Biological behaviour of bonelike ® graft implanted in the tibia of humans (2005) Key Eng Mater, 1041, pp. 284-286; Brause, B., Infections with prostheses in bones and joints (2000) Mandell, Douglas and Bennett's Principles and Practice of Infectious Diseases. 5th ed., pp. 1196-1200. , Mandell G., Bennet J., and Dolin R. (Eds), Churchill Livingstone, Philadelphia; Darley, E., MacGowan, A., Antibiotic treatment of Gram-positive bone and joint infections (2004) J Antimicrobial Chemotherapy, 53, pp. 928-935; Zucchelli, G., Sforza, N., Clauser, C., Cesari, C., De Sanctis, M., Topical and systemic antimicrobial therapy in guided tissue regeneration (1999) J Periodontol, 70, pp. 239-247; Yukna, R., Sepe, W., Clinical evaluation of localized periodontosis defects treated with freeze-dried bone allografts combined with local and systemic tetracyclines (1982) Int J Periodontics Restorative Dent, 2, pp. 8-21; Shirtliff, M., Mader, J., Acute septic arthritis (2002) Clin Microbiol Rev, 15, pp. 527-544; Sunder, M., Babu, N., Victor, S., Kumar, K., Kumar, T., Biphasic calcium phosphates for antibiotic release (2005) Trends Biomater Artif Organs, 18, pp. 213-218; Lieberman, J., Daluiski, A., Einhorn, T., The role of growth factors in the repair of bone: biology and clinical applications (2002) J Bone Joint Surg, 84, pp. 1032-1044; Carson, J., Bostrom, M., Synthetic bone scaffolds and fracture repair (2007) Injury, 38, pp. S33-S70; Regí-Vallet, M., Balas, F., Colilla, M., Manzano, M., Drug confinement and delivery in ceramic implants (2007) Drug Metabol Lett, 1, pp. 37-40; Lin, T.-L., Lu, F.-M., Conroy, S., Sheu, M.-S., Su, S.-H., Tang, L., Antimicrobial coatings: a remedy for medical device-related infections (2001) Med Device Technol., 12, pp. 26-30; Beardmore, A., Brooks, D., Wenke, J., Thomas, D., Effectiveness of local antibiotic delivery with an osteoinductive and osteoconductive bone-graft substitute (2005) J Bone Joint Surg, 87, pp. 107-112; Gomes, P., Fernandes, M., Effect of therapeutic levels of doxycycline and minocycline in the proliferation and differentiation of human bone marrow osteoblastic cells (2007) Arch Oral Biol, 52, pp. 251-259; Coelho, M., Fernandes, M., Human bone cell cultures in biocompatibility testing Part II. Effect of ascorbic acid, β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Jørgensen, N., Henriksena, Z., Sørensena, O., Civitelli, R., Dexamethasone, BMP-2, and 1,25-dihydroxyvitamin D enhance a more differentiated osteoblast phenotype: validation of an in vitro model for human bone marrow-derived primary osteoblasts (2004) Steroids, 69, pp. 219-226; Sakellari, D., Goodson, J., Socransky, S., Kolokotronis, A., Konstantinidis, A., Concentration of 3 tetracyclines in plasma, gingival crevice fluid and saliva (2000) J Clin Periodontol, 27, pp. 53-60; Stein, G., Lian, J., Molecular mechanisms mediating proliferation/differentiation interrelationships during progressive development of the osteoblast phenotype (1993) Endocr Rev, 14, pp. 424-442; Zhang, Y., Lopes, M., Santos, J., CaO-P 2O 5 Glass ceramics containing bioactive phases: crystallization and in vitro bioactivity studies (2001) Key Eng Mater, 192, pp. 643-646; Lopes, M., Knowles, J., Santos, J., Monteiro, F., Olsen, I., Direct and indirect effects of P 2O 5-glass reinforced hydroxyapatite on the growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Costa, M., Gutierres, M., Almeida, L., Lopes, M., Santos, J., Fernandes, M., In vitro mineralisation of human bone marrow cells cultured on Bonelike (2004) Key Eng Mater, pp. 254-256. , (821-4); Lopes, M., Santos, J., Monteiro, F., Ohtsuki, C., Osaka, A., Kaneko, S., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Gutierres, M., Hussain, N., Lopes, M., Afonso, A., Cabral, A., Almeida, L., Histological and scanning electron microscopy analyses of bone/implant interface using the novel Bonelike ® synthetic bone graft (2006) J Ortho Res, 24, p. 953; Kima, H.-W., Leea, E.-J., Kima, H.-E., Salihb, V., Knowles, J., Effect of fluoridation of hydroxyapatite in hydroxyapatite-polycaprolactone composites on osteoblast activity (2005) Biomaterials, 26, pp. 4395-4404; Williams, S., Barnes, J., Wakisaka, A., Ogasa, H., Liang, C., Treatment of osteoporosis with MMP inhibitors (1999) Ann NY Acad Sci, 878, pp. 191-200; Schwartz, Z., Lohmann, C., Wieland, M., Cochran, D., Dean, D., Textor, M., Osteoblast proliferation and differentiation on dentin slices are modulated by pretreatment of the surface with tetracycline or osteoclasts (2000) J Periodontol, 71, pp. 586-597; Bettany, J., Wolowacz, R., Tetracycline derivatives induce apoptosis selectively in cultured monocytes and macrophages but not in mesenchymal cells (1998) Adv Dent Res, 12, pp. 136-143; Duewelhenke, N., Krut, O., Eysel, P., Influence on mythochondria and cytotoxicity of different antibiotics administered in high concentrations on primary human osteoblasts and cell lines (2007) Antimicrobial Agents and Chemotherapy, 51, pp. 54-63; Golub, L., Wolff, M., Roberts, S., Lee, H.-M., Leung, M., Payonk, G., Treating periodontal diseases by blocking tissue-destructive enzymes (1994) JADA, 125, pp. 163-169; Woessner, J., Nagase, H., Inhibition of MMPs (2000) MMPs and Timps, pp. 109-125. , Woessner J., and Nagase H. (Eds), Oxford University Press, Oxford; Golub, L., Ramamurthy, N., McNamara, T., Gomes, B., Wolff, M., Casino, A., Tetracyclines inhibit tissue collagenase activity. A new mechanism in the treatment of periodontal disease (1984) J Periodontal Res, 19, pp. 651-655; Yu, Z., Ramamurthy, N., Leung, M., Chang, K., McNamara, T., Golub, L., Chemically-modified tetracycline normalizes collagen metabolism in diabetic rats: a dose-response study (1993) J Periodontal Res, 28, pp. 420-428; Karimbux, N., Ramamurthy, N., Golub, L., Nishimura, I., The expression of collagen I and XII on RNAs in porphyromonas gingivalis-induced periodontitis in rats: The effect of doxycycline and chemically-modified tetracycline (CMT-1) (1998) J Periodontol, 69, pp. 39-40; Ramamurthy, N., Pirila, E., Lee, H.-M., Delayed wound healing, altered collagen level and keratinocyte growth factor expression in skin of ovariectomized rat is normalized by estrogen or chemically modified doxycycline (2003) Menopause - The State of the Art in Research and Management. The Proceedings of the Tenth World Congress, pp. 236-243. , Schneider H. (Ed), Parthenon Publishing Group, New York; Gurkan, A., Çunarcuk, S., Huseyinov, A., Adjunctive subantimicrobial dose doxycycline: effect on clinical parameters and gingival crevicular fluid transforming growth factor-b 1 levels in severe, generalized chronic periodontitis (2005) J Clin Periodontol, 32, pp. 244-253; Caton, J., Evaluation of Periostat for patient management (1999) Compend Contin Edu Dent, 20, pp. 451-456; Salasznyk, R., Williams, W., Boskey, A., Batorsky, A., Plopper, G., Adhesion to vitronectin and collagen I promotes osteogenic differentiation of human mesenchymal stem cells (2004) J Biomed Biotechnol, 1, pp. 24-34; Gerstenfeld, L., Chipman, S., Kelly, C., Hodgens, K., Lee, D., Landis, W., Collagen expression, ultrastructural assembly, and mineralization in cultures of chicken embryo osteoblasts (1988) J Cell Biol, 106, pp. 979-989
Keywords: adult; alkaline phosphatase; alkaline phosphatase bone isoenzyme; antimicrobial activity; article; Bacteria (microorganisms); bone infection; bone marrow cell; Bone Marrow Cells; Bone Substitutes; Bonelike; Calcium; calcium phosphate; Cell culture; cell function; cell proliferation; cell survival; cell viability; Cells, Cultured; concentration response; controlled study; Culture Media; culture medium; doxycycline; Durapatite; enzyme activity; extracellular matrix; glass; human; human cell; Humans; hydroxyapatite; implant; Microscopy, Electron, Scanning; Middle Aged; Minerals; minocycline; osteoblast; Osteoblasts; priority journal; Scanning electron microscopy; stroma cell; Tetracycline; tetracycline derivative; Tetracyclines; X-Ray Diffraction

Chromatographic pattern classification - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (IEEE Transactions on Biomedical EngineeringIEEE Trans. Biomed. Eng., 2008)
In this paper, we propose and evaluate methodologies for the classification of images from thin-layer chromatography. Each individual sample is characterized by an intensity profile that is further represented into a feature space. The first steps of this process aim at obtaining a robust estimate of the intensity profile by filtering noise, reducing the influence of background changes, and by fitting a mixture of Gaussians. The resulting profiles are represented by a set of appropriate features trying to characterize the state of nature, here spread out over four classes, one for normal subjects and the other three corresponding to lysosomal diseases, which are disorders responsible for severe nerve degeneration. For classification purposes, a novel solution based on a hierarchical structure is proposed. The main conclusion of this paper is that an automatically generated decision tree presents better results than more conventional solutions, being able to deal with the natural imbalance of the data that, as consequence of the rarity of lysosomal disorders, has very few representative cases in the disease classes when compared with the normal population. © 2008 IEEE.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusArt. No.: 8CODEN: IEBEAdoi: 10.1109/TBME.2008.919852PubMed ID: 18714832Language of Original Document: EnglishCorrespondence Address: Sousa, A. V.; Instituto de Engenharia Biomédica (INEB), Instituto Superior de Engenharia Do Porto, 4200-465 Porto, Portugal; email: ats@isep.ipp.ptChemicals/CAS: Hydrolases, EC 3.-References: Keir, G., Winchester, B., Clayton, P., Carbohydrate-deficient glycoprotein syndromes: Inborn errors of protein glycosylation (1999) Ann. Clin. Biochem, 36 (1), pp. 20-36;Durand, G., Seta, N., Protein glycosylation and diseases: Blood and urinary oligosaccharides as markers for diagnosis and therapeutic monitoring (2000) Clin. Chem, 46, pp. 795-805; Scriver, S., Beaudet, A., Sly, W., Valle, D., (2001) The Metabolic Bases of Inherited Disease, 3. , New-York: McGraw-Hill; Pinto, R., Caseiro, C., Lemos, M., Lopes, L., Fontes, A., Miranda, M., Prevalence of lysosomal storage diseases in Portugal (2004) Eur. J. Hum. Genet, 12, pp. 87-92; Friedman, R., Williams, M., Moser, H., Kolodny, E., Improved thin-layer chromatographic method in the diagnosis of mannosidosis (1978) Clin. Chem, 24, pp. 1576-1577; Kurczynski, T., Kendzierski, K., Sewell, A., Kuczynski, T., Urinary oligosaccharides in pregnant or lactating women: Pitfall in screening (1993) Clin. Chem, 39, pp. 2346-2347; Sewell, A., Urinary oligosaccharides (1991) Techniques Diagnostic Human Biochemical Genetics, pp. 219-231. , New York: Wiley; Reich, E., Blatter, A., Modern TLC: A key technique for identification and quality control of botanicals and dietary supplements (2005) J. Planar Chromatogr. - Modern TLC, 18, pp. 34-37. , Jan./Feb; Duvdevani-Bar, S., Edelman, S., Visual recognition and categorization on the basis of similarities to multiple class prototypes (1999) Int. J. Comput. Vis, 33, pp. 201-228; Pekalska, E., Duin, R., Dissimilarity representations allow for building good classifiers (2002) Pattern Recognit. Lett, 23, pp. 943-956; Goldstone, R., Son, J., Similarity (2005) Cambridge Handbook of Thinking and Reasoning, pp. 13-36. , K. Holyoak and R. Morrison, Eds. Cambridge, MA: Cambridge Univ. Press; Lavine, B., Clustering and classification of analytical data (2000) Encyclopedia of Analytical Chemistry: Instrumentation and Applications, pp. 9689-9710. , R. Meyers, Ed. Chichester, U.K, Wiley; Japkowicz, N., Learning from imbalanced data sets: A comparison of various strategies (2000) Proc. Learn. Imbalanced Data, pp. 10-15; Weiss, G., Mining with rarity: A unifying framework (2004) Sigkdd Explor, 6, pp. 7-19; Kubat, M., Holte, R., Matwin, S., Machine learning for the detection of oil spills in satellite radar images (1998) Mach. Learn, 30, pp. 195-215; Tax, D., One-class classification; concept-learning in the absence of counter-examples, (2001), ASCI, pp. 1-190. , Ph.D. dissertation, Delft Univ. Technol, Dissertation Ser, ppSousa, A., Aguiar, R., Mendonça, A., Campilho, A., Automatic lane and band detection in images of thin layer chromatography (2004) Lecture Notes in Computer Science, 3212, pp. 158-165. , Image Analysis and Recognition, New York: Springer-Verlag; Schwedt, G., (1997) The Essential Guide to Analytical Chemistry, , New York: Wiley; Bajla, I., Hollander, I., Fluch, S., Burg, K., Kollar, M., An alternative method for electrophoretic gel image analysis in the GelMaster software (2005) Comput. Methods Programs Biomed, 77, pp. 209-231; Eibrand, R., Kennedy, P., Cotter, D., MacEvilly, U., Wu, B., Analysis of Atlantic salmon skin mucus: COPS - A computer-based system for protein pattern analysis of 1D SDS-PAGE gels (2003) Proc. IEEE Symp. Bioinf. BioEng, pp. 45-52; Gerasimov, A., Use of the software processing of scanned chromatogram images in quantitative planar chromatography (2004) J. Anal. Chem, 59, pp. 348-353; Goulding, P., (2000) Electrophoresis Gel Analysis Software: Important Aspects, p. 14. , Cambridge, U.K, UVItec Ltd; Jedra, M., El Khattabi, N., Limouri, M., Essaid, A., Recognition of seed varieties using a time-delay neural network: Analysis of electrophoretic images (1999) Comput. Electron. Agric, 22, pp. 1-10; Machado, A., Campos, M., Siqueira, A., Carvalho, O., An iterative algorithm for segmenting lanes in gel electrophoresis images (1997) Proc. Comput. Graph. Image Process. X Braz. Symp, pp. 140-146. , Campos do Jordao, Brazil, Oct; Ye, X., Suen, C., Cheriet, M., Wang, E., A recent development in image analysis of electrophoresis gels (1999) Proc. Vis. Interface, pp. 432-438; Shadle, S., Allen, D., Guo, H., Pogozelski, W., Bashkin, J., Tullius, T., Quantitative analysis of electrophoresis data: Novel curve fitting methodology and its application to the determination of a protein-DNA binding constant (1997) Nucleic Acids Res, 25, pp. 850-860; Bajla, I., Hollander, I., Burg, K., Improvement of electrophoretic gel image analysis (2001) Meas. Sci. Rev, 1, pp. 5-10; Bajla, I., Hollander, I., Burg, K., Fluch, S., A novel approach to quantitative analysis of electrophoretic gel images of DNA fragments (2002) Proc. IEEE Int. Symp. Biomed. Imag, pp. 899-902; Lonni, A., Scarminio, I., Silva, L., Ferreira, D., Differentiation of species of Baccharis Genus by HPLC and chemometrics methods (2003) Anal. Sci, 19, pp. 1013-1017; Beltrán, N., Duarte-Mermoud, M., Salah, S., Bustos, M., Feature selection algorithms using Chilean wine chromatograms as examples (2005) J. Food Eng, 67, pp. 483-490; Landgrebe, D., Information extraction principles and methods for multispectral and hyperspectral image data (2000) Information Processing for Remote Sensing, , Hackensack, NJ: World Scientific, ch. 1; Landgrebe, D., Hyperspectral image data analysis as a high dimensional signal processing problem (2002) IEEE Signal Process. Mag, 19 (1), pp. 17-28. , Jan; Jimenez, L., Landgrebe, D., Hyperspectral data analysis and feature reduction via projection pursuit (1999) IEEE Trans. Geosci. Remote Sens, 37 (6), pp. 2653-2667. , Nov; Jimenez, L., Landgrebe, D., Supervised classification in high- dimensional space: Geometrical, statistical, and asymptotical properties of multivariate data (1998) IEEE Trans. Syst., Man, Cybern, 28 (1), pp. 39-54. , Pt. C, Feb; Marques deSá, J., (2001) Pattern Recognition - Concepts, Methods and Applications, , Berlin, Germany: Springer-Verlag; Heijden, F., Duin, R., Ridder, D., Tax, D., (2004) Classification, Parameter Estimation and State Estimation, , New York: Wiley; Dudoit, S., Fridlyand, J., Speed, T., Comparison of discrimination methods for the classification of tumors using gene expression data (2002) J. Amer. Stat. Assoc, 97, pp. 77-87; Zomer, S., Brereton, R., Carter, J., Eckers, C., Support vector machines for the discrimination of analytical chemical data: Application to the determination of tablet production by pyrolysis-gas chromatography-mass spectrometry (2004) Analyst, 129, pp. 175-181; Zomer, S., Guillo, C., Brereton, R., Hanna-Brown, M., Toxicological classification of urine samples using pattern recognition techniques and capilarity electrophoresis (2003) Anal. Bioanal. Chem, 378, pp. 2008-2020; Fan, X., Bai, J., Shen, P., Diagnosis of breast cancer using HPLC metabonomics fingerprints coupled with computational methods (2005) 27th Annu. Conf. Eng. Med. Biol, pp. 6081-6084. , Shanghai, China; Skurichina, M., Raudys, S., Duin, R., K-nearest neighbors directed noise injection in multilayer perceptron training (2000) IEEE Trans. Neural Netw, 11 (2), pp. 504-511. , Mar; Ha, T., Bunke, H., Off-line, handwritten numeral recognition by perturbation method (1997) IEEE Trans. Pattern Anal. Mach. Intell, 19, pp. 535-539; Lee, S., Noisy replication in skewed binary classification (2000) Comput. Stat. Data Anal, 34, pp. 165-191; Demant, C., Streicher-Abel, B., Waszkewitz, P., (1999) Industrial Image Processing, , New York: Springer-Verlag; Dempster, A., Laird, N., Rubin, D., Maximum likelihood from incomplete data via the EM algorithm (1977) J. Roy. Stat. Soc. B, 39 (1), pp. 1-38; Moré, J., Sorensen, D., Computing a trust region step (1983) SIAM J. Sci. Stat. Comput, 4, pp. 553-572; Byrd, R., Schnabel, R., Shultz, G., Approximate solution of the trust region problem by minimization over two-dimensional subspaces (1988) Math. Program, 40, pp. 247-263; Sousa, A., Mendonça, A., Campilho, A., Aguiar, R., Miranda, C., Feature extraction for classification of thin-layer chromatography images (2005) Lecture Notes in Computer Science, 3656, pp. 974-981. , Image Analysis and Recognition, New York: Springer-Verlag; Ripley, B., (2004) Pattern Recognition and Neural Networks, , New York: Cambridge Univ. Press; Visa, S., Ralescu, A., Learning imbalanced and overlapping classes using fuzzy sets (2003) ICML 2003, Workshop Learn. Imbalanced Datasets, 2. , presented at the, Washington, DC
Keywords: Acoustic variables control; Algorithms; article; Chromatographic analysis; Chromatographic pattern features; Chromatographic profiles; Chromatography; Chromatography, Thin Layer; Classification; Diagnosis, Computer-Assisted; Gaussian noise (electronic); Hierarchical classifier; Humans; Hydrolases; imaging; Lysosomal Storage Diseases; lysosome storage disease; mathematical analysis; nerve degeneration; noise; normal distribution; Pattern recognition; Pattern Recognition, Automated; Reproducibility of Results; sensitivity and specificity; Urinalysis

A clinical report of bone regeneration in maxillofacial surgery using bonelike® synthetic bone graft - Sousa, R.C.; Lobato, J.V.; Maurício, A.C.; Hussain, N.S.; Botelho, C.M.; Lopes, M.A.; Santos, J.D. (Journal of Biomaterials ApplicationsJ. Biomater. Appl., 2008)
The objective of this study is to evaluate the osteoconductivity and bioactivity of the Bonelike® graft in repairing surgical cystic bone defects. Bonelike® is implanted in 11 patients, aged between 24 and 53 years with a mean age of 36 years, consisting of 5 men and 6 women. According to the standard follow up protocols, radiological examinations are performed and Bonelike® /bone retrieved samples have been analyzed histologically using non-decalcified sections obtained perpendicular to bone length axis. Radiographic examination and histological results clearly demonstrate an extensive new bone formation apposed on Bonelike® granules with a significant degree of maturation. These clinical applications in maxillary bone defects indicate perfect bone bonding between new bone formed and Bonelike® granules, along with partial surface biodegradation. This quick and effective osteoconductive response from Bonelike® may reduce the time needed to reconstruct the bone defected area of patients. © 2008 Sage Publications.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JBAPEdoi: 10.1177/0885328207078260Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua Campo Alegre 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Bone SubstitutesReferences: Mohamed, A., Sudha, K., Kim, F., Karl, K., Scott, P.B., Bone Graft Substitutes (2003) Cell Based Approaches for Bone Graft Substitutes, p. 127. , In: Laurencin, C.T. (ed.), Chapter 7 ASTM - International, USA;Mellonig, J.T., Prewett, A.B., Moyer, M.P., HIV Inactivation in a Bone Allograft (1992) J. Periodontol., 63, p. 979; Buck, B.E., Malinin, T.I., Brown, M.D., Bone Transplantation and Human Immunodeficiency Virus. An Estimate of Risk of Acquired Immunodeficiency Syndrome (AIDS) (1989) Clin. Orthop., 240, p. 129; Mary, E.A.R., Raymond, A.Y., Bone Replacement Grafts - The Bone Substitutes (1998) Dent. Clin. North Am., 42 (3), p. 491; Doron, I.I., Amy, L.L., Bone Graft Substitutes (2002) Oper. Tech. Plast. Reconsr. Surg., 9 (4), p. 151; Wright, S., Commentary The Bone-Graft Market in Europe, in Emerging Technologies in Orthopedics I: Bone Graft Substitutes (1999) Bone Growth Stimulators and Bone Growth Factors By Datamonitor Plc, p. 591; Knaack, D., Goad, M.E.P., Aiolova, M., Christian, R., Ali, T., Promod, C., Duke Lee, D., Resorbable Calcium Phosphate Bone Substitute (1998) J. Biomed. Mater. Res., 43, p. 399; Frayssinet, P., Trouillet, J.L., Rouquet, N., Azimus, E., Autefage, A., Osseointegration Macroporous Calcium Phosphate Ceramics Having a Different Chemical Composition (1993) Biomaterials, 14, p. 423; Klein, C.P.A.T., Driessen, A.A., Groot de, K., van den Hooff, A., Biodegradation Behavior of Various Calcium Phosphate Materials in Bone Tissue (1983) J. Biomed. Mater. Res., 17, p. 769; Daculsi, G., Biphasic Calcium Phosphate Concept Applied to Artificial Bone, Implant Coating and Injectable Bone Substitute (1998) Biomaterials, 19, p. 1473; Santos, J.D., Hastings, G.W., Knowles, J.C., Sintered Hydroxyapatite Compositions and Method for the Preparation Thereof (1999) Worldwide Applications, , (PCT), Patent No. 1 189 851; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass Reinforced Hydroxyapatite: A Comprehensive Study of the Effect of Glass Composition on the Crystallography of the Composite (1998) J. Biomed. Mater. Res., 39, p. 244; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced Hydroxyapatite Composites: Fracture Toughness and Hardness Dependence on Microstructural Characteristics (1999) Biomaterials, 20, p. 2085; Lopes, M.A., Silva, R.F., Monteiro, F.J., Santos, J.D., Microstructural Dependence of Young's and Shear Moduli of P 2 O 2 Glass Reinforced Hydroxyapatite for Biomedical Applications (2000) Biomaterials, 21, p. 749; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., Push-out Testing and Histological Evaluation of Glass Reinforced Hydroxyapatite Composites Implanted in the Tibia of Rabbits (2001) J. Biomed. Mater. Res., 54, p. 463; Lobato, J.V., Hussain, N.S., Botelho, C.M., Rodrigues, J.M., Luís, A.L., Maurício, A.C., Lopes, M.A., Santos, J.D., Assessment of the Potential of Bonelike® Graft for Bone Regeneration by using an Animal Model (2005) Key. Eng. Mater., 877, pp. 284-286; Lobato, J.V., Hussain, N.S., Botelho, C.M., Mauricio, A.C., Afonso, A., Ali, N., Santos, J.D., Assessment of Bonelike® Graft with a Resorbable Matrix using an Animal Model (2006) Thin Solid Films, 515, p. 362; Duarte, F., Santos, J.D., Afonso, A., Medical Applications of Bonelike® in Maxillofacial Surgery (2004) Mater. Sci. Forum, 370, pp. 455-456; Gutierres, M., Hussain, N.S., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Santos, J.D., Biological Behaviour of Bonelike® Graft Implanted in Tibia of Humans (2005) Key Eng. Mater., 1041, pp. 284-286; LeGeros, R.Z., Properties of Osteoconductive Biomaterials: Calcium Phosphates (2002) Clin. Orthop., 395, p. 81; Robert, D.A.G., Hanneke, G.T., Ronald, J.H., Buma, P., Mechanism of Bone Incorporation of β-TCP Bone Substitute in Open Wedge Tibial Osteotomy in Patients (2005) Biomaterials, 26, p. 6713; Hirotsugu, H., Norio, A., Kimimitsu, O., Noritaka, F., Ohnishi, H., Okada, A., Nomura, S., Maeda, T., A Histological Evaluation on Self setting α-tricalcium Phosphate Applied in the Rat Bone Cavity (2004) Biomaterials, 25, p. 431; Meinel, L., Betz, O., Fajardo, R., Hofmann, S., Nazarian, A., Cory, E., Hilbe, M., Kirker-Head, C., Silk Based Biomaterials to Heal Critical Sized Femur Defects (2006) Bone, 39, p. 922; Lim, S.C., Lee, M.J., Yeo, H.H., Effects of Various Implant Materials on Regeneration of Calvarial Defects in Rats (2000) Pathol. Int., 50, p. 594; Carano, R.A.D., Filvaroff, E.H., Angiogenesis and Bone Repair (2003) Drug Discov. Today, 21, p. 980; Gutierres, M., Hussain, N.S., Lopes, M.A., Afonso, A., Cabral, A.T., Almeida, L., Santos, J.D., Histomorphometric Measurements Histological and SEM Analyses of bone/ implant Interface: Clinical Trials using Bonelike® Granules (2006) J. Orthop. Res., 24, p. 953
Keywords: adult; article; Bioactivity; Bone; bone prosthesis; Bone Regeneration; Bone Substitutes; bone transplantation; Bonelike®; clinical trial; facial bone; Facial Bones; Female; Histological studies; histology; human; Humans; Implants (surgical); instrumentation; male; Maxillofacial surgery; methodology; Middle Aged; oral surgery; Pathology; Radiography; Radiology; Regeneration; Surgery; Surgery, Oral; Synthetic bone graft; treatment outcome

Comparative study of nanohydroxyapatite microspheres for medical applications - Mateus, A.Y.P.; Barrias, C.C.; Ribeiro, C.; Ferraz, M.P.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2008)
This study concerns the preparation, physical, and in vitro characterization of two different types of hydroxyapatite (HA) microspheres, which are intended to be used as drug-delivery systems and bone-regeneration matrices. Hydroxyapatite nanoparticles (HA-1 and HA-2) were prepared using the chemical precipitation synthesis with H 3PO 4, Ca(OH) 2, and a surfactant, SDS (sodium dodecyl sulfate), as starting reagents. The HA powders were dispersed in a sodium alginate solution, and spherical particles were obtained by droplet extrusion coupled with ionotropic gelation in the presence of Ca 2+. These were subsequently sintered to produce HA-1 and HA-2 microspheres with a uniform size and interconnected microporosity. Both powders and microspheres were characterized using FTIR and X-ray diffraction. Moreover, SEM and mercury intrusion porosimetry were used to analyze the microspheres, and TEM was used to analyze the powders. Results showed that pure HA and mixtures of HA/β-TCP in the nanometer range and needlelike shape were obtained for HA-1 and HA-2 powders, respectively. Neutral Red, scanning electron microscopy and confocal microscopy were used to evaluate the behavior of osteoblastic-like MG-63 cells cultured on HA microspheres surfaces for 7 days. Results showed that good adhesion and proliferation of osteoblasts on the HA microspheres surface. Cells built bridges between adjacent microspheres, forming microspheres-cells clusters in both types of materials. © 2007 Wiley Periodicals, Inc.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31634PubMed ID: 17975824Language of Original Document: EnglishCorrespondence Address: Mateus, A. Y. P.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: yovana@ibmc.up.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; calcium hydroxide, 1305-62-0; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; calcium, 7440-70-2; dodecyl sulfate sodium, 151-21-3; neutral red, 553-24-2; phosphoric acid, 7664-38-2; Biocompatible Materials; Durapatite, 1306-06-5; PowdersReferences: Jarcho, M., Calcium phosphates ceramics as hard tissue prosthetics (1981) Clin Orthop Relat Res, 157, pp. 259-278;Bucholz, R., Carlton, A., Holmes, R., Hydroxyapatite and tricalcium phosphate bone graft substitutes (1987) Orthop Clin N Am, 18, pp. 323-334; Daculsi, G., Passuti, N., Martins, S., Deudon, C., LeGeros, R., Raher, S., Macroporous calcium phosphate ceramic for ling bone surgery in humans and dogs: Clinical and histological study (1990) J Biomed Mater Res, 24, pp. 379-396; Gauthier, O., Bouler, J., Weiss, P., Bosco, J., Daculsi, G., Aguado, E., Kinetic study of bone in growth and ceramic resorption associated with the implantation of different injectable calcium-phosphate bone substitutes (1999) J Biomed Mater Res, 47, pp. 28-35; Rey, C., Calcium phosphate biomaterials and bone mineral: Differences in composition, structures and properties (1990) Biomaterials, 11, pp. 13-15; Yuan, H., Kurashina, K., de Bruijn, J., Li, Y., de Groot, K., Zhang, X., A preliminary study on osteoinduction of two kinds of calcium phosphate ceramics (1999) Biomaterials, 20, pp. 1799-1806; Liou, S., Chen, S., Liu, D., Synthesis and characterization of needlelike apatitic nanocomposite with controlled aspect ratios (2003) Biomaterials, 24, pp. 3981-3988; Earl, J.S., Wood, D.J., Mile, S.J., Hydrothermal synthesis of hydroxyapatite (2006) J Phys Conf, 26, pp. 268-271; Han, J.K., Song, H.Y., Fumio, S., Lee, B.T., Synthesis of high purity nano-sized hydroxyapatite powder by microwave-hydrothermal method (2006) Mater Chem Phys, 99, pp. 235-239; Yoshimura, M., Sujaridworakun, P., Koh, F., Fujiwara, T., Pongkao, D., Ahniyaz, A., Hydrothermal conversion of calcite crystals to hydroxyapatite (2004) Mater Sci Eng C, 24, pp. 521-525; Bogdanoviciene, I., Beganskiene, A., Tonsuaadu, K., Glaser, J., Meyer, H.J., Kareiva, A., Calcium hydroxyapatite Ca 10(PO 4) 6 (OH) 2 ceramics prepared by aqueous sol-gel processing (2006) Mater Res Bull, 41, pp. 1754-1762; Liu, D.M., Troczynski, T., Tseng, W.J., Water-based sol-gel synthesis of hydroxyapatite: Process development (2001) Biomaterials, 22, pp. 1721-1730; Bezzi, G., Celotti, G., Landi, E., La Torretta, T.M.G., Sopyan, I., Tampieri, A., A novel sol-gel technique for hydroxyapatite preparation (2003) Mater Chem Phys, 78, pp. 816-824; An, G.H., Wang, H.J., Kim, B.H., Jeong, Y.G., Choa, Y.H., Fabrication and characterization of a hydroxyapatite nanopowder by ultrasonic spray pyrolysis with salt-assisted decomposition (2007) Mater Sci Eng A, pp. 449-451,821-824; Varma, H.K., Babu, S., Synthesis of calcium phosphate bioceramics by citrate gel pyrolisis method (2005) Ceram Int, 31, pp. 109-114; Jarudilokkula, S., Tanthapanichakoonb, W., Boonamnuayvittayaa, V., Synthesis of hydroxyapatite nanoparticles using an emulsion liquid membrane system Colloids Surf A, , Forthcoming; Bose, S., Saha, S.K., Synthesis and characterization of hydroxyapatite nanopowders by emulsion technique (2003) Chem Mater, 15, pp. 4464-4469; Nayar, S., Sihna, M.K., Basu, D., Sinha, A., Synthesis and sintering of biomimetic hydroxyapatite nanoparticles for biomedical applications (2006) J Mater Sci: Mater Med, 17, pp. 1063-1068; Tas, A.C., Synthesis of biomimetic Ca-hydroxyapatite powders at 37°C in synthetic body fluids (2000) Biomaterials, 21, pp. 1429-1438; Wanga, A., Yina, H., Liua, D., Wub, H., Wadac, Y., Rena, M., Xua, Y., Chenga, X., Effects of organic modifiers on the size-controlled synthesis of hydroxyapatite nanorods (2007) Appl Surf Sci, 253, pp. 3311-3316; Zhang, H.G., Zhu, Q., Surfactant-assisted preparation of fluoride-substituted hydroxyapatite nanorods (2005) Mater Lett, 59, pp. 3054-3058; Liu, Y., Houa, D., Wangb, G., A simple wet chemical synthesis and characterization of hydroxyapatite nanorods (2004) Mater Chem Phys, 86, pp. 69-73; Pang, Y.X., Bao, X., Influence of temperature, ripening time and calcination on the morphology and crystallinity of hydroxyapatite nanoparticles (2003) J Eur Ceram Soc, 23, pp. 1697-1704; Gitzhofer, B.E., Boulos, M.I., Morpholgical study of hydroxyapatite nanocrystal suspension (2000) J Mater Sci: Mater Med, 11, pp. 523-531; Barbosa, M., Granja, P., Barrias, C., Amaral, I., Polysaccharides as scaffolds for bone regeneration (2005) ITBM-RBM, 26, pp. 212-217; Hari, P., Chandy, T., Sharma, C., Chitosan/calcium-alginate beads for oral delivery of insulin (1996) J Appl Polym Sci, 59, pp. 1796-1801; Barrias, C.C., Ribeiro, C.C., Barbosa, M.A., Adhesion and proliferation of human osteoblastic cells seeded on injectable hydroxyapatite microspheres (2004) Key Eng Mater, pp. 254-262,877-880; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Preparation and characterisation of calcium-phosphate porous microspheres with a uniform size for biomedical applications (2006) J Mater Sci: Mater Med, 17, pp. 455-463; Bowersock, T., Martins, S., Vaccine delivery to animals (1999) Adv Drug Deliv Rev, 32, pp. 167-194; Kong, H., Smith, M., Mooney, D., Designing alginate hydrogels to maintain viability of immobilized cells (2003) Biomaterials, 24, pp. 4023-4029; Legallais, C., David, B., Doré, E., Bioartificial livers (BAL): Current technological aspects and future developments (2001) J Membr Sci, 181, pp. 81-95; Liu, X.D., Yu, W.Y., Zhang, Y., Xue, W.M., Yu, W.T., Xiong, Y., Ma, X.J., Yuan, Q., Characterization of structure and diffusion behaviour of Ca-alginate beads prepared with external or internal calcium sources (2002) J Microencapsul, 19 (6 -1), pp. 775-782; Taqieddin, E., Amiji, M., Enzyme immobilization in novel alginate-chitosan coreshell microcapsules (2004) Biomaterials, 25, pp. 1937-1945; Ribeiro, C., Barrias, C., Barbosa, M., Calcium phosphate-alginate microspheres as enzyme delivery matrices (2004) Biomaterials, 25, pp. 4363-4373; Kim, Y.J., Park, H.G., Yang, Y.L., Yoon, Y., Kim, S., Oh, E., Multifunctional drug delivery system using starch-alginate beads for controlled release (2005) Biol Pharm Bull, 28, pp. 394-397; Barrias, C., Ribeiro, C., Lamghari, M., Sa, C., Barbosa, M., Proliferation, activity and osteogenic differentiation of bone marrow stromal cells cultured on calcium titanium phosphate microspheres (2005) J Biomed Mater Res A, 72, pp. 57-66; Mateus, A.Y.P., Ferraz, M.P., Monteiro, F.J., Microspheres based on hydroxyapatite nanoparticles aggregates for bone regeneration (2007) Key Eng Mater, pp. 330-332,243-246; Mankani, M., Fowler, B., Kingman, A., Robey, P., In vivo bone formation by human bone marrow stromal cells: Effect of carrier particle size and shape (2001) Biotechonol Bioeng, 72, pp. 96-107; Higashi, T., Okamoto, H., Influence of particle size of calcium phosphate ceramics as a capping agent on the formation of a hard tissue barrier in amputated dental pulp (1996) J Endodoncy, 22, pp. 281-283; Guo, G., Xun, Y., Wnag, Z., Guo, H., Preparation of hydroxyapatite nanoparticles by reverse microemulsion (2005) Ceram Int, 331, pp. 869-872; Sun, X.M., Chen, X., Deng, Z.X., Li, Y.D., A CTAB-assited hydrothermal orientation growth of ZnO nanorods (2002) Mater Chem Phys, 78, pp. 99-104; Uota, M., Arakawa, H., Kitamura, N., Yoshimura, T., Tanaka, J., Kijima, T., Synthesis of high surface area hydroxyapatite nanoparticles by mixed surfactant-mediated approach (2005) Langmuir, 21, pp. 4724-4728; Balasundaram, G., Sato, M., Webster, T.J., Using hydroxyapatite nanoparticles and decreased crystallinity to promote osteoblast adhesion similar to functionalizing with RGD (2006) Biomaterials, 27, pp. 2798-2805; Wutticharoenmongkol, P., Sanchavanakit, N., Pavasant, P., Supaphol, P., Novel bone scaffolds or electrospun polycaprolactone fibers filled with nanoparticles (2006) J Nanosci Nanotechnol, 6, pp. 514-522; Gonzalez-McQuire, R., Green, D., Walsh, D., Hall, S., Chane-Ching, J., Oreffo, R.O.C., Mann, S., Fabrication of hydroxyapatite sponges by dextran sulphate/amino acid templating (2005) Biomaterials, 26, pp. 6652-6656; Sun, W.B., Wu, Y.F., Ding, Y., Chu, C.L., Liu, T.J., The expression and activity of alkaline phosphatase in human periodontal ligament cells with nanometer hydroxyapatite (2006) Zhonghua Kou Qiang Yi Xue Za Zhi, 41, pp. 348-349; Bowers, K., Keller, J.C., Randolph, B., Wick, D., Michaels, C., Optimization of surface micromorphology for enhanced osteoblast responses in vitro (1992) Int J Oral Maxillofac Impl, 7, pp. 302-310; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford Jr, J., Dean, D.D., Boyan, B.D., Effect of titanium surface roughness on proliferation, differentiation, and protein synthesis of human osteoblast-like cells (MG63) (1995) J Biomed Mater Res, 29, pp. 389-401; Boyan, B.D., Batzer, R., Kieswetter, K., Liu, Y., Cochran, D.L., Szmuckler-Monclers, S., Dean, D.D., Schwartz, Z., Titanium surface roughness alters responsiveness of MG63 osteoblastic-like cells to 1α,25-(OH) 2D 3 (1998) J Biomed Mater Res, 39, pp. 77-85
Keywords: alginic acid; analytic method; Apatite; article; Biocompatible Materials; Biological materials; biomaterial; Bone Regeneration; Calcium; calcium hydroxide; calcium phosphate; cell adhesion; Cell Line; cell proliferation; Chemical precipitation; Chemotherapy; Comparative studies; comparative study; controlled study; dodecyl sulfate sodium; Drug delivery; Drug delivery system (DDS); Drug Delivery Systems; Drug dosage; Durapatite; Gelation; human; human cell; Humans; hydroxyapatite; Hydroxyapatite (HAP); Hydroxylation; In vitro characterization; in vitro study; infrared spectroscopy; materials testing; Medical applications; Mercury intrusion porosimetry; microsphere; Microspheres; Nano-hydroxyapatite (n-HA); Nanohydroxyapatite; nanoparticle; nanoparticles; neutral red; osteoblast; Osteoblasts; Particle Size; phosphoric acid; porosity; powder; Powders; precipitation; Precipitation (chemical); reagent; Regeneration (renovating); Scanning electron microscopy; surfactant; synthesis; Synthesis (chemical); X ray diffraction

Frequency domain and entropy analysis of fetal heart rate: Appealing tools for fetal surveillance and pharmacodynamic assessment of drugs - Gonçalves, H.; Rocha, A.P.; Ayres-de-Campos, D.; Bemardes, J. (Cardiovascular and Hematological Disorders - Drug TargetsCardiovasc. Hematol. Disord. Drug Targets, 2008)
Recently, frequency domain and entropy analysis of fetal heart rate (FHR) have been assessed in several studies, providing new insights into physiologic regulatory mechanisms, constituting appealing tools for pharmacodynamic assessment, namely during fetal life. There is evidence that entropy and frequency domain analysis convey information on cortical and autonomic nervous system activities, respectively. Use of internal versus external FHR acquisition sensors and the signal sampling frequency may dramatically affect results. Most FHR frequency domain indices are significantly increased with rising fetal activity, namely during active wakefulness and active sleep, whereas the opposite occurs with nonlinear indices. This is in favour of increased activity of the autonomous nervous system and decreased activity of the central nervous system complexity control systems, during periods of fetal activity. Progression of labor is associated with a significant increase in FHR frequency domain indices, whereas entropy indices are significantly decreased. This denotes activation of the autonomic nervous system in the final minutes of labour, associated with decreased central nervous system activity. The emerging knowledge on FHR frequency domain and entropy analysis substantiates a continued interest of these methods in evaluation of the fetal pathophysiologic regulatory mechanisms, and opens new perspectives for clinical and pharmacodynamic assessment. © 2008 Bentham Science Publishers Ltd.
Cited By (since 1996): 1Export Date: 21 November 2012Source: Scopusdoi: 10.2174/187152908784533720Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Departamento de Matemática Aplicada, Faculdade de Ciências, Universidade do Porto, Rua do Campo Alegre 687, 4169-007 Porto, Portugal; email: hernani.goncalves@fc.up.ptChemicals/CAS: atropine, 51-55-8, 55-48-1; betamethasone, 378-44-9; lidocaine, 137-58-6, 24847-67-4, 56934-02-2, 73-78-9; magnesium sulfate, 7487-88-9; opiate, 53663-61-9, 8002-76-4, 8008-60-4; propranolol, 13013-17-7, 318-98-9, 3506-09-0, 4199-09-1, 525-66-6; salbutamol, 18559-94-9References: Task-Force. Heart rate variability. Standards of measurement, physiological interpretation, and clinical use. Task Force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology (1996) Eur. Heart J, 17, pp. 354-381;Beckers, F., Verheyden, B., Aubert, A.E., Aging and nonlinear heart rate control in a healthy population (2006) Am. J. Physiol. Heart Circ. Physiol, 29, pp. H2560-H2570; Pincus, S.M., Minkin, M.J., Assessing sequential irregularity of both endocrine and heart rate rhythms (1998) Curr. Opin. Obstet. Gynecol, 1 (4), pp. 281-291; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring (1987) Int. J. Gynecol. Obstet, 25, pp. 159-167; American College of Obstetricians and Gynecologists. ACOG Practice Bulletin. Clinical Management Guidelines for Obstetrician-Gynecologists, Number 70, December 2005 (2005) Int. J. Gynecol. Obstet, 1, pp. 1453-1460. , ACOG; (2001) Royal College of Obstetricians and Gynaecologists. Evidence-Based Clinical Guideline Number 8. The Use of Electronic Fetal Monitoring, , RCOG, Royal College of Obstetricians and Gynaecologists: London; International Federation of Gynecology and Obstetrics. Intrapartum surveillance: Recommendations on current practice and overview of new developments. FIGO Study Group on the Assessment of New Technology. International Federation of Gynecology and Obstetrics (1995) Int. J. Gynecol. Obstet, 49 (2), pp. 213-221. , FIGO; National Institute of Child Health and Human Development Research Planning Worlshop. Electronic fetal heart rate monitoring: Research guidelines for interpretation (1997) Am. J. Obstet. Gynecol, 177, pp. 1385-1390. , NICH; Dawes, G.S., Moulden, M., Redman, C.W.G., System 8000 - Computerized antenatal FHR analysis (1991) J. Perinat. Med, 19 (1-2), pp. 47-51; Bernardes, J., Moura, C., Marques-de-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J. Perinat. Med, 19, pp. 61-65; Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sá, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J. Mat. Fet. Med, 9, pp. 311-318; Bernardes, J., Ayres-de-Campos, D., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int. J. Gynecol. Obstet, 2, pp. 141-147; Bernardes, J., Costa-Pereira, A., The effect of different sampling intervals on the measurement of intrapartum fetal heart rate variability. Letter to the Editor (1997) Obstet. Gynecol, 9, pp. 318-319; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in expert's classification of cardiotocograms and subsequent clinical decision (1999) Br. J. Obstet. Gynecol, 1, pp. 1307-1310; Ayres-de-Campos, D., Bernardes, J., Early, variable and late decelerations: Can a consensus be reached in their identification? (1999) Int. J. Gynecol. Obstet, 5 (3), pp. 305-306; Grant, J.M., The fetal heart rate trace is normal, isn't it? Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Bernardes, J.; Costa-Pereira, A. Efficacy and safety of intrapartum electronic fetal monitoring: An update. Obstet. Gynecol., 1996}, 87 3, 476-477Bernardes, J., Costa-Pereira, A., Admission cardiotocography (2003) Lancet, 3 (1), p. 1741; Alfirevic, Z., Devane, D., Gyte, G.M.L., Continuous cardiotocography (CTG) as a form of electronic fetal monitoring (EFM) for fetal assessment during labour (2006) Coch. Data. Sys. Rev, 3; Pincus, S., Viscarello, R., Approximate Entropy: A regularity measure for fetal heart rate analysis (1992) Obstet. Gynecol, 79 (2), pp. 249-255; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans. Biomed. Eng, 5 (3), pp. 365-373; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Med. Biol. Eng. Comput, 44 (1), pp. 847-855; Gonçalves, H., Bernardes, J., Rocha, A.P., Ayres-de-Campos, D., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Hum. Dev, 83, pp. 585-591; Parer, J.T., (1997) Handbook of Fetal Heart Rate Monitoring, , W. B. Saunders Company: Philadelphia, Pennsylvania; Oppenheimer, L.W., Lewinsky, R.M., Power spectral analysis of fetal heart rate (1994) Baillieres Clin. Obstet. Gynaecol, 8 (3), pp. 643-661; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Yaegashi, N., Murotsuki, J., Uehara, S., Yajima, A., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am. J. Obstet. Gynecol, 182, pp. 1227-1232; Li, X., Tang, D., Zhou, S., Zhou, G., Wang, C., Zhuang, Y., Wu, G., Shen, L., Redistribution of power spectrum of heart rate variability during acute umbilical artery embolism and hypoxemia in late-gestation fetal sheep (2004) Eur. J. Obstet. Gynecol. Reprod. Biol, 114, pp. 137-143; Court, D.J., Parer, J.T., In Research in Perinatal Medicine (1984) Experimental studies of fetal asphyxia and fetal heart rate interpretation, pp. 113-169. , Nathanielsz, P.W, Parer, J.T; Eds, Perinatology Press: New York; vanGeijn, H.P., Developments in CTG analysis (1996) Baillieres Clin. Obstet. Gynaecol, 1 (2), pp. 185-209; Bernardes, J., Costa-Pereira, A., A more objective fetal heart rate baseline estimation (1996) Br. J. Obstet. Gynaecol, 1 (3), pp. 714-715; Ayres-de-Campos, D., Bernardes, J., Marsal, K., Nickelsen, C., Makarainen, L., Banfield, P., Xavier, P., Campos, I., Can the reproducibility of fetal heart rate baseline estimation be improved? (2004) Eur. J. Obstet. Gynecol. Reprod. Biol, 112, pp. 49-54; Ayres-de-Campos, D., Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto ® multicentre validation study (2005) Eur. J. Obstet. Gynecol. Reprod. Biol, 118 (1), pp. 52-60; Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc. Natl. Acad. Sci. USA, 88, pp. 2297-2301; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am. J. Physiol. Heart. Circ. Physiol, 278, pp. H2039-H2049; Fusheng, Y., Bo, H., Qingyu, T., (1998) Nonlinear biomedical signal processing - Volume II: Dynamical analysis and modelling, pp. 72-91. , Ed, Approximate entropy and its application in biosignal analysis; IEEE Press: New York; Pincus, S., Approximate entropy (ApEn) as a complexity measure (1995) Chaos, 5 (1), pp. 110-117; Hayes, M., (1996) Statistical digital signal processing and modelling, , Jonh Wiley and Sons, Inc.:New York; Boog, G., Analyse informatisée du rythme cardiaque foetal au cours de la grossesse et de l'accouchement (2004) Encyclopédie Médico-Chirurgicale, 148, pp. 1-10. , 5.049-D-23; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters (2006) Physiol. Meas, 27, pp. 307-319; Magenes, G., Signorini, M.G., Arduini, D., Cerutti, S., Fetal heart rate variability due to vibroacoustic stimulation: Linear and nonlinear contribution (2004) Methods Inf. Med, 43 (1), pp. 47-51; Hallak, M.; Martinez-Poyer, J.; Kruger, M.L.; Hassan, S.; Blackwell, S.C.; Sorokin, Y. The effect of magnesium sulfate on fetal heart rate parameters: A randomized, placebo-controlled trial. Am. J. Obstet. Gynecol., 1999, 181 5 Part 1, 1122-1127Swartjes, J.M., van Geijn, H.P., Meinardi, H., Mantel, R., Fetal heart-rate patterns and chronic exposure to antiepileptic drugs (1992) Epilepsia, 33 (4), pp. 721-728; Bernardes, J., Costa-Pereira, A., Ayres-de-Campos, D., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int. J. Gynecol. Obstet, 57 (1), pp. 33-37; Rotmensch, S., Lev, S., Kovo, M., Efrat, Z., Zahavi, Z., Lev, N., Celentano, C., Ben-Rafael, Z., Effect of betamethasone administration on fetal heart rate tracing: A blinded longitudinal study (2005) Fetal. Diagn. Ther, 2 (5), pp. 371-376; Lunshof, M.S., Boer, K., Wolf, H., Koppen, S., Velderman, J.K., Mulder, E.J.H., Short-term (0-48h) effects of maternal betamethasone administration on fetal heart rate and its variability (2005) Pediatr. Res, 57 (4), pp. 545-549; Beckers, F.; Verheyden, B.; Ramaekers, D.; Swinghedauw, B.; Aubert, A.E. Effects of autonomic blockade on non-linear cardiovascular variability indices in rats. Clin. Exp. Pharmacol. Physiol., 2006, 33 5-, 431-439Georgoulas, G., Stylios, C.D., Groumpos, P.P., Predicting the risk of metabolic acidosis for newborns based on fetal heart rate signal classification using support vector machines (2006) IEEE Trans. Biomed. Eng, 53 (5), pp. 875-884; DiRenzo, G.C., Montani, M., Fioriti, V., Clerici, G., Branconi, F., Pardini, A., Indraccolo, R., Cosmi, E.V., Fractal analysis: A new method for evaluating fetal heart rate variability (1996) J. Perinat. Med, 24 (3), pp. 261-269; Felgueiras, C., Marques-de-Sá, J.P., Bernardes, J., Gama, S., Fractal characterisation of fetal heart rate sequences (1998) Biomed. Eng, 3 (2), pp. 197-201;
Keywords: acidemia; adrenergic receptor stimulating agent; alpha adrenergic receptor blocking agent; anticonvulsive agent; article; atropine; autonomic nervous system function; beta adrenergic receptor blocking agent; betamethasone; Cardiotocography; central depressant agent; central nervous system function; cholinergic receptor blocking agent; chronotropism; Computerized analysis; drug effect; drug mechanism; electronic sensor; entropy; External and internal monitoring; Female; Fetal behavioral states; Fetal heart rate (FHR); Fetal monitoring; fetus; fetus heart rate; fetus monitoring; frequency analysis; Frequency domain and entropy analysis; gestation period; Heart rate variability; Heart Rate, Fetal; human; Humans; instrumentation; labor; lidocaine; local anesthetic agent; magnesium sulfate; mathematical computing; methodology; nonhuman; opiate; pharmacodynamics; physiology; Pregnancy; prenatal screening; propranolol; pulse rate; review; salbutamol; signal detection

Hip fractures cluster in space: An epidemiological analysis in Portugal - De Pina, M.F.; Alves, S.M.; Barbosa, M.; Barros, H. (Osteoporosis InternationalOsteoporosis Int., 2008)
Summary: Using Portuguese hospital registers (2000-2002) we calculated age-standardized incidence rates of hip fractures. Spatial clusters of high incidence rates were found, with annual averages (per 100,000 inhabitants) varying from 154.4 to 572.2 and 77.3 to 231.5 for women and men, respectively. Geographic inequalities in the occurrence of hip fractures were also found. Introduction: The aim of this study was to identify spatial patterns in the incidence of hip fracture in Portugal during the period 2000 to 2002. Methods: From the National Hospital Discharge Register, admissions of patients (50 years of age or more) with low-energy hip fracture were selected. Age-standardized incidence rates in relation to the municipality of the patients' place of residence were calculated. Empirical Bayes estimators were used to smooth the local risk and spatial statistics methods were used to identify spatial clusters. Results: Of 25,634 hip fractures in individuals aged 50 years or more caused by low or moderate impact, 19,759 occurred in women (age, mean±SD, 80.6±8.6 years) and 5,875 in men (age 77.7±10.0 years). Incidence rates increased exponentially with age, being higher in women nation-wide (female to male ratio from 1.5 to 5.1). Significant geographic differences were found: the incidence rates (95% CI) varied from 154.4 (153.6-155.3) to 572.2 (569.5-575.0) in women and 77.3 (76.64-78.05) to 231.5 (229.9-233.0) in men per 100,000 inhabitants. Spatial autocorrelation values (Moran index) were 0.56 and 0.45 for women and men, respectively. Conclusion: Spatial clusters (p<0.0001) of high incidences were identified. Geographic differences in incidence rates were about threefold. Some regions had incidence rates as high as some north European countries. The geographic inequalities could be due to environmental or socioeconomic factors, but further investigation needs to be done to confirm this hypothesis. © 2008 International Osteoporosis Foundation and National Osteoporosis Foundation.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: OSINEdoi: 10.1007/s00198-008-0623-1PubMed ID: 18536955Language of Original Document: EnglishCorrespondence Address: De Pina, M. F.; Laboratório de Biomateriais, INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre, 823, Porto 4150-180, Portugal; email: fpina@ineb.up.ptReferences: Center, J., Eisman, J., The epidemiology and pathogenesis of osteoporosis (1997) Baillieres Clin Endocrinol Metab, 11, pp. 23-62. , 1;Cooper, C., Melton III, L.J., Marcus, R., Feldman, D., Kelsey, J., Magnitude and Impact of osteoporosis and fractures (1996) Osteoporosis, pp. 419-434. , Academic Press San Diego; Walker-Bone, K., Dennison, E., Cooper, C., Epidemiology of osteoporosis (2001) Rheum Dis Clin North Am, 27, pp. 1-18. , 1; Cummings, S.R., Melton III, L.J., Epidemiology and outcomes of osteoporotic fractures (2002) Lancet, 359, pp. 1761-1767; Cooper, C., Campion, G., Melton, L.J., Hip fractures in the elderly: A world-wide projection (1992) Osteoporos Int, 2, pp. 285-289; Karagas, M.R., Lu-Yao, G.L., Barrett, J.A., Heterogeneity of hip fracture: Age, race, sex, and geographic patterns of femoral neck and trochanteric fractures among the US elderly (1996) Am J Epidemiol, 143, pp. 677-682. , 7; Jordan, K.M., Cooper, C., Epidemiology of osteoporosis (2002) Best Pract Res Clin Rheumatol, 16, pp. 795-806. , 5; Orimo, H., Hashimoto, T., Sakata, K., Trends in the incidence of hip fracture in Japan, 1987-1997: The third nationwide survey (2000) J Bone Miner Metab, 18, pp. 126-131; Kennedy, S., Goodchild, M., Gopal, S., The small number problem and the accuracy of spatial databases (1994) Accuracy of Spatial Databases, pp. 187-196. , Taylor and Francis London; (1995) Interactive Spatial Data Analysis, , Bailey TC, Gatrell AC (eds) Longman, London; Anselin, L., Local indicators of spatial association - LISA (1995) Geogr Anal, 27, pp. 93-115. , 2; Chevalley, T., Herrmann, F.R., Delmi, M., Evaluation of the age-adjusted incidence of hip fractures between urban and rural areas: The difference is not related to the prevalence of institutions for the elderly (2002) Osteoporos Int, 13, pp. 113-118; Sanders, K., Nicholson, G.C., Ugoni, A.M., Fracture rates lower in rural than urban communities: The Geelong Osteoporosis Study (2002) J Epidemiol Community Health, 56, pp. 466-470; Vaz, A.L., Epidemiology and costs of osteoporotic hip fractures in Portugal (1993) Bone, 14, p. 9. , Suppl 1; Lofthus, C.M., Osnes, E.K., Falch, J.A., Epidemiology of hip fractures in Oslo, Norway (2001) Bone, 29, pp. 413-418. , 5; Nydegger, V., Rizzoli, R., Rapin, C.H., Epidemiology of fractures of the proximal femur in Geneva: Incidence, clinical and social aspects (1991) Osteoporos Int, 2, pp. 42-47. , 1; Hernandez, J., Olmos, J.M., Alonso, M.A., Trend in hip fracture epidemiology over a 14-year period in a Spanish population (2006) Osteoporos Int, 17, pp. 464-470; Giversen, I.M., Time trends of age-adjusted incidence rates of first hip fractures: A register-based study among older people in Viborg County, Denmark, 1987-1997 (2006) Osteoporos Int, 17, pp. 552-564; Coster, A., Haberkamp, M., Allolio, B., Incidence of femoral neck fractures in the German Federal Republic in comparison to other countries (1994) Soz Praventivmed, 39, pp. 287-292. , 5; Paspati, I., Galanos, A., Lyritis, G.P., Hip fracture epidemiology in Greece during 1977-1992 (1998) Calcif Tissue Int, 62, pp. 542-547. , 6; Kannus, P., Niemi, S., Parkkari, J., Hip fractures in Finland between 1970 and 1997 and predictions for the future (1999) Lancet, 353, pp. 802-805. , 9155
Keywords: adult; Age Distribution; aged; Aged, 80 and over; article; Bayes Theorem; Bone Density; Cluster Analysis; Databases, Factual; falling; Female; fracture; geographic information system; Geographic information systems; hip fracture; Hip fractures; human; Humans; incidence; international classification of diseases; major clinical study; male; Middle Aged; Osteoporosis; Portugal; priority journal; Risk Factors; sex difference; Sex Distribution; Space-Time Clustering; Spatial analysis; Spatial clusters; Spatial dependency

Jaw avascular osteonecrosis after treatment of multiple myeloma with zoledronate - Lobato, J.V.; Maurício, A.C.; Rodrigues, J.M.; Cavaleiro, M.V.; Cortez, P.P.; Xavier, L.; Botelho, C.; Hussain, N.S.; Santos, J.D. (Journal of Plastic, Reconstructive and Aesthetic SurgeryJ. Plast. Reconstr. Aesthetic Surg., 2008)
Purpose: Multiple myeloma, the second most common haematopoietic cancer, which represents the collection of plasma-cell neoplasms that invariably becomes fatal when self-renewing myeloma cells begin unrestrained proliferation. The major clinical manifestation of multiple myeloma is related to the loss of bone through osteolysis. This can lead to pathologic fractures, spinal cord compression, hypercalcaemia, and pain. It is also a major cause of morbidity and mortality in these patients, who frequently require radiation therapy, surgery and analgesic medications. Bisphosphonates are specific inhibitors of osteoclastic activity, and are currently used to prevent bone complications and to treat malignant hypercalcaemia in patients with multiple myeloma, or bone metastases from breast and prostate cancers. Hence, osteonecrosis of the mandible has been reported in three patients from Centro Hospitalar de Vila Nova de Gaia (CHVNG) with multiple myeloma treated for over 18-48 months with intravenous zoledronate, commonly prescribed for multiple myeloma therapy. Although, this report alerts clinicians about the potential complication of bone necrosis in patients receiving bisphosphonate therapy, many questions remain concerning the underlying pathogenesis of this process. Patients and methods: The medical and dental records of three patients with multiple myeloma, who were treated in CHVNG in the past 4 years, were reviewed. These three patients presented exposed bone and osteonecrosis of the mandible, and shared one common clinical feature: all of them were treated with bisphosphonate zoledronate, administered intravenously for long periods. Sequential orthopantomograms (OPGs) and histological evaluation have been analysed from the biopsies of the non healing dental extraction sites of these patients. Results: After a routine dental extraction, these patients developed avascular osteonecrosis of the mandible and secondary bone infection with Actinomyces israelii (actinomycotic osteomyelitis), with no evidence of metastatic disease evaluated by biopsy. In these three described clinical cases, surgical debridment without flap elevation, intensive antibiotherapy and the suspension of the zoledronate treatment allowed a partial recovery of the patients. The purpose of this clinical report is to point out that patients suffering from multiple myeloma can develop bone osteonecrosis induced by treatment with bisphosphonates. Research to determine the mechanism of this dental phenomenon is needed to fully validate and substantiate the possible link between bisphosphonate treatment of multiple myeloma or other cancer diseases and avascular osteonecrosis of the jaws. Until then, clinicians involved in the care of patients at risk should consider this possible complication. © 2006 British Association of Plastic, Reconstructive and Aesthetic Surgeons.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.bjps.2006.06.016PubMed ID: 18068658Language of Original Document: EnglishCorrespondence Address: Maurício, A.C.; Centro de Estudos de Ciência Animal (CECA), Instituto de Ciências, Tecnologias Agrárias e Agro-Alimentares (ICETA), Campus Agrario Vairao, Rua Padre Armando Quintas, 4485-661 Vairão, Portugal; email: ana.colette@mail.icav.up.ptChemicals/CAS: amoxicillin, 26787-78-0, 34642-77-8, 61336-70-7; cyclophosphamide, 50-18-0; cyclosporin, 79217-60-0; dexamethasone, 50-02-2; erythropoietin, 11096-26-7; thalidomide, 50-35-1; zoledronic acid, 118072-93-8, 131654-46-1, 165800-06-6, 165800-07-7; Bone Density Conservation Agents; Diphosphonates; Imidazoles; zoledronic acid, 118072-93-8References: Mundy, G.R., Bertoline, D.R., Bone destruction and hypercalcemia in plasma cell myeloma (1986) Semin Oncol, 13 (3), pp. 291-299;Belch, A.R., Bergsagel, D.E., Wilson, K., Effect of daily etidronate on the osteolysis of multiple myeloma (1991) J Clin Oncol, 9 (8), pp. 1397-1402; Kyle, R.A., Jowsey, J., Kelly, P.J., Multiple myeloma bone disease. The comparative effect of sodium fluoride and calcium carbonate or placebo (1975) N Engl J Med, 293 (26), pp. 1334-1338; Kyle, R.A., Multiple myeloma: review of 869 cases (1975) Mayo Clin Proc, 50 (1), pp. 29-40; Roodman, G.D., Pathogenesis of myeloma bone disease (2004) Blood Cells Mol Dis, 32 (2), pp. 290-292; Berenson, J.R., Myeloma bone disease (2005) Best Pract Res Clin Haematol, 18 (4), pp. 653-672; Ruggerio, S.L., Mekrotra, B., Rosenberg, T.J., Osteonecrosis of the jaws associated with the use of bisphosphonates: a review of 63 cases (2004) J Oral Maxillofac Surg, 62, pp. 527-534; Rodan, G.A., Fleisch, H.A., Bisphosphonates: mechanism of action (1996) J Clin Invest, 97 (12), pp. 2692-2696; Coleman, R.E., Metastatic bone disease: clinical features, pathophysiology and treatment strategies (2001) Cancer Treat Rev, 27 (3), pp. 165-176; Sietsema, W.K., Ebetino, F.H., Salvagno, A.M., Antiresorptive dose-response relationship across three generations of bisphosphonates (1989) Drugs Exp Clin Res, 15 (9), pp. 389-396; Schenk, R., Eggli, P., Fleisch, H., Quantitative morphometric evaluation of the inhibitory activity of new amino-bisphosphonates on bone resorption in the rat (1986) Calcif Tissue Int, 38, pp. 342-349; Jung, A., Bisaz, S., Fleisch, H., The binding of pyrophosphate and two diphosphonates by hydroxyapatite crystals (1973) Calcif Tissue Res, 11 (4), pp. 269-280; Coukell, A.J., Markham, A., Pamidronate. A review of its use in the management of osteolytic bone metastases, tumor-induced hypercalcaemia and Paget's disease of bone (1998) Drugs Aging, 12 (2), pp. 149-168; Hughes, D.E., MacDonald, B.R., Russel, R.G.G., Inhibition of osteoclast-like cell formation by bisphosphonates in long-term cultures of human bone marrow (1989) J Clin Invest, 83 (6), pp. 1930-1935; Hughes, D.E., Wright, K.R., Uy, H.L., Bisphosphonates promote apoptosis in murine osteoclasts in vitro and in vivo (1995) J Bone Miner Res, 10 (10), pp. 1478-1487; Murakami, H., Takahashi, N., Sasaki, T., A possible mechanism of the specific action of bisphosphonates on osteoclasts: tiludronate preferentially affects polarized osteoclasts having ruffled borders (1995) Bone, 17 (2), pp. 137-144; Sahni, M., Guenther, H.L., Fleisch, H., Bisphosphonates act on rat bone resorption through the mediation of osteoblasts (1993) J Clin Invest, 91 (5), pp. 2004-2011; Fleisch, H., Bisphosphonates: mechanisms of action (1998) Endocr Rev, 19 (1), pp. 80-100; Shinoda, H., Adamek, G., Félix, R., Structure-activity relationships of various bisphosphonates (1983) Calcif Tissue Int, 35 (1), pp. 87-99; Pereira, J., Mancini, I., Walker, P., The role of bisphosphonates in malignant bone pain: a review (1998) J Palliat Care, 14 (2), pp. 25-36; Purohit, O.P., Radstone, C.R., Anthony, C., A randomized double-blind comparison of intravenous pamidronate and clodronate in the hypercalcemia of malignancy (1995) Br J Cancer, 72 (5), pp. 1289-1293; Hillner, B.E., Ingle, J.N., Chlebowski, R.T., American Society of Clinical Oncology 2003 update on the role of bisphosphonates and bone health issues in women with breast cancer (2003) J Clin Oncol, 21 (21), pp. 4042-4057. , [Erratum in J Clin Oncol 2004;22(7):1351]; Hillner, B.E., Ingle, J.N., Berenson, J.R., American Society of Clinical Oncology guideline on the role of bisphosphonates in breast cancer. American Society of Clinical Oncology Bisphosphonates Expert Panel (2000) J Clin Oncol, 18 (6), pp. 1378-1391; Lacerna, L., Hohneker, J., Zoledronic acid for the treatment of bone metastases in patients with breast cancer and other solid tumours (2003) Semin Oncol, 30 (5 SUPPL. 16), pp. 150-160; Lipton, A., Costa, L., Ali, S., Use of markers of bone turnover for monitoring bone metastases and the response to therapy (2001) Semin Oncol, 28 (4 SUPPL. 11), pp. 54-59; Brincker, H., Westin, J., Abildgaard, N., Failure of oral pamidronate to reduce skeletal morbidity in multiple myeloma: a double-blind placebo-controlled trial. Danish-Swedish Co-operative Study Group (1998) Br J Haematol, 101 (2), pp. 3280-3286; Berenson, J.R., Lichtenstein, A., Porter, L., Long-term pamidronate treatment of advanced multiple myeloma patients reduces skeletal events. Myeloma Aredia Study Group (1998) J Clin Oncol, 16 (7), pp. 593-602; Berenson, J.R., Vescio, R.A., Lee, S.R., Phase I dose-ranging trial of monthly infusions of zoledronic acid for the treatment of osteolytic bone metastases (2001) Clin Cancer Res, 7 (3), pp. 478-485; Van Poznak, C.H., The use of bisphosphonates in patients with breast cancer (2002) Cancer Control, 9 (6), pp. 480-489; Marx, R.E., Pamidronate (Aredia) and zoledronate (Zometa) induced avascular necrosis of the jaws: a growing epidemic (2003) J Oral Maxillofac Surg, 61 (9), pp. 1115-1117; Vannucchi, A.M., Ficarra, G., Antonioli, E., Osteonecrosis of the jaw associated with zoledronate therapy in patient with multiple myeloma (2005) Br J Haematol, 128 (6), pp. 738-739; Wang, J., Goodger, N.M., Pogrel, M.A., Osteonecrosis of the jaws associated with cancer chemotherapy (2003) J Oral Maxillofac Surg, 61 (9), pp. 1104-1107; Purcell, P.M., Boyd, I.W., Bisphosphonates and osteonecrosis of the jaw (2005) Med J Aust, 182 (8), pp. 417-418; Carter, G., Goss, A.N., Doecke, C., Bisphosphonates and avascular necrosis of the jaw: a possible association (2005) Med J Aust, 182 (8), pp. 413-415; Durie, B., Katz, M., Crowley, J., Osteonecrosis of the jaw and bisphosphonates (2005) N Engl J Med, 353, pp. 99-102; Migliorati, C.A., Bisphosphonates and oral cavity avascular bone necrosis (2003) J Clin Oncol, 21 (22), pp. 4253-4254; Robinson, N.A., Yeo, J.F., Bisphosphonates - a word of caution (2004) Ann Acad Med Singapore, 33 (4), pp. 48-49; Starck, W.J., Epker, B.N., Failure of osseointegrated dental implants after diphosphonate therapy for osteoporosis: a case report (1995) Int J Oral Maxillofac Implants, 10 (1), pp. 74-78; Melo, M., Obeid, G., Osteonecrosis of the maxilla in a patient with a history of bisphosphonate therapy (2005) J Can Dent Assoc, 71 (2), pp. 111-113
Keywords: Actinomyces israelii; adult; aged; amoxicillin; antibiotic therapy; article; avascular necrosis; Avascular osteonecrosis; biopsy; Bisphosphonates; Bone Density Conservation Agents; case report; clinical feature; cyclophosphamide; cyclosporin; dexamethasone; Diphosphonates; drug induced disease; drug inhibition; drug withdrawal; erythropoietin; Female; histology; human; Humans; hypercalcemia; Imidazoles; Jaw; jaw avascular osteonecrosis; male; Mandibular Diseases; morbidity; mortality; Multiple myeloma; osteolysis; Osteonecrosis; pain; panoramic radiography; pathologic fracture; priority journal; Radiography, Panoramic; risk assessment; spinal cord compression; thalidomide; tooth extraction; zoledronic acid

Linear and complex heart rate dynamics vary with sex in relation to fetal behavioural states - Bernardes, J.; Gonçalves, H.; Ayres-de-Campos, D.; Rocha, A.P. (Early Human DevelopmentEarly Hum. Dev., 2008)
Background: A better understanding of gender influences on fetal heart rate can help to improve analysis of the latter and perhaps elucidate the increased risk of perinatal death that occurs in males. Aim: To assess differences in linear and complex heart rate dynamics according to fetal sex, in the antepartum period of normal term pregnancies, for patterns associated with fetal behavioural states. Study design and subjects: One hundred and eighty seven fetal heart rate segments of 10-minute duration, acquired with a system for computerized analysis of cardiotocograms and classified into fetal behavioural patterns A, B, C or D were analysed. They had been acquired from 24 female and 23 male term fetuses, with uneventful perinatal outcomes. Four different comparative studies between female and male fetuses were conducted, considering different adjustments for gestational age, weight and FHR pattern. Outcome measures: Indices of linear and nonlinear fetal heart rate variability, namely, long-term irregularity index, very low, low and high frequency spectral indices, approximate entropy and sample entropy. Results: Pattern B was the most frequent, both in female and male fetuses. Pattern A was more likely to be associated to female than male fetuses, whereas the opposite occurred with patterns C and D. Linear indices were significantly higher in male than in female fetuses, whereas the opposite occurred with nonlinear indices. Conclusions: Male fetuses exhibited significantly more linear and significantly less complex fetal heart rate activity than female fetuses, expressing signs of a more active autonomous nervous system and of less active complexity control systems. These aspects may need to be considered when interpreting FHR tracings. © 2007 Elsevier Ireland Ltd. All rights reserved.
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: EHDEDdoi: 10.1016/j.earlhumdev.2007.12.001PubMed ID: 18248921Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Departamento de Ginecologia e Obstetrícia, Faculdade de Medicina, Universidade do Porto and INEB (Instituto Nacional de Engenharia Biomédica), Porto, Portugal; email: jbernardes@mail.telepac.ptReferences: Ingemarsson, I., Herbst, A., Thorngren-Jerneck, K., Long term outcome after umbilical artery acidaemia at term birth: influence of gender and duration of fetal heart rate abnormalities (1997) Br J Obstet Gynaecol, 104 (10), pp. 1123-1127;Ingemarsson, I., Gender aspects of preterm birth (2003) BJOG, 110 (SUPPL. 20), pp. 34-38; DiPietro, J.A., Hodgson, D.M., Costigan, K.A., Hilton, S.C., Johnson, T.R., Development of fetal movement-fetal heart rate coupling from 20 weeks through term (1996) Early Hum Dev, 44 (2), pp. 139-151; DiPietro, J.A., Costigan, K.A., Shupe, A.K., Pressman, E.K., Johnson, T.R., Fetal neurobehavioral development: associations with socioeconomic class and fetal sex (1998) Dev Psychobiol, 33 (1), pp. 79-91; Ogueh, O., Steer, P., Gender does not affect fetal heart rate variation (1998) Br J Obstet Gynaecol, 105 (12), pp. 1312-1314; Dawes, N.W., Dawes, G.S., Moulden, M., Redman, C.W., Fetal heart rate patterns in term labor vary with sex, gestational age, epidural analgesia, and fetal weight (1999) Am J Obstet Gynecol, 180, pp. 181-187; Lange, S., Van Leeuwen, P., Geue, D., Hatzmann, W., Gronemeyer, D., Influence of gestational age, heart rate, gender and time of day on fetal heart rate variability (2005) Med Biol Eng Comput, 43 (4), pp. 481-486; Gonçalves, H., Bernardes, J., Rocha, A.P., Ayres-de-Campos, D., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Hum Dev, 83 (9), pp. 585-591; Nijhuis, J.G., Prechtl, H.F., Martin Jr., C.B., Bots, R.S., Are there behavioural states in the human fetus? (1982) Early Hum Dev, 6 (2), pp. 177-195; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: the effect on linear and nonlinear parameters (2006) Physiol Meas, 27 (3), pp. 307-319; Goncalves, H., Rocha, A.P., Bernardes, J., Ayres-de-Campos, D., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Med Biol Eng Comput, 44 (10), pp. 847-855; Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sá, Pereira-Leite, L., SisPorto 2.0 - a program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318.; Magenes, G., Signorini, M.G., Arduini, D., Classification of cardiotocographic records by neural networks (2000) IJCNN 2000, Proceedings of the IEEE-INNS-ENNS International Joint Conference on Neural Networks, 3, pp. 637-641; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans Biomed Eng, 50, pp. 365-373; Task force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology, Heart rate variability - standards of measurement, physiological interpretation and clinical use (1996) Circulation, 17, pp. 354-381; Boog, G., Analyse informatisée du rythme cardiaque foetal au cours de la grosssesse et de l'accouchement (2004) Encyclopédie Médico-Chirurgicale, 148 (5-49 -D-23), pp. 1-10; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Yaegashi, N., Murotsuki, J., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am J Obstet Gynecol, 182, pp. 1227-1232; Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc Natl Acad Sci U. S. A., 88, pp. 2297-2301; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am J Physiol Heart Circ Physiol, 278, pp. H2039-H2049; Fusheng, Y., Bo, H., Qingyu, T., Approximate entropy and its application in biosignal analysis (1998) Nonlinear biomedical signal processing - Volume II: Dynamical analysis and modelling, pp. 72-91. , Akay M. (Ed), IEEE Press; Pincus, S., Viscarello, R., Approximate entropy: a regularity measure for fetal heart rate analysis (1992) Obstet Gynecol, 79, pp. 249-255; Martinez, W.L., Martinez, A.R., (2002) Computational statistics handbook with MATLAB, , CRC Press; Dudewicz, E., Mishra, S., (1998) Modern Mathematical Statistics, , John Wiley and Sons, Inc; Robles de Medina, P.G., Visser, G.H., Huizink, A.C., Buitelaar, J.K., Mulder, E.J., Fetal behaviour does not differ between boys and girls (2003) Early Hum Dev, 73 (1-2), pp. 17-26; Ryan, S.M., Goldberger, A.L., Pincus, S.M., Mietus, J., Lipsitz, L.A., Gender- and age-related differences in heart rate dynamics: are women more complex than men? (1994) J Am Coll Cardiol, 24 (7), pp. 1700-1707; Jensen-Urstad, K., Storck, N., Bouvier, F., Ericson, M., Lindblad, L.E., Jensen-Urstad, M., Heart rate variability in healthy subjects is related to age and gender (1997) Acta Physiol Scand, 160 (3), pp. 235-241; Beckers, F., Verheyden, B., Aubert, A.E., Aging and nonlinear heart rate control in a healthy population (2006) Am J Physiol Heart Circ Physiol, 290 (6), pp. H2560-H2570; Kuo, T.B., Yang, C.C., Sexual dimorphism in the complexity of cardiac pacemaker activity (2002) Am J Physiol Heart Circ Physiol, 283 (4), pp. H1695-H1702; Groome, L.J., Mooney, D.M., Holland, S.B., Smith, L.A., Atterbury, J.L., Dykman, R.A., Behavioral state affects heart rate response to low-intensity sound in human fetuses (1999) Early Hum Dev, 54 (1), pp. 39-54; Fleisher, L.A., Dipietro, J.A., Johnson, T.R., Pincus, S., Complementary and non-coincident increases in heart rate variability and irregularity during fetal development (1997) Clin Sci (Lond), 92 (4), pp. 345-349; Bernardes, J., Costa-Pereira, A., Ayres-de-Campos, D., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, Suppl, 57 (1), pp. 33-37; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in expert's classification of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynecol, 106, pp. 1307-1310; Bernardes, J., Moura, C., Marques-de-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Bernardes, J., Ayres-de-Campos, D., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int J Gynaecol Obstet, 62 (2), pp. 141-147; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., SisPorto Multicentre Validation Study Group. Prediction of neonatal state by computer analysis of fetal heart rate tracings: the antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118 (1), pp. 52-60; Dawes, G.S., Moulden, M., Redman, C.W., Improvements in computerized fetal heart rate analysis antepartum (1996) J Perinat Med, 24 (1), pp. 25-36
Keywords: article; Behavior; Cardiotocography; comparative study; Computerized analysis; Entropy and spectral analysis; Female; Fetal behavioural states and sex; Fetal heart rate; Fetal monitoring; Fetal Movement; fetus; fetus heart rate; Gestational Age; heart hemodynamics; Heart Rate, Fetal; human; Humans; male; normal human; Pregnancy; Pregnancy Outcome; Sex Characteristics; sex difference; SisPorto

Linear and nonlinear heart-rate analysis in a rat model of acute anoxia - Gonçalves, H.; Henriques-Coelho, T.; Bernardes, J.; Rocha, A.P.; Nogueira, A.; Leite-Moreira, A. (Physiological MeasurementPhysiol. Meas., 2008)
The objective of this study was the assessment of heart-rate (HR) dynamics with linear and nonlinear methods during episodes of mechanical ventilation and acute anoxia in rats. Namely, to assess whether linear and nonlinear HR analysis was able to discriminate acute anoxia from baseline in rats and if this was consistent with human foetal and adult studies. Five HR segments of 1 min duration, during baseline recording, mechanical ventilation and first, second and third minutes of induced acute anoxia, were analysed in ten adult Wistar rats. Linear time and frequency domain and nonlinear methods were used, namely mean HR (mHR), long-term irregularity (LTI), interval index (II), low frequency (LF) and high frequency (HF), approximate entropy (ApEn) and sample entropy (SampEn). New parameters for the entropy indices are proposed for the analysis of rats' HR. Bootstrap percentile confidence intervals and nonparametric statistical tests were used in the evaluation of the differences between segments. During mechanical ventilation a clear spectral band was detectable at the ventilation rate, but mHR, II and the 'new' entropy indices were the only significantly changed indices. In the transition from baseline-mechanical- ventilation to mechanical-ventilation-induced anoxia, a statistically significant decrease of mHR, II and entropy indices was observed, clearly discriminating these two instances, whereas most linear indices increased. With continued anoxia, most linear indices decreased significantly, whereas entropy remained stably low. These results are consistent with other foetal human and non-human studies and evidence that the rat model may be used for further research on linear and nonlinear analysis of heart-rate dynamics. The transition from baseline to acute anoxia was encompassed by signs of increased activation of the autonomic nervous system sympathetic branch, and decreased or blunted activity of the HR complexity regulatory centres. © 2008 Institute of Physics and Engineering in Medicine.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: PMEAEdoi: 10.1088/0967-3334/29/9/010PubMed ID: 18784391Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Departamento de Matemática Aplicada, Faculdade de Ciências, Universidade Do Porto, Rua do Campo Alegre 687, 4169-007 Porto, Portugal; email: hernani.goncalves@fc.up.ptReferences: American College of Obstetricians and Gynecologists. ACOG Practice Bulletin. Clinical Management Guidelines for Obstetrician-Gynecologists, Number 70, December 2005 (2005) Obstet. Gynecol., 106, pp. 1453-1460;Ayres-De-Campos, D., Bernardes, J., Garrido, A., Marques-De-Sá, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J. Mat. Fet. Med., 9 (5), pp. 311-318; Ayres-De-Campos, D., Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto® validation study (2005) Eur. J. Obstet. Gynecol. Reprod. Biol., 118 (1), pp. 52-60; Beckers, F., Verheyden, B., Aubert, A.E., Aging and nonlinear heart rate control in a healthy population (2006) Am. J. Physiol. Heart Circ. Physiol., 290 (6), pp. 2560-H2570; Beckers, F., Verheyden, B., Ramaekers, D., Swinghedauw, B., Aubert, A.E., Effects of autonomic blockade on non-linear cardiovascular variability indices in rats (2006) Clin. Exp. Pharmacol. Physiol., 33 (5-6), pp. 431-439; Bernardes, J., Ayres-De-Campos, D., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int. J. Gynecol. Obstet., 62 (2), pp. 141-147; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J. Perinat. Med., 19, pp. 61-65; Cerutti, C., Gustin, M.P., Paultre, C.Z., Lo, M., Julien, C., Vincent, M., Sassard, J., Autonomic nervous-system and cardiovascular variability in rats-a spectral-analysis approach (1991) Am. J. Physiol., 261, pp. 1292-H1299; Chaffin, D.G., Barnard, J.M., Phernetton, T., Reed, K.L., Decreased approximate entropy of heart rate variability in the hypoxic ovine fetus (1998) J. Matern. Fetal Invest., 8, pp. 23-26; Dudewicz, E., Mishra, S., (1988) Modern Mathematical Statistics; Felgueiras, C., Marques-De-Sá, J.P., Bernardes, J., Gama, S., Fractal characterisation of fetal heart rate sequences (1998) Biomedical Eng., 36, pp. 197-201; Gonçalves, H., Bernardes, J., Rocha, A.P., Ayres-De-Campos, D., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Human Develop., 83 (9), pp. 585-591; Gonçalves, H., Rocha, A.P., Ayres-De-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters (2006) Physiol. Meas., 27 (3), pp. 307-319; Gonçalves, H., Rocha, A.P., Ayres-De-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Med. Biol. Eng. Comput., 44 (10), pp. 847-855; Hayes, M., (1996) Statistical Digital Signal Processing and Modelling; Henriques-Coelho, T., Correia-Pinto, J., Roncon-Albuquerque, R., Baptista, M.J., Lourenco, A.P., Oliveira, S.M., Brandao-Nogueira, A., Leite-Moreira, A.F., Endogenous production of ghrelin and beneficial effects of its exogenous administration in monocrotaline-induced pulmonary hypertension (2004) Am. J. Physiol. Heart Circ. Physiol., 287 (6), pp. 2885-H2890; Kuwahara, M., Yayou, K., Ishii, K., Hashimoto, S., Tsubone, H., Sugano, S., Power spectral analysis of heart rate variability as a new method for assessing autonomic activity in the rat (1994) J. Electrocardiology, 27 (4), pp. 333-337; Li, X., Tang, D., Zhou, S., Zhou, G., Wang, C., Zhuang, Y., Wu, G., Shen, L., Redistribution of power spectrum of heart rate variability during acute umbilical artery embolism and hypoxemia in late-gestation fetal sheep (2004) Eur. J. Obstet. Gynecol. Reprod. Biol., 114 (2), pp. 137-143; Lourenço, A.P., Roncon-Albuquerque, R., Bras-Silva, C., Faria, B., Wieland, J., Henriques-Coelho, T., Correia-Pinto, J., Leite-Moreira, A.F., Myocardial dysfunction and neurohumoral activation without remodeling in left ventricle of monocrotaline-induced pulmonary hypertensive rats (2006) Am. J. Physiol. Heart Circ. Physiol., 291 (4), pp. 1587-H1594; Magenes, G., Signorini, M.G., Arduini, D., Classification of cardiotocographic records by neural networks (2000) IJCNN 2000: Proc. IEEE-INNS-ENNS Int. Joint Conf. on Neural Network, 3, pp. 637-641; Martinez, W.L., Martinez, A.R., (2002) Computational Statistics Handbook with MATLAB; Moraru, L., Cimponeriu, L., Tong, S., Thakor, N., Bezerianos, A., Characterization of heart rate variability changes following asphyxia in rats (2004) Methods Inf. Med., 43 (1), pp. 118-121; Moraru, L., Tong, S., Malhotra, A., Geocadin, R., Thakor, N., Bezerianos, A., Investigation of the effects of ischemic preconditioning on the HRV response to transient global ischemia using linear and nonlinear methods (2005) Med. Eng. Phys., 27 (6), pp. 465-473; Murasato, Y., Hirakawa, H., Harada, Y., Nakamura, T., Hayashida, Y., Effects of systemic hypoxia on R-r interval and blood pressure variabilities in conscious rats (1998) Am. J. Physiol., 275, pp. 797-H804; Niklasson, U., Wiklund, U., Bjerle, P., Olofsson, B.O., Heart-rate variation-what are we measuring? (1993) Clin. Physiol., 13 (1), pp. 71-79; Pincus, S., Aproximate entropy (ApEn) as a complexity measure (1995) Chaos, 5 (1), pp. 110-117; Pincus, S.M., Gevers, E.F., Robinson, I.C.A.F., Vandenberg, G., Roelfsema, F., Hartman, M.L., Veldhuis, J.D., Females secrete growth hormone with more process irregularity than males in both humans and rats (1996) Am. J. Physiol., 270, pp. 107-E115; Pincus, S., Viscarello, R., Approximate Entropy: A regularity measure for fetal heart rate analysis (1992) Obstet. Gynecol., 79, pp. 249-255; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am. J. Physiol. Heart Circ. Physiol., 278, pp. 2039-H2049; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans. Biomed. Eng., 50 (3), pp. 365-373; Siira, S.M., Ojala, T.H., Vahlberg, T.J., Jalonen, J.O., Valimaki, I.A., Rosen, K.G., Ekholm, E.M., Marked fetal acidosis and specific changes in power spectrum analysis of fetal heart rate variability recorded during the last hour of labour (2005) BJOG, 112 (4), pp. 418-423; Task force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology, Heart rate variability-standards of measurement, physiological interpretation and clinical use (1996) Circulation, 93, pp. 1043-1065; Vieira, P., Marques-De-Sá, J.P., Bernardes, J., Fractal analysis of foetal heart rate (2004) Proc. Biosignal 2004, pp. 53-55
Keywords: acute disease; animal experiment; animal model; Animals; Anoxia; article; artificial ventilation; bootstrapping; controlled study; entropy; Female; Fetal monitoring; frequency analysis; Heart rate; Heart rate variability; Humans; Linear analysis; linear system; lung ventilation; Models, Cardiovascular; nonhuman; nonlinear system; priority journal; rat; Rats; Rats, Wistar; Rattus; Rattus norvegicus; Respiration, Artificial; Statistical analysis; Variability; Wistar rat; Wistar rats

Molecular epidemiology of pseudomonas aeruginosa clinical isolates from Portuguese Central Hospital - Fonseca, A.P.; Correia, P.; Extremina, C.I.; Sousa, J.C.; Tenreiro, R.; Barros, H. (Folia MicrobiologicaFolia Microbiol., 2008)
The relatedness between clinical isolates of P. aeruginosa obtained from patients during their stay in a Portuguese Central Hospital was evaluated. Genotypic fingerprinting (M13-PCR), phenotypic methods (biotyping and antibiotyping) and epidemiological information (spatial and temporal links) were used to evaluate the relatedness between 88 clinical isolates (68 patients), selected randomly out of 189. Sixty-two M13 types were found, 12 of them containing isolates from more than one patient. Thirty-four antibiotypes were found, as well as a significant association (p < 0.05) between epidemic isolates and multiresistance patterns. The nosocomial transmission of P. aeruginosa strains may be limited since M13 typing demonstrated a high degree of diversity among all the isolates, suggesting the occurrence of mainly independent infectious episodes. The results show the possible occurrence of cross-acquisition, cross-colonization and cross-infection and suggest an epidemic population structure for P. aeruginosa in this hospital.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: FOMIAdoi: 10.1007/s12223-008-0086-yLanguage of Original Document: EnglishCorrespondence Address: Fonseca, A. P.Rua Roberto Frias s/n, 4200-465 Porto, Portugal; email: apfonseca08@sapo.ptChemicals/CAS: DNA, BacterialReferences: Bergmans, D., Bonten, M., van tiel, F., Gaillard, C., London, N., van der Geest, S., de Leeuw, P., Stobbrringh, E., Value of phenotyping methods as an initial screening of Pseudomonas aeruginosa in epidemiologic studies (1997) Infection, 25, pp. 350-354;Bertrand, X., Thouverez, M., Talon, D., Boillot, A., Capellier, G., Floriot, C., Helias, J.P., Endemicity, molecular diversity and colonization routes of Pseudomonas aeruginosa in intensive care units (2001) Intens.Care Med., 27, pp. 1263-1268; Brízio, A., Silva, A., Canas, E., Ferreira, T., Lito, L.M., Cristino, J.M., Salgado, M.J., Duarte, A., Spread of ln58 containing bla VIM-2 among Pseudomonas aeruginosa (2006) Clin.Microbiol.Infect.Dis., 12 (SUPPL. 4), p. 931; Brízio, A., Vasco, S., Gonçalves, A.R., Lito, L.M., Cristino, J.M., Salgado, M.J., Duarte, A., Survey of extended-spectrum β-lactamases in Escherichia coli isolates from a Portuguese hospital and characterisation of a novel class 1 integron (In60A) carrying the blaCTX-M-9 gene (2006) Internat.J.Antimicrob.Agents, 28, pp. 320-324; Buchholz, P., Richter, M., Fiedler, G., Halle, E., Epidemiological fingerprinting of multiresistant strains of Pseudomonas aeruginosa isolated from patients of intensive care units of the Charité Hospital, Berlin (1995) Med.Microbiol.Lett., 4, pp. 7-13; Černohorská, L., Votava, M., Antibiotic synergy against biofilm-forming Pseudomonas aeruginosa (2008) Folia Microbiol, 53, pp. 57-61; Elaichouni, A., Verschraegen, G., Claeys, G., Devleeschouwer, M., Godard, C., Vaneechoutte, M., Pseudomonas aeruginosa serotype O12 outbreak studied by arbitrary primer PCR (1994) J.Clin.Microbiol., 32, pp. 666-671; Fonseca, A.P., Correia, P., Fonseca, A.F., Tenreiro, R., Sousa, J.C., Polyphasic approach to the characterization of Pseudomonas aeruginosa isolates from a Portuguese Central Hospital (2004) Clin.Microbiol.Infect., 10 (SUPPL. 3), p. 1113; Fonseca, A.P., Correia, P., Sousa, J.C., Tenreiro, R., Association patterns of Pseudomonas aeruginosa clinical isolates as revealed by virulence traits, antibiotic resistance, serotype and genotype (2007) FEMS Immunol.Med.Microbiol., 51, pp. 505-516; Grundmann, H., Kropec, A., Hartung, D., Berner, R., Daschner, F., Pseudomonas aeruginosa in a neonatal intensive care unit: Reservoirs and ecology of the nosocomial pathogen (1993) J.Infect.Dis., 168, pp. 943-947; Grundmann, H.J., Towner, K.J., Dijkshoorn, L., Gerner-smidt, P., Maher, M., Seifert, H., Vaneechoutte, M., Multicenter study using standardized protocols and reagents for evaluation of reproducibility of PCR-based fingerprinting of Acinetobacter spp (1997) J.Clin.Microbiol., 35, pp. 3071-3077; Hoštacká, A., Čižnár, I., Slobodníková, L., Kotulová, D., Clinical Pseudomonas aeruginosa: Potential factors of pathogenicity and resistance to antimicrobials (2006) Folia Microbiol, 51, pp. 633-638; Hunter, P.R., Gaston, M.M., Numerical index of the discriminatory ability of typing systems: An application of Simpson's index of diversity (1989) J.Clin.Microbiol., 26, pp. 2465-2466; Huston, W.M., Potter, A.J., Jennings, M.P., Rello, J., Hauser, A.R., McEwan, A.G., Survey of ferroxidase expression and siderophore production in clinical isolates of Pseudomonas aeruginosa (2004) J.Clin.Microbiol., 42, pp. 2806-2809; Jalaluddin, S., Devaster, J.-M., Scheen, R., Gerard, M., Butzler, J.-P., Molecular epidemiological study of nosocomial Enterobacter aerogenes isolates in a Belgian hospital (1998) J.Clin.Microbiol., 36, pp. 1846-1852; Juretschko, S., Labombardi, V.J., Lerner, S.A., Schreckenberger, P.C., Pseudomonas AST Study Group: Accuracies of β-lactam susceptibility test results for Pseudomonas aeruginosa with four automated systems (BD Phoenix, MicroScan WalkAway, Vitek, and Vitek 2) (2007) J.Clin.Microbiol., 45, pp. 1339-1342; King, E.O., Ward, M.K., Raney, D.E., Two simple media for the demonstration of pyocyanin and fluorescein (1954) J.Lab.Clin.Med., 44, pp. 301-307; Kiska, D.L., Gilligan, P.H., Pseudomonas and Burkholderia (1999) Manual of Clinical Microbiology, pp. 517-525. , in P.R.Murray,E.J.Baron,M.A.Pfaller,F.C.Tenover,R.H.Yolken(Eds) 7th ed. American Society for Microbiology,Washington (DC); Morales, G., Wiehlmann, L., Gudowius, P., van Delden, C., Tümmler, B., Martínez, J.L., Rojo, F., Structure of Pseudomonas aeruginosa populations analyzed by single nucleotide polymorphism and pulsed-field gel electrophoresis genotyping (2004) J.Bacteriol., 186, pp. 4228-4237; Nogueira, J.A., (1995) Pseudomonas Aeruginosa - Agente Nosocomial, , (In Portuguese) PhD Thesis. Faculdade de Medicina, Universidade do Porto, Porto (Portugal); Olive, P.B.D., Principles and applications of methods for DNA-based typing of microbial organisms (1999) J.Clin.Microbiol., 37, pp. 1661-1669; Pirnay, J.P., de Vos, D., Cochez, C., Bilocq, F., Vanderkelen, A., Zizi, M., Ghysels, B., Cornelis, P., Pseudomonas aeruginosa displays an epidemic population structure (2002) Environ.Microbiol., 4, pp. 898-911; Pirnay, J.P., Matthijs, S., Colak, H., Chablain, P., Bilocq, F., Van eldere, J., de Vos, D., Cornelis, P., Global Pseudomonas aeruginosa biodiversity as reflected in a Belgian river (2005) Environ.Microbiol., 7, pp. 969-980; Speijer, H., Savelkoulp, P.H.M., Bonten, M.J., Stobberingh, E.E., Tjhie, J.H.T., Application of different genotyping methods for Pseudomonas aeruginosa in a setting of endemicity in an intensive care unit (1999) J.Clin.Microbiol., 37, pp. 3654-3661; Tenover, F., Arbeit, R.D., Goering, R.V., Mickelsen, P.A., Murray, B.E., Persing, D.H., Swaminathan, B., Interpreting chromosomal DNA restriction patterns produced by pulsed-field gel electrophoresis: Criteria for bacterial strain typing (1995) J.Clin. Microbiol., 33, pp. 2233-2239; Wiehlmann, L., Wagner, G., Cramer, N., Siebert, B., Gudowius, P., Morales, G., Köhler, T., Tümmler, B., Population structure of Pseudomonas aeruginosa (2007) Proc.Nat.Acad.Sci.USA, 104, pp. 8101-8106
Keywords: antibiotic resistance; article; bacterial DNA; cross infection; disease transmission; DNA, Bacterial; Drug Resistance, Microbial; Electrophoresis, Gel, Pulsed-Field; epidemiology; genetics; genotype; Hospitals, Teaching; human; Humans; isolation and purification; microbiology; polymerase chain reaction; Portugal; Pseudomonas aeruginosa; Pseudomonas infection; Pseudomonas Infections; pulsed field gel electrophoresis; Sampling Studies; statistics; teaching hospital

Nanocrystalline diamond: In vitro biocompatibility assessment by MG63 and human bone marrow cells cultures - Amaral, M.; Dias, A.G.; Gomes, P.S.; Lopes, M.A.; Silva, R.F.; Santos, J.D.; Fernandes, M.H. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2008)
Nanocrystalline diamond (NCD) has a great potential for prosthetic implants coating. Nevertheless, its biocompatibility still has to be better understood. To do so, we employed several materials characterization techniques (SEM, AFM, micro-Raman spectroscopy) and cell culture assays using MG63 osteoblast-like and human bone marrow cells. Biochemical routines (MTT assays, Lowry's method, ALP activity) supported by SEM and confocal microscopy characterization were carried out. We used silicon nitride (Si 3N 4) substrates for NCD coatings based on a previous demonstration of the superior adhesion and tribological performance of these NCD coated ceramics. Results demonstrate an improved human osteoblast proliferation and the stimulation of differentiated markers, like ALP activity and matrix mineralization, compared with standard polystyrene tissue culture plates. The nanometric featuring of NCD, associated to its chemical affinity are key points for bone regeneration purposes. © 2007 Wiley Periodicals, Inc.
Cited By (since 1996): 25Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31742PubMed ID: 18085649Language of Original Document: EnglishCorrespondence Address: Silva, R. F.; CICECO, Department of Ceramics and Glass Engineering, University of Aveiro, 3810-193 Aveiro, Portugal; email: rsilva@cv.ua.ptChemicals/CAS: diamond, 7782-40-3; polystyrene, 9003-53-6; silicon nitride, 12033-89-5; Alkaline Phosphatase, EC 3.1.3.1; Ceramics; Coated Materials, Biocompatible; Diamond, 7782-40-3; Silicon Compounds; silicon nitride, 12033-89-5References: Ratner, B.D., Hoffman, A.S., Schoen, A.S., Lemons, J.E., (1996) Biomaterials Science: An Introduction to Materials in Medicine, , New York: Academic Press;;Emery, D.F.G., Clarke, H.J., Grover, M.L., Stanmore total hip replacement in younger patients: Review of a group of patients under 50 years of age at operation (1997) J Bone Joint Surg, 79, pp. 240-246; Shane, A.C., Monique, C., Yogesh, K.V., Erick, M.S., Michelle, D.M., David Moore, K., Surface crystalline phases and nanoindentation hardness of explanted zirconia femoral heads (2003) J Mater Sci: Mater Med, 14, pp. 863-867; Shane, A.C., Marc, D.F., Yogesh, K.V., William, R.L., Jack, E.L., Shanna, W., Ramakrishna, V., Nanostructured ceramics for biomedical implants (2002) J Nanosci Nanotechnol, 2, pp. 293-312; Palin, E., Liu, H., Webster, T.J., Mimicking the nanofeatures of bone increases bone-forming cell adhesion and proliferation (2005) Nanotechnology, 16, pp. 1828-1835; Webster, T.J., Siegel, R.W., Bizios, R., Osteoblast adhesion on nanophase ceramics (1999) Biomaterials, 20, pp. 1221-1227; Price, R.L., Haberstroh, K.M., Webster, T.J., Enhanced functions of osteoblasts on nanostructured surfaces of carbon and alumina (2003) Med Biol Eng Comput, 41, pp. 372-375; Perla, V., Webster, T.J., Better osteoblast adhesion on nanoparticulate selenium - A promising orthopedic implant material (2005) J Biomed Mater Res, 75 A, pp. 356-364; Fries, M.D., Vohra, Y.K., Nanostructure diamond film deposition on curved surfaces of metallic temporomandibular joint implant (2002) J Phys D: Appl Phys, 35, pp. L105-L107; Papo, M.J., Catledge, S.A., Vohra, Y.K., Mechanical wear behaviour of nanocrystalline and multilayer diamond coatings on temporomandibular joint implants (2004) J Mater Sci: Mater Med, 15, pp. 773-777; Aspenberg, P., Antilla, A., Konttinen, Y.T., Lappalainen, R., Goodman, S.B., Nordsletten, L., Santavirta, S., Benign response to particles of diamond and SiC: Bone chamber studies of new joint replacement coating materials in rabbits (1996) Biomaterials, 17, pp. 807-812; Nordsletten, L., Hogasen, A.K.M., Konttinen, Y.T., Santavirta, S., Aspenberg, P., Aasen, A.O., Human monocytes stimulation by particles of hydroxyapatite, silicon carbide and diamond: In vitro studies of new prosthesis coatings (1996) Biomaterials, 17, pp. 1521-1527; Mitura, S., Mitura, A., Niedzielski, P., Couvrat, P., Nanocrystalline diamond coatings (1999) Chaos Solitons Fractals, 10, pp. 2165-2176; Mitura, K., Niedzielski, P., Grzegorz, B., Moll, J., Walkowiak, B., Pawlowska, Z., Louda, P., Mitura, S., Interactions between carbon coatings and tissue (2006) Surf Coat Technol, 201, pp. 2117-2123; Garguilo, J.M., Davis, B.A., Buddie, M., Köck, F.A.M., Nemanich, R.J., Fibrinogen adsorption onto microwave plasma chemical vapour deposited diamond films (2004) Diamond Relat Mater, 13, pp. 595-599; Tang, L., Tsai, C., Gerberich, W.W., Kruckeberg, L., Kania, D.R., Biocompatibility of chemical-vapour deposited diamond (1995) Biomaterials, 16, pp. 483-488; Narayan, R.J., Wei, W., Jin, C., Andara, M., Agarwal, A., Gerhardt, R.A., Shih, C., Singh, R.N., Microstructural and biological properties of nanocrystalline diamond coatings (2006) Diamond Relat Mater, 15, pp. 1935-1940; Popov, C., Kulisch, W., Jelinek, M., Bock, A., Strnad, J., Nanocrystalline diamond/amorphous carbon composite films for applications in tribology, optics and biomedicine (2006) Thin Solid Films, 494, pp. 92-97; Nethl, D.S., Kloss, F.R., Haq, M.N.U., Rainer, M., Larsson, K., Linsmeier, C., Köhler, G., Bonn, G., Strong binding of bioactive BMP-2 to nanocrystalline diamond by physisorption (2006) Biomaterials, 27, pp. 4547-4556; Silva, V.A., Costa, F.M., Fernandes, A.J.S., Nazaré, M.H., Silva, R.F., Influence of SiC particle addition on the nucleation density and adhesion strength of MPCVD diamond coatings on S13N4 substrates (2000) Diamond Relat Mater, 9, pp. 483-488; Kue, R., Sahrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201; Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clin Orthop, 244, pp. 296-301; Amaral, M., Costa, M.A., Lopes, M.A., Silva, R.F., Santos, J.D., Fernandes, M.H., Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and support the osteogenic differentiation of human bone marrow cells (2002) Biomaterials, 23, pp. 4897-4906; Belmonte, M., Fernandes, A.J.S., Costa, F.M., Oliveira, F.J., Silva, R.F., Adhesion behaviour assessment on diamond coated silicon nitride by acoustic emission (2003) Diamond Relat Mater, 12, pp. 733-737; Coelho, M.J., Trigo Cabrai, A., Fernandes, M.H., Human bone cell cultures in biocompatibility testing, Part 1: Osteoblastic differentiation of serially passaged human bone marrow cells cultured in α-MEM and in DMEM (2000) Biomaterials, 21, pp. 1087-1094; Clifford, C.J., Downes, S., A comparative study of the use of colorimetric assays in the assessment of biocompatibility (1996) J Mater Sci: Mater Med, 7, pp. 637-643; Ciapetti, G., Cenni, E., Pratelli, L., Pizzoferrato, A., In vitro evaluation of cell/biomaterial interaction by MTT assay (1993) Biomaterials, 14, pp. 359-364; Ferrari AC, Robertson J. Origin of the 1150 cm -1 Raman mode in nanocrystalline diamond. Phys Rev B 2001;63:121405-1-4Pfeiffer, R., Kuzmany, H., Knoll, P., Bokova, S., Salk, N., Günther, B., Evidence for trans-polyacetylene in nano-crystalline diamond films (2003) Diamond Relat Mater, 12, pp. 268-271; Fernandes, A.J.S., Neto, M.A., Almeida, F.A., Silva, R.F., Costa, F.M., Nano- and micro-crystalline diamond growth by MPCVD in extremely poor hydrogen uniform plasmas (2007) Diamond Relat Mater, 16, pp. 757-761; Almeida, F.A., Amaral, M., Oliveira, F.J., Fernandes, A.J.S., Silva, R.F., Nano to micrometric HFCVD diamond adhesion strength to Si 3N 4 (2007) Vacuum, 81, pp. 1443-1447; Abreu, C.S., Amaral, M., Oliveira, F.J., Fernandes, A.J.S., Gomes, J.R., Silva, R.F., Enhanced performance of HFCVD nanocrystalline diamond self-mated tribosystems by plasma pretreatments on silicon nitride substrates (2006) Diamond Relat Mater, 15, pp. 2024-2028; Abreu, C.S., Amaral, M., Fernandes, A.J.S., Oliveira, F.J., Silva, R.F., Gomes, J.R., Friction and wear performance of HFCVD nano-crystalline diamond coated silicon nitride ceramics (2006) Diamond Relat Mater, 15, pp. 739-744; Stein, G.S., Lian, J.B., Molecular mechanisms mediated proliferation- differentiation interrelationships during progressive development of the osteoblast phenotype (1993) Endocr Rev, 14, pp. 424-442; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing, Part 2: Effect of ascorbic acid, β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Kaplan, F.S., Hayes, W.C., Keaveny, T.M., Boskey, A., Einhorn, T.A., Iannotti, J.P., Form and function of bone (1994) Orthopedic Basic Science, pp. 127-185. , Simon SP, editor, Columbus, OH: American Academy of Orthopedic Surgeons;; Webster, T.J., Ejiofor, J.U., Increased osteoblast adhesion on nanophase metals: Ti, Ti6A14V, and CoCrMo (2004) Biomaterials, 25, pp. 4731-4739; Kay, S., Thapa, A., Haberstroh, K.M., Webster, T.J., Nanostructured polymer/nanophase ceramic composites enhance osteoblast and chondrocyte adhesion (2002) Tissue Eng, 8, pp. 753-761; Webster, T.J., Smith, T.A., Increased osteoblast function on PLGA composites containing nanophase titania (2005) J Biomed Mater Res A, 74, pp. 677-686; Balasundaram, G., Sato, M., Webster, T.J., Using hydroxyapatite nanoparticles and decreased crystallinity to promote osteoblast adhesion similar to functionaizing with RGD (2006) Biomaterials, 27, pp. 2798-2805; Webster, T.J., (2004) Proteins: Structure and interactions patterns to solid surfaces, pp. 1-16. , editors. Encyclopedia of Nanoscience and Nanotechnology. New York: Marcel Dekker; Siegel RW. Creating nanophase materials. Sci Am (Int Ed) 1996;275:74-79Webster, T.J., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21, pp. 1803-1810; Webster, T.J., Enhanced osteoclast-like cell functions on nano-phase ceramics (2001) Biomaterials, 22, pp. 1327-1333; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Specific proteins mediate enhanced osteoblast adhesion on nano-phase ceramics (2000) J Biomed Mater Res, pp. 51475-51483; Webster, T.J., Schadler, L.S., Siegel, R.W., Bizios, R., Mechanisms of enhanced osteoblast sdhesion on nanophase alumina involve vitronectin (2001) Tissue Eng, 7, pp. 291-301
Keywords: adult; alkaline phosphatase; ALP activity; Animal cell culture; Architectural acoustics; article; Atomic force microscopy; Biocompatibility; Bone; bone marrow cell; Bone Marrow Cells; Bone Regeneration; Cell culture; cell proliferation; cell survival; Cells; Cells, Cultured; ceramics; Cladding (coating); Coated Materials, Biocompatible; confocal microscopy; controlled study; diamond; Diamonds; enzyme activity; extracellular matrix; human; Human bone marrow cells; human cell; Humans; Imaging techniques; Implants (surgical); In vitro biocompatibility; in vitro selection; Joint replacement; male; Materials characterization; materials testing; Micro-Raman spectroscopy; Microscopic examination; Microscopy, Atomic Force; Microscopy, Confocal; Microscopy, Electron, Scanning; mineralization; MTT assaying; Nano-crystalline diamond; nanocrystal; Nanocrystalline alloys; Nanocrystalline materials; nanoparticles; Nanostructured materials; Nitrides; Nonmetals; osteoblast; Osteoblasts; polystyrene; Prostheses and Implants; Raman spectrometry; Scanning electron microscopy; Secondary emission; Silicon; Silicon compounds; Silicon nitride; Spectrum Analysis, Raman; Surface Properties; Tissue engineering

Omniview-SisPorto® 3.5 - A central fetal monitoring station with online alerts based on computerized cardiotocogram+ST event analysis - Ayres-de-Campos, D.; Sousa, P.; Costa, A.; Bernardes, J. (Journal of Perinatal MedicineJ. Perinat. Med., 2008)
Visual analysis of cardiotocograms is poorly reproducible and is currently recognized as the main weakness of the STAN® methodology. The Omniview-SisPorto® 3.5 program is the most recent version of a central monitoring system that provides visual and sound alerts, based on computer analysis of cardiotocographic and ST event features. This paper describes the program's main characteristics and provides an overview of the system's online alerts. Omniview-SisPorto® 3.5 is the first central monitoring system to incorporate computerized analysis of cardiotocographic and ST event features, providing health professionals with online alerts for minor and major changes in monitored signals. The system is currently undergoing extensive clinical evaluation. © 2008 by Walter de Gruyter.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JPEMAdoi: 10.1515/JPM.2008.030Language of Original Document: EnglishCorrespondence Address: Ayres-De-Campos, D.; Departmento Ginecologia e Obstetricia, Faculdade de Medicina, Universidade Do Porto, Alameda Hernani Monteiro, 4200-319 Porto, Portugal; email: sisporto@med.up.ptTradenames: Omniview-SisPorto 3.5 system, SpeculumManufacturers: SpeculumReferences: Amer-Wahlin, I., Arulkumaran, S., Hagberg, H., Marsal, K., Visser, G., Fetal electrocardiogram: ST waveform analysis in intrapartum surveillance (2007) Br J Obstet Gynaecol, 114, pp. 1191-1193;Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marquesde-Sá, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Ayres-de-Campos, D., Bernardes, J., Comparison of fetal heart rate baseline estimation by SisPorto 2.01 and a consensus of clinicians (2004) Eur J Obstet Gynecol Reprod Biol, 117, pp. 174-178; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., SisPorto Multicentre Validation Study Group. Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118, pp. 52-60; Ayres-de-Campos, D., Bernardes, J., Kwee, A., Westehuis, M., Visser, G.H.A., Computer quantification of short-term variability as an adjunct to fetal electrocardiographic monitoring (2007) Br J Obstet Gynaecol, 114, pp. 1446-1447; Bernardes, J., Moura, C., Marques de, S.J., Pereira Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Electronic fetal heart rate monitoring: Research guidelines for interpretation (1997) Am J Obstet Gynecol, 177, pp. 1385-1390. , National Institute of Child Health and Human Development Research Planning Workshop; Neilson, J.P., Fetal electrocardiogram (ECG) for fetal monitoring during labor (2006) Cochrane Database of Systematic Reviews, (3); Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-165; (2001) Evidence-based clinical guideline: The use of electronic fetal monitoring, , RCOG, Royal College of Obstetricians and Gynaecologists, London, RCOG Press; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring (1987) Int J Gynecol Obstet, 25, pp. 159-167
Keywords: article; Cardiotocography; computer program; Computer-assisted; Electrocardiography; Female; Fetal; Fetal hypoxia; Fetal monitoring; fetus hypoxia; fetus monitoring; Heart rate; human; Humans; instrumentation; online system; Pregnancy; priority journal; Signal processing; ST segment

PLD bioactive ceramic films: The influence of CaO-P 2O 5 glass additions to hydroxyapatite on the proliferation and morphology of osteblastic like-cells - Oliveira, G.M.; Ferraz, M.P.; González, P.G.; Serra, J.; Leon, B.; Pèrez-Amor, M.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2008)
This work consists on the evaluation of the in vitro performance of Ti6Al4V samples PLD (pulsed laser deposition) coated with hydroxyapatite, both pure and mixed with a CaO-P 2O 5 glass. Previous studies on immersion of PLD coatings in SBF, showed that the immersion apatite films did not present the usual cauliflower morphology but replicated the original columnar structure and exhibited good bioactivity. However, the influence of glass associated to hydroxyapatite concerning adhesion, proliferation and morphology of MG63 cells on the films surface was unclear. In this study, the performance of these PLD coated samples was evaluated, not only following the physical-chemical transformations resulting from the SBF immersion, but also evaluating the cytocompatibility in contact with osteoblast-like MG63 cells. SEM and AFM confirmed that the bioactive ceramic PLD films reproduce the substrate's surface topography and that the films presented good adherence and uniform surface roughness. Physical-chemical phenomena occurring during immersion in SBF did not modify the original columnar structure. In contact with MG63 cells, coated samples exhibited very good acceptance and cytocompatibility when compared to control. The glass mixed with hydroxyapatite induced higher cellular proliferation. Cells grown on these samples presented many filipodia and granular structures, typical features of osteoblasts. © 2007 Springer Science+Business Media, LLC.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-007-3331-zPubMed ID: 18058197Language of Original Document: EnglishCorrespondence Address: Oliveira, G. M.; Universidade Fernando Pessoa, Praça Nove de Abril 349, 4249-004 Porto, Portugal; email: gisela@ufp.ptChemicals/CAS: calcium oxide, 1305-78-8; hydroxyapatite, 1306-06-5, 51198-94-8; oxide, 16833-27-5; Biocompatible Materials; Calcium Compounds; Ceramics; Durapatite, 1306-06-5; Oxides; Phosphorus Compounds; Polystyrenes; lime, 1305-78-8; phosphorus pentoxide, 1314-56-3References: Hench, L.L., (1991) J. Am. Ceram. Soc., 74, p. 1487;Hench, L.L., (1998) Biomaterials, 19, p. 1419; Park, S.H., Llinás, A., Goel, V.K., Keller, J.C., (2000) The Biomedical Engineering Handbook, , Edited by: J. D. BRONZINO (CRC Press, LLC, Boca Raton); Hench, L.L., (1994) 7th International Symposium on Ceramics in Medicine, p. 3. , Edited by: Ö. H. A. A. Y. URPO (Butterworth-Heinemann Ltd Oxford, England); Kokubo, T., (1991) Biomaterials, 12, p. 155; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, p. 6. , JAAS Takayan Press. Ishiyaku euroAmerica, Inc Tokyo; Orlovskii, V.P., Komlev, V.S., Barinov, S.M., (2002) Inorg. Mater., 38, p. 973; Kenny, S.M., Buggy, M., (2003) J. Mater. Sci. Mat. Med., 14, p. 923; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., (1995) J. Mat. Sci. Mat. Med., 6, p. 348; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., (2001) J. Mater. Sci.: Mater. Med., 12, p. 629; Ferraz, M.P., Monteiro, F.J., Gião, D., Léon, B., Gonzalez, P., Liste, S., Serra, J., Perez-Amor, M., (2004) Key Eng. Mat., 254-256, p. 347; Porter, A.E., Hobbs, L.W., Benezra Rosen, V., Spector, M., (2002) Biomaterials, 23, p. 725; Kim, H.-K., Jang, J.-W., Lee, C.-H., (2004) J. Mater. Sci.: Mater. Med., 15, p. 825; Harada, Y., Wang, J.-T., Doppalapudi, V.A., Willis, A.A., Jasty, M., Harris, W.H., Nagase, M., Goldring, S.R., (1996) J. Biomed. Mater. Res., 31, p. 19; Arias, J.L., Mayor, M.B., Pou, J., Léon, B., Pérez-Amor, M., (2000) Appl. Surf. Sci., 154-155, p. 434; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., (1996) J. Mater. Sci.: Mater. Med., 7, p. 187; Arias, J.L., Mayor, M.B., Pou, J., Leng, Y., Léon, B., Pérez-Amor, M., (2003) Biomaterials, 24, p. 3403; Arias, J.L., Mayor, M.B., Pou, J., Léon, B., Pérez-Amor, M., (2002) Appl. Surf. Sci., 182, p. 448; Arias, J.L., Mayor, M.B., Pou, J., Léon, B., Pérez-Amor, M., (2002) Vaccum, 67, p. 653; Arias, J.L., Garcia-Sanz, F.J., Mayor, M.B., Chiussi, S., Pou, J., Léon, B., Pérez-Amor, M., (1998) Biomaterials, 19, p. 883; Mayor, M.B., Arias, J.L., Chiussi, S., Garcia, F., Pou, J., Léon, B., Pérez-Amor, M., (1998) Thin Solid Films, 317, p. 363; Kokubo, T., Kushitani, H., Sakka, S., Kitsuki, T., Yamamuro, T., (1990) J. Biomed. Mater. Res., 24, p. 721; Monteiro, F.J., Ferraz, M.P., Gião, D., Leon, B., Gonzalez, P., Liste, S., Serra, J., Perez-Amor, M., (2002) 17th European Conference on Biomaterials, pp. P65. , Edited by: E. S. F. Biomaterials (Barcelona, Spain); Lossdörfer, S., Schwartz, Z., Wang, L., Lohmann, C.H., Turner, J.D., Wieland, M., Cochran, D.L., Boyan, B.D., (2004) J. Biomed. Mater. Res, 70, p. 361; Bannister, S.R., Lohmann, C.H., Liu, Y., Sylvia, V.L., Cochran, D.L., Dean, D.D., Boyan, B.D., Schwartz, Z., (2002) J. Biomed. Mater. Res., 60, p. 164; Cleries, L., Fernandez-Pradas, J.M., Sardin, G., Morenza, J.L., (1998) Biomaterials, 19, p. 1483; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., (1996) J. Mater. Sci.: Mater. Med., 7, p. 21; Knabe, C., Klar, F., Fitzner, R., Radlanski, R.J., Gross, U., (2002) Biomaterials, 23, p. 3235; Garcia, F., Arias, J.L., Mayor, M.B., Pou, J., Rehman, I., Knowles, J., Best, S., Bonefield, W., (1998) J. Biomed. Mater. Res. (Appl. Biomater), 43, p. 69; Peng, P., Kumar, S., Voelcker, N.H., Szili, E., Smart, R.S.C., Griesser, H.J., (2006) J. Biomed. Mater. Res., 76, p. 347; Borsari, V., Giavaresi, G., Fini, M., Torriceli, P., Salito, A., Chiesa, R., Chiusoli, L., Giardino, R., (2005) J. Biomed. Mater. Res. Part B: Appl. Biomater., 75, p. 359; Massaro, C., Baker, M.A., Cosentino, F., Ramires, P.A., Klose, S., Milella, E., (2001) J. Biomed. Mater. Res., 58, p. 651; Bigi, A., Bracci, B., Cuisinier, F., Elkaim, R., Fini, M., Mayer, I., Mihailescu, I.N., Torricelli, P., (2005) Biomaterials, 26, p. 2381; Zeng, H., Lacefield, W.R., (2000) J. Biomed. Mater. Res., 50, p. 239; Clèries, L., Fernandez-Pradas, J.M., Morenza, J.L., (2000) Biomaterials, 21, p. 1861; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 45, p. 376; Li, P., Ducheyne, P., (1998) J. Biomed. Mater. Res., 41, p. 341; Weng, J., Liu, Q., Wolke, J.G., Zhang, X., De Groot, K., (1997) Biomaterials, 18, p. 1027; Tas, A.C., (2000) Biomaterials, 21, p. 1429; Kokubo, T., Kim, H.-M., Kawashita, M., (2003) Biomaterials, 24, p. 2161; Dewez, J.-L., Doren, A., Schneider, Y.-J., Rouxhet, P.G., (1999) Biomaterials, 20, p. 547; Anselme, K., Linez, P., Bigerelle, M., Le Maguer, D., Le Maguer, A., Hardouin, P., Hildebrand, H.F., Leroy, J.M., (2000) Biomaterials, 21, p. 1567; Okumura, A., Goto, M., Goto, T., Yoshinari, M., Masuko, S., Katsuki, T., Tanaka, T., (2001) Biomaterials, 22, p. 2263; Kim, H.J., Kim, S.H., Kim, M.S., Lee, E.J., Oh, H.G., Oh, W.M., Park, S.W., Dean, D.D., (2005) J. Biomed. Mater. Res., 74, p. 366
Keywords: Apatite; Apatite films; Bioactive ceramic films; Bioactive glass; Bioactivity; Bioceramics; Biocompatible Materials; Biofilms; Brassica oleracea var. botrytis; Calcium Compounds; calcium oxide; Cauliflower morphology; cell adhesion; cell proliferation; cell structure; cell survival; ceramics; Columnar structure; conference paper; controlled study; Durapatite; glass; human; human cell; Humans; hydroxyapatite; Lasers; materials testing; Microscopy, Atomic Force; Microscopy, Electron, Scanning; morphology; osteoblast; Osteoblasts; oxide; Oxides; phosphorous pentoxide; Phosphorus Compounds; Polystyrenes; priority journal; Pulsed laser deposition; unclassified drug

Surface characterization and cell response of a PLA/CaP glass biodegradable composite material - Navarro, M.; Engel, E.; Planell, J.A.; Amaral, I.; Barbosa, M.; Ginebra, M.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2008)
Bioabsorbable materials are of great interest for bone regeneration applications, since they are able to degrade gradually as new tissue is formed. In this work, a fully biodegradable composite material containing polylactic acid (PLA) and calcium phosphate (CaP) soluble glass particles has been characterized in terms of surface properties and cell response. Cell cultures were performed in direct contact with the materials and also with their extracts, and were evaluated using the MTT assay, alkaline phosphatase activity, and osteocalcin measurements. The CaP glass and PLA were used as reference materials. No significant differences were observed in cell proliferation with the extracts containing the degradation by-products of the three materials studied. A relation between the materials wettability and the material-cell interactions at the initial stages of contact was observed. The most hydrophilic material (CaP glass) presented the highest cell adhesion values as well as an earlier differentiation, followed by the PLA/glass material. The incorporation of glass particles into the PLA matrix increased surface roughness. SEM images showed that the heterogeneity of the composite material induced morphological changes in the cells cytoskeleton. © 2007 Wiley Periodicals, Inc.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31546PubMed ID: 17729262Language of Original Document: EnglishCorrespondence Address: Ginebra, M. P.; Department of Materials Science, Institute of Bioengineering of Catalonia (IBEC), Technical University of Catalonia, Avda Diagonal 647, 08028-Barcelona, Spain; email: maria.pau.ginebra@upc.eduChemicals/CAS: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide, 298-93-1; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; osteocalcin, 136461-80-8; polylactic acid, 26100-51-6; Alkaline Phosphatase, EC 3.1.3.1; Bone Substitutes; calcium phosphate, 10103-46-5; Calcium Phosphates; Lactic Acid, 50-21-5; Osteocalcin, 104982-03-8; poly(lactic acid), 26100-51-6; PolymersReferences: Barrows, T., Degradable implants materials: A review of synthetic absorbable polymers and their applications (1986) Clin Mater, 1, pp. 233-267;Ciccone, W., Motz, C., Bentley, C., Tasto, J., Bioabsorbable implants in orthopaedics: New developments and clinical applications (2001) J Am Acad Orthop Surg, 9, pp. 280-288; Dunn, R.L., Clinical applications and update on the poly (alpha-hydroxy acids) (1995) Biomedical Applications of Synthetic Biodegradable Polymers, pp. 17-31. , Hollinger JO, editor, Boca Raton: CRC Press;; Middleton, J.C., Tipton, A.J., Synthetic biodegradable polymers as orthopedic devices (2000) Biomaterials, 21, pp. 2335-2346; Böstman O Current concepts review. Absorbable implants for fracture fixation. J Bone Joint Surgery 1991;73A:148-153Ashammakhi, N., Suuronen, R., Tiainen, J., Tormala, P., Waris, T., Spotlight on naturally absorbable osteofixation devices (2003) J Craniofac Surg, 14, pp. 247-259; Hou, Q.P., Grijpma, D.W., Feijen, J., Porous polymeric structures for tissue engineering prepared by a coagulation, compression moulding and salt leaching technique (2003) Biomaterials, 24, pp. 1937-1947; Kellomaki, M., Niiranen, H., Puumanen, K., Ashammakhi, N., Waris, T., Tormala, P., Bioabsorbable scaffolds for guided bone regeneration and generation (2000) Biomaterials, 21, pp. 2495-2505; Mooney, D.J., Park, S., Kaufmann, P.M., Sano, K., Mcnamara, K., Vacanti, J.P., Langer, R., Biodegradable sponges for hepatocyte transplantation (1995) J Biomed Mater Res, 29, pp. 959-965; Ragel, C.V., Vallet-Regi, M., In vitro bioactivity and gentamicin release from glass-polymer-antibiotic composites (2000) J Biomed Mater Res, 51, pp. 424-429; Kohn, J., Langer, R., Bioabsorbable and bioerodible materials (1996) Biomaterials Science, pp. 64-72. , Ratner BD, Hoffman A, Schoen F, Lemons J, editors, New York: Academic Press;; Navarro, M., Ginebra, M.P., Clement, J., Martinez, S., Avila, G., Planell, J.A., Physicochemical degradation of titania-stabilized soluble phosphate glasses for medical applications (2003) J Am Ceram Soc, 86, pp. 1345-1352; Navarro, M., Ginebra, M.P., Planell, J.A., Barrias, C.C., Barbosa, M., In vitro degradation behavior of a novel bioabsorbable composite material based on PLA and a soluble CaP glass (2005) Acta Biomaterialia, 1, pp. 411-419; Stephansson, S.N., Byers, B.A., Garcia, A.J., Enhanced expression of the osteoblastic phenotype on substrates that modulate fibronectin conformation and integrin receptor binding (2002) Biomaterials, 23, pp. 2527-2534; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) J Biomed Mater Res A, 66, pp. 247-259; Beumer, G., van Blitterswijk, C., Bakker, D., Ponec, M., Cell-seeding and in vitro biocompatibility evaluation of polymeric matrices of PEO/PBT copolymers and PLLA (1993) Biomaterials, 14, pp. 598-604; Ishaug, S., Yaszemski, M., Bizios, R., Mikos, A., Osteoblast function on synthetic biodegradable polymers (1994) J Biomed Mater Res, 28, pp. 1445-1453; Navarro, M., Ginebra, M.P., Planell, J.A., Cellular response to calcium phosphate glasses with controlled solubility (2003) J Biomed Mater Res A, 67, pp. 1009-1015; Huffman, K.R., Casey, D.J., Effect of carboxyl end groups on hydrolysis of polyglycolic acid (1985) J Polym Sci A: Polym Chem, 23, pp. 1939-1954; Ishaug-Riley, S.L., Okun, L.E., Prado, G., Applegate, M.A., Ratcliffe, A., Human articular chondrocyte adhesion and proliferation on synthetic biodegradable polymer films (1999) Biomaterials, 20, pp. 2245-2256; Park, A., Griffith, L., In vitro cell response to differences in poly-1-lactide crystallinity (1996) Biomaterials, 31, pp. 117-130; Cai, K.Y., Yao, K.D., Lin, S.B., Yang, Z.M., Li, X.Q., Xie, H.Q., Poly (D, L-lactic acid) surfaces modified by silk fibroin: Effects on the culture of osteoblast in vitro (2002) Biomaterials, 23, pp. 1153-1160; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tension, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Vogler, E.A., Structure and reactivity of water at biomaterial surfaces (1998) Adv Colloid Interface Sci, 74, pp. 69-117; Vogler, E.A., Interfacial chemistry in biomaterials science (1993) Surfactant Science Series, pp. 183-250. , Berg JC, editor. Wettability, Marcel Dekker, New York; Charles-Harris, M., Navarro, M., Engel, E., Aparicio, C., Ginebra, M.P., Planell, J., A Surface characterisation of completely degradable composite scaffolds (2005) J Mater Svi: Mater Med, 16, pp. 1125-1130; Lampin, M., WarocquierClerout, R., Legris, C., Degrange, M., SigotLuizard, M.F., Correlation between substratum roughness and wettability, cell adhesion, and cell migration (1997) J Biomed Mater Res, 36, pp. 99-108; Khang, G., Jeon, J.H., Lee, L.W., Cho, S.C., Lee, H.B., Cell and platlet adhesion on plasma glow discharge-treated poly(lactide-co-glycolide) (1997) Biomed Mater Engl, 7, pp. 357-368; Webb, K., Hlady, V., Tresco, P.A., Relative importance of surface wettability and charged functional groups on NIH 3T3 fibroblast attachment, spreading, and cytoskeletal organization (1998) J Biomed Mater Res, 41, pp. 422-430; Owen, T.A., Aronow, M., Shalhoub, V., Barone, L.M., Wilming, L., Tassinari, M.S., Progressive development of the rat osteoblast phenotype in vitro - Reciprocal relationships in expression of genes associated with osteoblast proliferation and differentiation during formation of the bone extracellular-matrix (1990) J Cell Physiol, 143, pp. 420-430; Lian, J.B., Stein, G.S., Concepts of osteoblast growth and differentiation - Basis for modulation of bone cell-development and tissue formation (1992) Crit Rev Oral Biol Med, 3, pp. 269-305; Quarles, L.D., Yohay, D.A., Lever, L.W., Caton, R., Wenstrup, R.J., Distinct proliferative and differentiated stages of murine Mc3T3-E1 cells in culture - An in vitro model of osteoblast development (1992) J Bone Miner Res, 7, pp. 683-692; Boyan, B.D., Dean, D.D., Lohmann, C.H., Cochran, D.L., Sylvia, V.L., Schwartz, Z., The titanium-bone cell interface in vitro: The role of the surface in promoting osteointegration (2001) Titanium in Medicine, pp. 562-585. , Brunette D, Tengvall P, Textor M, Thomsen P, editors, Berlin: Springer-Verlag;; Gronowicz, G., McCarthy, M.B., Ahmad, M., Direct integrin-mediated attachment of human osteoblasts to implants (1996) J Bone Miner Res, 11, pp. S323; Boyan, B.D., Hummert, T.W., Kieswetter, K., Schraub, D., Dean, D.D., Schwartz, Z., Effect of titanium surface characteristics on chondrocytes and osteoblasts in vitro (1995) Scan Electron Microsc, 5, pp. 323-335; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Effect of titanium surface-roughness on proliferation. Differentiation, and protein-synthesis of human osteoblast-like cells (MG63) (1995) J Biomed Mater Res, 29, pp. 389-401
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; Absorbable Implants; alkaline phosphatase; article; Biodegradable composite materials; biodegradable implant; Biodegradation; Bone; Bone Regeneration; Bone Substitutes; calcium phosphate; Calcium phosphates; cell adhesion; Cell culture; cell function; cell interaction; Cell Line; cell proliferation; Cell response; Composite materials; cytoskeleton; glass; human; human cell; Humans; hydrophilicity; hydrophobicity; In vitro test; Lactic Acid; materials testing; Osteoblasts; osteocalcin; polylactic acid; Polymers; scanning electron microscope; Surface analysis; Surface Properties; wettability

Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation - Amaral, I.F.; Cordeiro, A.L.; Sampaio, P.; Barbosa, M.A. (Journal of Biomaterials Science, Polymer EditionJ. Biomater. Sci. Polym. Ed., 2007)
Chitosan (Ch) is being actively investigated as a non-protein template for the growth of an increasing number of anchorage-dependent cells, including chondrocytes and bone cells. In the present work, Ch films with degrees of N-acetylation (DAs) in the range of 4 to 49% were evaluated with respect to the attachment, spreading and short-term proliferation of osteoblasts, using human osteoblastic MG-63 cells. The films were characterized in terms of surface morphology and surface charge by atomic force microscopy and streaming potential measurements, respectively. Cell attachment was assessed after 3 and 24 h of cell culture. After 24 h of incubation, cell attachment was found to be dependent on the DA, lower DAs favouring cell adhesion. With time, cell spreading and cytoskeleton organization were only attained for DAs ≤ 13%. Regarding cell proliferation, cells grown on films with the lowest DA (4%) revealed a higher specific growth rate as compared to those grown on films with higher DAs. Films with a DA of 49% failed to sustain cell proliferation. In addition, a longer lag-phase was observed on Ch, as compared to TCPS, in accordance to an observed delay of cell spreading. The present findings revealed that differences in the DA as small as 9% may be critical in terms of the osteoblast response to two-dimensional Ch-based matrices. © 2007 VSP.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JBSEEdoi: 10.1163/156856207780425068Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; Biocompatible Materials; Chitosan, 9012-76-4References: Vacanti, C.A., Bonassar, L.J., Vacanti, J.P., (2000) Principles of Tissue Engineering, p. 671. , R. P. Lanza, R. Langer and J. Vacanti Eds, p, Academic Press, San Diego, CA;Bruder, S.P., Caplan, A.I., (2000) Principles of Tissue Engineering, p. 683. , R. P. Lanza, R. Langer and J. Vacanti Eds, p, Academic Press, San Diego, CA; Burg, K.J.L., Porter, S., Kellam, J.F., (2000) Biomaterials, 21, p. 2347; Khor, E., Lim, L.Y., (2003) Biomaterials, 24, p. 2339; Nettles, D.L., Elder, S.H., Gilbert, J.A., (2002) Tissue Eng, 8, p. 1009; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., (2002) J. Control. Rel, 78, p. 187; Muzzarelli, R.A.A., (1997) Cell. Mol. Life Sci, 53, p. 131; Madihally, S.V., Matthew, H.W.T., (1999) Biomaterials, 20, p. 1133; Chupa, J.M., Foster, A.M., Sumner, S.R., Madihally, S.V., Matthew, H.W.T., (2000) Biomaterials, 21, p. 2315; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., (2000) J. Biomed. Mater. Res, 51, p. 586; Ho, M.H., Wang, D.M., Hsieh, H.J., Liu, H.C., Hsien, T.Y., Lai, J.Y., Hou, L.T., (2005) Biomaterials, 26, p. 3197; A. Domard, in: Advances in Chitin Science, II, A. Domard, G. A. F. Roberts and K. M. Varum (Eds), p. 410. Jacques André, Lyon (1997)Tomihata, K., Ikada, Y., (1997) Biomaterials, 18, p. 567; Baxter, A., Dillon, M., Taylor, K.D.A., Roberts, G.A.F., (1992) Int. J. Biol. Macromol, 14, p. 166; Anselme, K., (2000) Biomaterials, 21, p. 667; Prasitsilp, M., Jenwithisuk, R., Kongsuwan, K., Damrongchai, N., Watts, P., (2000) J. Mater. Sci. Mater. Med, 11, p. 773; Chatelet, C., Damour, O., Domard, A., (2001) Biomaterials, 22, p. 261; Dhiman, H.K., Ray, A.R., Panda, A.K., (2004) Biomaterials, 25, p. 5147; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., (2001) Polymer, 42, p. 3569; Mima, S., Miya, M., Iwamoto, R., Yoshikawa, S., (1983) J. Appl. Polym. Sci, 28, p. 1909; Aiba, S., (1986) Int. J. Biol. Macromol, 8, p. 173; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., (1996) Carbohydr. Polym, 29, p. 63; (1987) Guideline on Validation of the Limulus Amebocyte Lysate Test as an End-product Endotoxin Test for Human and Animal Parental Drugs, Biological Products, and Medical Devices, , US Department of Health and Human Services, Public Health Service, Food and Drug Administration, US Department of Health and Human Services, Washington, DC; Nakagawa, Y., Murai, T., Hasegawa, C., Hirata, M., Tsuchiya, T., Yagami, T., Haishima, Y., (2003) J. Biomed. Mater. Res, 66 B, p. 347; Walker, S.L., Bhattacharjee, S., Hoek, E.M.V., Elimelech, M., (2002) Langmuir, 18, p. 2193; Clover, J., Gowen, M., (1994) Bone, 15, p. 585; Mosmann, T., (1983) J. Immunol. Methods, 65, p. 55; Domke, J., Dannohl, S., Parak, W.J., Muller, O., Aicher, W.K., Radmacher, M., (2000) Colloid Surfaces B: Biointerfaces, 19, p. 367; Sorlier, P., Denuziere, A., Viton, C., Domard, A., (2001) Biomacromolecules, 2, p. 765; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., (2005) J. Biomed. Mater. Res, 75 A, p. 387; Andrade, J.D., Smith, L.M., Gregonis, D.E., (1985) Surface and Interfacial Aspects of Biomedical Polymers, 1, p. 249. , J. D. Andrade Ed, p, Plenum Press, New York, NY; Dewez, J.L., Doren, A., Schneider, Y.J., Rouxhet, P.G., (1999) Biomaterials, 20, p. 547; Kikuchi, T., Yoshikai, Y., Miyoshi, J., Katsuki, M., Musikacharoen, T., Mitani, A., Tanaka, S., Matsuguchi, T., (2003) J. Dent. Res, 82, p. 546; Denuziere, A., Ferrier, D., Damour, O., Domard, A., (1998) Biomaterials, 19, p. 1275; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2005) Biomaterials, 26, p. 485; Wang, J.H., Wei, C.W., Liu, H.C., Young, T.H., (2003) J. Biomed. Mater. Res, 64 A, p. 606; Michael, K.E., Vernekar, V.N., Keselowsky, B.G., Meredith, J.C., Latour, R.A., Garcia, A.J., (2003) Langmuir, 19, p. 8033; Keselowsky, B.G., Collard, D.M., Garcia, A.J., (2003) J. Biomed. Mater. Res, 66 A, p. 247; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., (2003) J. Biomed. Mater. Res, 67 A, p. 538; McFarland, C.D., Mayer, S., Scotchford, C., Dalton, B.A., Steele, J.G., Downes, S., (1999) J. Biomed. Mater. Res, 44, p. 1; Cowles, E.A., Brailey, L.L., Gronowicz, G.A., (2000) J. Biomed. Mater. Res, 52, p. 725; Marco, R.A.W., Diaz-Montero, C.M., Wygant, J.N., Kleinerman, E.S., McIntyre, B.W., (2003) J. Cell. Biochem, 88, p. 1038; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Dean, D.D., Boyan, B.D., (1995) J. Biomed. Mater. Res, 29, p. 389; Anselme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Iost, A., Hardouin, P., (2000) J. Biomed. Mater. Res, 49, p. 155; Zinger, O., Anselme, K., Denzer, A., Habersetzer, P., Wieland, M., Jeanfils, J., Hardouin, P., Landolt, D., (2004) Biomaterials, 25, p. 2695
Keywords: Acetylation; AFM; article; Atomic force microscopy; Biocompatible Materials; biofilm; Biofilms; biomaterial; bone cell; cartilage cell; cell adhesion; cell anchorage; Cell culture; cell growth; Cell Line, Tumor; cell proliferation; Cell Shape; cell spreading; cell survival; Chemical structure; chemistry; Chitin; chitosan; comparative study; controlled study; cytoskeleton; Degree of acetylation; drug effect; Growth kinetics; human; human cell; Humans; incubation time; metabolism; Microscopy, Atomic Force; osteoblast; Osteoblast-like cells; Osteoblasts; Pathology; priority journal; Surface charge; Surface Properties; surface property; Surface treatment; tumor cell line; Zeta potential

Laser surface treatment of hydroxyapatite for enhanced tissue integration: Surface characterization and osteoblastic interaction studies - Teixeira, S.; Monteiro, F.J.; Ferraz, M.P.; Vilar, R.; Eugénio, S. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2007)
Biocompatibility has long been associated with surface microtopography, microtexture, and microchemistry. The surface topography eventually affects the nature and the intensity of the interactions that occur at biomaterial- biological interface (cell adhesion, mobility, spreading, and proliferation). Therefore, it is necessary to produce and work with controlled microtopographical surfaces that present reproducible microdomains of a dimension similar to that of the biological elements of interest (in this case, osteoblasts). There are a number of substrates that already have been studied in terms of surface topography; however, few studies are related to hydroxyapatite (HA) substrates. As it is well established, HA is a well-known ceramic that is extremely used in medical applications, namely implants and coatings. In this work, the surface topography of dense HA substrates was altered by using KFr excimer laser. The surface was characterized by atomic force microscopy and contact angle measurements, while the cell distribution and morphology was assessed by scanning electron microscopy and confocal laser scanning microscopy. Results revealed that the surface is characterized by a homogeneous columnar structure with high specific area. Moreover, cells were able to attach and spread on the surface of the samples, and gradually grow into nearly confluent monolayers. © 2007 Wiley Periodicals, Inc.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31073PubMed ID: 17252543Language of Original Document: EnglishCorrespondence Address: Teixeira, S.; Laboratório de Biomateriais, INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre 823, 4150-180, Porto, Portugal; email: smsilva@ineb.up.ptChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; Ceramics; Durapatite, 1306-06-5Manufacturers: Plasma BiotalReferences: Teixeira S, Queiroz AC, Monteiro FJ, Ferraz MP, Vilar R, Eugenio S. Osteoblast proliferation and morphology analysis on laser modified hydroxyapatite surfaces: Preliminary results. Bioceramics 2006;18 (Parts 1, 2):309-311, 105-108Fernandez-Pradas, J.M., Cleries, L., Martinez, E., Sardin, G., Esteve, J., Morenza, J.L., Influence of thickness on the properties of hydroxyapatite coatings deposited by KrF laser ablation (2001) Biomaterials, 22, pp. 2171-2175;Fernandez-Pradas, J.M., Cleries, L., Serra, P., Sardin, G., Morenza, J.L., Evolution of the deposition rate during pulsed laser deposition of hydroxyapatite coatings and its relation with target morphology (2001) Appl Phys A: Mater Sci Process, 72, pp. 613-618; Foltyn, S.R., Dye, R., Ott, K.C., Peterson, E., Hubbard, K.M., Hutchinson, W., Muenchausen, R.E., Wu, X.D., Target modification in the excimer laser deposition of YBa 2Cu 3O 7-x thin films (1991) Appl Phys Lett, 59, pp. 594-596; Khor, K.A., Vreeling, A., Dong, Z.L., Cheang, P., Laser treatment of plasma sprayed HA coatings (1999) Mater Sci Eng A: Struct Mater Prop Microstruct Process, 266 (1-2), pp. 1-7; Ricci, J.L., Alexander, H., Laser microtexturing of implant surfaces for enhanced tissue integration (2001) Key Engineering Mater, pp. 198-199,179-202; Galli, C., Guizzardi, S., Passeri, G., Martini, D., Tinti, A., Mauro, G., Macaluso, G.M., Comparison of human mandibular osteoblasts grown on two commercially available titanium implant surfaces (2005) J Periodontol, 76, pp. 364-372; Oliveira, V., Conde, O., Vilar, R., UV laser micromachining of ceramic materials: Formation of columnar topographies (2001) Adv Eng Mater, 3 (1-2), pp. 75-81; Serra, P., FernandezPradas, J., Sardin, G., Morenza, J.L., Interaction effects of an excimer laser beam with hydroxyapatite targets (1997) Appl Surf Sci, 110, pp. 384-388; Serra, P., Morenza, J.L., Fluence dependence of hydroxyapatite laser ablation plumes (1998) Thin Solid Films, 335 (1-2), pp. 43-48; Duncan, A.C., Weisbuch, F., Rouais, F., Lazare, S., Baquey, C., Laser microfabricated model surfaces for controlled cell growth (2002) Biosens Bioelectron, 17, pp. 413-426; Walboomers, X.F., Croes, H.J.E., Ginsel, L.A., Jansen, J.A., Contact guidance of rat fibroblasts on various implant materials (1999) J Biomed Mater Res, 47, pp. 204-212; Carvalho, P., Manzanares, M.C., Franch, J., Belmonte, A.M., Lafuente, M.P., Serra, I., Fernandez-Pradas, J.M., Morenza, J.L., Osteointegration of calcium phosphate coatings obtained by pulsed laser deposition (2003) J Dent Res, 82, p. 573; Ahmad, M., McCarthy, M., Gronowicz, G., An in vitro model for mineralization of human osteoblast-like cells on implant materials (1999) Biomaterials, 20, pp. 211-220; Matsuura, T., Hosokawa, R., Okamoto, K., Kimoto, T., Akagawa, Y., Diverse mechanisms of osteoblast spreading on hydroxyapatite and titanium (2000) Biomaterials, 21, pp. 1121-1127; Torricelli, P., Fini, M., Giavaresi, G., Borsari, V., Carpi, A., Nicolini, A., Giardino, R., Comparative interspecies investigation on osteoblast cultures: Data on cell viability and synthetic activity (2003) Biomed Pharmacother, 57, pp. 57-62; Boyan, B.D., Lossdoerfer, S., Wang, L., Zhao, G., Lohmann, C.H., Cochran, D.L., Schwartz, Z., Osteoblasts generate an osteogenic microenvironment when grown on surfaces with rough microtopographies (2003) Eur Cell Mater, 6, pp. 22-27; Anselme, K., Bigerelle, M., Topography effects of pure titanium substrates on human osteoblast long-term adhesion (2005) Acta Biomater, 1, pp. 211-222; Anselme, K., Linez, P., Bigerelle, M., Le Maguer, D., Le Maguer, A., Hardouin, P., Hildebrand, H.F., Leroy, J.M., The relative influence of the topography and chemistry of TiAl 6V 4 surfaces on osteoblastic cell behaviour (2000) Biomaterials, 21, pp. 1567-1577; Anselme, K., Noel, B., Hardouin, P., Human osteoblast adhesion on titanium alloy, stainless steel, glass and plastic substrates with same surface topography (1999) J Mater Sci: Mater Med, 10, pp. 815-819; Cleries L, Fernandez-Pradas JM, Morenza JL. Bone growth on and resorption of calcium phosphate coatings obtained by pulsed laser deposition. J Biomed Mater Res 2000;49:43. Erratum 2001;57:473Deligianni, D.D., Katsala, N., Ladas, S., Sotiropoulou, D., Amedee, J., Missirlis, Y.F., Effect of surface roughness of the titanium alloy Ti-6Al-4V on human bone marrow cell response and on protein adsorption (2001) Biomaterials, 22, pp. 1241-1251; dos Santos, E.A., Farina, M., Soares, G.A., Specific proliferation rates of human osteoblasts on calcium phosphate surfaces with variable concentrations of α-TCP (2007) Mater Sci Eng, 27, pp. 61-66; Hao, L., Lawrence, J., Laser surface treatment of magnesia partially stabilized zirconia for enhanced human skin fibroblast cell response (2004) J Laser Appl, 16, pp. 55-64; Kieswetter, K., Schwartz, Z., Dean, D.D., Boyan, B.D., The role of implant surface characteristics in the healing of bone (1996) Crit Rev Oral Biol Med, 7, pp. 329-345; Saldaña, L., Gonzńlez-Carrasco, J.L., Rodriguez, M., Munuera, L., Vilaboa, N., Osteoblast response to plasma-spray porous Ti 6AL 4V coating on substrates of identical alloy (2006) J Biomed Mater Res A, 77, pp. 608-617; Lincks, J., Boyan, B.D., Blanchard, C.R., Lohmann, C.H., Liu, Y., Cochran, D.L., Dean, D.D., Schwartz, Z., Response of MG63 osteoblast-like cells to titanium and titanium alloy is dependent on surface roughness and composition (1998) Biomaterials, 19, pp. 2219-2232; Martin, J.Y., Dean, D.D., Cochran, D.L., Simpson, J., Boyan, B.D., Schwartz, Z., Proliferation, differentiation, and protein synthesis of human osteoblast-like cells (MG63) cultured on previously used titanium surfaces (1996) Clin Oral Implants Res, 7, pp. 27-37; Noth, U., Hendrich, C., Merklein, F., Altvater, T., Rader, C.P., Schutze, N., Eulert, J., Thull, R., Standardised testing of bone-implant surfaces using an osteoblast cell culture system. II. Titanium surfaces of varying degrees of roughness (1999) Biomedizinische Technik, 44 (1-2), pp. 6-11; Ponsonnet, L., Reybier, K., Jaffrezic, N., Comte, V., Lagneau, C., Lissac, M., Martelet, C., Relationship between surface properties (roughness, wettability) of titanium and titanium alloys and cell behaviour (2003) Mater Sci Eng C: Biomimetic Supramolecular Syst, 23, pp. 551-560; Ramires, P.A., Romito, A., Cosentino, F., Milella, E., The influence of titania/hydroxyapatite composite coatings on in vitro osteoblasts behaviour (2001) Biomaterials, 22, pp. 1467-1474; Redey, S.A., Nardin, M., Bernache-Assolant, D., Rey, C., Delannoy, P., Sedel, L., Marie, P.J., Behavior of human osteoblastic cells on stoichiometric hydroxyapatite and type A carbonate apatite: Role of surface energy (2000) J Biomed Mater Res, 50, pp. 353-364; Rosa, A.L., Beloti, M.M., van Noort, R., Osteoblastic differentiation of cultured rat bone marrow cells on hydroxyapatite with different surface topography (2003) Dent Mater, 19, pp. 768-772; Schmidt, C., Ignatius, A.A., Claes, L.E., Proliferation and differentiation parameters of human osteoblasts on titanium and steel surfaces (2001) J Biomed Mater Res, 54, pp. 209-215; Schwartz, Z., Kieswetter, K., Dean, D.D., Boyan, B.D., Underlying mechanisms at the bone-surface interface during regeneration (1997) J Periodontal Res, 32, pp. 166-171; Schwartz, Z., Martin, J.Y., Dean, D.D., Simpson, J., Cochran, D.L., Boyan, B.D., Effect of titanium surface roughness on chondrocyte proliferation, matrix production, and differentiation depends on the state of cell maturation (1996) J Biomed Mater Res, 30, pp. 145-155; Wang, J., de Boer, J., de Groot, K., Preparation and characterization of electrodeposited calcium phosphate/chitosan coating on Ti 6Al 4V plates (2004) J Dent Res, 83, pp. 296-301; Xavier, S.P., Carvalho, P.S.P., Beloti, M.M., Rosa, A.L., Response of rat bone marrow cells to commercially pure titanium submitted to different surface treatments (2003) J Dent, 31, pp. 173-180
Keywords: article; Atomic force microscopy; Biocompatibility; biomaterial; cell adhesion; Cell Communication; Cell Line, Tumor; cell motility; cell proliferation; cell spreading; cellular distribution; ceramic prosthesis; ceramics; chemistry; confocal laser microscopy; controlled study; Durapatite; Excimer laser; Excimer lasers; human; human cell; Humans; hydroxyapatite; laser; Lasers; material coating; Microchemistry; Microscopy, Atomic Force; Microscopy, Confocal; Microscopy, Electron, Scanning; Microtexture; monolayer culture; osteoblast; Osteoblasts; reproducibility; Scanning electron microscopy; Surface microtopography; Surface modification; Surface Properties; surface property; Surface topography; Surface treatment; Tissue engineering

Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period - Gonçalves, H.; Bernardes, J.; Paula Rocha, A.; Ayres-de-Campos, D. (Early Human DevelopmentEarly Hum. Dev., 2007)
Background: Fetal behavioral states are important indicators of fetal physiology and pathology associated to typical fetal heart rate (FHR) patterns. Aim: To provide linear and nonlinear analysis of FHR patterns associated with fetal behavioral states regarding a better understanding of these states and patterns. Study design and subjects: Fifty FHR tracings from normal term pregnancies with a median duration of 40.3 min were acquired with the SisPorto® 2.01 system for computerized analysis of cardiotocograms. Each tracing was divided into consecutive 10-minute segments and each segment was classified by two experts as pattern A, B, C or D. Outcome measures: Linear and nonlinear indices were computed in each segment, namely mean FHR, long-term irregularity index (LTI), very low (VLF), low (LF) and high (HF) frequency spectral indices, approximate entropy (ApEn) and sample entropy (SampEn). Kappa statistic (κ) and proportions of agreement (Pa) were used for assessment of inter-observer agreement. Bootstrap percentile confidence intervals and nonparametric statistical tests were calculated for statistical inference. Results: Overall agreement between experts in pattern classification was good to excellent with values for κ and Pa of 0.74 (95% CI: 0.64-0.94) and 0.94 (95% CI: 0.92-0.96), respectively. Most linear domain indices increased significantly with rising fetal activity whereas the opposite occurred with nonlinear indices, except for SampEn(2, 0.1). LF/(MF + HF) ratio also significantly increased with fetal activity, denoting an increased sympatho-vagal balance. Conclusions: Results support the hypothesis that entropy and linear variability indices measure different FHR features. FHR patterns associated with active sleep (B) and active wakefulness (D) evidenced more signs of autonomous nervous system activity, with sympatho-vagal imbalance, and less signs related to complexity or irregularity control systems than patterns associated with calm sleep (A) and calm wakefulness (C). © 2006 Elsevier Ireland Ltd. All rights reserved.
Cited By (since 1996): 17Export Date: 21 November 2012Source: ScopusCODEN: EHDEDdoi: 10.1016/j.earlhumdev.2006.12.006PubMed ID: 17261357Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Universidade do Porto, Faculdade de Ciências, Departamento de Matemática Aplicada, Porto, Portugal; email: hernani.goncalves@fc.up.ptReferences: Nijhuis, J.G., Prechtl, H.F., Martin, C.B.J., Bots, R.S., Are there behavioural states in the human fetus? (1982) Early Hum Dev, 6, pp. 177-195;Nijhuis, I., ten Hof, J., Development of fetal heart rate and behavior: indirect measures to assess the fetal nervous system (1999) Eur J Obstet Gynaecol Reprod Biol, 87, pp. 1-2; Vindla, S., James, D., Fetal behaviour as a test of fetal wellbeing (1995) Br J Obstet Gynaecol, 102, pp. 597-600; Swartjes, J.M., van Geijn, H.P., Mantel, R., van Woerden, E.E., Schoemaker, H.C., Coincidence of behavioural state parameters in the human fetus at three gestational ages (1990) Early Hum Dev, 23, pp. 75-83; Ayres-de-Campos, D., Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: the antepartum arm of the SisPorto® multicentre validation study (2005) Eur J Obstet Gynaecol Reprod Biol, 118, pp. 52-60; Ayres-de-Campos, D., Bernardes, J., Garrido, A., de Sá, J.M., Pereira-Leite, L., SisPorto 2.0: a program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Rooth, G., Huch, A., Huch, R., FIGO news. Guidelines for the use of fetal monitoring (1987) Int J Gynaecol Obstet, 25, p. 159; Bernardes, J., Moura, C., de Sá, J.P.M., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: the effect on linear and nonlinear parameters (2006) Physiol Meas, 27, pp. 307-319; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans Biomed Eng, 50 (3), pp. 365-373; Pincus, S., Viscarello, R., Approximate Entropy: a regularity measure for fetal heart rate analysis (1992) Obstet Gynaecol, 79 (2), pp. 249-255; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am J Physiol Heart Circ Physiol, 278, pp. H2039-H2049; Pincus, S., Approximate entropy (ApEn) as a complexity measure (1995) Chaos, 5 (1), pp. 110-117; Grant, J.M., The fetal heart rate trace is normal, isn't it? Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Martinez, W.L., Martinez, A.R., (2002) Computational statistics handbook with MATLAB, , CRC Press; van Woerden, E.E., Geijn, H.P., Caron, F.J., Swartjes, J.M., Mantel, R., Arts, N.F., Automated assignment of behavioural states in the human near term fetus (1989) Early Hum Dev, 19, pp. 137-146; Ten Hof, J., Nijhuis, I.J., Mulder, E.J., Nijhuis, J.G., Narayan, H., Taylor, D.J., Longitudinal study of fetal body movements: nomograms, intrafetal consistency, and relationship with episodes of heart rate patterns A and B (2002) Pediatr Res, 52 (4), pp. 568-575; Bernardes, J., Costa-Pereira, A., de Campos, D.A., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynaecol Obstet, 57 (1), pp. 33-37; Bernardes, J., Costa-Pereira, A., van Geijn, H.P., Pereira-Leite, L., A more objective fetal heart rate baseline estimation (1996) Br J Obstet Gynaecol, 103, pp. 714-715; Mantel, R., van Geijn, H.P., Ververs, I.A., Copray, F.J., Automated analysis of near-term antepartum fetal heart rate in relation to fetal behavioral states: the Sonicaid System 8000 (1992) Am J Obstet Gynaecol, 167 (6), pp. 1912-1914; Court, D.J., Parer, J.T., Experimental studies of fetal asphyxia and fetal heart rate interpretation (1984) Research in perinatal medicine, pp. 113-169. , Nathanielsz P.W., and Parer J.T. (Eds), Perinatology Press, New York; Oppenheimer, L.W., Lewinsky, R.M., Power spectral analysis of fetal heart rate (1994) Bailliere's Clin Obstet Gynaecol, 8 (3), pp. 643-661; van Woerden, E.E., Geijn, H.P., Caron, F.J., Mantel, R., Spectral analysis of fetal heart rhythm in relation to fetal regular mouthing (1990) Int J Biomed Comput, 25 (4), pp. 253-260; Boog, G., Analyse informatisée du rythme cardiaque foetal au cours de la grossesse et de l'accouchement (2004) Encycl Méd-Chir, 148 (5-49 -D-23), pp. 1-10; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Murotsuki, N.Y.J., Uehara, S., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am J Obstet Gynaecol, 182, pp. 1227-1232; Dawes, G.S., Moulden, M., Sheil, O., Redman, C.W.G., Approximate entropy, a statistic of regularity, applied to fetal heart rate data before and during labour (1992) Obstet Gynaecol, 80 (5), pp. 763-768; Magenes, G., Signorini, M.G., Arduini, D., Cerutti, S., Fetal heart rate variability due to vibroacoustic stimulation: linear and nonlinear contribution (2004) Methods Inf Med, 43 (1), pp. 47-51; Felgueiras, C., de Sá, J.P.M., Bernardes, J., Gama, S., Fractal characterisation of fetal heart rate sequences (1998) Biomed Eng, 36 (2), pp. 197-201; Vieira, P., Marques-de-Sá, J.P., Bernardes, J., Fractal analysis of foetal heart rate (2004) Proceedings of biosignal 2004, pp. 53-55. , Jan J., Kozumplík J., and Provazník I. (Eds), Vutium Press, Brno University of Technology; di Renzo, G.C., Montani, M., Fioriti, V., Clerici, G., Branconi, F., Pardini, A., Fractal analysis: a new method for evaluating fetal heart rate variability (1996) J Perinat Med, 24 (3), pp. 261-269
Keywords: adult; article; behavior change; Cardiotocography; Computerized analysis; controlled study; entropy; Female; Fetal behavioral states; Fetal heart rate; Fetal monitoring; fetus; fetus heart rate; fetus monitoring; Heart Rate, Fetal; human; Humans; Image Interpretation, Computer-Assisted; Linear Models; Nonlinear Dynamics; Pregnancy; SisPorto; Spectral analysis; vagus nerve stimulation

Nanohydroxyapatite microspheres as delivery system for antibiotics: Release kinetics, antimicrobial activity, and interaction with osteoblasts - Ferraz, M.P.; Mateus, A.Y.; Sousa, J.C.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2007)
Severe periodontitis treatment, where massive alveolar bone loss occurs, involves bone defect filling and intensive systemic log-term antibiotics administration. This study aims at developing novel injectable drug delivery systems (nanohydroxyapatite microspheres) with the drug releasing capability for periodontitis treatment and simultaneously initiating the osteointegration process. Materials were characterized by XRD, SEM, inverted stand optical microscope analysis, and mercury porosimetry method. Amoxicillin, amoxicillin + clavulanic acid, and erythromycin were the antibiotics used. Release properties during 28 days from the hydroxyapatite (HA) granules, and two types of nanoHA microspheres were investigated. Biocompatibility was assessed by cytotoxicity assays. HA granules were inadequate, releasing all antibiotic during the first hours. The concentration of antibiotics released in the first days from HA-2 was higher than from HA-1 microspheres, because of the increased porosity and surface area. The release profiles (fast initial release followed by long-term sustained release) of effective doses of antibiotics make these systems good alternatives for antibiotics delivery. Osteoblasts proliferated well on both types of microspheres, being cell growth enhanced in the presence of antibiotics. Erythromycin presented the most beneficial effect. Combining the sustained antibiotic release with the osteoconduction, resorbability, and potential use as injectable bone filling material of porous HA microspheres, these systems provided a forth fold beneficial effect. © 2007 Wiley Periodicals, Inc.
Cited By (since 1996): 32Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31151PubMed ID: 17252559Language of Original Document: EnglishCorrespondence Address: Ferraz, M.P.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: mpferraz@ufp.ptChemicals/CAS: amoxicillin, 26787-78-0, 34642-77-8, 61336-70-7; amoxicillin plus clavulanic acid, 74469-00-4, 79198-29-1; clindamycin, 18323-44-9; erythromycin, 114-07-8, 70536-18-4; hydroxyapatite, 1306-06-5, 51198-94-8; metronidazole, 39322-38-8, 443-48-1; minocycline, 10118-90-8, 11006-27-2, 13614-98-7; tetracycline, 23843-90-5, 60-54-8, 64-75-5; Anti-Bacterial Agents; Durapatite, 1306-06-5References: Krejci, C.B., Bissada, N.F., Farah, C., Greenwell, H., Clinical-evaluation of porous and nonporous hydroxyapatite in the treatment of human periodontal bony defects (1987) J Periodontol, 58, pp. 521-528;Kinane, D.F., Lindhe, J., Pathogenesis of periodontitis (2002) Clinical Periodontology and Implant Dentistry, pp. 189-225. , Lindhe J, Karring T, Lang NP, editors, Copenhagen: Munksgaard;; Slots, J., Armitage, G.C., Cochran, D., Cohen, R.E., Greenstein, G., Mariotti, A., Rethman, M.P., and others, Systemic antibiotics in periodontics (1996) J Periodontol, 67, pp. 831-838; Mombelli, A., Antibiotics in periodontal therapy (2002) Clinical Periodontology and Implant Dentistry, , Lindhe J, Karring T, Lang NP, editors, Copenhagen: Munksgaard;; Etienne, D., Locally delivered antimicrobials for the treatment of chronic periodontitis (2003) Oral Dis, 9, pp. 45-50; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Porous HA scaffolds for drug releasing (2005) Bioceramics, 17, pp. 407-410; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., Porous hydroxyapatite and glass reinforced hydroxyapatite for controlled release of sodium ampicillin (2004) Bioceramics, 16, pp. 997-1000; Hannes, P.J., Purvis, J.P., Local anti-infective therapy: Pharmacological agents. A systemic review (2003) Ann Periodontol, 8, pp. 79-98; Soskolne, W.A., Heasman, P.A., Stabholz, A., Smart, G.J., Palmer, M., Flashner, M., Newman, H.N., Sustained local delivery of chlorhexidine in the treatment of periodontitis: A multi-center study (1997) J Periodontol, 68, pp. 32-38; Greenstein, G., Polson, A., The role of local drug delivery in the management of periodontal diseases: A comprehensive review (1998) J Periodontol, 69, pp. 507-520; Killoy, W.J., Chemical treatment of periodontitis: Local delivery of antimicrobials (1998) Int Dent J, 48, pp. 305-315; Schwach-Abdellaoui, K., Vivien-Castioni, N., Gurny, R., Local delivery of antimicrobial agents for the treatment of periodontal diseases (2000) Eur J Pharm Biopharm, 50, pp. 83-99; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Development of a system to adsorb drugs onto calcium phosphate materials (2005) J Mater Sci-Mater Med, 16, pp. 641-646; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Adsorption isotherm of sodium ampicillin onto dense and porous hydroxyapatite (2005) Bioceramics, 17, pp. 387-390; Queiroz, A.C., Santos, J.D., Monteiro, F.J., da Silva, MHP dissolution studies of hydroxyapatite and glass-reinforced hydroxyapatite ceramics (2003) Mater Char, 50, pp. 197-202; Rauschmann, M.A., Wichelhaus, T.A., Stirnal, V., Dingeldein, E., Zichner, L., Schnettler, R., Alt, V., Nanocrystalline hydroxyapatite and calcium sulphate as biodegradable composite carrier material for local delivery of antibiotics in bone infections (2005) Biomaterials, 26, pp. 2677-2684; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., Production of porus hydroxyapatite with potential for controlled drug delivery (2004) Mater Sci Forum, 455-456, pp. 358-360; Daculsi, G., Passuti, N., Effect of the macroporosity for osseous substitution of calcium-phosphate ceramics (1990) Biomaterials, 11, pp. 86-87; Gauthier, O., Bouler, J.M., Weiss, P., Bosco, J., Daculsi, G., Aguado, E., Kinetic study of bone ingrowth and ceramic resorption associated with the implantation of different injectable calcium-phosphate bone substitutes (1999) J Biomed Mater Res, 47, pp. 28-35; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Specific proteins mediate enhanced osteoblast adhesion on nanophase ceramics (2000) J Biomed Mater Res, 51, pp. 475-483; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21, pp. 1803-1810; Webster, T.J., Siegel, R.W., Bizios, R., Enhanced surface and mechanical properties of nanophase ceramics to achieve orthopaedic/dental implant efficacy (2000) Bioceramics, 13, pp. 321-324; Liou, S.C., Chen, S.Y., Liu, D.M., Synthesis and characterization of needlelike apatitic nanocomposite with controlled aspect ratios (2003) Biomaterials, 24, pp. 3981-3988; Ferraz, M.P., Monteiro, F.J., Manuel, C.D., Hydroxyapatite nanoparticles: A review of preparation methodologies (2004) J Appl Biomater Biomech, 2, pp. 74-80; Barrias CC, Ribeiro CC, Martins MCL, Barbosa MA, Rodrigues D, Miranda MCS. Calcium phosphate microspheres for localised delivery of a therapeutic enzyme. Bioceramics 2006;18 (Parts 1/2):903-906Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Calcium phosphate-alginate microspheres as enzyme delivery matrices (2004) Biomaterials, 25, pp. 4363-4373; Socransky, S.S., Haffajee, A.D., Microbiology of periodontal disease (2002) Clinical Periodontology and Implant Dentistry, , Lindhe J, editor, Copenhagen: Munksgaard;; Slots, J., Selection of antimicrobial agents in periodontal therapy (2002) J Periodontal Res, 37, pp. 389-398; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Preparation and characterisation of calcium-phosphate porous microspheres with a uniform size for biomedical applications (2006) J Mater Sci-Mater Med, 17, pp. 455-463; Barrias, C.C., Ribeiro, C.C., Lamghari, M., Sá, C., Barbosa, M.A., Proliferation, activity and osteogenic differentiation of bone marrow stromal cells cultured on calcium titanium phosphate microspheres (2005) J Biomed Mater Res A, 72, pp. 57-66; Mateus, A.Y.P., Ferraz, M.P., Monteiro, F.J., Comparative study of injectable material synthesised from alginate and two types of hydroxyapatite Submitted for publicationFerraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P2O5 glass hydroxyapatite double layer plasma sprayed coatings: In vitro bioactivity evaluation (1999) J Biomed Mater Res, 45, pp. 376-383; Hyakuna, K., Yamamuro, T., Kotoura, Y., Oka, M., Nakamura, T., Kitsogi, T., Kokubo, T., Kushitani, H., Surface reactions of calcium phosphate ceramics to various solutions (1990) J Biomed Mater Res, 24, pp. 471-488; Gautier, H., Daculsi, G., Merle, C., Association of vancomycin and calcium phosphate by dynamic compaction: In vitro characterization and microbiological activity (2001) Biomaterials, 22, pp. 2481-2487; Kimakhe, S., Bohic, S., Larrose, C., Reynaud, A., Pilet, P., Giumelli, B., Heymann, D., Daculsi, G., Biological activities of sustained polymyxin B release from calcium phosphate biomaterial prepared by dynamic compaction: An in vitro study (1999) J Biomed Mater Res, 47, pp. 18-27; Korkusuz, F., Uchida, A., Shinto, Y., Araki, N., Inoue, K., Ono, K., Experimental implant-related osteomyelitis treated by antibiotic-calcium hydroxyapatite ceramic composites (1993) J Bone Joint Surg-Br, 75, pp. 111-114; Otsuka, M., Matsuda, Y., Kokubo, T., Yoshihara, S., Nakamura, T., Yamamuro, T., A novel skeletal drug-delivery system using self-setting bioactive glass bone-cement. II. Drug-release from a novel self-setting bioactive glass bone-cement containing cephalexin and its physicochemical properties (1995) J Biomed Mater Res, 29, pp. 33-38; Shinto, Y., Uchida, A., Korkusuz, F., Araki, N., Ono, K., Calcium hydroxyapatite ceramic used as a delivery system for antibiotics (1992) J Bone Joint Surg Br, 74, pp. 600-604; Yamamura, K., Iwata, H., Yotsuyanagi, T., Synthesis of antibiotic-loaded hydroxyapatite beads and invitro drug release testing (1992) J Biomed Mater Res, 26, pp. 1053-1064; Clover, J., Gowen, M., Are Mg-63 and Hos Te85 human osteosarcoma cell-lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591
Keywords: alveolar bone; amoxicillin; amoxicillin plus clavulanic acid; Anti-Bacterial Agents; Antibacterial; antibiotic agent; antibiotic resistance; Antibiotics administration; antimicrobial activity; article; Bacteria; Cell Communication; Cell Death; cell growth; cell kinetics; Cell Line; cell proliferation; clindamycin; concentration response; controlled study; Cytotoxicity; Drug delivery; drug delivery system; Drug Delivery Systems; Drug release; Durapatite; erythromycin; Escherichia coli; human; human cell; Humans; hydroxyapatite; Kinetics; materials testing; metronidazole; Microbial Sensitivity Tests; microsphere; Microspheres; minocycline; Nanohydroxyapatite; nanoparticle; nanoparticles; nonhuman; Optical microscope analysis; osteoblast; Osteoblasts; osteolysis; periodontitis; porosity; Staphylococcus aureus; surface property; sustained drug release; Tetracycline; unclassified drug; X ray diffraction

Opening wedge high tibial osteotomy using 3D biomodelling Bonelike® macroporous structures: Case report - Gutierres, M.; Dias, A.G.; Lopes, M.A.; Hussain, N.S.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2007)
Two synthetic calcium phosphates in porous wedge shape, Bonelike® and a commercial HA/β-TCP biphasic material, were used as an alternative to bone autografts and allografts in the treatment of medial compartment osteoarthritis of varus knees. The structure of Bonelike® has a 3D architecture that is computer controlled, and a composition that mimics the mineral composition of natural bone. The HA/β-TCP biphasic material used as a control material in this study was prepared using conventional foaming based methods. No signs of inflammatory reactions were observed post-operatively for both materials. After 4 months signs of fusion at the osteotomy site and good integration of the implanted wedges were observed, showing good mechanical resistance. Concerning the final correction attained, the left knee revealed a satisfactory valgus of 10°, but the right one only had a final value of 6°. The clinical evaluation using International Knee Score (IKS) showed good outcome in all parameters with complete range of motion in both knees and climbing stairs without crutches with only slight pain. © 2007 Springer Science+Business Media, LLC.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-007-3171-xPubMed ID: 17569003Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratório de Biomateriais, Instituto de Engenharia Biomédica (INEB), Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; Bone Substitutes; Calcium Phosphates; Ceratite, 124097-42-3; HydroxyapatitesTradenames: BonelikeReferences: Gaasbeek, R.D.A., Welsing, R.T.C., Verdonschot, N., Rijnberg, W.J., Van Loon, C.J.M., Van Kampen, A., (2005) Knee Surg. Sports Traumatol. Arthrosc., 13, p. 689. , 8;Scott, W.N., Clarke, H.D., (2004) Orthopedics, 27, p. 975. , 9; Virolainen, P., Aro, H.T., (2004) Arch. Orthop. Trauma Surg., 124, p. 258. , 4; Wright, J.M., Crockett, H.C., Slawski, D.P., Madsen, M.W., Windsor, R.E., (2005) J. Am. Acad. Orthop. Surg., 13, p. 279. , 4; Fujisawa, Y., Masura, K., Shiomi, S., (1979) Clin. Orthop. North Am., 10, p. 585; Odenbridge, S., Egund, N., Lindstrand, A., Lohmander, L.S., Willen, H., (1992) Clin Orthop., 277, p. 210; Koshino, T., Wada, S., Ara, Y., Saito, T., (2003) Knee, 10, p. 229; Hernigou, P., (2002) Knee, 9, p. 15. , 1; Hoell, S., Suttmoeller, J., Stoll, V., Fuchs, S., Gosheger, G., (2005) Arch. Orthop. Trauma Surg., 125, p. 638. , 9; Betz, R.R., (2002) Orthopedics, 25, p. 561. , 5; Legeros, R.Z., (2002) Clin. Orthop. Relat. Res., 395, p. 81; Steffen, T., Stoll, T., Arvinte, T., Schenk, R.K., (2001) Eur. Spine J., 10, p. 132; Chu, T.M.G., Orton, D.G., Hollister, S.J., Feinberg, S.E., Halloran, J.W., (2002) Biomaterials, 23, p. 1283. , 5; Hutmacher, D.W., Sittinger, M., Risbud, M.V., (2004) Trends Biotechnol., 22, p. 354. , 7; Jones, J.R., Ehrenfried, L.M., Hench, L.L., (2006) Biomaterials, 27, p. 964. , 7; Gauthier, O., Bouler, J.M., Aguado, E., Pilet, P., Daculsi, G., (1998) Biomaterials, 19, p. 133. , 1-3; LU, J.X., Flautre, B., Anselme, K., Hardouin, P., Gallur, A., Descamps, M., Thierry, B., (1999) J. Mater. Sci. Mater. Med., 10, p. 111. , 2; Martina, M., Subramanyam, G., Weaver, J.C., Hutmacher, D.W., Morse, D.E., Valiyaveettil, S., (2005) Biomaterials, 26, p. 5609. , 28; Moroni, L., De Wijn, J.R., Van Blitterswijk, C.A., (2006) Biomaterials, 27, p. 974. , 7; Duarte, F., Santos, J.D., Afonso, A., (2004) Adv. Mater. Forum, 455-456, p. 370; Lobato, J.V., Hussain, N.S., Botelho, C.M., Mauricio, A.C., Lobato, J.M., Lopes, M.A., Afonso, A., Santos, J.D., (2006) Thin Solid Films, 515, p. 279. , 1; Gutierres, M., Hussain, N.S., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Santos, J.D., (2005) Bioceramics, 17, p. 1041; Lobato, J.V., Hussain, N.S., Botelho, C.M., Rodrigues, J.M., Luís, A.L., Maurício, A.C., Lopes, M.A., Santos, J.D., (2005) Key Eng. Mater., 284-286, p. 877; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463; Leong, K.F., Cheah, C.M., Chua, C.K., (2003) Biomaterials, 24, p. 2363. , 13; Hutmacher, D.W., (2001) J. Biomater. Sci. Polym. Ed., 12, p. 107. , 1; Santos, J., Hastings, G., Knowles, J., Sintered hydroxyapatite compositions and method for the preparation thereof (1999), Worldwide Application (PCT), Patent No. 1 189 851Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244. , 2; Lopes, M.A., Knowles, J.C., Santos, J.D., (2000) Biomaterials, 21, p. 1905. , 18; Schwartz, C., Liss, P., Jacquemaire, B., Lecestre, P., Frayssinet, P., (1999) J. Mater. Sci. Mater. Med., 10, p. 821. , 12; Van Hemert, W.L.W., Willems, K., Anderson, P.G., Van Heerwaarden, R.J., Wymenga, A.B., (2004) Knee, 11, p. 451. , 6; Gaasbeek, R.D.A., Toonen, H.G., Van Heerwaarden, R.J., Buma, P., (2005) Biomaterials, 26, p. 6713. , 33; Hernigou, P., Ma, W., (2001) Knee, 8, p. 103. , 2; Koshino, T., Murase, T., Saito, T., (2003) J. Bone Joint Surg. Am., 85, p. 78. , 1; Koshino, T., Murase, T., Takagi, T., Saito, T., (2001) Biomaterials, 22, p. 1579. , 12; Zhim, F., Laflamme, G.Y., Viens, H., Saidane, K., Yahia, L., (2005) Clin. Biomech., 20, p. 871. , 8; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 20, p. 2085. , 21; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 48, p. 734. , 5
Keywords: adult; article; Biological organs; Biomodeling; Bone; bone allograft; Bone graft; bone mineral; Bone Substitutes; calcium phosphate; Calcium phosphates; case report; climbing; clinical evaluation; Computer simulation; Grafts; human; Humans; hydroxyapatite; Hydroxyapatites; Imaging, Three-Dimensional; knee; knee pain; Macroporous structures; male; Mechanical properties; Middle Aged; Osteoarthritis; Osteoarthritis, Knee; Osteoblasts; osteotomy; pain assessment; porosity; Porous wedge shapes; priority journal; Prostheses and Implants; range of motion; structure analysis; tibia; tibia osteotomy; Tibial osteotomy; Valgus; valgus knee

Cultivation of human embryonic stem cells without the embryoid body step enhances osteogenesis in vitro - Karp, J.M.; Ferreira, L.S.; Khademhosseini, A.; Kwon, A.H.; Yeh, J.; Langer, R.S. (Stem CellsStem Cells, 2006)
Osteogenic cultures of embryonic stem cells (ESCs) are predominately derived from three-dimensional cell spheroids called embryoid bodies (EBs). An alternative method that has been attempted and merits further attention avoids EBs through the immediate separation of ESC colonies into single cells. However, this method has not been well characterized and the effect of omitting the EB step is unknown. Herein, we report that culturing human embryonic stem cells (hESCs) without the EB stage leads to a sevenfold greater number of osteogenic cells and to spontaneous bone nodule formation after 10-12 days. In contrast, when hESCs were differentiated as EBs for 5 days followed by plating of single cells, bone nodules formed after 4 weeks only in the presence of dexamethasone. Furthermore, regardless of the inclusion of EBs, bone matrix formed, including cement line matrix and mineralized collagen, which displayed apatitic mineral (PO 4) with calcium-to-phosphorous ratios similar to those of hydroxyapatite and human bone. Together these results demonstrate that culturing hESCs without an EB step can be used to derive large quantities of functional osteogenic cells for bone tissue engineering. ©AlphaMed Press.
Cited By (since 1996): 80Export Date: 21 November 2012Source: ScopusCODEN: STCEEdoi: 10.1634/stemcells.2005-0383Language of Original Document: EnglishCorrespondence Address: Langer, R.S.; Massachusetts Institute of Technology, 77 Massachusetts Ave., Cambridge, MA 02139-4307, United States; email: rlanger@mit.eduChemicals/CAS: apatite, 64476-38-6; calcium, 7440-70-2; collagen, 9007-34-5; dexamethasone, 50-02-2; hydroxyapatite, 1306-06-5, 51198-94-8; phosphorus, 7723-14-0; alkaline phosphatase, 9001-78-9; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; osteocalcin, 136461-80-8; Alkaline Phosphatase, 3.1.3.1; Calcium Phosphates; Collagen, 9007-34-5; Osteocalcin, 104982-03-8; calcium phosphate, 10103-46-5References: Langer, R., Vacanti, J.P., Tissue engineering (1993) Science, 260, pp. 920-926;Alsberg, E., Anderson, K.W., Albeiruti, A., Cell-interactive alginate hydrogels for bone tissue engineering (2001) J Dent Res, 80, pp. 2025-2029; Bhatia, M., Derivation of the hematopoietic stem cell compartment from human embryonic stem cell lines (2005) Ann N Y Acad Sci, 1044, pp. 24-28; Thomson, J.A., Itskovitz-Eldor, J., Shapiro, S.S., Embryonic stem cell lines derived from human blastocysts (1998) Science, 282, pp. 1145-1147. , erratum in Science 1998 282:1827; Perlingeiro, R.C., Kyba, M., Daley, G.Q., Clonal analysis of differentiating embryonic stem cells reveals a hematopoietic progenitor with primitive erythroid and adult lymphoid-myeloid potential (2001) Development, 128, pp. 4597-4604; Zur Nieden, N.I., Kempka, G., Ahr, H.J., In vitro differentiation of embryonic stem cells into mineralized osteoblasts (2003) Differentiation, 71, pp. 18-27; Bourne, S., Polak, J.M., Hughes, S.P., Osteogenic differentiation of mouse embryonic stem cells: Differential gene expression analysis by cDNA microarray and purification of osteoblasts by cadherin-11 magnetically activated cell sorting (2004) Tissue Eng, 10, pp. 796-806; Buttery, L.D., Bourne, S., Xynos, J.D., Differentiation of osteoblasts and in vitro bone formation from murine embryonic stem cells (2001) Tissue Eng, 7, pp. 89-99; Shimko, D.A., Burks, C.A., Dee, K.C., Comparison of in vitro mineralization by murine embryonic and adult stem cells cultured in an osteogenic medium (2004) Tissue Eng, 10, pp. 1386-1398; Bronson, S.K., Bone nodule formation via in vitro differentiation of murine embryonic stem cells (2003) Methods Enzymol, 365, pp. 241-251; Sottile, V., Thomson, A., McWhir, J., In vitro osteogenic differentiation of human ES cells (2003) Cloning Stem Cells, 5, pp. 149-155; Bielby, R.C., Boccaccini, A.R., Polak, J.M., In vitro differentiation and in vivo mineralization of osteogenic cells derived from human embryonic stem cells (2004) Tissue Eng, 10, pp. 1518-1525; Cao, T., Heng, B.C., Ye, C.P., Osteogenic differentiation within intact human embryoid bodies result in a marked increase in osteocalcin secretion after 12 days of in vitro culture, and formation of morphologically distinct nodule-like structures (2005) Tissue Cell, 37, pp. 325-334; Ginis, I., Luo, Y., Miura, T., Differences between human and mouse embryonic stem cells (2004) Dev Biol, 269, pp. 360-380; Itskovitz-Eldor, J., Schuldiner, M., Karsenti, D., Differentiation of human embryonic stem cells into embryoid bodies compromising the three embryonic germ layers (2000) Mol Med, 6, pp. 88-95; Keller, G.M., In vitro differentiation of embryonic stem cells (1995) Curr Opin Cell Biol, 7, pp. 862-869; Yamada, T., Yoshikawa, M., Kanda, S., In vitro differentiation of embryonic stem cells into hepatocyte-like cells identified by cellular uptake of indocyanine green (2002) Stem Cells, 20, pp. 146-154; Aubin, J.E., Osteoprogenitor cell frequency in rat bone marrow stromal populations: Role for heterotypic cell-cell interactions in osteoblast differentiation (1999) J Cell Biochem, 72, pp. 396-410; Sarugaser, R., Lickorish, D., Baksh, D., Human umbilical cord perivascular (HUCPV) cells: A source of mesenchymal progenitors (2005) Stem Cells, 23, pp. 220-229; Komori, T., Yagi, H., Nomura, S., Targeted disruption of Cbfa1 results in a complete lack of bone formation owing to maturational arrest of osteoblasts (1997) Cell, 89, pp. 755-764; Bonewald, L.F., Harris, S.E., Rosser, J., Von Kossa staining alone is not sufficient to confirm that mineralization in vitro represents bone formation (2003) Calcif Tissue Int, 72, pp. 537-547; Amit, M., Carpenter, M.K., Inokuma, M.S., Clonally derived human embryonic stem cell lines maintain pluripotency and proliferative potential for prolonged periods of culture (2000) Dev Biol, 227, pp. 271-278; Karp, J.M., Shoichet, M.S., Davies, J.E., Bone formation on two-dimensional poly(DL-lactide-co-glycolide) (PLGA) films and three-dimensional PLGA tissue engineering scaffolds in vitro (2003) J Biomed Mater Res, 64 A, pp. 388-396; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Davies, J.E., In vitro modeling of the bone/implant interface (1996) Anat Rec, 245, pp. 426-445; Slizova, D., Krs, O., Pospisilova, B., Alternative method of rapid drying vascular specimens for scanning electron microscopy (2003) J Endovasc Ther, 10, pp. 285-287; Purpura, K.A., Aubin, J.E., Zandstra, P.W., Two-color image analysis discriminates between mineralized and unmineralized bone nodules in vitro (2003) Biotechniques, 34, pp. 1188-1192. , 1194, 1196 passim; Purpura, K.A., Aubin, J.E., Zandstra, P.W., Sustained in vitro expansion of bone progenitors is cell density dependent (2004) Stem Cells, 22, pp. 39-50; Klimanskaya, I., Chung, Y., Meisner, L., Human embryonic stem cells derived without feeder cells (2005) Lancet, 365, pp. 1636-1641; Draper, J.S., Pigott, C., Thomson, J.A., Surface antigens of human embryonic stem cells: Changes upon differentiation in culture (2002) J Anat, 200, pp. 249-258; Aubin, J.E., Liu, F., Malaval, L., Osteoblast and chondroblast differentiation (1995) Bone, 17, pp. 77S-83S; Aubin, J.E., Bone stem cells (1998) J Cell Biochem Suppl, 30-31, pp. 73-82; Schmitt, B., Ringe, J., Haupl, T., BMP2 initiates chondrogenic lineage development of adult human mesenchymal stem cells in high-density culture (2003) Differentiation, 71, pp. 567-577; Lian, J.B., McKee, M.D., Todd, A.M., Induction of bone-related proteins, osteocalcin and osteopontin, and their matrix ultrastructural localization with development of chondrocyte hypertrophy in vitro (1993) J Cell Biochem, 52, pp. 206-219; Wei, C.L., Miura, T., Robson, P., Transcriptome profiling of human and murine ESCs identifies divergent paths required to maintain the stem cell state (2005) Stem Cells, 23, pp. 166-185; Heng, B.C., Cao, T., Stanton, L.W., Strategies for directing the differentiation of stem cells into the osteogenic lineage in vitro (2004) J Bone Miner Res, 19, pp. 1379-1394
Keywords: alkaline phosphatase; Apatite; article; bone development; bone growth; bone matrix; bone mineralization; Bone tissue engineering; Calcium; calcium phosphate; Calcium phosphates; Cell Culture Techniques; cell differentiation; cell separation; Collagen; collagen synthesis; culture technique; cytology; dexamethasone; embryo; embryo culture; Embryoid bodies; embryonic stem cell; extracellular matrix; human; human cell; human embryo; Human embryonic stem cells; Humans; hydroxyapatite; in vitro study; Matrix characterization; metabolism; methodology; ossification; osteocalcin; Osteogenesis; Osteogenic cell frequency; phosphorus; spheroid cell; Tissue engineering; totipotent stem cell; Totipotent Stem Cells

Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers - Rodrigues, S.N.; Gonçalves, I.C.; Martins, M.C.L.; Barbosa, M.A.; Ratner, B.D. (BiomaterialsBiomaterials, 2006)
The effect of surface wettability on fibrinogen adsorption, platelet adhesion and platelet activation was investigated using self-assembled monolayers (SAMs) containing different ratios of longer chain methyl- and shorter chain hydroxyl-terminated alkanethiols (C15CH3 vs. C11OH) on gold. Protein adsorption studies were performed using radiolabeled human fibrinogen (HFG). Platelet adhesion and activation studies with and without pre-adsorbed fibrinogen, albumin and plasma were assessed using scanning electron microscopy (SEM) and a glutaraldehyde-induced fluorescence technique (GIFT). Results demonstrated a linear decrease of HFG adsorption with the increase of OH groups on the monolayer (increase of the hydrophilicity). Platelet adhesion and activation also decrease with increase of hydrophilicity of surface. Concerning SAMs pre-immersed in proteins, fibrinogen adsorption was related with high platelet adhesion and activation. The passivant effect of albumin on platelet adhesion and activation was only demonstrated on SAMs contained C11OH. When all the blood proteins are present (plasma) platelet adhesion was almost absent on SAMs with 65% and 100% C11OH. This could be explained by the higher albumin affinity of the SAMs with 65% C11OH and the lower total protein adsorption associated with SAMs with 100% C11OH. © 2006 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 70Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2006.06.010PubMed ID: 16842847Language of Original Document: EnglishCorrespondence Address: Martins, M.C.L.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cmartins@ibmc.up.ptChemicals/CAS: fibrinogen, 9001-32-5; glutaraldehyde, 111-30-8, 37245-61-7; gold, 7440-57-5; thiol derivative, 13940-21-1; Alkanes; Biocompatible Materials; Fibrinogen, 9001-32-5; hydroxide ion, 14280-30-9; Hydroxides; Sulfhydryl CompoundsReferences: Savage, B., Ruggeri, Z.M., Selective recognition of adhesive sites in surface-bound fibrinogen by glycoprotein-iib-iiia on nonactivated platelets (1991) J Biol Chem, 266 (17), pp. 11227-11233;Tsai, W.B., Grunkemeier, J.M., McFarland, C.D., Horbett, T.A., Platelet adhesion to polystyrene-based surfaces preadsorbed with plasmas selectively depleted in fibrinogen, fibronectin, vitronectin, or von Willebrand's factor (2002) J Biomed Mater Res, 60 (3), pp. 348-359; Kottkemarchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., Effect of albumin coating on the invitro blood compatibility of dacron arterial prostheses (1989) Biomaterials, 10 (3), pp. 147-155; Margel, S., Vogler, E.A., Firment, L., Watt, T., Haynie, S., Sogah, D.Y., Peptide, protein, and cellular interactions with self-assembled monolayer model surfaces (1993) J Biomed Mater Res, 27 (12), pp. 1463-1476; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalized, self-assembled monolayers of alkanethiolates on gold (1997) Langmuir, 13 (13), pp. 3404-3413; Gonçalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Protein adsorption on 18-alkyl chains immobilized on hydroxyl-terminated self-assembled monolayers (2005) Biomaterials, 26 (18), pp. 3891-3899; Peters, T., (1996) All about albumin: biochemistry, genetics and medical applications, , Academic Press Inc., San Diego, CA; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methylterminated alkanethiols self-assembled monolavers (2003) J Biomed Mater Res A, 67 A (1), pp. 158-171; Frank, R.D., Dresbach, H., Thelen, H., Sieberth, H.G., Glutaraldehyde induced fluorescence technique (GIFT): a new method for the imaging of platelet adhesion on biomaterials (2000) J Biomed Mater Res, 52 (2), pp. 374-381; Feng, L., Andrade, J.D., Protein adsorption on low-temperature isotropic carbon. 3. Isotherms, competitivity, desorption and exchange of human albumin and fibrinogen (1994) Biomaterials, 15 (5), pp. 323-333; (1993) Iodine-125. A guide to radioiodination techniques, , Amersham Life Science, Little Chalfort; Porter, M.D., Bright, T.B., Allara, D.L., Chidsey, C.E.D., Spontaneously organized molecular assemblies. 4. Structural characterization of normal-alkyl thiol monolayers on gold by optical ellipsometry, infrared-spectroscopy, and electrochemistry (1987) J Am Chem Soc, 109 (12), pp. 3559-3568; Sigal, G.B., Mrksich, M., Whitesides, G.M., Effect of surface wettability on the adsorption of proteins and detergents (1998) J Am Chem Soc, 120 (14), pp. 3464-3473; Goodman, S.L., Sheep, pig, and human platelet-material interactions with model cardiovascular biomaterials (1999) J Biomed Mater Res, 45 (3), pp. 240-250; Slack, S.M., Horbett, T.A., Changes in fibrinogen adsorbed to segmented polyurethanes and hydroxyethylmethacrylate-ethylmethacrylate copolymers (1992) J Biomed Mater Res, 26 (12), pp. 1633-1649; Andrade, J.D., Hlady, V., Protein adsorption and materials biocompatibility-a tutorial review and suggested hypotheses (1986) Adv Polym Sci, 79, pp. 1-63; Roach, P., Farrar, D., Perry, C.C., Interpretation of protein adsorption: surface-induced conformational changes (2005) J Am Chem Soc, 127 (22), pp. 8168-8173; Silin, V., Weetall, H., Vanderah, D.J., SPR studies of the nonspecific adsorption kinetics of human IgG and BSA on gold surfaces modified by self-assembled monolayers (SAMs) (1997) J Colloid Interf Sci, 185 (1), pp. 94-103; Lin, Y., Wang, J., Wan, L.J., Fang, X.H., Study of fibrinogen adsorption on self-assembled monolayers on Au (1 1 1) by atomic force microscopy (2005) Ultramicroscopy, 105 (1-4), pp. 129-136; Norde, W., Favier, J.P., Structure of adsorbed and desorbed proteins (1992) Colloid Surf, 64 (1), pp. 87-93; Alfonsi-Hourdin, S., Longchamp, S., Gallet, O., Nigretto, J.M., Electrochemical processing of fibrinogen modified-graphite surfaces: effect on plasmin generation from adsorbed plasminogen (2006) Biomaterials, 27 (1), pp. 52-60; Tsai, W.B., Shi, Q., Grunkemeier, J.M., McFarland, C., Horbett, T.A., Platelet adhesion to radiofrequency glow-discharge-deposited fluorocarbon polymers preadsorbed with selectively depleted plasmas show the primary role of fibrinogen (2004) J Biomater Sci-Polym E, 15 (7), pp. 817-840; Stryer, L., (1998) Biochemistry. 4th ed., , WH Freeman, New York; Doolittle, R.F., Watt, K.W.K., Cottrell, B.A., Strong, D.D., Riley, M., Amino-acid sequence of the alpha-chain of human-fibrinogen (1979) Nature, 280 (5722), pp. 464-468; Kloczewiak, M., Timmons, S., Lukas, T.J., Hawiger, J., Platelet receptor recognition site on human-fibrinogen-synthesis and structure-function relationship of peptides corresponding to the carboxy-terminal segment of the gamma-chain (1984) Biochemistry, 23 (8), pp. 1767-1774; Tsai, W.B., Grunkemeier, J.M., Horbett, T.A., Variations in the ability of adsorbed fibrinogen to mediate platelet adhesion to polystyrene-based materials: a multivariate statistical analysis of antibody binding to the platelet binding sites of fibrinogen (2003) J Biomed Mater Res A, 67 A (4), pp. 1255-1268; Salsmann, A., Schaffner-Reckinger, E., Kabile, F., Plancon, S., Kieffer, N., A new functional role of the fibrinogen RGD motif as the molecular switch that selectively triggers integrin alpha IIb beta 3-dependent RhoA activation during cell spreading (2005) J Biol Chem, 280 (39), pp. 33610-33619; Lin, J.C., Chuang, W.H., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionality (2000) J Biomed Mater Res, 51 (3), pp. 413-423; Tanaka, M., Motomura, T., Kawada, M., Anzai, T., Kasori, Y., Shiroya, T., Blood compatible aspects of poly(2-methoxyethylacrylate) (PMEA)-relationship between protein adsorption and platelet adhesion on PMEA surface (2000) Biomaterials, 21 (14), pp. 1471-1481; Barbucci, R., Lamponi, S., Magnani, A., Fibrinogen conformation and platelet reactivity in relation to material-blood interaction: effect of stress hormones (2003) Biomacromolecules, 4 (6), pp. 1506-1513; Hylton, D.M., Shalaby, S.W., Latour, R.A., Direct correlation between adsorption-induced changes in protein structure and platelet adhesion (2005) J Biomed Mater Res A, 73 A (3), pp. 349-358; Brash, J.L., Tenhove, P., Protein adsorption studies on standard polymeric materials (1993) J Biomat Sci-Polym E, 4 (6), pp. 591-599
Keywords: Adsorption; Albumin; alkane derivative; Alkanes; article; binding affinity; Biocompatible Materials; Blood Platelets; Cells, Cultured; Chemical reactions; controlled study; Crystallization; fibrinogen; Fluorescence; fluorescence analysis; glutaraldehyde; gold; human; human cell; Humans; hydrophilicity; Hydroxides; hydroxyl group; materials testing; methyl group; Methylation; monolayer culture; Monolayers; normal human; Organic compounds; plasma; Plasma protein; Platelet activation; Platelet adhesion; Platelet Adhesiveness; priority journal; Protein adsorption; protein binding; Proteins; Radiolabeled human fibrinogen (HFG); Scanning electron microscopy; Self assembled; SEM; Sulfhydryl Compounds; surface property; thiol derivative; thrombocyte adhesion; wettability

Histological and scanning electron microscopy analyses of bone/implant interface using the novel Bonelike® synthetic bone graft - Gutierres, M.; Hussain, N.S.; Lopes, M.A.; Alfonso, A.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Journal of Orthopaedic ResearchJ. Orthop. Res., 2006)
Synthetic bone grafts provide an alternative to autografts and allografts. Bonelike® is a patented synthetic bone graft that mimics the mineral composition of bone. The aim of the present work was to assess the biological behavior of Bonelike® graft in humans, before using the material in orthopedic applications of bone regeneration, for example, in opening wedge high tibial osteotomies for medial knee osteoarthritis. Bonelike® granules were implanted in cortical bone of 11 patients undergoing osteotomies, and new bone formation, osteoconductive properties, and resorption characteristics of the granules were analyzed. The granules ranged from 500 to 1000 μm and were implanted in the lateral aspect of the tibia. The patients' mean age was 59 years (range 48 to 70 years); there were eight women and three men, all suffering from medial compartment osteoarthritis of the knee. At surgery, a 1 × 1 × 1-cm cortical defect was created 3 cm distal to the entry point of the screws, in line with the long axis of tibia. The implanted Bonelike® graft sample was extracted for analysis during removal of the metallic prosthesis after implantation times of 6, 9, and 12 months. Radiological follow-up, scanning electron microscopy, histological analysis, and histomorphometric measurements were conducted on the retrieved samples to assess bone regeneration in the defect area. Osteoconductive capacity was demonstrated by extensive mature bone formation around the implanted granules and high levels of percentage bone-to-graft contact (from 67-84%). Bonelike® acted as an excellent bioactive scaffold, allowing the migration, proliferation, and differentiation of bone cells on its surface, and therefore regeneration of the defects was achieved in a rapid, controlled manner. Our results suggest that Bonelike® graft is an excellent candidate for orthopedic applications where rapid new bone formation is a fundamental requirement. © 2006 Orthopaedic Research Society. Published by Wiley Periodicals, Inc.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JOREDdoi: 10.1002/jor.20117Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; DEMM, Faculty of Engg., University of Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Bone SubstitutesTradenames: Bonelike; JSM 630IF, JeolManufacturers: JeolReferences: Peter, P., Heinrich, R., Meinrad, P., (2003) Orthopaedic Issues in Osteoporosis, , YH An, editor. Boca Raton, FL: CRC Press;Hench, L.L., Wilson, J., (1999) An Introduction to Bioceramics, , Singapore: World Scientific Publishing Co. Pvt. Ltd; Corpe, R.S., Steflik, D.E., Whitehead, R.Y., Correlative experimental animal and human clinical retrieval evaluations (2000) Crit Rev Biomed Eng, 28, pp. 395-398; Kitsugi, T., Yamamuro, T., Nakamura, T., Four calcium phosphate ceramics as bone substitutes for non-weight bearing (1993) Biomaterials, 14, pp. 216-224; Koshino, T., Murase, T., Takagi, T., New bone formation around porous hydroxyapatite wedge implanted in opening wedge high tibial osteotomy in patients with osteoarthritis (2001) Biomaterials, 22, pp. 1579-1582; LeGeros, R.Z., (1991) Calcium Phosphates in Oral Biology and Medicine, pp. 4-45. , Meyers HM, editor. New York: Karger; Macdonald, D.E., Betts, F., Stranick, M., Physicochemical study of plasma-sprayed hydroxyapatite-coated implants in humans (2001) J Biomed Mater Res, 54, pp. 480-490; Oonishi, H., Yamamoto, M., Ishimaru, H., The effect of hydroxyapatite coating on bone growth into porous titanium alloy implants (1989) J Bone Surg Br, 71, pp. 213-216; Thomas, K.A., Hydroxyapatite coatings (1994) Orthopedics, 17, pp. 267-278; Doron, H., Amy, L.L., Bone graft substitutes (2003) Oper Tech Plastic Reconstruct Surg, 9, pp. 151-160; Write, S., The bone-graft market in Europe. Commentary extracted from a report entitled "Emerging technologies in orthopedics I.: Bone graft substitutes, bone growth stimulators and bone growth factors" (1999), pp. 591-595. , London: Datamonitor plcBotelho, C.M., Brooks, R.A., Best, S.M., Biological and physical-chemical characterization of phase pure HA and si-substituted hydroxyapatite by different microscopy techniques (2004) Key Eng Mater, 254, p. 845; Costa, M.A., Gutierres, M., Almeida, L., In vitro mineralisation of human bone marrow cells cultured on bonelike® (2004) Key Eng Mater, 254-256, pp. 821-824; Gutierres, M., Hussain, N.S., Afonso, A., Biological behaviour of bonelike® graft Implanted in the tibia of humans (2005) Key Eng Mater, 284-286, pp. 1041-1044; Lopes, M.A., Santos, J.D., Monteiro, F.J., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: Fracture toughness and hardness dependence on microstructural characteristics (1999) Biomaterials, 20, pp. 2085-2090; Lopes, M.A., Silva, R.F., Monteiro, F.J., Microstructural dependence of Young's and shear moduli of P 2O 5 glass reinforced hydroxyapatite for biomedical applications (2000) Biomaterials, 21, pp. 749-754; Lopes, M.A., Knowles, J.C., Santos, J.D., Structural insights of glass-reinforced hydroxyapatite composites by Rietveld refinement (2000) Biomaterials, 21, pp. 1905-1910; Santos, J.D., Knowles, J.C., Reis, R.L., Microstructural characterization of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Felson, D.T., Naimark, A., Anderson, J., The prevalence of knee osteoarthritis in the elderly: The Framingham Study (1987) Arthritis Rheum, 30, pp. 914-918; Guincamp, C., Pap, T., Schedel, J., Gene therapy in osteoarthritis (2000) Joint Bone Spine, 67, pp. 570-571; Marc, F., Serge, P., Mario, M.L.C., Assessment of the test-retest reliability and construct validity of a modified lequesne index in knee osteoarthritis (2003) Joint Bone Spine, 70, pp. 520-525; Pendleton, A., Arden, N., Dougados, M., EULAR recommendations for the management of knee osteoarthritis: Report of a task force of the Standing Committee for International Clinical Studies Including Therapeutic Trials (ESCISIT) (2000) Ann Rheum Dis, 59, pp. 936-944; Santos, J.D., Hastings, G.W., Knowles, J.C., Sintered hydroxyapatite compositions and method for the preparation thereof (1999) Eur. Pat. WO 0068164; Coventry, M.B., Osteotomy of the upper portion of the tibia for degenerative arthritis of the knee: A preliminary report (1965) J Bone Joint Surg Am, 47, p. 984; Hing, K.A., Assessment of porous hydroxyapatite for bone replacement (1996), (Ph D Thesis). London: University of LondonLopes, M.A., Knowles, J.C., Santos, J.D., Direct and indirect effects of P 2O 5-glass reinforced-hydroxyapatite composites and growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Knowles, J.C., Santos, J.D., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Ross, M.H., Romrell, L.J., Kaye, G.I., (1995) Histology - A Text and Atlas, , 3rd ed. Baltimore, MD: Williams & Wilkins; Lobato, J.V., Hussain, N.S., Botelho, C.M., Assessment of the potential of Bonelike® graft for bone regeneration by using an animal model (2005) Key Eng Mater, 284-286, pp. 877-880; Duarte, F., Lopes, M.A., Santos, J.D., Bonelike® composites for the regeneration of bone lesions (2004) Mater Sci Forum, 455-456, pp. 370-373; Laurencin, C.T., (2003) Bone Graft Substitutes, , West Conshohocken, PA: ASTM International
Keywords: adult; aged; article; Bone; Bone and Bones; bone cell; bone conduction; bone development; Bone graft; bone prosthesis; bone radiography; Bone Regeneration; bone screw; Bone Substitutes; bone transplantation; Bonelike®; cell differentiation; cell migration; cell proliferation; Clinical applications; clinical article; controlled study; Female; follow up; Histological analysis; histology; human; Humans; knee osteoarthritis; male; Microscopy, Electron, Scanning; Middle Aged; morphometrics; orthopedics; ossification; Osteoconduction; Osteogenesis; osteolysis; Pathology; priority journal; Prostheses and Implants; prostheses and orthoses; prosthesis material; Scanning electron microscopy; surgical technique; Synthetic bone graft; tibia osteotomy; ultrastructure

Human osteoblast response to silicon-substituted hydroxyapatite - Botelho, C.M.; Brooks, R.A.; Best, S.M.; Lopes, M.A.; Santos, J.D.; Rushton, N.; Bonfield, W. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
Human osteoblasts were cultured on hydroxyapatite (HA), 0.8 wt % silicon substituted hydroxyapatite (Si-HA) and 1.5 wt % Si-HA discs. The influence of these substrates on cell behaviour in vitro was assessed by measuring total protein in the cell lysate and the production of several phenotypic markers: collagen type I (COL 1), alkaline phosphatase (ALP), osteocalcin (OC), and the formation of bone mineral. After 7 days, β-glycerophosphate and physiological levels of hydrocortisone were added to the culture medium to stimulate cell differentiation and mineral production. There was a significantly higher production of ALP on 1.5 wt % Si-HA at day 7 following which, the addition of hydrocortisone promoted the differentiation of cells on the other two substrates. Hydrocortisone addition also decreased the production of OC. During the period, when hydrocortisone was present, no significant difference in behavior was seen between cells on Si-HA and HA; however, following removal of hydrocortisone, cells responded to 0.8 wt % Si-HA with a significant increase in protein production. Using fluorescence microscopy, nodular structures labeled with tetracycline were observed on the surface of all substrates after 21 days. These structures were deposited on areas of high cell density but were not related to the presence or level of silicon in the substrate. These results indicate that human osteoblasts are affected by the presence of silicon in the HA substrate and that the timing of these effects may be dependent upon the level of silicon substitution. © 2006 Wiley Periodicals, Inc.
Cited By (since 1996): 33Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30806PubMed ID: 16871624Language of Original Document: EnglishCorrespondence Address: Brooks, R.A.; Orthopaedic Research Unit, Box 180, Addenbrooke's Hospital, Hills Road, Cambridge CB2 3QZ, United Kingdom; email: rb10003@cam.ac.ukChemicals/CAS: alkaline phosphatase, 9001-78-9; glycerol 2 phosphate, 17181-54-3; hydrocortisone, 50-23-7; hydroxyapatite, 1306-06-5, 51198-94-8; osteocalcin, 136461-80-8; silicon, 7440-21-3; tetracycline, 23843-90-5, 60-54-8, 64-75-5; Collagen Type I; Durapatite, 1306-06-5; ectonucleotide pyrophosphatase phosphodiesterase 1, EC 3.1.4.1; Minerals; Osteocalcin, 104982-03-8; Phosphoric Diester Hydrolases, EC 3.1.4.-; Pyrophosphatases, EC 3.6.1.-; Silicon, 7440-21-3References: Hench, L., Splinter, R., Allan, W., Greenlee, T., Bonding mechanism at the interface of ceramic prosthetic materials (1972) J Biomed Mater Res, 2, pp. 117-141;Ducheyne, P., Hench, L., Kagan, A., Martens, M., Burssens, A., Mulier, J., The effect of hydroxyapatite impregnation on skeletal bonding of porous coated implants (1980) J Biomed Mater Res, 14, pp. 225-237; Jarcho, M., Calcium phosphates ceramics as hard tissue prosthetics (1981) Clin Orthop, 157, pp. 259-278; Nakamura, T., Yamamuro, T., Higashi, S., Kokubo, T., Ito, S., A new glass-ceramic for bone replacement: Evaluation of its bonding to bone tissue (1985) J Biomed Mater Res, 19, pp. 685-698; Ducheyne, P., Bianci, P., Radin, S., Schepers, E., Bioactive materials: Mechanism and bioengineering considerations (1993) Bone-Bioactive Biomaterials, pp. 1-12. , Ducheyne P, Kokubo T, van Blitterswijik C, editors. Leiderdorp, The Netherlands: Reed Healthcare Communications; Patel, N., Best, S., Gibson, I.R., Hing, K., Damien, K., Bonfield, W., A comparative study on the in vivo behaviour of hydroxyapatite and silicon substituted hydroxyapatite granules (2002) J Mater Sci Mater Med, 13, pp. 1199-1206; Jha, L., Best, S., Santos, J., Gibson, I., Bonfield, W., Silicon-substituted apatites and process for the preparation thereof Worldwide Patent,PCT/GB97/02325 and US Patent0.9/147773, 1999Gibson, I.R., Best, S.M., Bonfield, W., Chemical characterization of silicon-substituted hydroxyapatite (1999) J Biomed Mater Res, 44, pp. 422-428; Schwarz, K., Significance and functions of silicon in warm-blooded animals (1977) Proceedings of the 40th Nobel Symposium, , Bendz G, Lindquist I, editors. Biochemistry of Silicon and Related Problems. New York: Plenum; Lidingö, Sweden, August 23-26; Baxter, J., Rousseau, G., Benson, M., Garcea, R.L., Ito, J., Tomkins, G., Role of DNA and specific cytoplasmic receptors in glucocorticoid action (1972) Proc Natl Acad Sci USA, 69, p. 1892; Darley, W., Volcani, B., Role of silicon in diatom metabolism. A silicon requirement for deoxyribonucleic acid synthesis in diatom Cylindrotheca-fusiformis reimann and lewin (1969) Exp Cell Res, 58 (2-3), p. 334; Finkelstein, D., Butow, R., DNA-binding proteins in yeast. Effect of growth phase and mitochondrial-function (1976) Arch Biochem Biophys, 174, pp. 52-65; Volcani, B.E., Role of silicon in diatom metabolism and silicification (1977) Proceedings of the 40th Nobel Symposium, , Bendz G, Lindquist I, editors. Biochemistry of Silicon and Related Problems. New York: Plenum; Lidingo, Sweden, August 23-26; Werner, D., Regulation of metabolism by silicate in diatoms (1977) Proceedings of the 40th Nobel Symposium, , Bendz G, Lindquist I, editors. Biochemistry of Silicon and Related Problems. New York: Plenum; Lidingö, Sweden, August 23-26; Carlisle, E., Essentiality and function of silicon (1977) Proceedings of the 40th Nobel Symposium, , Bendz C, Lindquist I, editors. Biochemistry of Silicon and Related Problems New York: Plenum; Lidingo, Sweden, August 23-26; Carlisle, E., (1986) Silicon Biochemistry, , New York: Wiley; Schwarz, K., Milne, D., Growth-promoting effects of silicon in rats (1972) Nature, 239, p. 333; Seaborn, C., Nielsen, F., Dietary silicon affects acid and alkaline phosphatase and 45calcium uptake in bone of rats (1994) J Trace Elem Exp Med, 7, pp. 11-18; Reffitt, D., Ogston, N., Jugdaohsingh, R., Cheung, H., Evans, B., Thompson, R., Powell, J.J., Hampson, G.N., Orthosilicic acid stimulates collagen type I synthesis and osteoblastic differentiation in human osteoblast-like cells in vitro (2003) Bone, 32, p. 127; Shi, S., Kirk, M., Kahan, A., The role of type 1 collagen in the regulation of the osteoblast phenotype (1996) J Bone Miner Res, 11, pp. 1139-1145; Hildebrand, M., Higgins, D., Busser, K., Benjamin, E., Silicon-responsive cDNA clones isolated from the marine diatom Cylindrotheca fusiformis (1993) Gene, 132, pp. 213-218; Voronkov, M.G., Skorobogatova, V.J., Vugmeíster, E.K., Makarskii, V.V., Silicon in nuclei acids (1975) Dokl Biochem, 222, p. 29; Hench, L., Orcel, G., Physical-chemical and biochemical factors in silica sol-gel (1986) J Non-Cryst Solids, 82, pp. 1-10; Keting, P., Oursler, M., Wiegand, K., Bonde, S., Spelsberg, T., Riggs, L., Zeolite a increases proliferation, differentiation, and transforming growth factor production in normal adult human osteoblast-like cells in vitro (1992) J Bone Miner Res, 7, p. 1281; Gibson, I.R., Huang, J., Best, S.M., Bonfield, W., Enhanced in vitro cell activity and surface apatite layer formation on novel silicon-substituted hydroxyapatites (1999) Bioceramics, 12, pp. 191-194. , Ohgushi H, Hastings GW, Yoshikawa T, editors. Nara, Japan: World Scientific Publishing Company; Botelho, C.M., Brooks, R., Lopes, M.A., Santos, J.D., Best, S.M., Bonfield, W., Biological and physical-chemical characterization of phase pure HA and Si-substituted hydroxyapatite by different microscopy techniques (2004) Key Eng Mater, 254-256, pp. 845-848; Botelho, C.M., Stokes, D., Brooks, K., Best, S., Lopes, M., Santos, J.D., Effect of human serum proteins on the surface of pure HA and Si-substituted HA: AFM and ESEM studies (2003) Mater Sci Forum, 455-456, pp. 378-382; Sakobar, A., Millet, P., Myer, B., Rushton, N., A rapid, quantitative assay for measuring alkaline phosphatase activity in osteoblastic cells in vitro (1994) Bone Miner, 27, pp. 57-67; Botelho, C.M., Lopes, M.A., Gibson, I.R., Best, S.M., Santos, J.D., Structural analysis of Si-substituted hydroxyapatite: Zeta potential and X-ray photoelectron spectroscopy (XPS) (2002) J Mater Sci Mater Med, pp. 1123-1127; Lian, J., Stein, G., Aubin, J., Bone formation: Maturation and functional activities of osteoblast lineage cells (2003) Primer on the Metabolic Bone Diseases and Disorders of Mineral Metabolism, pp. 13-28. , Favus M, editor. Philadelphia: Lippincott; Boskey, A., Biomineralization: Conflicts, challenges and opportunities (1998) J Cell BiochemSuppl, 30-31, pp. 83-91; Jaiswal, N., Haynesworth, S., Caplan, A., Bruder, S., Osteogenic differentiation of purified culture-expanded human mesenchymal stem cells in vitro (1997) J Cell Biochem, 64, pp. 295-312; Baylink, D., Glucocorticoid-induced osteoporosis (1983) N Engl J Med, 309, pp. 306-308; Ireland, D., Bord, S., Beavan, S., Compston, J., Hydrocortisone increases the rate of differentiation of culture human osteoblasts (2004) J Cell Biochem, 91, pp. 594-601; Lian, J., Stein, G., Stein, J., Wijnen, A., Osteocalcin gene promoter: Unlocking the secrets for regulation of osteoblasts growth and differentiation (1998) J Cell BiochemSuppl, 30-31, pp. 62-72; Canalis, E., Mechanisms of glucocorticoid action in bone: Implications to glucocorticoid-induced osteoporosis (1995) J Clin Endocrinol Metab, 10, pp. 3441-3447; Delany, A., Gabbitas, B., Canalis, E., Cortisol down-regulates osteoblast α 1 (I) procollagen mRNA by transcriptional and post-transcriptional mechanisms (1995) J Cell Biochem, 57, pp. 488-494; Bellows, C., Aubin, J., Heersche, J., Physiological concentrations of glucocorticoids stimulate formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Cheng, S., Zhang, S., Mohan, S., Eecanda, E., Eausto, A., Hunt, A., Canalis, E., Avioli, L.V., Regulation of insulin-like growth factors I and II and their binding proteins in human bone marrow stromal cells by dexamethasone (1998) J Cell Biochem, 71, pp. 449-458; Boskey, A., Paschalis, E., Matrix proteins and biomineralization (1999) Bone Engineering, pp. 44-62. , Davie J, editor. Toronto: Em Squared; Shiga, M., Kapila, Y., Zhang, Q., Hayami, T., Kapila, S., Ascorbic acid induces collagenase-1 in human periondontal ligament cells but not in MC3T3-E1 osteoblast-like cells: Potential association between collagenase expression and changes in alkaline phosphatase phenotype (2003) J Bone Miner Res, 18, pp. 67-77; Franceschi, R., Iyer, B., Cui, Y., Effects of ascorbic acid on collagen matrix formation ans osteoblast differentiation of murine MC3T3-E1 cells (1994) J Bone Miner Res, 9, pp. 843-854; Franceschi, R., Iyer, B., Relationship between collagen synthesis and expression of the osteoblast phenotype in MC3T3-E1 cells (1992) J Bone Miner Res, 7, pp. 235-246; Aronow, M., Gerstenfeld, E., Owen, T., Tassinari, M., Stein, G., Lian, J., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J Cell Physiol, 143, pp. 213-221; Chien, H., Lin, W., Cho, M., Interkukin-1b-induced release of matrix proteins into culture media causes inhibition of mineralization of nodules formed by periodontal ligament cells in vitro (1999) Calcif Tissue Int, 64, pp. 402-413; Botelho, C.M., Brooks, R.A., Kawai, T., Ogata, S., Ohtsuki, C., Lopes, M.A., Best, S.M., Bonfield, W., In vitro analysis of proteins adhesion to phase pure hydroxyapatite and silicon-substituted hydroxyapatite (2005) Key Eng Mater, 17, pp. 461-464; Kaji, T., Kawatani, R., Takata, M., Hoshino, T., Miyahara, T., Kozuka, H., Koizumi, F., The effects of cadmium, copper or zinc on formation of embryonic chick bone in tissue culture (1988) Toxicology, 50, pp. 303-316
Keywords: alkaline phosphatase; article; Biomarkers; bone mineral; cell activity; Cell culture; cell density; cell differentiation; cell function; cell lysate; cell marker; cell protein; Cells; Cells, Cultured; collagen type 1; Collagen type I; culture medium; Durapatite; Fluorescence microscopy; glycerol 2 phosphate; hormone determination; human; human cell; Human osteoblasts; Humans; Hydrocortisone; hydroxyapatite; in vitro study; Minerals; Nodular mineral formation; osteoblast; Osteoblasts; osteocalcin; Osteocalcin (OC); phenotype; Phosphoric Diester Hydrolases; protein analysis; protein synthesis; Pyrophosphatases; Silicon; Substitution reactions; Substrates; Tetracycline; β-glycerophosphate

Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery - Gonçalves, H.; Rocha, A.P.; Ayres-de-Campos, D.; Bernardes, J. (Medical and Biological Engineering and ComputingMed. Biol. Eng. Comput., 2006)
Linear and nonlinear fetal heart rate (FHR) indices, namely mean FHR, interval index (II), very low, low and high frequencies, approximate (ApEn) and sample entropy (SampEn), were computed, immediately before delivery, in the initial and final FHR tracing segments, from 48 normal, 10 mildly acidemic and 10 moderate-to-severely acidemic fetuses. Progression of labor was associated with a significant increase in linear frequency domain indices whereas nonlinear indices were significantly decreased. Moderate-to-severe fetal acidemia was associated with a significant decrease in nonlinear indices. The best discrimination between moderate-to-severe acidemic fetuses and the remaining cases was obtained combining II and ApEn(2,0.15), with a specificity of 71% and a sensitivity of 80%. These findings support the hypothesis of increased autonomic nervous system activity in the final minutes of labor and of decreased central nervous system activity, both in the final minutes of labor and in moderate-to-severe acidemic fetuses. © International Federation for Medical and Biological Engineering 2006.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: MBECDdoi: 10.1007/s11517-006-0105-6PubMed ID: 16988896Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Departamento de Matemática Aplicada, Faculdade de Ciências, Universidade do Porto, Rua do Campo Alegre - 687, 4169-007 Porto, Portugal; email: hernani.goncalves@fc.up.ptChemicals/CAS: AcidsReferences: ACOG technical bulletin. Fetal heart rate patterns: Monitoring, interpretation, and management (1995) Int J Gynecol Obstet, 51, pp. 65-74. , ACOG;Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in expert's classification of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynecol, 106, pp. 1307-1310; Ayres-de-Campos, D., Bernardes, J., Garrido, A., de Sá, J.M., Pereira-Leite, L., Sisporto 2.0: A program for automated analysis of cardiotocograms (2000) J Mat Fet Med, 9, pp. 311-318; Bernardes, J., de Campos, D.A., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int J Gynecol Obstet, 62, pp. 141-147; Bernardes, J., Costa-Pereira, A., de Campos, D.A., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57 (1), pp. 33-37; Bernardes, J., Moura, C., de Sá, J.P.M., Pereira-Leite, L., The porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Boog, G., Analyse informatisTe du rythme cardiaque foetal au cours de la grossesse et de l'accouchement (2004) EncyclopTdie MTdico-Chirurgicale, 148, pp. 1-10. , (5-049-D-23); Carter, M.C., Signal processing and display - Cardiotocographs (1993) Br J Obstet Gynaecol, 100 (9), pp. 21-23; Chaffin, D.G., Barnard, J.M., Phernetton, T., Reed, K.L., Decreased approximate entropy of heart rate variability in the hypoxic ovine fetus (1998) J Matern Fetal Invest, 8, pp. 23-26; Chung, D.Y., Sim, Y.B., Park, K.T., Yi, S.H., Shin, J.C., Kim, S.P., Spectral analysis of fetal heart rate variability as a predictor of intrapartum fetal distress (2001) Int J Gynecol Obstet, 73, pp. 109-116; Colenbrander, G.J., van Geijn, H.P., Goovaerts, H.G., Acquisition of fetal heart rate signals (1994) A Critical Appraisal of Fetal Surveillance, pp. 203-210. , In: Geijn HPV, Copray FJA (eds) Elsevier Science, Amsterdam; Dawes, G.S., Moulden, M., Sheil, O., Redman, C.W.G., Approximate entropy, a statistic of regularity, applied to fetal heart rate data before and during labour (1992) Obstet Gynecol, 80 (5), pp. 763-768; Dudewicz, E., Mishra, S., (1988) Modern Mathematical Statistics, , Wiley, New York; Echeverrfa, J.C., Hayes-Gill, B.R., Crowe, J.A., Woolfson, M.S., Croaker, G.D.H., Detrended fluctuation analysis: A suitable method for studying fetal heart rate variability? (1990) Int J Biomed Comput, 25, pp. 287-294; Felgueiras, C., de Sá, J.P.M., Bernardes, J., Gama, S., Fractal characterisation of fetal heart rate sequences (1998) Biomed Eng, 36 (2), pp. 197-201; Fusheng, Y., Bo, H., Qingyu, T., Approximate entropy and its application in biosignal analysis (1998) Nonlinear Biomedical Signal Processing. Dynamical Analysis and Modelling, 2, pp. 72-91. , In: Akay M (ed) IEEE Press, New York; Gonçalves, H., Rocha, A.P., de Campos, D.A., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters (2006) Physiol Meas, 27, pp. 307-319; Gough, N.A., Fractal analysis of foetal heart rate variability (1993) Physiol Meas, 14 (3), pp. 309-315; Hayes, M., (1996) Statistical Digital Signal Processing and Modelling, , Wiley, New York; Hewlett-Packard, (1993) Hewlett-Packard Series 50 Service Manual, , M1351A and 1353A. Germany; King, T., Parer, J., The physiology of fetal heart rate patterns and perinatal asphyxia (2000) J Perinat Neonat Nurs, 14 (3), pp. 19-39; Li, X., Tang, D., Zhou, S., Zhou, G., Wang, C., Zhuang, Y., Wu, G., Shen, L., Redistribution of power spectrum of heart rate variability during acute umbilical artery embolism and hypoxemia in late-gestation fetal sheep (2004) Eur J Obstet Gynecol Reprod Biol, 114, pp. 137-143; Magenes, G., Signorini, M.G., Arduini, D., Classification of cardiotocographic records by neural networks (2000) Proceedings of the IEEE-INNS-ENNS International Joint Conference on Neural Networks,, 3, pp. 637-641. , In: IJCNN 2000; Martin, J.C.B., Electronic fetal monitoring: A brief summary of its development, problems and prospects (1998) Eur J Obstet Gynecol Reprod Biol, 78, pp. 133-140; Martinez, W.L., Martinez, A.R., (2002) Computational Statistics Handbook With MATLAB, , CRC Press, Boca Raton; Oppenheimer, L.W., Lewinsky, R.M., Power spectral analysis of fetal heart rate (1994) Baillieres Clin Obstet Gynaecol, 8 (3), pp. 643-661; Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc Natl Acad Sci USA, 88, pp. 2297-2301; Pincus, S., Approximate entropy (apen) as a complexity measure (1995) Chaos, 5 (1), pp. 110-117; Pincus, S., Viscarello, R., Approximate entropy: A regularity measure for fetal heart rate analysis (1992) Obstet Gynecol, 79 (2), pp. 249-255; di Renzo, G.C., Montani, M., Fioriti, V., Clerici, G., Branconi, F., Pardini, A., Indraccolo, R., Cosmi, E.V., Fractal analysis: A new method for evaluating fetal heart rate variability (1996) J Perinat Med, 24 (3), pp. 261-269; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am J Physiol Heart Circ Physiol, 278, pp. H2039-H2049; Ripley, B.D., (1996) Pattern Recognition and Neural Networks, , Cambridge University Press, London; Rooth, G., Huch, A., Huch, R., FIGO news. Guidelines for the use of fetal monitoring (1987) Int J Gynecol Obstet, 25, p. 159; (2001) Evidence-Based Clinical Guideline Number 8. The Use of Electronic Fetal Monitoring, , Royal College of Obstetricians and Gynaecologists Royal College of Obstetricians and Gynaecologists, London; Salamalekis, E., Thomopoulos, P., Giannaris, D., Salloum, I., Vasios, G., Prentza, A., Koutsouris, D., Computerised intrapartum diagnosis of fetal hypoxia based on fetal heart rate monitoring and fetal pulse oximetry recordings utilising wavelet analysis and neural networks (2002) BJOG, 109 (10), pp. 1137-1142; Signorini, M.G., Cerutti, S., Nonlinear properties of cardiovascular time series (1999) Methodology and Clinical Applications of Blood Pressure and Heart Rate Analysis, pp. 73-89. , In: Di Rienzo M, Mancia G, Parati G, Pedotti A, Zanchetti A (eds) IOS Press, Amsterdam; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans Biomed Eng, 50 (3), pp. 365-373; Siira, S.M., Ojala, T.H., Vahlberg, T.J., Jalonen, J.O., Valimaki, I.A., Rosen, K.G., Ekholm, E.M., Marked fetal acidosis and specific changes in power spectrum analysis of fetal heart rate variability recorded during the last hour of labour (2005) Br J Obstet Gynaecol, 112, pp. 418-423; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Murotsuki, N.Y.J., Uehara, S., Yajima, A., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am J Obstet Gynecol, 182, pp. 1227-1232; Heart rate variability. Standards of measurement, physiological interpretation, and clinical use. Task force of the european society of cardiology and the north american society of pacing and electrophysiology (1996) Eur Heart J, 17, pp. 354-381. , Task-Force; Teich, M.C., Lowen, S.B., Jost, B.M., Vibe-Rheymer, K., Heneghan, C., Heart rate variability: Measures and models (1998) Nonlinear Biomedical Signal Processing. Dynamic Analysis and Modeling, 2, pp. 159-213. , In: Akay M (ed) IEEE Press, New York; Yum, M.K., Kim, K., Kim, J.H., Park, E.Y., A consistent abnormality in the average local smoothness of fetal heart rate in growth-restricted fetuses affected by severe pre-eclampsia (2004) Hypertens Res, 27 (12), pp. 911-918
Keywords: acidemia; Acidosis; Acids; article; autonomic nervous system; Biological materials; Cardiology; Central nervous system; clinical article; controlled study; delivery; Delivery, Obstetric; Discriminant Analysis; disease severity; entropy; Fetal Diseases; Fetal heart rate; Fetal heart rate (FHR); Fetal monitoring; fetus; fetus heart rate; Frequency domain analysis; Heart Rate, Fetal; human; Humans; hypothesis; labor; Linear and nonlinear indices; linear system; Neurology; newborn; nonlinear system; Prenatal Care; Second stage of labor; sensitivity and specificity; Severity of Illness Index

A model for educational simulation of neonatal cardiovascular pathophysiology. - Sá Couto, C.D.; van Meurs, W.L.; Goodwin, J.A.; Andriessen, P. (Simulation in healthcare : journal of the Society for Simulation in HealthcareSimul Healthc, 2006)
Full-body patient simulators provide a technological basis for clinical education without risk to real patients. In a previous study, we described a model for educational simulation of infant cardiovascular physiology. Using essentially the same methodology, we derive a mathematical model for the cardiovascular system of a healthy 1-week-old neonate. Computer simulations of this model result in vital signs that are close to target hemodynamic variables. Simulated systemic arterial pressure waveform and left ventricular pressure-volume loop are realistic, and the system reacts appropriately to blood loss. We also adapt the model structure and change its parameters to reflect the congenital heart defects: patent ductus arteriosus, tetralogy of Fallot, complex coarctation of the aorta with patent foramen ovale, and transposition of the great arteries. Simulated vital signs are again close to target hemodynamic variables. The resulting model for neonatal cardiovascular pathophysiology is an essential step in attaining a full-body, model-driven neonatal acute care simulator.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusPubMed ID: 19088566Language of Original Document: EnglishCorrespondence Address: Sá Couto, C.D.
Keywords: article; cardiovascular disease; Cardiovascular Diseases; cardiovascular function; Cardiovascular Physiological Phenomena; cardiovascular system; Computer simulation; congenital heart malformation; Education, Medical, Graduate; educational model; Heart Defects, Congenital; human; Humans; infant welfare; Infant, Newborn; medical education; methodology; Models, Educational; Models, Theoretical; newborn; theoretical model

The N-terminal half of the peroxisomal cycling receptor Pex5p is a natively unfolded domain - Carvalho, A.F.; Costa-Rodrigues, J.; Correia, I.; Costa Pessoa, J.; Faria, T.Q.; Martins, C.L.; Fransen, M.; Sá-Miranda, C.; Azevedo, J.E. (Journal of Molecular BiologyJ. Mol. Biol., 2006)
Targeting of most newly synthesised peroxisomal matrix proteins to the organelle requires Pex5p, the so-called PTS1 receptor. According to current models of peroxisomal biogenesis, Pex5p interacts with these proteins in the cytosol, transports them to the peroxisomal membrane and catalyses their translocation across the membrane. Presently, our knowledge on the structural details behind the interaction of Pex5p with the cargo proteins is reasonably complete. In contrast, information regarding the structure of the Pex5p N-terminal half (a region containing its peroxisomal targeting domain) is still limited. We have recently observed that the Stokes radius of this Pex5p domain is anomalously large, suggesting that this portion of the protein is either a structured elongated domain or that it adopts a low compactness conformation. Here, we address this issue using a combination of biophysical and biochemical approaches. Our results indicate that the N-terminal half of Pex5p is best described as a natively unfolded pre-molten globule-like domain. The implications of these findings on the mechanism of protein import into the peroxisome are discussed. © 2005 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 34Export Date: 21 November 2012Source: ScopusCODEN: JMOBAdoi: 10.1016/j.jmb.2005.12.002PubMed ID: 16403517Language of Original Document: EnglishCorrespondence Address: Azevedo, J.E.; Instituto de Biologia Molecular e Celular, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jazevedo@ibmc.up.ptChemicals/CAS: Amino Acids; peroxisome-targeting signal 1 receptor; Receptors, Cytoplasmic and NuclearReferences: Brown, L.A., Baker, A., Peroxisome biogenesis and the role of protein import (2003) J. Cell. Mol. Med., 7, pp. 388-400;Heiland, I., Erdmann, R., Biogenesis of peroxisomes. Topogenesis of the peroxisomal membrane and matrix proteins (2005) FEBS J., 272, pp. 2362-2372; Lazarow, P.B., Peroxisome biogenesis: Advances and conundrums (2003) Curr. Opin. Cell Biol., 15, pp. 489-497; Moyersoen, J., Choe, J., Fan, E., Hol, W.G., Michels, P.A., Biogenesis of peroxisomes and glycosomes: Trypanosomatid glycosome assembly is a promising new drug target (2004) FEMS Microbiol. Rev., 28, pp. 603-643; Weller, S., Gould, S.J., Valle, D., Peroxisome biogenesis disorders (2003) Annu. Rev. Genomics Hum. Genet., 4, pp. 165-211; Gould, S.J., Keller, G.A., Hosken, N., Wilkinson, J., Subramani, S., A conserved tripeptide sorts proteins to peroxisomes (1989) J. Cell Biol., 108, pp. 1657-1664; Klein, A.T., Barnett, P., Bottger, G., Konings, D., Tabak, H.F., Distel, B., Recognition of peroxisomal targeting signal type 1 by the import receptor Pex5p (2001) J. Biol. Chem., 276, pp. 15034-15041; Lametschwandtner, G., Brocard, C., Fransen, M., Van Veldhoven, P., Berger, J., Hartig, A., The difference in recognition of terminal tripeptides as peroxisomal targeting signal 1 between yeast and human is due to different affinities of their receptor Pex5p to the cognate signal and to residues adjacent to it (1998) J. Biol. Chem., 273, pp. 33635-33643; Brocard, C., Kragler, F., Simon, M.M., Schuster, T., Hartig, A., The tetratricopeptide repeat-domain of the PAS10 protein of Saccharomyces cerevisiae is essential for binding the peroxisomal targeting signal-SKL (1994) Biochem. Biophys. Res. Commun., 204, pp. 1016-1022; Dodt, G., Braverman, N., Wong, C., Moser, A., Moser, H.W., Watkins, P., Mutations in the PTS1 receptor gene, PXR1, define complementation group 2 of the peroxisome biogenesis disorders (1995) Nature Genet., 9, pp. 115-125; Fransen, M., Brees, C., Baumgart, E., Vanhooren, J.C., Baes, M., Mannaerts, G.P., Van Veldhoven, P.P., Identification and characterization of the putative human peroxisomal C-terminal targeting signal import receptor (1995) J. Biol. Chem., 270, pp. 7731-7736; Gatto Jr., G.J., Geisbrecht, B.V., Gould, S.J., Berg, J.M., A proposed model for the PEX5-peroxisomal targeting signal-1 recognition complex (2000) Proteins: Struct. Funct. Genet., 38, pp. 241-246; Otera, H., Setoguchi, K., Hamasaki, M., Kumashiro, T., Shimizu, N., Fujiki, Y., Peroxisomal targeting signal receptor Pex5p interacts with cargoes and import machinery components in a spatiotemporally differentiated manner: Conserved Pex5p WXXXF/Y motifs are critical for matrix protein import (2002) Mol. Cell. Biol., 22, pp. 1639-1655; Terlecky, S.R., Nuttley, W.M., McCollum, D., Sock, E., Subramani, S., The Pichia pastoris peroxisomal protein PAS8p is the receptor for the C-terminal tripeptide peroxisomal targeting signal (1995) EMBO J., 14, pp. 3627-3634; Gatto Jr., G.J., Geisbrecht, B.V., Gould, S.J., Berg, J.M., Peroxisomal targeting signal-1 recognition by the TPR domains of human PEX5 (2000) Nature Struct. Biol., 7, pp. 1091-1095; Agne, B., Meindl, N.M., Niederhoff, K., Einwachter, H., Rehling, P., Sickmann, A., Pex8p: An intraperoxisomal organizer of the peroxisomal import machinery (2003) Mol. Cell., 11, pp. 635-646; Albertini, M., Girzalsky, W., Veenhuis, M., Kunau, W.H., Pex12p of Saccharomyces cerevisiae is a component of a multi-protein complex essential for peroxisomal matrix protein import (2001) Eur. J. Cell Biol., 80, pp. 257-270; Reguenga, C., Oliveira, M.E., Gouveia, A.M., Sa-Miranda, C., Azevedo, J.E., Characterization of the mammalian peroxisomal import machinery: Pex2p. Pex5p, Pex12p, and Pex14p are subunits of the same protein assembly (2001) J. Biol. Chem., 276, pp. 29935-29942; Huhse, B., Rehling, P., Albertini, M., Blank, L., Meller, K., Kunau, W.-H., Pex17p of Saccharomyces cerevisiae is a novel peroxin and component of the peroxisomal protein translocation machinery (1998) J. Cell Biol., 140, pp. 49-60; Liu, H., Tan, X., Russell, K.A., Veenhuis, M., Cregg, J.M., PER3, a gene required for peroxisome biogenesis in Pichia pastoris, encodes a peroxisomal membrane protein involved in protein import (1995) J. Biol. Chem., 270, pp. 10940-10951; Rehling, P., Skaletz-Rorowski, A., Girzalsky, W., Voorn-Brouwer, T., Fransen, M.M., Distel, B., Pex8p, an intraperoxisomal peroxin of Saccharomyces cerevisiae required for protein transport into peroxisomes binds the PTS1 receptor pex5p (2000) J. Biol. Chem., 275, pp. 3593-3602; Smith, J.J., Szilard, R.K., Marelli, M., Rachubinski, R.A., The peroxin Pex17p of the yeast Yarrowia lipolytica is associated peripherally with the peroxisomal membrane and is required for the import of a subset of matrix proteins (1997) Mol. Cell. Biol., 17, pp. 2511-2520; Waterham, H.R., Titorenko, V.I., Haima, P., Cregg, J.M., Harder, W., Veenhuis, M., The Hansenula polymorpha PER1 gene is essential for peroxisome biogenesis and encodes a peroxisomal matrix protein with both carboxy- and amino-terminal targeting signals (1994) J. Cell Biol., 127, pp. 737-749; Costa-Rodrigues, J., Carvalho, A.F., Gouveia, A.M., Fransen, M., Sa-Miranda, C., Azevedo, J.E., The N terminus of the peroxisomal cycling receptor, Pex5p, is required for redirecting the peroxisome-associated peroxin back to the cytosol (2004) J. Biol. Chem., 279, pp. 46573-46579; Dodt, G., Gould, S.J., Multiple, P.E.X., Genes are required for proper subcellular distribution and stability of Pex5p, the PTS1 receptor: Evidence that PTS1 protein import is mediated by a cycling receptor (1996) J. Cell Biol., 135, pp. 1763-1774; Gouveia, A.M., Guimaraes, C.P., Oliveira, M.E., Reguenga, C., Sa-Miranda, C., Azevedo, J.E., Characterization of the peroxisomal cycling receptor, Pex5p, using a cell-free in vitro import system (2003) J. Biol. Chem., 278, pp. 226-232; Oliveira, M.E., Gouveia, A.M., Pinto, R.A., Sa-Miranda, C., Azevedo, J.E., The energetics of Pex5p-mediated peroxisomal protein import (2003) J. Biol. Chem., 278, pp. 39483-39488; Glover, J.R., Andrews, D.W., Rachubinski, R.A., Saccharomyces cerevisiae peroxisomal thiolase is imported as a dimer (1994) Proc. Natl Acad. Sci. USA, 91, pp. 10541-10545; McNew, J.A., Goodman, J.M., An oligomeric protein is imported into peroxisomes in vivo (1994) J. Cell Biol., 127, pp. 1245-1257; Stewart, M.Q., Esposito, R.D., Gowani, J., Goodman, J.M., Alcohol oxidase and dihydroxyacetone synthase, the abundant peroxisomal proteins of methylotrophic yeasts, assemble in different cellular compartments (2001) J. Cell Sci., 114, pp. 2863-2868; Walton, P.A., Hill, P.E., Subramani, S., Import of stably folded proteins into peroxisomes (1995) Mol. Biol. Cell, 6, pp. 675-683; Saidowsky, J., Dodt, G., Kirchberg, K., Wegner, A., Nastainczyk, W., Kunau, W.H., Schliebs, W., The di-aromatic pentapeptide repeats of the human peroxisome import receptor PEX5 are separate high affinity binding sites for the peroxisomal membrane protein PEX14 (2001) J. Biol. Chem., 276, pp. 34524-34529; Schliebs, W., Saidowsky, J., Agianian, B., Dodt, G., Herberg, F.W., Kunau, W.H., Recombinant human peroxisomal targeting signal receptor PEX5. Structural basis for interaction of PEX5 with PEX14 (1999) J. Biol. Chem., 274, pp. 5666-5673; Costa-Rodrigues, J., Carvalho, A.F., Fransen, M., Hambruch, E., Schliebs, W., Sa-Miranda, C., Azevedo, J.E., Pex5p, the peroxisomal cycling receptor, is a monomeric non-globular protein (2005) J. Biol. Chem., 280, pp. 24404-24411; Elgersma, Y., Elgersma-Hooisma, M., Wenzel, T., McCaffery, J.M., Farquhar, M.G., Subramani, S., A mobile PTS2 receptor for peroxisomal protein import in Pichia pastoris (1998) J. Cell Biol., 140, pp. 807-820; Rehling, P., Marzioch, M., Niesen, F., Wittke, E., Veenhuis, M., Kunau, W.H., The import receptor for the peroxisomal targeting signal 2 (PTS2) in Saccharomyces cerevisiae is encoded by the PAS7 gene (1996) EMBO J., 15, pp. 2901-2913; Zhang, J.W., Lazarow, P.B., Peb1p (Pas7p) is an intraperoxisomal receptor for the NH2-terminal, type 2, peroxisomal targeting sequence of thiolase: Peb1p itself is targeted to peroxisomes by an NH2-terminal peptide (1996) J. Cell Biol., 132, pp. 325-334; Dodt, G., Warren, D., Becker, E., Rehling, P., Gould, S.J., Domain mapping of human PEX5 reveals functional and structural similarities to Saccharomyces cerevisiae Pex18p and Pex21p (2001) J. Biol. Chem., 276, pp. 41769-41781; Einwachter, H., Sowinski, S., Kunau, W.H., Schliebs, W., Yarrowia lipolytica Pex20p Saccharomyces cerevisiae Pex18p/Pex21p and mammalian Pex5pL fulfil a common function in the early steps of the peroxisomal PTS2 import pathway (2001) EMBO Rep., 2, pp. 1035-1039; Matsumura, T., Otera, H., Fujiki, Y., Disruption of the interaction of the longer isoform of Pex5p, Pex5pL, with Pex7p abolishes peroxisome targeting signal type 2 protein import in mammals. Study with a novel Pex5-impaired Chinese hamster ovary cell mutant (2000) J. Biol. Chem., 275, pp. 21715-21721; Gouveia, A.M., Guimaraes, C.P., Oliveira, M.E., Sa-Miranda, C., Azevedo, J.E., Insertion of Pex5p into the peroxisomal membrane is cargo protein-dependent (2003) J. Biol. Chem., 278, pp. 4389-4392; De La Torre, J.G., Hydrodynamics of segmentally flexible macromolecules (1994) Eur. Biophys. J., 23, pp. 307-322; Denning, D.P., Uversky, V., Patel, S.S., Fink, A.L., Rexach, M., The Saccharomyces cerevisiae nucleoporin Nup2p is a natively unfolded protein (2002) J. Biol. Chem., 277, pp. 33447-33455; Permyakov, S.E., Millett, I.S., Doniach, S., Permyakov, E.A., Uversky, V.N., Natively unfolded C-terminal domain of caldesmon remains substantially unstructured after the effective binding to calmodulin (2003) Proteins: Struct. Funct. Genet., 53, pp. 855-862; Uversky, V.N., Natively unfolded proteins: A point where biology waits for physics (2002) Protein Sci., 11, pp. 739-756; Lydakis-Simantiris, N., Hutchison, R.S., Betts, S.D., Barry, B.A., Yocum, C.F., Manganese stabilizing protein of photosystem II is a thermostable, natively unfolded polypeptide (1999) Biochemistry, 38, pp. 404-414; Sreerama, N., Woody, R.W., Estimation of protein secondary structure from circular dichroism spectra: Comparison of CONTIN, SELCON, and CDSSTR methods with an expanded reference set (2000) Anal. Biochem., 287, pp. 252-260; Stanley, W.A., Sokolova, A., Brown, A., Clarke, D.T., Wilmanns, M., Svergun, D.I., Synergistic use of synchrotron radiation techniques for biological samples in solution: A case study on protein-ligand recognition by the peroxisomal import receptor Pex5p (2004) J. Synchrotron Radiat., 11, pp. 490-496; Oberg, K.A., Fink, A.L., A new attenuated total reflectance Fourier transform infrared spectroscopy method for the study of proteins in solution (1998) Anal. Biochem., 256, pp. 92-106; Navea, S., Tauler, R., De Juan, A., Application of the local regression method interval partial least-squares to the elucidation of protein secondary structure (2005) Anal. Biochem., 336, pp. 231-242; Obradovic, Z., Peng, K., Vucetic, S., Radijovac, P., Dunker, A.K., Exploiting heterogeneous sequence properties improves prediction of protein disorder (2006) Proteins, , In the press; Gould, S.J., Collins, C.S., Opinion: Peroxisomal-protein import: Is it really that complex? (2002) Nature Rev. Mol. Cell. Biol., 3, pp. 382-389; Shoemaker, B.A., Portman, J.J., Wolynes, P.G., Speeding molecular recognition by using the folding funnel: The fly-casting mechanism (2000) Proc. Natl Acad. Sci. USA, 97, pp. 8868-8873; Pontius, B.W., Close encounters: Why unstructured, polymeric domains can increase rates of specific macromolecular association (1993) Trends Biochem. Sci., 18, pp. 181-186; Tompa, P., Intrinsically unstructured proteins (2002) Trends Biochem. Sci., 27, pp. 527-533; Gouveia, A.M., Reguenga, C., Oliveira, M.E., Sa-Miranda, C., Azevedo, J.E., Characterization of peroxisomal Pex5p from rat liver. Pex5p in the Pex5p-Pex14p membrane complex is a transmembrane protein (2000) J. Biol. Chem., 275, pp. 32444-32451; Dammai, V., Subramani, S., The human peroxisomal targeting signal receptor, Pex5p, is translocated into the peroxisomal matrix and recycled to the cytosol (2001) Cell, 105, pp. 187-196; Imanaka, T., Small, G.M., Lazarow, P.B., Translocation of acyl-CoA oxidase into peroxisomes requires ATP hydrolysis but not a membrane potential (1987) J. Cell Biol., 105, pp. 2915-2922; Wendland, M., Subramani, S., Cytosol-dependent peroxisomal protein import in a permeabilized cell system (1993) J. Cell Biol., 120, pp. 675-685; Azevedo, J.E., Costa-Rodrigues, J., Guimaraes, C.P., Oliveira, M.E., Sa-Miranda, C., Protein translocation across the peroxisomal membrane (2004) Cell Biochem. Biophys., 41, pp. 451-468; Wang, D., Visser, N.V., Veenhuis, M., Van Der Klei, I.J., Physical interactions of the peroxisomal targeting signal 1 receptor pex5p, studied by fluorescence correlation spectroscopy (2003) J. Biol. Chem., 278, pp. 43340-43345; Oliveira, M.E., Reguenga, C., Gouveia, A.M., Guimaraes, C.P., Schliebs, W., Kunau, W.H., Mammalian Pex14p: Membrane topology and characterisation of the Pex14p-Pex14p interaction (2002) Biochim. Biophys. Acta, 1567, pp. 13-22; Fransen, M., Wylin, T., Brees, C., Mannaerts, G.P., Van Veldhoven, P.P., Human pex19p binds peroxisomal integral membrane proteins at regions distinct from their sorting sequences (2001) Mol. Cell. Biol., 21, pp. 4413-4424; Sreerama, N., Venyaminov, S.Y., Woody, R.W., Estimation of protein secondary structure from circular dichroism spectra: Inclusion of denatured proteins with native proteins in the analysis (2000) Anal. Biochem., 287, pp. 243-251; Vigano, C., Margolles, A., Van Veen, H.W., Konings, W.N., Ruysschaert, J.M., Secondary and tertiary structure changes of reconstituted LmrA induced by nucleotide binding or hydrolysis. a Fourier transform attenuated total reflection infrared spectroscopy and tryptophan fluorescence quenching analysis (2000) J. Biol. Chem., 275, pp. 10962-10967; Laurent, T.C., Killander, J., Theory of gel filtration + its experimental verification (1964) J. Chromatog., 14, pp. 217-230;
Keywords: Amino acids; amino terminal sequence; article; biogenesis; Calorimetry, Differential Scanning; cell membrane; cell receptor; Chromatography, Gel; circular dichroism; cytosol; differential scanning calorimetry; human; Humans; infrared spectroscopy; matrix protein; Natively unfolded; Peroxisomal protein import; peroxisome; Pex5p; priority journal; Protein conformation; protein degradation; protein domain; protein folding; protein interaction; protein Pex5p; protein structure; Protein Structure, Secondary; Protein Structure, Tertiary; protein transport; pts1 receptor; PTS1-receptor; Receptors, Cytoplasmic and Nuclear; Spectroscopy, Fourier Transform Infrared; unclassified drug

Three-dimensional culture of human osteoblastic cells in chitosan sponges: The effect of the degree of acetylation - Amaral, I.F.; Sampaio, P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
In this investigation, the effect of the degree of acetylation (DA) of chitosan on the behavior of human osteoblastic MG-63 cells cultured in three-dimensional chitosan matrices was assessed. Chitosan sponges with DAs in the range of 4 to 49% were prepared and characterized in terms of microstructure, porosity, and pore size. Collagen sponges were used as 3D control. Cell proliferation was determined using the MTT assay while the retention of the osteoblastic phenotype was monitored by assaying alkaline phosphatase activity. Cell morphology, cytoskeletal organization, and viability were assessed using different microscopy techniques. Chitosan sponges showed a similar microstructure regardless the DA, except for the highest DA used, where a more heterogeneous pore distribution was observed. In terms of cell proliferation, alkaline phosphatase activity and cell viability, cells cultured in chitosan scaffolds performed as well as in the 3D control regardless the DA, except for the highest DA used, where an inhibitory effect on cell proliferation was found. However, while in sponges with DAs ≤ 13% cells attached and spread displaying long cell filopodia and numerous cell-to-cell contacts, in sponges with higher DAs cells tended to remain spherical and grow into spheroid-like cellular aggregates. In the present study, the DA played a key role in determining the affinity of osteoblastic cells towards the substrates, possibly by influencing the nature of the initial adsorbed protein layer. © 2005 Wiley Periodicals, Inc.
Cited By (since 1996): 19Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30522PubMed ID: 16270345Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; chitosan, 9012-76-4; collagen, 9007-34-5; Alkaline Phosphatase, EC 3.1.3.1; Chitosan, 9012-76-4; Collagen, 9007-34-5References: Bruder, S.P., Caplan, A.I., Bone regeneration through cellular engineering (2000) Principles of Tissue Engineering, pp. 683-696. , Lanza RP, Langer R, Vacanti J, editors. San Diego: Academic Press;Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681; Khor, E., (2001) Chitin: Fulfilling a Biomaterials Promise, , Oxford, UK: Elsevier Science Ltd; Vandevord, P.J., Hwt, M., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., Evaluation of the biocompatibility of a chitosan scaffold in mice (2002) J Biomed Mater Res, 59, pp. 585-590; Tomihata, K., Ikada, Y., In vitro and in vivo degradation of films of chitin and its deacetylated derivatives (1997) Biomaterials, 18, pp. 567-575; Rao, S.B., Sharma, C.P., Sterilization of chitosan: Implications (1995) J Biomater Appl, 10, pp. 136-143; Muzzarelli, R.A.A., Zucchini, C., Ilari, P., Pugnaloni, A., Belmonte, M.M., Biagini, G., Castaldini, C., Osteoconductive properties of methylpyrrolidinone chitosan in an animal-model (1993) Biomaterials, 14, pp. 925-929; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., Enhanced bone formation by controlled growth factor delivery from chitosan-based biomaterials (2002) J Control Release, 78, pp. 187-197; Zhao, F., Yin, Y.J., Lu, W.W., Leong, J.C., Zhang, W.J., Zhang, J.Y., Zhang, M.F., Yao, K.D., Preparation and histological evaluation of biomimetic three-dimensional hydroxyapatite/chitosan-gelatin network composite scaffolds (2002) Biomaterials, 23, pp. 3227-3234; Nettles, D.L., Elder, S.H., Gilbert, J.A., Potential use of chitosan as a cell scaffold material for cartilage tissue engineering (2002) Tissue Eng, 8, pp. 1009-1016; Zhang, Y., Zhang, M.Q., Calcium phosphate/chitosan composite scaffolds for controlled in vitro antibiotic drug release (2002) J Biomed Mater Res, 62, pp. 378-386; Prasitsilp, M., Jenwithisuk, R., Kongsuwan, K., Damrongchai, N., Watts, P., Cellular responses to chitosan in vitro: The importance of deacetylation (2000) J Mater Sci Mater Med, 11, pp. 773-778; Chatelet, C., Damour, O., Domard, A., Influence of the degree of acetylation on some biological properties of chitosan films (2001) Biomaterials, 22, pp. 261-268; Dhiman, H.K., Ray, A.R., Panda, A.K., Characterization and evaluation of chitosan matrix for in vitro growth of MCF-7 breast cancer cell lines (2004) Biomaterials, 25, pp. 5147-5154; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., Rat bone marrow stromal cells osteogenic differentiation and fibronectin adsorption on chitosan membranes: The effect of the degree of acetylation (2005) J Biomed Mater Res Part A, 75 A, pp. 387-397; Cukierman, E., Pankov, R., Stevens, D.R., Yamada, K.M., Taking cell-matrix adhesions to the third dimension (2001) Science, 294, pp. 1708-1712; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Mima, S., Miya, M., Iwamoto, R., Yoshikawa, S., Highly deacetylated chitosan and its properties (1983) J Appl Polym Sci, 28, pp. 1909-1917; Aiba, S., Studies on Chitosan: 1. Determination of the degree of N-acetylation of chitosan by ultraviolet spectrophotometry and gel-permeation chromatography (1986) Int J Biol Macromol, 8, pp. 173-176; Hirano, S., Ohe, Y., Ono, H., Selective N-acylation of chitosan (1976) Carbohydr Res, 47, pp. 315-320; Baxter, A., Dillon, M., Taylor, K.D.A., Roberts, G.A.F., Improved method for Ir determination of the degree of N-acetylation of chitosan (1992) Int J Biol Macromol, 14, pp. 166-169; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., Molecular parameters of chitosans depolymerized with the aid of papain (1996) Carbohydr Polym, 29, pp. 63-68; Zhang, R.Y., Ma, P.X., Poly(alpha-hydroxyl acids) hydroxyapatite porous composites for bone-tissue engineering. I. Preparation and morphology (1999) J Biomed Mater Res, 44, pp. 446-455; Mosmann, T., Rapid colorimetric assay for cellular growth and survival: Application to proliferation and cytotoxicity assays (1983) J Immunol Methods, 65, pp. 55-63; Ashton, B.A., Abdullah, F., Cave, J., Williamson, M., Sykes, B.C., Couch, M., Poser, J.W., Characterization of cells with high alkaline-phosphatase activity derived from human-bone and marrow - Preliminary assessment of their osteogenicity (1985) Bone, 6, pp. 313-319; Kurita, K., Controlled functionalization of the polysaccharide chitin (2001) Prog Polym Sci, 26, pp. 1921-1971; Wang, W., Bo, S.Q., Li, S.Q., Qin, W., Determination of the Mark-Houwink equation for chitosans with different degrees of deacetylation (1991) Int J Biol Macromol, 13, pp. 281-285; Roberts, G.A.F., (1992) Chitin Chemistry, , Houndmills: The Macmillan Press Ltd; Ueda, H., Hong, L., Yamamoto, M., Shigeno, K., Inoue, M., Toba, T., Yoshitani, M., Shimizu, Y., Use of collagen sponge incorporating transforming growth factor-beta 1 to promote bone repair in skull defects in rabbits (2002) Biomaterials, 23, pp. 1003-1010; Hanthamrongwit, M., Grant, M.H., Wilkinson, R., Confocal laser-scanning microscopy (Clsm) for the study of collagen sponge microstructure (1994) J Biomed Mater Res, 28, pp. 213-216; Zinger, O., Anselme, K., Denzer, A., Habersetzer, P., Wieland, M., Jeanfils, J., Hardouin, P., Landolt, D., Time-dependent morphology and adhesion of osteoblastic cells on titanium model surfaces featuring scale-resolved topography (2004) Biomaterials, 25, pp. 2695-2711; Eggli, P.S., Muller, W., Schenk, R.K., Porous hydroxyapatite and tricalcium phosphate cylinders with 2 different pore-size ranges implanted in the cancellous bone of rabbits - A comparative histomorphometric and histologic-study of bony ingrowth and implant substitution (1988) Clin Orthop, 232, pp. 127-138; Madihally, S.V., Matthew, H.W.T., Porous chitosan scaffolds for tissue engineering (1999) Biomaterials, 20, pp. 1133-1142; Madihally, S.V., Frattaroli, T.L., Matthew, H.W.T., (1999) In Vivo Colonization of Chitosan Based Porous Scaffolds, p. 172. , Providence, RI: Transactions from the 25th Annual Meeting of the Society for Biomaterials, Providence, RI; Zhang, Y., Zhang, M.Q., Synthesis and characterization of macroporous chitosan/calcium phosphate composite scaffolds for tissue engineering (2001) J Biomed Mater Res, 55, pp. 304-312; Chung, T.W., Yang, J., Akaike, T., Cho, K.Y., Nah, J.W., Kim, S.I., Cho, C.S., Preparation of alginate/galactosylated chitosan scaffold for hepatocyte attachment (2002) Biomaterials, 23, pp. 2827-2834; Masi, L., Franchi, A., Santucci, M., Danielli, D., Arganini, L., Giannone, V., Formigli, L., Beghe, F., Adhesion, growth, and matrix production by osteoblasts on collagen substrata (1992) Calcif Tissue Int, 51, pp. 202-212; Wiesmann, H.P., Nazer, N., Klatt, C., Szuwart, T., Meyer, U., Bone tissue engineering by primary osteoblast-like cells in a monolayer system and 3-dimensional collagen gel (2003) J Oral Maxillofac Surg, 61, pp. 1455-1462; Henriksen, I., Green, K.L., Smart, J.D., Smistad, G., Karlsen, J., Bioadhesion of hydrated chitosans: An in vitro and in vivo study (1996) Int J Pharmaceut, 145, pp. 231-240; Lebaron, R.G., Athanasiou, K.A., Extracellular matrix cell adhesion peptides: Functional applications in orthopedic materials (2000) Tissue Eng, 6, pp. 85-103; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., Adhesive protein interactions with chitosan: Consequences for valve endothelial cell growth on tissue-engineering materials (2003) J Biomed Mater Res Part A, 67 A, pp. 538-547; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) J Biomed Mater Res Part A, 66 A, pp. 247-259; Webb, K., Hlady, V., Tresco, P.A., Relationships among cell attachment, spreading, cytoskeletal organization, and migration rate for anchorage-dependent cells on model surfaces (2000) J Biomed Mater Res, 49, pp. 362-368; Anselme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Lost, A., Hardouin, P., Qualitative and quantitative study of human osteoblast adhesion on materials with various surface roughnesses (2000) J Biomed Mater Res, 49, pp. 155-166; Domard, A., Chitosan interactions (1997) Advances in Chitin Science, pp. 410-420. , Domard A, Roberts GAF, Varum KM, editors. Lyon, France: Jacques André Publisher;
Keywords: Acetylation; Aggregates; alkaline phosphatase; article; Bone Regeneration; bone tissue; Bone tissue engineering; Cell culture; Cell Culture Techniques; Cell filopodia; cell growth; cell proliferation; Cell Shape; cell structure; cell survival; cell viability; chitosan; Collagen; confocal microscopy; controlled study; Cytoskeletal organization; cytoskeleton; Degree of acetylation (DA); enzyme activity; gel permeation chromatography; human; human cell; Humans; infrared spectroscopy; Microstructure; morphology; osteoblast; Osteoblastic cells; Osteoblasts; Phosphatase activity; porosity; Proteins; Scaffold; Scaffolds; Scanning electron microscopy; Substrates; Tissue engineering

Biological evaluation of calcium alginate microspheres as a vehicle for the localized delivery of a therapeutic enzyme - Barrias, C.C.; Lamghari, M.; Granja, P.L.; Sá Miranda, M.C.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2005)
Gaucher disease (GD) is caused by the decreased activity and/or stability of the lysosomal enzyme glucocerebrosidase (GCR). The available treatment consists in the intravenous administration of exogenous GCR, and is effective in reverting most of the symptoms. However, in terms of bone pathology, which is among the most disabling manifestations, a slow and incomplete response is observed, indicating that adjuvant therapies are necessary to consistently restore GCR activity in bone and accelerate regeneration. In this study, calcium alginate microspheres were analyzed as a vehicle for localized GCR delivery to bone. Results demonstrated that the entrapped enzyme retained full activity and exhibited a broader pH-dependent activity profile, compared to that of free-GCR, with improved stability at physiological pH. GCR release profile was established, and it was demonstrated that GCR could be released in a sustained manner. The biological behavior of the system was evaluated by analyzing the uptake of released GCR by GCR-deficient cells from GD patients, using different techniques: GCR activity measurements, radiolabeling, and cellulose acetate electrophoresis. Results demonstrated that GCR was internalized by cells significantly enhancing the residual enzymatic activity. To achieve an activity reconstitution level comparable to that obtained using free-GCR, only half of the dose was required with entrapped-GCR. © 2005 Wiley Periodicals, Inc.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30348PubMed ID: 16028235Language of Original Document: EnglishCorrespondence Address: Barrias, C.C.; Instituto de Engenharia Biomédica (INEB), Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: ccbarrias@ineb.up.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; calcium alginate, 9005-35-0; glucosylceramidase, 37228-64-1; iodine 125, 14158-31-7, 22822-81-7; Alginates; alginic acid, 9005-32-7; Drug Carriers; Enzymes, Immobilized; Glucosylceramidase, EC 3.2.1.45; Glucuronic Acid, 576-37-4; Hexuronic AcidsManufacturers: GenzymeReferences: Grabowski, G.A., Leslie, N., Wenstrup, R., Enzyme therapy for Gaucher disease: The first 5 years (1998) Blood Rev, 12, pp. 115-133;Zhao, H., Grabowski, G.A., Gaucher disease: Perspectives on a prototype lysosomal disease (2002) Cell Mol Life Sci, 59, pp. 694-707; Friedman, B., Vaddi, K., Preston, C., Mahon, E., Cataldo, J.R., McPherson, J.M., A comparison of the pharmacological properties of carbohydrate remodeled recombinant and placental-derived beta-glucocerebrosidase: Implications for clinical efficacy in treatment of Gaucher disease (1999) Blood, 93, pp. 2807-2816; Rasmussen, J., Barsomian, G., Bergh, M., Enzymatically active recombinant glucocerebrosidase. U.S. patent 6451600. 17 September 2002Elstein, D., Itzchaki, M., Mankin, H.J., Skeletal involvement in Gaucher's disease (1997) Baillieres Clin Haematol, 10, pp. 793-816; Wenstrup, R.J., Roca-Espiau, M., Weinreb, N.J., Bembi, B., Skeletal aspects of Gaucher disease: A review (2002) Br J Radiol, 75 (SUPPL. 1), pp. A2-A12; Mistry, P.K., Wraight, E.P., Cox, T.M., Therapeutic delivery of proteins to macrophages: Implications for treatment of Gaucher's disease (1996) Lancet, 348, pp. 1555-1559; Gregoriadis, G., Neerunjun, D., Meade, T.W., Goolamali, S.K., Weereratne, H., Bull, G., Experiences after long-term treatment of a type I Gaucher disease patient with liposome-entrapped glucocerebroside: Beta-glucosidase (1980) Birth Defects Orig Artic Ser, 16, pp. 383-392; Dale, G.L., Kuhl, W., Beutler, E., Incorporation of glucocerebrosidase into Gaucher's disease monocytes in vitro (1979) Proc Natl Acad Sci USA, 76, pp. 473-475; Beutler, E., Dale, G.L., Guinto, D.E., Kuhl, W., Enzyme replacement therapy in Gaucher's disease: Preliminary clinical trial of a new enzyme preparation (1977) Proc Natl Acad Sci USA, 74, pp. 4620-4623; Belchetz, P.E., Crawley, J.C., Braidman, I.P., Gregoriadis, G., Treatment of Gaucher's disease with liposome-entrapped glucocerebroside: Beta-glucosidase (1977) Lancet, 2, pp. 116-117; Korablyov, V., Zimran, A., Barenholz, Y., Cerebroside-beta-glucosidase encapsulation in liposomes for Gaucher's disease treatment revisited (1999) Pharm Res, 16, pp. 466-469; Busto, M.D., Ortega, N., Perez-Mateos, M., Effect of immobilization on the stability of bacterial and fungal beta-glucosidase (1997) Process Biochem, 32, pp. 441-449; Dashevsky, A., Protein loss by the microencapsulation of an enzyme (lactase) in alginate beads (1998) Int J Pharm, 161, pp. 1-5; Blandino, A., Macias, M., Cantero, D., Immobilization of glucose oxidase within calcium alginate gel capsules (2001) Process Biochem, 36, pp. 601-606; Kokufuta, E., Shimizu, N., Tanaka, H., Nakamura, I., Use of polyelectrolyte complex-stabilised calcium alginate gel for entrapment of beta-amylase (1988) Biotechnol Bioeng, 33, pp. 756-759; Edelman, E.R., Mathiowitz, E., Langer, R., Klagsbrun, M., Controlled and modulated release of basic fibroblast growth factor (1991) Biomaterials, 12, pp. 619-626; Peters, M.C., Isenberg, B.C., Rowley, J.A., Mooney, D.J., Release from alginate enhances the biological activity of vascular endothelial growth factor (1998) J Biomater Sci Polym Ed, 9, pp. 1267-1278; Alsberg, E., Anderson, K.W., Albeiruti, A., Franceschi, R.T., Mooney, D.J., Cell-interactive alginate hydrogels for bone tissue engineering (2001) J Dent Res, 80, pp. 2025-2029; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20, pp. 45-53; Gagne, T.A., Chappell-Afonso, K., Johnson, J.L., McPherson, J.M., Oldham, C.A., Tubo, R.A., Vaccaro, C., Vasios, G.W., Enhanced proliferation and differentiation of human articular chondrocytes when seeded at low cell densities in alginate in vitro (2000) J Orthop Res, 18, pp. 882-890; (1993) Iodine-125. A Guide to Radioiodination Techniques: Amersham Life Science, , Amersham Place, Little Chalfont, Bucks: Amersham International pic; 64 pp; Sa Miranda, M.C., Aerts, J.M., Pinto, R., Fontes, A., De Lacerda, L.W., Van Weely, S., Barranger, J., Tager, J.M., Activity of glucocerebrosidase in extracts of different cell types from type 1 Gaucher disease patients (1990) Clin Genet, 38, pp. 218-227; Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., Measurement of protein using bicinchoninic acid (1985) Anal Biochem, 150, pp. 76-85; Sa Miranda, M.C., Aerts, J.M., Pinto, R.A., Magalhaes, J.A., Barranger, J.A., Tager, J.M., Schram, A.W., Heterogeneity in human acid beta-glucosidase revealed by cellulose-acetate electrophoresis (1988) Biochim Biophys Acta, 965, pp. 163-168; Smidsrod, O., Draget, K.I., Chemistry and physical properties of alginates (1996) Carbohyd Eur, 14, pp. 6-13; Gaserod, O., Sannes, A., Skjak-Braek, G., Microcapsules of alginate-chitosan. II. A study of capsule stability and permeability (1999) Biomaterials, 20, pp. 773-783; Aslani, P., Kennedy, R.A., Studies on diffusion in alginate gels. I. Effect of cross-linking with calcium or zinc ions on diffusion of acetaminophen (1996) J Control Release, 42, pp. 75-82
Keywords: Alginates; alginic acid; article; Bone; bone disease; Bone Regeneration; Calcium alginate; Calcium Compounds; catalysis; Cell culture; Cells, Cultured; controlled study; Drug Carriers; drug delivery system; enzyme activity; enzyme assay; enzyme replacement; Enzymes; Enzymes, Immobilized; fibroblast culture; Fibroblasts; Gaucher disease; Gaucher disease (GD); Glucocerebrosidase (GCR); Glucosylceramidase; Glucuronic Acid; Hexuronic Acids; human; human cell; Humans; iodine 125; Localized delivery; lysosome enzyme; lysosome storage disease; microsphere; Microspheres; Pathology; pH effects; physiology; recombinant enzyme; Therapeutic enzyme

Development of a system to adsorb drugs onto calcium phosphate materials - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2005)
Several studies were carried out in order to reduce the systemic use of antibiotics due to the high concentration required to provide the minimum inhibitory concentration (MIC) at infected sites. The aim of this study was to develop a system of drug adsorption onto commercial hydroxyapatite (HA, Ca 10(PO 4) 6(OH) 2) and glass reinforced hydroxyapatite (GR-HA) granules. The drug will then be released for the local treatment of periodontitis. The antibiotics used in this study were metronidazole, a specific antibiotic indicated for the systemic treatment of periodontitis, and ampicillin, a wide spectrum antibiotic. UV spectroscopy was used to measure the amount of drug adsorbed onto HA and GR-HA granules. Results showed that metronidazole was unable to adsorb on the material's surface, as opposed to ampicillin which adsorbed both onto HA and GR-HA. Preliminary release kinetics studies were carried out using a flow through dissolution system. Results are discussed in terms of the influence of the different surface characteristics of the materials on the adsorption processes. © 2005 Springer Science + Business Media, Inc.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-005-2535-3PubMed ID: 15965596Language of Original Document: EnglishCorrespondence Address: Queiroz, A.C.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180, Porto, Portugal; email: aqueiroz@ineb.up.ptChemicals/CAS: ampicillin, 69-52-3, 69-53-4, 7177-48-2, 74083-13-9, 94586-58-0; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; metronidazole, 39322-38-8, 443-48-1; Ampicillin, 69-53-4; Anti-Infective Agents; calcium phosphate, 10103-46-5; Calcium Phosphates; Coated Materials, Biocompatible; Delayed-Action Preparations; Drug Carriers; Metronidazole, 443-48-1References: Seymour, R.A., Heasman, P.A., Macgregor, I.D.M., (1992) Drugs, Diseases, and the Periodontium, 1. , edited by R. A. Seymour and P. A. Heasman Oxford University Press, Oxford;Carnevale, R.A., Greco, G.W., Bullard, C.M., Hanker, J.S., (1987) Biomedical Materials and Devices, p. 247. , edited by J. S. Hanker and B. L. Giammara Materials Research Society, Pittsburgh; Friedman, M., Steinberg, D., (1990) Pharm. Res., 7, p. 313; Hagiwara, S., Takamatsu, N., Tominaga, Y., Umeda, M., (1998) J. Period., 69, p. 62; Wright, T.L., Ellen, R.P., Lacroix, J.M., Sinnadurai, S., Mittelman, M.W., (1997) J. Period. Res., 32, p. 473; Golomb, G., Friedman, M., Soskolne, A., Stabholz, A., Sela, M.N., (1984) J. Dent. Res., 63, p. 1149; Goodson, J.M., Hogan, P.E., Dunham, S.L., (1984) J. Period., 55, p. 81; Somayaji, B.V., Jariwala, U., Jayachandran, P., Vidyalakshim, K., Dudhani, R.V., (1998) J. Period., 69, p. 409; Stoltze, K., (1992) J. Clin. Period., 19, p. 698; Goodson, J.M., Holborow, D., Dunn, R.L., Hogan, P., Dunham, S., (1983) J. Period., 54, p. 575; Yu, D., Wong, J., Matsuda, Y., Fox, J.L., Higuchi, W.I., Otsuka, M., (1992) J. Pharm. Sci., 81, p. 529; Nishihara, K., (1993) Clin. Mater., 12, p. 159; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mat. Res., 45, p. 376; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mat. Res., 47, p. 603; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mat. Res., 54, p. 463; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Gibson, I.R., Knowles, J.C., (2001) Biomaterials, 22, p. 1393; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Knowles, J.C., Santos, J.D., Hastings, G.W., World Patent, WO0068164 (1994)Myers, H.M., Tochon-Danguy, H.J., Baud, C.A., (1983) Calcif. Tissue Int., 35, p. 745; Ratier, A., Gibson, I.R., Best, S.M., Freche, M., Lacout, J.L., Rodrigues, F., (2001) Biomaterials, 22, p. 897; Ando, D.J., (1996) Ultraviolet and Visible Spectroscopy, p. 16. , John Wiley & Sons, West Sussex
Keywords: Adsorption; ampicillin; Anti-Infective Agents; Antibiotics; article; Calcium Compounds; calcium phosphate; Calcium phosphates; Coated Materials, Biocompatible; concentration response; Delayed-Action Preparations; Diffusion; Dissolution; drug absorption; drug adsorption; Drug Carriers; Drug release; drug stability; glass; Glass reinforced hydroxyapatie (GR-HA); human; Humans; hydroxyapatite; Kinetics; Material's surface; Materials science; materials testing; metronidazole; minimum inhibitory concentration; Minimum inhibitory concentration (MIC); periodontitis; priority journal; Reaction kinetics; reduction; surface property; Ultraviolet spectroscopy

In vitro cytocompatibility of MG63 cells on chitosan-organosiloxane hybrid membranes - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Fernandes, M.H. (BiomaterialsBiomaterials, 2005)
Chitosan-silicate hybrids were synthesized using γ- glycidoxypropyltrimethoxysilane (GPSM) as the agent for cross-linking the chitosan chains. CaCl 2 was introduced in the hybrids in expectation that it would improve cell adhesion and differentiation of the hybrid surfaces. Fourier-transform infrared (FT-IR) spectroscopy and 29Si CP-MAS NMR spectroscopy were used to analyze the structures of the hybrids. Cytocompatibility of the hybrids was investigated in terms of proliferation of an osteoblastic cell line, MG63. The adhesion and proliferation of the osteoblastic cells cultured on the surface of a chitosan-GPSM hybrid without calcium were similar to those on a control culture plate, and were better than those on a chitosan membrane. The ALP activity of the cells cultured on this hybrid was higher than that on the chitosan membrane. Contrary to expectations, the incorporation of calcium ions into the hybrids did not improve cell attachment and proliferation on their surfaces. © 2004 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 55Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2004.02.056PubMed ID: 15276356Language of Original Document: EnglishCorrespondence Address: Hayakawa, S.; Biomaterial Laboratory, Faculty of Engineering, Okayama Univ., 3-1-1 T., Okayama-shi, Japan; email: satoshi@cc.okayama-u.ac.jpChemicals/CAS: calcium chloride, 10043-52-4; Alkaline Phosphatase, EC 3.1.3.1; Biocompatible Materials; Calcium, 7440-70-2; Chitosan, 9012-76-4; Cross-Linking Reagents; gamma-glycidoxypropyltrimethoxysilane, 2530-83-8; Membranes, Artificial; Neoplasm Proteins; SilanesManufacturers: Chisso, Japan; Kasei, JapanReferences: Park, J.B., Lakes, R.S., (1992) Biomaterials An Introduction, pp. 223-234. , New York: Plenum Press;Wise, D.L., (2000) Biomaterials and Bioengineering Handbook, pp. 556-559. , New York: Marcel Dekker; Lee, Y.K., Mooney, J.D., Hydrogels for tissue engineering (2001) Chem Rev, 101, pp. 1869-1879; Park, S.N., Park, J.C., Kim, H.O., Song, M.J., Suh, H., Characterization of porous collagen/hyaluronic acid scaffold modified by 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide cross-linking (2002) Biomaterials, 23, pp. 1205-1212; Kuo, C.K., Ma, P.X., Ionically crosslinked alginate hydrogels as scaffolds for tissue engineering: Part 1 Structure, gelation rate and mechanical properties (2001) Biomaterials, 22, pp. 511-521; Widmer, M.S., Gupta, P.K., Lu, L., Meszlenyi, R.K., Evans, G.R.D., Brandt, K., Savel, T., Mikos, A.G., Manufacture of porous biodegradable polymer conduits by an extrusion process for guided tissue regeneration (1998) Biomaterials, 19, pp. 1945-1955; Wang, Y.C., Lin, M.C., Wang, D.M., Hsieh, H.J., Fabrication of a novel porous PGA-chitosan hybrid matrix for tissue engineering (2003) Biomaterials, 24, pp. 1047-1057; Domard, A., Rinaudo, M., Preparation and characterization of fully deacetylated chitosan (1983) Int J Biol Macromol, 5, pp. 49-52; Chandy, T., Sharma, P.C., Chitosan - As a biomaterial (1990) Biomater Artif Cells Artif Organo, 18, pp. 1-24; Ueno, H., Yamada, H., Tanaka, I., Kaba, N., Matsuura, M., Okumura, M., Kadosawa, T., Fujinaga, T., Accelerating effects of chitosan for healing at early phase of experimental open wound in dogs (1999) Biomaterials, 20, pp. 1407-1414; Varma, H.K., Yokogawa, Y., Espinosa, F.F., Kawamoto, Y., Nishizawa, K., Nagata, F., Kameyama, T., Porous calcium phosphate coating over phosphorylated chitosan film by a biomimetic method (1999) Biomaterials, 20, pp. 879-884; Xiao, C., Gao, S., Wang, H., Zhang, L., Blend films from chitosan and konjac glucomannan solutions (2000) J Appl Polym Sci, 76, pp. 509-515; Chung, T.W., Lu, Y.F., Wang, S.S., Lin, Y.S., Chu, S.H., Growth of human endothelial cells on photochemically grafted Gly-Arg-Gly-Asp (GRGD) chitosans (2002) Biomaterials, 23, pp. 4803-4809; Muzzareli, R.A.A., Mattioli-Belmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Fini, M., Biagini, G., Stimulatory effect on bone formation exerted by a modified chitosan (1994) Biomaterials, 15, pp. 1075-1081; Park, Y.J., Lee, M.Y., Lee, J.Y., Seol, Y.J., Chung, C.P., Lee, S.J., Controlled release of platelet-derived growth factor-BB from chondroitin sulfate-chitosan sponge for guided bone regeneration (2000) J Controlled Rel, 67, pp. 385-394; Suzuki, T., Mizushima, Y., Umeda, T., Ohashi, R., Further biocompatibility testing of silica-chitosan complex membrane in the production of tissue plasminogen activator by epithelial and fibroblast cells (1999) J Biosci Bioeng, 88, pp. 194-199; Yamaguchi, I., Itoh, S., Suzuki, M., Sakane, M., Osaka, A., Tanaka, J., The chitosan prepared from crab tendon I: The characterization and the mechanical properties (2003) Biomaterials, 24, pp. 2031-2036; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., Enhanced bone formation by controlled growth factor delivery from chitosan-based biomaterials (2002) J Controlled Rel, 78, pp. 187-197; Kawamura, Y., Mitsuhashi, M., Tanibe, H., Yoshida, H., Adsorption of metal ions on polyaminated highly porous chelating resin (1993) Ing Eng Chem Res, 32, pp. 386-391; Jameela, S.R., Jayakrishnan, A., Glutaraldehyde crosslinked chitosan as a long acting biodegradable drug delivery vehicle: Studies on the in vitro release of mitoxantrone and in vivo degradation of microspheres in rat muscle (1995) Biomaterials, 16, pp. 769-775; Speer, D.P., Chvapil, M., Eskelson, C.D., Ulreich, J., Biological effects of residual glutaraldehyde in glutaraldehyde-tanned collagen biomaterials (1980) J Biomed Mater Res, 14, pp. 753-764; Nishi, C., Nakajima, N., Ikada, Y., In vitro evaluation of cytotoxicity of diepoxy compounds used for biomaterial modification (1995) J Biomed Mater Res, 29, pp. 829-834; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Sol-gel preparation and in vitro deposition of apatite on porous gelatin-siloxane hybrids (2001) J Non-Cryst Solid, 285, pp. 116-122; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Novel approach to fabricate porous gelatin-siloxane hybrids for bone tissue engineering (2002) Biomaterials, 23, pp. 4765-4773; Berridge, V., Tan, A.S., Characterization of the cellular reduction of 3-(4,5-dimethylthiazol-2- yl)-2,5-diphenyltetrazolium bromide (MTT) subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch Biochem Biophys, 303, pp. 474-482; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Incorporation of Ca 2+ ions in gelatin-siloxane hybrids through a sol-gel process (2001) J Ceramic Soc Japan, 109, pp. 403-408; Yamaguchi, I., Tokuchi, K., Fukuzaki, H., Koyama, Y., Takakuda, K., Monma, H., Tanaka, J., Preparation and microstructure analysis of chitosan/hydroxyapatite nanocomposites (2001) J Biomed Mater Res, 55, pp. 20-27; Hench, L.L., Ethridge, E.C., (1982) Biomaterias An Interfacial Approach, p. 10. , New York: Academic Press; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Martin, T.J., Findlay, D.M., Heath, J.K., Ng, K.W., Osteoblasts: Differentiation and function (1993) Handbook of Experimental Pharmacology, pp. 149-183. , J.R. Mundy, & T.J. Martin. Berlin: Springer; Aubin, J.E., Turksen, K., Heersch, J.N.M., Osteoblastic cell lineage (1993) Cellular and Molecular Biology of Bone, pp. 1-45. , M. Noda. Tokyo: Academic Press Inc; Anderson, S.I., Downes, S., Perry, C.C., Caballero, A.M., Evaluation of the osteoblast response to a silica gel in vitro (1998) J Mater Sci: Mater Med, 9, pp. 731-735; Rhee, S.H., Hwang, M., Si, H.J., Choi, J.Y., Biological activities of osteoblasts on poly(methyl methacrylate)/silica hybrid containing calcium salt (2003) Biomaterials, 24, pp. 901-906; Kalonji, E.E., Denis, I., Lieberherr, M., Pointillart, A., Effects of extracellular calcium on the proliferation and differentiation of porcine osteoblasts in vitro (1998) Cell Tissue Res, 292, pp. 163-171; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of pre-immersion on the biocompatibility of glass-reinforced hydroxyapatite plasma-sprayed coatings (2000) Biomaterials, 21, pp. 813-820; Bilezikian, J.P., Raisz, L.G., Rodan, G.A., (2002) Principles of Bone Biology, p. 1325. , New York: Academic Press
Keywords: alkaline phosphatase; article; artificial membrane; Biocompatibility; Biocompatible Materials; Bone Neoplasms; Calcium; calcium chloride; cell adhesion; Cell attachments; Cell culture; cell differentiation; Cell Division; Cell Line, Tumor; chitosan; chitosan derivative; controlled study; cross linking; Cross-Linking Reagents; Crosslinking; Cytocompatibility; Fourier transform infrared spectroscopy; human; human cell; Humans; hybrid; infrared spectroscopy; Magnetic Resonance Spectroscopy; materials testing; Membranes, Artificial; MG63 osteoblastic cells; Microscopy, Electron, Scanning; Neoplasm Proteins; Nuclear magnetic resonance spectroscopy; Organic-inorganic hybrid; osteoblast; Osteoblasts; Osteosarcoma; priority journal; Silanes; Silicates; siloxane; Spectroscopy, Fourier Transform Infrared; structure analysis; surface property; Synthesis (chemical); wettability; γ-Glycidoxypropyltrimethoxysilane (GPSM)

In vitro studies of calcium phosphate glass ceramics with different solubility with the use of human bone marrow cells - Dias, A.G.; Lopes, M.A.; Trigo Cabral, A.T.; Santos, J.D.; Fernandes, M.H. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2005)
Two glass ceramics in the CaO-P 2O 5-MgO system with the incorporation of K 2O or TiO 2 oxides were prepared with the goal of using them as potential bone graft substitutes. The incorporation of TiO 2 and K 2O led to the preparation of specific crystalline phases in the structure of the glass ceramics, which show different degrees of biodegradation. In fact, the 45CaO-45P 2O 5-5MgO-5K 2O has been previously demonstrated to be much more soluble in aqueous solutions than the 45CaO-37P 2O 5-5MgO-13TiO 2 glass ceramic. The in vitro biological activity of the two calcium phosphate glass ceramics was studied with the use of human bone marrow osteoblast cell cultures maintained for 28 days, and seeded materials were assessed for cell proliferation and function. The Ti-containing glass ceramic showed a stable surface throughout the culture time, on macroscopic and SEM observation. Osteoblast cells proliferated gradually, especially during the third week, with a high alkaline phosphatase activity and formation of a mineralized matrix. On SEM observation, attached cells appeared with a spreadpolygonal morphology typical of the osteoblast cells, with extensive cell-to-cell contact. Cell behavior on the seeded material was similar to that found on cultures performed on tissue-culture-grade polystyrene; except for the presence of lower cell numbers during the first 2 weeks. By contrast, the K-containing glass ceramic showed a highly instable surface with dissolution/precipitation processes occurring throughout the culture time. Few cells adhered to the material surface, and subsequent proliferation was also hindered, especially from the first week onwards. Cell numbers were significantly lower than those observed in the Ti-containing glass ceramic during most of the incubation time. Results suggest that the different in vitro biological behavior of these two glass ceramics is mainly due to the significant differences in the surface degradation rate, which is directly correlated to the chemical composition of the mother glass. © 2005 Wiley Periodicals, Inc.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30357PubMed ID: 15988737Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; FMDUP-Faculdade de Medicina Dentária da Universidade do Porto, Rua Dr. Manuel Pereira da Silva, 4200 Porto, Portugal; email: mhrf@portugalmail.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; polystyrene, 9003-53-6; titanium dioxide, 1317-70-0, 1317-80-2, 13463-67-7, 51745-87-0; Alkaline Phosphatase, EC 3.1.3.1; calcium phosphate, 10103-46-5; Calcium Phosphates; Ceramics; Glass ceramics, 85422-94-2References: Yaszemski, M.J., Payne, R.G., Hayes, W.C., Langer, R., Mikos, A.C., Evolution of bone transplantation: Molecular, cellular and tissue strategies to engineer human bone (1996) Biomaterials, 17, pp. 175-185;Rueger, J.M., Bone replacement materials-state of the art and the way ahead (1998) Orthopade, 27, pp. 72-79; Tadic, D., Epple, M., A thorough physicochemical characterization of 14 calcium phosphate-based bone substitution materials in comparison to natural bone (2004) Biomaterials, 25, pp. 987-994; Greenwald, A.C., Bolden, S.D., Goldberg, V.M., Khan, Y., Laurencin, C.T., Rosier, R.N., Bone-graft substitutes: Facts, fictions and applications (2001) J Bone Joint Surg, 83 A, pp. 98-103; Damien, C.J., Parson, J.R., Bone graft and bone graft substitutes: A review of current technology and applications (1997) J Appl Biomater, 2, pp. 187-208; Lettuec, J.C., Clément, D., Lesprit, E., Faber, J., The use of calcium phosphates, their biological properties (2000) Eur J Orthop Surg Traumatol, 10, pp. 223-229; Dorozhkin, S.V., Epple, M., Biological and medical significance of calcium phosphates (2002) Angew Chem Int Ed Engl, 41, pp. 3130-3146; Dias, A.G., Lopes, M.A., Gibson, I.R., Santos, J.D., In vitro degradation studies of calcium phosphate glass ceramics prepared by controlled crystallization (2003) J Non-Cryst Solids, 330, pp. 81-89; Fini, M., Giardino, R., In vitro and in vivo tests for the biological evaluation of candidate orthopedic materials: Benefits and limits (2003) J Appl Biomater Biomech, 1, pp. 155-163; Hunt, J.A., McLaughlin, P.J., Flanagan, B.F., Review-Techniques to investigate cellular and molecular interaction in the host response to implanted biomaterials (1997) Biomaterials, 18, pp. 1449-1459; Dias, A.G., Tsuru, K., Hayakawa, S., Lopes, M.A., Santos, J.D., Osaka, A., Crystallization studies of biodegradable CaO-P 2O 5 glass with MgO and TiO 2 for bone regeneration applications (2004) Glass Technol, 45; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681; Kumari, T.V., Vasudev, U., Kumar, A., Menon, B., Cell surface interactions in the study of biocompatibility (2002) Trends Biomater Artif Organs, 15, pp. 37-41; Sun, J.S., Tsuang, Y.H., Liao, C.J., Liu, H.C., Hang, Y.S., Lin, F.H., The effects of calcium phosphate particles on the growth of osteoblasts (1997) J Biomed Mater Res, 37, pp. 324-334; Sun, J.S., Whs, C., Chen, L.T., Huang, Y.C., Juang, L.W., Lin, F.H., The influence on gene-expression profiling of osteoblasts behavior following treatment with the ionic products of sintered β-dicalcium pyrophosphate dissolution (2004) Biomaterials, 25, pp. 607-616; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II: Effect of ascorbic acid b-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Morais, S., Dias, N., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro osteoblastic differentiation of human bone marrow cells in the presence of metal ions (1999) J Biomed Mater Res, 44, pp. 176-190; Coelho, M.J., Cabral, A.T., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part I: Osteoblastic differentiation of serially passaged human bone marrow cells cultured in alpha-MEM and in DMEM (2000) Biomaterials, pp. 211087-211094; Dias, A.G., Lopes, A.G., Santos, J.D., Fernandes, N.H., The influence of pre-incubation treatment in the in vitro biological performance of degradable CaO-P 2O 5 glass ceramics (2005) Key Eng Mater, 284-286, pp. 565-568; Bitar, M., Salih, V., Mudera, V., Knowles, J.C., Lewis, M.P., Soluble phosphate glasses: In vitro studies using human cells of hard and soft tissue origin (2004) Biomaterials, 25, pp. 2283-2292; Suzuki, T., Yamamoto, T., Toriyana, M., Nishizawa, K., Yokogawa, Y., Mucalo, M.R., Kawamoto, Y., Kameyama, T., Surface instability of calcium phosphate ceramics in tissue growth of anchorage-dependent animal cells (1997) J Biomed Mater Res, 34, pp. 507-517; Ducheyne, P., Qiu, Q., Bioactive ceramics: The effect of surface reactivity on bone formation and bone cell function (1999) Biomaterials, 20, pp. 2287-2303; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Mineral, 14, pp. 27-40; Stein, G.S., Lian, J.B., Stein, J.L., Van Wijnen, A.J., Frenkel, B., Montecino, M., Mechanism regulating osteoblast proliferation and differentiation (1996) Principles of Bone Biology, pp. 69-83. , Bilezikian JP, Raisz LG, Rodan GA, editors. New York: Academic Press; Chun, S., Na, S.W., Lee, J.H., Chung, J.P., Ryu, I.C., Kim, S.Y., Biodegradation study of potassium calcium metaphosphate in the SBF and Tris-buffer solution (2002) Key Eng Mater, 218-220, pp. 149-152; Ploska, U., Berger, G., Solubility of compositions in the system CaTi xZr 4 - X(PO 4) 6 with x = 0-4 (1997) Biomaterials, 18, pp. 1671-1675; Dias, A.G., Skakle, J.M.S., Gibson, I.R., Lopes, M.A., Santos, J.D., In situ thermal and structural characterization of bioactive calcium phosphate glass ceramics containing TiO 2 and MgO oxides: HT-XRD studies (2005) J Non-Cryst Solids, , Forthcoming; Chun, S., Jeong, J.H., Kim, K.H., Kim, S., Biodegradation study of amorphous and crystalline calcium metaphosphate in SBF and Tris-buffer solution (2001) Key Eng Mater, 192-195, pp. 131-134; Elghannam, A., Ducheyne, P., Shapiro, I.M., Bioactive material template for in vitro synthesis of bone (1995) J Biomed Mater Res, 29, pp. 359-370; Kitsugi, T.T., Yamamuro, T., Nakamura, T., Oka, M., Transmission electron microscopy observations at the interface of bone and four types of calcium phosphate ceramics with different calcium/phosphorous molar ratios (1995) Biomaterials, 16, pp. 1101-1107; Gross, U., Muller-Mai, C., Voigt, C., Mesgarian, M., Berger, G., Ploska, U., Tissue response in the femur of rabbits after implantation of a new calcium titanium phosphate composition (2001) Key Eng Mater, 192-195, pp. 383-386; Hill, P.A., Orth, M., Bone remodeling - Review (1998) Br J Orthod, 25, pp. 101-107
Keywords: alkaline phosphatase; aqueous solution; article; Biodegradation; Bone; Bone graft; bone marrow cell; Bone Marrow Cells; bone mineralization; bone prosthesis; Calcium Compounds; calcium phosphate; Calcium phosphate glass ceramic; Calcium phosphate glass ceramics; Calcium phosphates; cell contact; Cell culture; cell proliferation; Cells; ceramics; chemical composition; controlled study; crystal structure; Dissolution; enzyme activity; extracellular matrix; glass; Glass ceramics; human; Human bone marrow cells; human cell; Humans; in vitro study; In vitro testing; Magnesia; magnesium derivative; Microscopy, Electron, Scanning; osteoblast; Osteoblasts; polystyrene; Precipitation (chemical); Scanning electron microscopy; Solubility; Spectrum Analysis; Surface treatment; Titanium dioxide

Mineralization of regenerated cellulose hydrogels induced by human bone marrow stromal cells - Granja, P.L.; De Jéso, B.; Bareille, R.; Rouais, F.; Baquey, C.; Barbosa, M.A. (European Cells and MaterialsEur. Cells and Mater., 2005)
The proliferation of cultured human bone marrow stromal cells (HBMSC) on regenerated cellulose hydrogels was assessed. Regenerated cellulose hydrogels showed good rates of HBMSC proliferation, the cells exhibiting a flattened morphology, and after 22 days in culture, the cells had homogeneously colonized the surface of the materials. Moreover, since the early days in culture, between the surface of the materials and attached cells a continuous granulated hydroxyapatite layer was formed. It has been previously demonstrated in vitro, but without cells, that these materials did not mineralize. Hence, it seems that HBMSC promoted the mineralization of the surface.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusPubMed ID: 16217723Language of Original Document: EnglishCorrespondence Address: Granja, P.L.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: pgranja@ineb.up.ptChemicals/CAS: cellulose, 61991-22-8, 68073-05-2, 9004-34-6; hydroxyapatite, 1306-06-5, 51198-94-8; Calcium Phosphates; Cellulose, 9004-34-6; Hydrogels; calcium phosphate, 10103-46-5References: (1994) Evaluation Biologique des Dispositifs Médicaux. Partie 5: Essais Concernant la Cytotoxicité: Méthodes in Vitro. (Biological Evaluation of Medical Devices. Part 5: Cytotoxicity Assays: in Vitro Methods), , www.afnor.fr, AFNOR-NF EN 30993-5. Association Française de Normalization, Saint-Denis la Plaine, France;Albrektsson, T., Hard tissue response (1998) Handbook Of Biomaterial Properties, pp. 500-512. , Black J, Hastings G (eds). Chapman & Hall, London; Amédée, J., Bareille, R., Jeandot, R., Bordenave, L., Remy, M., Rouais, F., Baquey, C., Evaluation of cell colonization on biomaterials: Preventing cell attachment to plastic containers (1994) Biomaterials, 15, pp. 1029-1031; Bergsma, J.E., De Bruijn, W.C., Rozema, F.R., Bos, R.R.M., Boering, G., Late degradation tissue response to poly(L-lactide) bone plates and screws (1995) Biomaterials, 16, pp. 25-31; Bohic, S., Heymann, D., Pouezat, J.A., Gauthier, O., Daculsi, G., Transmission FT-IR microspectroscopy of mineral phases in calcified tissues (1998) Sciences de la Vie, 321, pp. 865-876; Burgess, E.A., Hollinger, J.O., Options for engineering bone (1998) Frontiers in Tissue Engineering, pp. 383-399. , Patrick Jr CW, Mikos AG, McIntire LV (eds). Elsevier Science, Oxford; Chauveaux, D., Barbie, C., Barthe, X., Baquey, C., Poustis, J., Biological behaviour of cellulosic materials after bone implantation: Preliminary results (1990) Clin Mater, 5, pp. 251-258; Choee, J.H., Lee, S.J., Lee, Y.M., Rhee, J.M., Lee, H.B., Khang, G., Proliferation rate of fibroblast cells on polyethylene surfaces with wettability gradient (2004) J Appl Polym Sci, 92, pp. 599-606; Curtis, A.S.G., Forrester, J.V., Clark, P., Substrate hydroxylation and cell adhesion (1986) J Cell Sci, 86, pp. 9-24; Dasarathy, H., Riley, C., Coble, H.D., Analysis of apatite deposits on substrates (1993) J Biomed Mater Res, 27, pp. 477-482; Degenshein, G.A., Hurwitz, A., Ribacoff, S., Experience with regenerated oxidized cellulose (1963) NY State J Med, 63, pp. 2639-2643; Dias, G.J., Peplow, P.V., Teixeira, F., Osseous regeneration in the presence of oxidized cellulose and collagen (2003) J Mater Sci Mater Med, 14, pp. 739-745; Dumitriu, S., Dumitriu, M., Hydrogels as support for drug delivery systems (1996) Polysaccharides in Medicinal Applications, pp. 705-764. , Dumitriu S (ed.). Marcel Dekker, New York; Franz, G., Polysaccharides in pharmacy (1986) Adv Polym Sci, 76, pp. 1-30; Friedman, R.J., Black, J., Galante, J.O., Jacobs, J.J., Skinner, H.B., Current concepts in orthopaedic biomaterials and implant fixation (1993) J Bone Joint Surg, 75 A, pp. 1086-1109; Galgut, P.N., Oxidized cellulose mesh. I. Biodegradable membrane in periodontal surgery (1990) Biomaterials, 11, pp. 561-564; Granja, P.L., Pouységu, L., Deffieux, D., Daudé, G., De Jéso, B., Labrugère, C., Baquey, C., Barbosa, M.A., Cellulose phosphates as biomaterials. Surface chemical modification of regenerated cellulose hydrogels (2001) J Appl Polym Sci, 82, pp. 3354-3365; Granja, P.L., Pouységu, L., De Jéso, B., Rouais, F., Baquey, C., Barbosa, M.A., Cellulose phosphates as biomaterials. Mineralization of chemically modified regenerated cellulose hydrogels (2001) J Mater Sci, 36, pp. 2163-2172; Granja, P.L., Ribeiro, C.C., De Jéso, B., Baquey, C., Barbosa, M.A., Mineralization of regenerated cellulose hydrogels (2001) J Mater Sci: Mater Med, 12, pp. 785-791; Hayashi, T., Biodegradable polymers for biomedical uses (1994) Prog Polym Sci, 19, pp. 663-702; Healy, K.E., Thomas, C.H., Rezania, A., Kim, J.E., McKeown, P.J., Lom, B., Hockberger, P.E., Kinetics of bone cell organization and mineralization on materials with patterned surface chemistry (1996) Biomaterials, 17, pp. 195-208; Hon, D.N.-S., Cellulose and its derivatives: Structures, reactions, and medical uses (1996) Polysaccharides in Medicinal Applications, pp. 87-105. , Dumitriu D (ed.). Marcel Dekker, New York; Horbett, T.A., The role of adsorbed proteins in tissue response to biomaterials (2004) Biomaterials Science: An Introduction to Materials in Medicine, 2nd Ed., pp. 237-246. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE (eds.). Elsevier-Academic Press, San Diego; Hosseini, M.M., Sodek, J., Franke, R.-P., Davies, J.E., The structure and composition of the bone-implant interface (2000) Bone Engineering, pp. 295-304. , Davies JE (ed.). em squared inc., Toronto; Ikada, Y., Biomedical applications of cellulose membranes (1989) Cellulose: Structural and Functional Aspects, pp. 447-455. , Kennedy JF, Phillips GO, Williams PA (eds.). Ellis Horwood, Chichester; Ishaug, S.L., Crane, G.M., Miller, M.J., Yasko, A.W., Yaszemski, M.J., Mikos, A.G., Bone formation by three-dimensional stromal osteoblast culture in biodegradable polymer scaffolds (1997) J Biomed Mater Res, 36, pp. 17-28; (1992) Biological Evaluation of Medical Devices. Test for Cytotoxicity: in Vitro Methods, , www.iso.org, ISO 10993-5. International Organization for Standardization, Geneva, Switzerland; Lamba, N.M.K., Baumgartner, J.A., Cooper, S.L., Cell-synthetic surface interactions (1998) Frontiers in Tissue Engineering, pp. 121-137. , Patrick Jr CW, Mikos AG, McIntire LV (eds). Elsevier Science, Oxford; Lee, J.H., Lee, J.W., Khang, G., Lee, H.B., Interaction of cells on chargeable functional group gradient surfaces (1997) Biomaterials, 18, pp. 351-358; Martson, M., Viljanto, J., Hurme, T., Saukko, P., Biocompatibility of cellulose sponge with bone (1998) Eur Surg Res, 30, pp. 426-432; Martson, M., Viljanto, J., Hurme, T., Laippala, P., Saukko, P., Is cellulose sponge degradable or stable as implantation materials? An in vivo subcutaneous study in the rat (1999) Biomaterials, 20, pp. 1899-1995; McFarland, C.D., Mayer, S., Scotchford, C., Dalton, B.A., Steele, J.G., Downes, S., Attachment of cultured human bone cells to novel polymers (1999) J Biomed Mater Res, 44, pp. 1-11; Miyamoto, T., Takahashi, S., Ito, H., Inagaki, H., Noishiki, Y., Tissue biocompatibility of cellulose and its derivatives (1989) J Biomed Mater Res, 23, pp. 125-133; Mosmann, T., Rapid colorimetric assay for cellular growth and survival: Application to proliferation and cytotoxicity assays (1983) J Immunol Meth, 65, pp. 55-63; Patrick Jr., C.W., Mikos, A.G., McIntire, L.V., Prospectus of tissue engineering (1998) Frontiers in Tissue Engineering, pp. 3-11. , Patrick Jr CW, Mikos AG, McIntire LV (eds). Elsevier Science, Oxford; Pommier, J.C., Poustis, J., Baquey, C., Chauveaux, D., (1990), Biocompatible, hydrophilic material. Method of manufacture and uses of same (Fr Pat 8610331, 1986; Eur Pat 0256906 A1, 1987) US Pat 4904258Poustis, J., Baquey, C., Chauveaux, D., Mechanical properties of cellulose in orthopaedic devices and related environments (1994) Clin Mater, 16, pp. 119-124; Puleo, D.A., Bizios, R., Formation of focal contacts by osteoblasts cultured on orthopedic biomaterials (1992) J Biomed Mater Res, 26, pp. 291-301; Puleo, D.A., Nanci, A., Understanding and controlling the bone-implant interface (1999) Biomaterials, 20, pp. 2311-2321; Shelton, R.M., Rasmussen, A.C., Davies, J.E., Protein adsorption at the interface between charged polymer substrata and migrating osteoblasts (1988) Biomaterials, 9, pp. 24-29; Skoog, T., The use of periosteum and surgicel® for bone restoration in congenital clefts of the maxilla (1967) Scand J Plast Reconstr Surg, 1, pp. 113-130; Smetana Jr., K., Cell biology of hydrogels (1993) Biomaterials, 14, pp. 1046-1050; Uysal, A., Ozbek, S., Ozcan, M., Comparison of the biological activities of high-density porous polyethylene implants and oxidized regenerated cellulose-wrapped diced cartilage grafts (2003) Plast Reconstr Surg, 112, pp. 540-546; Vert, M., Mauduit, J., Li, S., Biodegradation of PLA/GA polymers: Increasing complexity (1994) Biomaterials, 15, pp. 1209-1213; Vilamitjana-Amédée, J., Bareille, R., Rouais, F., Caplan, A.I., Harmand, M.F., Human bone marrow stromal cells express an osteoblastic phenotype in culture (1993) In Vitro Cell Dev Biol, 29 A, pp. 699-707; Recum, H.A., Yaszemski, M.J., Mikos, A.G., Tissue engineering concepts (1999) Handbook of Biomaterials Evaluation: Scientific, Technical and Clinical Testing of Implant Materials, 2nd Ed., pp. 385-409. , von Recum AF (ed.), Edwards Brothers, Ann Arbor; Webb, K., Hlady, V., Tresco, P.A., Relative importance of surface wettability and charged functional groups on NIH 2T3 fibroblast attachment, spreading and cytoskeletal organization (1998) J Biomed Mater Res, 41, pp. 422-430; Yaszemski, M.J., Payne, R.G., Hayes, W.C., Langer, R., Mikos, A.G., Evolution of bone transplantation: Molecular, cellular and tissue strategies to engineer human bone (1996) Biomaterials, 17, pp. 175-185; Kristen, H., Bosch, P., Bednar, H., Plenk Jr., H., Biocompatibility of wood in bone tissue (1977) Arch Orthop Unfallchir, 89, pp. 1-14; Kristen, H., Bosch, P., Bednar, H., Plenk Jr., H., The effects of dynamic loading on intracalcaneal wood implants and on the tissues surrounding them (1979) Arch Orthop Trauma Surg, 93, pp. 287-292; Li, S.H., Liu, Q., De Wijn, J., Zhou, B.L., De Groot, K., Calcium phosphate formation induced on silica in bamboo (1997) J Mater Sci Mater Med, 8, pp. 427-433; Li, S.H., Liu, Q., De Wijn, J.R., Zhou, B.L., De Groot, K., In vitro calcium phosphate formation on a natural composite material, bamboo (1997) Biomaterials, 18, pp. 389-395
Keywords: article; bone marrow cell; Bone Marrow Cells; bone mineralization; Calcification, Physiologic; Calcium phosphates; Cell culture; cell proliferation; cell regeneration; Cells, Cultured; Cellulose; hematopoietic stem cell; human; Human bone marrow stromal cells; human cell; Humans; hydrogel; Hydrogels; hydroxyapatite; in vitro study; mineralization; Regenerated cellulose hydrogels; Regeneration; Spectroscopy, Fourier Transform Infrared; stroma cell; Stromal Cells; Time series analysis

Recombinant glucocerebrosidase uptake by Gaucher disease human osteoblast culture model - Lamghari, M.; Barrias, C.C.; Sá Miranda, C.; Barbosa, M.A. (Blood Cells, Molecules, and DiseasesBlood Cells Mol. Dis., 2005)
Bone lesions are a major cause of morbidity in Gaucher disease (GD) type I. Enzyme replacement therapy (ERT) has been successful in treating many symptoms of type I GD but skeletal response lags behind. Local exogenous glucocerebrosidase supplementation in bone lesions via a drug delivery system may overcome this limitation. Although local enzyme supplementation aims to target lipid-engorged macrophages (Gaucher Cells) in bone compartment, enzyme uptake by osteoblasts is not excluded. To investigate the ability of human osteoblasts to internalize recombinant glucocerebrosidase (rGCR), we have used an artificial GD human osteoblasts cell culture system. MG63 human osteoblasts were treated with conduritol B epoxide (CBE) to induce complete and prolonged inhibition of endogenous glucocerebrosidase activity of cells. rGCR uptake by glucocerebrosidase-inactivated osteoblasts was examined using 125I-radiolabelling, Western blot analysis and measurement of glucocerebrosidase activity. Analysis of radiolabeled enzyme uptake by CBE treated osteoblasts showed 67.9% of internalized protein in cell extract. Enzyme internalization was also observed by Western blot analysis where the amount of mature form of glucocerebrosidase protein recognized by the glucocerebrosidase antibody was increased following the administrations of rGCR. Moreover, enzymatic activity measurement showed 23.9% of glucocerebrosidase activity of control cells. The rGCR internalization by MG63 osteoblast seems to be partially mediated by mannose receptors. These data provide evidence that MG63 human osteoblasts are able to internalize rGCR. © 2005 Elsevier Inc. All rights reserved.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: BCMDFdoi: 10.1016/j.bcmd.2005.07.009PubMed ID: 16125984Language of Original Document: EnglishCorrespondence Address: Lamghari, M.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, R. Campo Alegre 823, 4150-180 Porto, Portugal; email: lamghari@ineb.up.ptChemicals/CAS: conduritol b epoxide, 6090-95-5; imiglucerase, 154248-97-2; iodine 125, 14158-31-7, 22822-81-7; conduritol epoxide, 6090-95-5; Glucosylceramidase, EC 3.2.1.45; Inositol, 6917-35-7; Recombinant ProteinsTradenames: cerezyme, GenzymeManufacturers: GenzymeReferences: Beutler, E., Grabowski, G., Gaucher disease (1995) The Metabolic and Molecular Bases of Inherited Disease, 2, pp. 2641-2661. , C.R. Scriber A.L. Beaudet W.S. Sly 7th ed. McGraw-Hill New York, NY;Beutler, E., Enzyme replacement in Gaucher disease (2004) PLoS Med., 1 (2), p. 21; Elstein, D., Itzchaki, M., Mankin, H., Skeletal involvement in Gaucher's disease (1997) Ballière's Clin. Haematol., 10 (4), pp. 793-815; Wenstrup, R.J., Roca-Espiau, M., Weinreb, N.J., Bembi, B., Skeletal aspects of Gaucher disease: A review (2002) Br. J. Radiol., 75 (1 SUPPL.), pp. 2-A12; Barranger, J.A., O'Rourke, E., Lessons learned from the development of enzyme therapy for Gaucher disease (2001) J. Inherited Metab. Dis., 24 (2 SUPPL.), pp. 89-96; Zimran, A., Elstein, D., Levy-Lahad, E., Zevin, S., Hadas-Halpern, I., Bar-Ziv, Y., Foldes, J., Abrahamov, A., Replacement therapy with imiglucerase for type 1 Gaucher's disease (1995) Lancet, 345 (8963), pp. 1479-1480; Barton, N.W., Brady, R.O., Dambrosia, J.M., Di Bisceglie, A.M., Doppelt, S.H., Hill, S.C., Mankin, H.J., Argoff, C.E., Replacement therapy for inherited enzyme deficiency-macrophage-targeted glucocerebrosidase for Gaucher's disease (1991) N. Engl. J. Med., 324 (21), pp. 1464-1470; Barton, N.W., Furbish, F.S., Murray, G.J., Garfield, M., Brady, R.O., Therapeutic response to intravenous infusions of glucocerebrosidase in a patient with Gaucher disease (1990) Proc. Natl. Acad. Sci. U. S. A., 87 (5), pp. 1913-1916; Friedman, B., Vaddi, K., Preston, C., Mahon, E., Cataldo, J.R., McPherson, J.M., A comparison of the pharmacological properties of carbohydrate remodeled recombinant and placental-derived beta-glucocerebrosidase: Implications for clinical efficacy in treatment of Gaucher disease (1999) Blood, 93, pp. 2807-2816; Grabowski, G.A., Leslie, N., Wenstrup, R., Enzyme therapy for Gaucher disease: The first 5 years (1998) Blood Rev., 12 (2), pp. 115-133; Samuel, R., Katz, K., Papapoulos, S.E., Yosipovitch, Z., Zaizov, R., Liberman, U.A., Aminohydroxy propylidene bisphosphonate (APD) treatment improves the clinical skeletal manifestations of Gaucher's disease (1994) Pediatrics, 94 (3), pp. 385-389; Shiffmann, R., Mankin, H., Dambrosia, J.M., Xavier, R.J., Kreps, C., Hills, S.C., Barton, N.W., Rosenthal, D.I., Decreased bone density in splenectomized Gaucher patients receiving enzyme replacement therapy (2002) Blood Cells Mol. Dis., 28, pp. 288-296; (1993) Iodine-125, a Guide to Radioiodination, p. 64. , Amersham Life Science; Barrias, C.C., Martins, M.C.L., Sá Miranda, M.C., Barbosa, M.A., Adsorption of a therapeutic enzyme to self-assembled monolayers: Effect of surface chemistry and solution pH on the amount and activity of adsorbed enzyme (2005) Biomaterials, 26, pp. 2695-2704; Laemmli, U.K., (1970) Nature, 227, pp. 680-685; Sá Miranda, M.C., Aerts, J.M., Pinto, R., Fontes, A., Lacerda, L.W., Van Weely, S., Barranger, J., Tager, J.M., Activity of glucocerebrosidase in extracts of different cell types from type 1 Gaucher disease patients (1990) Clin. Genet., 38, pp. 218-227; Barrias, C.C., Lamghari, M., Granja, P.L., Sá Miranda, C., Barbosa, M.A., Biological evaluation of calcium alginate microspheres as a vehicle for the localised delivery of a therapeutic enzyme (2005) J. Biomed. Mater. Res.; Barrias, C.C., Ribeiro, C.C., Lamghari, M., Sá Miranda, C., Barbosa, M.A., Proliferation, activity, and osteogenic differentiation of bone marrow stromal cells cultured on calcium titanium phosphate microspheres (2005) J. Biomed. Mater. Res., 72 A (1), pp. 57-66; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Calcium phosphate-alginate microspheres as enzyme delivery matrices (2004) Biomaterials, 25 (18), pp. 4363-4373; Das, P.K., Murray, G.J., Gal, A.E., Barranger, J.A., Glucocerebrosidase deficiency and lysosomal storage of glucocerebroside induced in cultured macrophages (1987) Exp. Cell Res., 168 (2), pp. 463-474; Pelled, D., Shogomori, H., Futerman, A.H., The increased sensitivity of neurons with elevated glucocerebroside to neurotoxic agents can be reversed by imiglucerase (2000) J. Inherited Metab. Dis., 23 (2), pp. 175-184; Hanley, K., Jiang, Y., Holleran, W.M., Elias, P.M., Williams, M.L., Feingold, K.R., Glucosylceramide metabolism is regulated during normal and hormonally stimulated epidermal barrier development in the rat (1997) J. Lipid Res., 38 (3), pp. 576-584; Marshall, J., McEachern, K.A., Kyros, J.A., Nietupski, J.B., Budzinski, T., Ziegler, R.J., Yew, N.S., Cheng, S.H., Demonstration of feasibility of in vivo gene therapy for Gaucher disease using a chemically induced mouse model (2002) Mol. Ther., 6 (2), pp. 179-189; Mistry, P.K., Wraight, E.P., Cox, T.M., Therapeutic delivery of proteins to macrophages: Implications for treatment of Gaucher's disease (1996) Lancet, 348 (9041), pp. 1555-1559; Xu, Y.H., Ponce, E., Sun, Y., Leonova, T., Bove, K., Witte, D., Grabowski, G.A., Turnover and distribution of intravenously administered mannose-terminated human acid beta-glucosidase in murine and human tissues (1996) Pediatr. Res., 39 (2), pp. 313-322; Beutler, E., Kuhl, W., Vaughan, L.M., Failure of alglucerase infused into Gaucher disease patients to localize in marrow macrophages (1995) Mol. Med., 1, pp. 320-324; Sato, Y., Beutler, E., Binding, internalization, and degradation of mannose-terminated glucocerebrosidase by macrophages (1993) J. Clin. Invest., 91, pp. 1909-1917; Schueler, U., Kaneski, C., Murray, G., Sandhoff, K., Brady, R.O., Uptake of mannose-terminal glucocerebrosidase in cultured human cholinergic and dopaminergic neuron cell lines (2002) Neurochem. Res., 27 (4), pp. 325-330; Furbish, F.S., Steer, C.J., Barranger, J.A., Jones, E.A., Brady, R.O., The uptake of native and desialylated glucocerebrosidase by rat hepatocytes and Kupffer cells (1978) Biochem. Biophys. Res. Commun., 81, pp. 1047-1053; Furbish, F.S., Steer, C.J., Krett, N.L., Barranger, J.A., Uptake and distribution of placental glucocerebrosidase in rat hepatic cells and effects of sequential deglycosylation (1981) Biochim. Biophys. Acta, 673, pp. 425-434; East, L., Isacke, C.M., The mannose receptor family (2002) Biochim. Biophys. Acta., 1572, pp. 364-386; East, L., Rushton, S., Taylor, M.E., Isack, C.M., Characterization of sugar binding by the mannose receptor family member, Endo180 (2002) J. Biol. Chem., 277 (52), pp. 50469-50475; Engelholm, L.H., Nielsen, B.S., Netzel-Arnett, S., Solberg, H., Chen, X.D., Lopez Garcia, J.M., Lopez-Otin, C., Bugge, T.H., The urokinase plasminogen activator receptor-associated protein/endo180 is coexpressed with its interaction partners urokinase plasminogen activator receptor and matrix metalloprotease-13 during osteogenesis (2001) Lab. Invest., 81, pp. 1403-1414; Bailey, L., Wienke, D., Howard, M., Knauper, V., Isacke, C.M., Murphy, G., Investigation of the role of Endo180/urokinase-type plasminogen activator receptor-associated protein as a collagenase 3 (matrix metalloproteinase 13) receptor (2002) Biochem. J., 1 (363 PART 1), pp. 67-72
Keywords: article; Cell culture; cell extract; Cells, Cultured; conduritol b epoxide; controlled study; drug activity; drug uptake; enzyme activity; enzyme antibody; Enzyme inhibition; Enzyme uptake; epoxide; Gaucher disease; Glucocerebrosidase; Glucosylceramidase; human; human cell; Humans; imiglucerase; Inositol; internalization; iodine 125; isotope labeling; mannose receptor; osteoblast; Osteoblasts; priority journal; Recombinant Proteins; unclassified drug; Western blotting

TiO 2 type influences fibronectin adsorption - Sousa, S.R.; Moradas-Ferreira, P.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2005)
Human fibronectin (FN) plays a key role in the biointegration of implants as the success depends on adsorption of proteins like FN [1]. Indeed FN can be an intermediary between the biomaterial surface and cells. The adsorption of human fibronectin (FN) on commercially pure titanium with a titanium oxide layer formed in a H 2O 2 solution (TiO 2 cp) and TiO 2 sputtered on Si (TiO 2 sp) was studied. Adsorption isotherms and the work of adhesion were assessed by wettability studies, X-ray photoelectron spectroscopy (XPS), and by radiolabelling of FN with 125I, 125I-FN. Exchangeability of bound FN by free FN, was also evaluated by the radiolabelling technique. Contact angle determinations have shown that FN displays higher affinity for the TiO 2 cp surface than for the TiO 2 sp. As expected from the surface free energy values, the work of adhesion of FN is higher for the TiO 2 cp substrate, the more hydrophilic one, and lower for the TiO 2 sp substrate, the more hydrophobic one. The adsorption isotherms were evaluated by two different techniques: radiolabelling of FN ( 125I-FN) and XPS. TiO 2 cp adsorbs more FN than the TiO 2 sp surfaces as shown by the radiolabelling data. FN molecules are also more strongly attached to the former surface as indicated by the work of adhesion and by the exchangeability studies. Results using 125I-FN also suggests that FN adsorbs as a multilayer for FN concentrations in solution higher than 100 μg/mL. © 2005 Springer Science + Business Media, Inc.
Cited By (since 1996): 28Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-005-4725-4Language of Original Document: EnglishCorrespondence Address: Sousa, S.R.; INEB, Instituto de Engenharia Biomédica, Lab. Biomateriais, R. do Campo Alegre, 823, 4150-180 Porto, Portugal; email: ssousa@ibmc.up.ptChemicals/CAS: fibronectin, 86088-83-7; titanium dioxide, 1317-70-0, 1317-80-2, 13463-67-7, 51745-87-0; titanium, 7440-32-6; hydrogen peroxide, 7722-84-1; iodine 125, 14158-31-7, 22822-81-7; Fibronectins; Solutions; titanium dioxide, 13463-67-7; Titanium, 7440-32-6References: Horbett, T.A., (1994) Colloids and Surfaces B: Biointerfaces, 2, p. 225;Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., (2005) J Biomed Mater Res., 75 A, p. 387; Johnson, K.J., Sage, H., Briscoe, G., Erickson, H.P., (1999) J. Biol. Chem., 274, p. 15473; Bergkvist, M., Carlsson, J., Oscarsson, S., (2003) J. Biomed. Mater. Res. Part A., 64 A, p. 349; Ugarova, T.P., Zamarron, C., Veklich, Y., Bowditch, R.D., Ginsberg, M.H., Weisel, J.W., Plow, E.F., (1995) Biochemistry, 34, p. 4457; Sukenik, C.N., Balachander, N., Culp, L.A., Lewandowska, K., Merritt, K., (1990) J. Biomed. Mater. Res., 24, p. 1307; Sousa, S.R., Moradas- Ferreira, P., Melo, L.V., Saramago, B., Barbosa, M.A., (2004) Langmuir, 20, p. 9745; Gehanno, V., Freitas, P.P., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Soares, J.C., Silva, M.F., (1999) IEEE Trans. Magn., 35, p. 4361; (2003) Iodine-125, A Guide to Radioiodination Techniques - Amersham Life Science, p. 64. , Amersham International plc, Amersham Place, Little Chalfont, Bucks, HP7 9NA, England, 199; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., (2001) J. Biomed. Mater. Res., 55, p. 45; Yu, X.J., Brash, J.L., (1993) Test Procedures for the Blood Compatibility of Biomaterials, Dordrecht, p. 287. , edited by S. Dawids (Kluwer Academic Publishers, Dordrecht); Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., (1985) Analytical Biochemistry, 150, p. 76; Lindberg, B., Maripuu, R., Siegbahn, K., Larsson, R., Golander, C.G., Eriksson, J.C., (1983) J. Colloid Interface Sci., 95, p. 308; Auditore, A., Satriano, C., Coscia, U., Ambrosone, G., Parisi, V., Marletta, G., (2002) Biomolecular Engineering, 19, p. 85; Miller, R., Treppo, S., Voigt, A., Zingg, W., Neumann, A.W., (1993) Colloids and Surfaces, 69, p. 203; Serro, A.P.V., Fernandes, A.C., Saramago, B.D.V., (1997) Colloids and Surfaces A-Physicochemical and Engineering Aspects, 125, p. 209; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., (1997) Langmuir, 13, p. 3404; Matsuura, T., Hosokawa, R., Okamoto, K., Kimoto, T., Akagawa, Y., (2000) Biomaterials, 21, p. 1121; Ferraz, M.P., Monteiro, F.J., Serro, A.P., Saramago, B., Gibson, I.R., Santos, J.D., (2001) Biomaterials, 22, p. 3105; Do Serro, A., Fernandes, A.C., Saramago, B.D.V., Norde, W., (1999) J. Biomed. Mater. Res., 46, p. 376; Norde, W., Anusiem, A.C.I., (1992) Colloids and Surfaces, 66, p. 73; Rouxhet, L., Duhoux, F., Borecky, O., Legras, R., Schneider, Y.J., (1998) Journal of Biomaterials Science-Polymer Edition, 9, p. 1279; Norde, W., (1986) Advances in Colloid and Interface Science, 25, p. 267; Tamada, Y., Ikada, Y., (1993) J. Colloid Interface Sci., 155, p. 334
Keywords: Adsorption; adsorption kinetics; article; binding affinity; Biointegration; Biomaterials; Cells; chemistry; conference paper; Contact angles; Fibronectin; Fibronectins; human; Human fibronectin (FN); Humans; hydrogen peroxide; hydrophilicity; hydrophobicity; Implants (surgical); iodine 125; isotherm; Isotherms; isotope labeling; physical chemistry; priority journal; protein binding; Proteins; Radiolabelling; solution and solubility; Solutions; surface property; Titanium; Titanium dioxide; wettability; X ray photoelectron spectroscopy

Biocompatibility of chemoenzymatically derived dextran-acrylate hydrogels - Ferreira, L.; Rafael, A.; Lamghari, M.; Barbosa, M.A.; Gil, M.H.; Cabrita, A.M.S.; Dordick, J.S. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2004)
The biocompatibility of chemoenzymatically generated dextran-acrylate hydrogels has been evaluated in vitro, using human foreskin fibroblasts, and in vivo, by subcutaneous and intramuscular implantation in Wistar rats for up to 40 days. In vitro tests show that hydrogel extracts only minimally reduced (<10%) the mitochondrial metabolic activity of fibroblasts. Direct contact of the hydrogels with cells induced a cellular proliferation inhibition index (CPII) of 50-80%, compared with a control, whereas through indirect contact, the CPII values were <16%, suggesting that the high CPII values achieved in the direct assay test were likely due to mechanical stress or limitations in oxygen diffusion. Hence, the hydrogels were noncytotoxic. Moreover, cell-material interaction studies show that these hydrogels were nonadhesive. Finally, histologic evaluation of tissue response to subcutaneous and intramuscular implants showed acceptable levels of biocompatibility, as characterized by a normal cellular response and the absence of necrosis of the surrounding tissues of the implant. In the first 10 days, the foreign-body reaction in the intramuscular implantation was more severe than in subcutaneous implantation, becoming identical after 30 days. In both cases, dextran hydrogels did not show signs of degradation 6 weeks postimplantation and were surrounded by a thin fibrous capsule and some macrophages and giant cells. This response is typical with a number of nondegradable biocompatible materials. These results indicate that dextran hydrogels are biocompatible, and may have suitable applications as implantable long-term peptide/protein delivery systems or scaffolds for tissue engineering. © 2004 Wiley Periodicals, Inc.
Cited By (since 1996): 21Export Date: 21 November 2012Source: ScopusCODEN: JBMRCPubMed ID: 14762939Language of Original Document: EnglishCorrespondence Address: Dordick, J.S.; Department of Chemical Engineering, Rensselaer Polytechnic Institute, Troy, NY 12180, United States; email: dordick@rpi.eduChemicals/CAS: acrylic acid, 10344-93-1, 79-10-7; dextran, 87915-38-6, 9014-78-2; Acrylates; Biocompatible Materials; Dextrans, 9004-54-0; Enzymes; HydrogelsReferences: Ferreira, L., Gil, M.H., Dordick, J.S., Enzymatic synthesis of dextran-containing hydrogels (2002) Biomaterials, 23, pp. 3957-3967;Peppas, N.A., Bures, P., Leobandung, W., Ichikawa, H., Hydrogels in pharmaceutical formulations (2000) Eur J Pharm Biopharm, 50, pp. 27-46; Park, K., Park, H., Biocompatibility issues of implantable drug delivery systems (1996) Pharm Res, 13 (12), pp. 1770-1776; Novick, S.J., Dordick, J.S., Preparation of active and stable biocatalytic hydrogels for use in selective transformation (1998) Chem Mater, 10 (4), pp. 955-958; Letourneur, D., Machy, D., Pellé, A., Marcon-Bachari, E., Dángelo, G., Vogel, M., Chaubert, F., Michel, J.-B., Heparin and non-heparin-like dextrans differentially modulate endothelial cell proliferation: In vitro evaluation with soluble and crosslinked polysaccharide matrices (2002) J Biomed Mater Res, 60, pp. 94-100; Österberg, E., Bergström, K., Holmberg, K., Schuman, T.P., Riggs, J.A., Burns, N.L., Van Alstine, J.M., Harris, J.M., Protein-rejecting ability of surface-bound dextran in end-on and side-on configurations: Comparison to PEG (1995) J Biomed Mater Res, 29, pp. 741-747; Frazier, R.A., Matthijs, G., Davies, M.C., Roberts, C.J., Schacht, E., Tendler, S.J.B., Characterization of protein-resistant dextran monolayers (2000) Biomaterials, 21, pp. 957-966; Massia, S.P., Stark, J., Immobilized RGD peptides on surface-grafted dextran promote biospecific cell attachment (2001) J Biomed Mater Res, 56, pp. 390-399; Wong, W.H., Mooney, D.J., Synthesis and properties of biodegradable polymers used as synthetic matrices for tissue engineering (1997) Synthetic Biodegradable Polymer Scaffolds, p. 50. , Atala A, Mooney DJ, editors. Boston, MA: Birkhäuser; Lee, K.Y., Mooney, D.J., Hydrogels for tissue engineering (2001) Chem Rev, 101 (7), pp. 1869-1879; Hern, D.L., Hubbell, J.A., Incorporation of adhesion peptides into nonadhesive hydrogels useful for tissue resurfacing (1998) J Biomed Mater Res, 39, pp. 266-276; Mann, B.K., Gobin, A.S., Tsai, A.T., Schmedlen, R.H., West, J.L., Smooth muscle cell growth in photopolymerized hydrogels with cell adhesive and proteolytically degradable domains: Synthetic ECM analogs for tissue engineering (2001) Biomaterials, 22, pp. 3045-3051; De Groot, C.J., Van Luyn, M.J.A., Van Dijk-Wolthuis, W.N.E., Cadée, J.A., Plantinga, J.A., Den Otter, W., Hennink, W.E., In vitro biocompatibility of biodegradable dextran-based hydrogels tested with human fibroblasts (2001) Biomaterials, 22, pp. 1197-1203; Cadée, J.A., Luyn, M.J.A., Brouwer, L.A., Plantinga, J.A., Van Wachem, P.B., Groot, C.J., Otter, W., Hennink, W.E., In vivo biocompatibility of dextran-based hydrogels (2000) J Biomed Mater Res, 50, pp. 397-404; Anderson, J.M., In vivo biocompatibility of implantable delivery systems and biomaterials (1994) Eur J Pharm Biopharm, 40 (1), pp. 1-8; Anderson, J.M., Inflammation, wound healing, and the foreign body reaction response (1996) Biomaterials Science, pp. 165-173. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE, editors. New York: Academic Press; (1992) ISO 10993-5: Biological Evaluation of Medical Devices. Test for Cytotoxicity: In Vitro Methods, , Geneva, Switzerland: International Organization for Standardization; Pizzoferato, A., Ciapetti, G., Stea, S., Cenni, E., Arciola, C.R., Granchi, D., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin Mater, 15, pp. 173-190; Bancroft, J.D., Stevens, A., (1996) Theory and Practice of Histological Techniques, pp. 99-211. , Edinburg: Churchill Livingstone; Mosmann, T., Rapid colorimetric assay for cellular growth and survival: Application to proliferation and cytotoxicity assays (1983) J Immunol Methods, 65, pp. 55-63; Moreau, M.F., Chappard, D., Lesourd, M., Monthéard, J.P., Baslé, M.F., Free radicals and side products released during methylmethacrylate are cytotoxic for osteoblastic cells (1998) J Biomed Mater Res, 40, pp. 124-131; Black, J., The inflammatory response (1999) Biological Performance of Materials, p. 131. , Black J, editor. New York: Marcel Dekker; Murch, A.R., Grounds, M.D., Marshall, C.A., Papadimitriou, J.M., Direct evidence that inflammatory multinucleate giant cells form by fusion (1982) J Pathol, 137, pp. 177-180; Kuijpers, A.J., Wachem, P.B., Luyn, M.J.A., Plantinga, J.A., Engbers, G.H.M., Krijgsveld, J., Zaat, S.A.J., Feijen, J., In vivo compatibility and degradation of crosslinked gelatin gels incorporated in knitted Dacron (2000) J Biomed Mater Res, 51, pp. 136-145; Kuijpers, A.J., Van Wachem, P.B., Luyn, M.J.A., Brouwer, L.A., Engbers, G.H.M., Krijgsveld, J., Zaat, S.A.J., Feijen, J., In vitro and in vivo evaluation of gelatin-chondroitin sulphate hydrogels for controlled release of antibacterial proteins (2000) Biomaterials, 21, pp. 1763-1772; Hooper, K.A., Macon, N.D., Kohn, J., Comparative histological evaluation of new tyrosine-derived polymers and poly(L-lactic acid) as a function of polymer degradation (1998) J Biomed Mater Res, 41, pp. 443-454; Bos, R.R.M., Rozema, F.R., Boering, G., Nijenhuis, A.J., Pennings, A.J., Verwey, A.B., Nieuwenhuis, P., Jansen, H.W.B., Degradation of and tissue reaction to biodegradable poly(L-lactide) for use as internal fixation of fractures: A study in rats (1991) Biomaterials, 12, pp. 32-36; Nakamura, T., Veda, H., Tsuda, T., Li, Y.-H., Kiyotani, T., Inoue, M., Matsumoto, K., Shimizu, Y., Long-term implantation test and tumorigenicity of polyvinyl alcohol hydrogel plates (2001) J Biomed Mater Res, 56, pp. 289-296; Dziubla, T.D., Torjman, M.C., Joseph, J.I., Murphy-Tatum, M., Lowman, A.M., Evaluation of porous networks of poly(2-hydroxyethylmethacrylate) as interfacial drug delivery devices (2001) Biomaterials, 22, pp. 2893-2899; Spector, M., Lalor, P.A., In vivo assessment of tissue compatibility (1996) Biomaterials Science, pp. 220-228. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE, editors. New York: Academic Press
Keywords: Acrylates; acrylic acid; animal experiment; animal model; animal tissue; Animals; article; Biocatalytic polyester; Biocompatibility; Biocompatible Materials; Biodegradation, Environmental; Biodiversity; Biomaterials; cell adhesion; Cell Division; cell interaction; cell proliferation; Cells, Cultured; Coenzymes; controlled study; Cytotoxicity; dextran; dextran acrylate; dextran acrylate hydrogel; dextran hydrogel; Dextrans; drug delivery system; Enzymes; fibroblast; Fibroblasts; Fibrous capsules; foreign body reaction; Foreign-Body Reaction; giant cell; human; human cell; Humans; hydrogel; Hydrogels; implantation; Implants (surgical); Implants, Experimental; in vitro study; in vivo study; macrophage; male; materials testing; mechanical stress; Mechanical stresses; metabolism; Mitochondria; mitochondrial respiration; nonhuman; oxygen diffusion; prepuce; rat; Rats; Rats, Wistar; Tissue; Tissue engineering; unclassified drug

Human serum albumin adsorption on TiO 2 from single protein solutions and from plasma - Sousa, S.R.; Moradas-Ferreira, P.; Saramago, B.; Viseu Melo, L.; Barbosa, M.A. (LangmuirLangmuir, 2004)
In the present work, the adsorption of human serum albumin (HSA) on commercially pure titanium with a titanium oxide layer formed in a H 2O 2 solution (TiO 2 cp) and on TiO 2 sputtered on Si (TiO 2 sp) was analyzed. Adsorption isotherms, kinetic studies, and work of adhesion determinations were carried out. HSA exchangeability was also evaluated. Surface characterization was performed by atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), and wettability studies. The two TiO 2 surfaces have very distinct roughnesses, the TiO 2 sp having a mean R a value 14 times smaller than the one of TiO 2 cp. XPS analysis revealed consistent peaks representative of TiO 2 on sputtered samples as well as on Ti cp substrate after 48 h of H 2O 2 immersion. Nitrogen was observed as soon as protein was present, while sulfur, present in disulfide bonds in HSA, was observed for concentrations of protein higher than 0.30 mg/mL. The work of adhesion was determined from contact angle measurements. As expected from the surface free energy values, the work of adhesion of HSA solution is higher for the TiO 2 cp substrate, the more hydrophilic one, and lower for the TiO 2 sp substrate, the more hydrophobic one. The work of adhesion between plasma and the substrates assumed even higher values for the TiO 2 cp surface, indicating a greater interaction between the surface and the complex protein solutions. Adsorption studies by radiolabeling of albumin ( 125I-HSA) suggest that rapid HSA adsorption takes place on both surfaces, reaching a maximum value after ~60 min of incubation. For the higher HSA concentrations in solution, a multilayer coverage was observed on both substrates. After the adsorption step from single HSA solutions, the exchangeability of adsorbed HSA molecules by HSA in solution was evaluated. The HSA molecules adsorbed on TiO 2 sp seem to be more easily exchanged by HSA itself than those adsorbed on TiO 2 cp after 24 h. In contrast, after 72 h, nearly all the adsorbed albumin molecules effectively exchange with other albumin molecules.
Cited By (since 1996): 58Export Date: 21 November 2012Source: ScopusCODEN: LANGDdoi: 10.1021/la049158dPubMed ID: 15491210Language of Original Document: EnglishCorrespondence Address: Sousa, S.R.; Inst. de Engenharia Biomédica, Laboratório Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: ssousa@ibmc.up.ptChemicals/CAS: serum albumin, 9048-46-8; titanium dioxide, 1317-70-0, 1317-80-2, 13463-67-7, 51745-87-0; titanium, 7440-32-6; Serum Albumin; Solutions; titanium dioxide, 13463-67-7; Titanium, 7440-32-6References: Nakabayashi, N., Iwasaki, Y., (2000) European White Book on Fundamental Research in Materials Science, pp. pp70-71. , Rühle, M., Dosch, H., Mittemeijer, E. J.Van de Voorde, M. H., Eds.; Max Plank Institut fur Metallforschung: Stuttgart, Germany;Windler, M., Klabunde, R., (2001) Titanium in Medicine; Material Science, Surface Science, Engineering, Biological Responses and Medical Applications, pp. 703-746. , Brunette, D. M., Tengvall, P., Textor, M., Thomsen, P., Eds.; Springer-Verlag: Berlin, Germany; Larsson, C., Esposito, M., Liao, H., Thomsen, P., (2001) Titanium in Medicine: Material Science, Surface Science, Engineering, Biological Responses and Medical Applications, pp. 587-648. , Brunette, D.M., Tengvall, P., Textor, M., Thomsen, P., Eds.; Springer-Verlag: Berlin, Germany; Tengvall, P., Lundstrom, I., (1992) Clin. Mater., 9, pp. 116-134; Ostumi, E., Chapman, R.G., Liang, M.N., Meluleni, G., Pier, G., Ingberg, D.E., Whitesides, G.M., (2001) Langmuir, 17, pp. 6336-6343; Gehanno, V., Freitas, P.P., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Soares, J.C., Silva, M.F., (1999) IEEE Trans. Magn., 35, pp. 4361-4367; Owens, D.K., Wendt, E.C., (1969) J. Appl. Polym. Sci., 13, pp. 1741-1747; Kerkeb, M.L., González-Caballero, F., Chibowski, E., (1993) J. Colloid Interface Sci., 159, pp. 439-443; (1993) A Guide to Radioiodination Techniques; Amersham Life Science: Little Chalfont, p. 64. , Iodine-125, Buckinghamshire, U.K; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., (2001) J. Biomed. Mater. Res., 55, pp. 45-53; Williams, D.F., Askill, I.N., Smith, R., (1985) J. Biomed. Mater. Res., 19, pp. 313-320; Sheardown, H., Cornelius, R.M., Brash, J.L., (1997) Colloids Surf., B, 10, pp. 29-33; Du, Y.J., Cornelius, R.M., Brash, J.L., (2000) Colloids Surf., 17, pp. 59-67; Yu, X.J., Brash, J.L., (1993) Test Procedures for the Blood Compatibility of Biomaterials, pp. 287-330. , Dawids, S., Ed.; Kluwer Academic Publishers: Dordrecht, The Netherlands; Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., (1985) Anal. Biochem., 150, pp. 76-85; Shirkhanzadeh, M., (1996) J. Mater. Sci.: Mater. Med., 6, pp. 206-210; Kilpadi, D.V., Raikar, G.N., Liu, J., Lemons, J.E., Vohra, Y., Gregory, J.C., (1998) J. Biomed. Mater. Res., 40, pp. 646-659; Lausmaa, J., Kasemo, B., Mattsson, H., (1990) Appl. Surf. Sci., 44, pp. 133-146; Armstrong, N.R., Quinn, R.K., (1977) Surf. Sci., 67, pp. 451-468; Leitao, E., Barbosa, M.A., Degroot, K., (1997) J. Mater. Sci.: Mater. Med., 8, pp. 423-426; Ramqvist, L., Hamrin, K., Johansso, G., Fahlman, A., Nordling, C., (1969) J. Phys. Chem. Solids, 30, pp. 1835-1847; Hanawa, T., Ota, M., (1992) Appl. Surf. Sci., 55, pp. 269-276; Kuznetsov, M.V., Zhuravlev, J.F., Gubanov, V.A., (1992) J. Electron Spectrosc. Relat. Phenom., 58, pp. 169-176; Ikeo, N., Iijima, Y., Niimura, N., Sigematsu, M., Tazava, T., Matsumoto, S., Kojima, K., Nagasawa, Y., (1991) Handbook of X-ray Photo-electron Spectroscopy JEOL, , Tokyo, Japan; Porte-Durrieu, M.C., Labrugere, C., Villars, F., Lefebvre, F., Dutoya, S., Guette, A., Bordenave, L., Baquey, C., (1999) J. Biomed. Mater. Res., 46, pp. 368-375; Wagner, C.D., Riggs, W.M., Davis, L.E., Moulder, J.F., (1979) Handbook of X-ray Photoelectron Spectroscopy, , Mulenberg, G. E., Ed.; Perkin Elmer Corp: Eden Prairie, MN; Barr, T.L., (1991) J. Vac. Sci. Technol., A, 9, pp. 1793-1805; Wälivaara, B., Aronsson, B.O., Rodahl, M., Lausmaa, J., Tengvall, P., (1994) Biomaterials, 15, pp. 827-834; Oji, M.O., Wood, J.V., Downes, S., (1999) J. Mater. Sci.: Mater. Med., 10, pp. 869-872; Pan, J., Liao, H., Leygraf, C., Thierry, D., Li, J., (1998) J. Biomed. Mater. Res., 40, pp. 244-256; Ratner, B.D., Horbett, T.A., Shuttleworth, D., Thomas, H.R., (1981) J. Colloid Interface Sci., 83, pp. 630-642; Lindberg, B., Maripuu, R., Siegbahn, K., Larsson, R., Golander, C.G., Eriksson, J.C., (1983) J. Colloid Interface Sci., 95, pp. 308-321; Auditore, A., Satriano, C., Coscia, U., Ambrosone, G., Parisi, V., Marietta, G., (2002) Biomol. Eng., 19, pp. 85-90; Miller, B., Treppo, S., Voigt, A., Zingg, W., Neumann, A.W., (1993) Colloids Surf., 69, pp. 203-208; Serro, A.P.V., Fernandas, A.C., Saramago, B.D.V., (1997) Colloids Surf., A, 125, pp. 209-219; Lopes, M., Monteiro, F., Santos, J., Serro, A., Saramago, B., (1999) J. Biomed. Mater. Res., 45, pp. 370-375; Ferraz, M.P., Monteiro, F.J., Serro, A.P., Saramago, B., Gibson, I.R., Santos, J.D., (2001) Biomaterials, 22, pp. 3105-3112; Vogler, E.A., (1993) Surfactant Science Series, 49, pp. 183-250. , Wettability; Berg, J. C., Ed.; Marcel Dekker: New York; Feng, B., Weng, J., Yang, B.C., Qu, S.X., Zhang, X.D., (2003) Biomaterials, 24, pp. 4663-4670; Morra, M., Cassinelli, C., Cascardo, G., Cahalan, P., Cahalan, L., Fini, M., Giardino, R., (2003) Biomaterials, 24, pp. 4639-4654; Wälivaara, B., Lundstrom, I., Tengvall, P., (1993) Clin. Mater., 12, pp. 141-148; Lincks, J., Boyan, B.D., Blanchard, C.R., Lohmann, C.H., Liu, Y., Cochran, D.L., Dean, D.D., Schwartz, Z., (1998) Biomaterials, 19, pp. 2219-2232; Ong, J.L., Carnes, D.L., Cardenas, H.L., Cavin, R., (1997) Implant Dent., 6, pp. 19-24; Ricci, J.L., Spivak, J.M., Blumenthal, N.C., (1991) The Bone Biomaterial Interface, pp. 334-349. , Davis, J. E., Ed.; University of Toronto Press: Toronto; Busscher, H.J., Vanpelt, A.W.J., Deboer, P., Dejong, H.P., Arends, (1984) J. Colloids Surf., 9, pp. 319-331; Hitchcock, S.J., Carroll, N.T., Nicholas, M.G., (1981) J. Mater. Sci., 16, pp. 714-732; Rakhorst, G., Van Der Mei, H.C., Van Oeveren, W., Spijker, H.T., Int, B.H.J., (1999) J. Artif. Organs, 22, pp. 35-39; Martins, M.C., Ratner, B.D., Barbosa, M.A., (2003) J. Biomed. Mater. Res., 67 A, pp. 158-171; Sigal, G.B., Mrksich, M., Whitesides, G.M., (1998) J. Am. Chem. Soc., 120, pp. 3464-3473; Prime, K.L., Whitesides, G.M., (1991) Science, 252, pp. 1164-1167; Vandulm, P., Norde, W., (1983) J. Colloid Interface Sci., 91, pp. 248-255; Williams, R.L., Williams, D.F., (1988) J. Colloid Interface Sci., 126, pp. 596-603; Serro, A.P.V.A., Fernandes, A.C., Saramago, B.D.V., Norde, W., (1999) J. Biomed. Mater. Res., 46, pp. 376-381; Norde, W., Anusiem, A.C.I., (1992) Colloids Surf., 86, pp. 73-80; Young, B.R., Pitt, W.G., Cooper, S.L., (1988) J. Colloid Interface Sci., 125, pp. 246-260; Feng, L., Andrade, J.D., (1994) Biomaterials, 5, pp. 323-333; Norde, W., (1986) Adv. Colloid Interface Sci., 25, pp. 267-340; Kurrat, R., Prenosil, J.E., Ramsden, J.J., (1987) J. Colloid Interface Sci., 186, pp. 1-8; Brash, J.L., Uniyal, S., Samak, Q., (1974) Trans. Am. Soc. Artif. Intern. Organs, 20 A, pp. 69-76
Keywords: Adsorption; article; Atomic force microscopy; Blood; chemistry; human; Human serum albumin (HSA); Humans; hydrophobicity; Multilayers; plasma; Plasmas; Plastic surgery; Proteins; Radiolabeling; Serum Albumin; solution and solubility; Solutions; Substrates; Surface characterization; Surface Properties; surface property; Titanium; Titanium dioxide; X ray photoelectron spectroscopy

A model for educational simulation of infant cardiovascular physiology - Goodwin, J.A.; van Meurs, W.L.; Sá Couto, C.D.; Beneken, J.E.W.; Graves, S.A. (Anesthesia and AnalgesiaAnesth. Analg., 2004)
Full-body patient simulators provide the technology and the environment necessary for excellent clinical education while eliminating risk to the patient. The extension of simulator-based training into management of basic and critical situations in complex patient populations is natural. We describe the derivation of an infant cardiovascular model through the redefinition of a complete set of parameters for an existing adult model. Specifically, we document a stepwise parameter estimation process, explicit simplifying assumptions, and sources for these parameters. The simulated vital signs are within the target hemodynamic variables, and the simulated systemic arterial pressure wave form and left ventricular pressure volume loop are realistic. The system reacts appropriately to blood loss, and incorporation of aortic stenosis is straightforward. This infant cardiovascular model can form the basis for screen-based educational simulations. The model is also an essential step in attaining a full-body, model-driven infant simulator.
Cited By (since 1996): 19Export Date: 21 November 2012Source: ScopusCODEN: AACRAdoi: 10.1213/01.ANE.0000134797.52793.AFPubMed ID: 15562049Language of Original Document: EnglishCorrespondence Address: Goodwin, J.A.; Nemours Children's C., 807 Children's Way, Jacksonville, FL 32207, United States; email: jgoodwin@nemours.orgReferences: Good, M.L., Gravenstein, J.S., Training for safety in an anesthesia simulator (1993) Semin Anesth, 12, pp. 235-250;Gaba, D.M., DeAnda, A., The response of anesthesia trainees to simulated critical incidents (1989) Anesth Analg, 68, pp. 444-451; Howard, S.K., Gaba, D.M., Fish, K.J., Anesthesia crisis resource management training: Teaching anesthesiologists to handle critical incidents (1992) Aviat Space Environ Med, 63, pp. 763-770; Euliano, T.Y., Caton, D., Van Meurs, W., Good, M.L., Modeling obstetric cardiovascular physiology on a full-scale patient simulator (1997) J Clin Monit, 13, pp. 293-297; Halamek, L.P., Kaegi, D.M., Gaba, D.M., Time for a new paradigm in pediatric medical education: Teaching neonatal resuscitation in a simulated delivery room environment (2000) Pediatrics, 106, pp. E45; Beneken, J.E.W., (1965) A Mathematical Approach to Cardiovascular Function: The Uncontrolled Human System, , [PhD thesis]. Medisch Fysisch Institut TNO, Utrecht, The Netherlands; Beneken, J.E.W., DeWit, B., A physical approach to hemodynamic aspects of the human cardiovascular system (1967) Physical Bases of Circulatory Transport: Regulation and Exchange, pp. 1-45. , Reeve EB, Guyton AC, eds. Philadelphia: Saunders; Wesseling, K.H., Settels, J.J., Baromodulation explains short-term blood pressure variability (1985) Psychophysiology of Cardiovascular Control, pp. 69-97. , Orlebeke JF, Mulder G, van Doornen LJP, eds. New York: Plenum Press; Van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit, 13, pp. 317-324; Pruitt, A.W., Gersony, W.M., The cardiovascular system (1992) Nelson Textbook of Pediatrics. 14th Ed., pp. 1125-1227. , Behrman RE, ed. Philadelphia: Saunders; Gregory, G.A., Monitoring during surgery (1994) Pediatric Anesthesia, pp. 261-279. , Gregory GA, ed. New York: Churchill Livingstone; Graham Jr., T.P., Jarmakani, M.M., Evaluation of ventricular function in infants and children (1971) Pediatr Clin North Am, 18, pp. 1109-1132; Wodey, E., Plady, P., Copin, C., Comparative hemodynamic depression of sevoflurane versus halothane in infants (1997) Anesthesiology, 87, pp. 795-800; Suga, H., Sagawa, K., Shoukas, A.A., Load independence of the instantaneous pressure-volume ratio of the canine left ventricle and effects of epinephrine and heart rate on the ratio (1973) Circ Res, 2, pp. 314-322; Ten Voorde, B., (1992) Modeling the Baroreflex: A System Analysis Approach, , [PhD thesis]. Vakgroep Medische Fysica, Amsterdam, The Netherlands; Cunningham, M.D., Bedside pulmonary function testing of infants (1990) Essentials of Pediatric Intensive Care, pp. 878-883. , Levin DL, Morriss FC, eds. St. Louis: Quality Medical; Strafford, M.A., Cardiovascular physiology (1996) Smith's Anesthesia for Infants and Children, pp. 69-104. , Motoyama EK, Davis PJ, eds. St. Louis: Mosby; Lake, C.L., Cardiovascular anatomy and physiology (1992) Clinical Anesthesia, pp. 989-1020. , Barash PG, Cullen BF, Stoelting RK, eds. Philadelphia: Lippincott; Hsieh, K., Chen, P., Fu, S., A simple, noninvasive method to investigate vascular characteristics in children (1996) Angiology, 47, pp. 361-367; Stoelting, R.K., Miller, R.D., (2000) Basics of Anesthesia, pp. 364-375. , Philadelphia: Churchill Livingstone; Thilenius, O.G., Argilla, R.A., Angiographic right and left ventricular volume determination in normal infants and children (1974) Pediatr Res, 8, pp. 67-74; Drouin, E., Gournay, V., Calamel, J., Assessment of spontaneous baroreflex sensitivity in neonates (1997) Arch Dis Child Fetal Neonatal Ed, 76, pp. F108-12
Keywords: aging; Algorithms; Anesthesiology; aorta stenosis; Aortic Valve Stenosis; arterial pressure; article; Baroreflex; biological model; bleeding; Blood Loss, Surgical; cardiovascular function; Cardiovascular physiology; Computer simulation; education; heart ventricle pressure; hemodynamic parameters; Hemodynamic Processes; Humans; Infant; Models, Biological; priority journal; Pulmonary Circulation; simulation; Ventricular Function, Left; Ventricular Function, Right

Adhesion of human leukocytes to biomaterials: An in vitro study using alkanethiolate monolayers with different chemically functionalized surfaces - Barbosa, J.N.; Barbosa, M.A.; Água, A.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2003)
The adhesion of human leukocytes to self-assembled monolayers of well-defined surface chemistry was investigated in vitro. Polymorphonuclear (PMN) and mononuclear leukocytes were isolated from human blood by centrifugation techniques. The effect on adhesion of cell activation produced by pre-incubation of leukocytes with phytohemagglutinin (PHA) and phorbol 12-myristate 13-acetate (PMA) was also studied. Gold substrates were modified by treatment with alkanethiols with three different terminal chemical groups: COOH, OH, and CH 3. After incubation with the two subpopulations of leukocytes, the monolayers were washed, treated with fixative, stained with a Giemsa method, and observed by light microscopy to quantify the number of attached leukocytes. Comparative quantification of the density of leukocyte adhesion to the three types of self-assembled monolayers was determined. The hydrophobic surface expressing CH 3 was found to be the one that induced the highest adhesion density of leukocytes, both of PMN and mononuclear cells. In vitro activation of both mononuclear and PMN leukocytes further increased cell adhesion to the chemically defined monolayers that were used. This enhancement was higher for PHA-activated than for PMA-stimulated mononuclear cells, whereas PMA treatment of neutrophils resulted in a higher rate of adhesion of these cells than PHA stimulation. © 2003 Wiley Periodicals, Inc.
Cited By (since 1996): 24Export Date: 21 November 2012Source: ScopusCODEN: JBMRCLanguage of Original Document: EnglishCorrespondence Address: Barbosa, J.N.; INEB-Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: judite@ibmc.up.ptChemicals/CAS: gold, 7440-57-5; hydroxide, 14280-30-9; methane, 74-82-8; phorbol 12 acetate 13 myristate, 31365-46-5; phytohemagglutinin, 9008-97-3; phorbol 13 acetate 12 myristate, 16561-29-8; Biocompatible Materials; Gold, 7440-57-5; Phytohemagglutinins; Tetradecanoylphorbol Acetate, 16561-29-8References: Jones, D.A., Smith, C.W., McIntire, L.V., Leucocyte adhesion under flow conditions: Principles importante in tissue engineering (1996) Biomaterials, 17, pp. 337-347;Marchant, R.E., Cell adhesion and interactions with biomaterials (1984) J Adhes, 20, pp. 211-225; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Brunstedt, M.R., Anderson, J.M., Spilizewski, K.L., Marchant, R.E., Hiltner, A., In vivo leucocyte interactions on Pellethane surfaces (1990) Biomaterials, 11, pp. 370-378; Kao, W.J., Evaluation of leukocyte adhesion on polyurethanes: The effects of shear stress and blood proteins (2000) Biomaterials, 21, pp. 2295-2303; Lim, F., Cooper, S.L., Effect of sulphonate incorporation on in vitro leucocyte adhesion to polyuretanes (1995) Biomaterials, 16, pp. 457-466; Tomczok, J., Sliwa-Tomczok, W., Klein, C.L., Van Kooten, T.G., Kirkpatrick, C.J., Biomaterial-induced alterations of human neutrophils under fluid shear stress: Scanning electron microscopical study in vitro (1996) Biomaterials, 17, pp. 1359-1367; Yun, J.K., DeFife, K., Colton, E., Stack, S., Azeez, A., Cahalan, L., Verhoeven, M., Anderson, J.M., Human monocyte/macrophage adhesion and cytokine production on surface-modified poly(tetrafluoroethylene/hexafluoropropylene) polymers with and without protein preadsorption (1995) J Biomed Mater Res, 29, pp. 257-268; Mrksich, M., Whitesides, G.M., Interactions of SAMs with proteins (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-57; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Mrkisich, M., Tailored substrates for studies of attached cell culture (1998) Cell Mol Life Sci, 54, pp. 653-662; Kane, R.S., Takayama, S., Ostuni, E., Ingber, D.E., Whitesides, G.M., Patterning proteins and cells using soft lithography (1999) Biomaterials, 20, pp. 2363-2376; Mrksich, M., Using self-assembled monolayers to understand the biomaterials interface (1997) Curr Opin Colloid Int Sci, 2, pp. 83-88; Margel, S., Vogler, E.A., Firment, L., Watt, T., Haynie, S., Sogah, D.Y., Peptide, protein, and cellular interactions with self-assembled monolayer model surfaces (1993) J Biomed Mater Res, 27, pp. 1463-1476; Prime, K.L., Whitesides, G.M., Self assembled organic monolayers model systems for studying the adsorption of proteins at surfaces (1991) Science, 252, pp. 1164-1167; Lopez, G.P., Albers, M.W., Schreiber, S.L., Carroll, R., Peralta, E., Whitesides, G.M., Convenient methods for patterning the adhesion of mammalian cells to surfaces using self-assembled monolayers of alkane thiolates on gold (1993) J Am Chem Soc, 115, pp. 5877-5878; Shinghvi, R., Kumar, A., Lopez, G.P., Stephanopoulos, G.N., Wang, D.I.C., Whitesides, G.M., Ingber, D.E., Engineering cell shape and function (1994) Science, 264, pp. 696-698; Pan, S., Castner, D.G., Ratner, B.D., Multitechnique surface characterization of derivatization efficiencies for hydroxyl-terminated self-assembled monolayers (1998) Langmuir, 14, pp. 3545-3550; Lin, J., Chuang, W., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionality (2000) J Biomed Mater Res, 51, pp. 413-423; Lindblad, M., Lestelius, M., Johansson, A., Tengvall, P., Thomsen, P., Cell and soft tissue interactions with methyl- and hydroxyl-terminated alkane thiols on gold surfaces (1997) Biomaterials, 18, pp. 1059-1068; Baker, L.C., Davis, W.C., Autieri, J., Watach, M.J., Yamazaki, K., Litwak, P., Wagner, W.R., Flow cytometric assays to detect platelet activation and aggregation in device-implanted calves (1998) J Biomed Mater Res, 41, pp. 312-321; English, D., Andersen, B.R., Single-step separation of red blood cells. Granulocytes and mononuclear leukocytes on discontinuous density gradient of ficoll-hypaque (1974) J Immunol Methods, 5, pp. 249-253; Nygren, H., Hrustic, E., Karlsson, C., Öster, L., Respiratory burst response of peritoneal leukocytes adhering to titanium and stainless steel (2001) J Biomed Mater Res, 57, pp. 238-247; Gorbet, M.B., Yeo, E.L., Sefton, M.V., Flow cytometric study of in vitro neutrophil activation by biomaterials (1999) J Biomed Mater Res, 44, pp. 289-297; Källtrorp, M., Askendal, A., Thompsen, P., Tengvall, P., Inflammatory cell recruitment, distribution, and chemiluminescence response at IgG precoated- and thiol functionalized gold surfaces (1999) J Biomed Mater Res, 47, pp. 251-259; Mahiout, A., Courtney, J.M., Effect of dialyser membranes on extracellular and intracellular granulocyte and monocyte activation in ex vivo pyrogen-free conditions (1994) Biomaterials, 15, pp. 969-980; Davis, R.G., Goodman, S.B., Smith, R.L., Lerman, J.A., Williams III, R.J., The effects of bone cement powder on human adherent monocytes/ macrophages in vitro (1993) J Biomed Mater Res, 27, pp. 1039-1046; Gery, I., Gerhon, R.K., Waskman, B., Potentiation of the T lymphocyte response to mitogens. I. The responding cell (1972) J Exp Med, 136, pp. 128-134; Peters, S.P., Cerasoli Jr., F., Albertine, K.H., Gee, M.H., Berd, D., Ishihara, Y., "Autoregulation" of human neutrophil activation in vitro: Regulation of phorbol myristate acetate-induced neutrophil activation by cell density (1990) J Leukocyte Biol, 47, pp. 457-474; Esaguy, N., Águas, A.P., Vilanova, M., Silva, M.T., Activation of human neutrophils by phorbol ester decreases the cytoplasm compactness and the lactoferrin content of the granulocytes (1991) J Leukocyte Biol, 50, pp. 444-452; Collins, D.P., Cytokine and cytokine receptor expression as a biological indicator of immune activation: Important considerations in the development of in vitro model systems (2000) J Immunol Methods, 243, pp. 125-145; Ruoslahti, E., Integrin signaling and matrix assembly (1996) Tumor Biol, 17, pp. 117-128; Aoudjit, F., Vuori, K., Engagement of the α2β1 integrin inhibits Fas ligand expression and activation-induced cell death in T cells in a focal adhesion kinase-dependent manner (2000) Blood, 95, pp. 2044-2051; Lehr, H.A., Krombach, F., Munzing, S., Bodlaj, R., Glaubitt, S.I., Seiffge, D., Hubner, C., Messmer, K., In vitro effects of oxidized low density lipoprotein on CD11b/CD18 and L-selectin presentation on neutrophils and monocytes with relevance for the in vivo situation (1995) Am J Pathol, 146, pp. 218-227; Kansas, G.S., Tedder, T.F., Transmembrane signals generated through MHC class II, CD19, CD20, CD39, and CD40 antigens induce LFA-1-dependent adhesion in human B cells through a tyrosine kinase-dependent pathway (1991) J Immunol, 147, pp. 4094-4102; Damle, N.K., Eberhardt, C., Van Der Vieren, M., Direct interactions with primed CD4+ CD45R0+ memory T lymphocytes induces expression of endothelial leukocyte adhesion molecule-1 and vascular cell adhesion molecule-1 on the surface of vascular endothelial cells (1991) Eur J Immunol, 21, pp. 2915-2923; Murata, S., Tanaka, T., Miysaka, M., Lymphocyte binding to MAd-CAM-1 via α4β7 integrin activates a signal transduction pathway involving tyrosine phosphorylation of paxillin and p105 Cas-L (2002) Immunol Lett, 81, pp. 223-228; Roth, S.J., Carr, M.W., Rose, S.S., Springer, T.A., Characterization of transendothelial chemotaxis of T lymphocytes (1995) J Immunol Methods, 188, pp. 97-116; Aziz, K.E., Wakefield, D., In vivo and in vitro expression of adhesion molecules by peripheral blood lymphocytes from patients with primary Sjogren's syndrome: Culture-associated enhancement of LECAM-1 and CD4 (1995) Rheumatol Int, 15, pp. 69-74; Tengvall, P., Lundstrom, I., Liedberg, B., Protein adsorption studies on model organic surfaces: An ellipsometric and infrared spectroscopic approach (1998) Biomaterials, 19, pp. 407-422; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalised self-assembled monolayers of alkanethiols on gold (1997) Langmuir, 13, pp. 3404-3413; Tsai, M., Lin, J., Surface characterization and platelet adhesion studies of self-assembled monolayer with phosphonate ester and phosphonic acid functionalities (2001) J Biomed Mater Res, 55, pp. 554-565; Franco, M., Nealy, P.F., Campbell, S., Teixeira, A.I., Murphy, C.J., Adhesion and proliferation of corneal epithelial cells on self-assembled monolayers (2000) J Biomed Mater Res, 52, pp. 261-269; Scotchford, C.A., Gilmore, C.P., Cooper, E., Leggett, G.J., Downes, S., Protein adsorption and human osteoblast-like cell attachment and growth on alkylthiol on gold self-assembled monolayers (2002) J Biomed Mater Res, 59, pp. 84-99; Silin, V., Weetall, H., Vanderah, D.J., SPR studies of the non-specific adsorption kinetics of human IgG and BSA on gold surfaces modified by self-assembled monolayers (SAMs) (1997) J Colloid Interface Sci, 185, pp. 94-103
Keywords: alkane derivative; article; Biocompatible Materials; biomaterial; Biomaterials; Blood; carboxyl group; cell adhesion; cell interaction; cell isolation; cell subpopulation; cell surface; Cell-surface interactions; Cells; Centrifugation; controlled study; drug effect; Giemsa stain; gold; human; human cell; Humans; hydrophobicity; hydroxide; in vitro study; Incubation; lectin; Lectins; leukocyte; Leukocyte activation; leukocyte adherence; Leukocyte adhesion; Leukocytes; Leukocytes, Mononuclear; materials testing; methane; microscopy; Monolayers; mononuclear cell; neutrophil; Neutrophils; Optical microscopy; phorbol 12 acetate 13 myristate; phorbol 13 acetate 12 myristate; physiology; phytohemagglutinin; Phytohemagglutinins; polymorphonuclear cell; Self-assembled monolayers; Surface Properties; surface property; Tetradecanoylphorbol Acetate; thiolacid

Albumin adsorption on alkanethiols self-assembled monolayers on gold electrodes studied by chronopotentiometry - Martins, M.C.L.; Fonseca, C.; Barbosa, M.A.; Ratner, B.D. (BiomaterialsBiomaterials, 2003)
Chronopotentiometry was used to study the adsorption of human serum albumin (HSA) to self-assembled monolayers with the following terminal functional groups: CH 3, COOH and OH. Surfaces were characterized by X-ray photoelectron spectroscopy, water contact angle measurements and cyclic voltammetry. HSA coverage of the different SAMs was investigated by chronopotentiometry and the total amount of adsorbed protein was determined using radiolabelled albumin. Both techniques have demonstrated that HSA adsorption to the different SAM-modified electrodes increases in the following order: OH<COOH<CH 3-terminated SAMs. A good correlation between coverage and total amount of HSA adsorbed was observed for long adsorption times (900s). © 2003 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(03)00244-8PubMed ID: 12818541Language of Original Document: EnglishCorrespondence Address: Martins, M.C.L.; INEB - Inst. de Engenharia Biomed., Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cmartins@ibmc.up.ptChemicals/CAS: gold, 7440-57-5; thiol derivative, 13940-21-1; water, 7732-18-5; Albumins; Alkanes; Biocompatible Materials; Gold, 7440-57-5; Serum Albumin; Sulfhydryl CompoundsReferences: Ratner, B.D., Hoffman, A.S., Schoen, F.J., Lemons, J.L., (1996) Biomaterials science - an introduction to materials in medicine, , San Diego, CA, USA: Academic Press;Nakanishi, K., Sakiyama, T., Imamura, K., On the adsorption of proteins on solid surfaces, a common but very complicated phenomenon (2001) J Biosci Bioeng, 91, pp. 233-244; Mrksich, M., Whitesides, G.M., Using self-assembled monolayers to understand the interactions of man-made surfaces with proteins and cells (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-78; Sigal, G.B., Mrksich, M., Whitesides, G.M., Effect of surface wettability on the adsorption of proteins and detergents (1998) J Am Chem Soc, 120, pp. 3464-3473; Taborelli, M., Eng, L., Descouts, P., Ranieri, J.P., Bellamkonda, R., Aebisher, P., Bovine serum albumin conformation on methyl and amine functionalized surfaces compared by scanning force microscopy (1995) J Biomed Mater Res, 29, pp. 707-714; Silin, V., Weetall, H., Vanderah, D., SPR studies of the nonspecific adsorption kinetics of human IgG and BSA on gold surfaces modified by self-assembled monolayers (SAMs) (1997) J Colloid Interface Sci, 185, pp. 94-103; Margel, S., Vogler, E.A., Firment, L., Watt, T., Haynie, S., Sogah, D.Y., Peptide, protein, and cellular interactions with self-assembled monolayer model surfaces (1993) J Biomed Mater Res, 27, pp. 1463-1476; Wadu-Mesthrige, K., Amro, N.A., Liu, G., Immobilization of proteins on self-assembled monolayers (2000) Scanning, 22, pp. 380-388; Takahara, A., Hara, Y., Kojio, K., Kajiyama, T., Plasma protein adsorption behaviour onto the surface of phase-separated organosilane monolayers on the basis of scanning force microscopy (2002) Colloids Surf B: Biointerfaces, 23, pp. 141-152; Kalltorp, M., Carlén, A., Thomsen, P., Olsson, J., Tengvall, P., Analysis of rat plasma proteins desorbed from gold and methyl- and hydroxyl-terminated alkane thiols on gold surfaces (2000) J Mater Sci: Mater Med, 11, pp. 191-199; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Endothelial cell growth and protein adsorption on terminal functionalized, self-assembled monolayers of alkanethiolates on gold (1997) Langmuir, 13, pp. 3404-3413; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) J Am Chem Soc, 111, pp. 321-335; Ulman, A., (1991) An introduction to ultrathin organic films: From Langmuir-Blodgett to self-assembled, , San Diego, CA, USA: Academic Press; Lin, J., Chuang, W., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionlity (2000) J Biomed Mater Res, 51, pp. 413-423; Mirsky, V.M., Riepl, M., Wolfbeis, O.S., Capacitive monitoring of protein immobilization and antigen/antibody reactions on monomolecular alkylthiol films on gold electrodes (1997) Biosensors Bioelectron, 12, pp. 977-989; Viana, A.S., Jones, A.H., Abrantes, L.M., Kalaji, M., Redox induced orientational changes in a series of short chain ferrocenyl alkyl thiols self-assembled on gold(1 1 1) electrodes (2001) J Electroanal Chem, 500, pp. 290-298; Kondo, T., Okamura, M., Uosaki, K., Anion effect on the electrochemical characteristics of a gold electrode modified with a self-assembled monolayer of ferrocenylhexanethiol in aqueous and dichlomethane solutions (2001) J Organometal Chem, 637-639, pp. 841-844; Dong, S., Li, J., Self-assembled monolayers of thiols on gold electrodes for bioelectrochemistry and biosensors (1997) Bioelectrochem Bioenergetics, 42, pp. 7-14; Gooding, J.J., Hibbert, D.B., The application of alkanethiol self-assembled monolayers to enzyme electrodes (1999) Trends Anal Chem, 18, pp. 525-533; Spangler, B.D., Tyler, B.J., Capture agents for quartz crystal microbalance-continuous flow biosensor: Functionalized self-assembled monolayers on gold (1999) Anal Chem Acta, 399, pp. 51-62; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Tengvall, P., Lundstrom, I., Liedberg, B., Protein adsorption studies on model organic surfaces: An ellipsometric and infrared spectroscopic approach (1998) Biomaterials, 19, pp. 407-422; Shen, D., Huang, M., Chow, L., Yang, M., Kinetic profile of the adsorption and conformational change of lysozyme on self-assembled monolayers as revealed by quartz crystal resonator (2001) Sensor Actuators B, 77, pp. 664-670; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Silva, M.F., Ion beam deposition of Mn-Ir spin valves (1999) IEEE Trans Magn, 35, pp. 4361-4367; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of biocompatibility tests, 2, pp. 183-214. , Williams D.F. Harcover: CRC Press; Du, Y.J., Cornelius, R.M., Brash, J.L., Measurement of protein adsorption to gold surface by radioiodination methods: Suppression of free iodide sorption (2000) Colloid Surf B, 17, pp. 59-67; Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., Measurement of protein using bicinchoninic acid (1985) Anal Biochem, 150, pp. 756-785; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., Interactions between calcium, phosphate, and albumin on the surface of titanium (2001) J Biomed Mater Res, 55, pp. 45-53; (1993) Iodine-125. A Guide to Radioiodination Techniques, p. 64. , Amersham Life Science. Little Chalfort, UK: Amersham International plc; Bain, C.D., Evall, J., Whitesides, G.M., Formation of monolayer coadsorption of thiols on gold: Variation in the head group, tail group and solvent (1989) J Am Chem Soc, 111, pp. 7155-7164; Castner, D.G., Hinds, K., Grainger, D.W., X-ray photoelectron spectroscopy sulfur 2p study of organic thiol and disulfide binding interactions with gold surfaces (1996) Langmuir, 12, pp. 5083-5086; Keller, H., Schrepp, W., Fuchs, H., Self-assembled organic films on gold and silver (1992) Thin Solid Films, 210-211, pp. 799-802; Chidsey, C.E.D., Loiacono, D.N., Chemical functionality in self-assembled monolayers: Structural and electrochemical properties (1990) Langmuir, 6, pp. 682-691; Porter, M.D., Bright, T.B., Allara, D.L., Chidsey, C.E.D., Spontaneously organized molecular assemblies. 4. Structural characterization of n-alkyl thiol monolayers on gold by optical ellipsometry, infrared spectroscopy and electrochemistry (1987) J Am Chem Soc, 109, pp. 3559-3568; Miller, C., Cuendet, P., Gratzel, M., Adsorbed ω-hydroxy thiol monolayers on gold electrodes: Evidence for electron tunneling to redox species in solution (1991) J Phys Chem, 95, pp. 877-886; Krysinski, P., Brzostowska-Smolska, M., Capacitance characteristics of self-assembled monolayers on gold electrode (1998) Bioelectrochem Bioenergetics, 44, pp. 163-168; Guo, B., Anzai, J., OSA, T., Adsorption behaviour of serum albumin on electrodes surfaces and the effects of electrode potential (1996) Chem Pharm Bull, 44, pp. 800-803; Dent, A.H., Aslam, M., Other categories of protein coupling (1998) Bioconjugation, protein coupling techniques for the biomedical sciences, pp. 504-569. , M. Aslam, & A.H. Dent. London: Macmillan; Seigal, R.R., Harder, P., Dahint, R., Grunze, M., On-line detection of nonspecific protein adsorption at artificial surfaces (1997) Anal Chem, 69, pp. 3321-3328; Norde, W., Giacomelli, C.E., BSA structural changes during homomolecular exchange between the adsorbed and the dissolved states (2000) J Biotechnol, 79, pp. 259-268; Peters T., Jr., (1996) All about albumin: Biochemistry, genetics, and medical applications, , San Diego, CA, USA: Academic Press; Feng, L., Andrade, J.D., Protein adsorption on low temperature isotropic carbon. III. Isoterms, competitivity, desorption and exchange of albumin and fibrinogen (1994) Biomaterials, 15, pp. 323-333
Keywords: Adsorption; Albumin; Albumin adsorption; Albumins; alkane; Alkanes; article; Biocompatible Materials; biomaterial; Biomaterials; carboxyl group; Chemical modification; Chronopotentiometry; Contact angle; correlation analysis; cyclic potentiometry; Cyclic voltammetry; electrochemistry; electrode; Electron Probe Microanalysis; Functional groups; gold; Humans; hydroxyl group; isotope labeling; methyl group; Monolayers; potentiometry; priority journal; protein analysis; Self assembly; Self-assembled monolayers; Serum Albumin; Sulfhydryl Compounds; Surface modification; Surface Properties; surface property; temperature; thiol derivative; Time Factors; Water; X ray photoelectron spectroscopy

Albumin and fibrinogen adsorption on PU-PHEMA surfaces - Martins, M.C.L.; Wang, D.; Ji, J.; Feng, L.; Barbosa, M.A. (BiomaterialsBiomaterials, 2003)
Materials that adsorb specific proteins may find a variety of applications in the biomedical field. The aim of this study was the preparation of a hydrophilic surface, with low protein adsorption, to be used in the future as a support for the immobilisation of several species, e.g. Cibacron Blue F3G-A, which has been described to induce specific albumin adsorption. Poly(hydroxyethylmethacrylate) (PHEMA) and poly(hydroxyethylacrylate) (PHEA) were chosen as the hydrophilic surface because they can be easily polymerised and possess hydroxyl groups that can be used for the immobilisation of different compounds. Thin films of PHEMA and PHEA were successfully graft polymerised onto the surface of a commercial poly(etherurethane) (PU) using ceric ion as initiator. Grafting polymerisations were followed by mass gain and attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR). Since stability tests demonstrated that only PU-PHEMA was stable in alkaline solutions, a necessary condition to future immobilisations, the investigation was focused on the coating of PU with PHEMA. PU-PHEMA films were characterised in detail using several techniques as mass gain, ATR-FTIR, contact angle measurements, X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). Protein adsorption was evaluated using radiolabelled albumin and fibrinogen from pure solutions and from mixtures of both proteins. PU surfaces modified with PHEMA have demonstrated low protein adsorption, showing their potential use as substrates. This opens the possibly of exploring the advantages of selective adsorption by appropriate immobilisation of specific molecules. © 2003 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 41Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(03)00002-4PubMed ID: 12628827Language of Original Document: EnglishCorrespondence Address: Martins, M.C.L.; Laboratório de Biomateriais, Inst. de Engenharia Biomédica, Rua do Campo Algre 823, Porto 4150-180, Portugal; email: cmartins@ibmc.up.ptChemicals/CAS: acrylic acid ethyl ester, 140-88-5; fibrinogen, 9001-32-5; poly(2 hydroxyethyl acrylate), 26022-14-0; polyetherurethan, 76600-67-4; polymacon, 25053-81-0, 25249-16-5, 98932-78-6; protein, 67254-75-5; Albumins; Biocompatible Materials; Fibrinogen, 9001-32-5; poly(2-hydroxyethyl acrylate), 26022-14-0; Polyhydroxyethyl Methacrylate, 25249-16-5; Water, 7732-18-5References: Ratner, B.D., Hoffman, A.S., Schoen, F.J., Lemons, J.L., (1996) Biomaterials science - An introduction to materials in medicine, , CA, USA, San Diego: Academic Press;Greco, R.S., (1994) Implantation biology, the host response and biomedical devices, , Ann Arbour, USA: CRC Press; Sapatnekar, S., Anderson, J.M., Hemocompatibility: Effects on humoral elements (1999) Handbook of biomaterials evaluation, Scientific technical and clinical testing of implant materials, pp. 353-365. , A.F. von Recum. Philadelphia, PA, USA: Taylor & Francis; Lopez, G.P., Ratner, B.D., Tidwell, C.D., Haycox, C.L., Rapoza, R.J., Horbett, T.A., Glow discharge plasma deposition of tetraethylene glycol dimethyl ether for fouling-resistant biomaterials surfaces (1992) J Biomed Mater Res, 26, pp. 415-439; Johnston, E.E., Bryers, J.D., Ratner, B.D., Interactions between Pseudomonas Aeruginosa and plasma-deposited PEO-like thin films during initial attachment and growth (1997) ACS Polym Prep, 38, pp. 1016-1017; Kottke-Marchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., Effect of albumin coating on the in vitro blood compatibility of Dacron arterial prostheses (1998) Biomaterials, 10, pp. 147-155; Sapatnekar, S., Kieswetter, K.M., Merritt, K., Anderson, J.M., Cahalan, L., Verhoeven, M., Hendriks, M., Cahalan, P., Blood-biomaterial interactions in a flow system in the presence of bacterial, effect of protein adsorption (1995) J Biomed Mater Res, 29, pp. 247-256; Paulsson, M., Kober, M., Freij-Larsson, C., Stollenwerk Wesslén, B., Ljungh, Å., Adhesion of staphylococci to chemically modified and native polymers, and the influence of preadsorbed fibronectin, vitronectin and fibrinogen (1993) Biomaterials, 14, pp. 845-853; Keogh, J.R., Eaton, J.W., Albumin binding surfaces for biomaterials (1994) J Lab Clin Med, 121, pp. 537-545; Keogh, J.R., Velander, F.F., Eaton, J.W., Albumin-binding surfaces for implantable devices (1992) J Biomed Mater Res, 26, pp. 441-456; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., Alkyl substituted polymers with enhanced albumin affinity (1981) Trans Am Soc Artif Intern Organs, 27, pp. 499-503; Kamath, K.R., Park, K., Surface modification of polymeric biomaterials by albumin grafting using y-radiation (1994) J Appl Biomater, 5, pp. 163-173; McFarland, C.D., Filippis, C.D., Jenkins, M., Tunstell, A., Rhodes, N.P., Williams, D.F., Steele, J.G., Albumin binding surfaces: In vitro activity (1998) J Biomat Sci Polymer Ed, 9, pp. 1239-1277; Ji, J., Feng, L., Barbosa, M.A., Stearyl poly(ethylene oxide) grafted surfaces for preferential adsorption of albumin (2001) Biomaterials, 22, pp. 3015-3023; Tsai, C.C., Huo, H.H., Kulkarni, P., Eberhart, R.C., Biocompatible coatings with high albumin affinity (1990) ASAIO Trans, 36, pp. 307-M310; Bekos, E.J., Ranieri, J.P., Aebisher, P., Gardella J.A., Jr., Bright, F.V., Structural changes of bovine serum albumin upon adsorption to modified fluoropolymer substrates used for neural cell attachment studies (1995) Langmuir, 11, pp. 984-989; Bailly, A., Laurent, A., Lu, H., Elalami, I., Jacob, P., Mundler, O., Merland, J., Soria, C., Fibrinogen binding and platelet retention: Relationship with the thrombogenicity of catheters (1996) J Biomed Mater Res, 30, pp. 101-108; Montheard, J.P., Chatzopoulos, M., Chappard, D., 2-Hydroxyethyl methacrylate (HEMA): Chemical properties and applications in biomedical fields (1992) J M S-Rev Macromol Chem Phys, C32, pp. 1-34; Feng, X.D., Sun, Y.H., Qiu, K.Y., Reactive site and Mechanism of graft copolymerisation onto poly(ether urethane) with Ceric ion as initiator (1985) Macromolecules, 18, pp. 2105-2109; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of biocompatibility tests, 2, pp. 183-214. , Williams DF, editor. Harcover: CRC Press; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., Interactions between calcium, phosphate, and albumin on the surface of titanium (2001) J Biomed Mater Res, 55, pp. 45-53; (1993) Iodine-125. A Guide to Radioiodination Techniques, p. 64. , Amersham Life Science, Little Chalfont, England: Amersham International plc; Schrader, B., (1995) Infrared and Raman spectroscopy: methods and applications, , Weinheim: VCH Publishers, Inc., (Federal Republic of German); Lamba, N.M.K., Woodhouse, K.A., Cooper, S.L., (1998) Polyurethanes in biomedical applications, , Boca Raton, FL, USA: CRC Press; Bandekar, J., Sawyer, A., FT-IR spectroscopic studies of polyurethanes: IV studies of the effect of the presence of processing aids on the hemocompatibility of polyurethanes (1995) J Biomater Sci Polym Ed, 7, pp. 485-501; Tingey, K.G., Andrade, J.D., McGary C.W., Jr., Zdrahala, R.J., Surface analysis of commercial biomedical polyurethanes (1988) Polymer surface dynamics, , Andrade JD, editor. New York: Plenum Press; Beamson, G., Briggs, D., (1992) High resolution XPS of organic polymers - the scienta ESCA300 database, , Chichester, England: Wiley; Hsiue, G., Lee, S., Wang, C., Shiue, M.H., Chang, P.C., Plasma-induced graft copolymerisation of HEMA onto silicone rubber and TPX film improving rabbit corneal epithelial cell attachment and growth (1994) Biomaterials, 15, pp. 163-171; Lee, J.H., Ju, Y.M., Lee, W.K., Park, K.D., Kim, Y.H., Platelet adhesion onto segmented polyurethane surfaces modified by PEO - And sulfonated PEO-containing block copolymer additives (1998) J Biomed Mater Res, 40, pp. 314-323; Morra, M., Occhiello, E., Garbassi, F., On the wettability of poly(2-hydroxyethylmetacrylate) (1992) J Colloid Interface Sci, 149, pp. 84-91; Morra, M., Cassinelli, C., Surface field of forces and protein adsorption behavior of poly(hydroxyethylmethacrylate) films deposited from plasma (1995) J Biomed Mater Res, 29, pp. 39-45; Elam, J., Nygren, Adsorption of coagulation proteins from whole blood on to polymer materials: Relation to platelet activation (1992) Biomaterials, 13, pp. 3-8; Chin, J.A., Horbett, T.A., Ratner, B.D., Baboon fibrinogen adsorption and platelet adhesion to polymeric materials (1991) Thromb Haemostas, 65, pp. 608-617; Horbett, T.A., Adsorption of proteins from plasma to a series of hydrophilic-hydrophobic copolymers. II Compositional analysis with the prelabeled protein technique (1981) J Biom Mater Res, 15, pp. 673-695; Garrett, Q., Chatelier, R.C., Griesser, H.J., Milthorpe, B.K., Effect of charged groups on the adsorption and penetration of proteins onto and into carboxymethylated poly(HEMA) hydrogels (1998) Biomaterials, 19, pp. 2175-2186; Feng, L., Andrade, J.D., Protein adsorption on low temperature isotropic carbon. III. Isoterms, competitivity, desorption and exchange of albumin and fibrinogen (1994) Biomaterials, 15, pp. 323-333; Bohnert, J.L., Horbett, T.A., Changes in adsorbed fibrinogen and albumin interactions with polymers indicated by decreases in detergent elutability (1986) J Colloid Interface Sci, 111, pp. 363-377; Slack, S.M., Horbett, T.A., Changes in fibrinogen adsorbed to segmented polyurethanes and hydroxyethylmethacrylate-ethylmethacrylate copolymers (1992) J Biom Mater Res, 26, pp. 1633-1649; Tanaka, M., Motomura, T., Kawada, M., Anzai, T., Kasori, Y., Shiroya, T., Shimura, K., Mochizuki, A., Blood compatible aspects of poly(hydroxyethylacrylate) (PMEA) - Relationship between protein adsorption and platelet adhesion on PHEA surface (2000) Biomaterials, 21, pp. 1471-1481; Vroman, L., Adams, A.L., Fisher, G.C., Munoz, P.C., Interaction of high molecular weight kininogen, Factor XII and fibrinogen in plasma at interfaces (1980) Blood, 55, pp. 156-159; Vroman, L., Adams, A.L., Adsorption of proteins out of plasma and solutions in narrow spaces (1986) J Colloid Interface Sci, 111, pp. 391-402; Andrade, J.D., Hlady, V., Protein adsorption and materials biocompatibility: A tutorial review and suggested hypotheses (1986) Adv Polym Sci, 79, pp. 1-63; Andrade, J.D., Hlady, V., Vroman effects, techniques and philosophies (1991) J Biomater Sci Polym Ed, 2, pp. 161-172; Brash, J.L., Studies of protein adsorption relevant to blood compatible materials (1991) Modern aspects of protein adsorption on biomaterials, p. 23. , Y.F. Missirlis, & W. Lemm. Kluwer Netherland: Academic Publishers; Brash, J.L., Hove, P.T., Protein adsorption studies on standard polymeric materials (1993) J Biomater Sci Polymer Ed, 4, pp. 591-599
Keywords: acrylic acid ethyl ester; Adsorption; Albumin; Albumins; article; ATR-FTIR; Biocompatible Materials; Chemical modification; Dose-Response Relationship, Drug; fibrinogen; film; Fourier transform infrared spectroscopy; Graft polymerisation; Humans; Hydrogen-Ion Concentration; Hydrophilic surfaces; hydrophilicity; hydroxyl group; infrared spectroscopy; isotope labeling; Microscopy, Electron, Scanning; molecular stability; Pellethane; PHEMA; poly(2 hydroxyethyl acrylate); polyetherurethan; Polyhydroxyethyl Methacrylate; polymacon; Polymerization; priority journal; protein; Protein adsorption; Proteins; Scanning electron microscopy; Spectrometry, X-Ray Emission; Spectroscopy, Fourier Transform Infrared; surface property; Thin films; unclassified drug; Water; X ray photoelectron spectroscopy

Constructing thromboresistant surface on biomedical stainless steel via layer-by-layer deposition anticoagulant - Tan, Q.; Ji, J.; Barbosa, M.A.; Fonseca, C.; Shen, J. (BiomaterialsBiomaterials, 2003)
Multilayer films consisting of polyethylenimine (PEI) and heparin were successfully prepared on biomedical 316L stainless steel surface via electrostatic self-assembly (ESA) of the PEI and heparin. The process of ESA of PEI/heparin was monitored by static contact angle, electrochemical impedance spectroscopy (EIS), reflection adsorption spectroscopy and X-ray photoelectron spectroscopy data. The contact angle and EIS data revealed that the multilayer coating was stable in Tris-HCl (pH 7.35) buffer solution for 21 days. The static platelet adhesion and static clotting time experiments indicated that the PEI/heparin-deposited stainless steel could resist the platelet adhesion and prolong the static clotting time effectively. Such an easy processing and shape-independent method may have good potential for surface modification of cardiovascular devices. © 2003 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 67Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(03)00363-6PubMed ID: 12951013Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, Hangzhou 310027, China; email: jianji@mail.hz.zj.cnChemicals/CAS: heparin, 37187-54-5, 8057-48-5, 8065-01-8, 9005-48-5; polyethyleneimine, 74913-72-7; stainless steel, 12597-68-1; trometamol, 1185-53-1, 77-86-1; Anticoagulants; Coated Materials, Biocompatible; Heparin, 9005-49-6; Polyethyleneimine, 9002-98-6; Stainless Steel, 12597-68-1Manufacturers: AldrichReferences: Bertrand, P., Jonas, A., Laschewsky, A., Legras, R., Ultrathin polymer coating by complexation of polyelectrolytes at interfaces: Suitable materials, structure and properties (2000) Macromol Rapid Commun, 21, pp. 319-348;Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Sano, M., Lvov, Y., Kunitake, T., (1996) Annu Rev Mater Sci, 26, pp. 153-187; Laschewsky, A., (1997) Eur Chem Chron ECC, 2, pp. 13-24; Picart, C., Lavalle, Ph., Hubert, P., Cuisnier, Fj., Decher, G., Schaaf, P., Voegel, J.C., Buildup mechanism for poly (L-lysine)/hyaluronic acid films onto a solid surface (2001) Langmuir, 17, pp. 7414-7424; Houska, M., Brynda, E., Interactions of proteins with polyelectrolytes at solid/liquid interfaces: Sequential adsorption of albumin and heparin (1997) J Colloid Interface Sci, 188, pp. 243-250; Brynda, E., Houska, M., Multiple alternating molecular layers of albumin and heparin on solid surfaces (1996) J Colloid Interface Sci, 183, pp. 18-25; Thomann, U.I., Uggowitzer, P.J., Wear-corrosion behavior of biocompatible austenitic stainless steels (2000) Wear, 239, pp. 48-58; Cheatham, J., Improved stents for pediatric applications (2001) Prog Pediatr Cardiol, 14, pp. 95-115; Donachie, M., Biomedical alloys (1998) Adv Mater Process, 154, pp. 63-65; Decher, G., Fuzzy nanoassemblies: Toward layered polymeric multicomposites (1997) Science, 277, pp. 1232-1237; Raposo, M., Pontes, R.S., Mattoso, L.H.C., Oliveira, O.N., Kinetics of adsorption of poly (o-methoxyaniline) self-assembled films (1997) Macromolecules, 30, pp. 6095-6101; Vov, Y.L., Rusling, J., Thomsen, D.L., Papadimitrakopoulos, F., Kawakami, T., Kunitake, T., High-speed multilayer film assembly by alternate adsorption of silica nanoparticles and linear polycation (1998) Chem Commun, 11, pp. 1229-1230; Lowack, K., Helm, C.A., Controlling the self-assembly process of polyelectrolyte multilayers (1998) Macromolecules, 31, pp. 823-833; Cheng, Z., Cheng, L., Dong, S., Yang, X., Formation and characterization of heteropolyacid/polycation multilayer films on gold electrode (2001) J Electrochem Soc, 148, p. 227
Keywords: 316L stainless steel; Adhesion; Adsorption; anticoagulant agent; Anticoagulants; aqueous solution; article; Biocompatibility; biomaterial; Biomaterials; blood clotting time; Blood Platelets; Blood-compatibility; buffer; Coated Materials, Biocompatible; coating; Coatings; Contact angle; controlled study; Deposition; device; electricity; Electrochemical impedance spectroscopy; electrochemistry; Electrostatics; heparin; human; human cell; Humans; implant; Layer-by-layer; material coating; materials testing; Multilayers; Organic polymers; pH; Platelet Adhesiveness; Polyethyleneimine; priority journal; reflection adsorption spectroscopy; Self assembly; Spectroscopy; Stainless steel; Surface Properties; surface property; Surfaces; thrombocyte adhesion; Thromboresistant surfaces; trometamol; X ray photoelectron spectroscopy

Development of foetal and neonatal simulators at the University of Porto - van Meurs, W.L.; Sá Couto, P.M.; Sá Couto, C.D.; Bernardes, J.F.; Ayres-de-Campos, D. (Medical Education, SupplementMed. Educ. Suppl., 2003)
Background: Human error can be expected to play a significant role in adverse outcomes in perinatal acute care. In acute care of the adult, simulator based training is recommended and used to improve patient safety. Aims: Our general goal is to develop model-driven foetal and neonatal educational simulators and curricula. The specific objectives of this paper are to introduce the reader to the perinatal acute care context and simulator design considerations, as well as to give initial results and describe ongoing developments. A brief description of adult simulators and simulation engines is followed by a more detailed description of a foetal distress simulator (FDS) and of models for a neonatal simulator developed at the University of Porto. Ongoing developments involve the modelling of foetal baroreflexes, the effect of uterine contractions, and an adapted method for estimating foetal heart rate variability parameters. Results: We present FDS simulation results reflecting the changes in oxygen supply to the foetus and the foetal heart rate in response to a reduction in uterine blood flow. We also present a structural diagram of a model for the educational simulation of congenital heart disease and preliminary simulation results reflecting a patent ductus arteriosus. Conclusion: We expect that, after initial clinical and educational validation, the presented models and simulators will play a role in simulator-based educational programmes contributing to increased perinatal safety.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: MESECPubMed ID: 14641636Language of Original Document: EnglishCorrespondence Address: Van Meurs, W.L.; INEB - Inst. de Engenharia Biomedica, Lab. de Sinal e Imagem Biomedica, Edificio I-Poente, Rua Roberto Prias, s/n, 4200-465 Porto, Portugal; email: wvanmeurs@ineb.up.ptChemicals/CAS: oxygen, 7782-44-7References: Kohn, L.T., Corrigan, J.M., Donaldson, M.S., (2000) To Err Is Human, Building a Safer Health Care System, , Washington, DC: National Academic Press;Denson, J.S., Abrahamson, S., A computer-controlled patient simulator (1969) JAMA, 208, pp. 504-508; Gaba, D.M., DeAnda, A., A comprehensive anesthesia simulation environment. Re-creating the operating room for research and training (1988) Anesthesiology, 69, pp. 387-394; Good, M.L., Gravenstein, J.S., Anesthesia simulators and training devices (1989) Int Anesthesiol Clin, 27, pp. 161-168; Gaba, D., Howard, S., Fish, K., Smith, B., Sowb, Y., Simulation-based training in anesthesia crisis resource management (ACRM): A decade of experience (2001) Simulation Gaming, 32, pp. 175-193; Gordon, J.A., 'Practicing' medicine without risk: Students' and educators' responses to high-fidelity patient simulation (2001) Acad Med, 76, pp. 469-472; Ma, O., Simulation saves lives (2001) Newsletter of the American Society of Anesthesiologists, , Park Ridge: American Society of Anesthesiologists; October; Van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit, 13, pp. 317-324; Van Meurs, W.L., Nikkelen, E., Good, M.L., Pharmacokinetic-pharmacodynamic model for educational simulations (1998) IEEE Trans Biomed Eng, 45, pp. 582-590; Öhrn, M.A.K., Van Oostrom, J.H., Van Meurs, W.L., A comparison of traditional textbook and interactive computer learning of neuromuscular block (1997) Anesth Analg, 84, pp. 657-661; Euliano, T.Y., Caton, D., Van Meurs, W.L., Good, M.L., Modeling obstetric cardiovascular physiology on a full-scale patient simulator (1997) J Clin Monit, 13, pp. 293-297; Sá Couto, P.M., Van Meurs, W.L., Bernardes, J.F., Marques De Sá, J.P., Goodwin, J.A., Mathematical model for educational simulation of the oxygen delivery to the fetus (2002) Cont Eng Prac, 10, pp. 59-66; Sá Couto, P.M., Van Meurs, W.L., Bernardes, J.F., Marques De Sá, J.P., Goodwin, J.A., Combined model-driven and rule-based approach for educational simulation of fetal heart rate (2002) BIOSIGNAL 2002. Proceedings of the 16th Biennial International Conference of the European Association for Speech, Signal and Image Processing (EURASIP), 26-28 June 2002, Brno, Czech Republic, pp. 400-402. , Jan J, Kozumplík J, Provazník I, eds. Brno: Vutium Press; Itskovitz, J., LaGamma, E.F., Rudolph, A.M., Heart rate and blood pressure responses to umbilical cord compression in fetal lambs with special references to the mechanism of variable deceleration (1983) Am J Obstet Gynecol, 147, pp. 451-457; Lee, S.T., Hon, E.H., Fetal hemodynamic response to umbilical cord compression (1963) J Obstet Gynecol, 22, pp. 553-562; Goodlin, R.C., Lowe, E.W., A functional umbilical cord occlusion heart rate pattern - The significance of overshoot (1974) Obstet Gynecol, 43, pp. 22-30; Scheffs, J., Vasicka, A., Li, C., Solomon, N., Siler, W., Uterine blood flow during labor (1971) Obstet Gynecol, 38, pp. 15-24; Brotanek, V., Hendricks, C.H., Yoshida, T., Importance of changes in uterine blood flow in initiation of labor (1969) Am J Obstet Gynecol, 105, pp. 535-546; Butler, L.A., Longo, L.D., Power, G.G., Placental blood flows and oxygen transfer during uterine contractions: A mathematical model (1976) J Theor Biol, 61, pp. 81-95; Felgueiras, C., Marques De Sá, J.P., Bernardes, J., Gama, S., Classification of foetal heart rate sequences based on fractal features (1998) Med Biol Eng Comput, 36, pp. 197-201; Sá Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Graphical and mathematical representation of congenital heart disease (2002) Proceedings of the SESAM Annual Meeting, 10-11 May 2002; Centro de Entrenamiento en Situaciones Críticas, Santander, Spain, p. 18; Beneken, J.E.W., (1965) A Mathematical Approach to Cardiovascular Function: The Uncontrolled Human System, , PhD dissertation. Utrecht, The Netherlands: Rijksuniversiteit Utrecht; Huikeshoven, F., Coleman, T.G., Jongsma, H.W., Mathematical model of the fetal cardiovascular system: The uncontrolled case (1980) Am J Physiol, 239, pp. R317-25; Klaus, M.H., Fanaroff, A.A., (2001) Care of the High-Risk Neonate, 5th Edn., , Philadelphia: WB Saunders
Keywords: article; audiovisual equipment; blackstarPatient simulation; clinical competence; Clinical competence/blackstarstandards/economics; competence; Curriculum; Education, Medical, Undergraduate; Education, medical, undergraduate/blackstarmethods; Equipment Safety; fetus distress; human; Humans; Manikins; medical education; model; oxygen; Patient Simulation; perinatal care; Perinatal care/ blackstarstandards/methods; Portugal; safety; simulator; training

Preparation of albumin preferential surfaces on poly(vinyl chloride) membranes via surface self-segregation - Ji, A.; Feng, L.; Shen, J.; Barbosa, M.A. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 2002)
Poly(vinyl chlorides)-graft-[w-stearyl-poly(ethylene oxide)] (PVC-g-SPEO), which has a poly(vinyl chloride) (PVC) backbone, poly(ethylene oxide) (PEO) side chain, and stearyl end groups, has been synthesized. Self-organizing blends of the amphiphilic comb polymer in poly-(vinyl chlorides) have been examined as a means to create albumin preferential surfaces on polymer films. X-ray photoelectron spectroscopy (XPS) analysis indicates substantial surface segregation of the PVC-g-SPEO. A surface concentration of 59.9 EO wt % is achieved by the solution casting and heat treatment of a film with a bulk concentration of only 3.78 EO wt %. In the aqueous environment, the surface rearrangement of PVC-g-SPEO/PVC blend film is limited and presents a high interfacial energy and high depolar component of interfacial energy due to the "tail-like" SPEO side chain. Protein adsorption tests confirm that PVC-g-SPEO/PVC blend films absorb high levels of albumin and dramatically resist fibrinogen adsorption. Surfaces to attract and reversibly bind albumin, which might diminish the occurrence of thrombosis, inflammation, and infection, are developed by self-organizing blends of the amphiphilic comb polymer in poly(vinyl chlorides). © 2002 Wiley Periodicals, Inc.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/jbm.10187Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, HangZhou, 310027, China; email: jianji@mail.hz.zj.cnChemicals/CAS: Membranes, Artificial; Polyethylene Glycols; Polyvinyl Chloride, 9002-86-2; Serum Albumin; Stearates; stearyl poly(ethylene oxide)References: Blass, C.R., Jones, C., Courtney, J.M., Biomaterials for blood tubing: The application of plasticised poly(vinyl chloride) (1992) Int J Artif Organs, 15 (4), pp. 200-203;Brash, J.L., (1983) Biocompatible polymer, metals and composites, p. 35. , Szycher M, editor. London, UK: Technomic Pub. Co; Keogh, J.R., Velander, F.F., Eaton, W., Albumin-binding surfaces for implantable devices (1992) J Biomed Mater Res, 26 (4), pp. 441-456; Amiji, M., Park, K., Surface modification of polymeric biomaterials with poly(ethylene oxide), albumin, and heparin for reduced thrombogenicity (1993) J Biomater Sci Polym Ed, 4 (3), pp. 217-234; Ji, J., Feng, L., Barbosa, M.A., Stearyl poly(ethylene oxide) grafted surfaces as albumin preferential materials (2001) Biomaterials, 22, p. 3015; De Queiroz, A.A., Barrak, E.R., Gil, H.A., Higa, O.Z., Surface studies of albumin immobilized onto PE and PVC films (1997) J Biomater Sci Polym Ed, 8 (9), pp. 667-681; McFarland, C.D., Jenkins, M., Griesser, H.J., Chatelier, R.C., Steele, J.G., Underwood, P.A., Albumin-binding surfaces: Synthesis and characterization (1998) J Biomater Sci Polym Ed, 9 (11), pp. 1207-1225; Wang, D.A., Ji, J., Sun, Y.H., Yu, G.H., Feng, L.X., Blends of stearyl poly(ethylene oxide) coupling-polymer in chitosan as coating materials for polyurethane intravascular catheters (2001) J Biomed Mater Res, 58 (4), pp. 372-383; Wang, D.A., Ji, J., Gao, C.Y., Yu, G.H., Feng, L.X., Surface coating of stearyl poly(ethylene oxide) coupling-polymer on polyurethane guiding catheters with poly(ether urethane) film-building additive for biomedical applications (2001) Biomaterials, 22 (12), pp. 1549-1562; Ji, J., Feng, L., Qiu, Y., Yu, X., Barbosa, M.A., Self-assembly and surface structure of an amphiphilic graft copolymer, polystyrene-graft-omega-stearyl-poly(ethylene oxide) (2000) J Colloid Interface Sci, 224 (2), pp. 255-260; Jian, J., Feng, L., Qiu, Y., Yu, X., Stearyl poly(ethylene oxide) grafted surfaces for preferential adsorption of albumin Part 2 (2000) The effect of molecular mobility on protein adsorption Polymer, 41 (10), pp. 3713-3718; Wu, S., (1982) Polymer Interface and adhesion, , New York: Marcel Dekker; Garbassi, F., Morra, M., Occhliello, E., (1994) Polymer surface: From physics to technology, , New York: John Wiley & Sons; Walton, D.G., Mayes, A.M., Entropically-driven segregation in blend of branch and linear polymers (1996) Phys Rev E, 54 (3), pp. 2811-2815; Mayes, A.M., Irvine, D.J., Griffith, L.G., Tailoring polymer surfaces for control cell behavior (1998) Biomaterials regulating cell function and tissue development, pp. 73-86. , Thomson RC, Mooney DJ, Healy KE, Ikada T, Mikos AG, editors. Warrendale: Materials Research Society; Eberhart, R.C., Munro, M.S., Williams, G.B., Kulkarni, P.V., Shannon W.A., Jr., Brink, B.E., Fry, W.J., Albumin adsorption and retention on C18-alkyl-derivatized polyurethane vascular grafts (1987) Artif Organs, 11 (5), pp. 375-382; Grasel, T.G., Pierce, J.A., Cooper, S.L., Effects of alkyl grafting on surface properties and blood compatibility of polyurethane block copolymers (1987) J Biomed Mater Res, 21 (7), pp. 815-842; Gombotz, W.R., Guanghui, W., Horbett, T.A., Hoffman, A.S., Protein adsorption to poly(ethylene oxide) surfaces (1991) J Biomed Mater Res, 25 (12), pp. 1547-1562; Neumann, A.W., Goog, R.J., Surface and colloid science, experimental methods (1979), 11, p. 31. , New York: Plenum PressAndrade, J.D., Ma, S.M., Contact angle at the S-W interface (1979) J Colloid Interface Sci, 72, pp. 488-494; Brash, J.L., Davidson, V.J., Adsorption of glass and polyethylene from solutions of fibrinogen and albumin (1976) Thromb Res, 9 (3), pp. 249-259; Ranter, B.D., (1985) Surface and interfacial aspects of biomedical polymers, p. 374. , Andrade JD, editor. New York: Plenum Press; Van Oss, C.J., (1994) Interfacial forces in aqueous media, pp. 170-177. , Van Oss CJ, editor. New York: Marcel Dekker; Wu, D., Jian, K., (1995) Sci China (B), 25 (11), p. 1121; Wu, D., (1995) Jian K Sci China (B), 26 (5), p. 409; Jeon, S.I., Lee, J.H., Andrade, J.D., De Gennes, P.G., Protein-surface interactions in the presence of polyethylene oxide (1991) J Coll Interface Sci, 142 (1), pp. 149-158; Hester, J.F., Banerjee, P., Mayes, A.M., Preparation of protein-resistant surfaces on poly(vinylidene fluoride) membranes via surface segregation (1999) Macromolecules, 32 (5), pp. 1643-1650; Keogh, R.J., Eaton, J.W., Albumin binding surfaces for biomaterials (1994) J Lab Clin Med, 124 (4), pp. 537-545
Keywords: Adsorption; Albumin; Amphiphilic copolymer; amphophile; aqueous solution; article; artificial membrane; Biocompatible Materials; cell separation; cell surface; chemical binding; combinatorial chemistry; concentration response; conference paper; dimerization; energy resource; film; human; Humans; infection; Inflammation; Inflammations; macrogol; macrogol derivative; membrane structure; Membranes, Artificial; metabolism; Plastic films; Polyethylene Glycols; polymer; Polymeric membranes; Polyvinyl Chloride; Polyvinyl chlorides; polyvinylchloride; protein binding; Serum Albumin; Stearates; stearic acid derivative; stearyl poly(ethylene oxide); Surface modification; Surface Properties; surface property; Surface segregation; Synthesis (chemical); thrombosis; X ray analysis; X ray photoelectron spectroscopy

Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and support the osteogenic differentiation of human bone marrow cells - Amaral, M.; Costa, M.A.; Lopes, M.A.; Silva, R.F.; Santos, J.D.; Fernandes, M.H. (BiomaterialsBiomaterials, 2002)
The in vitro osteocompatibility of a novel Si 3N 4-bioglass composite (70-30% weight proportion) with improved mechanical properties (fracture toughness=4.4MPam 1/2; bending strength=383±47MPa) is reported. Immersion of the composite samples in culture medium (30min to 7 days) resulted in rapid protein adsorption to the surface and, also, dissolution of the intergranular phase of bioglass (time-dependent process) with the formation of different size cavities. "As-received" and pre-treated material samples presented a similar behaviour concerning the proliferation of MG63 osteoblast-like cells, evaluated during a 5-day culture period. Seeded materials showed a higher cell growth rate as compared to cultures performed on the standard plastic culture plates. To assess the osteogenic potential of the composite, "as-received" material samples were seeded with human bone marrow cells and cultured for 35 days in experimental conditions that favour the development of the osteoblastic phenotype. The cell adhesion process was similar to that observed in control cultures. Cells successfully adapted to the irregularities of the surface and were able to grow towards inside the cavities; in addition, osteogenic differentiation occurred with the formation of abundant cell-mediated mineralised deposits. Results suggest that this Si 3N 4-bioglass composite seems to be a promising candidate for high-stress medical applications. © 2002 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(02)00249-1PubMed ID: 12361631Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Universidade do Porto, Rua Dr Manuel Pereira da Silva, 4200-393 Porto, Portugal; email: mhrf@portugalmail.ptChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Calcium, 7440-70-2; Phosphorus, 7723-14-0; Silicon Compounds; silicon nitride, 12033-89-5References: Amaral, M., Lopes, M.A., Silva, R.F., Santos, J.D., Densification route and mechanical properties of Si 3N 4-bioglass biocomposites (2002) Biomaterials, 23, pp. 857-862;Kue, R., Sahrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201; Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clin Orthop, 244, pp. 296-301; Hench, L.L., Biomaterials: A forecast for the future (1998) Biomaterials, 19, pp. 1419-1423; Radin, S., Ducheyne, P., Falaize, S., Hammond, A., In vitro transformation of bioactive glass granules into Ca-P shells (2000) J Biomed Mater Res, 49, pp. 264-272; Santos, J.D., Amaral, M., Oliveira, S.M., Lopes, M.A., Silva, R.F., Silicon Nitride - Bioglass ® 45S5 composite for biomedical applications (2001) Key Eng Mater, 192-195, pp. 589-592; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Maniatopoulos, C., Sodek, J., Melcher, A., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblastic phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 43, pp. 213-221; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Stein, G.S., Lian, J.B., Stein, J.L., Van Wijnem, A.J., Frenkel, B., Montecino, M., Mechanisms regulating osteoblast proliferation and differentiation (1996) Principles of bone biology, pp. 69-86. , J.P. Bilizikian, L.G. Raisz, & G.A. Rodan. New York: Academic Press; Fernandes, M.H., Costa, M.A., Carvalho, G.S., Mineralization in serially passaged human alveolar bone cells (1997) J Mater Sci: Mater Med, 8, pp. 61-65; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II: Effect of ascorbic acid β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Costa, M.A., Fernandes, M.H., Long-term effects of parathyroid hormone, 1,25-dihydroxyvitamin D3 and dexamethasone on the cell growth and functional activity of human osteogenic alveolar bone cell cultures (2000) Pharmacol Res, 42, pp. 345-353; Coelho, M.J., Trigo Cabral, A., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part I: Osteoblastic differentiation of serially passaged human bone marrow cells cultured in α-MEM and in DMEM (2000) Biomaterials, 21, pp. 1087-1094; Aubin, J.E., Liu, F., The osteoblastic lineage (1996) Principles of bone biology, pp. 51-67. , J.P. Bilizikian, L.G. Raisz, & G.A. Rodan. New York: Academic Press; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P 2O 5 glass hydroxyapatite double layer plasma sprayed coatings: In vitro bioactivity evatuation (1999) J Biomed Mater Res, 45, pp. 376-383; Kokubo, T., Ito, S., Huang, Z.T., Hayashi, T., Sakka, S., Ca, P-rich layer formed on high-strenght bioactive glass-ceramic A-W (1990) J Biomed Mater Res, 24, pp. 331-343; Daculsi, G., Legeros, R.Z., Heughebaert, M., Barbieux, I., Formation of carbonato-apatite crystals after implantation of calcium phosphate ceramics (1990) Calcif Tissue Int, 46 (1), pp. 20-27; Neo, M., Nakamura, T., Ohtsuki, C., Kokubo, T., Yamamuro, T., Apatite formation on three kinds of bioactive material at an early stage in vivo: A comparative study by transmission electron microscopy (1993) J Biomed Mater Res, 27, pp. 999-1006; Bagambisa, F.B., Joos, U., Schilli, W., Mechanisms and structure of the bond between bone and hydroxyapatite ceramics (1993) J Biomed Mater Res, 27, pp. 1047-1055; Bagambisa, F.B., Kappert, H.F., Schilli, W., Interfacial reactions of osteoblast to dental and implant materials (1994) J Oral Maxillofac Surg, 52, pp. 52-56; De Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., Initial bone matrix formation at the hydroxyapatite interface (1995) J Biomed Mater Res, 29 (1), pp. 89-99; Hulshott, J.E.G., Van Kijk, K., De Ruijter, J.E., Rietveld, F.J.R., Ginsel, L.A., Jansen, J.A., Interfacial phenomena: An in vitro study of the effect of calcium phosphate (Ca-P) ceramic on bone formation (1998) J Biomed Mater Res, 40, pp. 464-474; De Santis, D., Guerriero, C., Nocini, P.F., Vangersbock, A., Richard, G., Gotte, P., Armato, U., Adult human bone cells from jaw bones cultured on plasma-sprayed or polished surfaces of titanium or hydroxyapatite discs (1996) J Mater Sci Mater Med, 7, pp. 21-28; Anselme, K., Sharrock, P., Hardouin, P., Dard, M., In vitro growth of human adult bone-derived cells on hydroxyapatite plasma-sprayed coatings (1997) J Biomed Mater Res, 34, pp. 247-259; Ferraz, M.P., Fernandes, M.H., Trigo Cabral, A., Santos, J.D., Monteiro, F.J., In vitro growth and differentiation of osteoblastic-like human bone marrow cells on a glass reinforced hydroxyapatite plasma-speayed coating (1999) J Mater Sci: Mater Med, 10, pp. 567-576; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of pre-immersion on the biocompatibility of glass-reinforced hydroxyapatite plasma sprayed coatings (2000) Biomaterials, 21, pp. 813-820; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., HA and double-layer HA/CaO-P 2O 5 glass coatings: Influence of chemical composition on human bone marrow cells osteoblastic behaviour (2001) J Mater Sci: Mater Med, 7, pp. 628-638; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Direct and indirect effects of P 2O 5-glass reinforced hydroxyapatite composites on the growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Gwynn, I.A.P., Cell biology at interfaces (1994) J Mater Sci Mater Med, 5, pp. 357-360; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681; KirkPatrick, C.J., Wagner, M., Kohler, H., Bittinger, F., Otto, M., Klein, C.L., The cell and molecular biological approach to biomaterial research: A perspective (1997) J Mater Sci Mater Med, 8, pp. 131-141; Verrier, S., Bareille, R., Rovira, A., Dard, M., Amedee, J., Human osteoprogenitor responses to orthopaedic implant: Mechanism of cell attachment and cell adhesion (1996) J Mater Sci Mater Med, 7, pp. 46-51; Dee, K.C., Rueger, D.C., Andersen, T.T., Bizios, R., Conditions which promote mineralization at the bone-implant interface: A model for in vitro study (1996) Biomaterials, 17, pp. 209-215; Anseme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Iost, A., Hardouin, P., Qualitative and quantitative study of human osteoblast adhesion on materials with various surface roughnesses (2000) J Biomed Mater Res, 49, pp. 155-166; Diniz, M.G., Soares, G.A., Coelho, M.J., Fernandes, M.H., Surface topography modulates the osteogenesis in human bone marrow cell cultures grown on titanium samples prepared by a combination of mechanical and acid treatments (2002) J Mater Sci: Mater Med, 13, pp. 421-432; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Min, 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone Min, 17, pp. 15-29
Keywords: 3N; 4-bioglass composite; Adhesion; Adsorption; alkaline phosphatase; article; Biocompatibility; Bioglass; Biomaterials; bone marrow cell; Bone Marrow Cells; Calcium; cell adhesion; Cell Culture Techniques; cell differentiation; Cell Division; cell growth; cell proliferation; composite material; controlled study; culture medium; Dissolution; glass; Growth kinetics; human; Human bone marrow cells; human cell; Humans; immersion; in vitro study; Mechanical properties; MG63 osteoblast-like cells; Microscopy, Electron, Scanning; osteoblast; Osteoblasts; Osteocompatibility; Osteogenic differentiation; phenotype; phosphorus; priority journal; Proteins; rigidity; Si; Silicon compounds; silicon derivative; surface property; tensile strength; Time Factors

Silicon and iron levels in tissues of animals treated with a "ferrimagnetic ceramic" with oncotherapeutic potential (anti-tumor) value - Almeida, T.; Soares, M.E.; Cavalheiro, J.; Bastos, M.D.L. (Journal of Trace Elements in Medicine and BiologyJ. Trace Elem. Med. Biol., 2002)
The stability in a biological environment of an injectable cement with oncotherapeutic potential - consisting of a glass powder of SiO 2 (35.6%), CaO (42.4%), P 2O 5 (17%), Na 2O (5%) and 30% of its weight of Fe 3O 4 dissolved in (NH 4) 2HPO 4 plus NH 4H 2PO 4 - was evaluated referring to the release of silicon and iron. The experimental model was the rat, and organs (liver, kidney, spleen, lung, heart, and brain) of the implanted and control animals were collected for quantification of these elements by electrothermal atomization atomic absorption spectrometry methods. In most of the analysed organs no significant difference in the contents of silicon and iron between the implanted and the control animals was found.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JTEBFdoi: 10.1016/S0946-672X(02)80054-2PubMed ID: 12530589Language of Original Document: EnglishCorrespondence Address: Bastos, M.D.L.; Toxicology Department, Faculty of Pharmacy, University of Porto, Rua Aníbal Cunha 164, 4050 Porto, PortugalChemicals/CAS: calcium oxide, 1305-78-8; iron, 14093-02-8, 53858-86-9, 7439-89-6; phosphorus pentoxide, 1314-56-3; silicon dioxide, 10279-57-9, 14464-46-1, 14808-60-7, 15468-32-3, 60676-86-0, 7631-86-9; silicon, 7440-21-3; Biocompatible Materials; Ceramics; Iron, 7439-89-6; Silicon, 7440-21-3; Tissue ExtractsReferences: Rofstad, E.K., Brustad, T., Primary and secondary cell death in human melanoma xenografts following hyperthermic treatment (1986) Cancer Res., 46, pp. 355-361;Nishimura, Y., Shibamoto, Y., Jo, S., Akuta, K., Hiraoka, M., Takahashi, M., Abe, M., Relationship between heat-induced vascular damage and thermosensitivity in four mouse tumors (1988) Cancer Res., 48, pp. 7226-7230; Brown, S.L., Hunt, J.W., Hill, R.P., Differential thermal sensitivity of tumour and normal tissue microvascular response during hyperthermia (1992) Int. J. Hyperthermia, 8, pp. 501-514; Dudar, T.E., Jain, R.K., Differential response of normal and tumor microcirculation to hyperthermia (1984) Cancer Res., 44, pp. 605-612; Hill, S.A., Smith, K.A., Denekamp, J., Reduced thermal sensitivity of the vasculature in a slowly growing tumour (1989) Int. J. Hyperthermia, 5, pp. 359-370; Bicher, H.I., Hetzel, F.W., Sandhu, T.S., Frinak, S., Vaupel, P., O'Hara, M.D., O'Brien, T., Effects of Hyperthermia on normal and tumor microenvironment (1980) Radiology, 137, pp. 523-530; Song, C.W., Kang, M.S., Rhee, J.G., Levitt, S.H., The effect of hyperthermia on vascular function, pH, and cell survival (1980) Radiology, 137, pp. 795-803; Emami, B., Song, C.W., Physiological mechanisms in hyperthermia: A review (1984) Int. J. Radiation Oncology Biol. Phys., 10, pp. 289-295; Cavalheiro, J., Vasconcelos, M., Afonso, A., Branco, R., Ferrimagnetic and biocompatible cement for tumours thermotherapy (1996) Bioceramics, 9, pp. 243-246; Coury, A.J., Levy, R.J., McMillin, C.R., Pathak, Y., Ratner, B.D., Schoen, F.J., Williams, D.F., Williams, R.L., Degradation of materials in the biological environment (1996) Biomaterials Science, pp. 243-260. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE (Eds). Academic Press, San Diego; Williams, D.F., Williams, R.L., Degradative effects of the biological environment on metals and ceramics (1996) Biomaterials Science, pp. 260-267. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE (Eds). Academic Press, San Diego; Van Dyck, K., Robberecht, H., Van Cauwenbergh, R., Deelstra, H., Arnaud, J., Willemyns, L., Benijts, F., Uytterhoeven, M., Spectrometric determination of silicon in food and biological samples: An interlaboratory trial (2000) J. Anal. At. Spectrom., 15, pp. 735-741; Adler, A.J., Etzion, Z., Berlyne, G.M., Uptake, distribution, and excretion of 31silicon in normal rats (1986) Am. J. Physiol., 251, pp. E670-E673; Beattie, J.H., Avenell, A., Trace element nutrition and bone metabolism (1992) Nutrition Res. Rev., 5, pp. 167-188; Robinson, C.H., Lawler, M.R., Mineral elements (1982) Normal and Therapeutic Nutrition, 16 th Edition, pp. 131-160. , Robinson CH, Lawler MR (Eds). Macmillan Publishing Co., Inc., New York, Collier Macmillan Publishers, London; Sorond, F.A., Ratan, R.R., Ironing-out mechanisms of neuronal injury under hypoxic-ischemic conditions and potential role of iron chelators as neuroprotective agents (2000) Antioxid. Redox Signal, 2, pp. 421-436; Bonkovsky, H.L., Lambrecht, R.W., Iron-induced liver injury (2000) Clin. Liver Dis., 4, pp. 409-429; Bartfay, W.J., Bartfay, E., Iron-overload cardiomyopathy: Evidence for a free radical-mediated mechanism of injury and dysfunction in a murine model (2000) Biol. Res. Nurs., 2, pp. 49-59; Kang, J.L., Pack, I.S., Lee, H.S., Castranova, V., Enhancement of nuclear factor-KB activation and protein tyrosine phosphorylation by a tyrosine phosphatase inhibitor, pervanadate, involves reactive oxygen species in silica-stimulated macrophages (2000) Toxicology, 151, pp. 81-89
Keywords: animal model; animal tissue; Animalia; Animals; article; atomic absorption spectrometry; Biocompatible Materials; calcium oxide; cancer therapy; cement; ceramics; controlled study; experimental model; Ferrimagnetic ceramic; heat; Humans; implant; Iron; Magnetics; materials testing; Neoplasms; nonhuman; Oncotherapy; phosphorus pentoxide; powder; priority journal; Prostheses and Implants; rat; Rats; Reproducibility of Results; Silicon; silicon dioxide; tissue distribution; Tissue Extracts

Comparative effects of nacre water-soluble matrix and dexamethasone on the alkaline phosphatase activity of MRC-5 fibroblasts - Almeida, M.J.; Pereira, L.; Milet, C.; Haigle, J.; Barbosa, M.; Lopez, E. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 2001)
In this study we demonstrate, for the first time, that dexamethasone and BMP-2 stimulated alkaline phosphatase (ALP) activity in MRC-5 fibroblasts, a cell line derived from human fetal lung. Previously we reported that the water-soluble matrix (WSM) of nacre obtained from the inner shell layer of the oyster Pinctada maxima, promoted an increase in ALP activity that was dose-dependent. In this work, we show that the effect of WSM is also time-dependent. As a comparison, the effect of WSM was also tested in bone marrow stromal cells because marrow and other bone surface-derived osteoblast stem cells have the inherent direct potential for osteogenesis. WSM promotes cell proliferation and ALP activity when tested with bone marrow cells in concentrations between 135 and 540 μg protein/mL. The effect of WSM on ALP activity of bone marrow stromal cells is similar to that obtained by dexamethasone. These results imply that MRC-5 fibroblasts respond to differentiating factors that promote osteoblastic phenotype in bone-derived cell cultures. © 2001 John Wiley & Sons, Inc.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/1097-4636(200111)57:2<306::AID-JBM1172>3.0.CO;2-HPubMed ID: 11484195Language of Original Document: EnglishCorrespondence Address: Lopez, E.; Lab. de Physiol. Gen. et Comparee, UMR CNRS 8572, Museum National d'Histoire Naturelle, 7 rue Cuvier, 75231 Paris Cedex 05, France; email: lopez@mnhn.frChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; BMP2 protein, human; Bmp2 protein, rat; bone morphogenetic protein 2; Bone Morphogenetic Proteins; Dexamethasone, 50-02-2; Glucocorticoids; Transforming Growth Factor betaReferences: Lopez, E., Vidal, B., Berland, S., Camprasse, S., Camprasse, G., Silve, C., Demonstration of the capacity of nacre to induce bone formation by human osteoblasts maintained in vitro (1992) Tissue Cell, 24, pp. 667-679;Lopez, E., Berland, S., Le Faou, A., Nacre, osteogenic and osteoinductive properties (1994) Bull Inst Océan Monaco, 14, pp. 49-57; Silve, C., Lopez, E., Vidal, B., Smith, D.C., Camprasse, S., Camprasse, G., Couly, G., Nacre initiates biomineralization by human osteoblasts maintained in vitro (1992) Calcif Tissue Int, 51, pp. 363-369; Atlan, G., Balmain, N., Berland, S., Vidal, B., Lopez, E., Reconstruction of human maxillary defects with nacre powder: Histological evidence for bone regeneration (1997) C R Acad Sci III, 320, pp. 253-258; Atlan, G., Delattre, O., Berland, S., Le Faou, A., Nabias, G., Cot, D., Lopez, E., Interface between bone and nacre implants in sheep (1999) Biomaterials, 20, pp. 1017-1022; Lamghari, M., Almeida, M.J., Berland, S., Huet, H., Laurent, A., Milet, C., Lopez, E., Stimulation of bone marrow cells and bone formation by nacre: In vivo and in vitro studies (1999) Bone, 25 S, pp. 91S-94S; Westbroek, P., Marin, F., A marriage of bone and nacre (1998) Nature, 392, pp. 861-862; Le Faou, A., Berland, S., Lallier, F., Lopez, E., Osteoinductive effects induced by nacre implanted in subcutaneous pouches in rat (1995) Calcif Tissue Int, 56 A, p. 156; Le Faou, A., Berland, S., Lallier, F., Lopez, E., Local regulation of the osteoinductive process induced by nacre in connective tissues (1996) Ann Endoc, 57 (SUPPL. 4A), p. 75; Aubin, J.E., Liu, F., Malaval, L., Gupta, A.K., Osteoblast and chondroblast differentiation (1995) Bone, (SUPPL. 2), pp. S77-S83; Huggins, C.B., Urist, M.R., Dentin matrix transformation: Rapid induction of alkaline phosphatase and cartilage (1970) Science, 167, pp. 896-897; Reddi, A.H., Huggins, C.B., Biochemical sequences in the transformation of normal fibroblasts in adolescent rats (1972) Proc Natl Acad Sci USA, 69, pp. 1601-1605; Glowacki, J., Mulliken, J.B., Demineralized bone implants (1985) Clin Plast Surg, 12 (2), pp. 233-241; Katagiri, T., Yamaguchi, A., Ikeda, T., Yoshiki, S., Wozney, J.M., Rosen, V., Wang, E.A., Suda, T., The nonosteogenic mouse pluripotent cell line, C3H10T1/2, is induced to differentiate into osteobtastic cells by recombinant human bone morphogenetic protein-2 (1990) Biochem Biophys Res Commun, 172, pp. 295-299; McCulloch, C.A.G., Tenenbaum, H.C., Dexamethasone induces proliferation and terminal differentiation of osteogenic cells in tissue culture (1986) Anat Rec, 215, pp. 397-402; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulate formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Bellows, C.G., Aubin, J.E., Determination of numbers of osteoprogenitors present in isolated fetal calvarial cells in vitro (1989) Dev Biol, 133, pp. 8-13; Bhargava, U., Bar-Lev, M., Bellows, C.G., Aubin, J.E., Ultrastructural analyses of bone nodules formed in vitro by isolated fetal rat calvaria cells (1988) Bone, 9, pp. 155-163; Wiren, K.M., Rodan, G.A., Dissociation between the effects of glucocorticosteroids on cell spreading and phenotypic expression (1985) The chemistry and biology of mineralized tissues, pp. 320-325. , Butler WT, editor. Birmingham, AL: EBSCO Media; Kasugai, S., Todescan, R., Nagata, T., Yao, K.-L., Butler, W.T., Sodek, J., Expression of bone matrix proteins associated with mineralized tissue formation by adult rat bone marrow cells in vitro: Inductive effects of dexamethasone on the osteoblastic phenotype (1991) J Cell Physiol, 147, pp. 111-120; Chen, T.L., Bates, R.L., Dudley, A., Hammonds, R.G., Amento, E.P., Bone morphogenetic protein-2b stimulation of growth and osteogenic phenotypes in rat osteobtast-like cells: Comparison with TGF-β1 (1991) J Bone Miner Res, 6, pp. 1387-1393; Hiraki, Y., Inoue, H., Shigeno, C., Sanma, Y., Bentz, H., Rosen, D.M., Asada, A., Suzuki, F., Bone morphogenetic proteins (BMP-2 and BMP-3) promote growth and expression of the differentiated phenotype of rabbit chondrocytes and osteoblastic MC3T3-E1 cells in vitro (1991) J Bone Miner Res, 6, pp. 1373-1385; Rosen, V., Thies, R.S., The BMP proteins in bone formation and repair (1992) Trends Genet, 8, pp. 97-102; Thies, R.S., Bauduy, M., Ashton, B.A., Kurtzberg, L., Wozney, J.M., Rosen, V., Recombinant human bone morphogenetic protein-2 induces osteoblastic differentiation in W-20-17 stromal cells (1992) Endocrinology, 130, pp. 1318-1324; Urist, M.R., Iwata, H., Ceccotti, P.L., Dorfman, R.L., Boyd, S.D., McDowell, R., Chien, C., Bone morphogenesis in implants of insoluble bone gelatin (1973) Proc Natl Acad Sci USA, 70, pp. 3511-3515; Almeida, M.J., Milet, C., Peduzzi, J., Pereira, L., Haigle, J., Barthélemy, M., Lopez, E., The effect of water-soluble matrix fraction extracted from the nacre of Pinctada maxima on the alkaline phosphatase activity of cultured fibroblasts (2000) J Exp Zool, 288, pp. 327-334; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Owen, M., Marrow stromal stem cells (1988) J Cell Sci, (SUPPL. 10), pp. 63-76; Triffitt, J.T., Initiation and enhancement of bone formation (1987) Acta Orthop Scand, 58, pp. 673-684; Triffitt, J.T., The stem cell of the osteoblast (1996) Principles of bone biology, pp. 39-50. , Bilezikian JP, Raisz LG, Rodan GA, editors. New York: Academic Press; Wharton, S.A., Hipkiss, A.R., Degradation of peptides and proteins of different sizes by homogenates of human MRC5 lung fibroblasts (1985) FEBS Lett, 184 (2), pp. 249-253; Harada, K., Oida, S., Sasaki, S., Chondrogenesis and osteogenesis of bone marrow-derived cells by bone-inductive factor (1988) Bone, 9, pp. 177-183; Tucker, R.F., Shipley, G.D., Moses, H.L., Growth inhibitor from BSC-1 cells closely related to platelet type β transforming factor (1984) Science, 226, pp. 705-707; Noda, M., Rodan, G.A., Type-β transforming growth factor inhibits proliferation and expression of alkaline phosphatase in murine osteoblast-like cells (1986) Biochem Biophys Res Commun, 140, pp. 56-65; Tintut, Y., Parhami, F., Boström, K., Jackson, S., Demer, L., cAMP stimulates osteoblast-like differentiation of calcifying vascular cells (1998) J Biol Chem, 273, pp. 7547-7553; Rickard, D.J., Sullivan, T.A., Shenker, B.J., Leboy, P.S., Kazhdan, I., Induction of rapid osteoblast differentiation in rat bone marrow stromal cell cultures by dexamethasone and BMP-2 (1994) Dev Biol, 161, pp. 218-228; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II. Effect of ascorbic acid, β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Green, S., Chambon, P., A superfamily of potentially oncogenic hormone receptors (1986) Nature, 324, pp. 615-617; Grigoriadis, A.E., Heersche, J.N.M., Aubin, J.E., Differentiation of muscle, fat, cartilage and bone from progenitor cells present in a bone-derived clonal cell population: Effect of dexamethasone (1988) J Cell Biol, 106, pp. 2139-2151; Leboy, P.S., Beresford, J.N., Devlin, C., Owen, M.E., Dexamethasone induction of osteoblast mRNAs in rat marrow stromal cell cultures (1991) J Cell Physiol, 146, pp. 370-378; Guerriero V., Jr., Florini, J.R., Dexamethasone effects on myoblast proliferation and differentiation (1980) Endocrinology, 106, pp. 1198-1202; Maor, G., Silbermann, M., Supraphysiological concentrations of dexamethasone induce elevation of calcium uptake and depression of [ 3H]-thymidine incorporation into DNA in cartilage in vitro (1986) Calcif Tissue Int, 39, pp. 284-290; Urist, M.R., Bone morphogenetic protein in biology and medicine (1996) Bone morphogenetic proteins: Biology, biochemistry and reconstructive surgery, pp. 7-27. , Lindholm TS, editor. Austin, TX: RG Landes Company; Wozney, J.M., Rosen, V., Byrne, T., Celeste, A.J., Moutsatsos, I., Wang, E.A., Growth factor influencing bone development (1990) J Cell Sci, 97 (SUPPL. 13), pp. 149-156; Takuwa, Y., Ohse, C., Wang, E.A., Wozney, J.M., Yamashita, K., Bone morphogenetic protein-2 stimulates alkaline phosphatase activity and collagen synthesis in cultured osteoblastic cells, MC3T3 (1991) Biochem Biophys Res Commun, 174, pp. 96-101; Jortikka, L., Target cells and receptors for bone morphogenetic protein (1996) Bone morphogenetic proteins: Biology, biochemistry and reconstructive surgery, pp. 65-73. , Lindholm TS, editor. Austin, TX: RG Landes Company; Canalis, E., Centrella, M., Urist, M.R., Effect of partially purified bone morphogenetic protein on DNA synthesis and cell replication in calvarial and fibroblast cultures (1985) Clin Orthop, 198, pp. 289-294; Centrella, M., Casinghino, S., Kim, J., Pham, T., Rosen, V., Wozney, J., McCarthy, T.L., Independent changes in type I and type II receptors for transforming growth factor β induced by bone morphogenetic protein 2 parallel expression of the osteoblast phenotype (1995) Mol Cell Biol, 15, pp. 3273-3281; Vukicevic, S., Luyten, F.P., Redi, A.H., Stimulation of the expression of osteogenic and chondrogenic phenotypes in vitro by osteogenin (1989) Proc Natl Acad Sci USA, 86, pp. 8793-8797
Keywords: alkaline phosphatase; Animals; article; Biomedical engineering; BMP-2; Bone; bone development; bone marrow; Bone Marrow Cells; Bone morphogenetic proteins; Cell culture; Cell Line; cell proliferation; Cells; concentration response; dexamethasone; differentiation inducing factor; dose response; Dose-Response Relationship, Drug; enzyme activity; fibroblast; Fibroblasts; Glucocorticoids; human; human cell; Humans; male; MRC-5 fibroblasts; Nacre; natural product; osteoblast; Ostreidae; oyster; phenotype; Proteins; Pulmonary diseases; Rats; Rats, Wistar; Solubility; stroma cell; time; Time Factors; Transforming Growth Factor beta; unclassified drug; Water; Water-soluble matrix

Stearyl poly(ethylene oxide) grafted surfaces for preferential adsorption of albumin - Ji, J.; Feng, L.; Barbosa, M.A. (BiomaterialsBiomaterials, 2001)
An ideal surface for many biomedical applications would resist non-specific protein adsorption while at the same time triggering a specific biological pathway. Based on the approach of selectively binding albumin to free fatty acids, stearyl groups were immobilized onto poly(styrene) backbone via poly(ethylene oxide) side chains. X-ray photoelectron spectroscopy (XPS) analysis indicates substantial surface enrichment of the stearyl poly(ethylene oxide) (SPEO). In an aqueous environment, the surface rearrangement is limited, as proved by dynamic contact angle tests. The comb-like copolymer presents a special hydrophobic surface with high SPEO surface density, which may be due to the 'tail like' SPEO architecture at the copolymer/water interface. Protein adsorption tests confirm that the comb-like surfaces adsorb high levels of albumin and resist fibrinogen adsorption very significantly. The surfaces prepared in this research attract and reversibly bind albumin due to the synergistic action of the PEO chains and the stearyl end groups. Copyright © 2001 Elsevier Science Ltd.
Cited By (since 1996): 26Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(01)00048-5PubMed ID: 11575476Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, Hangzhou 310027, China; email: @@@Chemicals/CAS: Biocompatible Materials; Fibrinogen, 9001-32-5; Ligands; polyethylene glycol-polystyrene; Polyethylene Glycols; Polystyrenes; Serum Albumin; Stearates; stearyl poly(ethylene oxide)References: Andrade, J.D., Nagaoka, S., Cooper, S., Okano, T., Kim, S.W., Surface and blood compatibility; current hypothesis (1987) ASAIO Trans, 33 (2), pp. 75-76;Ranter, B.D., The engineering of biomaterials exhibiting recognition and specificity (1996) J Mol Recognition, 9, pp. 617-625; Jeon, S.I., Lee, J.H., Andrade, J.D., De Gennes, P.G., Protein-surface interactions in the presence of polyethylene oxide (1991) J Colloid Interface Sci, 142 (1), pp. 149-158; Merrill, E.W., Salzman, E.W., Polyethylene oxide as a biomaterial (1983) ASAIO J, 6, pp. 60-64; Amiji, M., Park, K., Prevention of protein adsorption and platelet adhesion on surfaces by PEO/PPO/PEO triblock copolymers (1992) Biomaterials, 13, pp. 682-692; Mayes, A.M., Irine, D.J., Tailoring polymer surface for control cell behavior (1998), pp. 73-84. , Thomson G., Mooney R.C., Healy D.J., Ikada K.E., Mikos Y. (Eds.), Biomaterials regulating cell function and tissue development, Warrendale, PA: MRSKeogh, R.J., Eaton, J.W., Albumin binding surfaces for biomaterials (1994) J Lab Clin Med, 124 (4), pp. 537-545; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., Alkyl substituted polymers with enhanced albumin affinity (1981) Trans Am Soc Artif Intern Organs, 27, pp. 499-503; Pitt, W.G., Cooper, S.L., Albumin adsorption on alkyl chain derivatized polyurethane; I. The effect of C-18 alkylation (1988) J Biomed Mater Res, 22, pp. 359-382; Frautschi, J.R., Munro, M.S., Lloyd, D.R., Eberhart, R.C., Alkyl derivatized cellulose acetate membranes with enhanced albumin affinity (1983) Trans Am Soc Artif Intern Organs, 29, pp. 242-244; Keogh, J.R., Velander, F.F., Eaton, J.W., Albumin-binding surface for implantable devices (1992) J Biomed Mater Res, 26, pp. 441-456; Qiu, Y.X., Yu, X.J., Feng, L.X., Yang, S.L., Synthesis and characterization of amphiphilic and microphase-separated graft copolymer (1992) Makromol Chem, 173, p. 1377; Gallo BM, Russo S. In: Platzer NAJ, editor. Copolymer, polymers and composites. Washington, DC, 1975. p. 85Neumann AW, Good RJ. In: Good RJ, Stromberg RR, editors. Surface and colloid science, vol. 11, Experimental methods. New York: Plenum Press, 1979. p. 31Brash, J.L., Davidson, V.J., Adsorption of glass and polyethylene from solutions of fibrinogen and albumin (1976) Thromb Res, 9 (3), pp. 249-259; Lide DR. In: Lider DR, editor. Surface tension of common liquids, Handbook of chemistry and physics. Boca Raton, FL: CRC Press, 1996. p. 6-147Carel, J.V.O., (1994), pp. 170-177. , Carel J.V.O. (Ed.), Interfacial forces in aqueous media, New York: Marcel DekkerMori, Y., Nagaoka, S., Takiuchi, H., Kikuci, T., Noguchi, N., Tanzawa, H., Noishili, Y., A new antithrombogenic material with long polyethyleneoxide chains (1982) Trans Am Soc Artif Intern Organs, 28, pp. 459-463; Wu, D., Jian, K., (1995) Sci China (B), 25 (11), p. 1121; Wu, D., Jian, K., (1995) Sci China (B), 26 (5), p. 409; Walton, D.G., Soo, P.P., Mayes, A.M., Sofia Allgor, S.J., Fujii, J.T., Griffith, L.G., Ankner, J.F., Satija, S.K., Creation of stable poly(ethylene oxide) surfaces on poly(methyl methacrylate) using blends of branched and linear polymer (1997) Macromolecules, 30 (22), pp. 6947-6956; Walton, D.G., Mayes, A.M., Entropically driven segregation in blend of branched and liner polymers (1996) Phys Rev E, 54 (3), pp. 2811-2815
Keywords: Adsorption; Albumin; Amphiphilic copolymer; article; Biocompatible Materials; Biomedical engineering; Catalyst selectivity; Cell immobilization; Contact angle; copolymer; Copolymers; density; Electron Probe Microanalysis; fibrinogen; Grafting (chemical); Humans; hydrophobicity; Ligands; macrogol; macrogol derivative; materials testing; Polyethylene Glycols; Polystyrenes; priority journal; Protein adsorption; protein binding; Proteins; roentgen spectroscopy; Serum Albumin; Stearates; Stearyl end groups; Surface Properties; surface property; Ultraviolet spectroscopy; X ray photoelectron spectroscopy

Classification of breast tissue by electrical impedance spectroscopy - Estrela Da Silva, J.; Marques De Sá, J.P.; Jossinet, J. (Medical and Biological Engineering and ComputingMed. Biol. Eng. Comput., 2000)
Electrical impedance spectroscopy is a minimally invasive technique that has clear advantages for living tissue characterisation owing to its low cost and ease of use. The present paper describes how this technique can be applied to breast tissue classification and breast cancer detection. Statistical analysis is used to derive a set of rules based on features extracted from the graphical representation of electrical impedance spectra. These rules are used hierarchically to discriminate several classes of breast tissue. Results of statistical classification obtained from a data set of 106 cases representing six classes of excised breast tissue show an overall classification efficiency of ~92% with carcinoma discrimination > 86%.Electrical impedance spectroscopy is a minimally invasive technique that has clear advantages for living tissue characterization owing to its low cost and ease of use. The present paper describes how this technique can be applied to breast tissue classification and breast cancer detection. Statistical analysis is used to derive a set of rules based on features extracted from the graphical representation of electrical impedance spectra. These rules are used hierarchically to discriminate several classes of breast tissue. Results of statistical classification obtained from a data set of 106 cases representing six classes of excised breast tissue show an overall classification efficiency of approximately 92% with carcinoma discrimination >86%.
Cited By (since 1996): 42Export Date: 21 November 2012Source: ScopusCODEN: MBECDPubMed ID: 10829386Language of Original Document: EnglishCorrespondence Address: Marques de Sa, J.P.; INEB, Facul. Engenharia Universidade Porto, Porto, Portugal; email: jmsa@fe.op.ptReferences: Brown, B.H., Barber, D.C., Morice, A.H., Leathard, A.D., Cardiac and respiratory related electrical impedance changes in the human thorax (1994) IEEE Trans. Biomed. Eng., BME-41, pp. 729-734;Campbell, A.M., Land, D.V., Dielectric properties of female breast tissue measured in vitro at 3.2 GHz (1992) Phys. Med. Biol., 37, pp. 193-210; Duda, R., Hart, P., (1973) Pattern Classification and Scene Analysis, , Wiley, New York; Foley, D.H., Considerations of sample and feature size (1972) IEEE Trans. Inform. Theory, IT-18, pp. 618-626; Foster, K.R., Schwan, H.P., Dielectric properties of tissues and biological materials: A critical review (1989) CRC Crit. Reviews Biomed. Eng., 17, pp. 25-104; Fukunaga, K., (1972) Introduction to Statistical Pattern Recognition, , Academic Press, New York and London; Gersing, E., Schäfer, M., Osypka, M., The appearance of positive phase angles in impedance measurements on extended biological subjects (1995) Innov. Techn. Biol. Med., 16 (SPEC. ISSUE 2), pp. 72-76. , Proc. 'CAIT Workshop on Electrode-Skin Interface in EIT'; Heinitz, J., Minet, O., Dielectric properties of female breast tumors (1995) Proc. '9th Int. Conf. Electrical Bioimpedance', pp. 356-359. , University of Heidelberg Press; Henderson, R.P., Webster, J.G., An impedance camera for spatially specific measurements of the thorax (1978) IEEE Trans. Biomed. Eng., BME-27, pp. 250-254; Jossinet, J., Variability of impedivity in normal and pathological breast tissue (1996) Med. Biol. Eng. Comput., 34, pp. 346-350; Jossinet, J., The impedivity of freshly excised human breast tissue (1998) Physiol. Meas., 19, pp. 61-75; Jossinet, J., Lavandier, B., The discrimination of excised cancerous breast tissue samples using impedance spectroscopy (1998) Bioelectrochem. Bioenerg., 45, pp. 161-167; Kubicek, W.G., Patterson, R.P., Witsoe, D.A., Impedance cardiography as a noninvasive method of monitoring cardiac function and other parameters of the cardiovascular system (1970) Ann. N.Y. Acad. Sciences, 170, pp. 24-732; Morimoto, T., Kinouchi, Y., Iritani, T., Kimura, S., Konishi, Y., Mitsuyama, N., Komaki, K., Monden, Y., Measurement of the electrical bio-impedance of breast tumors (1990) Eur. Surg. Res., 22, pp. 86-92; Raudys, S., Pikelis, V., On dimensionality, sample size, classification error and complexity of classification algorithm in pattern recognition (1980) IEEE Trans. Patt. Anal. Mach. Intel., PAMI-2, pp. 242-252; Shapiro, S.S., Wilk, S.S., Chen, S.W., A comparative study of various tests for normality (1968) J. Am. Stat. Ass., 63, pp. 1343-1372; Swain, P.H., The decision tree classifier: Design and potential (1977) IEEE Trans. Geosci. Electronics, GE-15, pp. 142-147; Schwan, H.P., Alternating current spectroscopy of biological substances (1959) Proc. IRE, 47, pp. 1841-1855; Surowiec, A.J., Stuchly, S.S., Barr, J.R., Swarup, A., Dielectric properties of breast carcinoma and the surrounding tissues (1988) IEEE Trans. Biomed. Eng., BME-35, pp. 257-263; Tachibana, S., Aguilar, J.A., Birzis, L., Scanning the interior of living brain by impedography (1970) J. of App. Physiol., 28, pp. 534-539
Keywords: article; Breast; breast cancer; Breast Neoplasms; cancer classification; Data classification; Discriminant Analysis; Electric Impedance; Electrical impedance spectroscopy; Electrodiagnosis; Feature extraction; Female; human; Humans; impedance; Impedance spectroscopy; major clinical study; Medical imaging; Signal Processing, Computer-Assisted; Spectroscopy; Statistical analysis; Statistical methods; Tissue; Tissue characterisation

Concept, design and fabrication of smart orthopedic implants - Burny, F.; Donkerwolcke, M.; Moulart, F.; Bourgois, R.; Puers, R.; Van Schuylenbergh, K.; Barbosa, M.; Paiva, O.; Rodes, F.; Bégueret, J.B.; Lawes, P. (Medical Engineering and PhysicsMed. Eng. Phys., 2000)
Extensive clinical experience has been built up using orthopaedic implants instrumented with strain gauges connected to a Wheatstone bridge by means of percutaneous leads. This research showed the medical relevance of the monitoring of the deformation of implants as a powerful tool to evaluate nursing and rehabilitation exercises, for tracing dangerous overloads and anticipating implant failure and also to observe the healing process. The IMPACT 3500 project focuses on the instrumentation of femoral implants with on board sensors: regular Benoist-Girard implants have been modified, to contain a 'sensing cell', and thoroughly tested in vitro and in vivo. The implant deformations are measured with resistive strain gauges, and the signal is transferred to a personal computer for processing and display, via a hard wired connection, or via a telemetry system. Two fully implantable wireless designs, called Linkstrain and Sealstrain, are powered from the outside by magnetic induction. As Sealstrain contains the whole telemetric system in its cavity, the highest miniaturization was required; this seriously deteriorates the efficiency of the inductive power link. © 2001 IPEM.
Cited By (since 1996): 29Export Date: 21 November 2012Source: ScopusCODEN: MEPHEdoi: 10.1016/S1350-4533(00)00062-XPubMed ID: 11165144Language of Original Document: EnglishCorrespondence Address: Burny, F.; Service d'Orthopedie-Traumatologie, Cliniques Universitaires Bruxelles, Hôpital Erasme, Brussels, Belgium; email: fburny@ulb.ac.beChemicals/CAS: Biocompatible Materials; Ceramics; Metals; Stainless Steel, 12597-68-1References: Burny, F., Donkerwolcke, M., Moulart, F., Clinical application of the monitoring of orthopedic implants (1993), pp. 138-146. , Burny R, Puers F, editors. Monitoring of orthopedic implants. A biomaterials microelectronics - challenge. Amsterdam: ElsevierBurny, F., Zucman, J., Bourgois, R., Aubriot, J.H., Sedel, J., Utilisation des jauges extensométriques pour la mesure de la consolidation des fractures du tibia traitées par enclouage centromédullaire. Etude théorique et premiers résultats (1971) Acta Orthop Belg, 37, pp. 266-277;Moulart, F., (1975) Rééducation des fractures hautes du fémur. Mesure des déformations du matériel d'ostéosynthese, , Mémoire de Licence en Kinésithérapie, Université Libre de Bruxelles; Burny, F., Moulart, F., Hinsenkamp, M., Traitement des fractures métastatiques de la region sous-trochantérienne. Etude biomécanique; cas cliniques (1976) Acta Orthop Belg, 42, pp. 31-41; Burny, F., Donkerwolcke, M., Telemetry in the musculoskeletal system (1991), pp. 391-394. , Payne PA, editor. Concise encyclopedia of biological and biomedical measurement systems. Oxford: Pergamon PressPuers, R., Burny, F., Biotelemetry in orthopaedics (1992), 3, pp. 285-306. , Muster D. et al., editors. European Materials Research Society Monographs. Biomaterials. Hard Tissue Repair and Replacement, Amsterdam: ElsevierKadefors, R., Kaiser, E., Petersen, I., Energizing implantable transmitters by means of coupled inductance coils (1969) IEEE Trans Biomed Eng, 16 BME, pp. 177-183; Ko, W.H., Liang, S.P., Fung, C.D.F., Design of radio-frequency powered coils for implant intruments (1977) Med Biol Eng Comput, 15, pp. 634-640; Donaldson, N., De, N., Perkins, T.A., Analysis of resonant coupled coils in the design of radio frequency trancutaneous links (1983) Med Biol Eng Comput, 21, pp. 612-627; Grossman, D.G., Machining a machinable glass-ceramic (1978) Vacuum, 28, pp. 55-61; Van Schuylenbergh, K., Puers, R., The influence of moisture leakage on implant strain measurements with resistive strain gauges (1993), pp. 125-137. , Burny R, Puers F, editors. Monitoring of orthopedic implants. A biomaterials microelectronics - challenge. Amsterdam: ElsevierWranglén, G., (1985) An introduction to corrosion and protection of metals, , London: Chapman & Hall; Barbosa, M.A., Surface layers and the reactivity of metallic implants (1992), pp. 257-284. , Muster D, editor. Biomaterials - hard tissue repair and replacement, E-MRS Monographs. North-Holland: Elsevier ScienceNicholas, M.G., Active metal brazing (1986) British Ceramic Transactions Journal, 85, pp. 144-146; Pattee, H.E., Joining ceramics to metals and other materials (1972) Welding Research Council Bulletin, 178, pp. 2435-2442. , New York; Nicholas, M.G., Crispin, R.M., Brazing ceramics with alloys containing titanium (1989) Ceramic Engineering and Science Proceedings, 10, pp. 1602-1612; Rodes, F., Zardini, C., Devall, Y., Puers, R., Van Schuylenbergh, K., Burny, F., Donkerwolcke, M., Moulart, F., Direct digitization of low level transducer outputs for low power intracorporal telemetry systems (1993), pp. 401-409. , Mancini P, Fioretti S, editors. 12th Int. Symposium on Biotelemetry, Ancona. Pisa, Italy: Universitaria Litografia FeliciFlack, F.C., James, E.D., Schlapp, D.M., Mutual inductance of air-cored coils: Effect on design of radio-frequency coupled implants (1971) Med Biol Eng Comput, 9, pp. 79-85;
Keywords: article; atomic absorption spectrometry; Biocompatible Materials; biomechanics; body movement; Bone Plates; ceramics; compression; Corrosion; Failure of implants; Femoral Fractures; femur; Fracture healing; healing; Humans; materials testing; metal; metal implantation; Metals; microcomputer; Microscopy, Electron, Scanning; Monitoring, Physiologic; Orthopedic implants; orthopedic surgery; priority journal; Prostheses and Implants; Prosthesis Design; prosthesis failure; Rehabilitation; Scanning electron microscopy; sensor; Sensors; Smart implants; Spectrum Analysis; Stainless steel; strain gauge transducer; Strain measurements; Stress, Mechanical; Telemetry; Weight-Bearing

Direct and indirect effects of P 2O 5 glass reinforced-hydroxyapatite composites on the growth and function of osteoblast-like cells - Lopes, M.A.; Knowles, J.C.; Santos, J.D.; Monteiro, F.J.; Olsen, I. (BiomaterialsBiomaterials, 2000)
Human osteoblast-like cells were plated on hydroxyapatite and P 2O 5-glass reinforced hydroxyapatite composite discs. They were also cultured in the presence of media obtained by incubating the discs in the absence of cells. The effects of these direct and indirect interactions were examined by measuring cell proliferation and the expression of certain key extracellular matrix antigens. One composite was found to initially delay cell growth, while the extract of a different composite appeared to down-regulate DNA synthesis. Flow cytometry analysis showed that growth directly on the discs had little effect on collagen type I, but reduced fibronectin and osteocalcin levels. The extracts of the materials generally had less effect, although one extract obtained from the glass-reinforced hydroxyapatite significantly down-regulated fibronectin. These in vitro studies thus suggest that there were only few differences overall in the growth of the cells directly on the glass-reinforced compared with the hydroxyapatite discs and also only relatively small effects of the extracts on the cells. However, the flow cytometry results suggest that both the materials and the extracts may have a potentially important influence on connective tissue production, and that these effects are both material- and antigen-specific. Copyright (C) 2000 Elsevier Science Ltd. Human osteoblast-like cells were plated on hydroxyapatite and P 2O 5-glass reinforced hydroxyapatite composite discs. They were also cultured in the presence of media obtained by incubating the discs in the absence of cells. The effects of these direct and indirect interactions were examined by measuring cell proliferation and the expression of certain key extracellular matrix antigens. One composite was found to initially delay cell growth, while the extract of a different composite appeared to down-regulate DNA synthesis. Flow cytometry analysis showed that growth directly on the discs had little effect on collagen type I, but reduced fibronectin and osteocalcin levels. The extracts of the materials generally had less effect, although one extract obtained from the glass-reinforced hydroxyapatite significantly down-regulated fibronectin. These in vitro studies thus suggest that there were only few differences overall in the growth of the cells directly on the glass-reinforced compared with the hydroxyapatite discs and also only relatively small effects of the extracts on the cells. However, the flow cytometry results suggest that both the materials and the extracts may have a potentially important influence on connective tissue production, and that these effects are both material- and antigen-specific.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(00)00007-7PubMed ID: 10817269Language of Original Document: EnglishCorrespondence Address: Olsen, I.; Department of Periodontology, Eastman Dental Institute, University College London, 256 Gray's Inn Road, London WC1X 8LD, United Kingdom; email: iolsen@eastman.ucl.ac.ukChemicals/CAS: Antigens; Biocompatible Materials; DNA, 9007-49-2; Hydroxyapatites; PhosphatesReferences: Kirkpatrick, C.J., A critical view of current and proposed methodologies for biocompatibility testing: Cytoxicity in vitro (1992) Regulatory Affairs, 4, pp. 13-32;Hanson, S., Lalor, P.A., Niemi, S.M., Ratner, B.D., (1996) Biomaterials Science. An Introduction to Materials in Medicine, pp. 215-242. , B.D. Ratner, & A.S. Hoffman. Basel: Karger; Bou-Gharios, G., Osman, J., Atherton, A., Monoghan, P., Vancheeswaran, R., Black, C., Olsen, I., Expression of ectopeptidaes in scleroderma (1995) Ann Rheum Dis, 54, pp. 111-116; Goseki, T., Shimizu, N., Iwasawa, T., Takiguchi, H., Abiko, Y., Effects of in vitro cellular aging on alkaline phosphatase, cathepsin activities and collagen secretion of human periodontal ligament-derived cells (1996) Mech Age Dev, 91, pp. 1761-1783; Parkar, M.H., Kuru, L., O'Hare, M., Newman, H.N., Hughes, F., Olsen, I., Retroviral transduction of periodontal cells with a temperature-sensitive SV40 large T antigen (1999) Archs Oral Biol, 44, pp. 823-834; Simon, L.V., Beauchamp, J.R., O'Hare, M., Olsen, I., Establishment of long-term myogenic cultures from patients with Duchenne muscular dystrophy by retroviral transduction of a temperature-sensitive SV40 large T-antigen construct (1996) Exp Cell Res, 224, pp. 264-271; Clover, J., Gowen, M., Are MG-63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype (1994) Bone, 15, pp. 585-591; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Di Silvio, L., A novel application of two biomaterial for the delivery of growth hormone and its effect on osteoblasts (1995) PhD Thesis, , Univ Lon: Univ Coll Lon Med Sch; Kapuscinski, J., Skoczylas, B., Simple and rapid fluorimetric method for DNA microassay (1977) Anal Biochem, 83, pp. 252-257; Nishizawa, K., Toriyama, M., Suzuki, T., Kawamoto, Y., Yokogawa, Y., Nagae, H., Effects of the surface wettability and zeta potential of bioceramics on the adhesiveness of anchorage-dependent animal cells (1993) J Ferm Bioengng, 75, pp. 435-437; Chesmel, K.D., Clark, C.C., Brighton, C.T., Black, J., Cellular response to chemical and morphologic aspects of biomaterial surfaces. II. The biosynthetic and migratory response of bone cell populations (1995) J Biomed Mater Res, 29, pp. 1101-1110; Harmand, M.F., Human cell culture and characterization of cell-biomaterial interface (1992) Clinical Materials, 11, pp. 145-150; Lincks, J., Boyan, B.D., Blanchard, C.R., Lohmann, C.H., Liu, Y., Cochran, D.L., Dean, D.D., Schawrtz, Z., Response of MG63 osteoblast-like cells to titanium and titanium alloy is dependent on surface roughness and composition (1998) Biomaterials, 19, pp. 2219-2232; Lopes, M.A., Santos, J.D., Monteiro, F.J., Glass reinforced hydroxyapatite composites: Secondary phases proportions and densification effects on biaxial bending strength (1999) J Biomed Mater Res, 48, pp. 734-740; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Lopes, M.A., Saramago, B., Santos, J.D., Monteiro, F.J., Hydrophobicity and zeta potencial of glass reinforced hydroxyapatite composites (1999) J Biomed Mater Res: Appl Biomater, 45, pp. 370-375; Hall, B.K., (1992) Fracture Repair and Regeneration, pp. 33-66. , Boca Raton, FL, USA: CRC Press; Legeros, R.Z., (1991) Calcium Phosphates in Oral Biology and Medicine, , Basel: Karger; Altankov, G., Groth, T., Fibronectin matrix formation and the biocompatibility of materials (1996) J Mater Sci: Mater Med, 7, pp. 425-429; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Lopes, M.A., Knowles, J.C., Hing, K., Santos, J.D., Monteiro, F.J., Olsen, I., Sedel, L., Rey, C., Biological evaluation of glass reinforced hydroxyapatite by flow cytometry (1997) Bioceramics, 10, pp. 575-578. , Paris, Oxford, UK: Elsevier; Kirkpatrick, C.J., Mittermayer, C., Theoretical and practical aspects of testing potential biomaterials in vitro (1990) J Mater Sci: Mater Med, 1, pp. 9-13; Marie, P.J., De Vernejoul, M.C., Lomri, A., Stimulation of bone formation in osteoporosis patients treated with fluoride associated with increased DNA synthesis by osteoblastic cells in vitro (1992) J Bone Miner Res, 7, pp. 103-113; Davies, J.E., In vitro modelling of the bone-implant interface (1996) Anat Rec, 245, pp. 426-445; Verrier, S., Bareille, R., Rovira, A., Dard, M., Amdee, J., Human osteoprogenitor responses to orthopaedic implant: Mechanism of cell attachment and cell adhesion (1996) J Mater Sci: Mater Med, 17, pp. 46-51; Sumner, H., Abraham, D., Bou-Gharios, G., Plater-Zyberk, C., Olsen, I., Simultaneous measurement of cell surface and intracellular antigens by multiple flow cytometry (1991) J Immun Meth, 136, pp. 259-267; Bou-Gharios, G., Osman, J., Black, C., Olsen, I., Excess matrix accumulation in Scleroderma is caused partly by differential regulation of stromelysin and TIMP-1 synthesis (1994) Clin Chim Acta, 231, pp. 69-78; Kuru, L., Parkar, M.H., Griffiths, G.S., Newman, H.N., Olsen, I., Flow cytometry analysis of functionally distinct gingival and periodontal ligament cells (1998) J Dent Res, 77, pp. 555-564; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of glass on the biocompatibility of plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings (1999) J Biomed Mater Res, 47, pp. 603-611
Keywords: Animal cell culture; antigen expression; Antigens; article; Biocompatibility; Biocompatible Materials; Biomaterials; Bone; Bone cells; cell antigen; Cell culture; Cell Division; cell function; cell growth; Cell Line; cell proliferation; cell structure; collagen type 1; controlled study; DNA; DNA Replication; DNA synthesis; extracellular matrix; Fibronectin; flow cytometry; glass; Glass fibers; Glass-reinforced hydroxyapatite; Growth kinetics; human; human cell; Humans; hydroxyapatite; Hydroxyapatites; immunofluorescence; In vitro; Microscopy, Electron, Scanning; osteoblast; Osteoblasts; osteocalcin; Phosphate minerals; Phosphates; phosphorus pentoxide; priority journal; Proteins; Reinforcement; Scanning electron microscopy

Fetal heart rate baselines in twins: Interobserver agreement in antepartum estimation - Bernardes, J.; Costa-Pereira, A.; Calejo, L.; Ayres-de-Campos, D.; Patrício, B.; Pereira-Leite, L. (Journal of Reproductive Medicine for the Obstetrician and GynecologistJ. Reprod. Med. Obstet. Gynecol., 2000)
OBJECTIVE: To assess interobserver agreement in antepartum estimation of fetal heart rate (FHR) baselines in twins. STUDY DESIGN: Two residents and one specialist in obstetrics and gynecology, all with special interest in FHR monitoring, independently estimated baselines in 162 consecutive antepartum FHR tracings recorded in 24 twins. Tracings were obtained with a dual-channel fetal monitor for the simultaneous recording of both twins' heart rates. Baselines were estimated, as single values corresponding to the mean of the lowest stable FHR segment, in the absence of fetal movements and uterine contractions, within physiologic limits (110-150 beats per minute [bpm]). If these criteria were not met, the possibility of persistent bradycardia or tachycardia was considered, and if this was confirmed in a tracing with at least 40 minutes, a baseline < 110 or > 150 bpm was chosen. Interobserver agreement was assessed by the proportions of agreement (PA), kappa statistic (K) and intraclass correlation coefficient (ICCC), with 95% confidence intervals (CIs). RESULTS: Interobserver agreement was excellent, with a PA of 0.90 (95% CI: 0.89-0.91), K of 0.88 (95% CI: 0.84-0.92) and ICCC of 0.91 (95% CI: 0.88-0.94). CONCLUSION: Interobserver agreement in antepartum estimation of fetal heart rate baselines in twins was excellent with the baseline concept used in this study.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JRPMAPubMed ID: 10710739Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Depto. de Ginecologia e Obstetricia, Faculdade de Medicina do Porto, Al. Prof. Hernani Monteiro, 4200 Porto, Portugal; email: Jbernardes@mail.telepac.ptReferences: Sherman, S.J., Kovacs, B.W., Medearis, A.L., Nonstress test assessment of twins (1992) J Reprod Med, 37, pp. 804-808;Grant, J.M., The fetal heart rate is normal, isn't it?: Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Cibils, L.A., On intrapartum fetal monitoring (1996) Am J Obstet Gynecol, 174, pp. 1382-1389; Bernardes, J., Costa-Pereira, A., Ayres-De-Campos, D., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57, pp. 33-37; Bernardes, J., Costa-Pereira, A., Van Geijn, H.P., A more objective fetal heart rate baseline estimation (1996) Br J Obstet Gynaecol, 103, pp. 714-715; Bernardes, J., Ayres-De-Campos, D., Costa-Pereira, A., Objective computerized fetal heart rate analysis (1998) Int J Gynecol Obstet, 62, pp. 141-147; Bland, J.M., Altman, D.G., Statistical methods for assessing two methods of clinical measurement (1986) Lancet, 11, pp. 307-310; Armitage, P., Berry, G., (1994) Statistical Methods in Medical Research, pp. 273-276. , Oxford, Blackwell Science Ltd; Khan, K.S., Chien, P.F.W., Honest, M.R., Evaluating measurement variability of clinical investigations: The case of ultrasonic estimation of urinary bladder volume (1997) Br J Obstet Gynaecol, 104, pp. 1036-1043; Devoe, L.D., Carlton, E., Prescott, P., Neural network prediction of nonstress test results: How often should we perform nonstress tests? (1995) Am J Obstet Gynecol, 173, pp. 1128-1131; Bernardes, J., Ayres De Campos, D., Costa-Pereira, A., Baseline estimation in typical fetal heart rate patterns using different computerized methods (1997) Acta Obstet Gynecol Scand (Suppl), 76, p. 56;
Keywords: adult; article; clinical article; Electrocardiography; Female; Fetal heart rate; Fetal monitoring; fetus; fetus heart rate; fetus monitoring; Heart rate variability; Heart Rate, Fetal; human; Humans; Internship and Residency; observer variation; Obstetrics; Pregnancy; Prenatal Care; priority journal; Professional Competence; Twins

Flow cytometry analysis of the effects of pre-immersion on the biocompatibility of glass-reinforced hydroxyapatite plasma-sprayed coatings - Ferraz, M.P.; Knowles, J.C.; Olsen, I.; Monteiro, F.J.; Santos, J.D. (BiomaterialsBiomaterials, 2000)
Multilayered coatings composed of mixtures of HA and P 2O 5-based bioactive glasses are of potential clinical benefit in orthopaedic and dental surgery. Pre-immersion of these materials has been reported to further enhance their efficacy in vivo, although the precise biological effects of this treatment are not yet known. In this study we have therefore prepared double-layer plasma-sprayed coatings and evaluated the effects of pre-immersion on the growth and function of human osteosarcoma cells in vitro, using the MTT assay and flow cytometry analysis, respectively. The results showed that the increase in numbers of viable cells was the same or elevated following incubation on the pre-immersed HA and glass-reinforced HA coatings compared with the non-immersed materials. In addition, the expression of bone sialoprotein and fibronectin, two key connective tissue antigens, was up-regulated in cultures grown on the pre-immersed surfaces compared with the non-treated materials. Moreover, cell numbers and antigen expression both improved as the proportion of glass increased, particularly in the pre-immersed samples. Our findings thus suggest that the immersion treatment of these materials appeared to improve the response of these bone-like cells. Copyright (C) 2000 Elsevier Science Ltd. Multilayered coatings composed of mixtures of HA and P 2O 5-based bioactive glasses are of potential clinical benefit in orthopaedic and dental surgery. Pre-immersion of these materials has been reported to further enhance their efficacy in vivo, although the precise biological effects of this treatment are not yet known. In this study we have therefore prepared double-layer plasma-sprayed coatings and evaluated the effects of pre-immersion on the growth and function of human osteosarcoma cells in vitro, using the MTT assay and flow cytometry analysis, respectively. The results showed that the increase in numbers of viable cells was the same or elevated following incubation on the pre-immersed HA and glass-reinforced HA coatings compared with the non-immersed materials. In addition, the expression of bone sialoprotein and fibronectin, two key connective tissue antigens, was up-regulated in cultures grown on the pre-immersed surfaces compared with the non-treated materials. Moreover, cell numbers and antigen expression both improved as the proportion of glass increased, particularly in the pre-immersed samples. Our findings thus suggest that the immersion treatment of these materials appeared to improve the response of these bone-like cells.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(99)00249-5PubMed ID: 10721750Language of Original Document: EnglishCorrespondence Address: Olsen, I.; Department of Periodontology, Eastman Dental Institute, University College London, 256 Gray's Inn Road, London WC1X 8LD, United Kingdom; email: iolsen@eastman.ucl.ac.ukChemicals/CAS: Biocompatible Materials; bone sialoprotein; Coated Materials, Biocompatible; Durapatite, 1306-06-5; Fibronectins; SialoglycoproteinsManufacturers: Plasma Biotal, United KingdomReferences: Passuti, N., Daculsi, G., Martin, S., Macroporous calcium phosphate ceramics for long bone surgery in human and dogs - Clinical and histological studies (1990) Clinical Implant Materials, pp. 255-258. , V. Soltesz, & A. Lee. Amsterdam: Elsevier Science Publishers;Legeros, R., Calcium phosphate materials in restorative dentistry (1988) A Review. Adv Dent Res, 2, pp. 164-180; Hench, L.L., Bioactive ceramics: From concept to clinic (1992) J Am Ceram Soc, 74, pp. 1487-1510; Conish, H., Aoki, H., Sawai, K., (1981) Science and Medical Applications of Hydroxyaptite, , editors Tokyo: Takyama Press System Centre Co; Raemdonck, W., Ducheyne, P., Meester, P., Calcium phosphate ceramics (1984) Metal and Ceramic Materials, pp. 143-166. , P. Ducheyne, & G.W. Hastings. Boca Raton, FL, USA: CRC Press; Rey, C., Freche, M., Heughebaert, M., Vignoles, M., Apatite chemistry in biomaterial preparation, shaping and biological behaviour (1991) Fourth Symposium on Ceramics in Medicine - Bioceramics 4, pp. 57-64. , G.W. Hastings, & K.E. Tanner. London: Butterworth-Heinemann; Nagase, M., Abe, Y., Udagwa, E., Toxicity of silica-containing calcium phosphate glasses demonstrated in mice (1992) Biomaterials, 13, pp. 172-175; Burnie, J., Gilchrist, T., Controlled released glass - A new biomaterial (1983) Ceramics in Surgery, pp. 169-176. , P. Vicenzini. Amsterdam: Elsevier Science Publishers; Burnie, F., Gilchrist, T., (1983) Ceramics in Surgery, pp. 177-180. , P. Vicenzini. Amsterdam: Elsevier Science; Rawlings, R.D., Rogers, P.S., Stokes, P.M., Glass-ceramics containing apatite (1987) High Tech Ceramics, pp. 73-82. , P. Vicenzini. Amsterdam: Elsevier Science Publishers; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterization of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Santos, J.D., Lakhan, J.J., Monteiro, F.J., Surface modifications of glass-reinforced hydroxyapatite composites (1995) Biomaterials, 16, pp. 521-526; Ferraz, M.P., Monteiro, F.J., Santos, J.D., In vitro bioactivity and osteocompatibility evaluation of plasma sprayed hydroxyapatite/glass composite coatings onto Ti-6Al-4V substrates (1997) Ninth International Conference on Biomedical Engineering, pp. 557-559. , In: Goh JCH, editor Singapore; Klein, C.P.A.T., Patka, P., Van Der Lubbe, H.B.M., Plasma-sprayed coatings of tetracalciumphosphate, hydroxyl-apatite, and α-TCP on titanium alloy: An interface study (1991) J Biomed Mater Res, 25, pp. 53-65; Jansen, J.A., Van Der Waerden, J.P., Wolke, J.G., Histologic investigation of the biologic behavior of different hydroxyapatite plasma-sprayed coatings in rabbits (1993) J Biomed Mater Res, 4, pp. 603-610; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., The ultrastructure of the bone-hydroxyapatite interface in vitro (1992) J Biomed Mater Res, 26, pp. 1365-1382; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., Comparative biological properties of HA plasma-sprayed coatings having different crystallinities (1994) J Mater Sci: Mater Med, 5, pp. 11-17; Lugscheider, E., Knepper, M., Heimberg, B., Dekker, A., Kirkpatrick, C.J., Cytotoxicity investigations of plasma-sprayed calcium-phosphate coatings (1994) J Mater Sci: Mater Med, 5, pp. 371-375; Courteney-Harris, R.G., Kayser, M.V., Downes, S., Comparison of the early production of extracellular matrix on dense hydroxyapatite and hydroxyapatite-coated titanium in cell and organ culture (1995) Biomaterials, 16, pp. 489-495; Labat, B., Chanson, A., Frey, J., Effects of γ-alumina and hydroxyapatite coatings on the growth and metabolism of human osteoblasts (1995) J Biomed Mater Res, 29, pp. 1397-1401; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., Adult human bone cells derived from jaw bones cultured on plasma-sprayed or polished surfaces to titanium or hydroxyapatite discs (1996) J Mater Sci: Mater Med, 7, pp. 21-28; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Ariola, C.R., Granchi, D., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin Mater, 15, pp. 173-190; Puleo, D.A., Preston, K.E., Shaffer, J.B., Bizios, R., Examination of osteoblast-orthopaedic biomaterial interactions using molecular techniques (1993) Biomaterials, 14, pp. 111-114; Clifford, C.J., Downes, S., A comparative study of the use of colorimetric assays in the assessment of biocompatibility (1996) J Mater Sci: Mater Med, 7, pp. 637-643; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P 2O 5 glass hydroxyapatite double layer plasma sprayed coatings: In vitro evaluation (1999) J Biomed Mater Res, 45, pp. 376-383; Ferraz, M.P., Fernandes, M.H., Trigo Cabral, A., Santos, J.D., Monteiro, F.J., In vitro growth and differentiation of osteoblast-like human bone marrow cells on glass reinforced HA plasma sprayed coatings (1999) J Mater Sci: Mater Med, 10, pp. 567-576; Macey, M.G., (1994) Flow Cytometry - Clinical Applications, , editor Oxford: Blackwell Scientific; Shapiro, H.M., (1995) Practical Flow Cytometry, , New York: Wiley-Liss; Melamed, M.R., Lindmo, T., Mandelsohn, M.L., (1990) Flow Cytometry and Sorting, , editors New York: Wiley-Liss; Muirhead, K.A., Horan, P.K., Applications of flow cytometry to tissue culture systems (1983) Adv Cell Culture, 3, pp. 57-91; Corver, W.E., Cornelisse, C.J., Fleuren, G.J., Simultaneous measurement of two cellular antigens and DNA using fluorescein-isothiocyanate, R-phycoerythrin and propidium iodide on a standard FACScan (1994) Cytometry, 15, pp. 117-128; Pande, G., Kumar, N.A., Manogaran, P.S., Flow cytometric study of changes in intracellular free calcium during the cell cycle (1996) Cytometry, 24, pp. 55-63; Kamiya, I., Okuda, K., Hara, K., Flow cytometric identification and detection of Porphyromonas gingivalis by a LPS specific monoclonal antibody (1994) J Periodont, 65, pp. 309-315; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of glass on the biocompatibility of plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings J Biomed Mater Res, , in press; Cowles, E.A., DeRome, M.E., Pastizzo, G., Brailey, L.L., Gronowicz, G.A., Mineralization and the expression of matrix proteins during in vivo bone development (1998) Calcif Tissue Int, 62, pp. 74-82; Globus, R.K., Dotty, S.B., Lull, J.C., Holmuhamedov, E., Humphries, M.J., Damsky, C.H., Fibronectin is a survival factor for differentiated osteoblasts (1998) J Cell Sci, 111, pp. 1385-1393; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Wojciech, G., Melamed, M.R., Darzynkiewicz, Z., Analysis of apoptosis by flow cytometry (1998) Flow Cytometry Protocols, pp. 217-238. , M.J. Jaroszeski, & R. Heller. Totowa, NJ, USA: Humana Press
Keywords: antigen expression; article; Bioactive glasses; Biocompatibility; Biocompatible Materials; Biomaterials; Cell culture; Cell Division; cell growth; cell proliferation; Cell size; Coated Materials, Biocompatible; controlled study; cytology; Cytoplasmic Granules; Dental Materials; drug manufacture; Durapatite; Fibronectin; Fibronectins; flow cytometry; Flow cytometry analysis; glass; Glass fibers; Glass-reinforced hydroxyapatite; Growth kinetics; human; human cell; Humans; hydroxyapatite; in vitro study; materials testing; orthopedics; Osteosarcoma; osteosarcoma cell; Phosphates; Plasma spraying; Pre-immersion; priority journal; protein expression; Proteins; Sialoglycoproteins; sialoprotein; Sprayed coatings; Surface Properties; technique; Tumor Cells, Cultured

CaO-P 2O 5 glass hydroxyapatite double-layer plasma-sprayed coating: In vitro bioactivity evaluation - Ferraz, M.P.; Monteiro, F.J.; Santos, J.D. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
Double-layer composite coatings composed of a P 2O 5-based glass/Ca 10(PO 4) 6(OH) 2 (HA) mixture top layer and a simple HA underlayer, on Ti-6AI-4V substrates, were prepared using a plasma-spraying technique. The in vitro bioactivity of these coatings was assessed by immersion testing in simulated body fluid. Both scanning electron microscopy (SEM) analysis and the ionic solution changes followed by atomic absorption spectroscopy and the molybdenum blue method demonstrated that these composite coatings induce a faster surface Ca-P layer formation than the simple HA coatings used as a control. X-ray photoelectron spectroscopy (XPS) analysis demonstrated that the Ca-P layer formed was apatite. The combination of SEM and XPS analyses showed that the apatite layer was a calcium-deficient hydroxyapatite with a Ca/P ranging from 1.3 to 1.4 with CO 3 2- groups contained in the structure. Double-layer composite coatings composed of a P 2O 5-based glass/Ca 10(PO 4) 6(OH) 2 (HA) mixture top layer and a simple HA underlayer, on Ti-6AI-4V substrates, were prepared using a plasma-spraying technique. The in vitro bioactivity of these coatings was assessed by immersion testing in simulated body fluid. Both scanning electron microscopy (SEM) analysis and the ionic solution changes followed by atomic absorption spectroscopy and the molybdenum blue method demonstrated that these composite coatings induce a faster surface Ca-P layer formation than the simple HA coatings used as a control. X-ray photoelectron spectroscopy (XPS) analysis demonstrated that the Ca-P layer formed was apatite. The combination of SEM and XPS analyses showed that the apatite layer was a calcium-deficient hydroxyapatite with a Ca/P ranging from 1.3 to 1.4 with CO 3 2- groups contained in the structure.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(19990615)45:4<376::AID-JBM13>3.0.CO;2-SLanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; Departamento Engenharia Metalurgica, FEUP, Universidade do Porto, R. dos Bragas, 4099 Porto Codex, PortugalChemicals/CAS: Alloys; Calcium, 7440-70-2; CaO-SiO2-P2O5-CaF2 glass; Coated Materials, Biocompatible; Durapatite, 1306-06-5; Phosphates; Powders; Resin Cements; Solutions; titanium alloy (TiAl6V4), 12743-70-3; Titanium, 7440-32-6References: Denissen, H., Mangano, C., Venini, G., (1985) Hydroxylapatite Implants., , Padua: Piccin Nuova Libraria, S.P.A;Van Raemdonck, W., Ducheyne, P., De Meester, P., Calcium phosphate ceramics (1984) Metal and Ceramic Biomaterials, pp. 143-166. , Ducheyne P, Hastings GW, editors, Boca Raton, FL: CRC Press; Legeros, R.Z., Incorporation of magnesium in synthetic and biological apatites (1994) Tooth Enamel IV., pp. 32-36. , Fearnead RW, editor. Amsterdam: Elsevier Science; Jha, L.J., Best, S.M., Knowles, J.C., Rehman, I., Santos, J.D., Bonfield, W., Preparation and characterization of fluoride-substituted apatites (1997) J Mater Sci Mater Med, 8, pp. 185-191; Geesink, R.G.T., Degroot, K., Chemical implant fixation using hydroxyl-apatite coatings (1987) Clin Orthop, 2, pp. 147-170; Radin, S., Ducheyne, P., The effect of plasma sprayed induced changes in the characteristics on the in vitro stability of calcium phosphate ceramics (1990) Transactions of the 16th Annual Meeting of the Society for Biomaterials XIII, pp. 128-130; Cook, S.D., Thomas, K.A., Hydroxyapatite coated porous titanium for use as an orthopaedic biologic attachment (1989) Clin Orthop, 230, pp. 303-312; McPherson, R., Gane, N., Bastow, T.J., Structural characterization of plasma-sprayed hydroxylapatite coatings (1995) J Mater Sci Mater Med, 6, pp. 327-334; De Groot, K., Geesink, R., Klein, C.P.A.T., Serekian, P., Plasma sprayed coatings of hydroxylapatite (1987) J Biomed Mater Res, 21, pp. 1375-1381; Ravagliolli, A., Krajewszki, A., Laudadio, P., Presutti, L., Cunsolo, E., Martinetti, R., About ceramics for stapedial prostheses and the ossicular chain (1992) Fifth International Symposium on Ceramics in Medicine-Bioceramics 5, pp. 451-458. , Yamamuro T, Kokubo T, Nakamura T, editors. Kyoto: Kobunshi Kankokai; Hastings, G.W., Daily, D., Hydroxyapatite coatings (1989) First International Symposium on Ceramics in Medicine-Bioceramics 1, pp. 355-358. , Oonishi H, Aoki H, Sawai K, editors. Tokyo: Ishiyaku EuroAmerica; Aoki, H., Medical applications of hydroxyapatite (1991) Science and Medical Applications of Hydroxyaptite, pp. 175-192. , Aoki H, Sawai K, editors. Tokyo: Takyama Press System Centre; Rey, C., Calcium phosphate biomaterials and bone mineral: Differences in composition, structures and properties (1990) Biomaterials, 11, pp. 13-15; Evans, G., Behiri, J., Currey J, B.W., Microhardness and young's modulus in cortical bone exhibiting a wide range of mineral volume fractions, and in a bone analogue (1990) J Mater Sci Mater Med, 1, pp. 38-43; Rey, C., Froche, M., Heughebaert, M., Heughebaert, J.C., Lacout, J.L., Vignoles, M., Apatite chemistry in biomaterial preparation, shaping and biological behaviour (1991) Fourth International Symposium on Ceramics in Medicine-Bioceramics 4, pp. 57-60. , Bonfield W, Hastings GW, Tanner KE, editors. London: Butterworth-Heinemann; Knowles, J.C., Talal, S., Santos, J.D., Sintering effects in a glass reinforced hydroxyapatite (1996) Biomaterials, 17, pp. 1437-1442; Kokubo, T., Hayashi, T., Sakka, S., Kitsugi, T., Yamamuro, T., Takagi, M., Shibuya, T., Surface structure of a load bearable bioactive glass-ceramic A-W (1981) High Tech Ceramics, pp. 175-184. , Vicenzini P, editor. Amsterdam: Elsevier Science Publisher BV; Hench, L., Anderson, O.H., LaTorre, G.P., The kinetics of bioactive ceramics. Part III: Surface reactions for bioactive glasses compared with inactive glass (1991) Fourth International Symposium on Ceramics in Medicine-Bioceramics 4, , Bonfield W, Hastings GW, Tanner KE, editors. London: Butterworth-Heinemann; 155-162; Daculsi, G., LeGeros, R.Z., Heughebart, M., Barbieux, I., Formation of a carbonate apatite crystals after implantation of calcium phosphate ceramics (1990) Calcif Tissue Int, 46, pp. 20-27; Kokubo, T., Ito, S., Huang, Z.T., Hayashi, T., Sakka, S., Kitsugi, T., Yamamuro, T., Ca-P rich layer formed on high strength bioactive glass-ceramic A-W (1990) J Biomed Mater Res, 24, pp. 331-343; Ducheyne, P., Radin, S., Ishikawa, K., Kim, C.S., Dissolution and precipitation of calcium phosphate phases on biomaterials correlates with in vivo bioactivity (1991) Fourth International Symposium on Ceramics in Medicine-Bioceramics 4, pp. 135-144. , Bonfield W, Hastings GW, Tanner KE, editors. London: Butterworth-Heinemann; Rey, C., Hina, A., Amrah-Bouali, S., Ranz, X., Surface reactions of calcium-phosphate bioceramics, comparison with bone mineral surface chemistry (1995) Fourth Euro Ceramics., 8, pp. 301-312. , Ravaglioli A, editor. Faenza: Gruppo Editoriale Faenza Editrice; Van Blitterswijk, C.A., Grote, J.J., Kuypers, W., Blok-Van Hoek, C.J.G., Daems, W.T., Bioreactions at the tissue/hydroxyapatite interface (1985) Biomaterials, 6, pp. 243-251; Ducheyne, P., Bioceramics: Material characteristics versus in vivo behavior (1987) J Biomed Mater Res, 21, pp. 219-236; Hyakuna, K., Yamamuro, T., Kotoura, Y., Oka, M., Nakamura, T., Kitsogi, T., Kokubo, T., Kushitani, H., Surface reactions of calcium phosphate ceramics to various solutions (1990) J Biomed Mater Res, 24, pp. 471-488; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions: Structure and properties of the composites (1995) J Mater Sci Mater Med, 6, pp. 348-352; Tanahashi, M., Yao, T., Kokubo, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., Apatite coated on organic polymers by biomimetic process: Improvement in adhesion to substrate by HC1 treatment (1995) J Mater Sci Mater Med, 6, pp. 319-326; Neo, M., Nakamura, T., Yamamuro, T., Ohtsuki, C., Kokubo, T., Bando, Y., A comparative study of ultrastructures of the interfaces between four kinds of surface-active ceramic and bone (1992) J Biomed Mater Res, 26, pp. 1419-1432; Li, P., Ohtsuki, C., Kokubo, T., Nakanishi, K., Soga, N., Nakamura, T., Yamamuro, T., Process of formation of bone-like apatite layer on silica gel (1993) J Mater Sci Mater Med, 4, pp. 127-131; Santos, J.D., Jha, L.J., Monteiro, F.J., Surface modifications of glass-reinforced hydroxyapatite composites (1995) Biomaterials, 16, pp. 521-526; Neo, M., Kotani, S., Fujita, Y., Yamamuro, T., Bando, Y., Ohtsuki, C., Kokubo, T., Differences in ceramic-bone interface between surface-active ceramics and resorbable ceramics: A study by scanning and transmission electron microscope (1992) J Biomed Mater Res, 26, pp. 255-267; Li, P., Yang, Q., Zhang, F., Kokubo, T., The effect of residual glassy phase in a bioactive glass-ceramic on the formation of its surface apatite layer in vitro (1992) J Mater Sci Mater Med, 3, pp. 452-456; Kotani, S., Fujita, Y., Kitsugi, T., Nakamura, T., Yamamuro, T., Bone bonding mechanism of β-tricalcium phosphate (1991) J Biomed Mater Res, 25, pp. 1303-1315; Daculsi, G., LeGeros Rz, H.M., Barbieux, I., Formation of carbonate-apatite crystals after implantation of calcium phosphate ceramics (1990) Calcif Tissue Int, 46, pp. 20-27; Silva, P.L., Monteiro, F.J., Santos, J.D., Knowles, J.C., Adhesion and microstructural characterisation of plasma sprayed hydroxyapatite-glass ceramic coatings onto Ti-6Al-4V substrates (1998) Surf Coatings Technol, 102, pp. 191-196; Kokubo, T., Kushitani, H., Ohtsuki, C., Sakka, S., Yamamuro, T., Chemical reaction of bioactive glass and glass-ceramics with a simulated body fluid (1992) J Biomed Mater Res, 3, pp. 79-83; Blakeslee, D.M., Dal-Favero, M.E., (1997) NIST X-ray Photoelectron Spectroscopy Database, , Gaitherburg, MD: National Institute of Standards and Technology; Anderson, O.H., Kangasniemi, I., Calcium phosphate formation at the surface of bioactive glass in vitro (1991) J Biomed Mater Res, 25, pp. 1019-1030; Santos, J.D., Jha, L.J., Monteiro, F.J., In vitro calcium phosphate formation on SiO 2-Na 2O-CaO-P 2O 5 glass reinforced hydroxyapatite composite: A study by XPS analysis (1996) J Mater Sci Mater Med, 7, pp. 181-185; Verhoeven, J.A.T., Van Doveren, H., An XPS investigation of the interface of methane, ethyne, ethene and ethane with barium surface (1982) Surf Sci, 123, pp. 369-383
Keywords: alloy; Alloys; Apatite; article; Atomic absorption spectroscopy; Atomic spectroscopy; Bioactivity; Biocompatibility; biomaterial; Biomaterials; Biomedical engineering; Body fluids; Calcium; Calcium Compounds; CaO SiO2 P2O5 CaF2 glass; CaO-SiO2-P2O5-CaF2 glass; Chemical analysis; chemical composition; Coated Materials, Biocompatible; Double layer coatings; Double-layer coatings; Durapatite; film; glass; Glass plasma spraying; human; Humans; hydroxyapatite; immersion; implant; in vitro study; Ionic solution changes; Magnesium; materials testing; Molybdenum blue; Multilayers; Particle Size; phosphate; Phosphate minerals; Phosphates; Phosphorus Compounds; phosphorus pentoxide; Plasma spraying; potassium; powder; Powders; resin cement; Resin Cements; Scanning electron microscopy; Sodium; solution and solubility; Solutions; structure analysis; Substrates; Surface Properties; surface property; thickness; Tissue; Titanium; titanium alloy (TiAl6V4); Titanium alloys; X ray photoelectron spectroscopy

Flow cytometry analysis of effects of glass on response of osteosarcoma cells to plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings - Ferraz, M.P.; Knowles, J.C.; Olsen, I.; Monteiro, F.J.; Santos, J.D. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
Multilayered coatings composed of mixtures of hydroxyapatite (HA) and P 2O 5-based bioactive glasses offer potential clinical benefits in orthopedic and dental surgery. In this study double-layer plasma-sprayed coatings were prepared and the biological response evaluated in tissue culture using two human osteosarcoma cell lines, MG63 and HOS TE85 (HOS). The cells were cultured on the materials and the effects on cell growth were determined using a spectrophometric assay of a mitochondrial enzyme that is active in viable cells. While none of the materials influenced the growth of the MG63 cells, the HOS cells appeared to undergo less proliferation on all the HA materials. Flow cytometry analysis was carried out using rabbit antibodies against osteonectin, osteopontin, bone sialoprotein, fibronectin, and collagen type I to measure the effects of the materials on key cellular functions. The results showed that the materials downregulated the expression of these extracellular matrix antigens by MG63 cells whereas they had less effect on the HOS cells compared to the same cells incubated on a plastic surface. Notably, with both cell lines the composite with the higher percentage of glass restored the production of connective tissue proteins to levels that were more similar to those present in the control cells. In this study, double-layer plasma-sprayed coatings were prepared and the biological response evaluated in tissue culture using two human osteosarcoma cell lines, MG63 and HOS TE85 (HOS). The materials downregulated the expression of the extracellular matrix antigens by MG63 cells whereas they had less effect on the HOS cells compared to the same cells incubated on a plastic surface. Notably, with both cell lines the composite with the higher percentage of glass restored the production of connective tissue proteins to levels that were more similar to those present in the control cells.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(19991215)47:4<603::AID-JBM18>3.0.CO;2-6PubMed ID: 10497297Language of Original Document: EnglishCorrespondence Address: Olsen, I.; Department of Periodontology, Eastman Dental Institute, University of London, 256 Gray's Inn Road, London WC1X 8LD, United KingdomChemicals/CAS: Bone Substitutes; Coated Materials, Biocompatible; HydroxyapatitesReferences: Passuti, N., Daculsi, G., Martin, S., Macroporous calcium phosphate ceramics for long bone surgery in human and dogs - Clinical and histological studies (1990) Clinical Implant Materials, pp. 255-258. , Soltesz V, Lee A, editors. Amsterdam: Elsevier Sciesnce Publishers;Legeros, R., Calcium phosphate materials in restorative dentistry. A review (1988) Adv Dent Res, 2, pp. 164-180; Hench, L.L., Bioactive ceramics: From concept to clinic (1992) J Am Ceram Soc, 74, pp. 1487-1510; Conish, H., Aoki, H., Sawai, K., (1981) Science and Medical Applications of Hydroxyapatite, , Tokyo: Takyama Press System Centre Co; Raemdonick, W., Ducheyne, P., Meester, P., Calcium phosphate ceramics (1984) Metal and Ceramic Materials, pp. 143-166. , Ducheyne P, Hastings GW, editors. Boca Raton, FL: CRC Press; Rey, C., Freche, M., Heughebaert, M., Vignoles, M., Apatite chemistry in biomaterial preparation, shaping and biological behaviour (1991) 4th Symposium on Ceramics in Medicine - Bioceramics, 4, pp. 57-64. , Bonfield W, Hastings GW, Tanner KE, editors. London: Butterworth-Heinemann; Nagase, M., Abe, Y., Udagwa, E., Toxicity of silica-containing calcium phosphate glasses demonstrated in mice (1992) Biomaterials, 13, pp. 172-175; Burnie, J., Gilchrist, T., Controlled released glass - A new biomaterial (1983) Ceramics in Surgery, pp. 169-176. , Vicenzini P, editor. Amsterdam: Elsevier Science Publishers; Jha, L.J., Santos, J.D., Knowles, J.C., Characterization of apatite layer formation on P 2O 5-CaO, P 2O 5-CaO-Na 2O, P 2O 5-CaO-Na 2O-Al 2O 3 glass hydroxyapatite composites (1996) J Biomed Mater Res, 31, pp. 481-486; Rawlings, R.D., Rogers, P.S., Stokes, P.M., Glass-ceramics containing apatite (1987) High Tech Ceramics, pp. 73-82. , Vicenzini P, editor. Amsterdam: Elsevier Science Publishers; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterization of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Santos, J.D., Lakhan, J.J., Monteiro, F.J., Surface modifications of glass-reinforced hydroxyapatite composites (1995) Biomaterials, 16, pp. 521-526; Ferraz, M.P., Monteiro, F.J., Santos, J.D., In vitro bioactivity and osteocompatibility evaluation of plasma sprayed hydroxyapatite/glass composite coatings onto Ti-6AL-4V substrates (1997) 9th International Conference on Biomedical Engineering, pp. 557-559. , Goh JCH, editor. Singapore: BAC Printers; Klein, C.P.A.T., Patka, P., Van Der Lubbe, H.B.M., Plasma-sprayed coatings of tetracalcium phosphate, hydroxylapatite, and α-TCP on titanium alloy: An interface study (1991) J Biomed Mater Res, 25, pp. 53-65; Jansen, J.A., Van Der Waerden, J.P., Wolke, J.G., Histologic investigation of the biologic behavior of different hydroxyapatite plasma-sprayed coatings in rabbits (1993) J Biomed Mater Res, 14, pp. 603-610; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., The ultrastructure of the bone-hydroxyapatite interface in vitro (1992) J Biomed Mater Res, 26, pp. 1365-1382; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., Comparative biological properties of HA plasma-sprayed coatings having different crystallinities (1994) J Mater Sci Mater Med, 5, pp. 11-17; Lugscheider, E., Knepper, M., Heimberg, B., Dekker, A., Kirkpatrick, C.J., Cytotoxicity investigations of plasma-sprayed calcium-phosphate coatings (1994) J Mater Sci Mater Med, 5, pp. 371-375; Courteney-Harris, R.G., Kayser, M.V., Downes, S., Comparison of the early production of extracellular matrix on dense hydroxyapatite and hydroxyapatite-coated titanium in cell and organ culture (1995) Biomaterials, 16, pp. 489-495; Labat, B., Chanson, A., Frey, J., Effects of γ-alumina and hydroxyapatite coatings on the growth and metabolism of human osteoblasts (1995) J Biomed Mater Res, 29, pp. 1397-1401; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., Adult human bone cells derived from jaw bones cultured on plasma-sprayed or polished surfaces to titanium or hydroxyapatite discs (1996) J Mater Sci Mater Med, 7, pp. 21-28; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Ariola, C.R., Granchi, D., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin Biomater, 15, pp. 173-190; Puleo, D.A., Preston, K.E., Shaffer, J.B., Bizios, R., Examination of osteoblast-orthopaedic biomaterial interactions using molecular techniques (1993) Biomaterials, 14, pp. 111-114; Clifford, C.J., Downes, S., A comparative study of the use of colorimetric assays in the assessment of biocompatibility (1996) J Mater Sci Mater Med, 7, pp. 637-643; Macey, M.G., (1994) Flow Cytometry - Clinical Applications, , Oxford, UK: Blackwell Scientific Publications; Shapiro, H.M., (1995) Practical Flow Cytometry, , New York: Wiley-Liss; Melamed, M.R., Lindmo, T., Mendelsohn, M.L., (1990) Flow Cytometry and Sorting, , New York: Wiley-Liss; Muirhead, K.A., Horan, P.K., Applications of flow cytometry to tissue culture systems (1983) Adv Cell Culture, 3, pp. 57-91; Corver, W.E., Cornelisse, C.J., Fleuren, G.J., Simultaneous measurement of two cellular antigens and DNA using fluorescein-isothiocyanate, R-phycoerythrin and propidium iodide on a standard FACScan (1994) Cytometry, 15, pp. 117-128; Pande, G., Kumar, N.A., Manogaran, P.S., Flow cytometric study of changes in intracellular free calcium during the cell cycle (1996) Cytometry, 24, pp. 55-63; Kamiya, I., Okuda, K., Hara, K., Flow cytometric identification and detection of Porphyromonas gingivalis by a lps specific monoclonal antibody (1994) J Periodontol, 65, pp. 309-315; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Kuru, L., Parkar, M.H., Griffiths, G.S., Newman, H.N., Olsen, I., Flow cytometry analysis of functionally distinct gingival and periodontal ligament cells (1998) J Dent Res, 77, pp. 555-564; Abraham, D., Lupoli, S., McWhirter, A., Plater-Zyberk, C., Piela, T.H., Korn, J., Olsen, I., Black, C., Expression and function of surface antigens on scleroderma fibroblasts (1991) Arthritis Rheum, 34, pp. 1164-1172; Beauchamp, J.R., Abraham, D.J., Bou-Gharios, G., Partridge, T.A., Olsen, I., Expression and function of adhesion molecules during differentiation of human skeletal muscle in culture (1992) Am J Pathol, 140, pp. 387-401; Bou-Gharios, G., Osman, J., Black, C., Olsen, I., Excess matrix accumulation in scleroderma is caused partly by differential regulation of stromelysin and TIMP-1 synthesis (1994) Clin Chim Acta, 231, pp. 69-78; Lopes, M.A., Knowles, J.C., Hing, K.A., Santos, J.D., Monteiro, F.J., Olsen, I., Biological evaluation of glass reinforced hydroxyapatite by flow cytometry (1997) 10th Symposium on Ceramics in Medicine-bioceramics, 10, pp. 575-578. , Sedel L, Rey C, editors. Cambridge, UK: University Press; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Sandy, J., Davies, M., Prime, S., Farndale, R., Signal pathways that transduce growth factor-stimulated mitogenesis in bone cells (1998) Bone, 23, pp. 17-26
Keywords: Animals; Antibodies; antigen expression; article; Bioassay; Biomaterials; Bone cells; Bone sialoprotein; Bone Substitutes; calcium phosphate; cancer cell culture; Cell Division; cell function; cell granule; cell growth; cell proliferation; Cell size; Cells; Coated Materials, Biocompatible; Collagen; collagen type 1; connective tissue; controlled study; dentistry; enzyme activity; Enzymes; Fibronectin; flow cytometry; Flow cytometry analysis; glass; Growth kinetics; human; human cell; Humans; hydroxyapatite; Hydroxyapatite-glass; Hydroxyapatites; Incubation; Mitochondrial enzyme; orthopedics; Osteoblasts; osteonectin; Osteopontin; Osteosarcoma; osteosarcoma cell; Osteosarcoma cells; Phosphates; Proliferation; Proteins; Rabbits; sialoprotein; Spectrophometric assay; Tissue culture; Tumor Cells, Cultured

Glass-reinforced hydroxyapatite composites: Secondary phase proportions and densification effects on biaxial bending strength - Lopes, M.A.; Monteiro, F.J.; Santos, J.D. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
CaO-P 2O 5 glasses with additions of MgO and CaF 2 were used as a sintering aid of hydroxyapatite, and glass-reinforced hydroxyapatite composites obtained. Glasses promoted significant changes in the microstructure of the composites, namely with the formation of tricalcium phosphate secondary phases, β and α-TCP. Quantitative phase analysis was performed by the Rietveld method using General Structure Analysis Software. Grain size measurements were carried out on SEM photomicrographs, using a planimetric procedure according to ASTM E 112-88. Flexural bending strength was determined from concentric ring-on-ring testing. Flexural bending strength (FBS) of glass-reinforced hydroxyapatite composites was found to be about twice or three times higher than that of unreinforced hydroxyapatite and tended to depend more on porosity and β and α-TCP secondary phases, rather than on grain size. Traces of α-tricalcium phosphate significantly enhanced the strength of the composites. Using the rule of mixtures to estimate the zero porosity bending strength, the Duckworth-Knudsen model applied to the composites gave a porosity correction factor, b, with a value of 4.02. Weibull statistics were also used to analyze biaxial strength data and the level of reinforcement obtained by comparing failure probability for the composites and for the unreinforced hydroxyapatite. Lower activation energies for grain growth were observed for the composites compared to unreinforced hydroxyapatite, which should be attributed to the presence of a liquid glassy phase that promotes atomic diffusion during the sintering process. CaO-P 2O 5 glasses with additions of MgO and CaF 2 were used as a sintering aid of hydroxyapatite, and glass-reinforced hydroxyapatite composites obtained. Glasses promoted significant changes in the microstructure of the composites, namely with the formation of tricalcium phosphate secondary phases, β and α-TCP. Quantitative phase analysis was performed by the Rietveld method using General Structure Analysis Software. Grain size measurements were carried out on SEM photomicrographs, using a planimetric procedure according to ASTM E 112-88. Flexural bending strength was determined from concentric ring-on-ring testing. Flexural bending strength (FBS) of glass-reinforced hydroxyapatite composites was found to be about twice or three times higher than that of unreinforced hydroxyapatite and tended to depend more on porosity and β and α-TCP secondary phases, rather than on grain size. Traces of α-tricalcium phosphate significantly enhanced the strength of the composites. Using the rule of mixtures to estimate the zero porosity bending strength, the Duckworth-Knudsen model applied to the composites gave a porosity correction factor, b, with a value of 4.02. Weibull statistics were also used to analyze biaxial strength data and the level of reinforcement obtained by comparing failure probability for the composites and for the unreinforced hydroxyapatite. Lower activation energies for grain growth were observed for the composites compared to unreinforced hydroxyapatite, which should be attributed to the presence of a liquid glassy phase that promotes atomic diffusion during the sintering process.
Cited By (since 1996): 28Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(1999)48:5<734::AID-JBM20>3.0.CO;2-2PubMed ID: 10490690Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB-Instituto Engenharia Biomedica, Laboratorio de Biomateriais, Rua do Campo Alegre, 823, 4150 Porto, PortugalChemicals/CAS: alpha-tricalcium phosphate; Biocompatible Materials; calcium phosphate, 10103-46-5; Calcium Phosphates; dicalcium phosphate anhydrous, 7757-93-9; Hydroxyapatites; monocalcium phosphate; tetracalcium phosphateReferences: Yamamuro, Y., Hench, L.L., Wilson, J., (1990) CRC Handbook of Bioactive Ceramics, , Boca Raton, FL: CRC;Rice, R.W., Microstructure dependence of mechanical behaviour (1977) Treatise on Materials Science and Technology, 11. , MacCrone RK, editor. New York: Academic; Rice, R.W., Grain size and porosity dependence of ceramic fracture energy and toughness at 22°C (1996) J Mat Sci, 31, pp. 1969-1983; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Wayne, S.F., Buljan, S.T., Microstructure and wear resistance of silicon nitride composites (1994) Friction and Wear of Ceramics, p. 261. , Jahanmir S, editor. New York: Marcel Dekker; Kaysser, W.A., Sprissler, M., Handwerker, C.A., Blendell, J.E., Effect of liquid phase on the morphology of grain growth of alumina (1987) J Am Ceram Soc, 70, pp. 339-343; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Soltesz, U., Ritcher, H., Kienzler, R., The concentric-ring test and its applications for determining the surface strength of ceramics (1987) High Tech Ceram, pp. 149-159. , Amsterdam: Elsevier; Murtage, B., (1981) Advance Linear Programming, , New York: McGraw-Hill; Cha'tal, V., (1990) Linear Programming, , New York: Freeman; Davidge, R.W., (1986) Mechanical Behaviour of Ceramics, , Cambridge: Cambridge Univ Press; German, R.M., (1985) Liquid Phase Sintering, , New York: Plenum; Akao, M., Aoki, H., Kato, K., Mechanical properties of sintered hydroxyapatite for prosthetic applications (1981) J Mater Sci, 16, pp. 809-812; Fanovich, M.A., Lopes, J.M.P., Influence of temperature and additives on the microstructure and sintering behaviour of hydroxyapatites with different Ca/P ratios (1998) J Mat Sci Mat Med, 9, pp. 53-60; Jarcho, M., Bolen, C.H., Bobik, J., Kay, J.F., Doremus, R.H., Hydroxyapatite synthesis and characterisation in dense polycrystalline form (1976) J Mat Sci, 11, pp. 2027-2035; Van Landuyt, P., Li, F., Keustermans, J.P., Streydio, J.M., Delnnay, F., Munting, E., The influence of high sintering temperatures on the mechanical properties of hydroxyapatite (1995) J Mat Sci Mat Med, 6, pp. 8-13; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , Japanese Association of Apatite Layer; Chawla, K.K., (1993) Ceramic Matrix Composites, , London, UK: Chapman Hall; Barsoum, M., Fundamentals of Ceramics, , New York: McGraw-Hill; 1997
Keywords: article; atom; Bending (deformation); Biocompatibility; Biocompatible Materials; Biomaterials; calcium fluoride; calcium phosphate; Calcium phosphates; Composite materials; Densification; Dental application; dentistry; Duckworth-Knudsen model; glass; Glass reinforced hydroxyapatite; Humans; hydroxyapatite; Hydroxyapatite-glass composites; Hydroxyapatites; Implants (surgical); Magnesium Oxide; mathematical analysis; Mechanical strength; Mechanics; Medical applications; Microstructure; orthopedics; Phase composition; physical chemistry; porosity; Scanning electron microscopy; Strength of materials; tensile strength; Tissue; Tricalcium phosphate

In vitro osteoblastic differentiation of human bone marrow cells in the presence of metal ions - Morais, S.; Dias, N.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
For periods up to 21 days human bone marrow was cultured in control conditions that favor the proliferation and differentiation of osteoblastic cells. The effect of AISI 316L corrosion products and the corresponding major separate metal ions (Fe, Cr, and Ni) were studied in three different phases of the culture period in order to investigate the effects of metal ions in cell populations representative of osteoblastic cells in different stages of differentiation. Toxicity consequences of the presence of metal ions in bone marrow cultures were evaluated by biochemical parameters (enzymatic reduction of MTT, alkaline phosphatase activity, and total protein content), histochemical assays (identification of ALP-positive cells and Ca and phosphates deposits), and observation of the cultures by light and scanning electron microscopy. Culture media were analyzed for total and ionized Ca and P and also for metal ions (Fe, Cr, and Ni). The presence of AISI 316L corrosion products and Ni salt in bone marrow cultures during the first and second weeks of culture significantly disturbs the normal behavior of these cultures, interfering in the lag phase and exponential phase of cell growth and ALP expression. However, the presence of these species during the third week of culture, when expression of osteoblastic functions occurs (mineralization process), did not result in any detectable effect. Fe salt also disturbs the behavior of bone marrow cell cultures when present during the lag phase and proliferation phase, and a somewhat compromised response between the normal pattern (control cultures) and intense inhibition (AISI 316L corrosion products and Ni salt-added cultures) was observed. Fe did not affect the progression of the mineralization phase. Osteogenic cultures exposed to Cr salt (Cr 3+) presented a pattern similar to the controls, indicating that this element does not interfere, in the concentration studied, in the osteoblastic differentiation of bone marrow cells. Quantification of metal ions in the culture media showed that Cr (originated from AISI 316L corrosion products but from not Cr 3+ salt) and Ni (originated from AISI 316L corrosion products and Ni salt) appear to be retained by the bone marrow cultures. For periods up to 21 days human bone marrow was cultured in control conditions that favor the proliferation and differentiation of osteoblastic cells. The effect of AISI 316L corrosion products and the corresponding major separate metal ions (Fe, Cr, and Ni) were studied in three different phases of the culture period in order to investigate the effects of metal ions in cell populations representative of osteoblastic cells in different stages of differentiation. Toxicity consequences of the presence of metal ions in bone marrow cultures were evaluated by biochemical parameters (enzymatic reduction of MTT, alkaline phosphatase activity, and total protein content), histochemical assays (identification of ALP-positive cells and Ca and phosphates deposits), and observation of the cultures by light and scanning electron microscopy. Culture media were analyzed for total and ionized Ca and P and also for metal ions (Fe, Cr, and Ni). The presence of AISI 316L corrosion products and Ni salt in bone marrow cultures during the first and second weeks of culture significantly disturbs the normal behavior of these cultures, interfering in the lag phase and exponential phase of cell growth and ALP expression. However, the presence of these species during the third week of culture, when expression of osteoblastic functions occurs (mineralization process), did not result in any detectable effect. Fe salt also disturbs the behavior of bone marrow cell cultures when present during the lag phase and proliferation phase, and a somewhat compromised response between the normal pattern (control cultures) and intense inhibition (AISI 316L corrosion products and Ni salt-added cultures) was observed. Fe did not affect the progression of the mineralization phase. Osteogenic cultures exposed to Cr salt (Cr 3+) presented a pattern similar to the controls, indicating that this element does not interfere, in the concentration studied, in the osteoblastic differentiation of bone marrow cells. Quantification of metal ions in the culture media showed that Cr (originated from AISI 316L corrosion products but from not Cr 3+ salt) and Ni (originated from AISI 316L corrosion products and Ni salt) appear to be retained by the bone marrow cultures.
Cited By (since 1996): 35Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(199902)44:2<176::AID-JBM8>3.0.CO;2-6PubMed ID: 10397919Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Universidade do Porto, Rua Dr Manuel Pereira da Silva, 4200 Porto, PortugalChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Alloys; Biocompatible Materials; Calcium, 7440-70-2; Chromium, 7440-47-3; Iron, 7439-89-6; Metals; Nickel, 7440-02-0; Phosphorus, 7723-14-0; Proteins; Stainless Steel, 12597-68-1; Tetrazolium Salts; Thiazoles; thiazolyl blue, 298-93-1References: Williams, D., Cahn, R.W., Bever, M.B., (1990) Concise Encyclopedia of Medical & Dental Materials, pp. 4-70. , Oxford, New York, Beijing, Frankfurt, São Paulo, Sydney, Tokyo, Toronto: Permagon Press;Linden, J.V., Hopler, S.M., Gossling, H.R., Sunderman Jr., F.W., Blood nickel concentrations in patients with stainless-steel hip protheses (1985) Ann Clin Lab Sci, 15, pp. 459-464. , 1985; Weber, G.W., Reid, B.L., Nickel toxicity in young growing mice (1969) J Animal Sci, 28, pp. 620-623; O'Dell, G.D., Miller, W.J., King, W.A., Moore, S.L., Blackmon, D.M., Nickel toxicity in the young bovine (1970) J Nutrition, 100, pp. 1447-1453; Louria, D.B., Joselow, M.M., Browder, A.A., The human toxicity of certain trace elements (1972) Ann Intern Med, 76, pp. 307-319; Whanger, P.D., Effects of dietary nickel on enzyme activities and mineral contents in rats (1973) Toxicol Appl Pharmacol, 25, pp. 323-331; Woodman, J.L., Black, J., Jimenez, S., Organometallic corrosion products of 316L SS and HS-21 in serum: In vitro and in vivo comparison in an acute rat model (1982) Biomaterials 1980, pp. 245-253. , Winter GD, Gibbon DF, Plenk Jr H, editors. Chichester, New York, Brisbone, Toronto, Singapore: John Wiley & Sons; Parfitt, A.M., The physiological and clinical significance of bone histomorphometric data (1983) Bone Histomorphometry: Techniques and Interpretation, pp. 143-223. , Recker RR, editor. Boca Raton, Florida: CRC Press; Jilka, R.L., Manolagas, S.C., The cellular and biochemical basis of bone remodeling (1994) Osteoporosis, pp. 17-48. , Marcus R, editor. Boston: Blackwell Scientific Publications; Owen, M., Lineage of osteogenic cells and their relationship to the stromal system (1985) Bone and Mineral Research, 3, pp. 1-25. , Peck WA, editor. Amsterdam: Elsevier Science Publishers; Owen, T.A., Aronow, M., Shalhoub, V., Progressive development of the rat osteoblast phenotype in vitro: Reciprocal relationships in expression of genes associated with osteoblast proliferation and differentiation during formation of the bone extracellular matrix (1990) J Cell Physiol, 143, pp. 420-430; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionized Ca in osteoblast-like cell culture medium (1996) Electroanalysis, 8 (12), pp. 1174-1178; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9 (10), pp. 791-795; Morais, S., Carvalho, G.S., Sousa, J.P., Chromium determination in osteoblast-like cell culture medium by catalytic cathodic stripping voltammetry with a mercury microelectrode (1998) J Trace Elements Med Biol, 2, pp. 101-108; Morais, S., Carvalho, G.S., Sousa, J.P., Determination of Ni in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with mercury microelectrodes (1997) Electroanalysis, 9 (5), pp. 422-426; Morais, S., Carvalho, G.S., Sousa, J.P., Optimization study for nickel quantification in cell culture medium using mercury film microelectrodes (1996) Portugaliae Electrochimica Acta, 14, pp. 267-272; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tiss Res, 254, pp. 317-330; Berridge, V., Tan, A.S., Characterization of the cellular reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT): Subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch Biochem Biophys, 303, pp. 474-482; Bessey, O., Lowry, O., Breck, M., A method for the rapid determination of alkaline phosphatase with five cubic millileters of serum (1946) J Biol Chem, 164, pp. 321-326; McGee-Russell, M., Histochemical methods for calcium (1958) J Histochem Cytochem, 6, pp. 22-42; Fiske, C.H., Subbarow, Y., The colorimetric determination of phosphorus (1925) J Biol Chem, 66, pp. 373-400; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulate formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 143, pp. 213-221; Gotoh, Y., Hiraiwa, K., Narajama, M., In vitro mineralization of osteoblastic cells derived from human bone (1990) Bone and Miner, 8, pp. 239-250; Cheng, S.L., Yang, J.W., Riffas, L., Zhang, S.F., Avioli, L.V., Differentiation of human bone marrow osteogenic stromal cells in vitro. Induction of the osteoblast phenotype by dexamethasone (1994) Endocrinology, 134, pp. 277-286; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone-derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Arcicla, C.R., Granchi, D.C., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin Mater, 15, pp. 173-190; Gerstenfeld, L.C., Chipman, S.D., Glowacki, J., Lian, J.B., Expression of differential function by mineralizing cultures of chicken osteoblasts (1987) Dev Biol, 122, pp. 46-60; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone and Miner, 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone and Miner, 17, pp. 15-29; Chung, C.H., Golub, E.E., Forbes, E., Tokuoka, T., Shapiro, I.M., Mechanisms of action of β-glycerophosphate on bone cell mineralization (1992) Calcif Tissue Int, 51, pp. 305-311; Boskey, A.L., Stiner, D., Doty, S.B., Binderman, I., Levoy, P., Studies of mineralization in tissue culture: Optimal conditions for cartilage calcification (1992) Bone and Miner, 16, pp. 11-36; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., De Bruijn, J.D., Van Blitterswijk, C.A., Decreased consumption of Ca and P during in vitro biomineralization and biologically induced deposition of Ni and Cr in presence of stainless steel corrosion products (1998) J Biomed Mater Res, 42, pp. 199-212; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralization by osteoblast-like cells. 1. Retardation of tissue mineralization by metal salts (1998) Biomaterials, 19, pp. 13-21; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., De Bruijn, J.D., Van Blitterswijk, C.A., Effects of AISI 316L corrosion products in in vitro bone formation (1998) Biomaterials, 19, pp. 999-1007; Stein, G.S., Lian, J.B., Molecular mechanisms mediating developmental and hormone-regulated expression of genes in osteoblasts: An integrated relationship of cell growth and differentiation (1993) Cellular and Molecular Biology of Bone, pp. 47-95. , Noda M, editor. Tokyo: Academic Press Inc; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., The ultrastructure of the one-hydroxyapatite interface in vitro (1992) J Biomed Mater Res, 26, pp. 1365-1382; Stein, G.S., Lion, J.B., Molecular mechanisms mediated proliferation-differentiation interrelationships during progressive development of the osteoblast phenotype: Update 1995 (1995) Endocrin Rev, 4, pp. 290-297; Abe, Y., Akamine, A., Aida, Y., Maeda, K., Differentiation and mineralization in osteogenic precursor cells derived from fetal rat mandibular bone (1993) Calcif Tissue Int, 52, pp. 365-371; Lomri, A., Tran, M.P.V., Mott, M., Characterization of endosteal osteoblastic cells isolated from mouse caudal vertebrae (1988) Bone, 9, pp. 165-175; McCulloch, C.A.G., Fair, C.A., Tenebaum, H.C., Limeback, H., Homareau, R., Clonal distribution of osteoprogenitor cells in cultured chick peristoa: Functional relationship to bone formation (1990) Dev Biol, 140, pp. 352-361; Sun, Z.L., Wataha, J.C., Hanks, C.T., Effects of metal ions on osteoblast-like cell metabolism and differentiation (1997) J Biomed Mater Res, 34, pp. 29-37; Puleo, D.A., Huh, W.W., Acute toxicity of metal ions in cultures of osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 109-116; Katz, S.A., Salem, H., The toxicology of Cr with respect to its chemical speciation: A review (1993) J Appl Toxicol, 13, pp. 217-224; Anderson, H.C., Morris, D.C., Mineralization (1993) Handbook of Experimental Pharmacology, pp. 267-298. , Mundy GR, Martin TJ, editors. Berlin: Springer-Verlag; Merritt, K., Brown, S.A., Biological effects of corrosion products from metals (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 195-207. , Fraker AC, Griffin CD, editors. ASTM STP 859. Philadelphia: American Society for Testing and Materials; Rae, T., The toxicity of metals used in orthopaedic prostheses (1981) J Bone Joint Surg, 63 B, pp. 435-440; Webb, M., Weinzier, S.M., Uptake of 63Ni 2+ from its complexes with proteins and other ligands by mouse dermal fibroblasts in vitro (1972) Br J Cancer, 26, pp. 292-298; Merritt, K., Wortman, R.S., Millard, M., Brown, S.A., XPS analysis of 316LVM corroded in serum and saline (1983) Biomater Med Devices Artif Organs, 11, pp. 115-124; Bianchi, V., Toso, R.D., Debetto, P., Mechanisms of chromium toxicity in mammalian cell cultures (1980) Toxicology, 17, pp. 219-224; Lucas, L.C., Bearden, L.J., Lemons, J.E., Ultrastructural examination of in vitro and in vivo cells exposed to elements from type 316L stainless steel (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 208-222. , Fraker AC, Griffin CD, editors. ASTM STP 859. Philadelphia: American Society for Testing and Materials
Keywords: alkaline phosphatase; Alloys; article; Batch cell culture; Biocompatible Materials; biotechnology; Bone; Bone cells; bone marrow cell; Bone Marrow Cells; bone mineralization; bone prosthesis; Calcium; Cell culture; cell differentiation; Cell Division; cell population; Cells, Cultured; Chromium; controlled study; Corrosion; Corrosion products; Cytotoxicity; Differentiation; human; human cell; Human osteoblast-like cells; Humans; Implants (surgical); Ions; Iron; joint prosthesis; materials testing; metal ion; Metal ions; Metals; Nickel; osteoblast; Osteoblasts; phosphorus; Prostheses and Implants; Proteins; Stainless steel; Steel corrosion; Tetrazolium Salts; Thiazoles

Classification of foetal heart rate sequences based on fractal features - Felgueiras, C.S.; De Marques Sá, J.P.; Bernardes, J.; Gama, S. (Medical and Biological Engineering and ComputingMed. Biol. Eng. Comput., 1998)
Visual inspection of foetal heart rate (FHR) sequences is an important means of foetal well-being evaluation. The application of fractal features for classifying physiologically relevant FHR sequence patterns is reported. The use of fractal features is motivated by the difficulties exhibited by traditional classification schemes to discriminate some classes of FHR sequence and by the recognition that this type of signal exhibits features on different scales of observation, just as fractal signals do. To characterise the signals by fractal features, two approaches are taken. The first models the FHR sequences as temporal fractals. The second uses techniques from the chaos-theory field and aims to model the attractor based on FHR sequences. The fractal features determined by both approaches are used to design a Bayesian classification scheme. Classification results for three classes are presented; they are quite satisfactory and illustrate the importance of this type of methodology.Visual inspection of foetal heart rate (FHR) sequences is an important means of foetal well-being evaluation. The application of fractal features for classifying physiologically relevant FHR sequence patterns is reported. The use of fractal features is motivated by the difficulties exhibited by traditional classification schemes to discriminate some classes of FHR sequence and by the recognition that this type of signal exhibits features on different scales of observation, just as fractal signals do. To characterise the signals by fractal features, two approaches are taken. The first models the FHR sequences as temporal fractals. The second uses techniques from the chaos-theory field and aims to model the attractor based on FHR sequences. The fractal features determined by both approaches are used to design a Bayesian classification scheme. Classification results for three classes are presented; they are quite satisfactory and illustrate the importance of this type of methodology.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: MBECDdoi: 10.1007/BF02510743PubMed ID: 9684460Language of Original Document: EnglishCorrespondence Address: Felguiras, C.S.; Instituto de Engenharia Biomedica, Praca Coronel Pacheco 1, 4050 Porto, PortugalReferences: Bernardes, J., (1993) Leitura Automatizada Do Cardiotocograma. Desenvolvimento e Availiaçào, , Ph.D. thesis, Faculdade de Medicina da Universidade do Porto, Portugal;Bernardes, J., Moura, C., Marques De Sá, J.P., Pereira Leite, L., Van Geijn, H.P., The Porto system (1994) A Critical Appraisal of Foetal Surveillance, pp. 315-324. , VAN GEIJN H. P. and COPRAY, F. J. A. (Eds.) Elsevier Science, Amsterdam; Chaffin, D.G., Goldberg, C.C., Reed, K.L., The dimension of chaos in foetal heart rate (1991) Am. J. Obstet. Gynecol., 165 (5), pp. 1425-1429; Dawes, G.S., Visser, G.H.A., Goodman, J.D.S., Redman, C.W.G., Numerical analysis of human foetal heart rate: The quality of ultrasound records (1981) Am. J. Obstet, Gynecol., 141 (1), pp. 43-52; Felgueiras, C.S., Marques De Sá, J.P., Bernardes, J., Gama, S., On the reconstruction of foetal heart rate sequences (1996) Actas de Bieng '96, Sociedade Portuguesa de Engenharia Biomédica, Aveiro, Março, 1996, pp. VII61-VII65; Goldberger, A.L., Fractal mechanisms in the electrophysiology of the heart (1992) IEEE Eng. Med. Biol., pp. 47-52. , June; Grant, A., Principles for clinical evaluation of methods of perinatal monitoring (1984) J. Perinat. Med., 12, pp. 227-231; Grassberger, P., Procaccia, I., Measuring the strangeness of strange attractors (1983) Physica D, 9, pp. 189-208; Higushi, T., Approach to an irregular time series on the basis of the fractal theory (1988) Physica D, 31, pp. 277-283; Hoyer, D., Liebovitch, L.S., Schmidt, K., Luethke, B., Zwiener, U., Practical problems of determining the dimensions of heart rate data (1997) Med. Biol. Eng. Comput., 35, pp. 27-32; Maldelbrot, B.B., Van Ness, J.W., Fractional Brownian motions, fractional noises and applications (1968) SIAM Rev., 10 (4), pp. 422-437; Marques De Sa, J.P., Moura, A.C., Bernardes, J., Pereira Leite, L., Análise automática de sinais cardiotocográficos (1992) Acta Médica Portuguesa 11 Série, 5 (1), pp. 28-30; Parker, T.S., Chua, L.O., (1989) Practical Numerical Algorithms for Chaotic Systems, , Springer-Verlag; Schulman, H., Schulman, S., Lai, P., Schneider, E., Farmakides, G., Dawes, G., Antepartum computerized foetal heart rate, chaos analysis, blood gases and perinatal outcome (1994) J. Maternal-Fetal Invest., 4, pp. 59-63
Keywords: article; Bayes Theorem; Cardiology; Chaos techniques; Chaos theory; Classification; Computer aided analysis; Computer simulation; Electrocardiography; Female; Fetal monitoring; fetus; fetus heart rate; FHR classification; FHR sequence; Foetal heart rate sequences; fractal analysis; Fractal features; Fractals; Heart Rate, Fetal; human; Humans; Pattern recognition; Pregnancy; Signal Processing, Computer-Assisted; technique

Flow cytometry for assessing biocompatibility - Lopes, M.A.; Knowles, J.C.; Kuru, L.; Santos, J.D.; Monteiro, F.J.; Olsen, I. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1998)
Flow cytometry (FCM) was examined as a possible procedure for measuring in vitro the biocompatibility of implant materials for orthopedic and dental surgery. The human osteoblast-like cell line MG63 was grown on hydroxyapatite (HA) and P 2O 5 glass-reinforced HA composite discs and compared with the same cells grown on polystyrene culture dishes. While morphological observation at the light and electron microscopic levels showed no major deleterious effects, FCM indicated that cell size was somewhat reduced, particularly by growth on the HA composite. Moreover, this material also appeared to delay the progression of the cells from the G0/G1 into the S phase of the cell cycle. In addition to this low level of inhibition of cell growth relative to control cultures, FCM analysis also demonstrated that the glass-reinforced HA caused some down-regulation of the expression of osteocalcin and fibronectin, two antigens which play a vital part in the integrity and function of bone and soft connective tissue, respectively. These results thus show, first, that although HA and the HA composite used in these experiments were generally biocompatible, they nevertheless had certain suboptimal effects on the cells; and second, that FCM could be a highly useful procedure for effectively screening and evaluating important biological responses to implant materials. Flow cytometry (FCM) was examined as a possible procedure for measuring in vitro the biocompatibility of implant materials for orthopedic and dental surgery. The human osteoblast-like cell line MG63 was grown on hydroxyapatite (HA) and P 2O 5 glass-reinforced HA composite discs and compared with the same cells grown on polystyrene culture dishes. While morphological observation at the light and electron microscopic levels showed no major deleterious effects, FCM indicated that cell size was somewhat reduced, particularly by growth on the HA composite. Moreover, this material also appeared to delay the progression of the cells from the G0/G1 into the S phase of the cell cycle. In addition to this low level of inhibition of cell growth relative to control cultures, FCM analysis also demonstrated that the glass-reinforced HA caused some down-regulation of the expression of osteocalcin and fibronectin, two antigens which play a vital part in the integrity and function of bone and soft connective tissue, respectively. These results thus show, first, that although HA and the HA composite used in these experiments were generally biocompatible, they nevertheless had certain suboptimal effects on the cells; and second, that FCM could be a highly useful procedure for effectively screening and evaluating important biological responses to implant materials.
Cited By (since 1996): 33Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(19980915)41:4<649::AID-JBM17>3.0.CO;2-9PubMed ID: 9697038Language of Original Document: EnglishCorrespondence Address: Olsen, I.; Department of Periodontology, Eastman Dental Institute, University of London, 256 Gray's Inn Rd., London WC1X 8LD, United KingdomChemicals/CAS: Biocompatible Materials; Collagen, 9007-34-5; Dental Implants; Fibronectins; Osteocalcin, 104982-03-8References: Kirkpatrick, C.J., A critical view of current and proposed methodologies for biocompatibility testing: Cytotoxicity in vitro (1992) Regul. Affairs, 4, pp. 13-32;Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Ariola, C.R., Granchi, D., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin. Mater., 15, pp. 173-190; Puleo, D.A., Preston, K.E., Shaffer, J.B., Bizios, R., Examination of osteoblast-orthopaedic biomaterial interactions using molecular techniques (1993) Biomaterials, 14, pp. 111-114; Clifford, C.J., Downes, S., A comparative study of the use of colorimetric assays in the assessment of biocompatibility (1996) J. Mater. Sci. Mater. Med., 7, pp. 637-643; Macey, M.G., (1994) Flow Cytometry: Clinical Applications, , Blackwell Scientific Publications, Oxford; Salzman, G.C., Singham, S.B., Johnston, R.G., Bohren, C.F., Light scattering and cytometry (1990) Flow Cytometry and Sorting, pp. 81-107. , M. R. Melamed, T. Lindmo, and M. L. Mendelsohn (eds.), Wiley-Liss, New York; Corver, W.E., Cornelisse, C.J., Fleuren, G.J., Simultaneous measurement of two cellular antigens and DNA using fluorescein-isothiocyanate, R-phycoerythrin and propidium iodide on a standard FACScan (1994) Cytometry, 15, pp. 117-128; Macon, W.R., Salhany, K.E., TI- T-cell subset analysis of paraffin-embedded peripheral T-cell lymphomas (PTCLs) with correlation of CD4/CD8 results by flow cytometry (FACs) (1997) Lab. Invest., 76, p. 753; Kuru, L., Parkar, M.H., Griffiths, G.S., Newman, H.N., Olsen, I., Flow cytometry analysis of functionally distinct gingival and periodontal ligament cells (1998) J. Dent. Res., 77, pp. 555-564; Kamiya, I., Okuda, K., Hara, K., Flow cytometric identification and detection of Porphromonas gingivalis by an LPS specific monoclonal antibody (1994) J. Periodontol., 65, pp. 309-315; Sumner, H., Abraham, D., Bou-Gharios, G., Plater-Zyberk, C., Olsen, I., Simultaneous measurement of cell surface and intracellular antigens by multiple flow cytometry (1991) J. Immunol. Methods, 136, pp. 259-267; Beauchamp, J.R., Abraham, D.J., Bou-Gharios, G., Partridge, T.A., Olsen, I., Expression and function of adhesion molecules during differentiation of human skeletal muscle in culture (1992) Am. J. Pathol., 140, pp. 387-401; Abraham, D., Lupoli, S., McWhirter, A., Plater-Zyberk, C., Piela, T.H., Korn, J., Olsen, I., Black, C., Expression and function of surface antigens on scleroderma fibroblasts (1991) Arthritis Rheum., 34, pp. 1164-1172; Bou-Gharios, G., Osman, J., Black, C., Olsen, I., Excess matrix accumulation in scleroderma is caused partly by differential regulation of stromelysin and TIMP-1 synthesis (1994) Clin. Chim. Acta, 231, pp. 69-78; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Best, S., Sim, B., Kayser, M., Downes, S., The dependence of osteoblastic response on variations in the chemical composition and physical properties of hydroxyapatite (1997) J. Mater. Sci. Mater. Med., 8, pp. 97-103; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Dean, D.D., Boyan, B.D., Effect of titanium surface roughness on proliferation, differentiation and protein synthesis of human osteoblast-like cells (MG-63) (1995) J. Biomed. Mater. Res., 29, pp. 389-401; Granchi, D., Stea, S., Ciapetti, G., Savarino, L., Cavedagna, D., Pizzoferatto, A., In vitro effects of bone cements on the cell cycle of osteoblast-like cells (1995) Biomaterials, 16, pp. 1187-1192; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Scharla, S.H., Strong, D.D., Rosen, C., Mohan, S., Holick, M., Baylink, D.J., Linkhart, T.A., 1,25-Dihydroxyvitamin D3 increases secretion of insulin-like growth factor binding protein-4 (IGFBP-4) by human osteoblast-like cells in vitro and elevates IGFBP-4 serum levels in vivo (1993) J. Clin. Endocrinol. Metabol., 77, pp. 1190-1197; De Bart, A.C., Quax, P.H., Lowik, C.W., Verheijen, J.H., Regulation of plasminogen activation, matrix metalloproteinases and urokinase-type plasminogen activator-mediated extracellular matrix degradation in human osteosarcoma cell line MG63 by interleukin-1 alpha (1995) J. Bone Min. Res., 19, pp. 1374-1384; Barille, S., Collette, M., Bataille, R., Amiot, M., Myeloma cells upregulate interleukin-6 secretion in osteoblastic cells through cell-to-cell contact but downregulate osteocalcin (1995) Blood, 86, pp. 3151-3159; Maillard, C., Malaval, L., Delmas, P.D., Immunological screening of SPARC/osteonectin in nonmineralized tissue (1992) Bone, 13, pp. 257-264; Bou-Gharios, G., Osman, J., Atherton, A., Monoghan, P., Vancheeswaran, R., Black, C., Olsen, I., Expression of ectopeptidases in scleroderma (1995) Ann. Rheum. Dis., 54, pp. 111-116; Goseki, T., Shimizu, N., Iwasawa, T., Takiguchi, H., Abiko, Y., Effects of in vitro cellular aging on alkaline phosphatase, cathepsin activities and collagen secretion of human peridontal ligament-derived cells (1996) Mech. Age. Dev., 91, pp. 1761-11183; Hallab, N.J., Bundy, K.J., O'Connor, K., Clark, R., Moses, R.L., Cell adhesion to biomaterials: Correlations between surface charge, surface roughness, adsorbed protein and cell morphology (1995) J. Long-Term Effects Med. Implants, 5, pp. 209-231; Kieswetter, K., Schwartz, Z., Hummert, T.W., Cochran, D.L., Simpson, J., Sean, D.P., Boyan, B.D., Surface roughness modulates the local production of growth factors and cytokines by osteoblast-like MG-63 cells (1996) J. Biomed. Mater. Res., 32, pp. 55-63; Altankov, G., Grinnell, F., Groth, T., Studies on the biocompatibility of materials: Fibroblast reorganization of substratumbound fibronectin on surfaces varying in wettability (1996) J, Biomed. Mater. Res., 30, pp. 385-391; Chesmel, K.D., Clark, C.C., Brighton, C.T., Black, J., Cellular response to chemical and morphologic aspects of biomaterial surfaces. II. The biosynthetic and migratory response of bone cell populations (1995) J. Biomed. Mater. Res., 29, pp. 1101-1110; Nishizawa, K., Toriyama, M., Suzuki, T., Kawamoto, Y., Yokogawa, Y., Nagae, H., Effects of the surface wettability and zeta potential of bioceramics on the adhesiveness of anchorage-dependent animal cells (1993) J. Ferment. Bioeng., 75, pp. 435-437; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J. Biomed. Mater. Res., 39, pp. 244-251
Keywords: antigen expression; Antigens; Biocompatibility; Biocompatible Materials; biomaterial; Biomaterials; Biomedical engineering; Bone and Bones; bone prosthesis; Cell culture; cell cycle; cell cycle s phase; Cell Line; Cell size; cell ultrastructure; Cells; Collagen; conference paper; Dental Implants; dentistry; extracellular matrix; Fibronectin; Fibronectins; flow cytometry; Glass fiber reinforced plastics; growth inhibition; human; human cell; Humans; hydroxyapatite; Implants; Implants (surgical); Microscopy, Electron, Scanning; mitosis inhibition; morphology; orthopedics; Osteoblasts; osteocalcin; Polystyrenes; Prostheses and Implants; prosthesis material; Tissue; tooth prosthesis

Objective computerized fetal heart rate analysis - Bernardes, J.; Ayres-de-Campos, D.; Costa-Pereira, A.; Pereira-Leite, L.; Garrido, A. (International Journal of Gynecology and ObstetricsInt. J. Gynecol. Obstet., 1998)
Objective: To assess the validity of a computerized methodology for cardiotocogram analysis based on a recently described reproducible visual estimation of the baseline. Methods: Forty-two antepartum and 43 intrapartum cardiotocograms (CTGs) acquired by a personal computer were selected. Antepartum tracings were performed in the 48 h that preceded an elective cesarean section, and intrapartum tracings were performed until delivery. FHR baselines were estimated by an expert, according to an objective and reproducible methodology. Using these baselines, automated detection of accelerations and decelerations and estimation of variability was performed by the personal computer. A quantitative adaptation of the FIGO guidelines for fetal monitoring was used to classify tracings. Perinatal outcome was classified according to the Apgar score and umbilical arterial pH. Validity was then assessed by the proportions of agreement (PA), kappa statistic (κ), sensitivity and specificity, with 95% confidence intervals (95% CI). Cases showing a disagreement between CTG and perinatal classification were reviewed and an adjustment in baseline definition was tested. Results: The initial overall PA and κ between CTG and perinatal classification were, respectively, 0.79 (95% CI: 0.69-0.87) and 0.62 (95% CI: 0.41-0.83). The overall PA and κ, after baseline adjustment were, respectively, 0.89 (95% CI: 0.81-0.95) and 0.78 (95% CI: 0.58-0.98). Sensitivities and specificities ranged between 79% (95% CI: 60-92%) and 100% (95% CI: 95-100%). Conclusions: Good clinical prediction may be possible with an objective methodology for cardiotocogram analysis based on a recently described reproducible baseline estimation.
Cited By (since 1996): 23Export Date: 21 November 2012Source: ScopusCODEN: IJGOAdoi: 10.1016/S0020-7292(98)00079-4PubMed ID: 9749885Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Departmento Ginecologia Obstetricia, Faculdade Medicina-Hospital S. Joao, Porto, Portugal; email: sisporto@mail.telepac.ptReferences: Bernardes, J., Costa-Pereira, A., Ayres-De-Campos, D., Van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57 (1), pp. 33-37;Bernardes, J., Costa-Pereira, A., Van Geijn, H.P., Pereira-Leite, L., A more objective fetal heart rate baseline estimation (1996) Br J Obstet Gynaecol, 103, pp. 714-715; Grant, A., Principles for clinical evaluation of methods of perinatal monitoring (1984) J Perinat Med, 12, pp. 227-231; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., Van Geijn, H.P., The Porto System (1994) A Critical Appraisal of Fetal Surveillance, pp. 315-324. , In: van Geijn HP, Copray FJA, editors. Amsterdam: Elsevier Science; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring. FIGO news (1987) Int J Gynaecol Obstet, 25, pp. 159-167; Mohide, P., Grant, A., Evaluating diagnosis and screening during pregnancy and childbirth (1989) Effective Care in Pregnancy and Childbirth, pp. 66-80. , In: Chalmers I, Enkin M, Keirse M JNC, editors. Oxford University Press; Garcia-Romero, H., Garcia-Barrios, C., Ramos-Gutierrez, F.R., Effects of uncertain results on sensitivity and specificity of diagnostic tests (1996) Lancet, 348, pp. 1745-1746; Grant, J.M., The fetal heart rate is normal, isn't it?. Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Guzman, E., Vintzileos, A., Martins, M., Benito, C., Houlihan, C., The efficacy of individual computer heart rate indices in detecting acidemia at birth in growth-restricted fetuses (1996) Obstet Gynecol, 87, pp. 969-974; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., Computer assessment of the intrapartum cardiotocogram. II. The value of compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464; Chung, T.K.H., Mohajer, M.P., Yang, Z.J., Chang, A.M.Z., Sahota, D.S., The prediction of fetal acidosis at birth by computerized analysis of intrapartum cardiotocography (1995) Br J Obstet Gynaecol, 102, pp. 454-460; Stigsby, B., Nielson, P.V., Nickelsen, C., Nim, J., Computer assessment of the intrapartum cardiotocogram. I. Methods of data reduction and diagnostic procedure (1988) Acta Obstet Gynecol Scand, 67, pp. 455-460
Keywords: Apgar score; arterial pH; article; Cardiotocography; cesarean section; computer analysis; Computerized analysis; Female; Fetal heart rate; fetus; fetus heart rate; fetus monitoring; Heart Rate, Fetal; human; Humans; Image Processing, Computer-Assisted; practice guideline; Predictive Value of Tests; Pregnancy; priority journal; umbilical artery; validity

Semiautomated ultrasonographic measurement of fetal nuchal translucency using a computer software tool - Bernardino, F.; Cardoso, R.; Montenegro, N.; Bernardes, J.; Marques de Sá, J. (Ultrasound in Medicine and BiologyUltrasound Med. Biol., 1998)
Nuchal translucency (NT) thickness measurement has been recently proposed as a part of routine ultrasound scanning during the late first trimester of pregnancy, for the early screening of chromosomal abnormalities. Manual determination of NT is currently performed using electronic callipers placed by the operator in the middle of two echogenic fines displayed on the screen. Therefore, intraobserver and interobserver repeatability can be questioned. This paper presents a software tool that has been developed for achieving this goal in a semiautomatic way, improving the reproducibility of the method.Nuchal translucency (NT) thickness measurement has been recently proposed as a part of routine ultrasound scanning during the late first trimester of pregnancy, for the early screening of chromosomal abnormalities. Manual determination of NT is currently performed using electronic callipers placed by the operator in the middle of two echogenic lines displayed on the screen. Therefore, intraobserver and interobserver repeatability can be questioned. This paper presents a software tool that has been developed for achieving this goal in a semiautomatic way, improving the reproducibility of the method.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: USMBAdoi: 10.1016/S0301-5629(97)00235-4PubMed ID: 9483771Language of Original Document: EnglishCorrespondence Address: Marques De Sa, J.; Instituto de Engenharia Biomedica, Pt. Coronel Pacheco 1, P-4050 Porto, Portugal; email: jmsa@garfield.fe.up.ptTradenames: Microsoft Visual C++, microsoft, United StatesManufacturers: microsoft, United StatesReferences: Jain, A.K., (1982) Fundamentals of Digital Image Processing, , New York: Prentice Hall International Editions;Neilson, J., Grant, A., Ultrasound in pregnancy (1989) A Guide to Effective Care in Pregnancy and Childbirth., pp. 48-56. , Enkin M, Keirse MJN, Chalmers I. eds. New York, London: Oxford University Press; Nicolaides, K.H., Azar, G., Byrne, D., Mansur, C., Marks, K., Fetal nuchal translucency: Ultrasound screening for chromosomal detects in first trimester of pregnancy (1992) BMJ, 304, pp. 867-869; Pandya, P.P., Brizot, M.L., Kuhn, P., Snijders, R.J.M., Nicolaides, K.H., First trimester fetal nuchal translucency thickness and risk for trisomies (1994) Obstet Gynecol, 84, pp. 420-423; Pandya, P.P., Kondylios, A., Hilbert, L., Snijders, R.J.M., Nicolaides, K.H., Chromosomal defects and outcome in 1015 fetuses with increased nuchal translucency (1995) Ultrasound Obstet Gynecol, 5, pp. 15-19; Pandya, P.P., Altman, D.G., Brizot, M.L., Pettersen, H., Nicolaides, K.H., Repeatability of measurement of fetal nuchal translucency thickness (1995) Ultrasound Obstet Gynecol, 5, pp. 334-337; Roberts, L.J., Bewley, S., Mackinson, A.M., Rodeck, C.H., First trimester fetal nuchal translucency: Problems of screening the general population (1995) Br J Obstet Gynaecol, 102, pp. 381-385; Zador, I.E., Salari, V., Sokol, R.J., Computer applications in fetal medicine (1994) The Fetus As A Patient, pp. 117-124. , Kurjak A, Chervenak FA, eds. London/ New York: Parthenon Publ
Keywords: article; cervical spine; chromosome aberration; Chromosome Aberrations; Chromosome Disorders; Computer aided diagnosis; computer program; Computer software; computer system; Female; Fetal monitoring; Fetal nuchal translucency; fetus echography; first trimester pregnancy; Humans; Image analysis; Image Processing, Computer-Assisted; Image thresholding; Medical imaging; Neck; observer variation; Pregnancy; Pregnancy Trimester, First; priority journal; reproducibility; Reproducibility of Results; Software; Software package NUCA; Thickness measurement; Ultrasonic imaging; Ultrasonography, Prenatal; ultrasound

Influence of substrate material and surface finishing on the morphology of the calcium-phosphate coating - Leitão, E.; Barbosa, M.A.; De Groot, K. (Journal of Biomedical Materials ResearchJ. BIOMED. MATER. RES., 1997)
The formation of an apatite-like layer was achieved by immersing Ti- 6A1-4V, Ti-A1-2.5Fe, and 316 L stainless-steel substrata in Hank's balanced salt solution (HBSS). The layer was characterized by surface analysis techniques, namely, X-ray microanalysis and X-ray diffraction, and the morphology was observed by scanning electron microscopy and atomic force microscopy. The concentrations of Ca and P were monitored as a function of time. The morphology of the precipitate layer seems to be dependent both on the type of metal substrate and its surface finish. Polished Ti-6A1-4V and Ti-A1-2.5Fe surfaces exhibit a plate precipitate morphology, whereas rougher surfaces show scattered crystal-like precipitation. The results suggest that the layer produced by immersion of polished titanium alloys in HBSS is constituted by an amorphous apatite.The formation of an apatite-like layer was achieved by immersing Ti-6Al-4V, Ti-Al-2.5Fe, and 316 L stainless-steel substrata in Hank's balanced salt solution (HBSS). The layer was characterized by surface analysis techniques, namely, X-ray microanalysis and X-ray diffraction, and the morphology was observed by scanning electron microscopy and atomic force microscopy. The concentrations of Ca and P were monitored as a function of time. The morphology of the precipitate layer seems to be dependent both on the type of metal substrate and its surface finish. Polished Ti-6Al-4V and Ti-Al-2.5Fe surfaces exhibit a plate precipitate morphology, whereas rougher surfaces show scattered crystal-like precipitation. The results suggest that the layer produced by immersion of polished titanium alloys in HBSS is constituted by an amorphous apatite.
Cited By (since 1996): 11Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(199707)36:1<85::AID-JBM10>3.0.CO;2-IPubMed ID: 9212392Language of Original Document: EnglishCorrespondence Address: Leitao, E.; INEB, FEUP, Praca do Coronel Pacheco 1, 4050 Porto, PortugalChemicals/CAS: Alloys; alpha-tricalcium phosphate; Aluminum, 7429-90-5; Biocompatible Materials; calcium phosphate, 10103-46-5; Calcium Phosphates; dicalcium phosphate anhydrous, 7757-93-9; Hanks Balanced Salt Solution; Iron, 7439-89-6; Isotonic Solutions; monocalcium phosphate; Stainless Steel, 12597-68-1; tetracalcium phosphate; titanium alloy (TiAl6V4), 12743-70-3; Titanium, 7440-32-6References: Fujishiro, Y., Sato, T., Okuwaki, A., Coating of hydroxyapatite on metal plates using thermal dissociation of calcium-EDTA chelate in phosphate solutions under hydrothermal conditions (1995) Mater. Sci. Mater. Med., 6, pp. 172-176;Shirkhanzadeh, M., Calcium phosphate coatings prepared by electrocrystallization from aqueous electrolytes (1995) J. Mater, Sci. Mater. Med., 6, pp. 90-93; De Groot, K., Ceramics of calcium phosphates (1983) Bioceramics of Calcium Phosphates, p. 100. , K. de Groot (ed.), CRC Press, Boca Raton, FL; Leitão, E., Barbosa, M.A., De Groot, K., In vitro calcification of orthopaedic implant materials (1995) J. Mater. Sci. Mater. Med., 6, pp. 849-852; Ducheyne, P., Radin, S., Ishikawa, K., The rate of calcium phosphate precipitation on metal and ceramics, and the relationship to bioactivity (1992) Bone Bonding Biomaterials, pp. 213-218. , P. Ducheyne, T. Kokubo, and C. A. van Blitterswijk (eds.), Reed Heathcare Communications, The Netherlands; Li, P., (1993) In Vitro and in Vivo Calcium Phosphate Induction on Gel Oxides, , Ph.D. thesis, Leiden University; Kokubo, T., Bioactivity of glasses and glass ceramics (1992) Bone Bonding Biomaterials, pp. 31-46. , P. Ducheyne, T. Kokubo, and C. A. van Blitterswijk (eds.), Reed Healthcare Communications, The Netherlands; Kokubo, T., Tanahashi, M., Yao, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., Apatitepolymer composites prepared by biomimetic process: Improvement of adhesion of apatite to polymer by glow-discharge treatment (1993) Bioceramics, 6, pp. 327-332. , P. Ducheyne and D. Christiansen (eds.), Butterworth-Heinemann, Oxford, United Kingdom; Hanawa, T., Titanium and its oxide film: A substrate for forming apatite (1991) Proceedings of the Bone Biomaterial Interface Workshop, pp. 49-61. , Toronto, Dec., 1990, J. E. Davies (ed.), University of Toronto Press, Toronto, Canada; Hanawa, T., Ota, M., Calcium phosphate naturally formed on titanium in electrolyte solution (1991) Biomaterials, 12, pp. 767-774; Hanawa, T., Ota, M., Characterization of surface film formed on titanium in electrolyte using XPS (1992) Appl. Surface Sci., 55, pp. 269-276; Radin, S.R., Ducheyne, P., The effect of calcium phosphate ceramic composition and structure on in vivo behavior. II. Precipitation (1993) J. Biomed. Mater. Res., 27, pp. 35-45
Keywords: Alloys; Aluminum; Aluminum alloys; article; Biocompatibility; Biocompatible Materials; biomaterial; Calcium Compounds; calcium phosphate; Calcium phosphate coatings; Calcium phosphates; Coatings; Finishing; Humans; hydroxyapatite; Implants (surgical); Iron; Isotonic Solutions; materials testing; metal implantation; Microscopy, Electron, Scanning; morphology; Phosphates; Stainless steel; Surface Properties; surface property; Surface testing; Surface treatment; Time Factors; Titanium; Titanium alloys; X ray diffraction; X ray diffraction analysis